1,064-nm diode laser therapy of onychomycosis: results of a prospective open treatment of 82 toenails - Renner, Regina; Gruesser, Kathrin; Sticherling, Michael (Dermatology, 2015)
Onychomycosis is one of the most prevalent nail disorders in adults, where conventional topical therapy is often protracted and in most cases ineffective. On the other hand, systemic/oral therapy is not suitable for all patients and might be associated with relevant side effects. Therefore, laser therapy can be used as an alternative to or extension of existing treatment protocols.We used diode laser treatment for onychomycosis to evaluate the efficacy of this treatment as single therapy as well as in combination with an ongoing antimycotic treatment.We used a 1,064-nm diode laser (FOX Laser, ARC Laser GmbH, Germany) in pulse mode with a spot size of 4 mm. The laser's settings were: 8 W, with a pulse duration of 80 ms and a repetition rate of 5.6 Hz; the energy fluence/pulse was 5.1 J/cm(2), and a total energy of 250-500 J for large and/or thickened nails (digit I), 120-200 J for medium nails (digits II-IV) and 60-120 J for small and/or very thin nail plates (digit V) was counted in the laser display. Two to three passes where applied continuously over the entire area of the nail (nail plate, nail folds and eponychium) in a grid pattern. Eighty-two affected toenails were treated at least twice every 8 weeks; all nails treated were clinically diagnosed as onychomycosis. The evaluation of the treated nails was conducted by two dermatologists, initially by semiquantitative visual examination, followed by evaluation with the Onychomycosis Severity Index (OSI). In addition, the patients were asked to state their satisfaction with the treatment and its results in a written questionnaire.All nails showed an improvement ranging between 14 and 56% including the analytical evaluation scale (OSI). Two dermatologists evaluated 34 nails. Both reported significant improvement and/or good clinical improvement, which corresponds to about 41% for both evaluations. The mean OSI of all patients was 18.9/19.9 before treatment which changed to 14.3/14.8 after treatment. This corresponds to an improvement of about 25% (-4.6/-5.1) compared to the initial value. Specifically the subgroup with positive antimycotic culture and no additional antimycotic treatment showed an improvement of about 25%. This improvement can be attributed to the effect of the diode laser treatment. When evaluating the OSI of all nails, it appears that about 15-20% of the severe OSIs improved and changed to a moderate level, while a similar portion of patients with moderate onychomycosis improved to mild onychomycosis. Patient satisfaction was measured to an average value of 4.6 out of a maximum of 10 points. About 60% of the treated patients would recommend the treatment to their family members or friends.This investigation demonstrated that diode laser treatment of onychomycosis provides acceptable results with minimal to no side effects. Further clinical evaluations could help to establish better therapy protocols, especially for those patients who had no benefit from the laser treatment, or could also be used as an add-on to an existing therap
EVALuna2:19549

12/15-Lipoxygenase-mediated enzymatic lipid oxidation regulates DC maturation and function - Rothe, Tobias; Gruber, Florian; Uderhardt, Stefan; Ipseiz, Natacha; Rössner, Susanne; Oskolkova, Olga; Blueml, Stephan; Leitinger, Norbert; Bicker, Wolfgang; Bochkov, Valery N.; Yamamoto, Masayuki; Steinkasserer, Alexander; et al. (Journal of Clinical Investigation, 2015)
DCs are able to undergo rapid maturation, which subsequently allows them to initiate and orchestrate T cell-driven immune responses. DC maturation must be tightly controlled in order to avoid random T cell activation and development of autoimmunity. Here, we determined that 12/15-lipoxygenase-meditated (12/15-LO-mediated) enzymatic lipid oxidation regulates DC activation and fine-tunes consecutive T cell responses. Specifically, 12/15-LO activity determined the DC activation threshold via generation of phospholipid oxidation products that induced an antioxidative response dependent on the transcription factor NRF2. Deletion of the 12/15-LO-encoding gene or pharmacologic inhibition of 12/15-LO in murine or human DCs accelerated maturation and shifted the cytokine profile, thereby favoring the differentiation of Th17 cells. Exposure of 12/15-LO-deficient DCs to 12/15-LO-derived oxidized phospholipids attenuated both DC activation and the development of Th17 cells. Analysis of lymphatic tissues from 12/15-LO-deficient mice confirmed enhanced maturation of DCs as well as an increased differentiation of Th17 cells. Moreover, experimental autoimmune encephalomyelitis in mice lacking 12/15-LO resulted in an exacerbated Th17-driven autoimmune disease. Together, our data reveal that 12/15-LO controls maturation of DCs and implicate enzymatic lipid oxidation in shaping the adaptive immune response.
EVALuna2:13111

50-year-old woman with cold-associated attacks of white discoloration of individual fingers: Preparation for the specialist examination: part 51 50/w mit kälteabhängiger, anfallsweiser Weißverfärbung einzelner Finger: Vorbereitung auf die Facharztprüfung: Folge 51 - Sticherling, Michael (Hautarzt, 2019)
CRIS-Team Scopus Importer:2019-05-02

50-year-old Woman with cold-associated attacks of White Discoloration of individual Fingers Preparation for the Specialist Examination: Part 51 - Sticherling, Michael (Hautarzt, 2019)
CRIS-Team WoS Importer:2019-05-03

A benchmark for neural network robustness in skin cancer classification - Maron, Roman C.; Schlager, Justin G.; Haggenmüller, Sarah; von Kalle, Christof; Utikal, Jochen S.; Meier, Friedegund; Gellrich, Frank F.; Hobelsberger, Sarah; Hauschild, Axel; French, Lars; Heinzerling, Lucie; Schlaak, Max; et al. (European Journal of Cancer, 2021)
Background: One prominent application for deep learning–based classifiers is skin cancer classification on dermoscopic images. However, classifier evaluation is often limited to holdout data which can mask common shortcomings such as susceptibility to confounding factors. To increase clinical applicability, it is necessary to thoroughly evaluate such classifiers on out-of-distribution (OOD) data. Objective: The objective of the study was to establish a dermoscopic skin cancer benchmark in which classifier robustness to OOD data can be measured. Methods: Using a proprietary dermoscopic image database and a set of image transformations, we create an OOD robustness benchmark and evaluate the robustness of four different convolutional neural network (CNN) architectures on it. Results: The benchmark contains three data sets—Skin Archive Munich (SAM), SAM-corrupted (SAM-C) and SAM-perturbed (SAM-P)—and is publicly available for download. To maintain the benchmark's OOD status, ground truth labels are not provided and test results should be sent to us for assessment. The SAM data set contains 319 unmodified and biopsy-verified dermoscopic melanoma (n = 194) and nevus (n = 125) images. SAM-C and SAM-P contain images from SAM which were artificially modified to test a classifier against low-quality inputs and to measure its prediction stability over small image changes, respectively. All four CNNs showed susceptibility to corruptions and perturbations. Conclusions: This benchmark provides three data sets which allow for OOD testing of binary skin cancer classifiers. Our classifier performance confirms the shortcomings of CNNs and provides a frame of reference. Altogether, this benchmark should facilitate a more thorough evaluation process and thereby enable the development of more robust skin cancer classifiers.
CRIS-Team Scopus Importer:2021-08-20
Keywords: Artificial intelligence; Benchmarking; Deep learning; Dermatology; Melanoma; Nevus; Skin neoplasms

A chimeric il-15/il-15rα molecule expressed on nfκb-activated dendritic cells supports their capability to activate natural killer cells† - Bosch, Naomi C.; Martin, Lena Marie; Voskens, Caroline; Berking, Carola; Seliger, Barbara; Schuler, Gerold; Schaft, Niels; Dörrie, Jan (International Journal of Molecular Sciences, 2021)
Natural killer (NK) cells, members of the innate immune system, play an important role in the rejection of HLA class I negative tumor cells. Hence, a therapeutic vaccine, which can activate NK cells in addition to cells of the adaptive immune system might induce a more comprehensive cellular response, which could lead to increased tumor elimination. Dendritic cells (DCs) are capable of activating and expanding NK cells, especially when the NFκB pathway is activated in the DCs thereby leading to the secretion of the cytokine IL-12. Another prominent NK cell activator is IL-15, which can be bound by the IL-15 receptor alpha-chain (IL-15Rα) to be transpresented to the NK cells. However, monocyte-derived DCs do neither secrete IL-15, nor express the IL-15Rα. Hence, we designed a chimeric protein consisting of IL-15 and the IL-15Rα. Upon mRNA electroporation, the fusion protein was detectable on the surface of the DCs, and increased the potential of NFκB-activated, IL-12-producing DC to activate NK cells in an autologous cell culture system with ex vivo-generated cells from healthy donors. These data show that a chimeric IL-15/IL-15Rα molecule can be expressed by monocyte-derived DCs, is trafficked to the cell surface, and is functional regarding the activation of NK cells. These data represent an initial proof-of-concept for an additional possibility of further improving cellular DC-based immunotherapies of cancer.
CRIS-Team Scopus Importer:2021-10-01
Keywords: Adoptive cellular immunotherapy; Dendritic cell; IL-15; Natural killer cell; NF-κB

A comparative analysis of articular bone in large cohort of patients with chronic inflammatory diseases of the joints, the gut and the skin - Simon, David; Kleyer, Arnd; Englbrecht, Matthias; Stemmler, Fabian; Simon, Christoph; Berlin, Andreas; Kocijan, Roland; Haschka, Judith; Hirschmann, Simon; Atreya, Raja; Neurath, Markus; Sticherling, Michael; et al. (Bone, 2018)
Chronic inflammatory diseases are associated with bone loss. While the occurrence of systemic bone loss is well described in chronic inflammatory diseases, the impact of these conditions on articular bone has not been systematically investigated. Recent refinements in high-resolution CT assessment of the joints now allow the accurate measure of articular bone composition. In this study 476 subjects comprising healthy individuals and patients with anticitrullinated protein antibody (ACPA)-positive rheumatoid arthritis (RA), ACPA-negative RA, Crohn's disease (CD), ulcerative colitis (UC), psoriasis (PsO) and psoriatic arthritis (PsA) were subjected to high-resolution quantitative computed tomography (HR-pQCT) of the hand. Metacarpal heads were assessed for total, trabecular and cortical volumetric bone mineral density (vBMD). Only ACPA+RA, but not the remaining inflammatory diseases (ACPA-RA, CD, UC, PsO, PsA) showed significant (p < 0.001) loss of articular bone affecting both the trabecular and the cortical compartments. Age and body mass index were also associated with articular bone changes, the former with lower, the latter with higher articular bone mass. In multivariate models, presence of ACPA+RA was an independent factor for articular bone loss. Among chronic inflammatory diseases ACPA+RA is the most potent precipitator for articular bone loss pointing out the role of autoimmunity in the development of articular bone disease in the context of chronic inflammatory disease.
EVALuna2:34480

Acral lentiginous melanoma: a skin cancer with unfavourable prognostic features. A study of the German central malignant melanoma registry (CMMR) in 2050 patients - Teramoto, Y.; Keim, U.; Gesierich, A.; Schuler, Gerold; Fiedler, E.; Tueting, T.; Ulrich, C.; Wollina, Uwe; Hassel, J. C.; Gutzmer, R.; Goerdt, S.; Zouboulis, C.; et al. (British Journal of Dermatology, 2018)
BACKGROUND: Acral lentiginous melanoma (ALM) is one of the four major subtypes in cutaneous melanoma (CM). Although ALM has a poorer prognosis than other CM subtypes, the prognostic factors associated with ALM have only been verified in small-sized cohorts because of the low incidence of ALM worldwide. OBJECTIVES: To investigate the clinical characteristics of ALM and to evaluate their prognostic values based on a large dataset from the Central Malignant Melanoma Registry (CMMR) of the German Dermatologic Society. METHODS: The Kaplan-Meier method was used to estimate the potential influence of clinical and histological parameters on ALM disease-specific survival (DSS) curves, which were compared using the log-rank test. A Cox proportional hazards model was used to identify independent prognostic factors for DSS. RESULTS: In total, 2050 patients with ALM were identified from 58 949 patients with CM recorded by the CMMR with follow-up data. In multivariate analyses, age (P = 0·006), ulceration (P = 0·013), tumour thickness (P < 0·001) and tumour spread (P < 0·001) turned out to be significant prognostic factors for DSS in ALM whereas sex, nevus association and level of invasion were not independent factors. CONCLUSIONS: ALM has the same prognostic factors as other subtypes of melanoma. Unfavourable prognosis probably derives from the delay in diagnosis in comparison with other melanoma subtypes.
EVALuna2:34403

A critical appraisal of evidence-and consensus-based guidelines for actinic keratosis - Wessely, Anja; Steeb, Theresa; Heppt, Franz; Hornung, Annkathrin; Kaufmann, Matthias; Koch, Elias; Toussaint, Frédéric; Erdmann, Michael; Berking, Carola; Heppt, Markus (Current Oncology, 2021)
Actinic keratoses (AK) are common lesions of the skin that can be effectively treated with several lesion-and field-directed treatments. Clinical practice guidelines assist physicians in choosing the appropriate treatment options for their patients. Here, we aimed to systematically identify and evaluate the methodological quality of currently available guidelines for AK. Guidelines published within the last 5 years were identified in a systematic search of guideline databases, Medline and Embase. Then, six independent reviewers evaluated the methodological quality using the tools “Appraisal of Guidelines for Research and Evaluation” (AGREE II) and “Recommendation EXcellence” (AGREE-REX). The Kruskal–Wallis (H) test was used to explore differences among subgroups and Spearman’s correlation to examine the relationship between individual domains. Three guidelines developed by consortia from Canada, Germany and the United Kingdom were eligible for the evaluation. The German guideline achieved the highest scores, fulfilling 65 to 92% of the criteria in AGREE II and 67 to 84% in AGREE-REX, whereas the Canadian guideline scored 31 to 71% of the criteria in AGREE II and 33 to 46% in AGREE-REX. The domains “stakeholder involvement“ and “values and preferences“ were identified as methodological weaknesses requiring particular attention and improvement in future guideline efforts.
CRIS-Team Scopus Importer:2021-04-02
Keywords: actinic keratosis; AGREE; Level of evidence; Practice guideline; Solar keratosis

A cross-tissue protein profiling atlas reveals distinct cDC2 subpopulations within the murine conventional dendritic cell network - Amon, Lukas; Lehmann, Christian; Seichter, A.; Heger, Lukas; Dudziak, Diana (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Actinic keratoses: Current guideline and practical recommendations Aktinische Keratosen: Aktuelle Leitlinie und praxisbezogene Empfehlungen - Nashan, D.; Hüning, S.; Heppt, Markus; Brehmer, A.; Berking, Carola (Hautarzt, 2020)
The S3 guideline “Actinic keratosis and squamous cell carcinoma of the skin” was published on 30 June 2019. Subsequently, publications, reviews and meta-analyses appeared with new questions regarding the comparability of study data and heterogeneity of the evaluations, which are caused, among other things, by divergent measurement parameters as well as insufficient consideration of pretreatments and combined treatments. This concise overview was written in the context of criticism and in view of necessary developments and research. Topics include epidemiology, pathogenesis, prevention, clinical presentation, therapy and BK5103. Therapy is divided into local destructive procedures and topical applications. Recommendations with quotation marks are based on the actual guideline. Corresponding evidence levels are given. For the implementation in daily routine basic data, side effects and features of therapeutic options are mentioned. The current developments and questions concerning actinic keratoses become clear.
CRIS-Team Scopus Importer:2020-06-09
Keywords: BK5103; Diagnosis; Precision medicine; S3 guideline; Therapy

A disease network-based deep learning approach for characterizing melanoma - Lai, Xin; Zhou, Jinfei; Wessely, Anja; Heppt, Markus; Maier, Andreas; Berking, Carola; Vera, Julio; Zhang, Le (International Journal of Cancer, 2021)
Multiple types of genomic variations are present in cutaneous melanoma and some of the genomic features may have an impact on the prognosis of the disease. The access to genomics data via public repositories such as The Cancer Genome Atlas (TCGA) allows for a better understanding of melanoma at the molecular level, therefore making characterization of substantial heterogeneity in melanoma patients possible. Here, we proposed an approach that integrates genomics data, a disease network, and a deep learning model to classify melanoma patients for prognosis, assess the impact of genomic features on the classification and provide interpretation to the impactful features. We integrated genomics data into a melanoma network and applied an autoencoder model to identify subgroups in TCGA melanoma patients. The model utilizes communities identified in the network to effectively reduce the dimensionality of genomics data into a patient score profile. Based on the score profile, we identified three patient subtypes that show different survival times. Furthermore, we quantified and ranked the impact of genomic features on the patient score profile using a machine-learning technique. Follow-up analysis of the top-ranking features provided us with the biological interpretation of them at both pathway and molecular levels, such as their mutation and interactome profiles in melanoma and their involvement in pathways associated with signaling transduction, immune system and cell cycle. Taken together, we demonstrated the ability of the approach to identify disease subgroups using a deep learning model that captures the most relevant information of genomics data in the melanoma network.
CRIS-Team Scopus Importer:2021-11-26
Keywords: autoencoder; disease network; genomics; melanoma; neural network; systems medicine

Adjuvant treatment and outcome of stage III melanoma patients: Results of a multicenter real-world German Dermatologic Cooperative Oncology Group (DeCOG) study - Lodde, Georg C.; Hassel, Jessica; Wulfken, Lena M.; Meier, Friedegund; Mohr, Peter; Kähler, Katharina; Hauschild, Axel; Schilling, Bastian; Loquai, Carmen; Berking, Carola; Hüning, Svea; Eckardt, Julia; et al. (European Journal of Cancer, 2023)
Purpose: Clinical trials demonstrated significantly improved recurrence-free survival (RFS) of melanoma patients receiving adjuvant treatment. As data from controlled trials are based on selected populations, we investigated adjuvantly treated stage III melanoma patients under real-world conditions. Patients and methods: In a prior multicenter cohort study, stage III-IV melanoma patients were analysed for their choice of adjuvant therapy. In this follow-up study, we examined RFS, overall and melanoma-specific survival (MSS) and response to the subsequent treatment of 589 stage III patients (232 BRAF-mutated) receiving adjuvant PD-1 inhibitors (PD1; n = 479) or targeted therapy (TT; n = 110). Results: The median follow-up of the total cohort was 25.7 months. The main reason for premature discontinuation of adjuvant therapy was disease progression in PD1- (28.8%, n = 138/479) and adverse events in TT-treated patients (28.2%, n = 31/110). Among BRAF-mutated patients, RFS at 24 months was 49% (95% CI 40.6–59.0%) for PD1- and 67% (95% CI 58–77%) for TT-treated patients. The risk of recurrence was higher for BRAF-mutated PD1 than TT (hazard ratio 1.99; 95% CI 1.34–2.96; hazard ratio adjusted for age, sex and tumour stage, 2.21; 95% CI 1.48–3.30). Twenty-four months MSS was 87% (95% CI 81.0–94.1) for PD1 and 92% (95% CI 86.6–97.0) for TT. Response to subsequent systemic treatment for unresectable disease was 22% for all PD1- and 16% for TT-treated patients. Conclusions: PD1-treated patients had more and earlier recurrences than TT patients. In BRAF-mutated patients, adjuvant TT might prevent early recurrences more effectively than PD1 treatment. Management of recurrence despite adjuvant treatment is challenging, with low response to current therapeutic options. Data availability statement: The datasets generated during and/or analysed during the current study are available for qualified researchers from the corresponding authors upon request.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Adjuvant treatment; BRAF; Immunotherapy; Melanoma; PD1; Real-world; Targeted therapy

Advanced neural networks for classification of MRI in psoriatic arthritis, seronegative, and seropositive rheumatoid arthritis - Folle, Lukas; Bayat, Sara; Kleyer, Arnd; Fagni, Filippo; Kapsner, Lorenz; Schlereth, Maja; Meinderink, Timo; Breininger, Katharina; Tascilar, Koray; Krönke, Gerhard; Uder, Michael; Sticherling, Michael; et al. (Rheumatology, 2022)
Objectives: To evaluate whether neural networks can distinguish between seropositive rheumatoid arthritis (RA), seronegative RA and psoriatic arthritis (PsA) based on inflammatory patterns from hand MRI and to test how psoriasis patients with subclinical inflammation fit into such patterns. Methods: ResNet neural networks were utilized to compare (i) seropositive RA vs. PsA, (ii) seronegative RA vs. PsA and (iii) seropositive vs. seronegative RA with respect to hand MRI data. Results from T1 coronal, T2 coronal, T1 coronal and axial fat suppressed contrast-enhanced (CE) and T2 fat suppressed axial sequences were used. The performance of such trained networks was analyzed by the area-under-the-receiver-operating-characteristic curve (AUROC) with and without presentation of demographic and clinical parameters. Additionally, the trained networks were applied to psoriasis patients without clinical arthritis. Results: MRI scans from 649 patients (135 seronegative RA, 190 seropositive RA, 177 PsA, 147 psoriasis) were fed into ResNet neural networks. AUROC was 75% for seropositive RA vs. PsA, 74% for seronegative RA vs. PsA and 67% for seropositive vs. seronegative RA. All MRI sequences were relevant for classification, however, when deleting contrast agent-based sequences the loss of performance was only marginal. The addition of demographic and clinical data to the networks did not provide significant improvements for classification. Psoriasis patients were mostly assigned to PsA by the neural networks, suggesting that a PsA-like MRI pattern may be present early in the course of psoriatic disease. Conclusion: Neural networks can be successfully trained to distinguish MRI inflammation related to seropositive RA, seronegative RA, and PsA.
Keywords: Rheumatoid arthritis; Psoriatic arthritis; neural networks; deep learning

A fast and robust method to clone and functionally validate T-cell receptors - Birkholz, Katrin; Hofmann, Christian; Hoyer, Stefanie; Schulz, Bastian; Harrer, Thomas; Kämpgen, Eckhart; Schuler, Gerold; Dörrie, Jan; Schaft, Niels (Journal of Immunological Methods, 2009)
Sequencing, cloning and functional testing of T-cell-receptor (TCR) α- and β-chains from T-cell clones is often required in immunotherapy and in immunological research. However, the determination of the TCR chains by a simple PCR is not possible, since, in contrast to the 3′ constant domain and untranslated region (UTR), no conserved sequences are present in the 5′ region. Furthermore, subsequent functional testing of cloned TCRs requires laborious cell-culture experiments, often involving primary human material and time-consuming viral transduction strategies. Here we present a universal PCR-based protocol, adapted from the capswitch technology, that allows for amplification of the TCR α- and β-chain mRNAs without knowledge of the TCR variable domain subtype by attaching a designed sequence to the mRNA's 5′ end. Two different MelanA/HLA-A2-specific and one HIVgag/HLA-A2-specific TCR were cloned that way, and were functionally tested by a newly developed easy, fast, and low-cost method: we electroporated Jurkat T cells simultaneously with TCR-encoding RNA and an NFAT-reporter construct, and measured the activation status of the cells upon specific stimulation. The results of this assay correlated with the cytokine release, functional avidity, proliferative activity, and the ability to recognize MelanA/HLA-A2-presenting tumor cells of bulk T cells electroporated with RNA encoding the same TCR. Together these two protocols represent a rapid and low-cost tool for the identification and functional testing of TCRs of T-cell clones, which can then be applied in immunotherapy or immunological research. © 2009 Elsevier B.V. All rights reserved.
CRIS-Team Scopus Importer:2021-10-01
Keywords: Cellular immunology; Immunotherapy; Signal transduction; T cells; TCR

A gene regulatory architecture that controls region-independent dynamics of oligodendrocyte differentiation - Cantone, Martina; Küspert, Melanie; Reiprich, Simone; Lai, Xin; Eberhardt, Martin; Göttle, Peter; Beyer, Felix; Azim, Kasum; Küry, Patrick; Wegner, Michael; Vera, Julio (Glia, 2019)
Oligodendrocytes (OLs) facilitate information processing in the vertebrate central nervous system via axonal ensheathment. The structure and dynamics of the regulatory network that mediates oligodendrogenesis are poorly understood. We employed bioinformatics and meta-analysis of high-throughput datasets to reconstruct a regulatory network underpinning OL differentiation. From this network, we identified families of feedforward loops comprising the transcription factors (TFs) Olig2, Sox10, and Tcf7l2 and their targets. Among the targets, we found eight other TFs related to OL differentiation, suggesting a hierarchical architecture in which some TFs (Olig2, Sox10, and Tcf7l2) regulate via feedforward loops the expression of others (Sox2, Sox6, Sox11, Nkx2-2, Nkx6-2, Hes5, Myt1, and Myrf). Model simulations with a kinetic model reproduced the mechanisms of OL differentiation only when in the model, Sox10-mediated repression of Tcf7l2 by miR-338/miR-155 was introduced, a prediction confirmed in genetic functional experiments. Additional model simulations suggested that OLs from dorsal regions emerge through BMP/Sox9 signaling.
EVALuna2:35752

A GMP-compliant protocol to expand and transfect cancer patient T cells with mRNA encoding a tumor-specific chimeric antigen receptor - Krug, Christian; Wiesinger, Manuel; Abken, Hinrich; Schuler-Thurner, Beatrice; Schuler, Gerold; Dörrie, Jan; Schaft, Niels (Cancer Immunology Immunotherapy, 2014)
Chimeric antigen receptors (CARs), which combine an antibody-derived binding domain (single chain fragment variable) with T-cell-activating signaling domains, have become a promising tool in the adoptive cellular therapy of cancer. Retro- and lenti-viral transductions are currently the standard methods to equip T cells with a CAR; permanent CAR expression, however, harbors several risks like uncontrolled auto-reactivity. Modification of T cells by electroporation with CAR-encoding RNA to achieve transient expression likely circumvents these difficulties. We here present a GMP-compliant protocol to activate and expand T cells for clinical application. The protocol is optimized in particular to produce CAR-modified T cells in clinically sufficient numbers under full GMP-compliance from late-stage cancer patients. This protocol allows the generation of 6.7 × 10(8) CAR-expressing T cells from one patient leukapheresis. The CAR-engineered T cells produced pro-inflammatory cytokines after stimulation with antigen-bearing tumor cells and lysed tumor cells in an antigen-specific manner. This functional capacity was maintained after cryopreservation. Taken together, we provide a clinically applicable protocol to transiently engineer sufficient numbers of antigen-specific patient T cells for use in adoptive cell therapy of cancer.
EVALuna2:19440

A humanized mouse identifies the bone marrow as a niche with low therapeutic IgG activity - Lux, Anja; Seeling, Michaela; Baerenwaldt, Anne; Lehmann, Birgit; Schwab, Inessa; Repp, Roland; Meidenbauer, Norbert; Mackensen, Andreas; Hartmann, Arndt; Heidkamp, Gordon Frederik; Dudziak, Diana; Nimmerjahn, Falk (Cell Reports, 2014)
Genetic differences between humans and in vivo model systems, including mice and nonhuman primates, make it difficult to predict the efficacy of immunoglobulin G (IgG) activity in humans and understand the molecular and cellular mechanisms underlying that activity. To bridge this gap, we established a small-animal model system that allowed us to study human IgG effector functions in the context of an intact human immune system without the interference of murine Fc? receptors expressed on mouse innate immune effector cells in vivo. Using a model of B cell depletion with different human IgG variants that recognize CD20, we show that this humanized mouse model can provide unique insights into the mechanism of human IgG activity in vivo. Importantly, these studies identify the bone marrow as a niche with low therapeutic IgG activity.
EVALuna2:6588

Akte AK: eine große dermatologische Spielwiese für eine kleine Verhornung - Berking, Carola (Journal der Deutschen Dermatologischen Gesellschaft, 2024)
CRIS-Team Scopus Importer:2024-05-24

Aktinische Keratosen - Heppt, Markus; Steeb, Theresa; Szeimies, R. M.; Berking, Carola (Hautarzt, 2020)
Actinic keratoses (AK) are common precancerous cutaneous lesions in fair-skinned individuals as a result of cumulative exposure to ultraviolet radiation. Due to their high prevalence, AK account for a large disease burden, in particular in older persons. As AK may potentially progress into invasive cutaneous squamous cell carcinoma, guidelines recommend early and consequent treatment. Numerous lesion- and field-directed interventions with different efficacy and safety profiles are currently licensed in Germany. The appropriate intervention should be chosen together with the patient based on his or her motivation and expectations towards the treatment.
CRIS-Team Scopus Importer:2020-06-05
Keywords: 5‑Fluorouracil; Ingenol mebutate; Non-melanoma skin cancer; Photodynamic therapy; Squamous cell carcinoma

Allergenic and microbiological hazards caused by skin markings during medical procedures? - Maronna, Andreas; Psaier, Sigrid; Geier, Johannes; Mahler, Vera; Erfurt-Berge, Cornelia (Journal der Deutschen Dermatologischen Gesellschaft, 2017)
EVALuna2:35403

Alopecia areata- Clinical Picture and Therapy Response of Heterogeneous Disease - Busch, D.; Sticherling, Michael (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-05-17

Alzheimer's disease protease-containing plasma extracellular vesicles transfer to the hippocampus via the choroid plexus - Lee, Jung Hyun; Ostalecki, Christian; Oberstein, Timo; Schierer, Stefan; Zinser, Elisabeth; Eberhardt, Martin; Blume, Katja; Plosnita, Bianca; Stich, Lena; Bruns, Heiko; Coras, Roland; Vera González, Julio; et al. (EBioMedicine, 2022)
Background: Plasma extracellular vesicles (pEV) can harbor a diverse array of factors including active proteases and the amyloid-precursor-protein (APP) cleavage product Aβ, involved in plaque formation in Alzheimer`s diseases (AD). A potential role of such vesicles in AD pathology is unexplored. Methods: In a case-control study of randomly selected patients with AD and other neurological diseases (n = 14), and healthy controls (n = 7), we systematically analyzed the content of pEV, using different assay systems. In addition, we determined their entry path into brain tissue, employing animal (mice) injection experiments with ex vivo generated EV that were similar to AD-pEV, followed by multi antigen analysis (MAA) of brain tissue (n = 4 per condition). The results were compared with an IHC staining of human brain tissue in a small cohort of AD patients (n = 3) and controls with no neurodegenerative diseases (n = 3). Findings: We show that pEV levels are considerably upregulated in AD patients. Besides numerous inflammatory effectors, AD-pEV contained α-, β- and γ-secretases, able to cleave APP in in target cells. In vitro generated EV with similar characteristics as AD-pEV accumulated in the choroid plexus (CP) of injected animals and reached primarily hippocampal neurons. Corroborating findings were made in human brain samples. An inhibitor of hyaluronic-acid-synthetase (HAS) blocked uploading of proteases and Hyaluronan onto EV in vitro and abolished CP targeting in animal injection experiments. Interpretation: We conclude that protease-containing pEV could be part of a communication axis between the periphery and the brain that could be become detrimental depending on pEV concentration and duration of target cell impact.
CRIS-Team Scopus Importer:2022-03-04
Keywords: Alzheimer's disease; APP; Aβ; BACE; Choroid plexus; Hippocampus; Hyaluronan; Hyaluronic acid synthetase; Plasma extracellular vesicles; Secretases

A matter of perspective: Imputation methods and their effects illustrated with the use of data from the PRIME study - Reich, Kristian; Bachhuber, Teresa; Melzer, Nima; Sieder, Christian; Sticherling, Michael (2018)
EVALuna2:34782

A model-based strategy to investigate the role of microRNA regulation in cancer signalling networks - Nikolov, Svetoslav; Vera, Julio; Schmitz, Ulf; Wolkenhauer, Olaf (Theory in Biosciences, 2011)
In this paper we present and discuss a model-based approach to link miRNA translational control with cell signalling networks. MicroRNAs are small regulatory RNAs that are able to regulate the activity and the stability of specific messenger RNA and have been implicated in tumour progression due to their ability to translationally regulate critical oncogenes and tumour suppressors. In our approach, data on protein-protein interactions and miRNA regulation, obtained from bioinformatics databases, are integrated with quantitative experimental data using mathematical modelling. Predictive computational simulations and qualitative (bifurcation) analyses of those mathematical models are employed to further support the investigation of such multifactorial networks in the context of cancer progression. We illustrate our approach with the C-Myc/E2F signalling network, involved in the progression of several tumour subtypes, including colorectal cancer.
Keywords: Systems biology; Translational regulation; Bioinformatics; miRNA; Cancer networks

A Modified Surgical Technique for Kidney Transplantation in Mice - Yin, Decheng; Fu, Jian; Chen, Rongjun; Shushakova, Nelli; Allabauer, Ida; Wei, Xinyi; Schiffer, Mario; Dudziak, Diana; Rong, Song; Hörning, André (Journal of Visualized Experiments, 2022)
Kidney transplantation in mice is a complicated and challenging surgery procedure. There are very few publications demonstrating the key steps of this operation. Therefore, this article introduces the technique and points out the surgical caveats associated with this operation. In addition, important modifications in comparison to the conventional procedure are demonstrated. Firstly, a patch of the abdominal aorta is cut and prepared so that the proximal bifurcations of the renal artery, including the ureteral artery are transected together with the donor kidney en bloc. This reduces the risk of a ureter necrosis and avoids the development of a urinary tract occlusion. Secondly, a new method of the vascular anastomosis is demonstrated that allows the operator to flexibly increase or decrease the size of the anastomosis after renal transplant reperfusion has already been initiated. This avoids the development of vessel strictures and intraabdominal bleeding. Thirdly, a technique that enables the anastomosis of the delicate donor ureter and the recipient bladder that does not cause a trauma is shown. Adopting this protocol can shorten the operation time and reduces the damage to the recipient's bladder, thereby significantly increasing the operation success rate for the recipient mice.
CRIS-Team Scopus Importer:2022-08-19

Analyses of association of psoriatic arthritis and psoriasis vulgaris with functional NCF1 variants - Löhr, Sabine; Ekici, Arif Bülent; Uebe, Steffen; Büttner, Christian; Köhm, Michaela; Behrens, Frank; Böhm, Beate; Sticherling, Michael; Schett, Georg; Simon, David; Mössner, Rotraut; Nimeh, Ali; et al. (Rheumatology, 2019)
CRIS-Team Scopus Importer:2019-07-02

Analysis of complex behavior of stem cell populations in colonic crypts - Vera González, Julio; et al. (International Journal Bioautomation, 2015)
Mathematical models of the stem cell populations in colonic crypts can contribute to a better understanding of basic mechanisms underlying tissue organization. We here study the complex dynamic behaviour of a time delay model that describes stem cells in the niche of colonic crypts. We analyze the conditions for the various regimes that would lead to oscillations. The work presented here the first description of a chaotic system describing stem cell population dynamics in colonic crypt
Keywords: Time delay model; Nonlinear analysis; Stem cells; Colonic crypts

Analysis of IFN gamma-mediated Transcriptome Changes in Merkel Cell Carcinoma Cell Lines via Nanopore Sequencing - Sauerer, Tatjana; Lischer, Christopher; Berking, Carola; Vera-Gonzalez, J.; Dörrie, Jan (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2021)
CRIS-Team WoS Importer:2021-09-24

Analysis of periarticular bone changes in patients with cutaneous psoriasis without associated psoriatic arthritis - Simon, Dominic; Faustini, F.; Englbrecht, Matthias; Kleyer, Arnd; Kocijan, R.; Haschka, Judith; Finzel, Stephanie; Kraus, Sebastian; Hueber, Axel; Sticherling, Michael; Schett, Georg; Rech, J. (Annals of the Rheumatic Diseases, 2016)
To search for structural bone changes in the joints of psoriasis patients without psoriatic arthritis (PsA).55 psoriasis patients without any current or past symptoms of arthritis or enthesitis and 47 healthy controls were examined by high-resolution peripheral quantitative CT scans of the metacarpophalangeal joints. Number, size and exact localisation of erosions and enthesiophytes were recorded by analysing axial scans of the metacarpal heads and phalangeal bases and were confirmed in additional coronal and/or sagittal sections. In addition, we collected demographic and clinical data including subtype, duration and severity of psoriasis.Psoriasis patients showed a larger and significantly increased number of enthesiophytes (total number 306; mean±SD/patient 5.62±3.30) compared with healthy controls (total number 138; mean±SD/patient 3.04±1.81, p<0.001). Enthesiophytes were typically found at the dorsal and palmar sides of the metacarpal heads where functional entheses related to extensor and flexor tendons are localised. Bone erosions were rare and not significantly different between psoriasis patients and healthy controls. If present, erosions were almost exclusively found at the radial side of the second metacarpal head in both psoriasis patients and healthy controls.Psoriasis patients without PsA show substantial signs of enthesiophyte formation compared with healthy controls. These changes represent new bone formation at mechanically exposed sites of the joint and substantiate the concept of the existence of a 'Deep Koebner Phenomenon' at enthesial sites in psoriasis patients.
EVALuna2:13130

A network medicine approach for identifying diagnostic and prognostic biomarkers and exploring drug repurposing in human cancer - Zhang, Le; Fan, Shiwei; Vera, Julio; Lai, Xin (Computational and Structural Biotechnology Journal, 2023)
Cancer is a heterogeneous disease mainly driven by abnormal gene perturbations in regulatory networks. Therefore, it is appealing to identify the common and specific perturbed genes from multiple cancer networks. We developed an integrative network medicine approach to identify novel biomarkers and investigate drug repurposing across cancer types. We used a network-based method to prioritize genes in cancer-specific networks reconstructed using human transcriptome and interactome data. The prioritized genes show extensive perturbation and strong regulatory interaction with other highly perturbed genes, suggesting their vital contribution to tumorigenesis and tumor progression, and are therefore regarded as cancer genes. The cancer genes detected show remarkable performances in discriminating tumors from normal tissues and predicting survival times of cancer patients. Finally, we developed a network proximity approach to systematically screen drugs and identified dozens of candidates with repurposable potential in several cancer types. Taken together, we demonstrated the power of the network medicine approach to identify novel biomarkers and repurposable drugs in multiple cancer types. We have also made the data and code freely accessible to ensure reproducibility and reusability of the developed computational workflow.
CRIS-Team Scopus Importer:2023-01-06
Keywords: Drug repositioning; Gene prioritization; Machine learning; Network oncology; Pan-cancer diagnosis and prognosis; Systems medicine

A new method to monitor antigen-specific CD8+ T cells, avoiding additional target cells and the restriction to human leukocyte antigen haplotype. - Prommersberger, S.; Hoefflin, S.; Schuler-Thurner, Beatrice; Schuler, Gerold; Schaft, Niels; Dörrie, Jan (Gene Therapy, 2015)
Therapeutic vaccination of cancer patients with dendritic cells aims at inducing a strong tumor-specific T-cell response. Testing new target antigens for their immunogenicity is crucial to evaluate their suitability for this approach. Here we demonstrate a comfortable and reliable method to detect antigen-specific CD8(+) T-cell responses without the knowledge of the precise T-cell epitope and without the usage of additional target cells. We used the CD8(+) T cells themselves and electroporated them with RNA encoding the respective tumor antigen. The cells expressed, processed and presented the antigen and were capable of stimulating each other in functional readouts. For the model antigen MelanA, the number of interferon-?-secreting cells obtained with this method highly correlated with the numbers obtained by exogenous peptide loading (R(2)=0.8). The method was also applicable for the tumor-associated antigen Wilms' tumor protein 1. This system is quick and easy to perform, independent of the donors human leukocyte antigen type and circumvents the need for additional cells as targets. It can be used in preclinical research to test new antigens for their immunogenic potential and for immunomonitoring in cancer patients.
EVALuna2:19552

A new promising candidate to overcome drug resistant herpes simplex virus infections - Zinser, Elisabeth; Krawczyk, Adalbert; Mühl-Zürbes, Petra; Aufderhorst, Ulrich; Drassner, Christina; Stich, Lena; Zaja, Mirko; Strobl, Stefan; Steinkasserer, Alexander; Heilingloh, Christiane (Antiviral Research, 2018)
Infections with Herpes simplex viruses (HSV) belong to the most common human diseases worldwide, resulting in symptoms ranging from painful, but commonly self-limiting lesions of the orofacial or genital tract to severe infections of the eye or life-threatening generalized infections. Frequent HSV-reactivations at the eye may lead to the development of herpetic stromal keratitis, which is one of the major causes of infectious blindness in developed countries. The vast majority of life-threatening generalized infections occur in immunocompromised individuals, such as transplant recipients or patients suffering from advanced human immunodeficiency virus (HIV) infection with concurrent HSV-reactivation. Over the past decades, Acyclovir (ACV) became the golden standard for the treatment of HSV infections. However, long-term antiviral treatment, as it is required mainly in immunocompromised patients, led to the emergence of resistances towards ACV and other antivirals. Therefore, there is a clear need for the development of new potent antivirals which combine good oral bioavailability and tolerability with low side effects. In the current study we present SC93305 as a novel potent antiviral substance that proved to be highly effective not only against different HSV-1 and HSV-2 strains but also towards ACV- and multi-resistant HSV-1 and HSV-2 isolates. SC93305 shows comparable antiviral activity as reported for ACV and very importantly it does not interfere with the activation of specific immune cells. Here we report that SC93305 does not affect the biological function of dendritic cells (DC), the most potent antigen presenting cells of the immune system to induce antiviral immune responses, nor T cell stimulation or the release of inflammatory cytokines. Thus, SC93305 is a new and promising candidate for the treatment of HSV-1 and HSV-2 infections and in particular also for the inhibition of drug-resistant HSV-1/2 strains.
EVALuna2:34804

A new semisynthetic cardenolide analog 3β-[2-(1-amantadine)-1-on-ethylamine]-digitoxigenin (AMANTADIG) affects G2/M cell cycle arrest and miRNA expression profiles and enhances proapoptotic survivin-2B expression in renal cell carcinoma cell lines - Nolte, Elke; Wach, Sven; Silva, Izabella Thais; Lukat, Sabine; Ekici, Arif Bülent; Munkert, Jennifer; Müller-Uri, Frieder; Kreis, Wolfgang; Simões, Cláudia M. O.; Vera González, Julio; Wullich, Bernd; Taubert, Helge; et al. (Oncotarget, 2017)
EVALuna2:9377
Keywords: Cardiac glycoside analog; Cell cycle; 3β-[2-(1-amantadine)-1-on-ethylamine]-digitoxigenin; Human renal cell carcinoma cells; MiRNA

An integrative network-driven pipeline for systematic identification of lncRNA-associated regulatory network motifs in metastatic melanoma - Singh, Nivedita; Eberhardt, Martin; Wolkenhauer, Olaf; Vera, Julio; Gupta, Shailendra K. (BMC Bioinformatics, 2020)
BACKGROUND: Melanoma phenotype and the dynamics underlying its progression are determined by a complex interplay between different types of regulatory molecules. In particular, transcription factors (TFs), microRNAs (miRNAs), and long non-coding RNAs (lncRNAs) interact in layers that coalesce into large molecular interaction networks. Our goal here is to study molecules associated with the cross-talk between various network layers, and their impact on tumor progression. RESULTS: To elucidate their contribution to disease, we developed an integrative computational pipeline to construct and analyze a melanoma network focusing on lncRNAs, their miRNA and protein targets, miRNA target genes, and TFs regulating miRNAs. In the network, we identified three-node regulatory loops each composed of lncRNA, miRNA, and TF. To prioritize these motifs for their role in melanoma progression, we integrated patient-derived RNAseq dataset from TCGA (SKCM) melanoma cohort, using a weighted multi-objective function. We investigated the expression profile of the top-ranked motifs and used them to classify patients into metastatic and non-metastatic phenotypes. CONCLUSIONS: The results of this study showed that network motif UCA1/AKT1/hsa-miR-125b-1 has the highest prediction accuracy (ACC = 0.88) for discriminating metastatic and non-metastatic melanoma phenotypes. The observation is also confirmed by the progression-free survival analysis where the patient group characterized by the metastatic-type expression profile of the motif suffers a significant reduction in survival. The finding suggests a prognostic value of network motifs for the classification and treatment of melanoma.
CRIS-Team Scopus Importer:2020-08-07
Keywords: Data integration; LncRNA; Melanoma; MiRNA; Network approach; RNA motif; Systems biology; Transcription factor

An Interactive Macrophage Signal Transduction Map Facilitates Comparative Analyses of High-Throughput Data - Wentker, Pia; Eberhardt, Martin; Dreyer, Florian; Bertrams, Wilhelm; Cantone, Martina; Griss, Kathrin; Schmeck, Bernd; Vera, Julio (Journal of Immunology, 2017)
Macrophages (Mϕs) are key players in the coordination of the lifesaving or detrimental immune response against infections. The mechanistic understanding of the functional modulation of Mϕs by pathogens and pharmaceutical interventions at the signal transduction level is still far from complete. The complexity of pathways and their cross-talk benefits from holistic computational approaches. In the present study, we reconstructed a comprehensive, validated, and annotated map of signal transduction pathways in inflammatory Mϕs based on the current literature. In a second step, we selectively expanded this curated map with database knowledge. We provide both versions to the scientific community via a Web platform that is designed to facilitate exploration and analysis of high-throughput data. The platform comes preloaded with logarithmic fold changes from 44 data sets on Mϕ stimulation. We exploited three of these data sets-human primary Mϕs infected with the common lung pathogens Streptococcus pneumoniae, Legionella pneumophila, or Mycobacterium tuberculosis-in a case study to show how our map can be customized with expression data to pinpoint regulated subnetworks and druggable molecules. From the three infection scenarios, we extracted a regulatory core of 41 factors, including TNF, CCL5, CXCL10, IL-18, and IL-12 p40, and identified 140 drugs targeting 16 of them. Our approach promotes a comprehensive systems biology strategy for the exploitation of high-throughput data in the context of Mϕ signal transduction. In conclusion, we provide a set of tools to help scientists unravel details of Mϕ signaling. The interactive version of our Mϕ signal transduction map is accessible online at https://vcells.net/macrophage.
EVALuna2:35413

Annual Health Care Utilization and Costs for Treatment of Cutaneous and Anogenital Warts Among a Commercially Insured Population in the US, 2017-2019 Reply - Heppt, Markus; Steeb, Theresa; Berking, Carola (JAMA Dermatology, 2022)
CRIS-Team WoS Importer:2022-05-13

An open, multicentre, randomized clinical study in patients with bullous pemphigoid comparing methylprednisolone and azathioprine with methylprednisolone and dapsone - Sticherling, Michael; Franke, A.; Aberer, E.; Glaeser, R.; Hertl, Michael; Pfeiffer, C.; Rzany, B.; Schneider, S.; Shimanovich, I.; Werfel, T.; Wilczek, A.; Zillikens, Detlef; et al. (British Journal of Dermatology, 2017)
BACKGROUND: Current treatment of bullous pemphigoid (BP) is based on the long-term use of topical and/or systemic corticosteroids, which are associated with a high rate of adverse events and increased mortality. OBJECTIVES: To study the corticosteroid-sparing potential of azathioprine and dapsone. METHODS: This was a prospective, multicentre, randomized, nonblinded clinical trial that compared the efficacy and safety of two parallel groups of patients with BP treated with oral methylprednisolone 0·5 mg kg-1 per day in combination with either azathioprine 1·5-2·5 mg kg-1 per day or dapsone 1·5 mg kg-1 per day. Nine German and Austrian departments of dermatology included 54 patients based on clinical lesions, positive direct immunofluorescence (IF) microscopy and detection of serum autoantibodies by indirect IF microscopy, immunoblotting or enzyme-linked immunosorbent assay. The primary end point was the time until complete tapering of methylprednisolone, and the most important secondary end point was the cumulative corticosteroid dose. RESULTS: In eight patients (five azathioprine, three dapsone), methylprednisolone could be discontinued after a median time of 251 days in the azathioprine group and 81 days in the dapsone group. The median cumulative corticosteroid dose was 2·65 g for azathioprine compared with 1·92 g for dapsone (P = 0·06). The median numbers of days when corticosteroids were applied were 148 and 51, respectively (P = 0·24). No significant difference in the number of adverse events was seen between the treatment arms. Four patients (8%) died within the observation period of 12 months. CONCLUSIONS: Due to the lower than intended number of patients, the results of the primary and secondary end points were not or only barely significant. Dapsone appeared to have a moderately higher corticosteroid-sparing potential than azathioprine. The combination regimen of either drug with oral methylprednisolone is associated with a relatively low 1-year mortality in this vulnerable patient population.
EVALuna2:34338

Another step on the road towards standardized outcome reporting for congenital melanocytic naevi: one more to go! - Heppt, Markus; Steeb, Theresa; Berking, Carola (British Journal of Dermatology, 2021)
CRIS-Team Scopus Importer:2021-09-10

Antigen delivery to CD11c+CD8- dendritic cells induces protective immune responses against experimental melanoma in mice in vivo - Neubert, Kirsten; Lehmann, Christian; Heger, Lukas; Baranska, Anna; Staedtler, Anna Maria; Buchholz, Veit R.; Yamazaki, Sayuri; Heidkamp, Gordon Frederik; Eissing, Nathalie; Zebroski, Henry; Nussenzweig, Michel C.; Nimmerjahn, Falk; et al. (Journal of Immunology, 2014)
Dendritic cells (DCs) are central modulators of immune responses and, therefore, interesting target cells for the induction of antitumor immune responses. Ag delivery to select DC subpopulations via targeting Abs to DC inhibitory receptor 2 (DCIR2, clone 33D1) or to DEC205 was shown to direct Ags specifically to CD11c(+)CD8(-) or CD11c(+)CD8(+) DCs, respectively, in vivo. In contrast to the increasing knowledge about the induction of immune responses by efficiently cross-presenting CD11c(+)CD8(+) DCs, little is known about the functional role of Ag-presenting CD11c(+)CD8(-) DCs with regard to the initiation of protective immune responses. In this study, we demonstrate that Ag targeting to the CD11c(+)CD8(-) DC subpopulation in the presence of stimulating anti-CD40 Ab and TLR3 ligand polyinosinic-polycytidylic acid induces protective responses against rapidly growing tumor cells in naive animals under preventive and therapeutic treatment regimens in vivo. Of note, this immunization protocol induced a mixed Th1/Th2-driven immune response, irrespective of which DC subpopulation initially presented the Ag. Our results provide important information about the role of CD11c(+)CD8(-) DCs, which have been considered to be less efficient at cross-presenting Ags, in the induction of protective antitumor immune responses.
EVALuna2:19490

Antigen targeting of Fc receptors induces strong and functional relevant T cell responses in vivo independent of ITAM signaling but dependent on dendritic cell subsets - Lehmann, Christian; Baranska, A.; Heidkamp, Gordon Frederik; Amon, Lukas; Seeling, Michaela; Soulat, D.; Krug, A. B.; Ravetch, J. V.; Leusen, J. H. W.; Nimmerjahn, Falk; Dudziak, Diana (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08

Antigen targeting of Fc receptors induces strong T cell responses in vivo independent of ITAM signaling but dependent on dendritic cell subset - Lehmann, Christian; Baranska, A.; Heidkamp, Gordon Frederik; Seeling, Michaela; Soulat, D.; Krug, A.; Ravetch, J.; Leusen, J.; Nimmerjahn, Falk; Dudziak, Diana (2018)
EVALuna2:34795

Antigen targeting of Fc-receptors induces strong T cell responses in vivo independent of ITAM signaling but dependent on dendritic cell subset - Lehmann, C. H. K.; Baranska, A.; Heidkamp, G. F.; Heger, L.; Neubert, K.; Lühr, Jennifer; Hoffmann, Alana; Reimer, Katharina; Brückner, Christin; Beck, S.; Seeling, M.; Kießling, Melissa; et al. (2017)
EVALuna2:33396

Antigen targeting of Fc-receptors induces strong T cell responses in vivo independent of ITAM signaling but dependent on dendritic cell subsets - Lehmann, Christian; Baranska, A.; Heidkamp, Gordon Frederik; Heger, Lukas; Neubert, K.; Lühr, Jennifer; Hoffmann, Alana; Reimer, Katharina; Brückner, Christin; Beck, S.; Seeling, Michaela; Kießling, Melissa; et al. (2017)
EVALuna2:33397

Antigen targeting of Fc-receptors induces strong T cell responses in vivo independent of ITAM signalling - Lehmann, Christian; Baranska, Anna; Heidkamp, Gordon Frederik; Kiessling, M.; Soulat, Didier; Krug, A.; Ravetch, J. V.; Leusen, J. H.; Nimmerjahn, Falk; Dudziak, Diana (JOURNAL OF INVESTIGATIVE DERMATOLOGY, 2016)
Created from Fastlane, WoS look-up

Antigen targeting of Fc-receptors induces strong T cell responses in vivo independent of ITAM signalling - Lehmann, Christian; Baranska, Anna; Heidkamp, Gordon Frederik; Kiessling, M.; Soulat, D.; Krug, A.; Ravetch, J. V.; Leusen, J. H.; Nimmerjahn, Falk; Dudziak, Diana (Journal of Investigative Dermatology, 2016)

Anti-PD-1 Therapy in SUFU mutant Patients with Gorlin-Goltz Syndrome - Moreira, Alvaro; Kirchberger, M. C.; Toussaint, Frédéric; Erdmann, M.; Schuler, Gerold; Heinzerling, Lucie (2018)
EVALuna2:34776

Anti-PD-(L)1 plus BRAF/MEK inhibitors (triplet therapy) after failure of immune checkpoint inhibition and targeted therapy in patients with advanced melanoma. - Albrecht, Lea Jessica; Dimitriou, Florentia; Grover, Piyush; Hassel, Jessica C.; Erdmann, Michael; Forschner, Andrea; Johnson, Douglas B.; Váraljai, Renáta; Lodde, Georg; Placke, Jan Malte; Krefting, Frederik; Zaremba, Anne; et al. (European Journal of Cancer, 2024)
BACKGROUND: Effective treatment options are limited for patients with advanced melanoma who have progressed on immune checkpoint inhibitors (ICI) and targeted therapies (TT). Preclinical models support the combination of ICI with TT; however, clinical trials evaluating the efficacy of triplet combinations in first-line setting showed limited advantage compared to TT only. METHODS: We conducted a retrospective, multicenter study, that included patients with advanced melanoma who were treated with BRAF/MEK inhibitors in combination with an anti-PD-(L)1 antibody (triplet therapy) after failure of at least one anti-PD-(L)1-based therapy and one TT in seven major melanoma centers between February 2016 and July 2022. RESULTS: A total of 48 patients were included, of which 32 patients, 66.7% had brain metastases, 37 patients (77.1%) had three or more metastatic organs and 21 patients (43.8%) had three or more treatment lines. The median follow-up time was 31.4 months (IQR, 22.27-40.45 months). The treatment with triplet therapy resulted in an ORR of 35.4% (n = 17) and a DCR of 47.9% (n = 23). The median DOR was 5.9 months (range, 3.39-14.27 months). Patients treated with BRAF/MEK inhibitors as the last treatment line showed a slightly lower ORR (29.6%) compared to patients who received ICI or chemotherapy last (ORR: 42.9%). Grade 3-4 treatment-related adverse events occurred in 25% of patients (n = 12), with seven patients (14.6%) requiring discontinuation of treatment with both or either drug. CONCLUSIONS: Triplet therapy has shown activity in heavily pretreated patients with advanced melanoma and may represent a potential treatment regimen after failure of ICI and TT.
EVALuna2:568040

Anti-TNF-refractory colitis after checkpoint inhibitor therapy: Possible role of CMV-mediated immunopathogenesis - Lankes, Katharina; Hundorfean, Gheorghe; Harrer, Thomas; Pommer, Ansgar J.; Agaimy, Abbas; Angelovska, Irena; Tajmir-Riahi, Azadeh; Göhl, Jonas; Schuler, Gerold; Neurath, Markus; Hohenberger, Werner; Heinzerling, Lucie (OncoImmunology, 2016)
Immune-related adverse events (irAEs) induced by checkpoint inhibitors are well known. Since fatal outcomes have been reported early detection and adequate management are crucial. In particular, colitis is frequently observed and can result in intestinal perforation. This is the first report of an autoimmune colitis that was treated according to algorithms but became resistant due to a CMV reactivation. The 32-y-old male patient with metastatic melanoma treated within an anti-PD-1/ipilimumab combination study developed severe immune-mediated colitis (CTCAE grade 3) with up to 18 watery stools per day starting 2 weeks after treatment initiation. After improving upon therapy with immunosuppressive treatment (high dose steroids and infliximab) combined with parenteral nutrition diarrhea again exacerbated. Additionally, the patient had asymptomatic grade 3 CTCAE amylase and lipase elevation. Colitis was monitored by weekly endoscopies and colon biopsies were analyzed histologically with CMV staining, multi-epitope ligand cartography (MELC) and qRT-PCR for inflammatory genes. In the course, CMV reactivation was detected in the colon and treated with antiviral medication in parallel to a reduction of corticosteroids. Subsequently, symptoms improved. The patient showed a complete response for 2 y now including regression of bone metastases. CMV reactivation under checkpoint inhibitor therapy in combination with immunosuppressive treatment for autoimmune side effects has to be considered in these patients and if present treated. Potentially, CMV reactivation is underdiagnosed. Treatment algorithms should include CMV diagnostics.
EVALuna2:2063

A One-Armed Phase I Dose Escalation Trial Design: Personalized Vaccination with IKKβ-Matured, RNA-Loaded Dendritic Cells for Metastatic Uveal Melanoma - Koch, Elias; Schaft, Niels; Kummer, Mirko; Berking, Carola; Schuler, Gerold; Hasumi, Kenichiro; Dörrie, Jan; Schuler-Thurner, Beatrice (Frontiers in Immunology, 2022)
Uveal melanoma (UM) is an orphan disease with a mortality of 80% within one year upon the development of metastatic disease. UM does hardly respond to chemotherapy and kinase inhibitors and is largely resistant to checkpoint inhibition. Hence, further therapy approaches are urgently needed. To improve clinical outcome, we designed a trial employing the 3rd generation personalized IKKβ-matured RNA-transfected dendritic cell (DC) vaccine which primes T cells and in addition activates NK cells. This ongoing phase I trial [NCT04335890 (www.clinicaltrials.gov), Eudract: 2018-004390-28 (www.clinicaltrialsregister.eu)] investigates patients with treatment-naive metastatic UM. Monocytes are isolated by leukapheresis, differentiated to immature DCs, matured with a cytokine cocktail, and activated via the NF-κB pathway by electroporation with RNA encoding a constitutively active mutant of IKKβ. Three types of antigen-RNA are co-electroporated: i) amplified mRNA of the tumor representing the whole transcriptome, ii) RNA encoding driver mutations identified by exome sequencing, and iii) overexpressed non-mutated tumor antigens detected by transcriptome sequencing. This highly personalized DC vaccine is applied by 9 intravenous infusions in a staggered schedule over one year. Parallel to the vaccination, standard therapy, usually an immune checkpoint blockade (ICB) as mono (anti-PD-1) or combined (anti-CTLA4 and anti-PD-1) regimen is initiated. The coordinated vaccine-induced immune response encompassing tumor-specific T cells and innate NK cells should synergize with ICB, perhaps resulting in measurable clinical responses in this resistant tumor entity. Primary outcome measures of this trial are safety, tolerability and toxicity; secondary outcome measures comprise overall survival and induction of antigen-specific T cells.
CRIS-Team Scopus Importer:2022-03-04
Keywords: IKKβ-matured dendritic cells; Immune checkpoint blockade; metastatic uveal melanoma; personalized vaccine; tumor antigen vaccine; tumor antigens

Are YouTube videos on cutaneous squamous cell carcinoma a useful and reliable source for patients? - Reinhardt, Lydia; Steeb, Theresa; Harlaß, Matthias; Brütting, Julia; Meier, Friedegund; Berking, Carola (Journal der Deutschen Dermatologischen Gesellschaft, 2022)
EVALuna2:510787

Arming T cells with a gp100-specific TCR and a CSPG4-specific CAR using combined DNA-and RNA-based receptor transfer - Simon, Bianca; Harrer, Dennis C.; Schuler-Thurner, Beatrice; Schuler, Gerold; Uslu, Ugur (Cancers, 2019)
Tumor cells can develop immune escape mechanisms to bypass T cell recognition, e.g., antigen loss or downregulation of the antigen presenting machinery, which represents a major challenge in adoptive T cell therapy. To counteract these mechanisms, we transferred not only one, but two receptors into the same T cell to generate T cells expressing two additional receptors (TETARs). We generated these TETARs by lentiviral transduction of a gp100-specific T cell receptor (TCR) and subsequent electroporation of mRNA encoding a second-generation CSPG4-specific chimeric antigen receptor (CAR). Following pilot experiments to optimize the combined DNA-and RNA-based receptor transfer, the functionality of TETARs was compared to T cells either transfected with the TCR only or the CAR only. After transfection, TETARs clearly expressed both introduced receptors on their cell surface. When stimulated with tumor cells expressing either one of the antigens or both, TETARs were able to secrete cytokines and showed cytotoxicity. The confirmation that two antigen-specific receptors can be functionally combined using two different methods to introduce each receptor into the same T cell opens new possibilities and opportunities in cancer immunotherapy. For further evaluation, the use of these TETARs in appropriate animal models will be the next step towards a potential clinical use in cancer patients.
CRIS-Team Scopus Importer:2019-06-21
Keywords: Antigen loss; Cancer; Chimeric antigen receptor; Electroporation; Immune escape; Immunotherapy; Lentiviral transduction; Lentivirus; Melanoma

Artificial intelligence in cancer target identification and drug discovery - You, Yujie; Lai, Xin; Pan, Yi; Zheng, Huiru; Vera, Julio; Liu, Suran; Deng, Senyi; Zhang, Le (Signal Transduction and Targeted Therapy, 2022)
Artificial intelligence is an advanced method to identify novel anticancer targets and discover novel drugs from biology networks because the networks can effectively preserve and quantify the interaction between components of cell systems underlying human diseases such as cancer. Here, we review and discuss how to employ artificial intelligence approaches to identify novel anticancer targets and discover drugs. First, we describe the scope of artificial intelligence biology analysis for novel anticancer target investigations. Second, we review and discuss the basic principles and theory of commonly used network-based and machine learning-based artificial intelligence algorithms. Finally, we showcase the applications of artificial intelligence approaches in cancer target identification and drug discovery. Taken together, the artificial intelligence models have provided us with a quantitative framework to study the relationship between network characteristics and cancer, thereby leading to the identification of potential anticancer targets and the discovery of novel drug candidates.
CRIS-Team WoS Importer:2022-05-20

A single-center, retrospective Analysis for the Detection of Distant Metastases in Patients with regionally metastatic Melanoma in the Era of effective adjuvant Therapies - Toussaint, Frédéric; Kramer, Robert Anton; Bender-Säbelkampf, Sophia; Hornung-Eichler, Annkathrin; Karimi, Bita; Heppt, Markus; Bosch-Voskens, Caroline; Berking, Carola; Erdmann, Michael (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2022)
CRIS-Team WoS Importer:2022-09-23

Assessment of sorafenib induced changes in tumor perfusion of uveal melanoma metastases with dynamic contrast-enhanced ultrasound (DCE-US) - Wildner, Dane; Heinzerling, Lucie; Scheulen, Max E.; Kämpgen, Eckhart; Schuler, Gerold; Strobel, Deike; Janka, Rolf Matthias; Neurath, Markus; Sturm, Jörg; Knieling, Ferdinand (Journal of Cancer Research and Clinical Oncology, 2021)
Purpose Dynamic contrast-enhanced ultrasound (DCE-US) was used to monitor early response to sorafenib therapy in patients with liver metastases from uveal melanoma. Methods In total, 21 patients with liver metastases were recruited within a prospective trial and underwent daily sorafenib therapy. DCE-US of a target lesion was performed before initiation of treatment, on day 15 and 56. Two independent blinded investigators performed software analysis for DCE-US parameters and inter-observer-correlation was calculated. Response to treatment was evaluated on day 56. DCE-US parameters were correlated with clinical response and RECIST1.1 criteria. Results Inter-observer-correlation (r) of DCE-US parameters [time-to-peak (TTP), mean-transit-time (MTT), peak intensity (PI), regional blood volume (RBV), regional blood flow (RBF)] at baseline, day 15, and day 56 was highly significant (r-range 0.73-0.97, all p < 0.001). Out of 17 evaluable patients, 12 patients survived day 56 (clinical responders, cRE), whereas, five patients died before day 56 and were classified as non-responders (cNR). TTP values significantly increased in the cRE group 15 days after initiation of treatment for investigator 1 (p = 0.034) and at day 56 for both investigators (p = 0.028/0.028). MTT had increased significantly in the cRE group on day 56 (p = 0.037/0.022). In the cNR group changes for TTP and MTT remained insignificant. Thus, increase of the DCE-US parameters TTP and MTT are associated with response to treatment and prognosis. Conclusion An increase of TTP and MTT at frequent intervals could serve as a surrogate marker for early response evaluation to anti-angiogenic treatment of metastatic uveal melanoma.
CRIS-Team WoS Importer:2021-06-04

Assessment of the Quality, Understandability, and Reliability of YouTube Videos as a Source of Information on Basal Cell Carcinoma:Web-Based Analysis - Steeb, Theresa; Reinhardt, Lydia; Harlaß, Matthias; Heppt, Markus; Meier, Friedegund; Berking, Carola (JMIR Cancer, 2022)
Background: Patients with skin cancer increasingly watch online videos to acquire disease-related information. Until now, no scientific evaluation of the quality of videos available for German-speaking patients with basal cell carcinoma (BCC) has been performed. Objective: In this study, we aimed to identify and evaluate videos about BCC provided on YouTube. Methods: A video search on YouTube was conducted in July 2020, using German BCC-related keywords (eg, "Basalzellkarzinom," "Basaliom," "weißer hautkrebs," and "heller hautkrebs"). The first three pages (ie, 60 videos) were searched by two independent researchers for each keyword. Two authors evaluated videos that met the predefined eligibility criteria. The quality of the information of the videos was evaluated using the DISCERN tool and the Global Quality Scale (GQS). The understandability and actionability were assessed with the Patient Education Materials Assessment Tool for Audiovisual Materials (PEMAT-A/V). The reliability was assessed with the JAMA (Journal of the American Medical Association) criteria score. Subgroup differences were identified using the Kruskal-Wallis test. Results: A total of 41 videos were included in the evaluation. The mean assessment scores were as follows: DISCERN, 3.3 (SD 0.80); GQS, 3.8 (SD 1.1); JAMA, 27.74% (SD 22.1%); understandability, 70.8% (SD 13.3%); and actionability, 45.9% (SD 43.7%). These values indicated that the videos were of medium to good quality and had good understandability, low actionability, and poor reliability. The quality of videos provided by health professionals was significantly higher than that of videos provided by laypersons. Conclusions: Optimization of health-related videos about BCC is desirable. In particular, adaptation to reliability criteria is necessary to support patient education and increase transparency.
CRIS-Team Scopus Importer:2022-03-25
Keywords: basal cell carcinoma; information; internet; patient education; quality; reliability; shared decision-making; videos; YouTube

Assessment of the Severity of Atopic Dermatitis by Physicians and Patients depending on Gender: Results from the German Atopic Dermatitis Registry TREATgermany - Heinrich, L.; Haufe, E.; Abraham, S.; Heratizadeh, A.; Harder,; Kleinheinz, A.; Wollenberg, A.; Weisshaar, E.; Wiemers, F.; Ertner, K.; Schaekel, K.; Augustin, M.; et al. (GESUNDHEITSWESEN, 2021)
CRIS-Team WoS Importer:2022-05-20

Association analyses of functional NCF1 variants in psoriatic arthritis and psoriasis vulgaris - Hüffmeier, Ulrike; Löhr, Sabine; Ekici, Arif Bülent; Uebe, S.; Koehm, M.; Behrens, F.; Boehm, B.; Sticherling, Michael; Schett, Georg; Moessner, R.; Nimeh, A.; Assmann, G.; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2019)
CRIS-Team WoS Importer:2019-10-25

Association of Fabry Disease and Psoriasis - therapeutically significant? - Sollfrank, Lukas; Sticherling, Michael (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2021)
CRIS-Team WoS Importer:2021-04-16

Association of Structural Entheseal Lesions With an Increased Risk of Progression From Psoriasis to Psoriatic Arthritis - Simon, David; Tascilar, Koray; Kleyer, Arnd; Bayat, Sara; Kampylafka, Eleni; Sokolova, Maria; Zekovic, Ana; Hueber, Axel; Rech, Jürgen; Schuster, Louis; Engel, Klaus; Sticherling, Michael; et al. (Arthritis and Rheumatology, 2021)
Objective. To test whether the presence of structural entheseal lesions in psoriasis patients influences the risk of progression to psoriatic arthritis (PsA).
CRIS-Team WoS Importer:2022-01-07

A Systematic Review and Meta-Analysis of Interventions for Actinic Keratosis from Post-Marketing Surveillance Trials - Steeb, Theresa; Wessely, Anja; Harla, Matthias; Heppt, Franz; Koch, Elias; Leiter, Ulrike; Garbe, Claus; Schöffski, Oliver; Berking, Carola; Heppt, Markus (Journal of Clinical Medicine, 2020)
Multiple interventions are available for the treatment of actinic keratosis (AK) showing high efficacy in pivotal trials. However, data from post-marketing surveillance studies have received little attention until now. Here, we systematically investigate interventions for AK from post-marketing surveillance trials as a proxy for real-world efficacy and tolerability. A systematic literature search was conducted in Medline, Embase, and CENTRAL. Pertinent trial registers were hand-searched until 25 March 2020. Results were pooled using a random-effects model to calculate pooled proportions and relative risks (RR) or were described qualitatively. Eleven records with a total sample size ofn= 4109 were included. Three of the studies had an active-controlled design, while seven were single-armed. Participant complete clearance ranged from 23.1% for diclofenac sodium 3% gel to 88.9% for ingenol mebutate 0.05% gel. The lesion-specific clearance rate for photodynamic therapy (PDT) was 74% (95% confidence interval (CI) 56-87%). The recurrence rate was significantly higher for diclofenac sodium 3% in comparison to imiquimod 5% cream (RR 1.10, 95% CI 1.02-1.1.8) and ranged from 10.6% for ingenol mebutate 0.015% gel to 23.5% for PDT. Few patients discontinued the trials due to adverse events. The results from the majority of the post-marketing surveillance studies deviated from those of pivotal trials.
CRIS-Team WoS Importer:2020-08-21

A systems biology approach to characterize the function of miRNAs in dendritic cell-mediated immunogenicity and therapeutic cancer vaccination - Lai, X.; Dreyer, F.; Jaitly, T.; Gerer, K. F.; Schuler, Gerold; Dörrie, Jan; Schaft, Niels; Vera, Julio (2017)
EVALuna2:34309

A systems' biology approach to study microRNA-mediated gene regulatory networks - Lai, Xin; Bhattacharya, Animesh; Schmitz, Ulf; Kunz, Manfred; Wolkenhauer, Olaf; Vera González, Julio (BioMed Research International, 2013)
MicroRNAs (miRNAs) are potent effectors in gene regulatory networks where aberrant miRNA expression can contribute to human diseases such as cancer. For a better understanding of the regulatory role of miRNAs in coordinating gene expression, we here present a systems biology approach combining data-driven modeling and model-driven experiments. Such an approach is characterized by an iterative process, including biological data acquisition and integration, network construction, mathematical modeling and experimental validation. To demonstrate the application of this approach, we adopt it to investigate mechanisms of collective repression on p21 by multiple miRNAs. We first construct a p21 regulatory network based on data from the literature and further expand it using algorithms that predict molecular interactions. Based on the network structure, a detailed mechanistic model is established and its parameter values are determined using data. Finally, the calibrated model is used to study the effect of different miRNA expression profiles and cooperative target regulation on p21 expression levels in different biological context
Keywords: miRNAs; bioiformatics; network biology; systems biology

A Tribute to Robert (Bob) Sim-Personal Memories of Working in Bob's Lab - Williams, Samantha; Steinkasserer, Alexander (Viruses, 2021)
This article is intended as a tribute to Robert B. Sim through the sharing of personal memories and anecdotes from two of Bob's lab members who worked in his lab between 1989 to 1994.
CRIS-Team Scopus Importer:2021-10-29
Keywords: complement; obituary; Robert B. Sim

Author Correction: DeepNAPSI multi-reader nail psoriasis prediction using deep learning. - Folle, Lukas; Fenzl, Pauline; Fagni, Filippo; Thies, Mareike; Christlein, Vincent; Meder, Christine; Simon, David; Minopoulou, Ioanna; Sticherling, Michael; Schett, Georg; Maier, Andreas; Kleyer, Arnd (Scientific Reports, 2023)
EVALuna2:538275

Autocrine TNF is critical for the survival of human dendritic cells by regulating BAK, BCL-2, and FLIP L - Lehner, Manfred; Kellert, Beate; Proff, Julia; Schmid, Martina A.; Diessenbacher, Philip; Enßer, Armin; Dörrie, Jan; Schaft, Niels; Leverkus, Martin; Kämpgen, Eckhart; Holter, Wolfgang (Journal of Immunology, 2012)
The life span of dendritic cells (DCs) is determined by the balance of pro- and antiapoptotic proteins. In this study, we report that serum-free cultured human monocyte-derived DCs after TLR stimulation with polyinosinic acid-polycytidylic acid or LPS underwent apoptosis, which was correlated with low TNF production. Apoptosis was prevented by the addition of exogenous TNF or by concomitant stimulation with R-848, which strongly amplified endogenous TNF production. Neutralization of TNF confirmed that DC survival was mediated by autocrine TNF induced either by stimulation with R-848 or by ligation of CD40. DCs stimulated by polyinosinic acid-polycytidylic acid or IFN-β, another known inducer of DC apoptosis, were characterized by high levels and activation of the proapoptotic protein BAK. The ratio of antiapoptotic BCL-2 to BAK correlated best with the survival of activated DCs. Addition of TNF increased this ratio but had little effect on BAX and XIAP. Knockdown experiments using small interfering RNAs confirmed that the survival of activated and also of immature DCs was regulated by BAK and showed that TNF was protective only in the presence of FLIP L. Together, our data demonstrate that the survival of DCs during differentiation and activation depends on autocrine TNF and that the inhibition of BAK plays an important role in this process. Copyright © 2012 by The American Association of Immunologists, Inc.
CRIS-Team Scopus Importer:2021-10-01

Autoimmune Colitis and Subsequent CMV-induced Hepatitis After Treatment With Ipilimumab - Uslu, Ugur; Agaimy, Abbas; Hundorfean, Gheorghe; Harrer, Thomas; Schuler, Gerold; Heinzerling, Lucie (Journal of Immunotherapy, 2015)
Ipilimumab, a humanized CTLA-4 antibody, improves overall survival in patients with metastatic melanoma. However, immune-related adverse effects occur in about 65% of ipilimumab-treated patients and have to be adequately managed. A 55-year-old patient developed grade 3 autoimmune colitis 7 weeks after initiation of ipilimumab treatment and subsequently hepatitis with grade 3 elevation of transaminases and ?-glutamyl transferase. Colitis manifested with up to 18 watery and bloody stools per day and severe attacks of abdominal pain. After exclusion of infectious causes, immunosuppression with corticosteroids was initiated. Because of recurrent abdominal pain, spontaneous perforation of the colon had to be excluded. Elevated liver function tests (grade 3 CTCAE) occurred and differential diagnosis included immune-mediated, toxic, and viral hepatitis. It is interesting to note that, not an immune-mediated but a cytomegalovirus-induced hepatitis was diagnosed by serum blood tests and liver biopsy and was subsequently successfully treated. Careful elaboration of the patient under immunotherapy was essential as further immunosuppression mandatory for autoimmune hepatitis would have worsened the viral hepatitis. In conclusion, cytomegalovirus reactivation should be included in the differential in patients under immunotherapy with checkpoint inhibitors and has to be considered as a cause for morbidity.
EVALuna2:1966

Autologous regulatory T-cell transfer in refractory ulcerative colitis with concomitant primary sclerosing cholangitis - Voskens, Caroline; Stoica, Diane; Rosenberg, Marita; Vitali, Francesco; Zundler, Sebastian; Ganslmayer, Marion; Knott, Heike; Wiesinger, Manuel; Wunder, Jutta; Kummer, Mirko; Siegmund, Britta; Schnoy, Elisabeth; et al. (Gut, 2022)
Objective Ulcerative colitis (UC) is a chronic, debilitating immune-mediated disease driven by disturbed mucosal homeostasis, with an excess of intestinal effector T cells and an insufficient expansion of mucosal regulatory T cells (Tregs). We here report on the successful adoptive transfer of autologous, ex vivo expanded Tregs in a patient with refractory UC and associated primary sclerosing cholangitis (PSC), for which effective therapy is currently not available.
CRIS-Team WoS Importer:2022-04-29

Automated closed-system manufacturing of human monocyte-derived dendritic cells for cancer immunotherapy - Erdmann, Michael; Uslu, Ugur; Wiesinger, Manuel; Bruening, Mareke; Altmann, Tobias; Strasser, Erwin; Schuler, Gerold; Schuler-Thurner, Beatrice (Journal of Immunological Methods, 2018)
Dendritic cell (DC)-based vaccines have been successfully used for immunotherapy of cancer and infections. A major obstacle is the need for high-level class A cleanroom cGMP facilities for DC generation. The CliniMACS Prodigy® (Prodigy) represents a new platform integrating all GMP-compliant manufacturing steps in a closed system for automated production of various cellular products, notably T cells, NK cells and CD34+ cells. We now systematically tested its suitability for producing human mature monocyte-derived DCs (Mo-DCs), and optimized it by directly comparing the Prodigy approach to our established standard production of Mo-DCs from elutriated monocytes in dishes or bags. Upon step-by-step identification of an optimal cell concentration for the Prodigy's CentriCult culture chamber, the total yield (% of input CD14+ monocytes), phenotype, and functionality of mature Mo-DCs were equivalent to those generated by the standard protocol. Technician's labor time was comparable for both methods, but the Prodigy approach significantly reduced hands-on time and high-level clean room resources. In summary, using our optimized conditions for the CliniMACS Prodigy, human Mo-DCs for clinical application can be generated almost automatically in a fully closed system. A significant drawback of the Prodigy approach was, however, that due to the limited size of the CentriCult culture chamber, in contrast to our standard semi-closed elutriation approach, only one fourth of an apheresis could be processed at once.
EVALuna2:203616

Automated Good Manufacturing Practice–compliant generation of human monocyte-derived dendritic cells from a complete apheresis product using a hollow-fiber bioreactor system overcomes a major hurdle in the manufacture of dendritic cells for cancer vaccines - Uslu, Ugur; Erdmann, Michael; Wiesinger, Manuel; Schuler, Gerold; Schuler-Thurner, Beatrice (Cytotherapy, 2019)
Background: Although dendritic cell (DC)–based cancer vaccines represent a promising treatment strategy, its exploration in the clinic is hampered due to the need for Good Manufacturing Practice (GMP) facilities and associated trained staff for the generation of large numbers of DCs. The Quantum bioreactor system offered by Terumo BCT represents a hollow-fiber platform integrating GMP-compliant manufacturing steps in a closed system for automated cultivation of cellular products. In the respective established protocols, the hollow fibers are coated with fibronectin and trypsin is used to harvest the final cell product, which in the case of DCs allows processing of only one tenth of an apheresis product. Materials and Results: We successfully developed a new protocol that circumvents the need for fibronectin coating and trypsin digestion, and makes the Quantum bioreactor system now suitable for generating large numbers of mature human monocyte-derived DCs (Mo-DCs) by processing a complete apheresis product at once. To achieve that, it needed a step-by-step optimization of DC-differentiation, e.g., the varying of media exchange rates and cytokine concentration until the total yield (% of input CD14+ monocytes), as well as the phenotype and functionality of mature Mo-DCs, became equivalent to those generated by our established standard production of Mo-DCs in cell culture bags. Conclusions: By using this new protocol for the Food and Drug Administration–approved Quantum system, it is now possible for the first time to process one complete apheresis to automatically generate large numbers of human Mo-DCs, making it much more feasible to exploit the potential of individualized DC-based immunotherapy.
CRIS-Team Scopus Importer:2019-11-12
Keywords: adoptive cell transfer; cell therapy; cellular therapy; dendritic cell vaccine; dendritic cells; immunotherapy; monocyte-derived dendritic cells; vaccines

Autophagic degradation of lamins facilitates the nuclear egress of herpes simplex virus type 1 - Turan, Aykut; Grosche, Linda; Krawczyk, Adalbert; Mühl-Zürbes, Petra; Drassner, Christina; Düthorn, Alexandra; Kummer, Mirko; Hasenberg, Mike; Voortmann, Sylvia; Jastrow, Holger; Dörrie, Jan; Schaft, Niels; et al. (The Journal of Cell Biology, 2019)
Dendritic cells (DCs) are crucial for the induction of potent antiviral immune responses. In contrast to immature DCs (iDCs), mature DCs (mDCs) are not permissive for infection with herpes simplex virus type 1 (HSV-1). Here, we demonstrate that HSV-1 infection of iDCs and mDCs induces autophagy, which promotes the degradation of lamin A/C, B1, and B2 in iDCs only. This in turn facilitates the nuclear egress of progeny viral capsids and thus the formation of new infectious particles. In contrast, lamin protein levels remain stable in HSV-1-infected mDCs due to an inefficient autophagic flux. Elevated protein levels of KIF1B and KIF2A in mDCs inhibited lamin degradation, likely by hampering autophagosome-lysosome fusion. Therefore, in mDCs, fewer progeny capsids were released from the nuclei into the cytosol, and fewer infectious virions were assembled. We hypothesize that inhibition of autophagic lamin degradation in mDCs represents a very powerful cellular counterstrike to inhibit the production of progeny virus and thus viral spread.
CRIS-Team WoS Importer:2019-02-21

Autophagy-Mediated Breakdown of the nuclear lamina facilitates nuclear egress of HSV-1 capsids and thus generation of progeny virus in dendritic cells - Turan, A.; Krawczyk, A.; Grosche, Linda; Mühl-Zürbes, Petra; Drassner, C.; Hasenberg, M.; Voortmann, S.; Jastrow, H.; Kraner, Max; Doehner, K.; Sodeik, B.; Heilingloh, Christiane; et al. (2018)
EVALuna2:36213

A web-based comprehensive map including regulatory pathways subverted in melanoma that can be visualized, browsed and used for analysing cell line and patient high through put data - Dreyer, Florian; Cantone, Martina; Eberhardt, Martin; Schuler, Gerold; Vera, Julio (2016)
EVALuna2:19614

A web platform for the network analysis of high-throughput data in melanoma and its use to investigate mechanisms of resistance to anti-PD1 immunotherapy - Dreyer, Florian; Cantone, Martina; Eberhardt, Martin; Jaitly, Tanushree; Walter, Lisa; Wittmann, Jürgen; Gupta, Shailendra; Khan, Faiz M.; Wolkenhauer, Olaf; Puetzer, Brigitte M.; Jäck, Hans-Martin; Heinzerling, Lucie; et al. (Biochimica et Biophysica Acta - Molecular Basis of Disease, 2018)
Cellular phenotypes are established and controlled by complex and precisely orchestrated molecular networks. In cancer, mutations and dysregulations of multiple molecular factors perturb the regulation of these networks and lead to malignant transformation. High-throughput technologies are a valuable source of information to establish the complex molecular relationships behind the emergence of malignancy, but full exploitation of this massive amount of data requires bioinformatics tools that rely on network-based analyses. In this report we present the Virtual Melanoma Cell, an online tool developed to facilitate the mining and interpretation of high-throughput data on melanoma by biomedical researches. The platform is based on a comprehensive, manually generated and expert-validated regulatory map composed of signaling pathways important in malignant melanoma. The Virtual Melanoma Cell is a tool designed to accept, visualize and analyze user-generated datasets. It is available at: https://www.vcells.net/melanoma. To illustrate the utilization of the web platform and the regulatory map, we have analyzed a large publicly available dataset accounting for anti-PD1 immunotherapy treatment of malignant melanoma patients.
EVALuna2:34379
Keywords: Therapy resistance; Databases; Network genomics; Systems biology; Immunotherapy; Melanoma

A web tool for the oligodendrocyte differentiation data and network analysis - Cantone, Martina; Eberhardt, Martin; Küspert, Melanie; Reiprich, Simone; Wegner, Michael; Vera, Julio (2017)
EVALuna2:33481

Bacterial Adherence and Dwelling Probability: Two Drivers of Early Alveolar Infection by Streptococcus pneumoniae Identified in Multi-Level Mathematical Modeling - Santos, Guido; Lai, Xin; Eberhardt, Martin; Vera, Julio (Frontiers in Cellular and Infection Microbiology, 2018)
Pneumococcal infection is the most frequent cause of pneumonia, and one of the most prevalent diseases worldwide. The population groups at high risk of death from bacterial pneumonia are infants, elderly and immunosuppressed people. These groups are more vulnerable because they have immature or impaired immune systems, the efficacy of their response to vaccines is lower, and antibiotic treatment often does not take place until the inflammatory response triggered is already overwhelming. The immune response to bacterial lung infections involves dynamic interactions between several types of cells whose activation is driven by intracellular molecular networks. A feasible approach to the integration of knowledge and data linking tissue, cellular and intracellular events and the construction of hypotheses in this area is the use of mathematical modeling. For this paper, we used a multi-level computational model to analyse the role of cellular and molecular interactions during the first 10 h after alveolar invasion of Streptococcus pneumoniae bacteria. By "multi-level" we mean that we simulated the interplay between different temporal and spatial scales in a single computational model. In this instance, we included the intracellular scale of processes driving lung epithelial cell activation together with the scale of cell-to-cell interactions at the alveolar tissue. In our analysis, we combined systematic model simulations with logistic regression analysis and decision trees to find genotypic-phenotypic signatures that explain differences in bacteria strain infectivity. According to our simulations, pneumococci benefit from a high dwelling probability and a high proliferation rate during the first stages of infection. In addition to this, the model predicts that during the very early phases of infection the bacterial capsule could be an impediment to the establishment of the alveolar infection because it impairs bacterial colonization.
EVALuna2:34792

Baseline characteristics, disease severity and treatment history of patients with atopic dermatitis included in the German AD Registry TREATgermany - Heratizadeh, A.; Haufe, E.; Stoelzl, D.; Abraham, S.; Heinrich, L.; Kleinheinz, A.; Wollenberg, A.; Weisshaar, E.; Augustin, M.; Wiemers, F.; Zink, A.; Von Kiedrowski, R.; et al. (Journal of the European Academy of Dermatology and Venereology, 2020)
Background The Atopic Dermatitis (AD) TREATgermany registry was initiated by the German Society for Dermatology (DDG) in 2011 to evaluate the 'real-life' situation of health care for patients with AD.
CRIS-Team WoS Importer:2020-02-28

B cells are critical for autoimmune pathology in Scurfy mice. - Aschermann, Susanne; Lehmann, Christian; Mihai, Sidonia; Schett, Georg; Dudziak, Diana; Nimmerjahn, Falk (Proceedings of the National Academy of Sciences of the United States of America, 2013)
Impaired regulatory T-cell function results in a severe chronic autoimmune disease affecting multiple organs in Scurfy mice and humans with the immune dysregulation, polyendocrinopathy, enteropathy, X-linked (IPEX) syndrome. Previous studies have shown that T helper cells but not cytotoxic T cells are critical for the disease pathology. Whether this T-cell subset is responsible directly for tissue inflammation or rather indirectly via the interaction with B cells or myeloid cells is largely unknown. To study this and to identify potential therapeutic targets for this lethal disease we investigated the contribution of B cells to this complex autoimmune phenotype. We show that B cells and the production of autoantibodies plays a major role for skin, liver, lung, and kidney inflammation and therapeutic depletion of B cells resulted in reduced tissue pathology and in prolonged survival. In contrast, the absence of B cells did not impact systemic T-cell activation and hyperreactivity, indicating that autoantibody production by B cells may be a major factor for the autoimmune pathology in mice deficient for regulatory T cells.

B-cells in psoriasis? - Banki, Simon; Heusinger, Juliane; Herter-Kermann, T.; Sticherling, Michael (EXPERIMENTAL DERMATOLOGY, 2021)
CRIS-Team WoS Importer:2021-05-14

BCL2 Inhibition Reveals a Dendritic Cell-Specific Immune Checkpoint That Controls Tumor Immunosurveillance - Zhao, Liwei; Liu, Peng; Mao, Misha; Zhang, Shuai; Bigenwald, Camille; Dutertre, Charles Antoine; Lehmann, Christian; Pan, Hui; Paulhan, Nicolas; Amon, Lukas; Buqué, Aitziber; Yamazaki, Takahiro; et al. (Cancer Discovery, 2023)
We developed a phenotypic screening platform for the functional exploration of dendritic cells (DC). Here, we report a genome-wide CRISPR screen that revealed BCL2 as an endogenous inhibitor of DC function. Knockout of BCL2 enhanced DC antigen presentation and activation as well as the capacity of DCs to control tumors and to synergize with PD-1 blockade. The pharmacologic BCL2 inhibitors venetoclax and navitoclax phenocopied these effects and caused a cDC1-dependent regression of orthotopic lung cancers and fibrosarcomas. Thus, solid tumors failed to respond to BCL2 inhibition in mice constitutively devoid of cDC1, and this was reversed by the infusion of DCs. Moreover, cDC1 depletion reduced the therapeutic efficacy of BCL2 inhibitors alone or in combination with PD-1 blockade and treatment with venetoclax caused cDC1 activation, both in mice and in patients. In conclusion, genetic and pharmacologic BCL2 inhibition unveils a DC-specific immune checkpoint that restrains tumor immunosurveillance. SIGNIFICANCE: BCL2 inhibition improves the capacity of DCs to stimulate anticancer immunity and restrain cancer growth in an immunocompetent context but not in mice lacking cDC1 or mature T cells. This study indicates that BCL2 blockade can be used to sensitize solid cancers to PD-1/PD-L1-targeting immunotherapy. This article is featured in Selected Articles from This Issue, p. 2293.
CRIS-Team Scopus Importer:2023-11-17

Behandlung der Psoriasis mit Secukinumab: Praxisrelevante Hinweise - Körber, Andreas; Augustin, Matthias; Behrens, Frank; Gerdes, Sascha; von Kiedrowski, Ralph; Schäkel, Knut; Sticherling, Michael; Wilsmann-Theis, Dagmar; Wohlrab, Johannes; Simon, Jan Christoph (Hautarzt, 2021)
Background: Moderate to severe plaque psoriasis can be treated effectively with immunomodulating biologicals such as the interleukin-17A inhibitor secukinumab. In practice, however, questions often arise as to how to proceed in special situations, such as infections, comorbidity, pregnancy, or surgery. Objectives: To address frequent questions about the treatment of plaque psoriasis with secukinumab in a consensus document of German psoriasis experts that supplements current guidelines. Methods: In a virtual expert meeting in May 2020, practical aspects of the treatment of psoriasis were discussed based on the experience of the participants and on current literature. The results of this discussion were summarized in the present consensus document. Results: This article provides practical guidance on case history, documentation of previous therapies, severity of psoriasis, and comorbidities before starting therapy with secukinumab. For patients treated with secukinumab, the course of action in case of vaccinations, chronic or acute infections, surgical interventions, special manifestations of psoriasis, and comorbidities including history of cancer and autoimmune disorders is discussed. Questions regarding family planning and health policy regulations are also addressed. Discussion: The recommendations for the treatment of psoriasis with secukinumab summarized in this consensus document may contribute to achieve optimal therapy for patients and to improve their quality of life.
CRIS-Team Scopus Importer:2021-08-27
Keywords: Biological products; Comorbidity; Infections; Perioperative management; Special situations

Beyond-Mild Psoriasis: A Consensus Statement on Calcipotriol and Betamethasone Dipropionate Foam for the Topical Treatment of Adult Patients - Aschoff, Roland; Bewley, Anthony; Dattola, Annunziata; De Simone, Clara; Lahfa, Mourad; Llamas-Velasco, Mar; Martorell, Antonio; Pavlovic, Mira; Sticherling, Michael (Dermatology and Therapy, 2021)
Introduction There are clear treatment options for mild psoriasis where topical therapies are the mainstay, and for severe psoriasis where systemic therapy (biologic or non-biologic) is necessary. However, there is less clarity in the 'grey zone' of patients in the moderate or so-called 'beyond-mild' segment. There are frequent delays to the initiation, discontinuation, switching and dose change in treatment, and many patients fail to continue treatment because of concerns about safety or lack of efficacy. Treatment with topical therapies, such as calcipotriol and betamethasone dipropionate (Cal/BD) combinations, may be suitable for these patients. Method These consensus recommendations on the use of topical therapies including Cal/BD foam for beyond-mild psoriasis originated from a modified Delphi process of European clinical experts. In the process, the experts iteratively refined a series of draft statements, which had to receive >= 80% approval to be incorporated into the consensus. Results The experts identified three main themes: Cal/BD foam as monotherapy, as an add-on to non-biologic systemic therapies and as an add-on to systemic biologics. The consensus emphasises disease factors and patient preference in treatment choice, summarises the evidence base for Cal/BD foam monotherapy for flare treatment as well as long-term management, and identifies the potential for improved treatment outcomes, such as reduced time to onset of action and reduced systemic dose to minimise side effects for add-on Cal/BD therapy to non-biologic systemics. The recommendations regarding add-on Cal/BD foam to biologics are similar to those for non-biologic systemic therapies, but also include suggestions for patients on biologics who are late responders. As clinical choices of Cal/BD combination vary, we have here often used 'Cal/BD' without reference to any particular formulation. Conclusions These recommendations aim to give practical guidance to those treating patients with beyond-mild psoriasis, to support patients' use of topical preparations and to optimise treatment outcomes.
CRIS-Team WoS Importer:2021-09-24

Bin-based visualization of cytokine-co-expression patterns of IL-10-producing CD4 T cell subsets - Mohr, Elodie; Hinnenthal, Timo; Gryzik, Stefanie; Hoang, Yen; Lischke, Timo; Retzlaff, Jimmy; Mekonnen, Ariana; Paul, Friedemann; Valleriani, Angelo; Radbruch, Andreas; Vera, Julio; Baumgrass, Ria (European Journal of Immunology, 2022)
CRIS-Team Scopus Importer:2022-10-07
Keywords: cytokine; cytometry; IL-10; pattern perception; T cells

BIOACTIVE GLASSES AND THE IMMUNE SYSTEM: RECENT FINDINGS AND FUTURE PERSPECTIVES - Boccaccini, Aldo R.; Schuhladen, Katharina; Steinkasserer, Alexander; Zinser, Elisabeth (TISSUE ENGINEERING PART A, 2022)
CRIS-Team WoS Importer:2022-08-12

Block Excision of Iridociliary Tumors Enables Molecular Profiling and Immune Vaccination - Heindl, Ludwig M.; Koch, Konrad R.; Hermann, Manuel M.; Merkelbach-Bruse, Sabine; Schultheis, Anne M.; Wagener, Svenja; Buettner, Reinhard; Mauch, Cornelia; Schuler-Thurner, Beatrice; Schuler, Gerold; Cursiefen, Claus (Ophthalmology, 2017)
EVALuna2:34326

Blood-Based Biomarkers of Inflammation and Tissue Remodeling Can Discriminate Between Rheumatoid Arthritis, Psoriasis, and Psoriatic Arthritis and Are Associated with Hand Function - Port Linares, Helena; Coppers, Birte; Bayat, Sara; Elie-Tino, Godonou; Fagni, Filippo; Corte, Giulia; Bay-Jensen, Anne-Christine; Tascilar, Koray; Hueber, Axel; Schönau, Verena; Sticherling, Michael; Heinrich, Simon; et al. (poster, American College of Rheumatology Convergence, 2023)

Blood eosinophilia is an on-treatment biomarker in patients undergoing vaccination with dendritic cells that correlates with long-term patient outcome - Moreira, Alvaro; Vass, V.; Erdmann, M.; Sponagl, F.; Schuler, Gerold; Schuler-Thurner, Beatrice (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-09-13

Blood eosinophilia is an on-treatment biomarker in patients with solid tumors undergoing dendritic cell vaccination with autologous tumor-RNA - Moreira, Alvaro; Erdmann, Michael; Uslu, Ugur; Vass, Verona; Schuler, Gerold; Schuler-Thurner, Beatrice (Pharmaceutics, 2020)
Background: The approvals of immune checkpoint inhibitors for several cancer types and the rapidly growing recognition that T cell-based immunotherapy significantly improves outcomes for cancer patients led to a re-emergence of cancer vaccines, including dendritic cell (DC)-based immunotherapy. Blood and tissue biomarkers to identify responders and long-term survivors and to optimize cost and cost-effectiveness of treatment are greatly needed. We wanted to investigate whether blood eosinophilia is a predictive biomarker for patients with solid tumors receiving vaccinations with DCs loaded with autologous tumor-RNA. Methods: In total, 67 patients with metastatic solid tumors, who we treated with autologous monocyte-derived DCs transfected with total tumor mRNA, were serially analyzed for eosinophil counts and survival over the course of up to 14 years. Eosinophilic counts were performed on peripheral blood smears. Results: Up to 87% of the patients treated with DC-based immunotherapy experienced at least once an eosinophilia of ≥ 5% after initiation of therapy; 61 % reached levels of ≥ 10% eosinophils, and 13% of patients showed eosinophil counts of 20% or above. While prevaccination eosinophil levels were not associated with survival, patients with blood eosinophilia at any point after initiation of DC-based immunotherapy showed a trend towards longer survival. There was a statistically significant difference for the patients with eosinophil counts of 20% or more (p = 0.03). In those patients, survival was prolonged to a median of 58 months (range 2-111 months), compared to a median of 20 months (range 0-119 months) in patients with lower eosinophil counts. In 12% of the patients, an immediate increase in eosinophil count of at least 10 percentage points could be detected after the first vaccine, which also appeared to correlate with survival (65 vs. 24 months; p = 0.06). Conclusion: Blood eosinophilia appears to be an early, on-therapy biomarker in patients with solid tumors undergoing vaccination with RNA-transfected DC, specifically autologous tumor mRNA-transfected DC vaccines, and it correlates with long-term patient outcome. Eosinophilia should be systematically investigated in future trials.
CRIS-Team Scopus Importer:2020-03-17
Keywords: Biomarkers; Dendritic cell vaccines; Eosinophils

Bone microstructure and volumetric bone mineral density in patients with hyperuricemia with and without psoriasis - Simon, David; Haschka, J.; Muschitz, C.; Kocijan, A.; Baierl, A.; Kleyer, Arnd; Schett, Georg; Kapiotis, S.; Resch, H.; Sticherling, Michael; Rech, Jürgen; Kocijan, R. (Osteoporosis international, 2020)
Summary: We analyzed volumetric bone mineral density (vBMD) and bone microstructure using HR-pQCT in subjects with normouricemia (NU) and subjects with hyperuricemia (HU) with and without psoriasis (PSO). HU was associated with higher cortical vBMD and thickness. Differences in average and trabecular vBMD were found between patients with PSO + HU and NU. Introduction: Hyperuricemia (HU) and gout are co-conditions of psoriasis and psoriatic arthritis. Current data suggest a positive association between HU and areal bone mineral density (BMD) and a negative influence of psoriasis on local bone, even in the absence of arthritis. However, the influence of the combination of HU and psoriasis on bone is still unclear. The aim of this study was to assess the impact of HU with and without psoriasis on bone microstructure and volumetric BMD (vBMD). Methods: Healthy individuals with uric acid levels within the normal range (NU), with hyperuricemia (HU), patients with hyperuricemia and psoriasis (PSO + HU), and patients with uric acid within the normal range and psoriasis (PSO + NU) were included in our study. Psoriasis patients had no current or past symptoms of arthritis. Average, trabecular, and cortical vBMD (mgHA/cm3); trabecular number (Tb.N, 1/mm) and thickness (Tb.Th, mm); inhomogeneity of the network (1/N.SD, mm); and cortical thickness (Ct.Th., mm) were carried out at the ultradistal radius using high-resolution peripheral quantitative computed tomography. In addition, bone turnover markers such as DKK-1, sclerostin, and P1NP were analyzed. Results: In total, 130 individuals were included (44 NU participants (34% female), 50 HU (24%), 16 PSO + HU (6%), 20 PSO + NU (60%)). Subjects were aged: NU 54.5 (42.8, 62.1), HU 57.5 (18.6, 65.1), PSO + HU 52.0 (42.3, 57.8), and PSO + NU 42.5 (34.8, 56.8), respectively. After adjusting for age, sex, BMI, and diabetes, patients in the HU group revealed significantly higher values of cortical vBMD (p < 0.001) as well as cortical thickness (p = 0.04) compared to the NU group. PSO + NU showed no differences to NU, but PSO + HU demonstrated both lower average (p = 0.03) and trabecular vBMD (p = 0.02). P1NP was associated with average, cortical, and trabecular vBMD as well as cortical thickness while sclerostin levels were related to trabecular vBMD. Conclusion: Hyperuricemia in otherwise healthy subjects was associated with a better cortical vBMD and higher cortical thickness. However, patients with both psoriasis and hyperuricemia revealed a lower vBMD.
CRIS-Team Scopus Importer:2020-01-21
Keywords: Bone Mineral Density; HR-pQCT; Hyperuricemia; Psoriasis

Bone Microstructure in Patients with Cutaneous Psoriasis and No History of Psoriatic Arthritis Shows Bone Anabolic Changes at a Greater Extent Than in Healthy Controls - Simon, David; Faustini, Francesca; Englbrecht, Matthias; Kleyer, Arnd; Kocijan, Roland; Haschka, Judith; Finzel, Stephanie; Kraus, Sebastian; Hueber, Axel; Sticherling, Michael; Schett, Georg; Rech, Jürgen (2014)
EVALuna2:13229

BRAF and MEK inhibitors affect dendritic cell maturation and T cell stimulation - Hoyer, Stefanie; Eberlein, V.; Schuler, Gerold; Berking, Carola; Heinzerling, Lucie; Schaft, Niels; Dörrie, Jan (EXPERIMENTAL DERMATOLOGY, 2021)
CRIS-Team WoS Importer:2021-05-14

BRAF and MEK Inhibitors Affect Dendritic-Cell Maturation and T-Cell Stimulation - Hoyer, Stefanie; Eberlein, Valentina; Schuler, Gerold; Berking, Carola; Heinzerling, Lucie; Schaft, Niels; Dörrie, Jan (International Journal of Molecular Sciences, 2021)
BRAF and MEK inhibitor (BRAFi/MEKi) combinations are currently the standard treatment for patients with BRAFV600 mutant metastatic melanoma. Since the RAS/RAF/MEK/ERK-pathway is crucial for the function of different immune cells, we postulated an effect on their function and thus interference with anti-tumor immunity. Therefore, we examined the influence of BRAFi/MEKi, either as single agent or in combination, on the maturation of monocyte-derived dendritic cells (moDCs) and their interaction with T cells. DCs matured in the presence of vemurafenib or vemurafenib/cobimetinib altered their cytokine secretion and surface marker expression profile. Upon the antigen-specific stimulation of CD8+ and CD4+ T cells with these DCs or with T2.A1 cells in the presence of BRAFi/MEKi, we detected a lower expression of activation markers on and a lower cytokine secretion by these T cells. However, treatment with any of the inhibitors alone or in combination did not change the avidity of CD8+ T cells in peptide titration assays with T2.A1 cells. T-helper cell/DC interaction is a bi-directional process that normally results in DC activation. Vemurafenib and vemurafenib/cobimetinib completely abolished the helper T-cell-mediated upregulation of CD70, CD80, and CD86 but not CD25 on the DCs. The combination of dabrafenib/trametinib affected DC maturation and activation as well as T-cell activation less than combined vemurafenib/cobimetinib did. Hence, for a potential combination with immunotherapy, our data indicate the superiority of dabrafenib/trametinib treatment.
Keywords: vemurafenib; dabrafenib; cobimetinib; trametinib; BRAF inhibitor; MEK inhibitor; DCs; T cells; immunotherapy; melanoma

BRAF and MEK inhibitors change human immune cell phenotype and function; possible consequences for combination therapy - Hoyer, S.; Eberlein, V.; Babalija, L.; Gerer, K.; Walter, L.; Schuler, Gerold; Schaft, Niels; Heinzerling, Lucie; Dörrie, Jan (2018)
EVALuna2:34394

BRAF and MEK inhibitors influence human immune cell phenotype and function - Hoyer, S.; Eberlein, V.; Babalija, L.; Gerer, K. F.; Walter, L.; Schuler, Gerold; Schaft, Niels; Heinzerling, Lucie; Dörrie, Jan (2017)
EVALuna2:34310

BRAF and MEK Inhibitors Influence the Function of Reprogrammed T Cells: Consequences for Adoptive T-Cell Therapy - Dörrie, Jan; Babalija, Lek; Hoyer, Stefanie; Gerer, Kerstin F.; Schuler, Gerold; Heinzerling, Lucie; Schaft, Niels (International Journal of Molecular Sciences, 2018)
BRAF and MEK inhibitors (BRAFi/MEKi), the standard treatment for patients with BRAFV600 mutated melanoma, are currently explored in combination with various immunotherapies, notably checkpoint inhibitors and adoptive transfer of receptor-transfected T cells. Since two BRAFi/MEKi combinations with similar efficacy are approved, potential differences in their effects on immune cells would enable a rational choice for triple therapies. Therefore, we characterized the influence of the clinically approved BRAFi/MEKi combinations dabrafenib (Dabra) and trametinib (Tram) vs. vemurafenib (Vem) and cobimetinib (Cobi) on the activation and functionality of chimeric antigen receptor (CAR)-transfected T cells. We co-cultured CAR-transfected CD8⁺ T cells and target cells with clinically relevant concentrations of the inhibitors and determined the antigen-induced cytokine secretion. All BRAFi/MEKi reduced this release as single agents, with Dabra having the mildest inhibitory effect, and Dabra + Tram having a clearly milder inhibitory effect than Vem + Cobi. A similar picture was observed for the upregulation of the activation markers CD25 and CD69 on CAR-transfected T cells after antigen-specific stimulation. Most importantly, the cytolytic capacity of the CAR-T cells was significantly inhibited by Cobi and Vem + Cobi, whereas the other kinase inhibitors showed no effect. Therefore, the combination Dabra + Tram would be more suitable for combining with T-cell-based immunotherapy than Vem + Cobi.
EVALuna2:34407

BRAF Inhibitors and Radiation Do Not Act Synergistically to Inhibit WT and V600E BRAF Human Melanoma - Walter, Lisa; Heinzerling, Lucie (Anticancer Research, 2018)
BACKGROUND/AIM: Recent evidence suggests that melanoma patients treated with BRAF inhibitors experience radiosensitization with an increased frequency of side-effects. This could also imply increased effectiveness when treating melanoma. MATERIALS AND METHODS: To test whether the BRAF inhibitors dabrafenib and vemurafenib together with ionizing radiation more effectively inhibit melanoma cells, primary human melanoma tumor cell lines expressing wild-type (WT) or mutant V600E BRAF were analyzed by cell survival, cell death, and cell-cycle testing. RESULTS: All melanoma cell lines examined were radioresistant in these assays. BRAF inhibitor treatment alone suppressed cell survival more effectively than radiation in all the mutant V600E BRAF cell lines, and vemurafenib, but not dabrafenib, also inhibited cell survival in the WT BRAF cell lines at clinically relevant concentrations. However, when cells were treated with BRAF inhibitor followed by radiation, there was no increased effect on the suppression of cell survival. Vemurafenib induced more necrosis than radiation in most melanoma cell lines, irrespective of BRAF status, but this effect was not additive with the combination treatment. BRAF inhibitors and radiation had variable, but independent effects on the induction of cell-cycle arrest. CONCLUSION: These results suggest that BRAF inhibitors and ionizing radiation do not act synergistically to inhibit the growth of primary human melanoma cells.
EVALuna2:34396
Keywords: Radiotherapy; V600E mutant BRAF; Dabrafenib; Melanoma; Vemurafenib; BRAF inhibitor; BRAF

Breaking Entry-and Species Barriers: LentiBOOST® Plus Polybrene Enhances Transduction Efficacy of Dendritic Cells and Monocytes by Adenovirus 5 - Strack, Astrid; Deinzer, Anja; Thirion, Christian; Schrödel, Silke; Dörrie, Jan; Sauerer, Tatjana; Steinkasserer, Alexander; Knippertz, Ilka (Viruses, 2022)
Due to their ability to trigger strong immune responses, adenoviruses (HAdVs) in general and the serotype5 (HAdV-5) in particular are amongst the most popular viral vectors in research and clinical application. However, efficient transduction using HAdV-5 is predominantly achieved in coxsackie and adenovirus receptor (CAR)-positive cells. In the present study, we used the transduc-tion enhancer LentiBOOST® comprising the polycationic Polybrene to overcome these limitations. Using LentiBOOST® /Polybrene, we yielded transduction rates higher than 50% in murine bone marrow-derived dendritic cells (BMDCs), while maintaining their cytokine expression profile and their capability to induce T-cell proliferation. In human dendritic cells (DCs), we increased the transduction rate from 22% in immature (i)DCs or 43% in mature (m)DCs to more than 80%, without inducing cytotoxicity. While expression of specific maturation markers was slightly upregulated using LentiBOOST® /Polybrene on iDCs, no effect on mDC phenotype or function was observed. Moreover, we achieved efficient HAdV5 transduction also in human monocytes and were able to subsequently differentiate them into proper iDCs and functional mDCs. In summary, we introduce LentiBOOST® comprising Polybrene as a highly potent adenoviral transduction agent for new in-vitro applications in a set of different immune cells in both mice and humans.
CRIS-Team Scopus Importer:2022-01-28
Keywords: Adenoviral transduction; Adenovirus; Dendritic cells; LentiBOOST®; Monocytes; T cells

Brn3a expression is epigenetically controlled by HDAC2 in melanocytes and melanoma - Heppt, Markus; Wessely, A.; Hornig, E.; Kammerbauer, C.; Graf, S.; Besch, R.; French, L. E.; Kuphal, Silke; Kappelmann-Fenzl, Melanie; Boßerhoff, Anja Katrin; Berking, Carola (EXPERIMENTAL DERMATOLOGY, 2021)
CRIS-Team WoS Importer:2021-05-14

Can checkpoint inhibitor therapy improve response to chemotherapy? - Boßerhoff, Anja Katrin; Schuler, Gerold; Heinzerling, Lucie; Schilling, Bastian; Haferrkamp, Sebastian; Kirchberger, MC (2017)
EVALuna2:4767

Can checkpoint inhibitor therapy improve response to chemotherapy? - Kirchberger, Michael Constantin; Schilling, Bastian; Haferkamp, Sebastian; Boßerhoff, Anja Katrin; Schuler, Gerold; Heinzerling, Lucie (Journal of Cancer Research and Clinical Oncology, 2018)
EVALuna2:34410

Can Gamification Contribute to Computer Modeling-Driven Biomedical Research? - Vera, Julio; Santos Rosales, Guido (Frontiers in Physiology, 2018)
EVALuna2:34787

CARs: Beyond T Cells and T Cell-Derived Signaling Domains. - Sievers, Nico M.; Dörrie, Jan; Schaft, Niels (International Journal of Molecular Sciences, 2020)
When optimizing chimeric antigen receptor (CAR) therapy in terms of efficacy, safety, and broadening its application to new malignancies, there are two main clusters of topics to be addressed: the CAR design and the choice of transfected cells. The former focuses on the CAR construct itself. The utilized transmembrane and intracellular domains determine the signaling pathways induced by antigen binding and thereby the cell-specific effector functions triggered. The main part of this review summarizes our understanding of common signaling domains employed in CARs, their interactions among another, and their effects on different cell types. It will, moreover, highlight several less common extracellular and intracellular domains that might permit unique new opportunities. Different antibody-based extracellular antigen-binding domains have been pursued and optimized to strike a balance between specificity, affinity, and toxicity, but these have been reviewed elsewhere. The second cluster of topics is about the cellular vessels expressing the CAR. It is essential to understand the specific attributes of each cell type influencing anti-tumor efficacy, persistence, and safety, and how CAR cells crosstalk with each other and bystander cells. The first part of this review focuses on the progress achieved in adopting different leukocytes for CAR therapy.
CRIS-Team Scopus Importer:2020-05-29
Keywords: 2B4; Chimeric antigen receptor (CAR); DAP10; Intracellular signaling domain; Myeloid cells; NK cell; NKG2D; NKT cell; T cell; γ/δ T cells

CAR/TCR-transfected gamma/delta T cells for immunotherapy of melanoma - Harrer, D. C.; Simon, B.; Fujii, S.; Shimizu, K.; Uslu, U.; Schoch, L.; Schuler, Gerold; Gerer, K. F.; Hoyer, S.; Dörrie, Jan; Schaft, Niels (2017)
EVALuna2:34323

Case report: Bullous pemphigoid in HIV-1-positive patients: interplay or coincidence? A case series and review of the literature - Foerster, Yannick; Sollfrank, Lukas; Rechtien, Laura; Harrer, Thomas; Berking, Carola; Sticherling, Michael (Frontiers in Immunology, 2023)
Bullous pemphigoid (BP) is an autoimmune inflammatory skin disease, mostly affecting the elderly population. Therefore, patients often have multiple comorbidities, but there is inconsistent data regarding the relationship between HIV-1 infection and BP, which has been rarely reported in combination. Herein, we describe three patients who presented with BP and concomitant HIV-1 infection that was well controlled with modern combined antiretroviral therapy. All patients received topical and oral corticosteroids. Depending on the individual severity, further add-on therapeutics, such as azathioprine, dapsone, doxycycline and the interleukin 4/13 antibody dupilumab, were added to the therapy regimen. All patients recovered from pruritic skin lesions and blistering. The cases are further discussed in the context of the current study landscape. In conclusion, HIV-1 infection shifts the cytokine profile from T-helper type 1 (TH1) towards T-helper type 2 (TH2), resulting in the excessive secretion of distinct cytokines, such as interleukin 4 (IL-4) and interleukin 10 (IL-10). With IL-4 being a main driver in the pathogenesis of BP, HIV-1-positive patients may benefit greatly from targeting IL-4 with monoclonal antibodies.
CRIS-Team Scopus Importer:2023-07-07
Keywords: aids; bullous pemphigoid; COVID-19; dupilumab; HIV-1; immune reconstitution inflammatory syndrome; iris

Case report: Patient specific combination of surgery and immunotherapy in advanced squamous cell carcinoma of the head and neck – a case series and review of literature - Olmos, Manuel; Lutz, Rainer; Büntemeyer, Tjark-Ole; Glajzer, Jacek; Nobis, Christopher-Philipp; Ries, Jutta; Möst, Tobias; Eckstein, Markus; Hecht, Markus; Gostian, Antoniu-Oreste; Erdmann, Michael; Foerster, Yannick; et al. (Frontiers in Immunology, 2022)
Background: Prognosis of patients with recurrent or metastatic head and neck cancer is generally poor. Adjuvant immunotherapy (IT) featuring immune checkpoint inhibition (ICI) is standard of care in advanced stage head and neck squamous cell carcinoma (HNSCC) and cutaneous squamous cell carcinoma (CSCC). ICI response rates in CSCC are described as higher than in HNSCC. IT is constantly shifting into earlier disease stages which confronts the surgeon with immunotherapeutically pre-treated patients. It is therefore becoming increasingly difficult to assess which patients with symptomatic tumor disease and a lack of curative surgical option might benefit from salvage surgery. Case presentations: The following 6 cases describe therapeutic decision-making regarding ICI and (salvage) surgery in patients with advanced stage HNSCC or CSCC. Cases A and B focus on neoadjuvant ICI followed by salvage surgery. In Cases C and D salvage surgery was performed after short-term stabilization with partial response to ICI. The last two cases (Cases E and F) address the surgical approach after failure of ICI. All cases are discussed in the context of the current study landscape and with focus on individual decision-making. For better understanding, a timetable of the clinical course is given for each case. Conclusions: ICI is rapidly expanding its frontiers into the neoadjuvant setting, frequently confronting the surgeon with heavily pretreated patients. Salvage surgery is a viable therapeutic concept despite the rise of systemic treatment options. Decision-making on surgical intervention in case of a salvage surgery remains an individual choice. For neoadjuvant ICI monitoring regarding pathological tumor response or tumor necrosis rate, we suggest correlation between the initial biopsy and the definite tumor resectate in order to increase its significance as a surrogate marker. Scheduling of neoadjuvant ICI should be further investigated, as recent studies indicate better outcomes with shorter time frames.
CRIS-Team Scopus Importer:2022-11-25
Keywords: anti-PD 1; checkpoint inhibition; CSCC; HNSCC; immunotherapy; neoadjuvant; OSCC; salvage surgery

Case Report: The many faces of bullous pemphigoid - Rechtien, Laura; Sollfrank, Lukas; Foerster, Yannick; Berking, Carola; Sticherling, Michael (Frontiers in Immunology, 2023)
The pemphigoid group comprises a number of bullous skin diseases with autoantibodies against different constituents of the basement membrane zone that result in subepidermal detachment and clinically characteristic tense blisters, erosions, urticarial erythema, and itching. Apart from the most frequent type of bullous pemphigoid with antibodies against BP180, which is found predominantly in elderly patients, the disease may present at other ages and different pathogenic conditions. Here, four cases are presented of young age (3 months and 25, 34, and 46 years) and in association with vaccination, pregnancy, or metastatic cancer. Though anti-BP180 was found in all cases, a different pathogenic background may be found in any of them, resulting in characteristic clinical manifestation, yet demanding specifically adapted therapeutic approaches.
CRIS-Team Scopus Importer:2023-11-03
Keywords: bullous autoimmune disease; bullous pemphigoid; COVID-19 vaccination; juvenile pemphigoid; pemphigoid gestationis

Cash is king: the balance of costs and effectiveness of treatments for actinic keratosis - Steeb, Theresa; Heppt, Franz; Berking, Carola (British Journal of Dermatology, 2020)
CRIS-Team Scopus Importer:2020-04-17

Cathepsin S provokes interleukin-6 (IL-6) trans-signaling through cleavage of the IL-6 receptor in vitro - Flynn, Charlotte M.; Garbers, Yvonne; Düsterhöft, Stefan; Wichert, Rielana; Lokau, Juliane; Lehmann, Christian; Dudziak, Diana; Schröder, Bernd; Becker-Pauly, Christoph; Rose-John, Stefan; Aparicio-Siegmund, Samadhi; Garbers, Christoph (Scientific Reports, 2020)
The cytokine interleukin-6 (IL-6) fulfills its pleiotropic functions via different modes of signaling. Regenerative and anti-inflammatory activities are mediated via classic signaling, in which IL-6 binds to the membrane-bound IL-6 receptor (IL-6R). For IL-6 trans-signaling, which accounts for the pro-inflammatory properties of the cytokine, IL-6 activates its target cells via soluble forms of the IL-6R (sIL-6R). We have previously shown that the majority of sIL-6R in human serum originates from proteolytic cleavage and mapped the cleavage site of the IL-6R. The cleavage occurs between Pro-355 and Val-356, which is the same cleavage site that the metalloprotease ADAM17 uses in vitro. However, sIL-6R serum levels are unchanged in hypomorphic ADAM17ex/ex mice, making the involvement of ADAM17 questionable. In order to identify other proteases that could be relevant for sIL-6R generation in vivo, we perform a screening approach based on the known cleavage site. We identify several candidate proteases and characterize the cysteine protease cathepsin S (CTSS) in detail. We show that CTSS is able to cleave the IL-6R in vitro and that the released sIL-6R is biologically active and can induce IL-6 trans-signaling. However, CTSS does not use the Pro-355/Val-356 cleavage site, and sIL-6R serum levels are not altered in Ctss−/− mice. In conclusion, we identify a novel protease of the IL-6R that can induce IL-6 trans-signaling, but does not contribute to steady-state sIL-6R serum levels.
CRIS-Team Scopus Importer:2020-12-25

CD83 acts as immediate early response gene in activated macrophages and exhibits specific intracellular trafficking properties - Langguth, Pia; Peckert, Katrin; Beck, Philipp; Kuhnt, Christine; Draßner, Christina; Deinzer, Andrea; Steinkasserer, Alexander; Wild, Andreas (Biochemical and Biophysical Research Communications, 2023)
Macrophages (MΦ) are remarkably plastic cells, which assume phenotypes in every shade between a pro-inflammatory classical activation, and anti-inflammatory or resolving activation. Therefore, elucidation of mechanisms involved in shaping MΦ plasticity and function is key to understand their role during immunological balance. The immune-modulating CD83 molecule is expressed on activated immune cells and various tissue resident MΦ, rendering it an interesting candidate for affecting MΦ biology. However, in-depth analyses of the precise kinetics and trafficking of CD83 within pro-inflammatory, LPS activated bone-marrow-derived MΦ have not been performed. In this study, we show that activation with LPS leads to a very fast and strong, but transient increase of CD83 expression on these cells. Its expression peaks within 2 h of stimulation and is thereby faster than the early activation antigen CD69. To trace the CD83 trafficking through MΦs, we employed multiple inhibitors, thereby revealing a de novo synthesis and transport of the protein to the cell surface followed by lysosomal degradation, all within 6 h. Moreover, we found a similar expression kinetic and trafficking in human monocyte derived MΦ. This places CD83 at a very early point of MΦ activation suggesting an important role in decisions regarding the subsequent cellular fate.
CRIS-Team Scopus Importer:2023-02-10
Keywords: CD83; expression; intracellular trafficking; lipopolysaccharide; macrophages

CD83 and GRASP55 interact in human dendritic cells - Stein, Marcello F.; Blume, Katja; Heilingloh, Christiane; Kummer, Mirko; Biesinger, Brigitte; Sticht, Heinrich; Steinkasserer, Alexander (Biochemical and Biophysical Research Communications, 2015)
CD83 is one of the best known surface markers for mature human dendritic cells (DCs). The full-length 45 kDa type-I membrane-bound form (mbCD83) is strongly glycosylated upon DCs maturation. As co-stimulatory properties of CD83 are attributed to mbCD83 surface expression is required for efficient T-cell stimulation by mature DCs. By yeast two-hybrid screening, we were able to identify GRASP55 as interaction partner of CD83. DCs maturation induces endogenous CD83 protein expression with simultaneous regulation of CD83 glycosylation, interaction and co-localization with GRASP55 and CD83 surface exposure. GRASP55 is especially known for its role in maintaining Golgi architecture, but also plays a role in Golgi transport of specific cargo proteins bearing a C-terminal valine residue. Here we additionally demonstrate that binding of CD83 and GRASP55 rely on the C-terminal TELV-motif of CD83. Mutation of this TELV-motif not only disrupted binding to GRASP55, but also altered the glycosylation pattern of CD83 and reduced its membrane expression. Here we show for the first time that GRASP55 interacts with CD83 shortly after induction of DC maturation and that this interaction plays a role in CD83 glycosylation as well as in surface expression of CD83 on DCs.
EVALuna2:8259

CD83 expressed by macrophages is an important immune checkpoint molecule for the resolution of inflammation - Peckert-Maier, Katrin; Langguth, Pia; Strack, Astrid; Stich, Lena; Mühl-Zürbes, Petra; Kuhnt, Christine; Drassner, Christina; Zinser, Elisabeth; Wrage, Marius; Mattner, Jochen; Steinkasserer, Alexander; Royzman, Dmytro; et al. (Frontiers in Immunology, 2023)
Excessive macrophage (M phi) activation results in chronic inflammatory responses or autoimmune diseases. Therefore, identification of novel immune checkpoints on M phi, which contribute to resolution of inflammation, is crucial for the development of new therapeutic agents. Herein, we identify CD83 as a marker for IL-4 stimulated pro-resolving alternatively activated M phi (AAM). Using a conditional KO mouse (cKO), we show that CD83 is important for the phenotype and function of pro-resolving M phi. CD83-deletion in IL-4 stimulated M phi results in decreased levels of inhibitory receptors, such as CD200R and MSR-1, which correlates with a reduced phagocytic capacity. In addition, CD83-deficient M phi upon IL-4 stimulation, show an altered STAT-6 phosphorylation pattern, which is characterized by reduced pSTAT-6 levels and expression of the target gene Gata3. Concomitantly, functional studies in IL-4 stimulated CD83 KO M phi reveal an increased production of pro-inflammatory mediators, such as TNF-alpha, IL-6, CXCL1 and G-CSF. Furthermore, we show that CD83-deficient M phi have enhanced capacities to stimulate the proliferation of allo-reactive T cells, which was accompanied by reduced frequencies of Tregs. In addition, we show that CD83 expressed by M phi is important to limit the inflammatory phase using a full-thickness excision wound healing model, since inflammatory transcripts (e.g. Cxcl1, Il6) were increased, whilst resolving transcripts (e.g. Ym1, Cd200r, Msr-1) were decreased in wounds at day 3 after wound infliction, which reflects the CD83 resolving function on M phi also in vivo. Consequently, this enhanced inflammatory milieu led to an altered tissue reconstitution after wound infliction. Thus, our data provide evidence that CD83 acts as a gatekeeper for the phenotype and function of pro-resolving M phi.
CRIS-Team WoS Importer:2023-03-17

CD83 expression is essential for Treg cell differentiation and stability - Döbbeler, Marina; Koenig, Christina; Krzyzak, Lena; Seitz, Christine; Wild, Andreas; Ulas, Thomas; Bassler, Kevin; Kopelyanskiy, Dmitry; Butterhof, Alina; Kuhnt, Christine; Kreiser, Simon; Stich, Lena; et al. (JCI Insight, 2018)
Foxp3-positive regulatory T cells (Tregs) are crucial for the maintenance of immune homeostasis and keep immune responses in check. Upon activation, Tregs are transferred into an effector state expressing transcripts essential for their suppressive activity, migration, and survival. However, it is not completely understood how different intrinsic and environmental factors control differentiation. Here, we present for the first time to our knowledge data suggesting that Treg-intrinsic expression of CD83 is essential for Treg differentiation upon activation. Interestingly, mice with Treg-intrinsic CD83 deficiency are characterized by a proinflammatory phenotype. Furthermore, the loss of CD83 expression by Tregs leads to the downregulation of Treg-specific differentiation markers and the induction of an inflammatory profile. In addition, Treg-specific conditional knockout mice showed aggravated autoimmunity and an impaired resolution of inflammation. Altogether, our results show that CD83 expression in Tregs is an essential factor for the development and function of effector Tregs upon activation. Since Tregs play a crucial role in the maintenance of immune tolerance and thus prevention of autoimmune disorders, our findings are also clinically relevant.
EVALuna2:36212

CD83 Modulates B Cell Activation and Germinal Center Responses - Krzyzak, Lena; Seitz, Christine; Urbat, Anne; Hutzler, Stefan; Ostalecki, Christian; Glaesner, Joachim; Hiergeist, Andreas; Gessner, Andre; Winkler, Thomas; Steinkasserer, Alexander; Nitschke, Lars (Journal of Immunology, 2016)
CD83 is a maturation marker for dendritic cells. In the B cell lineage, CD83 is expressed especially on activated B cells and on light zone B cells during the germinal center (GC) reaction. The function of CD83 during GC responses is unclear. CD83(-/-) mice have a strong reduction of CD4(+) T cells, which makes it difficult to analyze a functional role of CD83 on B cells during GC responses. Therefore, in the present study we generated a B cell-specific CD83 conditional knockout (CD83 B-cKO) model. CD83 B-cKO B cells show defective upregulation of MHC class II and CD86 expression and impaired proliferation after different stimuli. Analyses of GC responses after immunization with various Ags revealed a characteristic shift in dark zone and light zone B cell numbers, with an increase of B cells in the dark zone of CD83 B-cKO mice. This effect was not accompanied by alterations in the level of IgG immune responses or by major differences in affinity maturation. However, an enhanced IgE response was observed in CD83 B-cKO mice. Additionally, we observed a strong competitive disadvantage of CD83-cKO B cells in GC responses in mixed bone marrow chimeras. Furthermore, infection of mice with Borrelia burgdorferi revealed a defect in bacterial clearance of CD83 B-cKO mice with a shift toward a Th2 response, indicated by a strong increase in IgE titers. Taken together, our results show that CD83 is important for B cell activation and modulates GC composition and IgE Ab responses in vivo.

CD83 orchestrates immunity toward self and non-self in dendritic cells - Wild, Andreas; Krzyzak, Lena; Peckert, Katrin; Stich, Lena; Kuhnt, Christine; Butterhof, Alina; Seitz, Christine; Mattner, Jochen; Grner, Niklas; Gänsbauer, Maximilian; Purtak, Martin; Soulat, Didier; et al. (JCI Insight, 2019)
Dendritic cells (DCs) are crucial to balance protective immunity and autoimmune inflammatory processes. Expression of CD83 is a well-established marker for mature DCs, although its physiological role is still not completely understood. Using a DC-specific CD83-conditional KO (CD83(Delta DC)) mouse, we provide new insights into the function of CD83 within this cell type. Interestingly, CD83-deficient DCs produced drastically increased IL-2 levels and displayed higher expression of the costimulatory molecules CD25 and OX40L, which causes superior induction of antigen-specific T cell responses and compromises Treg suppressive functions. This also directly translates into accelerated immune responses in vivo. Upon Salmonella typhimurium and Listeria monocytogenes infection, CD83(Delta DC) mice cleared both pathogens more efficiently, and CD83-deficient DCs expressed increased IL-12 levels after bacterial encounter. Using the experimental autoimmune encephalomyelitis model, autoimmune inflammation was dramatically aggravated in CD83(Delta DC) mice while resolution of inflammation was strongly reduced. This phenotype was associated with increased cell influx into the CNS accompanied by elevated Th17 cell numbers. Concomitantly, CD83(Delta DC) mice had reduced Treg numbers in peripheral lymphoid organs. In summary, we show that CD83 ablation on DCs results in enhanced immune responses by dysregulating tolerance mechanisms and thereby impairing resolution of inflammation, which also demonstrates high clinical relevance.
CRIS-Team WoS Importer:2019-11-01

CD8+ T-cell priming and boosting: More antigen-presenting DC, or more antigen per DC? - Schaft, Niels; Wellner, Verena; Wohn, Christian; Schuler, Gerold; Dörrie, Jan (Cancer Immunology, Immunotherapy, 2013)
RNA transfection is a standard method to load dendritic cells (DC) with antigen for therapeutic cancer vaccination. While electroporation yields high transfection efficiency and satisfying expression levels, lipofection results in only few cells expressing high amounts of antigen. We compared antigen loading of human monocyte-derived DC by MelanA RNA electroporation and lipofection. No differences in phenotype or migrational capacity were detected, but lipofected DC induced stronger cytokine secretion by antigen-specific T cells and were superior in priming and boosting of MelanA-specific CD8+ T cells. Interestingly, T cells stimulated with the differently transfected DC did not differ in their functional avidity. To determine whether the amount of antigen per cell is indeed responsible for the superiority of the lipofected DC, we increased the amount of MelanA RNA fivefold and mixed those DC with mock-electroporated ones to mimic the antigen distribution of lipofected cells. This significantly improved the stimulatory capacity, indicating that indeed the amount of antigen per cell seems to be the responsible feature for the observed superiority of lipofected DCs. These data suggest that a few DC that express high amounts of antigen are more immunogenic than many DC expressing lower amounts, although this needs to be tested in a two-armed immunogenicity trial. © 2013 Springer-Verlag Berlin Heidelberg.
CRIS-Team Scopus Importer:2021-10-01
Keywords: Antigen presentation; Dendritic cells; Electroporation; Lipofection; T cells

Cdc42-dependent actin dynamics controls maturation and secretory activity of dendritic cells - Schulz, Anna M.; Stutte, Susanne; Hogl, Sebastian; Luckashenak, Nancy; Dudziak, Diana; Leroy, Celine; Forne, Ignasi; Imhof, Axel; Mueller, Stephan A.; Brakebusch, Cord H.; Lichtenthaler, Stefan F.; Brocker, Thomas (The Journal of Cell Biology, 2015)
Cell division cycle 42 (Cdc42) is a member of the Rho guanosine triphosphatase family and has pivotal functions in actin organization, cell migration, and proliferation. To further study the molecular mechanisms of dendritic cell (DC) regulation by Cdc42, we used Cdc42-deficient DCs. Cdc42 deficiency renders DCs phenotypically mature as they up-regulate the co-stimulatory molecule CD86 from intracellular storages to the cell surface. Cdc42 knockout DCs also accumulate high amounts of invariant chain-major histocompatibility complex (MHC) class II complexes at the cell surface, which cannot efficiently present peptide antigens (Ag's) for priming of Ag-specific CD4 T cells. Proteome analyses showed a significant reduction in lysosomal MHC class II-processing proteins, such as cathepsins, which are lost from DCs by enhanced secretion. As these effects on DCs can be mimicked by chemical actin disruption, our results propose that Cdc42 control of actin dynamics keeps DCs in an immature state, and cessation of Cdc42 activity during DC maturation facilitates secretion as well as rapid up-regulation of intracellular molecules to the cell surface.
EVALuna2:19559

Cellular and humoral immune responses to SARS-CoV-2 vaccination in patients after CD19.CAR T-cell therapy - Reimann, Hannah; Kremer, Anita; Blumenberg, Viktoria; Schmidt, Katja; Aigner, Michael; Jacobs, Benedikt; Eisenhauer, Nina; Kämpf, Alina; Rösler, Wolf; Kharboutli, Soraya; Mougiakakos, Dimitrios; Lang, Vanessa; et al. (Blood Advances, 2023)
EVALuna2:512817

Characterization and Expansion of Autologous GMP-ready Regulatory T Cells for TREG-based Cell Therapy in Patients with Ulcerative Colitis - Voskens, Caroline J.; Fischer, Anika; Roessner, Susanne; Lorenz, Carmen; Hirschmann, Simon; Atreya, Raja; Neufert, Clemens; Atreya, Imke; Neurath, Markus; Schuler, Gerold (Inflammatory Bowel Diseases, 2017)
BACKGROUND: A local imbalance between regulatory (Treg) and effector T cells is believed to play a major role in gut-specific inflammation, including ulcerative colitis (UC). Restoration of this balance through an adoptive Treg transfer is an attractive new treatment approach in patients who are refractory to current standard therapies. It was our goal to develop a Good Manufacturing Practices (GMP)-conform protocol for expansion of UC Treg cells as a rational backbone for future studies on Treg therapy in UC. METHODS: CD25 blood T cells derived from patients with UC were ex vivo expanded in the presence of IL-2, rapamycin, and anti-CD3/anti-CD28 expander beads using a GMP-conform protocol. Cells were subsequently assessed for stability and function. RESULTS: Patient-derived ex vivo rapamycin-expanded GMP-ready CD25 cells were polyclonal, hypomethylated at intron 1 of the FoxP3 locus, and suppressive in carboxyfluorescein succinimidyl ester-dilution assays against autologous peripheral blood-derived and allogeneic colon-derived responder cells. Function was mediated by soluble factors, including toxic granules. In addition to CD4 T cells, suppressive hypermethylated CD8 T-cell subsets were also induced during the expansion process. CONCLUSIONS: Patient-derived rapamycin-expanded CD25 cells are stable and functional, and as such, ready to serve in a phase I dose-escalation safety study in UC.
EVALuna2:33805

Characterization and Manipulation of the Crosstalk Between Dendritic and Natural Killer Cells Within the Tumor Microenvironment - Jacobs, Benedikt; Gebel, Veronika; Heger, Lukas; Greze, Victoria; Schild, Hansjorg; Dudziak, Diana; Ullrich, Evelyn (Frontiers in Immunology, 2021)
Cellular therapy has entered the daily clinical life with the approval of CAR T cell therapeutics and dendritic cell (DCs) vaccines in the US and the EU. In addition, numerous other adoptive cellular products, including natural killer (NK) cells, are currently evaluated in early phase I/ II clinical trials for the treatment of cancer patients. Despite these promising accomplishments, various challenges remain to be mastered in order to ensure sustained therapeutic success. These include the identification of strategies by which tumor cells escape the immune system or establish an immunosuppressive tumor microenvironment (TME). As part of the innate immune system, DCs and NK cells are both present within the TME of various tumor entities. While NK cells are well known for their intrinsic anti-tumor activity by their cytotoxicity capacities and the secretion of pro-inflammatory cytokines, the role of DCs within the TME is a double-edged sword as different DC subsets have been described with either tumor-promoting or -inhibiting characteristics. In this review, we will discuss recent findings on the interaction of DCs and NK cells under physiological conditions and within the TME. One focus is the crosstalk of various DC subsets with NK cells and their impact on the progression or inhibition of tumor growth. In addition, we will provide suggestions to overcome the immunosuppressive outcome of the interaction of DCs and NK cells within the TME.
CRIS-Team Scopus Importer:2021-06-11
Keywords: cellular therapies; DC-NK cell interaction; dendritic cells; NK cells; tumor microenvironment

Characterization of tanning behavior assessed via online survey: Attitudes, habits, and preventive measures with focus on sunscreen use - Schneiderbanger, Constanze K.; Schuler, Gerold; Heinzerling, Lucie; Kirchberger, Michael C. (Photodermatology Photoimmunology & Photomedicine, 2019)
Background/purpose: Incidence of melanoma is increasing globally. Exposure to ultraviolet radiation (UVR) as important risk factor for developing skin cancer can be influenced by tanning behavior. Only a few studies are available concerning sun tanning behavior and protective measures. Methods: An online survey was distributed via social media to assess tanning habits and examine associated demographic and behavioral factors. Results: In total, 403 questionnaires were distributed, and mean age of respondents was 32. Having a tanned skin, feeling warm and relaxed were the most common motivations for tanning. The use of sunscreen varied and seemed to depend on the occasion of UVR exposure, constantly applied during vacation and during tanning, less commonly applied in daily life and during work. Avoiding painful solar dermatitis was more important as motivation for the use of sunscreen than skin cancer prevention. Skin aging as reason for the use of sunscreen was especially important for females younger than 26 years. The most common applied sun protection factor was 16-49. The main reason opposing the use of sunscreen was a too laborious usage, which was significantly associated with male. Beauty was the only association related to tanned skin the majority (62%) agreed with. Conclusion: The motivation for tanning and reasons for avoiding sunscreen strongly varies. Knowledge about these factors could be used for improving campaigns with respect to target groups. Clarifying the appropriate application of sunscreen, developing convenient sunscreen formulations and providing information about UVR-induced skin aging could lead to an increased usage of sunscreen and therefore to an improved UVR protection.
CRIS-Team Scopus Importer:2019-07-30
Keywords: melanoma; sunscreen; tanning; ultraviolet radiation

Characterization of the impact of immune checkpoint inhibitors on platelet activation and aggregation - Schlüter, Julian; Cunningham, Sarah; Zimmermann, Robert; Achenbach, Susanne; Kramer, Rafaela; Erdmann, Michael; Beckmann, Matthias; Heinzerling, Lucie; Hackstein, Holger (Immunobiology, 2023)
Immune checkpoint inhibitors (ICIs) are effective oncological drugs which block cellular check-point receptors typically targeted by tumor immune evasion strategies. Despite their benefits, clinicians have reported treatment-associated thromboembolism during ICI therapy in recent years. Though several theories on this ICI-associated pathogenesis exist, the direct effects of ICIs on platelets remains unknown. We therefore investigated the potential direct and indirect effect of PD-1, PD-L1 and CTLA-4-targeting ICIs on platelet functionality in multifaceted in vitro experiments. Interestingly, we could not observe a clear effect of ICI on platelet aggregation and primary hemostasis in whole blood and platelet concentrate-based assays. Furthermore, the presence of ICIs in toll-like receptor stimulation had no significant impact on platelet surface marker expression. In a second approach, we investigated the indirect immunological impact of ICIs on platelet activation by exposing platelets to supernatants from ICI- and Staphylococcal enterotoxin B-exposed PBMCs. Whereas ICIs affected IL-2 levels in supernatants, we could not detect clear differences in the secretion of pro-thrombogenic factors and platelet responses. The obtained data suggest that the direct influence of ICIs on platelet activation or the influence of altered T cell function on platelet activation cannot be considered a major factor in the development of thrombotic events.
CRIS-Team Scopus Importer:2023-01-13
Keywords: Immune checkpoint inhibitors; Platelet activation; Platelet function tests; Platelets; Thrombosis

Checkpoint inhibitor-induced bullous pemphigoid differs from spontaneous bullous pemphigoid - Kramer, N.; Müller, G.; Zierold, S.; Röckel, Magdalena; Fröhlich, Waltraud; Schefzyk, M.; Kumbrink, J.; Hassel, J. C.; Berking, Carola; Ziemer, M.; Nashan, D.; French, L. E.; et al. (Journal of the European Academy of Dermatology and Venereology, 2024)
CRIS-Team Scopus Importer:2024-03-15

Checkpoint inhibitor-induced eosinophilic fasciitis following high eosinophilia associated with complete response - Toussaint, Frédéric; Hammon, Matthias; Erdmann, Michael; Moreira, Alvaro; Kirchberger, Michael C.; Schuler, Gerold; Schett, Georg; Heinzerling, Lucie (Rheumatology, 2019)
CRIS-Team Scopus Importer:2019-10-01

Checkpoint inhibitor–induced lichen planus differs from spontaneous lichen planus on the clinical, histological, and gene expression level - Meier-Schiesser, Barbara; Zecha, Christine; Zierold, Sarah; Kolm, Isabel; Röckel, Magdalena; Fröhlich, Waltraud; Mittag, Nora; Schmitt, Christina; Kumbrink, Joerg; Hassel, Jessica C.; Berking, Carola; Nashan, Dorothee; et al. (Journal of the American Academy of Dermatology, 2024)
Background: Although highly efficacious, immune checkpoint inhibitors induce a multitude of immune-related adverse events including lichenoid skin reactions (irLP) that are often therapy-resistant. Objectives: To compare the clinical, histological, and transcriptional features of irLP with spontaneous lichen planus (LP). Methods: Clinical and histological presentations of irLP and LP, as well as the gene expression profiles of irLP and LP lesional and healthy skin were assessed. Results: irLP differed considerably from LP with regard to the distribution pattern of skin lesions with irLP appearing mostly in an exanthematous form, whereas lesions were more localized in the LP group. Histologically, dermal lymphocyte infiltration was significantly lower in irLP compared with LP, whereas lymphocyte exocytosis and apoptotic keratinocytes were significantly higher in irLP. Gene expression analysis revealed irLP to have a more inflammatory profile with elevated IFNG levels and a possible role of phagosome signaling compared with LP. Limitations: The study is descriptive and necessitates further investigation with larger cohorts and broader analyses. Conclusion: irLP differs from spontaneous LP on the clinical, histopathological, and gene expression level. The inflammatory gene signature in irLP suggests that topical JAK inhibitors could be an effective treatment, targeting local skin inflammation without systemic immunosuppression.
CRIS-Team Scopus Importer:2024-04-05
Keywords: cutaneous side effects; exanthematous; gene expression profiles; immune-related adverse events; inflammatory signatures

Chemical peelings for the treatment of actinic keratosis: a systematic review and meta-analysis - Steeb, Theresa; Koch, Elias; Wessely, A.; Wiest, L. G.; Schmitz, L.; Berking, Carola; Heppt, Markus (Journal of the European Academy of Dermatology and Venereology, 2020)
Background: Actinic keratosis (AK) is a common precancerous lesion of the skin that may be treated with chemical peelings. Despite their long-standing usage and clinical experience, no evidence-based recommendation regarding the efficacy and safety of chemical peelings for AK exists. Objectives: To systematically review and synthesize the current knowledge on chemically exfoliative peelings as interventions for AK. Methods: We performed a systematic literature research in Medline, Embase and CENTRAL and hand-searched pertinent trial registers for eligible records until 5 August 2019. Results from individual studies were pooled using a random-effects model or described in a qualitative synthesis. The risk of bias was estimated with the tools provided by the Cochrane Collaboration (randomized and non-randomized trials) and the Evidence Project (single-arm trials). Results: Four randomized controlled trials, two non-randomized controlled trials and two single-arm studies with a total sample size of n = 170 patients were included. Trichloroacetic acid (TCA) plus Jessner’s solution showed significantly lower participant complete clearance (RR 0.36, 95% CI: 0.14–0.90, two studies, I2 = 0%, P = 0.03) and lower lesion clearance (RR 0.92, 95% CI: 0.85–0.99, one study, P = 0.03) compared to 5-fluorouracil (5-FU) 5% cream. TCA as monotherapy showed lower lesion complete clearance (RR 0.75, 95% CI: 0.69–0.82, two studies, I2 = 7%, P < 0.001) and lower mean lesion reduction per patient compared to conventional photodynamic therapy (cPDT) (MD −20.48, 95% CI: −31.55 to −9.41, two studies, I2 = 43%, P = 0.0003). Pain was more pronounced in patients treated with cPDT in comparison with TCA (MD −1.71 95% CI: −3.02 to −0.41, two studies, I2 = 55%, P = 0.01). In the single-arm studies, 5-FU plus glycolic acid showed 92% lesion clearance and phenol peeling 90.6% participant complete clearance. All studies showed a high risk for bias. Conclusions: Future high-quality studies and a standardization of peeling protocols are warranted to determine the value of chemical peelings in the treatment of AK.
CRIS-Team Scopus Importer:2020-08-28

Chemotherapy-induced ileal crypt apoptosis and the ileal microbiome shape immunosurveillance and prognosis of proximal colon cancer - Roberti, Maria Paula; Yonekura, Satoru; Duong, Connie P.M.; Picard, Marion; Ferrere, Gladys; Tidjani Alou, Maryam; Rauber, Conrad; Iebba, Valerio; Lehmann, Christian; Amon, Lukas; Dudziak, Diana; Derosa, Lisa; et al. (Nature Medicine, 2020)
The prognosis of colon cancer (CC) is dictated by tumor-infiltrating lymphocytes, including follicular helper T (TFH) cells and the efficacy of chemotherapy-induced immune responses. It remains unclear whether gut microbes contribute to the elicitation of TFH cell-driven responses. Here, we show that the ileal microbiota dictates tolerogenic versus immunogenic cell death of ileal intestinal epithelial cells (IECs) and the accumulation of TFH cells in patients with CC and mice. Suppression of IEC apoptosis led to compromised chemotherapy-induced immunosurveillance against CC in mice. Protective immune responses against CC were associated with residence of Bacteroides fragilis and Erysipelotrichaceae in the ileum. In the presence of these commensals, apoptotic ileal IECs elicited PD-1+ TFH cells in an interleukin-1R1- and interleukin-12-dependent manner. The ileal microbiome governed the efficacy of chemotherapy and PD-1 blockade in CC independently of microsatellite instability. These findings demonstrate that immunogenic ileal apoptosis contributes to the prognosis of chemotherapy-treated CC.
CRIS-Team Scopus Importer:2020-06-02

Chk1 and Wee1 control genotoxic-stress induced G2-M arrest in melanoma cells - Vera, Julio; Raatz, Yvonne; Wolkenhauer, Olaf; Kottek, Tina; Bhattacharya, Animesh; Simon, Jan C.; Kunz, Manfred (Cellular Signalling, 2015)
In the present report, the role of ATR-Chk1-Wee1 and ATM-Chk2-p53-p21 pathways in stress-induced cell cycle control is analysed in melanoma cells. Treatment of p53 wild-type melanoma cells with the genotoxic agent doxorubicin induces G2-M arrest, inhibitory phosphorylation of cell cycle kinase Cdc2 (CDK1) and enhanced expression of p53/p21. Wee1 inhibition under doxorubicin pulse-treatment reduces G2-M arrest and induces apoptosis. Inhibition of upstream kinase Chk1 under doxorubicin treatment almost completely abolishes stress-induced G2-M arrest and induces enhanced apoptosis. Interestingly, Chk1 inhibition alone even further increases apoptosis. While Chk1 inhibition alone almost completely abolishes G0-G1 arrest, combined treatment with doxorubicin re-establishes G0-G1 arrest. Moreover, Chk1 inhibition alone induces only a slight p53/p21 induction, while a strong induction of both proteins is observed by the combination with doxorubicin. These findings are suggestive for a particular role of p53/p21 in G0-G1, and Chk1 in G0-G1 and G2-M arrest. In line with this, the p53-mutant SK-Mel-28 melanoma cells do not mount a significant G0-G1 arrest under combined doxorubicin and Chk1 inhibitor treatment but rather show extensive apoptosis. Moreover, knockdown of p21 dramatically reduces stress-induced G0-G1 arrest under doxorubicin and Chk1 inhibitor treatment accompanied by massive DNA damage and apoptosis induction. Treatment of melanoma cells with an inhibitor of Chk2 upstream kinase ATM and doxorubicin almost completely abolishes G0-G1 arrest. Taken together, both Chk1 and Wee1 are mediators of G2-M arrest, while p53, p21 and Chk1 are mediators of G0-G1 arrest in melanoma cells. Combined treatment with chemotherapeutic agents such as doxorubicin and Chk1 inhibitors may help to overcome apoptosis resistance of p53-proficient melanoma cells. But treatment with Chk1 inhibitor alone may even be more efficient.
EVALuna2:19518

Chronische Entzündungserkrankungen in Deutschland: Eine Querschnittanalyse über Begleiterkrankungen und Arzneimitteleinsatz - Leipe, Jan; Schmelz, Renate; Riemekasten, Gabriela; Thaçi, Diamant; Henes, Jörg; Schäkel, Knut; Pinter, Andreas; Sticherling, Michael; Wegner, Joanna; Fusco, Stefano; Linke, Miriam; Weber, Valeria; et al. (Zeitschrift für Rheumatologie, 2023)
Background: Immune-mediated inflammatory diseases (IMID) can lead to a substantial disease burden for those affected, in particular by the concomitant occurrence of other IMIDs or in the presence of comorbidities. The care of patients with IMIDs is complex and involves various medical disciplines. Objective: To describe the burden of disease and the current routine drug treatment of patients with IMID. Material and methods: The retrospective cross-sectional analysis was based on statutory health insurance claims data from the InGef database. Prevalent patients with psoriasis (Pso), psoriatic arthritis (PsA), spondylarthritis (SpA), rheumatoid arthritis (RA), Crohn’s disease (MC), ulcerative colitis (CU), or connective tissue disease were identified among 3,988,695 insured patients in 2018. The concomitant occurrence of different IMIDs and the extent to which patients with IMID are affected by other comorbidities compared to a reference population were investigated. The current routine drug treatment was described based on the use of predefined forms of treatment. Results: In the database 188,440 patients with IMID (4.7%) were identified. Compared to the reference population the prevalence of comorbidities, such as depressive episodes and cardiovascular risk factors was higher in patients with IMID. For MC, CU, RA, and PsA disease-modifying antirheumatic drugs (DMARD) and classical systemic forms of treatment were used most commonly. In Pso, SpA, and connective tissue disease nonsteroidal anti-inflammatory drugs (NSAID) were the most frequently used treatment often in combination with other drugs. Conclusion: A considerable number of patients with IMIDs (16.9–27.5%) suffer from different diseases of the IMID group. They are frequently affected by accompanying illnesses and require interdisciplinary medical treatment.
CRIS-Team Scopus Importer:2023-01-13
Keywords: Chronic inflammatory diseases; Epidemiology; Pharmacotherapy; Real-world evidence; Statutory health insurance data analysis

Circumventing pyroptosis via hyperactivation shapes superior immune responses of human type 2 dendritic cells compared to type 3 dendritic cells - Hatscher, Lukas; Kaszubowski, Tomasz; Amon, Lukas; Dudziak, Diana; Heger, Lukas (European Journal of Immunology, 2023)
Exploiting inflammasome activation in dendritic cells (DCs) is a promising approach to fight cancer and to augment adjuvant-induced immune responses. As inflammasome formation is typically accompanied by pyroptosis, hyperactivation—defined as inflammasome activation in the absence of pyroptosis—represents a mechanism of circumventing cell death of DCs while simultaneously benefitting from inflammasome signaling. We previously demonstrated a unique specialization for inflammasome responses and hyperactivation of human cDC2 among all human DC subsets. As recent investigations revealed heterogeneity among the human cDC2 population, we aimed to analyze whether the two recently identified cDC2 subpopulations DC2 and DC3 harbor similar or different inflammasome characteristics. Here, we report that both DC2 and DC3 are inflammasome competent. We show that DC3 generally induce stronger inflammasome responses, which are associated with higher levels of cell death. Although DC2 release lower levels of inflammasome-dependent IL-1β, they induce stronger CD4+ T cell responses than DC3, which are predominantly skewed toward a TH1/TH17 phenotype. Thus, mainly DC2 seem to be able to enter a state of hyperactivation, resulting in enhanced T cell stimulatory capacity.
CRIS-Team Scopus Importer:2023-03-31
Keywords: DC2; DC3; dendritic cells; inflammasome; pyroptosis

Citrate-coated superparamagnetic iron oxide nanoparticles enable a stable non-spilling loading of t cells and their magnetic accumulation - Boosz, Philipp; Pfister, Felix; Stein, René; Friedrich, Bernhard; Fester, Lars; Band, Julia; Mühlberger, Marina; Schreiber, Eveline; Lyer, Stefan; Dudziak, Diana; Alexiou, Christoph; Janko, Christina (Cancers, 2021)
T cell infiltration into a tumor is associated with a good clinical prognosis of the patient and adoptive T cell therapy can increase anti-tumor immune responses. However, immune cells are often excluded from tumor infiltration and can lack activation due to the immune-suppressive tumor microenvironment. To make T cells controllable by external forces, we loaded primary human CD3+ T cells with citrate-coated superparamagnetic iron oxide nanoparticles (SPIONs). Since the efficacy of magnetic targeting depends on the amount of SPION loading, we investigated how experimental conditions influence nanoparticle uptake and viability of cells. We found that loading in the presence of serum improved both the colloidal stability of SPIONs and viability of T cells, whereas stimulation with CD3/CD28/CD2 and IL-2 did not influence nanoparticle uptake. Further-more, SPION loading did not impair cytokine secretion after polyclonal stimulation. We finally achieved 1.4 pg iron loading per cell, which was both located intracellularly in vesicles and bound to the plasma membrane. Importantly, nanoparticles did not spill over to non-loaded cells. Since SPION-loading enabled efficient magnetic accumulation of T cells in vitro under dynamic condi-tions, we conclude that this might be a good starting point for the investigation of in vivo delivery of immune cells.
CRIS-Team Scopus Importer:2021-09-03
Keywords: Adoptive T cell transfer; Immune therapy; Magnetic targeting; Nanomedicine; Solid tumor; Superparamagnetic iron oxide nanoparticles (SPIONs); Targeted transport

c-Kit inhibitors for unresectable or metastatic mucosal, acral or chronically sun-damaged melanoma: a systematic review and one-arm meta-analysis - Steeb, Theresa; Wessely, Anja; Petzold, Anne; Kohl, Christoph; Erdmann, Michael; Berking, Carola; Heppt, Markus (European Journal of Cancer, 2021)
Background: Activating genomic alterations of the receptor tyrosine kinase KIT are found preferentially in certain melanoma subtypes such as acral and mucosal melanoma or melanoma arising in chronically sun-damaged skin. However, the therapeutic value of c Kit inhibitors for these subtypes currently remains unclear. Objectives: The objective of this study was to summarise the efficacy and safety of c-Kit inhibitors for unresectable or metastatic mucosal, acral or chronically sun-damaged melanoma. Methods: We performed a systematic literature research in MEDLINE, Embase and CENTRAL and hand searched pertinent trial registers and conference abstracts for eligible trials until 23rd June 2020. Results were pooled using a random-effects model to calculate pooled proportions of objective response rates (ORRs) and severe adverse events (sAEs) from unselected KIT mutant or amplified cohorts. Results: Nineteen single-arm studies with an overall sample size of 601 patients were included. The studies investigated imatinib (n = 8), nilotinib (n = 7), dasatinib (n = 3) and sunitinib (n = 1). The pooled ORR for all inhibitors was 15% (95% confidence interval [CI]: 12-18%). Subgroup analysis revealed the highest ORR (20%; 95% CI: 14-26%) for nilotinib. The ORR for mucosal melanoma was 14% (95% CI: 6-24%) and 22% for acral lentiginous melanoma (95% CI: 14-30%). At least one sAE was reported in 42% of patients (95% CI: 34-50%). Conclusions: c-Kit inhibitors represent a valuable treatment option for patients with KIT mutant melanoma, in particular for mutations of exons 11 and 13. Furthermore, high-quality trials are urgently needed to investigate putative combinations of specific targeted therapies with immunotherapy. (c) 2021 Elsevier Ltd. All rights reserved.
CRIS-Team WoS Importer:2021-10-15

CLASSIFICATION OF PSORIATIC ARTHRITIS, SERONEGATIVE RHEUMATOID ARTHRITIS, AND SEROPOSITIVE RHEUMATOID ARTHRITIS USING DEEP LEARNING ON MAGNETIC RESONANCE IMAGING - Folle, Lukas; Bayat, Sara; Kleyer, Arnd; Fagni, Filippo; Kapsner, Lorenz; Schlereth, Maja; Meinderink, Timo; Breininger, Katharina; Tascilar, Koray; Krönke, Gerhard; Uder, Michael; Sticherling, Michael; et al. (Supplement 1, 2022)
Background: While MRI evaluation of joints has been primarily used to quantify inflammation at a cross-sectional and longitudinal level, less is known about the potential of MRI in distinguishing different patterns of inflammation in the various forms of arthritis. Objectives: To evaluate (i) whether deep learning using neural networks can be trained to distinguish between seropositive rheumatoid arthritis (RA+), seronegative RA (RA-), and psoriatic arthritis (PsA) based on structural inflammatory patterns on hand magnetic resonance imaging and (ii) to assess if psoriasis patients with subclinical inflammation fit into such patterns. Methods: ResNet 3D [1] neural networks were trained to distinguish (i) RA+ vs. PsA, (ii) RA- vs. PsA and (iii) RA+ vs. RA- with respect to hand MRI data. Diagnosis of patients was determined using the following guidelines: ACR/EULAR 2010 [2] for RA and CASPAR [3] for PsA. Results from T1 coronal, T2 coronal, T1 coronal and axial fat suppressed contrast-enhanced (CE) and T2 fat suppressed axial sequences were used. The performance of such trained networks was analyzed by the area-under-the-receiver-operating-characteristic curve (AUROC) with and without imputation of demographic and clinical parameters ( Figure 1A ). Additionally, the trained networks were applied to psoriasis patients without clinical signs of PsA. Results: MRI scans from 649 patients (135 RA-, 190 RA+, 177 PsA, 147 psoriasis) were included ( Table 1 ). The AUROC for differentiation between disease entities was 75% (SD 3%) for RA+ vs. PsA, 74% (SD 8%) for RA- vs. PsA, and 67% (6%) for RA+ vs. RA-. All MRI sequences were relevant for classification, however, when deleting CE sequences, the loss of performance was only marginal. The addition of patient-specific data to the networks did not provide significant improvements. Increasing amounts of training data demonstrated improved performance of the networks ( Figure 1B ). Psoriasis patients were mostly assigned to PsA by the neural networks, suggesting that PsA-like MRI pattern may be present early in the course of psoriatic disease. Conclusion: Deep learning can be successfully applied to differentiate MRI inflammatory patterns related to RA+, RA-, and PsA. Early changes in psoriasis patients can be recognized by neural networks and are characterized by a pattern that allowed the networks to classify them as PsA. <
Keywords: Rheumatoid arthritis; deep learning; neural networks

CLEC10A Is a Specific Marker for Human CD1c+ Dendritic Cells and Enhances Their Toll-Like Receptor 7/8-Induced Cytokine Secretion - Heger, Lukas; Balk, Silke; Lühr, Jennifer; Heidkamp, Gordon Frederik; Lehmann, Christian; Hatscher, Lukas; Purbojo, Ariawan; Hartmann, Arndt; Garcia-Martin, Fayna; Nishimura, Shin-Ichiro; Cesnjevar, Robert; Nimmerjahn, Falk; et al. (Frontiers in Immunology, 2018)
Dendritic cells (DCs) are major players for the induction of immune responses. Apart from plasmacytoid DCs (pDCs), human DCs can be categorized into two types of conventional DCs: CD141+ DCs (cDC1) and CD1c+ DCs (cDC2). Defining uniquely expressed surface markers on human immune cells is not only important for the identification of DC subpopulations but also a prerequisite for harnessing the DC subset-specific potential in immunomodulatory approaches, such as antibody-mediated antigen targeting. Although others identified CLEC9A as a specific endocytic receptor for CD141+ DCs, such a receptor for CD1c+ DCs has not been discovered, yet. By performing transcriptomic and flow cytometric analyses on human DC subpopulations from different lymphohematopoietic tissues, we identified CLEC10A (CD301, macrophage galactose-type C-type lectin) as a specific marker for human CD1c+ DCs. We further demonstrate that CLEC10A rapidly internalizes into human CD1c+ DCs upon binding of a monoclonal antibody directed against CLEC10A. The binding of a CLEC10A-specific bivalent ligand (the MUC-1 peptide glycosylated with N-acetylgalactosamine) is limited to CD1c+ DCs and enhances the cytokine secretion (namely TNFα, IL-8, and IL-10) induced by TLR 7/8 stimulation. Thus, CLEC10A represents not only a candidate to better define CD1c+ DCs-due to its high endocytic potential-CLEC10A also exhibits an interesting candidate receptor for future antigen-targeting approaches.
EVALuna2:34257

Clec12A, CD301b, and FcγRIIB/III define the heterogeneity of murine DC2s and DC3s - Amon, Lukas; Seichter, Anna; Vurnek, Damir; Heger, Lukas; Lächele, Lukas; Tochoedo, Nounagnon Romaric; Kaszubowski, Tomasz; Hatscher, Lukas; Baranska, Anna; Tchitashvili, Giorgi; Nimmerjahn, Falk; Lehmann, Christian; et al. (Cell Reports, 2024)
Over the last decade, multiple studies have investigated the heterogeneity of murine conventional dendritic cells type 2 (cDC2s). However, their phenotypic similarity with monocytes and macrophages renders their clear identification challenging. By creating a protein atlas utilizing multiparameter flow cytometry, we show that ESAM+ cDC2s are a specialized feature of the spleen strongly differing in their proteome from other cDC2s. In contrast, all other tissues are populated by Clec12A+ cDC2s or Clec12A− cDC2s (high or low for Fcγ receptors, C-type lectin receptors, and CD11b, respectively), rendering Clec12A+ cDC2s classical sentinels. Further, expression analysis of CD301b, Clec12A, and FcγRIIB/III provides a conserved definition of cDC2 heterogeneity, including the discovery of putative FcγRIIB/III+ DC3s across tissues. Finally, our data reveal that cell identity (ontogeny) dictates the proteome that is further fine-tuned by the tissue environment on macrophages and dendritic cells (DCs), while monocytes and plasmacytoid DCs (pDCs) display subset intrinsic default settings.
CRIS-Team Scopus Importer:2024-04-12
Keywords: CD301b; CP: Immunology; DC3; dendritic cells; heterogeneity; macrophages; monocytes; mouse; myeloid cells; proteome atlas; subpopulations

Clinical characteristics and treatment modalities in uremic and non uremic calciphylaxis - a dermatological single-center experience - Yousuf, Sabine; Busch, Dorothee; Renner, Regina; Schliep, Stefan; Erfurt-Berge, Cornelia (Renal Failure, 2024)
Calciphylaxis (CP) is a serious, potentially life-threatening disease that presents with medial calcification of small-sized vessels and painful ischemic ulcerations. Although calciphylaxis is frequently seen in patients with end-stage kidney disease on dialysis (calcific uremic arteriolopathy, CUA), there are reported cases of nonuremic calciphylaxis (NUC), which often remain undiagnosed. We conducted a retrospective chart review at our dermatological hospital and evaluated data concerning the epidemiology, comorbidities, medication, laboratory abnormalities, and therapeutic approaches of 60 patients diagnosed with calciphylaxis between 01/2012 and 12/2022. We identified 21 patients diagnosed with NUC and 39 with kidney disease. The predilection sites of skin lesions were the lower legs in 88% (n = 53), followed by the thigh and gluteal regions in 7% (n = 4). Significant differences were identified in comorbidities, such as atrial fibrillation (p < 0.001) and hyperparathyroidism (p < 0.01) accounting for CUA patients. Medication with vitamin K antagonists (p < 0.001), phosphate binders (p < 0.001), and loop diuretics (p < 0.01) was found to be associated with the onset of calciphylaxis. Hyperphosphatemia (p < 0.001), increased parathyroid hormone (p < 0.01) and triglyceride levels (p < 0.01), hypoalbuminemia (p < 0.01) and decreased hemoglobin values (p < 0.001) in the CUA cohort were significantly different from those in the NUC group. All patients with CUA received systemic medication. In contrast, only 38% (n = 8) of patients with NUC received systemic treatment. Striking discrepancies in the treatment of both cohorts were detected. In particular, NUC remains a disease pattern that is still poorly understood and differs from CUA in several important parameters.
CRIS-Team Scopus Importer:2024-01-19
Keywords: calcific uremic arteriolopathy; Calciphylaxis; leg ulcer; nonuremic calciphylaxis

Clinical determinants of long-term survival in metastatic uveal melanoma - Koch, Elias; Petzold, Anne; Wessely, Anja; Dippel, Edgar; Erdmann, Michael; Heinzerling, Lucie; Hohberger, Bettina; Knorr, Harald; Leiter, Ulrike; Meier, Friedegund; Mohr, Peter; Rahimi, Farnaz; et al. (Cancer Immunology, Immunotherapy, 2021)
This study aimed to identify prognostic factors in patients with metastatic uveal melanoma (UM) that were associated with long-term survival in a real-world setting. A total of 94 patients with metastatic UM were included from German skin cancer centers and the German national skin cancer registry (ADOReg). Data were analyzed for the response to treatment, progression-free survival, and overall survival (OS). Prognostic factors were explored with univariate Cox regression, log-rank, and χ2-tests. Identified factors were subsequently validated after the population was divided into two cohorts of short-term survival (< 2 years OS, cohort A, n = 50) and long-term survival (> 2 years OS, cohort B, n = 44). A poor ECOG performance status (hazard ratio [HR] 2.0, 95% confidence interval [CI] 1.0–3.9) and elevated serum LDH (HR 2.0, 95% CI 1.0–3.8) were associated with a poor OS, whereas a good response to immune checkpoint blockade (ICB, p < 0.001), radiation therapy (p < 0.001), or liver-directed treatments (p = 0.01) were associated with a prolonged OS. Long-term survivors (cohort B) showed a higher median number of organs affected by metastasis (p < 0.001), while patients with liver metastases only were more common in cohort A (40% vs. 9%; p = 0.002). A partial response to ICB was observed in 16% (12/73), being 21% (8/38) for combined ICB, 17% (1/6) for single CTLA4 inhibition, and 10% (3/29) for single PD1 inhibition. One complete response occurred in cohort B with combined ICB. We conclude that the response to ICB and the presence of extrahepatic disease were favorable prognostic factors for long-term survival.
CRIS-Team Scopus Importer:2021-11-05
Keywords: Immune checkpoint blockade; Liver metastases; Liver-directed treatment; Long-term survival; Registry; Uveal melanoma

Clinical impact of COVID-19 on patients with cancer treated with immune checkpoint inhibition - Rogiers, Aljosja; Da Silva, Ines Pires; Tentori, Chiara; Tondini, Carlo Alberto; Grimes, Joseph M.; Trager, Megan H.; Nahm, Sharon; Zubiri, Leyre; Manos, Michael; Bowling, Peter; Elkrief, Arielle; Papneja, Neha; et al. (Journal for ImmunoTherapy of Cancer, 2021)
Background Patients with cancer who are infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are more likely to develop severe illness and die compared with those without cancer. The impact of immune checkpoint inhibition (ICI) on the severity of COVID-19 illness is unknown. The aim of this study was to investigate whether ICI confers an additional risk for severe COVID-19 in patients with cancer. Methods We analyzed data from 110 patients with laboratory-confirmed SARS-CoV-2 while on treatment with ICI without chemotherapy in 19 hospitals in North America, Europe and Australia. The primary objective was to describe the clinical course and to identify factors associated with hospital and intensive care (ICU) admission and mortality. Findings Thirty-five (32%) patients were admitted to hospital and 18 (16%) died. All patients who died had advanced cancer, and only four were admitted to ICU. COVID-19 was the primary cause of death in 8 (7%) patients. Factors independently associated with an increased risk for hospital admission were ECOG ≥2 (OR 39.25, 95% CI 4.17 to 369.2, p=0.0013), treatment with combination ICI (OR 5.68, 95% CI 1.58 to 20.36, p=0.0273) and presence of COVID-19 symptoms (OR 5.30, 95% CI 1.57 to 17.89, p=0.0073). Seventy-six (73%) patients interrupted ICI due to SARS-CoV-2 infection, 43 (57%) of whom had resumed at data cut-off. Interpretation COVID-19-related mortality in the ICI-treated population does not appear to be higher than previously published mortality rates for patients with cancer. Inpatient mortality of patients with cancer treated with ICI was high in comparison with previously reported rates for hospitalized patients with cancer and was due to COVID-19 in almost half of the cases. We identified factors associated with adverse outcomes in ICI-treated patients with COVID-19.
CRIS-Team Scopus Importer:2021-02-05
Keywords: immunotherapy

Clinical outcome of concomitant vs interrupted BRAF inhibitor therapy during radiotherapy in melanoma patients - Hecht, Markus; Meier, Friedegund; Zimmer, Lisa; Polat, Bulent; Loquai, Carmen; Weishaupt, Carsten; Forschner, Andrea; Gutzmer, Ralf; Utikal, Jochen S.; Goldinger, Simone M.; Geier, Michael; Hassel, Jessica C.; et al. (British Journal of Cancer, 2018)
This corrects the article DOI: 10.1038/bjc.2017.85.
EVALuna2:34392

Clinical Prognostic Factors in metastatic Choroidal Melanoma - Koch, Elias; Petzold, Anne; Wessely, Anja; Dippel, E.; Erdmann, Michael; Heinzerling, L.; Hohberger, Bettina; Knorr, H.; Leiter-Stoppke, U.; Meier, F.; Mohr, P.; Rahimi, F.; et al. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2021)
CRIS-Team WoS Importer:2021-09-24

Clinical-Scale Production of CAR-T Cells for the Treatment of Melanoma Patients by mRNA Transfection of a CSPG4-Specific CAR under Full GMP Compliance. - Wiesinger, Manuel; Maerz, Johannes; Kummer, Mirko; Schuler, Gerold; Dörrie, Jan; Schuler-Thurner, Beatrice; Schaft, Niels (Cancers, 2019)
Chimeric antigen receptor (CAR)-T cells already showed impressive clinical regressions in leukemia and lymphoma. However, the development of CAR-T cells against solid tumors lags behind. Here we present the clinical-scale production of CAR-T cells for the treatment of melanoma under full GMP compliance. In this approach a CAR, specific for chondroitin sulfate proteoglycan 4 (CSPG4) is intentionally transiently expressed by mRNA electroporation for safety reasons. The clinical-scale protocol was optimized for: (i) expansion of T cells, (ii) electroporation efficiency, (iii) viability, (iv) cryopreservation, and (v) potency. Four consistency runs resulted in CAR-T cells in clinically sufficient numbers, i.e., 2.4 x 10(9) CAR-expressing T cells, starting from 1.77x10(8)PBMCs, with an average expansion of 13.6x, an electroporation efficiency of 88.0% CAR-positive cells, a survival of 74.1% after electroporation, and a viability of 84% after cryopreservation. Purity was 98.7% CD3(+) cells, with 78.1% CD3(+)/CD8(+) T cells and with minor contaminations of 1.2% NK cells and 0.6% B cells. The resulting CAR-T cells were tested for cytolytic activity after cryopreservation and showed antigen-specific and very efficient lysis of tumor cells. Although our work is descriptive rather than investigative in nature, we expect that providing this clinically applicable protocol to generate sufficient numbers of mRNA-transfected CAR-T cells will help in moving the field of adoptive cell therapy of cancer forward.
CRIS-Team WoS Importer:2019-09-24

Combination therapies to improve DC-based treatment of melanoma - Seretis, A.; Cappellano, G.; Bellmann, L.; Schachtl-Riess, J.; Steindl, R.; Prokopi, N.; Ortner-Tobider, D.; Komenda, K.; Tripp, C.; Brinckerhoff, C. E.; Lühr, Jennifer; Amon, Lukas; et al. (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-11

Combined cytotoxic activity of an infectious, but non-replicative herpes simplex virus type 1 and plasmacytoid dendritic cells against tumour cells - Thomann, Sabrina; Boscheinen, Jan; Vogel, Karin; Knipe, David M.; Deluca, Neal; Gross, Stefanie; Schuler-Thurner, Beatrice; Schuster, Philipp; Schmidt, Barbara (Immunology, 2015)
Malignant melanoma is an aggressive tumour of the skin with increasing incidence, frequent metastasis and poor prognosis. At the same time, it is an immunogenic type of cancer with spontaneous regressions. Most recently, the tumoricidal effect of plasmacytoid dendritic cells (pDC) and their capacity to overcome the immunosuppressive tumour microenvironment are being investigated. In this respect, we studied the effect of the infectious, but replication-deficient, herpes simplex virus 1 (HSV-1) d106S vaccine strain, which lacks essential immediate early genes, in pDC co-cultures with 11 melanoma cell lines. We observed a strong cytotoxic activity, inducing apoptotic and necrotic cell death in most melanoma cell lines. The cytotoxic activity of HSV-1 d106S plus pDC was comparable to the levels of cytotoxicity induced by natural killer cells, but required only a fraction of cells with effector : target ratios of 1 : 20 (P < 0·05). The suppressive activity of cell-free supernatants derived from virus-stimulated pDC was significantly neutralized using antibodies against the interferon-? receptor (P < 0·05). In addition to type I interferons, TRAIL and granzyme B contributed to the inhibitory effect of HSV-1 d106S plus pDC to a minor extent. UV-irradiated viral stocks were significantly less active than infectious particles, both in the absence and presence of pDC (P < 0·05), indicating that residual activity of HSV-1 d106S is a major component and sensitizes the tumour cells to interferon-producing pDC. Three leukaemic cell lines were also susceptible to this treatment, suggesting a general anti-tumour effect. In conclusion, the potential of HSV-1 d106S for therapeutic vaccination should be further evaluated in patients suffering from different malignancies.
EVALuna2:8282

Combined immunotherapy with nivolumab and ipilimumab with and without local therapy in patients with melanoma brain metastasis: a DeCOG* study in 380 patients - Amaral, Teresa; Kiecker, Felix; Schaefer, Sarah; Stege, Henner; Kaehler, Katharina; Terheyden, Patrick; Gesierich, Anja; Gutzmer, Ralf; Haferkamp, Sebastian; Uttikal, Jochen; Berking, Carola; Rafei-Shamsabadi, David; et al. (Journal for ImmunoTherapy of Cancer, 2020)
BACKGROUND: Nivolumab combined with ipilimumab have shown activity in melanoma brain metastasis (MBM). However, in most of the clinical trials investigating immunotherapy in this subgroup, patients with symptomatic MBM and/or prior local brain radiotherapy were excluded. We studied the efficacy of nivolumab plus ipilimumab alone or in combination with local therapies regardless of treatment line in patients with asymptomatic and symptomatic MBM. METHODS: Patients with MBM treated with nivolumab plus ipilimumab in 23 German Skin Cancer Centers between April 2015 and October 2018 were investigated. Overall survival (OS) was evaluated by Kaplan-Meier estimator and univariate and multivariate Cox proportional hazard analyses were performed to determine prognostic factors associated with OS. RESULTS: Three hundred and eighty patients were included in this study and 31% had symptomatic MBM (60/193 with data available) at the time of start nivolumab plus ipilimumab. The median follow-up was 18 months and the 2 years and 3 years OS rates were 41% and 30%, respectively. We identified the following independently significant prognostic factors for OS: elevated serum lactate dehydrogenase and protein S100B levels, number of MBM and Eastern Cooperative Oncology Group performance status. In these patients treated with checkpoint inhibition first-line or later, in the subgroup of patients with BRAFV600-mutated melanoma we found no differences in terms of OS when receiving first-line either BRAF and MEK inhibitors or nivolumab plus ipilimumab (p=0.085). In BRAF wild-type patients treated with nivolumab plus ipilimumab in first-line or later there was also no difference in OS (p=0.996). Local therapy with stereotactic radiosurgery or surgery led to an improvement in OS compared with not receiving local therapy (p=0.009), regardless of the timepoint of the local therapy. Receiving combined immunotherapy for MBM in first-line or at a later time point made no difference in terms of OS in this study population (p=0.119). CONCLUSION: Immunotherapy with nivolumab plus ipilimumab, particularly in combination with stereotactic radiosurgery or surgery improves OS in asymptomatic and symptomatic MBM.
CRIS-Team Scopus Importer:2020-04-07
Keywords: immunology; oncology; radiotherapy; surgery

Combined low-dose ipilimumab and pembrolizumab after sequential ipilimumab and pembrolizumab failure in advanced melanoma - Kirchberger, Michael C.; Hauschild, Axel; Schuler, Gerold; Heinzerling, Lucie (European Journal of Cancer, 2016)
With the wide use of anti-PD-1 therapy, an increasing number of patients progress under treatment. Combined immunotherapy with anti-CTLA-4 and anti-PD-1 antibodies induces higher response rates as first-line treatment in comparison to single-agent therapy, however, with substantial toxicity since the combination of ipilimumab (3 mg/kg) and nivolumab (1 mg/kg) induced 55% grade 3/4 treatment-related adverse events and treatment discontinuation rates of 39%. In this case series, we investigated the efficacy and toxicity of the combined immunotherapy with low-dose ipilimumab (1 mg/kg) plus pembrolizumab (2 mg/kg) in patients with metastatic melanoma with progressive disease under sequential monotherapy with both agents. All patients had received at least three lines of treatment, 78% of patients were M1c, and 67% had brain metastases. Stable disease was observed in 3 out of 9 patients with a median overall survival of 8 months after double checkpoint inhibition. No treatment-related grade 3/4 adverse events occurred, and none of the patients needed to discontinue the treatment due to toxicity. Further trials are needed to investigate combined immunotherapy as rescue treatment in heavily pretreated melanoma patients to find optimal dosage in regard to outcome and toxicity.
EVALuna2:19622

Combining a CAR and a TCR to generate T cells expressing two additional receptors (TETARs) for melanoma immunotherapy - Uslu, Ugur; Gerer, K.; Hoyer, S.; Schuler, Gerold; Dörrie, Jan; Schaft, Niels (2016)
EVALuna2:19613

Combining a chimeric antigen receptor and a conventional T-cell receptor to generate T cells expressing two additional receptors (TETARs) for a multi-hit immunotherapy of melanoma. - Uslu, Ugur; Schuler, Gerold; Dörrie, Jan; Schaft, Niels (Experimental Dermatology, 2016)
The adoptive transfer of engineered T cells represents an important approach in immunotherapy of melanoma. However, relapse of the tumor can occur due to immune-escape mechanisms developed by the tumor cells, for example antigen loss, downregulation of the major histocompatibility complex presentation machinery and defects in antigen processing. To counteract these mechanisms, we combined a T-cell receptor and a chimeric antigen receptor, specific for different common melanoma antigens, gp100 (PMEL) and MCSP (HMW-MAA), to generate functional CD8(+) T cells expressing two additional receptors (TETARs) by electroporation of receptor-encoding mRNA. These TETARs produced cytokines and were lytic upon recognition of each of their cognate antigens, while no reciprocal inhibition of the receptors occurred. When stimulated with target cells, which express both antigens, an enhanced effect was suggested. The confirmation that chimeric antigen receptors and T-cell receptors can be functionally combined opens up new avenues in cancer immunotherapy, and the generation of TETARs helps by-passing major mechanisms by which tumor cells escape immune recognition.
EVALuna2:19624

COMBI-r: A Prospective, Non-Interventional Study of Dabrafenib Plus Trametinib in Unselected Patients with Unresectable or Metastatic BRAF V600-Mutant Melanoma - Berking, Carola; Livingstone, Elisabeth; Debus, Dirk; Loquai, Carmen; Weichenthal, Michael; Leiter, Ulrike; Kiecker, Felix; Mohr, Peter; Eigentler, Thomas K.; Remy, Janina; Schober, Katharina; Heppt, Markus; et al. (Cancers, 2023)
Combined BRAF/MEK-inhibition constitutes a relevant treatment option for BRAF-mutated advanced melanoma. The prospective, non-interventional COMBI-r study assessed the effectiveness and tolerability of the BRAF-inhibitor dabrafenib combined with the MEK-inhibitor trametinib in patients with advanced melanoma under routine clinical conditions. Progression-free survival (PFS) was the primary objective, and secondary objectives included overall survival (OS), disease control rate, duration of therapy, and the frequency and severity of adverse events. This study enrolled 472 patients at 55 German sites. The median PFS was 8.3 months (95%CI 7.1–9.3) and the median OS was 18.3 months (14.9–21.3), both tending to be longer in pre-treated patients. In the 147 patients with CNS metastases, PFS was similar in those requiring corticosteroids (probably representing symptomatic patients, 5.6 months (3.9–7.2)) compared with those not requiring corticosteroids (5.9 months (4.8–6.9)); however, OS was shorter in patients with brain metastases who received corticosteroids (7.8 (6.3–11.6)) compared to those who did not (11.9 months (9.6–19.5)). The integrated subjective assessment of tumor growth dynamics proved helpful to predict outcome: investigators’ upfront categorization correlated well with time-to-event outcomes. Taken together, COMBI-r mirrored PFS outcomes from other prospective, observational studies and confirmed efficacy and safety findings from the pivotal phase III COMBI-d/-v and COMBI-mb trials.
CRIS-Team Scopus Importer:2023-10-20
Keywords: BRAF mutation; brain metastases; dabrafenib; MAPK pathway; melanoma; trametinib; tumor dynamics

Common German language nomenclature for systemic sclerosis - Aringer, Martin; Mueller-Ladner, U.; Burkhardt, H.; Distler, Jörg; Distler, O.; Graninger, W. B.; Guenther, C.; Hunzelmann, N.; Kiener, H.; Sticherling, Michael; Sunderkoetter, C.; Walker, U. A.; et al. (Zeitschrift für Rheumatologie, 2015)
Large data bases and the projects arising from them have led to a much improved understanding of systemic sclerosis over the last decade. Serology has developed further so that more autoantibodies are available for routine testing. Capillary microscopy has become standard and relevant progress has also been made in therapy. Many diagnostic terms found in medical documentation do not adequately reflect this progress. The nomenclature is inconsistent and, therefore, confusing. The international classification of diseases (ICD) nomenclature is, from our point of view, also in need of improvement. This article aims to reestablish a common German language standard for systemic sclerosis, which reflects current knowledge and is suitable for implementation in the clinical routine.
EVALuna2:13102

Community effort endorsing multiscale modelling, multiscale data science and multiscale computing for systems medicine - Zanin, Massimiliano; Chorbev, Ivan; Stres, Blaz; Stalidzans, Egils; Vera, Julio; Tieri, Paolo; Castiglione, Filippo; Groen, Derek; Zheng, Huiru; Baumbach, Jan; Schmid, Johannes A.; Basilio, Jose; et al. (Briefings in Bioinformatics, 2019)
Systems medicine holds many promises, but has so far provided only a limited number of proofs of principle. To address this road block, possible barriers and challenges of translating systems medicine into clinical practice need to be identified and addressed. The members of the European Cooperation in Science and Technology (COST) Action CA15120 Open Multiscale Systems Medicine (OpenMultiMed) wish to engage the scientific community of systems medicine and multiscale modelling, data science and computing, to provide their feedback in a structured manner. This will result in follow-up white papers and open access resources to accelerate the clinical translation of systems medicine.
CRIS-Team WoS Importer:2019-08-09

Comparative analysis of human dendritic cell subpopulations in steady state and inflammation - Heger, Lukas; Heidkamp, Gordon Frederik; Lehmann, Christian; Eissing, N.; Söder, Stephan; Hartmann, Arndt; Zenk, J.; Alexiou, Christoph; Schuler, Gerold; Purbojo, Ariawan; Cesnjevar, Robert; Nimmerjahn, Falk; et al. (2017)
EVALuna2:33136

Comparative analysis of human dendritic cell subpopulations in steady state and inflammation - Heger, Lukas; Heidkamp, Gordon Frederik; Lehmann, Christian; Söder, Stephan; Hartmann, Arndt; Alexiou, Christoph; Schuler, Gerold; Purbojo, Ariawan; Cesnjevar, Robert; Nimmerjahn, Falk; Dudziak, Diana (2018)
EVALuna2:34382

Comparative Analysis of Radiomic Features and Gene Expression Profiles in Histopathology Data using Graph Neural Networks - Rivera Monroy, Luis; Rist, Leonhard; Eberhardt, Martin; Ostalecki, Christian; Bauer, Andreas; Vera, Julio; Breininger, Katharina; Maier, Andreas (Bildverarbeitung für die Medizin 2024, 2024)
This study leverages graph neural networks to integrate MELC data with Radiomic-extracted features for melanoma classification, focusing on cellwise analysis. It assesses the effectiveness of gene expression profiles and Radiomic features, revealing that Radiomic features, particularly when combined with UMAP for dimensionality reduction, significantly enhance classification performance. Notably, using Radiomics contributes to increased diagnostic accuracy and computational efficiency, as it allows for the extraction of critical data from fewer stains, thereby reducing operational costs. This methodology marks an advancement in computational dermatology for melanoma cell classification, setting the stage for future research and potential developments.<br

Comparative analysis of the phototoxicity induced by BRAF inhibitors and alleviation through antioxidants - Heppt, Markus V.; Clanner-Engelshofen, Benjamin M.; Marsela, Enklajd; Wessely, Anja; Kammerbauer, Claudia; Przybilla, Bernhard; French, Lars E.; Berking, Carola; Reinholz, Markus (Photodermatology Photoimmunology & Photomedicine, 2019)
BACKGROUND: Small molecules tackling mutated BRAF (BRAFi) are an important mainstay of targeted therapy in a variety of cancers including melanoma. Albeit commonly reported as side effect, the phototoxic potential of many BRAFi is poorly characterized. In this study, we evaluated the phototoxicity of 17 distinct agents and investigated whether BRAFi-induced phototoxicity can be alleviated by antioxidants. METHODS: The ultraviolet (UV) light absorbance of 17 BRAFi was determined. Their phototoxic potential was investigated independently with a reactive oxygen species (ROS) and the 3T3 neutral red uptake (NRU) assay in vitro. To test for a possible phototoxicity alleviation by antioxidants, vitamin C, vitamin E phosphate, trolox, and glutathione (GSH) were added to the 3T3 assay of selected inhibitors. RESULTS: The highest cumulative absorbance for both UVA and UVB was detected for vemurafenib. The formation of ROS was more pronounced for all compounds after irradiation with UVA than with UVB. In the 3T3 NRU assay, 8 agents were classified as phototoxic, including vemurafenib, dabrafenib, and encorafenib. There was a significant correlation between the formation of singlet oxygen (P = .026) and superoxide anion (P < .001) and the phototoxicity observed in the 3T3 NRU assay. The phototoxicity of vemurafenib was fully rescued in the 3T3 NRU assay after GSH was added at different concentrations. CONCLUSION: Our study confirms that most of the BRAF inhibitors exhibited a considerable phototoxic potential, predominantly after exposure to UVA. GSH may help treat and prevent the phototoxicity induced by vemurafenib.
EVALuna2:208521

Comparative efficacy analysis identifies immune checkpoint blockade as a new survival benchmark in advanced cutaneous squamous cell carcinoma - Petzold, Anne; Steeb, Theresa; Wessely, Anja; Schatton, Tobias; Berking, Carola; Heppt, Markus (European Journal of Cancer, 2022)
Background: Cutaneous squamous cell carcinoma is a common type of skin cancer that may progress to locally advanced or metastatic disease. Both disease stages are managed by a variety of treatment options, including immune checkpoint blockade (ICB), targeted therapy to epidermal growth factor, chemotherapy or treatment combinations. However, the comparative efficacy of such treatments is unclear. Methods: We performed a systematic literature search of Medline, Embase and Central to identify eligible studies reporting Kaplan–Meier curves or individual patient data for overall survival (OS) or progression-free survival (PFS). Kaplan–Meier curves were digitised using the “‘WebPlotDigitizer” program. Individual patient data was subsequently remodelled and pooled for distinct treatment groups. Results: Overall, 22 independent studies were included of which n = 927 patients were evaluable for PFS and n = 1054 for OS. ICB showed the highest median PFS (mPFS 9.9 months (95% CI: 8.1–19.9)) and median OS (mOS not reached (95% CI: 31.5 months-not reached)) compared to chemotherapy (mPFS 3.0 months (95% CI: 2.2–4.8), mOS 12.6 months (95% CI: 9.6–15.8)), targeted therapy to epidermal growth factor (mPFS 4.9 months (95% CI: 4.4–5.6), mOS 12.7 months (95% CI: 11.9–14.9)) and combination therapies without ICB (mPFS 9.1 months (95% CI: 8.0–12.1), mOS 18.1 months (95% CI: 16.3–22.8)). The survival benchmark with ICB after 26 months for metastatic squamous cell carcinoma was 70.8% (95% CI: 61.5%–81.5%) versus 37.9% (95% CI: 29.5%–48.8%) for the combination group and 17.1% (95% CI: 9.5%–30.8%) for chemotherapy. Conclusion: ICB is superior to other systemic treatments and sets a novel survival benchmark for advanced cutaneous squamous cell carcinoma.
CRIS-Team Scopus Importer:2022-06-17
Keywords: Cutaneous neoplasm; Cutaneous squamous cell carcinoma; Immune checkpoint blockade; Indirect comparison; Individual patient data; Overall survival; PD-1 therapy; Progression-free survival; Skin cancer

COMPARISON OF BONE MICROSTRUCTURE OF PSORIATIC ARTHRITIS AND PSORIASIS PATIENTS - AN HR-PQCT STUDY OF ANABOLIC AND CATABOLIC BONE CHANGES - Simon, David; Faustini, F.; Englbrecht, Matthias; Kleyer, Arnd; Kocijan, R.; Haschka, J.; Figueiredo, C.; Kraus, S.; Hueber, Axel; Sticherling, Michael; Schett, Georg; Rech, Jürgen (2015)
EVALuna2:34458

Comparison of guidelines for the management of patients with high-risk and advanced cutaneous squamous cell carcinoma - a systematic review - Heppt, M. V.; Steeb, T.; Berking, Carola; Nast, A. (Journal of the European Academy of Dermatology and Venereology, 2019)
The management of high-risk cutaneous squamous cell carcinoma (cSCC) can be a challenge as evidence from high quality clinical trials is rare. Guideline developers are challenged to provide practical and useful guidance for clinicians even in the absence of good evidence. In order to compare treatment recommendations for high-risk and advanced cSCC among national and international guidelines and to extract the most precise guidance provided, a systematic search was carried out in guideline databases Medline and Embase with a cutoff of 4 March 2019. Treatment recommendations for predefined clinical scenarios were extracted from selected guidelines and compared qualitatively. Five guidelines published from 2015 to 2018 were included. Excision of high-risk tumours with margin assessment was recommended in all guidelines. A safety margin of at least 6 mm was suggested in four guidelines. There was no clear recommendation to perform a sentinel lymph node biopsy in any guideline. Lymph node dissection was uniformly recommended in the presence of nodal disease. Treatment for metastatic cSCC was poorly characterized and restricted to the use of chemotherapy and epidermal growth factor receptor inhibitors. Recommendations for the management of high-risk and advanced cSCC were limited. We propose that guidelines should be updated to reflect recent advances in checkpoint blockade for metastatic cSCC.
EVALuna2:212853

Comparison of sedation with dexmedetomidine vs propofol during hysteroscopic surgery: Single-centre randomized controlled trial - Tanriverdi, Tugba Bingol; Koceroglu, Ikbal; Devrim, Sibel; Celik, Melek Gura (Journal of Clinical Pharmacy and Therapeutics, 2019)
What is known and objective The most appropriate sedative agent for conscious sedation in minor hysteroscopic surgeries is still unclear. Dexmedetomidine a sedative and analgesic agent, may be appropriate for outpatient procedures. The aim of our study was to compare the sedative, analgesic and hemodynamic effects of dexmedetomidine vs propofol in combination with fentanyl and midazolam in patients undergoing minor hysteroscopy surgery. Methods Sixty patients undergoing minor hysteroscopic surgery were randomized to receive either dexmedetomidine (n = 30) or propofol (n = 30) groups. Dexmedetomidine was infused at 1 mu g/kg for 10 minutes followed by a 0.7 mu g/kg/h maintenance infusion. Propofol was infused a bolus of 1.5 mg/kg followed by a 2.5 mg/kg/h maintenance infusion. Fentanyl 1.5 mcg/kg and midazolam 0.03 mg/kg were performed to all patients as premedication therapy before the hysteroscopic surgery. Post-operative pain score was assessed with visual analogue scale (VAS). Hemodynamic variables and Riker Sedation-Agitation Scale (SAS) scores were recorded for all patients. Results Mean arterial pressure and heart rate in the dexmedetomidine group were significantly lower than in propofol group, whereas SpO2 was similar between two groups. In addition, post-operative Riker SAS and VAS scores were significantly lower in dexmedetomidine group than in the propofol group. Bradycardia, hypotension and serious adverse events did not occur in any patients. What is new and conclusion Dexmedetomidine was associated with better analgesia and lower post-operative pain score than propofol in patients undergoing hysteroscopic surgery. However, arterial pressure and heart rate should be more closely monitored in patients received dexmedetomidine.
CRIS-Team WoS Importer:2019-03-20

Comparison of the Serum Tumor Markers S100 and Melanoma-inhibitory Activity (MIA) in the Monitoring of Patients with Metastatic Melanoma Receiving Vaccination Immunotherapy with Dendritic Cells - Uslu, Ugur; Schliep, Stefan; Schliep, Klaus; Erdmann, Michael; Koch, Hans-Uwe; Parsch, Hans; Rosenheinrich, Stina; Anzengruber, Doris; Boßerhoff, Anja Katrin; Schuler, Gerold; Schuler-Thurner, Beatrice (Anticancer Research, 2017)
In patients with melanoma, early dissemination via lymphatic and hematogenous routes is frequently seen. Thus, besides clinical follow-up examination and imaging, reliable melanoma-specific serological tumor markers are needed.We retrospectively compared two serum markers for melanoma, S100 and melanoma-inhibitory activity (MIA), for monitoring of patients with metastatic melanoma under either adjuvant or therapeutic vaccination immunotherapy with dendritic cells (DC). Serum was obtained from a total of 100 patients (28 patients in stage III and 72 patients in stage IV, according to the American Joint Committee on Cancer 2002) at regular intervals during therapy, accompanied by follow-up imaging.When relapse was detected, both markers often remained within normal range. In contrast, in patients with metastatic measurable disease receiving therapeutic and not adjuvant DC vaccination, an increase of both markers was a strong indicator for disease progression. When comparing both markers in the whole study population, MIA showed a superior sensitivity to detect disease progression.S100 and MIA are highly sensitive tumor markers for monitoring of patients with melanoma with current metastases, but less sensitive for monitoring of tumor-free patients. In the current study, MIA had a slightly superior sensitivity to detect progressive disease compared to S100 and seems to be more useful in monitoring of patients with metastatic melanoma receiving immunotherapy.
EVALuna2:4755

Computational Approaches in microRNA Biology - Schmitz, Ulf; Gupta, Shailendra K.; Vera, Julio; Wolkenhauer, Olaf (Encyclopedia of Biomedical Engineering, Vol. 3, 2019)
MicroRNAs (miRNAs) are small noncoding RNAs that regulate gene expression at the posttranscriptional level by binding to mRNA targets and inducing translational repression or target degradation via the RNA-induced silencing complex. Since miRNAs were first identified, computational approaches have played an important role for understanding their biosynthesis, modes of target regulation, and interplay with other mechanisms of gene regulation. In this essay we discuss computational methodologies used in miRNA biology research. More specifically, we introduce concepts for the prediction of miRNAs and their target genes: miRNA structure prediction and miRNA expression profiling approaches, coupled with the functional characterization of miRNAs. We then review approaches used for modeling miRNA-mediated gene regulatory networks.<br
CRIS-Team WoS Importer:2020-03-27
Keywords: Mathematical modeling of miRNA regulation; microRNA; microRNA databases and web resources; microRNA gene prediction; microRNA target hubs; microRNA target prediction; Regulatory networks; Target regulation

Computational Biology of Non-Coding RNA Methods and Protocols Preface - Lai, Xin; Gupta, Shailendra K.; Vera, Julio (Methods in Molecular Biology, 2019)
CRIS-Team WoS Importer:2021-10-18

Concealed complete response in melanoma patients under therapy with immune checkpoint inhibitors: two case reports - Schliep, Stefan; Agaimy, Abbas; Kiesewetter, Franklin; Schuler, Gerold; Heinzerling, Lucie; Cavallaro, Alexander Josef (Journal for ImmunoTherapy of Cancer, 2018)
BACKGROUND: The assessment of tumor size by RECIST using CT scans and MRIs is considered to be standard of care for staging cancer patients. Despite radiologic evidence of widespread disease, we document for the first time that patients were completely free of viable tumor. CASE PRESENTATION: Two patients with metastatic melanoma were treated with immune checkpoint inhibitors (ipilimumab/ nivolumab) and progressive metastases were detected on CT-scans performed shortly before histologic examinations. In both patients histologic assessment revealed a complete response with necrotic and scarred lesions free of tumor. One of the patients had started immunotherapy 20 months before with an initial partial response. CONCLUSIONS: This phenomenon of a concealed complete response can lead to overtreatment or unnecessary change in treatment. Thus, it is essential to raise awareness for it. Correct identification of responders to immune checkpoint inhibitor therapy is crucial to spare patients immune-mediated side effects and unnecessary as well as expensive treatment. Regression of metastases without decline in size, in these cases manifesting as complete responses, are probably more common than expected and identified to date. Until such responses can be readily identified by new imaging techniques, we recommend liberal biopsies for histologic assessment of progressive metastases in patients during and/or after immune checkpoint inhibitor therapy.
EVALuna2:34405

Concurrent interaction of DCs with CD4(+) and CD8(+) T cells improves secondary CTL expansion: It takes three to tango. - Hoyer, Stefanie; Prommersberger, Sabrina; Pfeiffer, Isabell; Schuler-Thurner, Beatrice; Schuler, Gerold; Dörrie, Jan; Schaft, Niels (European Journal of Immunology, 2014)
T-cell help is essential for CTL-memory formation. Nevertheless, it is unclear whether the continuous presence of CD4(+) T-helper (Th) cells is required during dendritic cell (DC)/CD8(+) T-cell encounters, or whether a DC will remember the helper signal after the Th cell has departed. This question is relevant for the design of therapeutic cancer vaccines. Therefore, we investigated how human DCs need to interact with CD4(+) T cells to mediate efficient repetitive CTL expansion in vitro. We established an autologous antigen-specific in vitro system with monocyte-derived DCs, as these are primarily used for cancer vaccination. Contrary to common belief, a sequential interaction of licensed DCs with CD8(+) T cells barely improved CTL expansion. In sharp contrast, simultaneous encounter of Th cells and CTLs with the same DC during the first in vitro encounter is a prerequisite for optimal subsequent CTL expansion in our in vitro system. These data suggest that, in contrast to DC maturation, the activation of DCs by Th cells, which is necessary for optimal CTL stimulation, is transient. This knowledge has significant implications for the design of new and more effective DC-based vaccination strategies. Furthermore, our in vitro system could be a valuable tool for preclinical immunotherapeutical studies.
EVALuna2:19507

Consensus nomenclature for CD8(+) T cell phenotypes in cancer - Apetoh, Lionel; Smyth, Mark J.; Drake, Charles G.; Abastado, Jean-Pierre; Apte, Ron N.; Ayyoub, Maha; Blay, Jean-Yves; Bonneville, Marc; Butterfield, Lisa H.; Caignard, Anne; Castelli, Chiara; Cavallo, Federica; et al. (OncoImmunology, 2015)
Whereas preclinical investigations and clinical studies have established that CD8(+) T cells can profoundly affect cancer progression, the underlying mechanisms are still elusive. Challenging the prevalent view that the beneficial effect of CD8(+) T cells in cancer is solely attributable to their cytotoxic activity, several reports have indicated that the ability of CD8(+) T cells to promote tumor regression is dependent on their cytokine secretion profile and their ability to self-renew. Evidence has also shown that the tumor microenvironment can disarm CD8(+) T cell immunity, leading to the emergence of dysfunctional CD8(+) T cells. The existence of different types of CD8(+) T cells in cancer calls for a more precise definition of the CD8(+) T cell immune phenotypes in cancer and the abandonment of the generic terms "pro-tumor" and "antitumor." Based on recent studies investigating the functions of CD8(+) T cells in cancer, we here propose some guidelines to precisely define the functional states of CD8(+) T cells in cancer.
EVALuna2:19573

Consensus statement on the diagnosis and treatment of sclerosing diseases of the skin, Part 1: Localized scleroderma, systemic sclerosis and overlap syndromes - Knobler, R.; Geroldinger-Simić, M.; Kreuter, A.; Hunzelmann, N.; Moinzadeh, P.; Rongioletti, F.; Denton, C. P.; Mouthon, L.; Cutolo, M.; Smith, V.; Gabrielli, A.; Bagot, M.; et al. (Journal of the European Academy of Dermatology and Venereology, 2024)
The term ‘sclerosing diseases of the skin’ comprises specific dermatological entities, which have fibrotic changes of the skin in common. These diseases mostly manifest in different clinical subtypes according to cutaneous and extracutaneous involvement and can sometimes be difficult to distinguish from each other. The present consensus provides an update to the 2017 European Dermatology Forum Guidelines, focusing on characteristic clinical and histopathological features, diagnostic scores and the serum autoantibodies most useful for differential diagnosis. In addition, updated strategies for the first- and advanced-line therapy of sclerosing skin diseases are addressed in detail. Part 1 of this consensus provides clinicians with an overview of the diagnosis and treatment of localized scleroderma (morphea), and systemic sclerosis including overlap syndromes.
CRIS-Team Scopus Importer:2024-04-12

Consensus statement on the diagnosis and treatment of sclerosing diseases of the skin, Part 2: Scleromyxoedema and scleroedema - Knobler, Robert; Geroldinger-Simić, Marija; Kreuter, Alexander; Hunzelmann, Nicolas; Moinzadeh, Pia; Rongioletti, Franco; Denton, Christopher; Mouthon, Luc; Cutolo, Maurizio; Smith, Vanessa; Gabrielli, Armando; Bagot, Martine; et al. (Journal of the European Academy of Dermatology and Venereology, 2024)
The term ‘sclerosing diseases of the skin’ comprises specific dermatological entities, which have fibrotic changes of the skin in common. These diseases mostly manifest in different clinical subtypes according to cutaneous and extracutaneous involvement and can sometimes be difficult to distinguish from each other. The present consensus provides an update to the 2017 European Dermatology Forum Guidelines, focusing on characteristic clinical and histopathological features, diagnostic scores and the serum autoantibodies most useful for differential diagnosis. In addition, updated strategies for the first- and advanced-line therapy of sclerosing skin diseases are addressed in detail. Part 2 of this consensus provides clinicians with an overview of the diagnosis and treatment of scleromyxoedema and scleroedema (of Buschke).
CRIS-Team Scopus Importer:2024-04-12

Contrary immediate effect of abatacept on skin and joint manifestations in psoriatic arthritis - Valor-Méndez, Larissa; Kleyer, Arnd; Schett, Georg; Manger, Bernhard; Sticherling, Michael (Rheumatology, 2021)
CRIS-Team Scopus Importer:2021-11-05

Conventional and three-dimensional photography as a tool to map distribution patterns of in-transit melanoma metastases on the lower extremity - Müller, Kilian; Berking, Carola; Voskens, Caroline; Heppt, Markus; Heinzerling, Lucie; Koch, Elias; Kramer, Rafaela; Merkel, Susanne; Schuler-Thurner, Beatrice; Schellerer, Vera; Steeb, Theresa; Wessely, Anja; et al. (Frontiers in Medicine, 2023)
Background: In melanoma, in-transit metastases characteristically occur at the lower extremity along lymphatic vessels. Objectives: The objective of this study was to evaluate conventional or three-dimensional photography as a tool to analyze in-transit metastasis pattern of melanoma of the lower extremity. In addition, we assessed risk factors for the development of in-transit metastases in cutaneous melanoma. Methods: In this retrospective, monocentric study first we compared the clinical data of all evaluable patients with in-transit metastases of melanoma on the lower extremity (n = 94) with melanoma patients without recurrence of disease (n = 288). In addition, based on conventional (n = 24) and three-dimensional photography (n = 22), we defined the specific distribution patterns of the in-transit metastases on the lower extremity. Results: Using a multivariate analysis we identified nodular melanoma, tumor thickness, and ulceration as independent risk factors to develop in-transit metastases ITM (n = 94). In patients with melanoma on the lower leg (n = 31), in-transit metastases preferentially developed along anatomically predefined lymphatic pathways. In contrast when analyzing in-transit metastases of melanoma on the foot (n = 15) no clear pattern could be visualized. In addition, no difference in distance between in-transit metastases and primary melanoma on the foot compared to the lower leg was observed using three-dimensional photography (n = 22). Conclusion: A risk-adapted follow-up of melanoma patients to detect in-transit metastases can be applied by knowledge of the specific lymphatic drainage of the lower extremity. Our current analysis suggests a more complex lymphatic drainage of the foot.
CRIS-Team Scopus Importer:2023-02-10
Keywords: 3D photography; in-transit metastasis; lower extremity; lymphatic pathways; melanoma

Cooperative gene regulation by microRNA pairs and their identification using a computational workflow - Schmitz, Ulf; Lai, Xin; Winter, Felix; Wolkenhauer, Olaf; Vera González, Julio; Gupta, Shailendra K. (Nucleic Acids Research, 2014)
MicroRNAs (miRNAs) are an integral part of gene regulation at the post-transcriptional level. Recently, it has been shown that pairs of miRNAs can repress the translation of a target mRNA in a cooperative manner, which leads to an enhanced effectiveness and specificity in target repression. However, it remains unclear which miRNA pairs can synergize and which genes are target of cooperative miRNA regulation. In this paper, we present a computational workflow for the prediction and analysis of cooperating miRNAs and their mutual target genes, which we refer to as RNA triplexes. The workflow integrates methods of miRNA target prediction; triplex structure analysis; molecular dynamics simulations and mathematical modeling for a reliable prediction of functional RNA triplexes and target repression efficiency. In a case study we analyzed the human genome and identified several thousand targets of cooperative gene regulation. Our results suggest that miRNA cooperativity is a frequent mechanism for an enhanced target repression by pairs of miRNAs facilitating distinctive and fine-tuned target gene expression patterns. Human RNA triplexes predicted and characterized in this study are organized in a web resource at www.sbi.uni-rostock.de/triplexrna/.
EVALuna2:19517

Corrigendum: Multiplicity of Mathematical Modeling Strategies to Search for Molecular and Cellular Insights into Bacteria Lung Infection - Cantone, Martina; Santos, Guido; Wentker, Pia; Lai, Xin; Vera, Julio (Frontiers in Physiology, 2017)
[This corrects the article on p. 645 in vol. 8, PMID: 28912729.].
EVALuna2:35402
Keywords: Systems biology; Systems medicine; ODE models; Stochastic modeling; Boolean network; Agent-based modeling; Mathematical modeling; Lung infection

COVID-19 and immune-mediated inflammatory diseases: effect of disease and treatment on COVID-19 outcomes and vaccine responses - Fagni, Filippo; Simon, David; Tascilar, Koray; Schoenau, Verena; Sticherling, Michael; Neurath, Markus; Schett, Georg (The Lancet Rheumatology, 2021)
At the beginning of the COVID-19 pandemic, patients with immune-mediated inflammatory diseases were considered to be at high risk for SARS-CoV-2 infection and the development of severe COVID-19. Data collected over the past year, however, suggest that a diagnosis of inflammatory arthritis, psoriasis, or inflammatory bowel diseases does not increase risk for SARS-CoV-2 infection or severe COVID-19 compared with people without these diseases. Furthermore, substantial data suggest that certain medications frequently used in patients with immune-mediated inflammatory diseases, in particular cytokine inhibitors, might even lower the risk for severe COVID-19. Conversely, glucocorticoids and potentially B-cell-depleting treatments seem to worsen COVID-19 outcomes. Additionally, the first data on SARS-CoV-2 vaccination in patients with these diseases suggest that tolerability of vaccination in patients with immune-mediated inflammatory diseases is good, although the immune response to vaccination can be somewhat reduced in this patient group, particularly those taking methotrexate or CD20-targeted treatment.
CRIS-Team Scopus Importer:2021-10-01

COVID-19 and immunological regulations – from basic and translational aspects to clinical implications - Schoen, Michael P.; Berking, Carola; Biedermann, Tilo; Buhl, Timo; Erpenbeck, Luise; Eyerich, Kilian; Eyerich, Stefanie; Ghoreschi, Kamran; Goebeler, Matthias; Ludwig, Ralf J.; Schaekel, Knut; Schilling, Bastian; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2020)
The COVID-19 pandemic caused by SARS-CoV-2 has far-reaching direct and indirect medical consequences. These include both the course and treatment of diseases. It is becoming increasingly clear that infections with SARS-CoV-2 can cause considerable immunological alterations, which particularly also affect pathogenetically and/or therapeutically relevant factors. Against this background we summarize here the current state of knowledge on the interaction of SARS-CoV-2/COVID-19 with mediators of the acute phase of inflammation (TNF, IL-1, IL-6), type 1 and type 17 immune responses (IL-12, IL-23, IL-17, IL-36), type 2 immune reactions (IL-4, IL-13, IL-5, IL-31, IgE), B-cell immunity, checkpoint regulators (PD-1, PD-L1, CTLA4), and orally druggable signaling pathways (JAK, PDE4, calcineurin). In addition, we discuss in this context non-specific immune modulation by glucocorticosteroids, methotrexate, antimalarial drugs, azathioprine, dapsone, mycophenolate mofetil and fumaric acid esters, as well as neutrophil granulocyte-mediated innate immune mechanisms. From these recent findings we derive possible implications for the therapeutic modulation of said immunological mechanisms in connection with SARS-CoV-2/COVID-19. Although, of course, the greatest care should be taken with patients with immunologically mediated diseases or immunomodulating therapies, it appears that many treatments can also be carried out during the COVID-19 pandemic; some even appear to alleviate COVID-19.
CRIS-Team Scopus Importer:2020-08-14

COVID-19 and implications for dermatological and allergological diseases - Buhl, Timo; Beissert, Stefan; Gaffal, Evelyn; Goebeler, Matthias; Hertl, Michael; Mauch, Cornelia; Reich, Kristian; Schmidt, Enno; Schoen, Michael P.; Sticherling, Michael; Sunderkoetter, Cord; Traidl-Hoffmann, Claudia; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2020)
COVID-19, caused by the coronavirus SARS-CoV-2, has become pandemic. A further level of complexity opens up as soon as we look at diseases whose pathogenesis and therapy involve different immunological signaling pathways, which are potentially affected by COVID-19. Medical treatments must often be reassessed and questioned in connection with this infection. This article summarizes the current knowledge of COVID-19 in the light of major dermatological and allergological diseases. It identifies medical areas lacking sufficient data and draws conclusions for the management of our patients during the pandemic. We focus on common chronic inflammatory skin diseases with complex immunological pathogenesis: psoriasis, eczema including atopic dermatitis, type I allergies, autoimmune blistering and inflammatory connective tissue diseases, vasculitis, and skin cancers. Since several other inflammatory skin diseases display related or comparable immunological reactions, clustering of the various inflammatory dermatoses into different disease patterns may help with therapeutic decisions. Thus, following these patterns of skin inflammation, our review may supply treatment recommendations and thoughtful considerations for disease management even beyond the most frequent diseases discussed here.
CRIS-Team Scopus Importer:2020-08-07

COVID-19: risk for cytokine targeting in chronic inflammatory diseases? - Schett, Georg; Sticherling, Michael; Neurath, Markus (Nature Reviews Immunology, 2020)
CRIS-Team Scopus Importer:2020-04-28

COVID-19 und Auswirkungen auf dermatologische und allergologische Erkrankungen - Buhl, Timo; Beissert, Stefan; Gaffal, Evelyn; Goebeler, Matthias; Hertl, Michael; Mauch, Cornelia; Reich, Kristian; Schmidt, Enno; Schön, Michael P.; Sticherling, Michael; Sunderkötter, Cord; Traidl-Hoffmann, Claudia; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2020)
CRIS-Team Scopus Importer:2020-08-28

COVID-19 und Immunregulation – von grundlegenden und translationalen Aspekten zu klinischen Implikationen - Schön, Michael P.; Berking, Carola; Biedermann, Tilo; Buhl, Timo; Erpenbeck, Luise; Eyerich, Kilian; Eyerich, Stefanie; Ghoreschi, Kamran; Goebeler, Matthias; Ludwig, Ralf J.; Schäkel, Knut; Schilling, Bastian; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2020)
CRIS-Team Scopus Importer:2020-08-28

C-reactive protein as an early marker of immune-related adverse events - Abolhassani, Amir-Reza; Schuler, Gerold; Kirchberger, Michael Constantin; Heinzerling, Lucie (Journal of Cancer Research and Clinical Oncology, 2019)
Purpose Immune checkpoint inhibitors (ICIs) are effective against a wide variety of cancers. However, they also induce a plethora of unique immune-related adverse events (irAEs). Since for many organ systems symptoms can be unspecific, differential diagnosis with progression of disease or infection may be difficult. C-reactive protein (CRP) has been suggested as a marker for infection. The purpose of this study was to evaluate the diagnostic value of CRP in differentiating infectious causes from autoimmune side effects induced by ICIs. Methods In order to investigate the role of CRP in irAEs, we screened our patient data base. Only events with full infectious workup were included. In total 88 events of irAEs in 37 melanoma patients were analyzed. CRP levels before and during irAEs were evaluated. Statistical analyses were conducted using the Chi-square test for categorical variables. Results At the onset of irAE, CRP rose in 93% of cases to a mean of 52.7 mg/L (CI 35.1-70.3) from 8.4 mg/L at baseline (normal < 5 mg/L) (P < 0.0001). Other causes of CRP elevation including infectious diseases were excluded, and procalcitonin (PCT) levels were normal in 92% of events. Importantly, in 42% of cases CRP elevations preceded clinical symptoms. Conclusion CRP elevation can predict the onset of irAEs in patients treated with ICIs in the absence of infectious disease.
CRIS-Team WoS Importer:2019-10-04

Crusted Nodules on the Lower Left Arm in a Traveller Returning from South America: A Quiz. Furuncular myiasis - Uslu, Ugur; Erdmann, Michael; Schliep, Stefan; Sticherling, Michael (Acta Dermato-Venereologica, 2018)
EVALuna2:34409

Cryopreservation impairs 3-D migration and cytotoxicity of natural killer cells - Mark, Christoph; Czerwinski, Tina; Roessner, Susanne; Mainka, Astrid; Hörsch, Franziska; Heublein, Lucas; Winterl, Alexander; Sanokowski, Sebastian; Richter, Sebastian; Bauer, Nina; Angelini, Thomas E.; Schuler, Gerold; et al. (Nature Communications, 2020)
Natural killer (NK) cells are important effector cells in the immune response to cancer. Clinical trials on adoptively transferred NK cells in patients with solid tumors, however, have thus far been unsuccessful. As NK cells need to pass stringent safety evaluation tests before clinical use, the cells are cryopreserved to bridge the necessary evaluation time. Standard degranulation and chromium release cytotoxicity assays confirm the ability of cryopreserved NK cells to kill target cells. Here, we report that tumor cells embedded in a 3-dimensional collagen gel, however, are killed by cryopreserved NK cells at a 5.6-fold lower rate compared to fresh NK cells. This difference is mainly caused by a 6-fold decrease in the fraction of motile NK cells after cryopreservation. These findings may explain the persistent failure of NK cell therapy in patients with solid tumors and highlight the crucial role of a 3-D environment for testing NK cell function.
CRIS-Team Scopus Importer:2020-10-23

Cryopreservation reduces the Ability to migrate and the Cytotoxicity of natural Killer Cells in 3D: Possible Effects on cellular Immunotherapy - Mark, Christoph; Czerwinksi, T.; Roessner, S.; Mainka, Astrid; Hoersch, F.; Heublein, L.; Winterl, Alexander; Sanokowski, Sebastian; Richter, S.; Bauer, N.; Angelini, T.; Schuler, Gerold; et al. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2020)
CRIS-Team WoS Importer:2020-09-11

Crystal Structure of the Extracellular Domain of the Human Dendritic Cell Surface Marker CD83 - Heilingloh, Christiane; Klingl, Stefan; Egerer-Sieber, Claudia; Schmid, Benedikt; Weiler, Sigrid; Mühl-Zürbes, Petra; Hofmann, Jörg; Stump, Joachim; Sticht, Heinrich; Kummer, Mirko; Steinkasserer, Alexander; Muller, Yves (Journal of Molecular Biology, 2017)
Keywords: homotypic interactions; immune co-stimulation and -suppression; structure–function relationships; V-set Ig-domain; X-ray crystallography

CSPG4-Specific CAR T Cells for High-Risk Childhood B Cell Precursor Leukemia - Harrer, Dennis C.; Schuler, Gerold; Dörrie, Jan; Schaft, Niels (International Journal of Molecular Sciences, 2019)
The advent of CD19-specific chimeric antigen receptor (CAR) T cells has proven to be a powerful asset in the arsenal of cancer immunotherapy of acute lymphoblastic leukemia and certain B cell lymphomas. However, a sizable portion of patients treated with CD19-CAR T cells relapse with CD19-negative cancer cells, necessitating the quest for back-up antigens. Chondroitin sulfate proteoglycan 4 (CSPG4) expression has been reported on leukemic blasts bearing the ill-fated MLL 11q23 rearrangement. We aimed at exploring the use of CSPG4-specific CAR T cells against mixed-lineage leukemia (MLL)-rearranged leukemic blasts, using the precursor B cell leukemia cell line KOPN8 (MLL-MLLT1 translocation) as a model. First, we confirmed CSPG4 expression on KOPN8 cells. Bulk T cells electroporated with mRNA encoding a CSPG4-specific CAR upregulated activation markers and secreted the Th1 cytokines TNF and IFNγ in an antigen-specific manner upon co-culture with KOPN8 cells. More importantly, CSPG4-specific CAR T cells evinced specific degranulation towards KOPN8 cells and specifically lysed KOPN8 target cells in chromium lysis experiments. CSPG4 is a well-established CAR target in cutaneous melanoma. Here, we provide proof-of-principle data for the use of CSPG4-specific CAR T cells against MLL-translocated leukemias.
CRIS-Team Scopus Importer:2019-07-09
Keywords: back-up target antigen; CAR T cells; CSPG4; high-risk childhood B cell precursor leukemia; MLL-translocated leukemias

Curatopes Melanoma: A Database of Predicted T-cell Epitopes from Overly Expressed Proteins in Metastatic Cutaneous Melanoma. - Lischer, Christopher; Eberhardt, Martin; Jaitly, Tanushree; Schinzel, Cornelia; Schaft, Niels; Dörrie, Jan; Schuler, Gerold; Vera González, Julio (Cancer Research, 2019)
Therapeutic anticancer vaccination has been adapted as an immunotherapy in several solid tumors. However, the selection of promising candidates from the total quantity of possible epitopes poses a challenge to clinicians and bioinformaticians alike, and very few epitopes have been tested in experimental or clinical settings to validate their efficacy. Here, we present a comprehensive database of predicted nonmutated peptide epitopes derived from genes that are overly expressed in a group of 32 melanoma biopsies compared with healthy tissues and that were filtered against expression in a curated list of survival-critical tissues. We hypothesize that these "self-tolerant" epitopes have two desirable properties: they do not depend on mutations, being immediately applicable to a large patient collective, and they potentially cause fewer autoimmune reactions. To support epitope selection, we provide an aggregated score of expected therapeutic efficiency as a shortlist mechanism. The database has applications in facilitating epitope selection and trial design and is freely accessible at https://www.curatopes.com. SIGNIFICANCE: A database is presented that predicts and scores antitumor T-cell epitopes, with a focus on tolerability and avoidance of severe autoimmunity, offering a supplementary epitope set for further investigation in immunotherapy.
CRIS-Team Scopus Importer:2019-10-22

Cutaneous, gastrointestinal, hepatic, endocrine, and renal side-effects of anti-PD-1 therapy - Hofmann, Lars; Forschner, Andrea; Loquai, Carmen; Goldinger, Simone M.; Zimmer, Lisa; Ugurel, Selma; Schmidgen, Maria I.; Gutzmer, Ralf; Utikal, Jochen S.; Goeppner, Daniela; Hassel, Jessica C.; Meier, Friedegund; et al. (European Journal of Cancer, 2016)
Anti-programmed cell death receptor-1 (PD-1) antibodies represent an effective treatment option for metastatic melanoma as well as for other cancer entities. They act via blockade of the PD-1 receptor, an inhibitor of the T-cell effector mechanisms that limit immune responses against tumours. As reported for ipilimumab, the anti-PD-1 antibodies pembrolizumab and nivolumab can induce immune-related adverse events (irAEs). These side-effects affect skin, gastrointestinal tract, liver, endocrine system and other organ systems. Since life-threatening and fatal irAEs have been reported, adequate diagnosis and management are essential.In total, 496 patients with metastatic melanoma from 15 skin cancer centers were treated with pembrolizumab or nivolumab; 242 side-effects were described in 138 patients. In 116 of the 138 patients, side-effects affected the skin, gastrointestinal tract, liver, endocrine, and renal system. Rare side-effects included diabetes mellitus, lichen planus, and pancreas insufficiency due to pancreatitis.Anti-PD1 antibodies can induce a plethora of irAEs. The knowledge of them will allow prompt diagnosis and improve the management resulting in decreased morbidity.
EVALuna2:19570

Cu, Zn doped borate bioactive glasses: antibacterial efficacy and dose-dependent in vitro modulation of murine dendritic cells - Schuhladen, Katharina; Stich, Lena; Schmidt, Jochen; Steinkasserer, Alexander; Boccaccini, Aldo R.; Zinser, Elisabeth (Biomaterials Science, 2020)
Among emerging biomaterials, bioactive glasses (BGs) are being widely explored for various applications in tissue engineering. However, the effects of BGs (in particular BG ionic dissolution products) on immune cells and specifically on dendritic cells (DCs), which are the most potent antigen-presenting cells of the immune system, have not been previously investigated in detail. Such interactions between BGs and DCs must be assessed as a novel biocompatibility criterion for biomaterials, since, with the increased application possibilities of BGs, the modulation of the immune system may induce potential complications and undesired side effects. Indeed, the effects of BG exposure on specific immune cells are not well understood. Thus, in this study we investigated, for the first time, the effect of borate BGs doped with biologically active ions on specific immune cells, such as DCs and we further investigated the antibacterial properties of these borate BGs. The compositions of the borate BGs (B3) were based on the well-known 13-93 (silicate) composition by replacing silica with boron trioxide and by adding copper (3 wt%) and/or zinc (1 wt%). By performing an agar diffusion test, the antibacterial effect depending on the compositions of the borate BGs could be proved. Furthermore we found a dose-dependent immune modulation of DCs after treatment with borate BGs, especially when the borate BGs contained Zn and/or Cu. Depending on the ion concentration and the rise in pH, the phenotype and function of DCs were modified. While at low doses B3 and Zn-doped B3 BGs had no impact on DC viability, Cu containing BGs strongly affected cell viability. Furthermore, the surface expression of DC-specific activation markers, such as the major histocompatibility complex (MHC)-II, CD86 and CD80, was modulated. In addition, also DC mediated T-cell proliferation was remarkably reduced when treated with high doses of B3-Cu and B3-Cu-Zn BGs. Interestingly, the release of inflammatory cytokines increased after incubation with B3 and B3-Zn BGs compared to mock-treated DCs. Considering the essential role of DCs in the modulation and regulation of immune responses, these findings provide first evidence of phenotypic and functional consequences regarding the exposure of DCs to BGs in vitro.
CRIS-Team Scopus Importer:2020-04-28

CXCR4 blockade reduces the severity of murine heart allograft rejection by plasmacytoid dendritic cell-mediated immune regulation - Fu, Jian; Lehmann, Christian; Wang, Xinning; Wahlbuhl, Mandy; Allabauer, Ida; Wilde, Benjamin; Amon, Lukas; Dolff, Sebastian; Cesnjevar, Robert; Kribben, Andreas; Wölfle, Joachim; Rascher, Wolfgang; et al. (Scientific Reports, 2021)
Allograft-specific regulatory T cells (Treg cells) are crucial for long-term graft acceptance after transplantation. Although adoptive Treg cell transfer has been proposed, major challenges include graft-specificity and stability. Thus, there is an unmet need for the direct induction of graft-specific Treg cells. We hypothesized a synergism of the immunotolerogenic effects of rapamycin (mTOR inhibition) and plerixafor (CXCR4 antagonist) for Treg cell induction. Thus, we performed fully-mismatched heart transplantations and found combination treatment to result in prolonged allograft survival. Moreover, fibrosis and myocyte lesions were reduced. Although less CD3+ T cell infiltrated, higher Treg cell numbers were observed. Noteworthy, this was accompanied by a plerixafor-dependent plasmacytoid dendritic cells-(pDCs)-mobilization. Furthermore, in vivo pDC-depletion abrogated the plerixafor-mediated Treg cell number increase and reduced allograft survival. Our pharmacological approach allowed to increase Treg cell numbers due to pDC-mediated immune regulation. Therefore pDCs can be an attractive immunotherapeutic target in addition to plerixafor treatment.
CRIS-Team Scopus Importer:2021-12-24

CXCR4-SDF1 alpha Blockade Reduces the Severity of Murine Heart Allograft Rejection - Fu, J.; Wahlbuhl, Mandy; Wang, X.; Wilde, B.; Jing, L.; Kribben, A.; Hoyer, P.; Lehmann, C. H. K.; Dudziak, Diana; Witzke, O.; Hoerning, A. (2017)
EVALuna2:34369

DC subset–specific induction of T cell responses upon antigen uptake via Fcγ receptors in vivo - Lehmann, Christian; Baranska, Anna; Heidkamp, Gordon Frederik; Heger, Lukas; Neubert, Kirsten; Lühr, Jennifer; Hoffmann, Alana; Reimer, Katharina; Brückner, Christin; Beck, Simone; Seeling, Michaela; Kießling, Melissa; et al. (Journal of Experimental Medicine, 2017)
Dendritic cells (DCs) are efficient antigen-presenting cells equipped with various cell surface receptors for the direct or indirect recognition of pathogenic microorganisms. Interestingly, not much is known about the specific expression pattern and function of the individual activating and inhibitory Fcγ receptors (FcγRs) on splenic DC subsets in vivo and how they contribute to the initiation of T cell responses. By targeting antigens to select activating and the inhibitory FcγR in vivo, we show that antigen uptake under steady-state conditions results in a short-term expansion of antigen-specific T cells, whereas under inflammatory conditions especially, the activating FcγRIV is able to induce superior CD4+ and CD8+ T cell responses. Of note, this effect was independent of FcγR intrinsic activating signaling pathways. Moreover, despite the expression of FcγRIV on both conventional splenic DC subsets, the induction of CD8+ T cell responses was largely dependent on CD11c+CD8+ DCs, whereas CD11c+CD8− DCs were critical for priming CD4+ T cell responses.<br
Keywords: Infectious disease and host defense; Innate immunity and inflammation; Tolerance

Decitabine-Mediated Upregulation of CSPG4 in Ovarian Carcinoma Cells Enables Targeting by CSPG4-Specific CAR-T Cells - Harrer, Dennis Christoph; Schenkel, Charlotte; Berking, Carola; Herr, Wolfgang; Abken, Hinrich; Dörrie, Jan; Schaft, Niels (Cancers, 2022)
Simple Summary Cancer therapy by specifically redirected T cells has revolutionized the field of oncology. However, the repertoire of targetable antigens is small. Here, we use the FDA-approved drug decitabine to upregulate the surface antigen CSPG4 on CSPG4-negative ovarian carcinoma cells. By optimizing decitabine dosing, we converted more than 50% of treated ovarian carcinoma cells to CSPG4-positive cells. Importantly, CSPG4 is a very well-established target antigen in melanoma, and we could previously demonstrate that T cells engineered to target CSPG4 could reliably kill CSPG4-positive melanoma cells. Using CSPG4-specific T cells, we demonstrate CSPG4-directed killing of decitabine-treated ovarian carcinoma cells, thereby adding CSPG4 to the repertoire of target antigens for ovarian cancer. The addition of CAR-T cells to the armamentarium of immunotherapy revigorated the field of oncology by inducing long-lasting remissions in patients with relapsing/refractory hematological malignancies. Nevertheless, in the lion's share of patients diagnosed with solid tumors, CAR-T-cell therapy so far failed to demonstrate satisfactory anti-tumor activity. A crucial cause of resistance against the antigen-specific attack of CAR-T cells is predicated on the primary or secondary absence of suitable target antigens. Thus, the necessity to create a broad repertoire of different target antigens is vital. We aimed to evaluate the potential of the well-established melanoma antigen chondroitin sulfate proteoglycan 4 (CSPG4) as an inducible antigen in ovarian cancer cells, using CSPG4-negative SKOV-3 ovarian cancer cells as a model. Based on the hypomethylating activity of the FDA-approved drug decitabine, we refined a protocol to upregulate CSPG4 in the majority of decitabine-treated SKOV-3 cells. CSPG4-specific CAR-T cells generated by mRNA-electroporation showed CSPG4-directed cytokine secretion and cytotoxicity towards decitabine-treated SKOV-3. Another ovarian cancer cell line (Caov-3) and the neoplastic cell line 293T behaved similar. In aggregate, we generated proof-of-concept data paving the way for the further exploration of CSPG4 as an inducible antigen for CAR-T cells in ovarian cancer.
CRIS-Team WoS Importer:2022-11-11

Deepnapsi: Deep Learning for Nail Psoriasis Prediction - Folle, Lukas; Fenzl, Pauline; Fagni, Filippo; Thies, Mareike; Christlein, Vincent; Meder, Christine; Sticherling, Michael; Simon, David; Schett, Georg; Maier, Andreas; Kleyer, Arnd (Proceedings - International Symposium on Biomedical Imaging, 2023)
Nail psoriasis is a frequent condition that is associated with a severe course of rheumatic diseases. Thus, it may be used to adapt the therapy of patients according to the change of nail psoriasis. The nail psoriasis severity index (NAPSI) was developed to measure this condition. Nevertheless, there is a lack of application for the NAPSI, as its use in the clinic is too time-consuming. In this work, we propose the use of advancements in deep learning in a new domain by recording, annotating, and predicting the NAPSI based on photographs of the hand and term our approach DeepNAPSI. This allows not just the automated recording of the NAPSI in the clinic, but also patient self-assessment from home. Our method achieved an area-under-receiver-operator-characteristic curve (AUROC) of 0.83 and 0.86 for macro and micro averaging, respectively, and a mean absolute error of 0.55.
CRIS-Team Scopus Importer:2023-10-06
Keywords: Deep Learning; Mobile device; Nail psoriasis; Precision medicine

DeepNAPSI multi-reader nail psoriasis prediction using deep learning - Folle, Lukas; Fenzl, Pauline; Fagni, Filippo; Thies, Mareike; Christlein, Vincent; Meder, Christine; Simon, David; Minnopoulou, Ioanna; Sticherling, Michael; Schett, Georg; Maier, Andreas; Kleyer, Arnd (Nature Scientific Reports, 2023)
Nail psoriasis occurs in about every second psoriasis patient. Both, finger and toe nails can be affected and also severely destroyed. Furthermore, nail psoriasis is associated with a more severe course of the disease and the development of psoriatic arthritis. User independent quantification of nail psoriasis, however, is challenging due to the heterogeneous involvement of matrix and nail bed. For this purpose, the nail psoriasis severity index (NAPSI) has been developed. Experts grade pathological changes of each nail of the patient leading to a maximum score of 80 for all nails of the hands. Application in clinical practice, however, is not feasible due to the time-intensive manual grading process especially if more nails are involved. In this work we aimed to automatically quantify the modified NAPSI (mNAPSI) of patients using neuronal networks retrospectively. First, we performed photographs of the hands of patients with psoriasis, psoriatic arthritis, and rheumatoid arthritis. In a second step, we collected and annotated the mNAPSI scores of 1154 nail photos. Followingly, we extracted each nail automatically using an automatic key-point-detection system. The agreement among the three readers with a Cronbach’s alpha of 94% was very high. With the nail images individually available, we trained a transformer-based neural network (BEiT) to predict the mNAPSI score. The network reached a good performance with an area-under-receiver-operator-curve of 88% and an area-under precision-recall-curve (PR-AUC) of 63%. We could compare the results with the human annotations and achieved a very high positive Pearson correlation of 90% by aggregating the predictions of the network on the test set to the patient-level. Lastly, we provided open access to the whole system enabling the use of the mNAPSI in clinical practice.

Deficiency of the Intramembrane Protease SPPL2a Alters Antimycobacterial Cytokine Responses of Dendritic Cells - Gradtke, Ann-Christine; Mentrup, Torben; Lehmann, Christian; Cabrera-Cabrera, Florencia; Desel, Christine; Okakpu, Darian; Assmann, Maike; Dalpke, Alexander; Schaible, Ulrich E.; Dudziak, Diana; Schroder, Bernd (Journal of Immunology, 2021)
Signal peptide peptidase-like 2a (SPPL2a) is an aspartyl intramembrane protease essential for degradation of the invariant chain CD74. In humans, absence of SPPL2a leads to Mendelian susceptibility to mycobacterial disease, which is attributed to a loss of the dendritic cell (DC) subset conventional DC2. In this study, we confirm depletion of conventional DC2 in lymphatic tissues of SPPL2a(-/-) mice and demonstrate dependence on CD74 using SPPL2a(-/-) CD74(-1-) mice. Upon contact with mycobacteria, SPPL2a(-/-) bone marrow-derived DCs show enhanced secretion of IL-1 beta, whereas production of IL-10 and IFN-beta is reduced. These effects correlated with modulated responses upon selective stimulation of the pattern recognition receptors TLR4 and Dectin-1. In SPPL2a(-/-) bone marrow-derived DCs, Dectin-1 is redistributed to endosomal compartments. Thus, SPPL2a deficiency alters pattern recognition receptor pathways in a CD74-dependent way, shifting the balance from anti- to proinflammatory cytokines in antimycobacterial responses. We propose that in addition to the DC reduction, this altered DC functionality contributes to Mendelian susceptibility to mycobacterial disease upon SPPL2a deficiency.
CRIS-Team WoS Importer:2021-01-15

Delay in antibiotic therapy results in fatal disease outcome in murine pneumococcal pneumonia - Berger, Sarah; Goekeri, Cengiz; Gupta, Shishir K.; Vera, Julio; Dietert, Kristina; Behrendt, Ulrike; Lienau, Jasmin; Wienhold, Sandra-Maria; Gruber, Achim D.; Suttorp, Norbert; Witzenrath, Martin; Nouailles, Geraldine (Critical Care, 2018)
BACKGROUND: Community-acquired pneumonia (CAP) remains a major cause of death worldwide. Mechanisms underlying the detrimental outcome despite adequate antibiotic therapy and comorbidity management are still not fully understood. METHODS: To model timely versus delayed antibiotic therapy in patients, mice with pneumococcal pneumonia received ampicillin twice a day starting early (24 h) or late (48 h) after infection. Clinical readouts and local and systemic inflammatory mediators after early and late antibiotic intervention were examined. RESULTS: Early antibiotic intervention rescued mice, limited clinical symptoms and restored fitness, whereas delayed therapy resulted in high mortality rates. Recruitment of innate immune cells remained unaffected by antibiotic therapy. However, both early and late antibiotic intervention dampened local levels of inflammatory mediators in the alveolar spaces. Early treatment protected from barrier breakdown, and reduced levels of vascular endothelial growth factor (VEGF) and perivascular and alveolar edema formation. In contrast, at 48 h post infection, increased pulmonary leakage was apparent and not reversed by late antibiotic treatment. Concurrently, levels of VEGF remained high and no beneficial effect on edema formation was evident despite therapy. Moreover, early but not late treatment protected mice from a vast systemic inflammatory response. CONCLUSIONS: Our data show that only early antibiotic therapy, administered prior to breakdown of the alveolar-capillary barrier and systemic inflammation, led to restored fitness and rescued mice from fatal streptococcal pneumonia. The findings highlight the importance of identifying CAP patients prior to lung barrier failure and systemic inflammation and of handling CAP as a medical emergency.
EVALuna2:34760

Dendritic cells are involved in the resolution of inflammation by IVIg in arthritis - Lehmann, Christian; Amon, Lukas; Seichter, A.; Brückner, Christin; Altmann, Leon; Heger, Lukas; Heger, L.; Ravetch, J. V.; Nimmerjahn, Falk; Dudziak, Diana (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Dendritic Cells Control Regulatory T Cell Function Required for Maintenance of Intestinal Tissue Homeostasis - Hilpert, Cornelia; Sitte, Selina; Arnold, Harald; Lehmann, Christian; Dudziak, Diana; Mattner, Jochen; Vöhringer, David (Journal of Immunology, 2019)
Dendritic cells (DCs) together with regulatory T cells (Tregs) are essential mediators of immune homeostasis. Disruption of function or frequency of either cell type can lead to fatal autoimmunity. We previously described that mice constitutively lacking DCs (∆DC) develop autoimmunity characterized by reduced body weight, autoantibodies, and pronounced intestinal inflammation. In this study, we show that lack of DCs leads to an altered gene expression profile in peripheral but not thymic Tregs with increased expression of inhibitory receptors. The suppressive function of Tregs from ΔDC mice was impaired in T cell cocultures. In a model of transfer colitis, Tregs from ∆DC mice were only functional in the presence of DCs in recipient mice. Lack of MHC class II on DCs also resulted in upregulation of inhibitory receptors on Tregs, reduced body weight, and elevated serum IgA levels. Further analysis of the IgA response revealed an expansion of IgA+ germinal center B cells and plasma cells in mesenteric lymph nodes and more IgA-coated commensal bacteria in feces of ∆DC mice. Thus, we show a critical role for DCs to establish intestinal homeostasis by regulating Treg function for prevention of spontaneous inflammation.
CRIS-Team Scopus Importer:2019-11-29

Dermatological Moulages in Germany- Comparison of Two Representative Collections - Sticherling, Michael (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-05-17

Dermatological Quality of Life and Neurodermatitis: Results from the German Neurodermatitis Registry TREATgermany - Helmert, C.; Haufe, E.; Abraham, S.; Heratizadeh, A.; Harder, I.; Kleinheinz, A.; Wollenberg, A.; Wiemers, F.; Weisshaar, E.; Augustin, M.; Zink, A.; Von Kiedrowski, R.; et al. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2021)
CRIS-Team WoS Importer:2021-04-16

Dermatology Part 2: Ichthyoses and Psoriasis - Sticherling, Michael (Handbook of Experimental Pharmacology, 2020)
Acute and chronic inflammatory skin diseases are frequent in childhood and may be hereditary or acquired. In this context, ichthyosis is rather a symptom than a defined disease as scaling is accompanying a number of disorders and is mostly consequence of a disrupted skin barrier. Ichthyosis is the basic pathogenic trait of atopic dermatitis but on the other side describes a group of rare hereditary diseases. These may only affect the skin or comprise several internal symptoms as well. Psoriasis is another scaling inflammatory skin disease with classical sharply demarcated erythematosquamous plaques and with a distinct immunogenetic background. It comprises several clinical subsets, some of which are characteristic for children and demanding in both diagnostics and therapy. Comorbid diseases point towards a systemic inflammatory response and require ample, often systemic treatment. Both ichthyosis and psoriasis may be topically treated including emollients with and without humectants as well as active agents like corticosteroids, vitamin D derivatives, and calcineurin inhibitors. In moderate to severe diseases, systemic treatment should be applied using methotrexate, ciclosporin, fumarates, or biologics. Their use should be critically discussed yet if necessary and indicated be applied to avoid chronic physical and psychological damage to the affected children.
EVALuna2:212856

Dermatomyositis- a rare, but important Disease between Dermatology and Internal Medicine - Sell, S.; Sticherling, Michael (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-05-17

Design and Implementation of an ETL-Process to Transfer Wound-Related Data into a Standardized Common Data Model - Przysucha, Mareike; Hüsers, Jens; Liberman, Daniil; Kersten, Oliver; Schlüter, Aphrodite; Fraas, Sebastian; Busch, Dorothee; Moelleken, Maurice; Erfurt-Berge, Cornelia; Dissemond, Joachim; Hübner, Ursula (German Medical Data Sciences 2023 – Science. Close to People., 2023)
For observational studies, which are relevant especially for chronic conditions like chronic wounds, the Observational Medical Outcomes Partnership (OMOP) Common Data Model (CDM) offers a standardized database schema. In this study an ETL process for the transition of wound related data was developed. After understanding the data in general and mapping the relevant codes to concepts available in OMOP, the ETL process was implemented. In a first step, a generic algorithm to convert data to a csv format was implemented in Java. The resulting csv file was then processed within KNIME to be loaded into an OMOP CDM conformant database. During the whole ETL process, HL7 FHIR CodeSystem and ConceptMap resources were used for coding and mapping. First clinical test cases to retrieve data were successfully processed as an example to demonstrate the feasibility and usefulness. They concerned wound size at the first visit and the main issues of patients in the wound quality of life questionnaire (n = 24). In general, the ETL process worked well, yet some challenges arose, like post coordinated SNOMED codes or conditions, which might occur more than once.
CRIS-Team Scopus Importer:2023-09-22
Keywords: ETL Process; OMOP CDM; Wound Care

Detection and Analysis of Critical Dynamic Properties of Oligodendrocyte Differentiation - Nikolov, Svetoslav G.; Wolkenhauer, Olaf; Nenov, Momchil; Vera González, Julio (Mathematics, 2022)
In this paper, we derive a four-dimensional ordinary differential equation (ODE) model representing the main interactions between Sox9, Sox10, Olig2 and several miRNAs, which drive the process of (olygodendrocyte) differentiation. We utilize the Lyapunov-Andronov theory to analyze its dynamical properties. Our results indicated that the strength of external signaling (morphogenic gradients shh and bmp), and the transcription rate of mOlig2 explain the existence of stable and unstable (sustained oscillations) behavior in the system. Possible biological implications are discussed.
CRIS-Team WoS Importer:2022-09-09

Detection and Assessment of epidermotropic, pigmented Melanoma Metastases under Therapy using 3D Whole-Body Photography - Erdmann, M.; Toussaint, Frédéric; Hornung, Annkathrin; Heinzerling, Lucie; Berking, Carola; Schliep, S. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2020)
CRIS-Team WoS Importer:2020-09-11

Detection and Characterization of Circulating Tumor Cells in Patients with Merkel Cell Carcinoma - Riethdorf, Sabine; Hildebrandt, Lina; Heinzerling, Lucie; Heitzer, Ellen; Fischer, Nicole; Bergmann, Sonja; Mauermann, Oliver; Waldispuehl-Geigl, Julie; Coith, Cornelia; Schoen, Gerhard; Peine, Sven; Schuler, Gerold; et al. (Clinical Chemistry, 2019)
BACKGROUND: Merkel cell carcinoma (MCC) is a rare, aggressive skin cancer with increasing incidence and high mortality rates. MCC has recently become the subject of immune checkpoint therapy, but reliable biomarkers for estimating prognosis, risk stratification, and prediction of response are missing.
CRIS-Team WoS Importer:2019-03-15

Development and evaluation of a digital education tool for medical students in wound care - Schlupeck, Mischa; Stubner, Birgit; Erfurt-Berge, Cornelia (International Wound Journal, 2020)
The aim of this study was to develop and evaluate an interactive, video-enhanced, and case-based online course for medical students. We chose a case about wound care since this topic is still underrepresented in the medical curriculum. First, instructional videos were created to teach practical skills in wound care. These were implemented into a case-based online course, using the online learning platform ILIAS. In a comparative initial and final survey, numbers of users were assessed, content and structure of the course, as well as the thematic interest of the students and self-assessed gain of competence, were evaluated. Since the summer of 2019, 310 students have successfully completed the course. The survey data showed a high participation rate and a positive response regarding the content as well as the structural concept. Most of the students rated the content within the course as useful for their future medical work (86.1%) and the gain of knowledge superior to a traditional lecture (69.4%). Self-assessments of video-mediated skills showed a significant increase in subjectively perceived competence. The online course is an efficient way to reach many students by the small use of resources. It resembles an option to arouse growing interest in wound care in medical students.
CRIS-Team Scopus Importer:2020-09-25
Keywords: digital education; health care; medical students; practical skills; wound care

Development of a digital Teaching Project on the Topic of "Immunooncology" - Kaufmann, Matthias; Berking, Carola; French, L. E.; Meyerolbersleben, Marion; Reinholz, M.; Steeb, Theresa; Heppt, Markus (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2021)
CRIS-Team WoS Importer:2021-09-24

Development of combination therapy to delay resistance in BRAF-inhibitor treated melanoma - Seretis, A.; Cappellano, G.; Bellmann, L.; Hornsteiner, F.; Tripp, C. H.; Ortner-Tobider, D.; Mullins, D. W.; Amon, Lukas; Lehmann, Christian; Dudziak, Diana; Stoitzner, P. (EXPERIMENTAL DERMATOLOGY, 2021)
CRIS-Team WoS Importer:2021-05-14

Differential effects of ?4?7 and GPR15 on homing of effector and regulatory T cells from patients with UC to the inflamed gut in vivo - Fischer, Anika; Zundler, Sebastian; Atreya, Raja; Rath, Timo; Voskens, Caroline; Hirschmann, Simon; Lopez Posadas, Rocío; Watson, Alastair; Becker, Christoph; Schuler, Gerold; Neufert, Clemens; Atreya, Imke; et al. (Gut, 2016)
Gut homing of lymphocytes via adhesion molecules has recently emerged as new target for therapy in IBDs. We aimed to analyse the in vivo homing of effector (Teff) and regulatory (Treg) T cells to the inflamed gut via ?4?7 and G protein receptor GPR15.We assessed the expression of homing receptors on T cells in peripheral blood and inflamed mucosa. We studied the migration pattern and homing of Teff and Treg cells to the inflamed gut using intravital confocal microscopy and FACS in a humanised mouse model in dextran sodium sulfate-treated NSG (NOD.Cg-Prkdcscid-Il2rgtm1Wjl/SzJ) mice.Expression of GPR15 and ?4?7 was significantly increased on Treg rather than Teff cells in peripheral blood of patients with UC as compared with Crohn's disease and controls. In vivo analysis in a humanised mouse model showed augmented gut homing of UC Treg cells as compared with controls. Moreover, suppression of UC (but not control) Teff and Treg cell homing was noted upon treatment with the ?4?7 antibody vedolizumab. In contrast, siRNA blockade of GPR15 had only effects on homing of Teff cells but did not affect Treg homing in UC. Clinical vedolizumab treatment was associated with marked expansion of UC Treg cells in peripheral blood.?4?7 rather than GPR15 is crucial for increased colonic homing of UC Treg cells in vivo, while both receptors control UC Teff cell homing. Vedolizumab treatment impairs homing of UC Treg cells leading to their accumulation in peripheral blood with subsequent suppression of systemic Teff cell expansion.
EVALuna2:2173

Differential expression of toll like receptors and antibiotic peptides by human keratinocytes - Heusinger, Juliane; Herter-Kermann, T.; Sticherling, Michael (2019)
EVALuna2:212072

Differential Modulation of Dendritic Cell Biology by Endogenous and Exogenous Aryl Hydrocarbon Receptor Ligands - Sadeghi Shermeh, Atefeh; Royzman, Dmytro; Kuhnt, Christine; Draßner, Christina; Stich, Lena; Steinkasserer, Alexander; Knippertz, Ilka; Wild, Andreas (International Journal of Molecular Sciences, 2023)
The aryl hydrocarbon receptor (AhR) is a decisive regulatory ligand-dependent transcription factor. It binds highly diverse ligands, which can be categorized as either endogenous or exogenous. Ligand binding activates AhR, which can adjust inflammatory responses by modulating immune cells such as dendritic cells (DCs). However, how different AhR ligand classes impact the phenotype and function of human monocyte-derived DCs (hMoDCs) has not been extensively studied in a comparative manner. We, therefore, tested the effect of the representative compounds Benzo(a)pyrene (BP), 6-formylindolo[3,2-b]carbazole (FICZ), and Indoxyl 3-sulfate (I3S) on DC biology. Thereby, we reveal that BP significantly induces a tolerogenic response in lipopolysaccharide-matured DCs, which is not apparent to the same extent when using FICZ or I3S. While all three ligand classes activate AhR-dependent pathways, BP especially induces the expression of negative immune regulators, and subsequently strongly subverts the T cell stimulatory capacity of DCs. Using the CRISPR/Cas9 strategy we also prove that the regulatory effect of BP is strictly AhR-dependent. These findings imply that AhR ligands contribute differently to DC responses and incite further studies to uncover the mechanisms and molecules which are involved in the induction of different phenotypes and functions in DCs upon AhR activation.
CRIS-Team Scopus Importer:2023-05-26
Keywords: aryl hydrocarbon receptor; dendritic cells; endogenous ligands; exogenous ligands

Direct delivery of antigens to dendritic cells via antibodies specific for endocytic receptors as a promising strategy for future therapies - Lehmann, Christian; Heger, Lukas; Heidkamp, Gordon Frederik; Baranska, Anna; Lühr, Jennifer; Hoffmann, Alana; Dudziak, Diana (Vaccines, 2016)
Dendritic cells (DCs) are the most potent professional antigen presenting cells and are therefore indispensable for the control of immunity. The technique of antibody mediated antigen targeting to DC subsets has been the basis of intense research for more than a decade. Many murine studies have utilized this approach of antigen delivery to various kinds of endocytic receptors of DCs both in vitro and in vivo. Today, it is widely accepted that different DC subsets are important for the induction of select immune responses. Nevertheless, many questions still remain to be answered, such as the actual influence of the targeted receptor on the initiation of the immune response to the delivered antigen. Further efforts to better understand the induction of antigen-specific immune responses will support the transfer of this knowledge into novel treatment strategies for human diseases. In this review, we will discuss the state-of-the-art aspects of the basic principles of antibody mediated antigen targeting approaches. A table will also provide a broad overview of the latest studies using antigen targeting including addressed DC subset, targeted receptors, outcome, and applied coupling techniques.
Created from Fastlane, Scopus look-up
Keywords: Antigen targeting; Antigen targeting antibodies; Cancer; CLR; DC; DCIR; DEC205; Dendritic cell subsets; moDC; Vaccine

DISEASE INTERCEPTION IN PSORIASIS PATIENTS WITH SUBCLINICAL JOINT INFLAMMATION BY INTERLEUKIN 17 INHIBITION WITH SECUKINUMAB - DATA FROM A PROSPECTIVE OPEN LABEL STUDY - Kamoylafka, E.; Oliveira, I. D.; Linz, C.; Lerchen, V.; Englbrecht, Matthias; Simon, David; Sticherling, Michael; Rech, Jürgen; Kleyer, Arnd; Schett, Georg; Hueber, Axel (2018)
EVALuna2:34789

Disease interception with interleukin-17 inhibition in high-risk psoriasis patients with subclinical joint inflammation - Data from the prospective IVEPSA study - Kampylafka, Eleni; Simon, David; D'Oliveira, Isabelle; Linz, Christina; Lerchen, Veronika; Englbrecht, Matthias; Rech, Jürgen; Kleyer, Arnd; Sticherling, Michael; Schett, Georg; Hueber, Axel (Arthritis Research & Therapy, 2019)
Background: A specific subset of psoriasis patients is characterized by subclinical inflammatory changes. These patients frequently present with arthralgia and have a higher risk to develop psoriatic arthritis (PsA). We hypothesized that IL-17A inhibition in this subset of patients can intercept the link between skin and joint disease and resolves pain and inflammatory changes. Methods: Psoriasis, but no PsA, patients were included in the open prospective exploratory Interception in very early PsA (IVEPSA) study. Patients had to have nail or scalp involvement or a high psoriasis area severity index (PASI) (> 6) as well as inflammatory or erosive changes in MRI or CT. Patients received treatment with the anti-interleukin (IL)-17A antibody secukinumab over 24 weeks. Clinical assessments of skin and joint disease were done at baseline and after 12 and 24 weeks, MRI and CT at baseline and after 24 weeks. Results: Twenty patients were included, 85% of them reporting arthralgia and 40% had tender joints at the examination. Eighty-three percent had at least one inflammatory lesion in the MRI, most of them synovitis/enthesitis. Skin disease (PASI: p < 0.002; BSA: p < 0.003) and arthralgia (VAS pain: p < 0.003) significantly improved after 24 weeks. Total PsAMRIS (p = 0.005) and synovitis subscore (p = 0.008) also significantly improved. Erosions and enthesiophytes did not progress, while bone mass in the distal radius significantly (p = 0.020) increased after 24 weeks. Conclusions: These data suggest that very early disease interception in PsA is possible leading to a comprehensive decline in skin symptoms, pain, and subclinical inflammation. IVEPSA therefore provides rationale for future early interventions with the concept to prevent the onset of PsA in high-risk individuals. Trial registration: Trial registry name PSARTROS; trial registry number: NCT02483234; June 26, 2015.
CRIS-Team Scopus Importer:2019-08-06
Keywords: Interleukin-17; Magnetic resonance imaging; Psoriasis; Psoriatic arthritis

Dissecting the IFN gamma-mediated transcriptomic alterations in Merkel cell carcinoma cell lines using Nanopore sequencing - Sauerer, Tatjana; Lischer, Christopher; Berking, Carola; Vera González, Julio; Dörrie, Jan (EXPERIMENTAL DERMATOLOGY, 2022)
CRIS-Team WoS Importer:2022-03-04

Disseminated Pustules in a 3 Year Old Boy - Grosch, Ella; Koeceroglu, M.; Schliep, S.; Kiesewetter, Franklin; Sticherling, Michael; Voskens, C. J. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-05-17

DIVERSITY OF CD4(+) BLOOD T-CELL CLONALITY PREDICTS LONGER SURVIVAL WITH CTLA4 OR PD-1 CHECKPOINT INHIBITION IN ADVANCED MELANOMA - Arakawa, A.; Vollmer, S.; Tietze, J.; Galinski, A.; Heppt, Markus; Berking, Carola; Prinz, J. C. (JOURNAL FOR IMMUNOTHERAPY OF CANCER, 2021)
CRIS-Team WoS Importer:2021-12-03

Do B-Cells play a Role in Patients with Psoriasis? - Banki, Simon; Heusinger, Juliane; Herter-Kermann, T.; Sticherling, Michael (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2021)
CRIS-Team WoS Importer:2021-04-16

Documentation of psoriasis in routine care – expert consensus on a German data set - Otten, Marina; Mrowietz, Ulrich; Von Kiedrowski, Ralph Michael; Otto, Ramona; Altenburg, Andreas; Aschoff, Roland; Beissert, Stefan; Beiteke, Ulrike; Bonnekoh, Bernd; Hoffmann, Matthias; Koerber, Andreas; Maassen, Dirk; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2021)
Background and objectives: Documenting patient data in psoriasis clinical practice can improve care, but standardized and transparent documentation is rare. The current project aimed to develop a data set for the documentation of psoriasis in daily practice. Material and methods: In four online Delphi rounds and one in-person meeting, 27 psoriasis experts allocated variables to a standard, an optimal and an optional data set. Most of the questions were standardized. Open questions were included to allow for the provision of reasons and to enlarge the data sets. Furthermore, in the in-person meeting we considered a) patients’ attitudes and b) dermatologists’ information on the current usage and acceptability in Germany. Results: The consensus approach resulted in a data set with 69 variables. The standard data set includes 20, the optimal data set 31 and the optional data set 18 variables. In summary, the data set can mainly be grouped into master data, general status and medical history data, medical history of psoriasis, status of psoriasis, diagnostics and comorbidity, therapies and patient-reported outcomes. Conclusions: The consensus recommendation of a standard, an optimal and an optional data set for routine care of psoriasis intends to be a decision-making aid and an orientation for both daily practice and further development of documentation systems.
CRIS-Team Scopus Importer:2021-10-22

Does In-transit-Metastasis in lower Extremity Melanoma Patients correlate with anatomical Lymphatic Drainage Pathways? - Müller, Kilian; Schellerer, Vera; Berking, Carola; Erdmann, Michael (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2021)
CRIS-Team WoS Importer:2021-09-24

Does Subjectively Perceived Loss Of Hand Function Sufficiently Represent Ultrasonography-Detected Synovitis And Tenosynovitis In Patients With Psoriasis And Psoriatic Arthritis? - Coppers, Birte; Bayat, Sara; Elie-Tino, Godonou; Valor-Mendez, Larissa; Fagni, Filippo; Corte, Giulia; Tascilar, Koray; Hueber, Axel; Schönau, Verena; Sticherling, Michael; Schett, Georg; Kleyer, Arnd; et al. (poster, European Alliance of Association for Rheumatology (EULAR) Congress, 2023)

Dokumentation der Psoriasis in der Routineversorgung – Expertenkonsens zu einem deutschen Datensatz - Otten, Marina; Mrowietz, Ulrich; von Kiedrowski, Ralph Michael; Otto, Ramona; Altenburg, Andreas; Aschoff, Roland; Beissert, Stefan; Beiteke, Ulrike; Bonnekoh, Bernd; Hoffmann, Matthias; Körber, Andreas; Maaßen, Dirk; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2021)
CRIS-Team Scopus Importer:2021-10-29
Keywords: Datensatz; Delphi; Dokumentation; klinische Praxis; Patientenbeteiligung; Psoriasis

Do Patients with Lower Limb Melanoma have an increased Risk of a "false negative" Sentinel Node Biopsy? - Braun, L.; Schellerer, Vera; Schuler, Gerold; Goeol, J.; Erdmann, M. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-09-13

Doxycycline versus Prednisolone for the initial Treatment of bullous Pemphigoids: a pragmatic prospective randomized Study - Schmidt, E.; Benoit, S.; Ehrchen, J.; Glaeser, R.; Guenther, C.; Steinbrink, K.; Sticherling, Michael; Van Beek, N.; Wojnarowska, F.; Kirtschig, G.; Mason, J.; Godec, T.; et al. (2017)
EVALuna2:34351

Drei Generationen Leiden: Cryopyrin-assoziiertes periodisches Syndrom mit familiärer NLRP3-Mutation - Wagner, Nicola; Manger, Bernhard; Kittler, Julia; Rech, Jürgen; Sticherling, Michael; Berking, Carola; Kirchberger, Michael (Journal der Deutschen Dermatologischen Gesellschaft, 2022)
CRIS-Team Scopus Importer:2022-02-04

Drug-induced dilemma: angiokeratomas and decreased renal function - Schliep, Stefan; Kiesewetter, Franklin; Simon, Miklos; Grupp, Clemens; Heinzerling, Lucie (American Journal of Medicine, 2014)
EVALuna2:19482

Dupilumab but not cyclosporine treatment shifts the microbiome toward a healthy skin flora in patients with moderate-to-severe atopic dermatitis - Hartmann, Jan; Moitinho-Silva, Lucas; Sander, Nicole; Harder, Inken; Häsler, Robert; Rodriguez, Elke; Haufe, Eva; Kleinheinz, Andreas; Abraham, Susanne; Heratizadeh, Annice; Weisshaar, Elke; Schäkel, Knut; et al. (Allergy, 2023)
Background: Atopic dermatitis (AD) patients display an altered skin microbiome which may not only be an indicator but also a driver of inflammation. We aimed to investigate associations among AD patients' skin microbiome, clinical data, and response to systemic therapy in patients of the TREATgermany registry. Methods: Skin swabs of 157 patients were profiled with 16S rRNA gene amplicon sequencing before and after 3 months of treatment with dupilumab or cyclosporine. For comparison, 16s microbiome data from 258 population-based healthy controls were used. Disease severity was assessed using established instruments such as the Eczema Area and Severity Index (EASI). Results: We confirmed the previously shown correlation of Staphylococcus aureus abundance and bacterial alpha diversity with AD severity as measured by EASI. Therapy with Dupilumab shifted the bacterial community toward the pattern seen in healthy controls. The relative abundance of Staphylococci and in particular S. aureus significantly decreased on both lesional and non-lesional skin, whereas the abundance of Staphylococcus hominis increased. These changes were largely independent from the degree of clinical improvement and were not observed for cyclosporine. Conclusions: Systemic treatment with dupilumab but not cyclosporine tends to restore a healthy skin microbiome largely independent of the clinical response indicating potential effects of IL-4RA blockade on the microbiome.
CRIS-Team Scopus Importer:2023-05-05
Keywords: atopic dermatitis; dupilumab; inflammation; microbiome

Dupilumab-induced erythema nodosum in a patient with atopic hand eczema - Ronicke, Moritz; Sticherling, Michael; Wagner, Nicola (ALLERGOLOGIE, 2022)
CRIS-Team WoS Importer:2023-03-24

Dynamic regulation and differential compartmentaliztion of C-type lectin receptors in the dendritic cell membrane - Lühr, Jennifer; Eissing, N.; Heger, Lukas; Lehmann, C.; Heidkamp, Gordon Frederik; Nimmerjahn, Falk; Balint, S.; Sezgin, E.; Eggeling, C.; Dustin, M.; Dudziak, Diana (2018)
EVALuna2:34794

Easy performance of 6-color confocal immunofluorescence with 4-laser line microscopes - Eissing, Nathalie; Heger, Lukas; Baranska, Anna; Cesnjevar, Robert; Büttner, Maike; Söder, Stephan; Hartmann, Arndt; Heidkamp, Gordon Frederik; Dudziak, Diana (Immunology Letters, 2014)
Confocal laser scanning microscopy is an advanced technique for imaging tissue samples in vitro and in vivo at high optical resolution. The development of new fluorochrome variants do not only make it possible to perform multicolor flow cytometry of single cells, but in combination with high resolution laser scanning systems also to investigate the distribution of cells in lymphoid tissues by confocal immunofluorescence analyses, thus allowing the distinction of various cell populations directly in the tissue. Here, we provide a protocol for the visualization of at least six differently fluorochrome-labeled antibodies at the same time using a conventional confocal laser scanning microscope with four laser lines (405 nm, 488 nm, 555 nm, and 639 nm laser wavelength) in both murine and human tissue samples. We further demonstrate that compensation correction algorithms are not necessary to reduce spillover of fluorochromes into other channels when the used fluorochromes are combined according to their specific emission bands and the varying Stokes shift for co-excited fluorochromes with the same laser line.
EVALuna2:6626

Eccrine porocarcinoma mimicking a venous leg ulcer - Erdmann, Michael; Brauner, Kathrin; Bauerschmitz, Jürgen; Erfurt-Berge, Cornelia (International Wound Journal, 2016)
EVALuna2:19627

ECP as prognostic Marker for Melanoma - Moreira, Alvaro; Krueckel, A.; Schuler, Gerold; Utikal, J.; Heinzerling, Lucie (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-09-13

Editorial: Foundations of Theoretical Approaches in Systems Biology - Marin-Sanguino, Alberto; Vera, Julio; Alves, Rui (Frontiers in Genetics, 2018)
EVALuna2:34783

Editorial: Local Immune Modulation of Macrophages and Dendritic Cells - Local Matters - Bock, Felix; Saban, Daniel; Steinkasserer, Alexander (Frontiers in Immunology, 2022)
CRIS-Team Scopus Importer:2022-07-22
Keywords: cornea; dendritic cells; immune modulation; macrophages; microenviroment; transplantation

Editorial: Multiomics and multiparametric analyses to characterize myeloid cell subsets - Vu Manh, Thien Phong; Dalod, Marc; Dudziak, Diana (Frontiers in Immunology, 2023)
CRIS-Team Scopus Importer:2023-10-20
Keywords: cell state characterization; cell type identification; multiomics; multiparametric analysis; myeloid cells

Editorial: Sentinel CLECs at Immunological Decision Nodes - Hoober, J. Kenneth; van Vliet, Sandra J.; Dudziak, Diana; Eggink, Laura L. (Frontiers in Immunology, 2020)
CRIS-Team Scopus Importer:2020-10-02
Keywords: CLEC receptors; dendritic cells; immunomodulation; ligand diversity; sentinel receptors

Effective anti-programmed death-1 therapy in a SUFU-mutated patient with Gorlin-Goltz syndrome - Moreira, Alvaro; Kirchberger, M. C.; Toussaint, Frédéric; Erdmann, M.; Schuler, Gerold; Heinzerling, Lucie (British Journal of Dermatology, 2018)
We present the case of a 77-year-old male patient with more than 50 basal cell carcinomas on the head and upper trunk. The patient did not respond to several lines of treatment, including surgery, imiquimod, retinoids, itraconazole and therapy with the hedgehog inhibitor vismodegib. The patient responded well to off-label therapy with the anti-programmed death-1 antibody pembrolizumab after four infusions.
EVALuna2:34414

Effectiveness and Safety of Dabrafenib and Trametinib in Patients with BRAFV600 Mutated Metastatic Melanoma in the Real-World Setting - Final Results of the Non-Interventional COMBI-r Study - Berking, Carola; Livingstone, E.; Weichenthal, M.; Leiter-Stoeppke, U.; Remy, J.; Eigentler, T.; Mohr, P.; Kiecker, F.; Loquai, C.; Debus, D.; Gutzmer, R. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2022)
CRIS-Team WoS Importer:2022-09-23

Effectiveness and tolerability of ipilimumab: experiences from 198 patients included in a named-patient program in various daily-practice settings and multiple institutions - Eigentler, Thomas K.; Schlaak, Max; Hassel, Jessica C.; Loquai, Carmen; Stoffels, Ingo; Gutzmer, Ralf'; Paetzold, Sylvie; Mohr, Peter; Keller, Ulrich; Starz, Hans; Ulrich, Jens; Tsianakas, Athanasios; et al. (Journal of Immunotherapy, 2014)
Ipilimumab is an approved anti-cytotoxic T-lymphocyte-associated antigen-4 monoclonal antibody introducing immune responses in melanoma patients. Treatment experiences from named-patient programs support the evaluation of the efficacy and tolerability of new medicines under usual circumstances of health care practice. Here, the largest ever reported cohort treated with ipilimumab 3 mg/kg alone is described.This report retrospectively analyzes data of 198 patients who were followed up in 15 hospital centers in Germany between April 2010 and March 2013. Patients had received prior therapy for unresectable stage III or IV melanoma before receiving ipilimumab (4 doses of 3 mg/kg every 21 d). Routine staging and tumor response evaluation procedures were applied.Of the patients, 119 received the planned 4-course therapy schedule; in further 79 patients, the number of doses was reduced mainly because of toxicity or fast progression. In all, 196 patients were eligible for evaluation of the efficacy of ipilimumab under routine care conditions. Median overall survival (OS) was 6.8 months [95% confidence interval, 5.6-10.3] from the start of therapy. OS differed significantly among patients who received 4 doses (n=119) and those receiving <4 doses (n=79) (14.2 vs. 2.0 mo; P<0.0001). The overall response rate (ORR) of 11% was in the same range as reported from previous clinical trials; and stable disease (SD) was observed in 11% resulting in a disease control rate (ORR+SD) of 22%. In 23 of the 79 patients with reduced dosing, dose omission was most probably caused by toxicity, whereas 56 patients had progressive disease before receiving all 4 treatment cycles. Immune-related adverse events (irAE) were reported in 30% of all treated patients, the occurrence of irAE correlated significantly with the probability of response to therapy and prolonged OS.In this named-patient program including heavily pretreated patients, the efficacy and tolerability of ipilimumab 3 mg/kg corresponds with findings from the confirmatory clinical trial.
EVALuna2:19484

Effectiveness of an employee skin cancer screening program for secondary prevention - Uslu, Ugur; Hees, Felix; Winnik, Eva; Uter, Wolfgang; Sticherling, Michael (Cutis, 2016)
Incidences of UV-induced skin cancer are continuously increasing. For this reason, early diagnosis is becoming more important. In this study, 783 employees of a technical company participated in an employee skin cancer screening program, which consisted of a physical examination for benign and malignant skin lesions and premalignant conditions. To ensure the quality of the examinations, screening was only performed by 5 trained dermatologists. Participants also were asked to complete a standardized questionnaire prior to examination. A total of 661 skin lesions were diagnosed among 48% of participants; 12.8% of participants exhibited 50 or more melanocytic nevi and the risk for developing skin cancer was categorized as at least moderate for 64.9%. Additionally, 84.4% of participants with at least 1 skin lesion were advised to have a checkup within 1 year. The high rate of suspicious nevi detected in this study suggested that employee skin cancer screening programs are effective and also should be recommended at companies where employees are not at increased risk for developing skin cancer due to the nature of their work (eg, those who work outdoors). Despite the comparatively selective and young study population, these examinations provide evidence of the importance of skin cancer screening for the wider population.
EVALuna2:5563

Effectiveness of Dabrafenib plus Trametinib during the Treatment of Melanoma Patients with BRAFV600 mutated Brain Metastases - Berking, Carola; Schadendorf, D.; Weichenthal, M.; Eigentler, T.; Schober, K.; Mohr, P.; Kiecker, F.; Loquai, C.; Debus, D.; Gutzmer, R.; Leiter-Stoeppke, U. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2020)
CRIS-Team WoS Importer:2020-09-11

Effectiveness, safety and drug survival of dupilumab in patients with moderate to severe atopic dermatitis: an interim analysis of the TREATgermany registry - Stoelzl, D.; Boraczynski, N.; Heratizadeh, A.; Haufe, Eva; Harder, I.; Abraham, S.; Heinrich, Luise; Kleinheinz, A.; Wollenberg, A.; Weisshaar, E.; Schaekel, K.; Ertner, K.; et al. (EXPERIMENTAL DERMATOLOGY, 2022)
CRIS-Team WoS Importer:2022-03-04

Effectiveness, safety and utilization of vismodegib in locally advanced basal cell carcinoma under real-world conditions in Germany - The non-interventional study NIELS - Gutzmer, R.; Schulze, H. -J.; Hauschild, A.; Leiter, U.; Meier, F.; Haferkamp, S.; Ulrich, C.; Wahl, R. U.; Berking, Carola; Herbst, R.; Haeckl, M.; Schadendorf, D. (Journal of the European Academy of Dermatology and Venereology, 2021)
Background Basal cell carcinoma (BCC) can arise by the uncontrolled proliferation of cells from multiple epidermal compartments due to aberrant activation of the Hedgehog (Hh) signalling pathway. Vismodegib, a small-molecule inhibitor of this pathway, is approved for treatment of patients with locally advanced (la) BCC inappropriate for surgery or radiotherapy or patients with symptomatic metastatic (m) BCC.
CRIS-Team WoS Importer:2021-06-04

Effect of sCD83 on macrophages in corneal high-risk transplantation - Schoenberg, Alfrun; Peckert-Maier, Katrin; Wild, Andreas; Royzman, Dmytro; Braun, Gabriele; Stich, Lena; Cursiefen, Claus; Steinkasserer, Alexander; Bock, Felix; Zinser, Elisabeth (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2021)
CRIS-Team WoS Importer:2021-10-15

Effects of Label Noise on Deep Learning-Based Skin Cancer Classification - Hekler, Achim; Kather, Jakob N.; Krieghoff-Henning, Eva; Utikal, Jochen S.; Meier, Friedegund; Gellrich, Frank F.; Upmeier zu Belzen, Julius; French, Lars; Schlager, Justin G.; Ghoreschi, Kamran; Wilhelm, Tabea; Kutzner, Heinz; et al. (Frontiers in Medicine, 2020)
Recent studies have shown that deep learning is capable of classifying dermatoscopic images at least as well as dermatologists. However, many studies in skin cancer classification utilize non-biopsy-verified training images. This imperfect ground truth introduces a systematic error, but the effects on classifier performance are currently unknown. Here, we systematically examine the effects of label noise by training and evaluating convolutional neural networks (CNN) with 804 images of melanoma and nevi labeled either by dermatologists or by biopsy. The CNNs are evaluated on a test set of 384 images by means of 4-fold cross validation comparing the outputs with either the corresponding dermatological or the biopsy-verified diagnosis. With identical ground truths of training and test labels, high accuracies with 75.03% (95% CI: 74.39–75.66%) for dermatological and 73.80% (95% CI: 73.10–74.51%) for biopsy-verified labels can be achieved. However, if the CNN is trained and tested with different ground truths, accuracy drops significantly to 64.53% (95% CI: 63.12–65.94%, p < 0.01) on a non-biopsy-verified and to 64.24% (95% CI: 62.66–65.83%, p < 0.01) on a biopsy-verified test set. In conclusion, deep learning methods for skin cancer classification are highly sensitive to label noise and future work should use biopsy-verified training images to mitigate this problem.
CRIS-Team Scopus Importer:2020-06-02
Keywords: artificial intelligence; dermatology; label noise; melanoma; nevi; skin cancer

Effects of structured patient education in adults with atopic dermatitis: Multicenter randomized controlled trial - Heratizadeh, Annice; Werfel, Thomas; Wollenberg, Andreas; Abraham, Susanne; Plank-Habibi, Sibylle; Schnopp, Christina; Sticherling, Michael; Apfelbacher, Christian; Biedermann, Tilo; Breuer, Kristine; Fell, Isabel; Foelster-Holst, Regina; et al. (Journal of Allergy and Clinical Immunology, 2017)
BACKGROUND: Atopic dermatitis (AD) is a chronic relapsing skin disease prevalent in 1% to 3% of adults in Western industrialized countries. OBJECTIVE: We sought to investigate the effectiveness of educational training in an outpatient setting on coping with the disease, quality of life, symptoms, and severity in adults with AD. METHODS: In this German prospective, randomized controlled multicenter study, adult patients with moderate-to-severe AD were educated by referring to a comprehensive 12-hour training manual consented by a multiprofessional study group from different centers (Arbeitsgemeinschaft Neurodermitisschulung für Erwachsene [ARNE]). Patients were randomly allocated to the intervention or waiting control groups. Study visits were performed at baseline and after 1 year (1 year of follow-up). Primary outcomes were defined as a decrease in (1) "catastrophizing cognitions" with respect to itching (Juckreiz-Kognitions-Fragebogen questionnaire), (2) "social anxiety" (Marburger Hautfragebogen questionnaire), (3) subjective burden by symptoms of the disease (Skindex-29 questionnaire), and (4) improvement of disease signs and symptoms assessed by using the SCORAD index at 1 year of follow-up. Data were analyzed on an intention-to-treat basis. RESULTS: At 1 year of follow-up, patients from the intervention group (n = 168) showed a significantly better improvement compared with the waiting group (n = 147) in the following defined primary study outcomes: coping behavior with respect to itching (P < .001), quality of life assessed by using the Skindex-29 questionnaire (P < .001), and the SCORAD index (P < .001). CONCLUSIONS: This is the first randomized, controlled multicenter study on patient education in adult AD. The ARNE training program shows significant beneficial effects on a variety of psychosocial parameters, as well as AD severity.
EVALuna2:34346

Efficacy of different Interventions for the Treatment of cutaneous Squamous Cell Carcinoma in situ (Bowen's Disease) - a systematic Literature Review and Meta-Analysis - Petzold, Anne; Steeb, Theresa; Wessely, Anja; Berking, Carola; Heppt, Markus (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2021)
CRIS-Team WoS Importer:2021-09-24

Efficient generation of a monoclonal antibody against the human C-type lectin receptor DCIR by targeting murine dendritic cells. - Heidkamp, Gordon Frederik; Neubert, Kirsten; Härtel, Eric; Nimmerjahn, Falk; Nussenzweig, Michel C.; Dudziak, Diana (Immunology letters, 2010)
Dendritic cells (DCs) are very important for the generation of long lasting immune responses against pathogens or the induction of anti-tumor responses. Targeting antigen to dendritic cells via monoclonal antibodies specific for DC cell surface receptors such as DEC205 was shown to elicit potent cellular and humoral immune responses in vivo. Therefore, we investigated whether this novel strategy might also be useful for the generation of new monoclonal antibodies against molecules of choice. We show, that by targeting the extracellular domain of the human C-type lectin receptor ClecSF6/DCIR/LLIR (hDCIR) to DEC205 on DCs in vivo, we were able to generate highly specific monoclonal antibodies against hDCI

eImmunonkologie: Development and Launch of a Virtual Education Platform for the Immunotherapy of Cutaneous Neoplasms - Kaufmann, Matthias; Steeb, Theresa; Wessely, Anja; Meyerolbersleben, Marion; French, Lars E. E.; Berking, Carola; Heppt, Markus (Medical Science Educator, 2022)
The use of immunotherapies in clinical practice has significantly expanded treatment options and improved the prognosis of patients with advanced cancers over the past decade. We have developed a virtual teaching module entitled "eImmunonkologie" which is the first interdisciplinary virtual course on immuno-oncology for medical students in German-speaking countries.
CRIS-Team WoS Importer:2023-01-20

Eine übermäßige Phagozytose von Myelomzellen induziert Pyroptose in Myelom-assoziierten Makrophagen und beeinträchtigt die Wirksamkeit therapeutischer Antikörper - Flamann, Cindy; Biedermann, Alexander; Mougiakakos, D.; Bitterer, Katrin; Karg, K.; Bittenbring, J.; Büttner-Herold, Maike; Liebisch, G.; Leffler, M.; Lischer, Christopher; Eberhardt, Martin; Vera-Gonzales, J.; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-11-18

Ein Lues-ähnliches Bild verursacht durch PVL-positive Staphylokokken - Busch, Dorothee; Schliep, Stefan; Berking, Carola; Bosch-Voskens, Caroline (Journal der Deutschen Dermatologischen Gesellschaft, 2023)
CRIS-Team Scopus Importer:2023-05-05

Ein Lues-ähnliches Bild verursacht durch PVL-positive Staphylokokken - Busch, Dorothee; Schliep, Stefan; Berking, Carola; Bosch-Voskens, Caroline (Journal der Deutschen Dermatologischen Gesellschaft, 2023)
EVALuna2:537510

Elective Discontinuation of Checkpoint Inhibitor Therapy in Patients with advanced Melanoma - Persa, O. D.; Schatton, K.; Ruebben, A.; Berking, Carola; Erdmann, M.; Schlaak, M.; Mauch, C.; Steeb, T. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2021)
CRIS-Team WoS Importer:2021-09-24

Electroporated Antigen-Encoding mRNA Is Not a Danger Signal to Human Mature Monocyte-Derived Dendritic Cells - Hoyer, Stefanie; Gerer, Kerstin F.; Pfeiffer, Isabell A.; Prommersberger, Sabrina; Hoefflin, Sandra; Jaitly, Tanushree; Beltrame, Luca; Cavalieri, Duccio; Schuler, Gerold; Vera, Julio; Schaft, Niels; Dörrie, Jan (Journal of immunology research, 2015)
For therapeutic cancer vaccination, the adoptive transfer of mRNA-electroporated dendritic cells (DCs) is frequently performed, usually with monocyte-derived, cytokine-matured DCs (moDCs). However, DCs are rich in danger-sensing receptors which could recognize the exogenously delivered mRNA and induce DC activation, hence influencing the DCs' immunogenicity. Therefore, we examined whether electroporation of mRNA with a proper cap and a poly-A tail of at least 64 adenosines had any influence on cocktail-matured moDCs. We used 16 different RNAs, encoding tumor antigens (MelanA, NRAS, BRAF, GNAQ, GNA11, and WT1), and variants thereof. None of those RNAs induced changes in the expression of CD25, CD40, CD83, CD86, and CD70 or the secretion of the cytokines IL-8, IL-6, and TNFα of more than 1.5-fold compared to the control condition, while an mRNA encoding an NF-B-activation protein as positive control induced massive secretion of the cytokines. To determine whether mRNA electroporation had any effect on the whole transcriptome of the DCs, we performed microarray analyses of DCs of 6 different donors. None of 60,000 probes was significantly different between mock-electroporated DCs and MelanA-transfected DCs. Hence, we conclude that no transcriptional programs were induced within cocktail-matured DCs by electroporation of single tumor-antigen-encoding mRNAs.
CRIS-Team Scopus Importer:2021-10-01

Electroporation of siRNA into Mouse Bone Marrow-Derived Macrophages and Dendritic Cells - Siegert, Isabel; Schatz, Valentin; Prechtel, Alexander T.; Steinkasserer, Alexander; Bogdan, Christian; Jantsch, Jonathan (Methods in Molecular Biology, 2014)
Dendritic cells (DC) and macrophages (M?) play a pivotal role in antimicrobial defense, in the regulation of immune responses, and in maintaining tissue homeostasis. The analysis of DC and M? function relies on primary cells albeit these cells are known to be difficult to transfect. This makes the use of small interfering RNA (siRNA) for targeted manipulation of gene expression by RNA interference difficult. In the following chapter, we provide a detailed protocol for the successful transfer of siRNA via electroporation into a defined population of mouse bone marrow-derived M? or DC that does not cause toxicity to the myeloid cells or nonspecific alterations of their biological functions. Factors that influence the transfection and knockdown rate will be highlighted.
EVALuna2:7575

Elevated aluminum excretion in patients by long-term subcutaneous immunotherapy – A cross-sectional case-control study - Hiller, Julia; Göen, Thomas; Drexler, Hans; Berking, Carola; Wagner, Nicola (International Journal of Hygiene and Environmental Health, 2024)
Background: Aluminum (Al) adjuvants have been used in vaccines and subcutaneous immunotherapy (SCIT) for decades. Despite indisputable neurotoxic properties of Al, there is no clear evidence of a causal relationship between their use and any neurotoxic side effects. However, recent rat studies have shown an accumulation of Al from adjuvants in tissues, especially in bones. Objectives: Since the human toxicokinetics of Al-adjuvants are poorly understood, this study aimed to evaluate whether up-dosed or long-term SCIT with Al-coupled extracts leads to increased Al load in humans. Methods: This observational cross-sectional case-control study explored Al excretion in hymenoptera venom allergy patients recruited in 2020 before initiation (n = 10) and during ongoing (n = 12) SCIT with Al-based preparations. Urine samples were collected before and 24 h after the SCIT injections and analyzed for aluminum content by using atomic absorption spectrometry. The cumulative administered Al dose was extracted from patient records. Patients receiving long-term immunotherapy were treated between 2.8 and 13.6 years (mean 7.1). Other potential sources of Al exposure were surveyed. Results: Patients who had received Al-coupled immunotherapy for several years showed significantly (p < 0.001) higher Al excretion than the controls at initiation of immunotherapy (mean 18.2 μg/gC vs. 7.9 μg/gC) and predominantly (73%) were above the 95th percentile of the general populations' exposure (>15 μg/gC), however, without reaching levels of toxicological concern (>50 μg/gC). Taking both groups together excreted Al levels correlated with the cumulative administered Al dose from SCIT (linear regression: Alurine = 8.258 + 0.133*Alcum; p = 0.001). Discussion: These results suggest a relevant iatrogenic contribution of long-term SCIT to human internal Al burden and potential accumulation. Considering the medical benefits of Al-adjuvants and SCIT a differentiated risk-benefit analysis is needed. For certain scenarios of potential toxicological concern in clinical practice biomonitoring might be advisable.
CRIS-Team Scopus Importer:2024-03-15
Keywords: Adjuvant; Aluminum; Biomonitoring; Immunologic desensitization; Risk assessment; Venom hypersensitivity

Emerging functional markers for cancer stem cell-based therapies: Understanding signaling networks for targeting metastasis - Marquardt, Stephan; Solanki, Manish; Spitschak, Alf; Vera, Julio; Puetzer, Brigitte M. (Seminars in Cancer Biology, 2018)
Metastasis is one of the most challenging issues in cancer patient management, and effective therapies to specifically target disease progression are missing, emphasizing the urgent need for developing novel anti-metastatic therapeutics. Cancer stem cells (CSCs) gained fast attention as a minor population of highly malignant cells within liquid and solid tumors that are responsible for tumor onset, self-renewal, resistance to radio- and chemotherapies, and evasion of immune surveillance accelerating recurrence and metastasis. Recent progress in the identification of their phenotypic and molecular characteristics and interactions with the tumor microenvironment provides great potential for the development of CSC-based targeted therapies and radical improvement in metastasis prevention and cancer patient prognosis. Here, we report on newly uncovered signaling mechanisms controlling CSC's aggressiveness and treatment resistance, and CSC-specific agents and molecular therapeutics, some of which are currently under investigation in clinical trials, gearing towards decisive functional CSC intrinsic or surface markers. One special research focus rests upon subverted regulatory pathways such as insulin-like growth factor 1 receptor signaling and its interactors in metastasis-initiating cell populations directly related to the gain of stem cell- and EMT-associated properties, as well as key components of the E2F transcription factor network regulating metastatic progression, microenvironmental changes, and chemoresistance. In addition, the study provides insight into systems biology tools to establish complex molecular relationships behind the emergence of aggressive phenotypes from high-throughput data that rely on network-based analysis and their use to investigate immune escape mechanisms or predict clinical outcome-relevant CSC receptor signaling signatures. We further propose that customized vector technologies could drastically enhance systemic drug delivery to target sites, and summarize recent progress and remaining challenges. This review integrates available knowledge on CSC biology, computational modeling approaches, molecular targeting strategies, and delivery techniques to envision future clinical therapies designed to conquer metastasis-initiating cells.
EVALuna2:203615

Employing Graph Representations for Cell-Level Characterization of Melanoma MELC Samples - Rivera Monroy, Luis; Rist, Leonhard; Eberhardt, Martin; Ostalecki, Christian; Baur, Andreas; Vera, Julio; Breininger, Katharina; Maier, Andreas (2023 IEEE 20th International Symposium on Biomedical Imaging (ISBI), 2023)
Histopathology imaging is crucial for the diagnosis and treatment of skin diseases. For this reason, computer-assisted approaches have gained popularity and shown promising results in tasks such as segmentation and classification of skin disorders. However, collecting essential data and sufficiently high-quality annotations is a challenge. This work describes a pipeline that uses suspected melanoma samples that have been characterized using Multi-Epitope-Ligand Cartography (MELC). This cellular level characterization of the tissue is then represented as a graph and finally used to train a graph neural network. This imaging technology, combined with the methodology proposed in this work, achieves a classification accuracy of 87 %, outperforming existing approaches by 10 %.<br

EMT transcription factor ZEB1 alters the epigenetic landscape of colorectal cancer cells - Lindner, Pablo; Paul, Sushmita; Eckstein, Markus; Hampel, Chuanpit; Muenzner, Julienne K.; Erlenbach-Wuensch, Katharina; Ahmed, Husayn P.; Mahadevan, Vijayalakshmi; Brabletz, Thomas; Hartmann, Arndt; Vera, Julio; Schneider-Stock, Regine (Cell Death & Disease, 2020)
Epigenetic deregulation remarkably triggers mechanisms associated with tumor aggressiveness like epithelial–mesenchymal transition (EMT). Since EMT is a highly complex, but also reversible event, epigenetic processes such as DNA methylation or chromatin alterations must be involved in its regulation. It was recently described that loss of the cell cycle regulator p21 was associated with a gain in EMT characteristics and an upregulation of the master EMT transcription factor ZEB1. In this study, in silico analysis was performed in combination with different in vitro and in vivo techniques to identify and verify novel epigenetic targets of ZEB1, and to proof the direct transcriptional regulation of SETD1B by ZEB1. The chorioallantoic-membrane assay served as an in vivo model to analyze the ZEB1/SETD1B interaction. Bioinformatical analysis of CRC patient data was used to examine the ZEB1/SETD1B network under clinical conditions and the ZEB1/SETD1B network was modeled under physiological and pathological conditions. Thus, we identified a self-reinforcing loop for ZEB1 expression and found that the SETD1B associated active chromatin mark H3K4me3 was enriched at the ZEB1 promoter in EMT cells. Moreover, clinical evaluation of CRC patient data showed that the simultaneous high expression of ZEB1 and SETD1B was correlated with the worst prognosis. Here we report that the expression of chromatin modifiers is remarkably dysregulated in EMT cells. SETD1B was identified as a new ZEB1 target in vitro and in vivo. Our study demonstrates a novel example of an activator role of ZEB1 for the epigenetic landscape in colorectal tumor cells.
CRIS-Team Scopus Importer:2020-03-20

Endogenous Expression of the Human CD83 Attenuates EAE Symptoms in Humanized Transgenic Mice and Increases the Activity of Regulatory T Cells - Zinser, Elisabeth; Naumann, Ronald; Wild, Andreas; Michalski, Julia; Deinzer, Anja; Stich, Lena; Kuhnt, Christine; Steinkasserer, Alexander; Knippertz, Ilka (Frontiers in Immunology, 2019)
The CD83 is a type I membrane protein and part of the immunoglobulin superfamily of receptors. CD83 is involved in the regulation of antigen presentation and dendritic cell dependent allogeneic T cell proliferation. A soluble form of CD83 inhibits dendritic cell maturation and function. Furthermore, CD83 is expressed on activated B cells, T cells, and in particular on regulatory T cells. Previous studies on murine CD83 demonstrated this molecule to be involved in several immune-regulatory processes, comprising that CD83 plays a key role in the development and function of different immune cells. In order to get further insights into the function of the human CD83 and to provide preclinical tools to guide the function of CD83/sCD83 for therapeutic purposes we generated Bacterial Artificial Chromosomes (BAC) transgenic mice. BACs are excellent tools for manipulating large DNA fragments and are utilized to engineer transgenic mice by pronuclear injection. Two different founders of BAC transgenic mice expressing human CD83 (BAC-hCD83(tg) mice) were generated and were examined for the hCD83 expression on different immune cells as well as both the in vitro and in vivo role of human CD83 (hCD83) in health and disease. Here, we found the hCD83 molecule to be present on activated DCs, B cells and subtypes of CD4(+) T cells. CD8(+) T cells, on the other hand, showed almost no hCD83 expression. To address the function of hCD83, we performed in vitro mixed lymphocyte reactions (MLR) as well as suppression assays and we used the in vivo model of experimental autoimmune encephalomyelitis (EAE) comparing wild-type and hCD83-BAC mice. Results herein showed a clearly diminished capacity of hCD83-BAC-derived T cells to proliferate accompanied by an enhanced activation and suppressive activity of hCD83-BAC-derived Tregs. Furthermore, hCD83-BAC mice were found to recover faster from EAE-associated symptoms than wild-type mice, encouraging the relevance also of the hCD83 as a key molecule for the regulatory phenotype of Tregs in vitro and in vivo.
CRIS-Team WoS Importer:2019-07-12

Engulfment of mast cell secretory granules on skin inflammation boosts dendritic cell migration and priming efficiency - Dudeck, Jan; Froebel, Julia; Kotrba, Johanna; Lehmann, Christian; Dudziak, Diana; Speier, Stephan; Nedospasov, Sergei A.; Schraven, Burkhart; Dudeck, Anne (Journal of Allergy and Clinical Immunology, 2019)
Background: Mast cells (MCs)are best known as key effector cells of allergic reactions, but they also play an important role in host defense against pathogens. Despite increasing evidence for a critical effect of MCs on adaptive immunity, the underlying mechanisms are poorly understood. Objective: Here we monitored MC intercellular communication with dendritic cells (DCs), MC activation, and degranulation and tracked the fate of exocytosed mast cell granules (MCGs)during skin inflammation. Methods: Using a strategy to stain intracellular MCGs in vivo, we tracked the MCG fate after skin inflammation–induced MC degranulation. Furthermore, exogenous MCGs were applied to MC-deficient mice by means of intradermal injection. MCG effects on DC functionality and adaptive immune responses in vivo were assessed by combining intravital multiphoton microscopy with flow cytometry and functional assays. Results: We demonstrate that dermal DCs engulf the intact granules exocytosed by MCs on skin inflammation. Subsequently, the engulfed MCGs are actively shuttled to skin-draining lymph nodes and finally degraded inside DCs within the lymphoid tissue. Most importantly, MCG uptake promotes DC maturation and migration to skin-draining lymph nodes, partially through MC-derived TNF, and boosts their T-cell priming efficiency. Surprisingly, exogenous MCGs alone are sufficient to induce a prominent DC activation and T-cell response. Conclusion: Our study highlights a unique feature of peripheral MCs to affect lymphoid tissue–borne adaptive immunity over distance by modifying DC functionality through delivery of granule-stored mediators.
CRIS-Team Scopus Importer:2019-05-03
Keywords: adaptive immune response; dendritic cells; Mast cells; skin inflammation; T-cell response

Enhancing lentiviral transduction to generate melanoma-specific human T cells for cancer immunotherapy - Simon, Bianca; Harrer, Dennis C.; Thirion, Christian; Schuler-Thurner, Beatrice; Schuler, Gerold; Uslu, Ugur (Journal of Immunological Methods, 2019)
Introduction of a tumor antigen-specific T cell receptor (TCR) into patient-derived lymphocytes has already exhibited promising results for the treatment of melanoma and other malignancies in clinical trials. However, insufficient or unsuccessful ex vivo manufacturing of engineered T cells due to low expansion and/or transduction rate can still be observed in some patients. Thus, we isolated human CD8+ T cells from healthy donors and equipped them with a gp100-specific TCR using a lentiviral construct in combination with a novel chemical lentiviral transduction enhancer (Lentiboost) to increase the rate of transduced cells. Following experiments to determine the ideal multiplicity of infection (MOI) and to analyze the efficacy of the transduction enhancer using a GFP-encoding lentivirus, we analyzed in the next step the transduction rate, cell count, and functionality of gp100 TCR-transduced T cells, i.e. antigen-specific cytokine secretion and lytic capacity. In order to increase the number of transduced cells, antigen-specific stimulation was performed, either once for 1 week (1st activation) or twice for another week (2nd activation). In general, each cycle of antigen-specific stimulation resulted in expansion of TCR-positive cells, while no further significant increase of transduced cells was observed after 2nd activation. Cytokine production pattern of transduced cells after antigen encounter, however, revealed significant antigen-specific secretion of TNF and IFNγ after the 1st as well as the 2nd activation. Furthermore, TCR T cells, either activated once or twice, showed significant cytotoxicity towards antigen-positive tumor cells. Taken together, these results show that it is feasible to transduce human T cells using a lentiviral construct in combination with this novel lentiviral transduction enhancer, which shows potential in the growing field of cancer immunotherapy.
CRIS-Team Scopus Importer:2019-06-25
Keywords: Adoptive T cell therapy; gp100; Lentiboost; Lentivirus; T cell receptor; Tumor antigen

Environment affects dendritic cells' response via Aryl Hydrocarbon Receptor ligands: a comparison between endogenous and exogenous ligands - Sadeghi Shermeh, Atefeh; Wild, Andreas; Michalski, Julia; Steinkasserer, Alexander (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Environmental signals rather than layered ontogeny imprint the function of type 2 conventional dendritic cells in young and adult mice - Papaioannou, Nikos E.; Salei, Natallia; Rambichler, Stephan; Ravi, Kaushikk; Popovic, Jelena; Küntzel, Vanessa; Lehmann, Christian; Fiancette, Remi; Salvermoser, Johanna; Gajdasik, Dominika W.; Mettler, Ramona; Messerer, Denise; et al. (Nature Communications, 2021)
Conventional dendritic cells (cDC) are key activators of naive T cells, and can be targeted in adults to induce adaptive immunity, but in early life are considered under-developed or functionally immature. Here we show that, in early life, when the immune system develops, cDC2 exhibit a dual hematopoietic origin and, like other myeloid and lymphoid cells, develop in waves. Developmentally distinct cDC2 in early life, despite being distinguishable by fate mapping, are transcriptionally and functionally similar. cDC2 in early and adult life, however, are exposed to distinct cytokine environments that shape their transcriptional profile and alter their ability to sense pathogens, secrete cytokines and polarize T cells. We further show that cDC2 in early life, despite being distinct from cDC2 in adult life, are functionally competent and can induce T cell responses. Our results thus highlight the potential of harnessing cDC2 for boosting immunity in early life.
CRIS-Team Scopus Importer:2021-01-29

Envisioning the application of systems biology in cancer immunology - Jaitly, Tanushree; Gupta, Shailendra K.; Wolkenhauer, Olaf; Schuler, Gerold; Vera, Julio (Cancer Immunology: A Translational Medicine Context, 2020)
Biomedical research is nowadays concerned with the investigation of complex biological networks, in which dozens to thousands of proteins, genes, and miRNAs interact to control cellular or tissue-level phenotypes. Investigation of these complex biological networks requires the use of various experimental methodologies that generate massive amounts of quantitative data. In this scenario, Systems Biology emerged a decade ago as a methodological approach that combines quantitative experimental data, mathematical modeling, and other tools from computational biology, aiming to understand the regulation of these complex biochemical systems. The interaction between tumors and the immune system is not an exception to this scenario. The immune system is by definition a multiscale system not only because it involves biochemical networks that regulate the fate of immune cells, but also because immune cells communicate with each other by direct contact or through secretion of local or global signals. Furthermore, tumor and immune cells communicate, and this interaction is affected by the features of the microenvironment in which the tumor is hosted. Altogether, we are envisioning a complex multiscale biological system, whose analysis requires a systemic view to succeed integrating massive amounts of quantitative experimental data coming from different temporal and spatial scales. In this book chapter, we introduce the elements of the systems biology approach. Furthermore, we discuss some published results that suggest how systems biology can be used in the context of oncology and tumor immunology, with a focus on the development and assessment of anticancer therapies. To facilitate the reading, the chapter contains a glossary of systems biology terms.
CRIS-Team Scopus Importer:2020-06-19
Keywords: Biochemical Networks; Computational Approaches; Immunolgy; Omics; Tumor

Eosinophil-cationic protein - a novel liquid prognostic biomarker in melanoma - Krueckel, Annika; Moreira, Alvaro; Froehlich, Waltraud; Schuler, Gerold; Heinzerling, Lucie (BMC Cancer, 2019)
BackgroundThe role of eosinophils in cancer is not yet completely understood, but patients with eosinophilia show a trend towards longer survival in several types of cancer, including melanoma. However, eosinophil count at initial diagnosis of metastatic melanoma does not predict survival. Since eosinophil cationic protein (ECP) mediates anticancer effects, such as tissue remodelling and cytotoxic activity, we investigated this marker as an early prognostic marker in metastatic melanoma.MethodsSerum of 56 melanoma patients was collected at the time of diagnosis of metastatic disease. ECP levels as measured by ELISA were correlated with overall survival (OS) in patients before systemic therapy with immunotherapy or chemotherapy. Statistical analyses were performed using the Log-Rank (Mantel-Cox) test.ResultsThe median OS for patients with high serum ECP above 12.2ng/ml was 12months (n=39), compared to 28months for patients with ECP below this threshold (n=17; p=0.0642). In patients with cutaneous melanoma, excluding patients with uveal and mucosal melanoma, the survival difference was even more striking (p=0.0393). ECP's effect size on OS was observed independently of the consecutive therapy. ECP levels were not correlated with LDH levels.ConclusionECP seems to be a novel prognostic serum marker for the outcome of melanoma patients, which is independent of LDH and easy to perform in clinical practice. The striking negative prognostic value of high ECP level is unanticipated and can guide patient management.
CRIS-Team WoS Importer:2019-03-22

Eosinophil-cationic protein: A novel liquid prognostic biomarker in melanoma - Moreira, Alvaro; Krueckel, Annika; Schuler, Gerold; Heinzerling, Lucie (2018)
EVALuna2:203621

Eosinophilic count as a biomarker for prognosis of melanoma patients and its importance in the response to immunotherapy - Moreira, Alvaro; Leisgang, Waltraud; Schuler, Gerold; Heinzerling, Lucie (Immunotherapy, 2017)
AIM: The prognostic role of eosinophils in cancer has been controversial. Some entities such as gastrointestinal cancers show a better survival, while others such as Hodgkin's lymphoma a worse survival in patients with eosinophilia. Patients who exhibited an increase in eosinophils upon therapy with ipilimumab or pembrolizumab were shown to survive longer. We wanted to investigate whether eosinophilia is a prognostic marker in metastatic melanoma. METHODS: In total, 173 patients with metastatic melanoma from our data base (median age 60 years; n = 86 with immunotherapy, n = 87 without immunotherapy) were analyzed for eosinophil counts and survival over the course of 12 years. Eosinophilic count was detected by peripheral blood smear. The ethical committee had approved this retrospective study. RESULTS: Melanoma patients with eosinophilia at any point in their course of disease show a trend toward longer survival independently of their therapy. There is a statistically significant difference for the patients who survive at least 12 months (p < 0.005). In patients with checkpoint inhibitor therapy, survival was significantly prolonged in every patient with eosinophilia (p < 0.05). Furthermore, 69% of the patients treated with immunotherapy experienced at least once an eosinophilia of 5% or greater compared with 46% in the immunotherapy naive-group; for an eosinophilia of 10% values were 30 and 9%, respectively. Interestingly, in patients with more than 20% eosinophils (n = 7) survival was prolonged with a median of 35 months (range 19-60 months) as compared with 16 months (range 1-117 months). CONCLUSION: Eosinophilia is a prognostic marker in patients with metastatic melanoma.
EVALuna2:34325

Eosinophilic Fasciitis by Treatment with Checkpoint Inhibitors in metastatic Melanoma - Toussaint, Frédéric; Erdmann, M.; Moreira, Alvaro; Kirchberger, M. C.; Schuler, Gerold; Heinzerling, Lucie (2018)
EVALuna2:34779

Epidermotropism of inflammatory cells differentiates pyoderma gangrenosum from venous leg ulcers - Ronicke, Moritz; Baur, Andreas; Kirr, Michael; Erdmann, Michael; Erfurt-Berge, Cornelia; Ostalecki, Christian (Journal der Deutschen Dermatologischen Gesellschaft, 2022)
Background and objectives Pyoderma gangrenosum is an ulcerative autoinflammatory disease, lacking distinct histopathological characteristics to differentiate from other ulcerating conditions, like venous leg ulcers. The objective of this study was therefore to find histopathological characteristics of pyoderma gangrenosum in a head-to-head comparison to venous leg ulcers. Patients and methods Eight tissue samples of pyoderma gangrenosum, twelve samples of venous leg ulcers and six samples of healthy skin were stained using an immunohistological multi antigen staining technology. The immune infiltrate and its spatial distribution were analyzed with contextual tissue cytometry software using fluorescence images. Results The dense epidermal presence of CD45RO(+) memory T cells and the rarefication of CD1a(+) Langerhans cells in the epidermis were defining markers for pyoderma gangrenosum, implicating an epidermal immune reaction. In addition, high numbers of CD11c(+)CD68(+) pro-inflammatory M1 macrophages were detected in the dermis, significantly extending the numbers seen in venous leg ulcers. Conclusions The histopathological differences found between pyoderma gangrenosum and venous leg ulcer can be used to distinguish between the two diseases and thus provide an important aid for the rapid initiation of adequate therapy. In addition, our data hint at an antigen-driven process in the epidermis, possibly involving CD1a(+) Langerhans cells.
CRIS-Team WoS Importer:2022-05-13

Erkennen und Management relevanter Komorbiditäten bei chronischer spontaner Urtikaria - Wagner, Nicola; Berking, Carola (Die Dermatologie, 2024)
Various mechanisms contributing to the activity of chronic spontaneous urticaria (CU) have been postulated. Associated comorbidities are increasingly leading to the discovery of further signaling pathways which may support the activity of chronic urticaria or contribute to low-grade systemic inflammation. Moreover psychoimmunological factors may also be involved. The aim of this work is to improve the clinical care of patients with CU by increasing knowledge regarding optional influencing factors due to comorbidities and to possibly influence disease activity. Chronic urticaria due to autoimmune mechanisms may dispose to other autoimmune diseases, especially autoimmune thyroiditis, which can trigger chronic disease. Association of CU with metabolic syndrome has received little attention to date. Obesity may contribute to low-grade systemic inflammation by cytokine-secreting adipose tissue and hence to mediator-release of mast cells. Furthermore, neuroimmunological pathways, especially increased release of substance P, an activating ligand of Mas-related G protein-coupled receptor X2 (MRGPX2) on mast cells, should be addressed when optimizing therapy.
CRIS-Team Scopus Importer:2024-03-08
Keywords: Chronic disease; Co-factors; Disease progression; Risk factors; Treatment optimization

European consensus-based interdisciplinary guideline for diagnosis, treatment and prevention of actinic keratoses, epithelial UV-induced dysplasia and field cancerization on behalf of European Association of Dermato-Oncology, European Dermatology Forum, European Academy of Dermatology and Venereology and Union of Medical Specialists (Union Européenne des Médecins Spécialistes) - Kandolf, Lidija; Peris, Ketty; Malvehy, Josep; Mosterd, Klara; Heppt, Markus; Fargnoli, Maria Concetta; Berking, Carola; Arenberger, Petr; Bylaite-Bučinskiene, Matilda; del Marmol, Veronique; Dirschka, Thomas; Dreno, Brigitte; et al. (Journal of the European Academy of Dermatology and Venereology, 2024)
A collaboration of multidisciplinary experts from the European Association of Dermato-Oncology, the European Dermatology Forum, the European Academy of Dermatology and Venereology, and the European Union of Medical Specialists was formed to develop European recommendations on AK diagnosis and treatment, based on current literature and expert consensus. This guideline addresses the epidemiology, diagnostics, risk stratification and treatments in immunocompetent as well as immunosuppressed patients. Actinic keratoses (AK) are potential precursors of cutaneous squamous cell carcinoma (cSCC) and display typical histopathologic and immunohistochemical features of this malignancy in an early stage. They can develop into cSSC in situ and become invasive in a low percentage of cases. AK is the most frequent neoplasia in white populations, frequently occurring within a cancerous field induced by ultraviolet radiation. Since it cannot be predicted, which lesion will progress to cSCC and when treatment is usually recommended. The diagnosis of AK and field cancerization is made by clinical examination. Dermatoscopy, confocal microscopy, optical coherence tomography or line-field confocal-OCT can help in the differential diagnosis of AK and other skin neoplasms. A biopsy is indicated in clinically and/or dermatoscopically suspicious and/or treatment-refractory lesions. The choice of treatment depends on patients' and lesion characteristics. For single non-hyperkeratotic lesions, the treatment can be started upon patient's request with destructive treatments or topical treatments. For multiple lesions, field cancerization treatment is advised with topical treatments and photodynamic therapy. Preventive measures such as sun protection, self-examination and repeated field cancerization treatments of previously affected skin areas in high-risk patients are advised.
CRIS-Team Scopus Importer:2024-05-17

European Dermatology Forum S1-guideline on the diagnosis and treatment of sclerosing diseases of the skin, Part 1: localized scleroderma, systemic sclerosis and overlap syndromes - Knobler, R.; Moinzadeh, P.; Hunzelmann, N.; Kreuter, A.; Cozzio, A.; Mouthon, L.; Cutolo, M.; Rongioletti, F.; Denton, C. P.; Rudnicka, L.; Frasin, L. A.; Smith, V.; et al. (Journal of the European Academy of Dermatology and Venereology, 2017)
The term 'sclerosing diseases of the skin' comprises specific dermatological entities, which have fibrotic changes of the skin in common. These diseases mostly manifest in different clinical subtypes according to cutaneous and extracutaneous involvement and can sometimes be difficult to distinguish from each other. The present guideline focuses on characteristic clinical and histopathological features, diagnostic scores and the serum autoantibodies most useful for differential diagnosis. In addition, current strategies in the first- and advanced-line therapy of sclerosing skin diseases are addressed in detail. Part 1 of this guideline provides clinicians with an overview of the diagnosis and treatment of localized scleroderma (morphea), and systemic sclerosis including overlap syndromes of systemic sclerosis with diseases of the rheumatological spectrum.
EVALuna2:34344

European dermatology forum S1-guideline on the diagnosis and treatment of sclerosing diseases of the skin, Part 2: Scleromyxedema, scleredema and nephrogenic systemic fibrosis - Knobler, R.; Moinzadeh, P.; Hunzelmann, N.; Kreuter, A.; Cozzio, A.; Mouthon, L.; Cutolo, M.; Rongioletti, F.; Denton, C. P.; Rudnicka, L.; Frasin, L. A.; Smith, V.; et al. (Journal of the European Academy of Dermatology and Venereology, 2017)
The term 'sclerosing diseases of the skin' comprises specific dermatological entities which have fibrotic changes of the skin in common. These diseases mostly manifest in different clinical subtypes according to cutaneous and extracutaneous involvement and can sometimes be difficult to distinguish from each other. The present guideline focuses on characteristic clinical and histopathological features, diagnostic scores and the serum autoantibodies most useful for differential diagnosis. In addition, current strategies in the first- and advanced-line therapy of sclerosing skin diseases are addressed in detail. Part 2 of this guideline provides clinicians with an overview of the diagnosis and treatment of scleromyxedema, scleredema (of Buschke) and nephrogenic systemic sclerosis (nephrogenic fibrosing dermopathy).
EVALuna2:34341

Evaluation of Long-term Clearance Rates of Interventions for Actinic Keratosis. A Systematic Review - Steeb, Theresa; Wessely, Anja; Petzold, Anne; Brinker, Titus Josef; Schmitz, Lutz; Leiter, Ulrike; Garbe, Claus; Schöffski, Oliver; Berking, Carola; Heppt, M. V. (JAMA Dermatology, 2021)
Importance Multiple interventions are available for the treatment of actinic keratosis (AK). However, most randomized clinical trials and meta-analyses focus on short-term efficacy outcomes. Objective To investigate and synthesize the long-term efficacy (≥12 months) of interventions for AK from parallel-arm randomized clinical trials. Data Sources Searches in MEDLINE, Embase, and Central were conducted from inception until April 6, 2020. The reference lists of the included studies and pertinent trial registers were hand searched. The study was completed February 27, 2021. Study Selection Two reviewers screened the titles and abstracts of 2741 records. Finally, 17 published reports (original studies and follow-up reports) referring to 15 independent randomized clinical trials with an overall sample size of 4252 patients were included. Data Extraction and Synthesis Two reviewers independently extracted data on study, patient, and intervention characteristics. Network meta-analysis (NMA) of each outcome was conducted with a frequentist approach. The Grading of Recommendations Assessment, Development, and Evaluation (GRADE) guidance for NMA was used to assess the certainty of evidence. The revised Cochrane risk-of-bias tool for randomized clinical trials was used to evaluate the methodologic quality. Main Outcomes and Measures Participant complete clearance, participant partial clearance, and lesion-specific clearance were the outcomes, with each assessed at least 12 months after the end of treatment. Results Data from 15 independent randomized clinical trials including 4252 patients were extracted and synthesized. Ten studies were included in an NMA for the outcome of participant complete clearance, with photodynamic therapy with aminolevulinate (ALA-PDT) showing the most favorable risk ratio (RR) compared with placebo (RR, 8.06; 95% CI, 2.07-31.37; GRADE, moderate), followed by imiquimod, 5% (RR, 5.98; 95% CI, 2.26-15.84; GRADE, very low), photodynamic therapy with methyl aminolevulinate (MAL-PDT) (RR, 5.95; 95% CI, 1.21-29.41; GRADE, low), and cryosurgery (RR, 4.67; 95% CI, 1.36-16.66; GRADE, very low). Similarly, ALA-PDT had the highest RR in the NMA for lesion-specific clearance (RR, 5.08; 95% CI, 2.49-10.33; GRADE, moderate). No NMA was possible for participant partial clearance owing to poor reporting of this outcome. Conclusions and Relevance This systematic review and network meta-analysis found that therapy including ALA-PDT, imiquimod, 5%, MAL-PDT, and cryosurgery was associated with significant long-term efficacy in the NMA. This study provides data for a possible use in an evidence-based framework for selecting interventions with sustained lesion clearanc
CRIS-Team WoS Importer:2021-08-13

Evaluation of PD-L1 Expression and HPV Genotyping in Anal Squamous Cell Carcinoma - Wessely, Anja; Heppt, Markus; Kammerbauer, Claudia; Steeb, Theresa; Kirchner, Thomas; Flaig, Michael J.; French, Lars E.; Berking, Carola; Schmoeckel, Elisa; Reinholz, Markus (Cancers, 2020)
Simple Summary
CRIS-Team WoS Importer:2020-11-06

Evidence for liver and peripheral immune cells secreting tumor-suppressive extracellular vesicles in melanoma patients - Lee, Jung Hyun; Eberhardt, Martin; Blume, Katja; Vera, Julio; Baur, Andreas (EBioMedicine, 2020)
Background: Before and after surgery melanoma patients harbor elevated levels of extracellular vesicles in plasma (pEV), suppressing tumor cell activity. However, due to technical reasons and lack of cell-specific biomarkers, their cellular origin remains obscure. Methods: We mimicked the interaction of tumor cells with liver cells and PBMC in vitro, and compared newly secreted EV-associated miRNAs and protein factors with those detected in melanoma patient`s pEV. Findings: Our results suggest that pEV from melanoma patients are secreted in part by residual or relapsing tumor cells, but also by liver and peripheral blood mononuclear cells (PBMC). Our approach identified factors that were seemingly associated either with tumor cell activity, or the counteracting immune system, including liver cells. Notably, the presence/absence of these factors correlated with the clinical stage and tumor relapse. Interpretation: Our study may provide new insights into the innate immune defense against tumor cells and implies that residual tumor cells could be more active than previously thought. In addition we provide some preliminary evidence that pEV marker patterns could be used to predict cancer relapse.
CRIS-Team Scopus Importer:2020-12-04
Keywords: Circulating tumor cells; Liver cells; Melanoma.; miRNA; Pev origin; Plasma extracellular vesicles (pev); Pro-inflammatory cytokines

Exosomal lncRNAs and cancer: connecting the missing links - Naderi-Meshkin, Hojjat; Lai, Xin; Amirkhah, Raheleh; Vera, Julio; Rasko, John E. J.; Schmitz, Ulf (Bioinformatics, 2019)
Motivation: Extracellular vesicles (EVs), including exosomes and microvesicles, are potent and clinically valuable tools for early diagnosis, prognosis and potentially the targeted treatment of cancer. The content of EVs is closely related to the type and status of the EV-secreting cell. Circulating exosomes are a source of stable RNAs including mRNAs, microRNAs and long noncoding RNAs (lncRNAs).
CRIS-Team WoS Importer:2019-03-06

Experiences of In-Patients with Skin Cancer in a German University Hospital Setting: A Cross-Sectional Survey - Steeb, Theresa; Wessely, Anja; Merkl, Heike; Voskens, Caroline; Erdmann, Michael; Heinzerling, Lucie; Berking, Carola; Heppt, Markus (Patient Preference and Adherence, 2021)
Purpose: An important measure of hospital quality is the satisfaction of the patients receiving in-patient care. This cross-sectional study aimed to assess skin cancer patients' experiences in a university hospital setting as a measure of quality of cancer care.
CRIS-Team WoS Importer:2021-01-29

Explainable artificial intelligence in skin cancer recognition: A systematic review - Hauser, Katja; Kurz, Alexander; Haggenmüller, Sarah; Maron, Roman C.; von Kalle, Christof; Utikal, Jochen S.; Meier, Friedegund; Hobelsberger, Sarah; Gellrich, Frank F.; Sergon, Mildred; Hauschild, Axel; French, Lars E.; et al. (European Journal of Cancer, 2022)
Background: Due to their ability to solve complex problems, deep neural networks (DNNs) are becoming increasingly popular in medical applications. However, decision-making by such algorithms is essentially a black-box process that renders it difficult for physicians to judge whether the decisions are reliable. The use of explainable artificial intelligence (XAI) is often suggested as a solution to this problem. We investigate how XAI is used for skin cancer detection: how is it used during the development of new DNNs? What kinds of visualisations are commonly used? Are there systematic evaluations of XAI with dermatologists or dermatopathologists? Methods: Google Scholar, PubMed, IEEE Explore, Science Direct and Scopus were searched for peer-reviewed studies published between January 2017 and October 2021 applying XAI to dermatological images: the search terms histopathological image, whole-slide image, clinical image, dermoscopic image, skin, dermatology, explainable, interpretable and XAI were used in various combinations. Only studies concerned with skin cancer were included. Results: 37 publications fulfilled our inclusion criteria. Most studies (19/37) simply applied existing XAI methods to their classifier to interpret its decision-making. Some studies (4/37) proposed new XAI methods or improved upon existing techniques. 14/37 studies addressed specific questions such as bias detection and impact of XAI on man-machine-interactions. However, only three of them evaluated the performance and confidence of humans using CAD systems with XAI. Conclusion: XAI is commonly applied during the development of DNNs for skin cancer detection. However, a systematic and rigorous evaluation of its usefulness in this scenario is lacking.
CRIS-Team Scopus Importer:2022-04-15
Keywords: Artificial intelligence; Dermatology; Man-machine systems; Skin neoplasms; Systematic review

Expression of Senescence Markers - Is Predictive for Immune Therapy with Checkpoint Inhibitors? - Moreira, Alvaro; Gross, S.; Kirchberger, M. C.; Erdmann, M.; Schuler, Gerold; Heinzerling, Lucie (2018)
EVALuna2:34778

Extensive furuncular myiasis in a travel returnee from Africa - Rechtien, Laura; Kaufmann, Matthias; Sticherling, Michael (Journal of the European Academy of Dermatology and Venereology, 2023)
CRIS-Team Scopus Importer:2023-02-17

Extracellular vesicles from mature dendritic cells (DC) differentiate monocytes into immature DC - Schierer, Stefan; Ostalecki, Christian; Zinser, Elisabeth; Lamprecht, Ricarda; Plosnita, Bianca; Stich, Lena; Dörrie, Jan; Lutz, Manfred B.; Schuler, Gerold; Baur, Andreas (Life Science Alliance, 2018)
During inflammation, murine and human monocytes can develop into dendritic cells (DC), but this process is not entirely understood. Here, we demonstrate that extracellular vesicles (EV) secreted by mature human DC (maDC) differentiate peripheral monocytes into immature DC, expressing a unique marker pattern, including 6-sulfo LacNAc (slan), Zbtb46, CD64, and CD14. While EV from both maDC and immature DC differentiated monocytes similar to GM-CSF/IL-4 stimulation, only maDC-EV produced precursors, which upon maturation stimulus developed into T-cell-activating and IL-12p70-secreting maDC. Mechanistically, maDC-EV induced cell signaling through GM-CSF, which was abundant in EV as were IL-4 and other cytokines and chemokines. When injected into the mouse skin, murine maDC-EV attracted immune cells including monocytes that developed activation markers typical for inflammatory cells. Skin-injected EV also reached lymph nodes, causing a similar immune cell infiltration. We conclude that DC-derived EV likely serve to perpetuate an immune reaction and may contribute to chronic inflammation.
EVALuna2:36337

Extracellular Vesicles in the Plasma of Melanoma Patients under-press beta Catenin in Tumor Cells by using miRNA-34a - Baur, A.; Lee, J. H.; Dindorf, J.; Eberhardt, Martin; Lai, Xin; Ostalecki, Christian; Koliha, N.; Wild, Stefanie; Gross, S.; Schuler, Gerold; Vera González, Julio (2018)
EVALuna2:34772

Ex vivo expanded NK Cells from Melanoma Patients receive their Migration in a 3D Model and lyse autologous Melanoma Cells - Rossner, S.; Czerwinski, Tina; Mark, Christoph; Gross, S.; Karg, Margarete; Bosch, Jacobus J.; Schuler-Thurner, Beatrice; Fabry, Ben; Schuler, Gerold; Bosch-Voskens, C. (2018)
EVALuna2:34775

Ex vivo expanded NK cells up-regulate natural cytotoxicity receptors able to mediate autologous melanoma cell killing - Roessner, S.; Gross, S.; Karg, M.; Hamann, A.; Campana, D.; Schuler-Thurner, Beatrice; Bosch, Jacobus J.; Schuler, Gerold; Voskens, C. J. (2017)
EVALuna2:34314

Factors Influencing Disease Progression in Patients with Head and Neck Melanoma - Uslu, Ugur; Schuler, Gerold; Breuninger, Helmut (Anticancer Research, 2017)
BACKGROUND: Histological parameters as well as the status of sentinel lymph node are known to be strong prognostic factors in patients with melanoma. PATIENTS AND METHODS: In this study, we retrospectively analyzed 1,384 patients who were diagnosed with head and neck melanoma between 1976 and 2010 regarding prognostic factors [tumor thickness, level of invasion, sentinel lymph node (SLN) status, ulceration, histological subtype, localization, and gender], overall survival, and disease-free survival. RESULTS: Patients who developed metastases had a significantly thicker tumor than patients without metastases. Additionally, a thicker tumor was often associated with a higher level of invasion (Clark level). There was no overall survival benefit in patients who underwent SLN dissection when compared to patients who did not (p=0.07). Compared to SLN-negative patients, patients with SLN involvement had a significantly shorter disease-free period (p<0.001) and shorter overall survival time (p<0.001). CONCLUSION: In summary, tumor thickness is the most important prognostic factor. SLN dissection does not affect the overall survival of patients with melanoma. However, a positive SLN is a marker for a worse outcome in these patients.
EVALuna2:34319

Factors influencing the adjuvant therapy decision: Results of a real-world multicenter data analysis of 904 melanoma patients - Lodde, Georg; Forschner, Andrea; Hassel, Jessica; Wulfken, Lena M.; Meier, Friedegund; Mohr, Peter; Kähler, Katharina; Schilling, Bastian; Loquai, Carmen; Berking, Carola; Hüning, Svea; Schatton, Kerstin; et al. (Cancers, 2021)
Adjuvant treatment of melanoma patients with immune-checkpoint inhibition (ICI) and targeted therapy (TT) significantly improved recurrence-free survival. This study investigates the real-world situation of 904 patients from 13 German skin cancer centers with an indication for adjuvant treatment since the approval of adjuvant ICI and TT. From adjusted log-binomial regression models, we estimated relative risks for associations between various influence factors and treatment decisions (adjuvant therapy yes/no, TT vs. ICI in BRAF mutant patients). Of these patients, 76.9% (95% CI 74–80) opted for a systemic adjuvant treatment. The probability of starting an adjuvant treatment was 26% lower in patients >65 years (RR 0.74, 95% CI 68–80). The most common reasons against adjuvant treatment given by patients were age (29.4%, 95% CI 24–38), and fear of adverse events (21.1%, 95% CI 16–28) and impaired quality of life (11.9%, 95% CI 7–16). Of all BRAF-mutated patients who opted for adjuvant treatment, 52.9% (95% CI 47–59) decided for ICI. Treatment decision for TT or ICI was barely associated with age, gender and tumor stage, but with comorbidities and affiliated center. Shortly after their approval, adjuvant treatments have been well accepted by physicians and patients. Age plays a decisive role in the decision for adjuvant treatment, while pre-existing autoimmune disease and regional differences influence the choice between TT or ICI.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Adjuvant treatment; BRAF; Checkpoint blocker; Melanoma; PD-1; Targeted therapy

Fatigue and Atopic Dermatitis: Results from the German Atopic Dermatitis Registery TREATgermany - Helmert, C.; Haufe, E.; Abraham, S.; Heratizadeh, A.; Harder,; Kleinheinz, A.; Wollenberg, A.; Wiemers, F.; Weisshaar, E.; Augustin, M.; Von Kiedrowski, R.; Wildberg, J.; et al. (GESUNDHEITSWESEN, 2021)
CRIS-Team WoS Importer:2022-05-20

Fcγ receptor IIB (FcγRIIB) maintains humoral tolerance in the human immune system in vivo. - Bärenwaldt, Anne; Lux, Anja; Danzer, Heike; Spriewald, Bernd M.; Ullrich, Evelyn; Heidkamp, Gordon Frederik; Dudziak, Diana; Nimmerjahn, Falk (Proceedings of the National Academy of Sciences of the United States of America, 2011)
Maintenance of immunological tolerance is crucial to prevent development of autoimmune disease. The production of autoantibodies is a hallmark of many autoimmune diseases and studies in mouse model systems suggest that inhibitory signaling molecules may be important checkpoints of humoral tolerance. By generating humanized mice with normal and functionally impaired Fcγ receptor IIB (FcγRIIB) variants, we show that the inhibitory Fcγ-receptor is a checkpoint of humoral tolerance in the human immune system in vivo. Impaired human FcγRIIB function resulted in the generation of higher levels of serum immunoglobulins, the production of different autoantibody specificities, and a higher proportion of human plasmablasts and plasma cells in vivo. Our results suggest that the inhibitory FcγRIIB may be an important checkpoint of humoral tolerance in the human immune system.

FcγRIV deletion reveals its central role for IgG2a and IgG2b activity in vivo. - Nimmerjahn, Falk; Lux, Anja; Albert, Heike; Woigk, Melissa; Lehmann, Christian; Dudziak, Diana; Smith, Patrick; Ravetch, J. V. (Proceedings of the National Academy of Sciences of the United States of America, 2010)
Cellular Fcγ receptors are essential for IgG-dependent effector functions in vivo. There is convincing evidence that selective activating Fcγ receptors are responsible for the activity of individual IgG subclasses. Thus, IgG1 activity is absent in FcγRIII-deficient mice, and several studies suggest that the activity of the most potent IgG subclasses, IgG2a and IgG2b, might be dependent on either individual or a combination of activating FcγRs. To study the role of individual activating FcγRs for IgG subclass activity, we generated an FcγRIV-deficient mouse and showed that a variety of IgG2a- and IgG2b-dependent effector functions are impaired in the absence of this activating Fc receptor in models of autoimmunity and antibody-dependent cellular cytotoxicity.

Federated Learning for Decentralized Artificial Intelligence in Melanoma Diagnostics - Haggenmüller, Sarah; Schmitt, Max; Krieghoff-Henning, Eva; Hekler, Achim; Maron, Roman C.; Wies, Christoph; Utikal, Jochen S.; Meier, Friedegund; Hobelsberger, Sarah; Gellrich, Frank F.; Sergon, Mildred; Hauschild, Axel; et al. (JAMA Dermatology, 2024)
Importance: The development of artificial intelligence (AI)-based melanoma classifiers typically calls for large, centralized datasets, requiring hospitals to give away their patient data, which raises serious privacy concerns. To address this concern, decentralized federated learning has been proposed, where classifier development is distributed across hospitals. Objective: To investigate whether a more privacy-preserving federated learning approach can achieve comparable diagnostic performance to a classical centralized (ie, single-model) and ensemble learning approach for AI-based melanoma diagnostics. Design, Setting, and Participants: This multicentric, single-arm diagnostic study developed a federated model for melanoma-nevus classification using histopathological whole-slide images prospectively acquired at 6 German university hospitals between April 2021 and February 2023 and benchmarked it using both a holdout and an external test dataset. Data analysis was performed from February to April 2023. Exposures: All whole-slide images were retrospectively analyzed by an AI-based classifier without influencing routine clinical care. Main Outcomes and Measures: The area under the receiver operating characteristic curve (AUROC) served as the primary end point for evaluating the diagnostic performance. Secondary end points included balanced accuracy, sensitivity, and specificity. Results: The study included 1025 whole-slide images of clinically melanoma-suspicious skin lesions from 923 patients, consisting of 388 histopathologically confirmed invasive melanomas and 637 nevi. The median (range) age at diagnosis was 58 (18-95) years for the training set, 57 (18-93) years for the holdout test dataset, and 61 (18-95) years for the external test dataset; the median (range) Breslow thickness was 0.70 (0.10-34.00) mm, 0.70 (0.20-14.40) mm, and 0.80 (0.30-20.00) mm, respectively. The federated approach (0.8579; 95% CI, 0.7693-0.9299) performed significantly worse than the classical centralized approach (0.9024; 95% CI, 0.8379-0.9565) in terms of AUROC on a holdout test dataset (pairwise Wilcoxon signed-rank, P <.001) but performed significantly better (0.9126; 95% CI, 0.8810-0.9412) than the classical centralized approach (0.9045; 95% CI, 0.8701-0.9331) on an external test dataset (pairwise Wilcoxon signed-rank, P <.001). Notably, the federated approach performed significantly worse than the ensemble approach on both the holdout (0.8867; 95% CI, 0.8103-0.9481) and external test dataset (0.9227; 95% CI, 0.8941-0.9479). Conclusions and Relevance: The findings of this diagnostic study suggest that federated learning is a viable approach for the binary classification of invasive melanomas and nevi on a clinically representative distributed dataset. Federated learning can improve privacy protection in AI-based melanoma diagnostics while simultaneously promoting collaboration across institutions and countries. Moreover, it may have the potential to be extended to other image classification tasks in digital cancer histopathology and beyond..
CRIS-Team Scopus Importer:2024-02-23

Fertilität, Kontrazeption und Teratogenität bei Immuncheckpointblockade - Hassel, Jessica C.; Berking, Carola (Die Dermatologie, 2023)
Background: Immune checkpoint inhibitors (ICI) are now being used in a number of dermato-oncological indications. In particular, the approval for adjuvant therapy of high-risk stage IIB/C and III melanoma means that more patients of fertile age receive ICI. Objectives: This raises the question of how ICIs affect male and female fertility and whether they are teratogenic. Materials and methods: Compilation of current data from the summary of product characteristics (SmPCs) and by literature search (PubMed). Results: Immune-related adverse events of ICI can impair fertility in the acute stage, and especially in the case of endocrine side effects, also in the long term. These include hypothyroidism, as well as adrenal and pituitary insufficiency. However, fertility can usually be restored with hormone replacement. Direct autoimmune effects on the reproductive organs are probably very rare, although immune-related orchitis has been described. Reliable contraception should be used in women of childbearing age. Pregnant women should only receive ICI in urgent exceptional cases, because the miscarriage rate is probably significantly increased. Conclusions: Unfortunately, the current data on patient counselling is still very sparse. Scientific studies on the influence of ICI on fertility and teratogenicity are urgently needed.
CRIS-Team Scopus Importer:2023-07-07
Keywords: Autoimmune-associated side effects; Endocrine side effects; High-risk melanoma; Immunotherapy; Miscarriage risk

Fertilität, Teratogenität und Kontrazeption bei BRAF-/MEK-Inhibition - Livingstone, Elisabeth; Berking, Carola (Die Dermatologie, 2023)
Background: Targeted mutation-based therapy with BRAF and MEK inhibitors has become an integral part of systemic therapy for metastatic melanoma in the advanced setting and for the adjuvant therapy of melanoma in stage III after complete resection. Due to the increased chances of survival and early use in the adjuvant situation, fertility preservation as well as aspects of teratogenicity and pregnancy are increasingly relevant in patients who are often still young. Objectives: To communicate the published and study-based information on fertility preservation, teratogenicity and pregnancy under therapy with BRAF and MEK inhibitors. Materials and methods: Summaries of product characteristics as well as studies and case reports on BRAF and MEK inhibitors published in PubMed were used as sources of information. Results: There are no specific preclinical studies or experience in humans on fertility, teratogenicity, and contraception with targeted therapy. Recommendations can only be derived from toxicity studies and individual case reports. Conclusions: Patients should be offered counseling on the options for fertility-protective measures before starting targeted therapy. Due to unclear teratogenicity, adjuvant melanoma therapy with dabrafenib and trametinib should not be initiated in pregnant patients. In the advanced metastatic situation, BRAF and MEK inhibitors should only be given after extensive interdisciplinary education and counselling of the pregnant patient and her partner. Patients should be informed about the need for adequate contraception during targeted therapy.
CRIS-Team Scopus Importer:2023-07-07
Keywords: Fertility preservation; Melanoma; Pharmaceutic adjuvants; Systemic chemotherapy treatment; Targeted therapy

Fertility preservation and management of pregnancy in melanoma patients requiring systemic therapy - Hassel, J. C.; Livingstone, E.; Allam, J. P.; Behre, H. M.; Bojunga, J.; Klein, H. H.; Landsberg, J.; Nawroth, F.; Schuering, A.; Susok, L.; Thoms, K. M.; Kiesel, L.; et al. (ESMO Open, 2021)
Melanoma is one of the most common cancers in adolescents and adults at fertile age, especially in women. With novel and more effective systemic therapies that began to profoundly change the dismal outcome of melanoma by prolonging overall survival, the wish for fertility preservation or even parenthood has to be considered for a growing portion of melanoma patients-from the patients' as well as from the physicians' perspective. The dual blockade of the mitogen-activated protein kinase pathway by B-Raf proto-oncogene serine/threonine kinase and mitogen-activated protein kinase inhibitors and the immune checkpoint inhibition by anti-programmed cell death protein 1 and anti-cytotoxic T-lymphocyte-associated protein-4 monoclonal antibodies constitute the current standard systemic approaches to combat locally advanced or metastatic melanoma. Here, the preclinical data and clinical evidence of these systemic therapies are reviewed in terms of their potential gonadotoxicity, teratogenicity, embryotoxicity and fetotoxicity. Recommendations for routine fertility and contraception counseling of melanoma patients at fertile age are provided in line with interdisciplinary recommendations for the diagnostic work-up of these patients and for fertility-protective measures. Differentiated recommendations for the systemic therapy in both the adjuvant and the advanced, metastatic treatment situation are given. In addition, the challenges of pregnancy during systemic melanoma therapy are discussed.
CRIS-Team WoS Importer:2021-10-29

Fertility preservation in patients with melanoma—a huge relief for those affected Fertilitätserhalt beim Melanom – eine große Entlastung der Betroffenen - Berking, Carola; Hassel, Jessica C.; Livingstone, Elisabeth (Die Dermatologie, 2023)
CRIS-Team Scopus Importer:2023-07-07

First real-world insights on benefit of apremilast treatment in patients with moderate to severe psoriasis after switching from fumaric acid esters from the APART Study - an interim analysis - Mrowietz, U.; Ertner, K.; Sticherling, Michael; Grosse, V.; Popp, G.; Roemmler-Zehrer, J.; Lampl, M.; Helget, U.; Gomez, Nunez N. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-05-17

Four-and-a-Half LIM-Domain Protein 2 (FHL2) Induces Neuropeptide Y (NPY) in Macrophages in Visceral Adipose Tissue and Promotes Diet-Induced Obesity - Sommer, Judith; Ehnis, Hanna; Seitz, Tatjana; Schneider, Julia; Wild, Andreas; Moceri, Sandra; Buechler, Christa; Bozec, Aline; Weber, Georg; Merkel, Susanne; Beckervordersandforth, Ruth; Steinkasserer, Alexander; et al. (International Journal of Molecular Sciences, 2023)
Obesity is characterized by the expansion of the adipose tissue, usually accompanied by inflammation, with a prominent role of macrophages infiltrating the visceral adipose tissue (VAT). This chronic inflammation is a major driver of obesity-associated comorbidities. Four-and-a-half LIM-domain protein 2 (FHL2) is a multifunctional adaptor protein that is involved in the regulation of various biological functions and the maintenance of the homeostasis of different tissues. In this study, we aimed to gain new insights into the expression and functional role of FHL2 in VAT in diet-induced obesity. We found enhanced FHL2 expression in the VAT of mice with Western-type diet (WTD)-induced obesity and obese humans and identified macrophages as the cellular source of enhanced FHL2 expression in VAT. In mice with FHL2 deficiency (FHL2KO), WTD feeding resulted in reduced body weight gain paralleled by enhanced energy expenditure and uncoupling protein 1 (UCP1) expression, indicative of activated thermogenesis. In human VAT, FHL2 was inversely correlated with UCP1 expression. Furthermore, macrophage infiltration and the expression of the chemokine MCP-1, a known promotor of macrophage accumulation, was significantly reduced in WTD-fed FHL2KO mice compared with wild-type (wt) littermates. While FHL2 depletion did not affect the differentiation or lipid metabolism of adipocytes in vitro, FHL2 depletion in macrophages resulted in reduced expressions of MCP-1 and the neuropeptide Y (NPY). Furthermore, WTD-fed FHL2KO mice showed reduced NPY expression in VAT compared with wt littermates, and NPY expression was enhanced in VAT resident macrophages of obese individuals. Stimulation with recombinant NPY induced not only UCP1 expression and lipid accumulation but also MCP-1 expression in adipocytes. Collectively, these findings indicate that FHL2 is a positive regulator of NPY and MCP-1 expression in macrophages and herewith closely linked to the mechanism of obesity-associated lipid accumulation and inflammation in VAT. Thus, FHL2 appears as a potential novel target to interfere with the macrophage–adipocyte crosstalk in VAT for treating obesity and related metabolic disorders.
CRIS-Team Scopus Importer:2023-11-03
Keywords: adipocytes; FHL2; macrophages; MCP-1; NPY; obesity; thermogenesis

FRA-1 TRANSCRIPTION FACTOR EXPRESSION IN MACROPHAGES FOSTER INFLAMMATION DURING RHEUMATOID ARTHRITIS DEVELOPMENT - Hannemann, Nicole; Schnelzer, Anne; Jordan, Jutta; Eberhardt, Martin; Schleicher, Ulrike; Hueber, Axel; Reid, Stephen; Sonnewald, Sophia; Bäuerle, Tobias; Vera, Julio; Bogdan, Christian; Schett, Georg; et al. (2017)
EVALuna2:13497

From relative to absolute Treatment Goals - Correlation of PASI 90 and PASI <=2 in three clinical Studies with Secukinumab - Reich, Kristian; Bachhuber, Teresa; Melzer, Nima; Sieder, Christian; Sticherling, Michael (2018)
EVALuna2:34398

From relative to absolute treatment outcomes-Correlation of PASI 90 and PASI <= 2 in three clinical trials with secukinumab - Reich, Kristian; Bachhuber, Teresa; Melzer, Nima; Sieder, Christian; Sticherling, Michael (2018)
EVALuna2:34781

Fumaric Acid Esters and TNF alpha Inhibitors - Do they affect the Fertility of male Patients with Psoriasis? - Heppt, Franz; Colsmann, A.; Maronna, A.; Uslu, Ugur; Heppt, M.; Kiesewetter, Franklin; Sticherling, Michael (2017)
EVALuna2:34352

Fumaric Acid Esters: Patient Characteristics and Duration of Therapy from the PsoBest German Psoriasis Registry - Augustin, M.; Reich, K.; Spehr, C.; Rustenbach, S. J.; Mrowietz, U.; Radtke, M. A.; Wilsman-Theis, D.; Sticherling, Michael; Thaci, D. (2017)
EVALuna2:34356

Functionalization of T lymphocytes for magnetically controlled immune therapy: Selection of suitable superparamagnetic iron oxide nanoparticles - Mühlberger, Marina; Janko, Christina; Unterweger, Harald; Schreiber, Eveline; Band, Julia; Lehmann, Christian; Dudziak, Diana; Lee, Geoffrey; Alexiou, Christoph; Tietze, Rainer (Journal of Magnetism and Magnetic Materials, 2019)
According to the World Health Organization, cancer is the second most important cause of death in Europe. Due to its manifold manifestations, it is not possible to treat all patients according to a uniform scheme. However, all solid tumors have one thing in common: independent of the tumor's molecular subgroup and the treatment protocol, the immune status of the tumor, especially the amount of tumor infiltrating lymphocytes (TILs), is important for the patient's clinical outcome - the higher the number of TILs, the better the outcome. For this reason it seems desirable to increase the number of TILs. One way to accumulate T cells in the tumor area is to make them magnetizable and attract them with an external magnetic field. Magnetization can be achieved by superparamagnetic iron oxide nanoparticles (SPIONs) which can be bound to the cells' surface or internalized into the cells. For this study, SPIONs with different coatings were synthesized and incubated with immortalized mouse T lymphocytes. SPIONs only stabilized with lauric acid (LA) coated in situ or afterwards showed high toxicity. Addition of an albumin layer increased the biocompatibility but reduced cellular uptake. To increase the cellular uptake the albumin coated particles were aminated, leading to both higher uptake and toxicity, dependent on the degree of amination. In the presence of an externally applied magnetic field, T cells loaded with selected types and amounts of SPIONs were guidable. With this promising pilot study we already can demonstrate that it is possible to attract SPION bearing T cells by an external magnet. To sum up, biocompatibility and uptake of SPIONs by T cells are opposing events. Thus, for the functionalization of T cells with SPIONs the balance between uptake and toxicity must be evaluated carefully.
EVALuna2:35445

Functionalization Of T Lymphocytes With Citrate-Coated Superparamagnetic Iron Oxide Nanoparticles For Magnetically Controlled Immune Therapy - Mühlberger, Marina; Janko, Christina; Unterweger, Harald; Friedrich, Ralf P.; Friedrich, Bernhard; Band, Julia; Cebulla, Nadine; Alexiou, Christoph; Dudziak, Diana; Lee, Geoffrey; Tietze, Rainer (International Journal of Nanomedicine, 2019)
Purpose: Immune activation with T cell tumor infiltration is beneficial for the prognosis of patients suffering from solid cancer. Depending on their immune status, solid tumors can be immunologically classified into three groups: "hot" tumors are infiltrated with T lymphocytes, "cold" tumors are not infiltrated and "immune excluded" tumors are only infiltrated in the peripheral tumor tissue. Checkpoint inhibitors provide new therapeutic options for "hot" tumors by triggering the immune response of T cells. In order to enable this for cold tumors as well, T cells must be enriched in the tumor. Therefore, we use the principle of magnetic targeting to guide T cells loaded with citrate-coated superparamagnetic iron oxide nanoparticles (SPIONCitrate) to the tumor by an externally applied magnetic field. Methods: SPIONCitrate were produced by alkaline coprecipitation of iron(II) and iron(III) chloride and in situ coating with sodium citrate. The concentration-dependent cytocompatibility of the particles was determined by flow cytometry and blood stability assays. Atomic emission spectroscopy was used for the quantification of the particle uptake into T lymphocytes. The attractability of the loaded cells was observed by live-cell imaging in the presence of an externally applied magnetic field. Results: SPIONCitrate displayed good cytocompatibility to T cells and did not show any sign of aggregation in blood. Finally, SPIONCitrate-loaded T cells were strongly attracted by a small external magnet. Conclusion: T cells can be "magnetized" by incorporation of SPIONCitrate for magnetic targeting. The production of the particle-cell hybrid system is straightforward, as the loading process only requires basic laboratory devices and the loading efficiency is sufficient for cells being magnetically controllable. For these reasons, SPIONCitrate are potential suitable candidates for magnetic T cell targeting.
EVALuna2:209938

Functional modulation of regulatory T cells (Tregs) and analyses of the underlying mechanisms - Marosán, Anita; Steinkasserer, Alexander; Wild, Andreas (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-02-17

Functional Specialization of Dendritic Cell Subsets - Heidkamp, Gordon Frederik; Lehmann, Christian; Heger, Lukas; Baransk, A.; Hoffmann, A.; Lühr, Jennifer; Dudziak, Diana (Functional Cell Biology, 2016)
Dendritic cells (DCs) are sentinels of the immune system. Under inflammatory conditions DCs undergo various phenotypical changes, including DC migration, upregulation of co-stimulatory and activating molecules, secretion of cytokines, but also the processing of the engulfed antigens. The DC presents short antigenic peptides on the DC surface as peptide MHC class I or MHC class II complexes to CD8+ or CD4+ T cells, respectively. This article will provide a detailed overview on the antigen processing machineries and specialized functions of the increasing variety of DC subsets in mice and men.
Created from Fastlane, Scopus look-up
Keywords: Antigen presentation; Antigen processing; Antigen targeting; Autophagy; CLR; Cross-presentation; DC; Dendritic cell subsets; FcR; Immune responses; MHC-I; MHC-II; PDC; TLR

FV03 MEK Inhibitors improved the Survival of NRAS-mutated Melanoma Patients by using Checkpoint Inhibitors: Results of a retrospective, multicenter Analysis of 364 Patients - Kirchberger, M. C.; Ugurel, S.; Mangana, J.; Heppt, M.; Eigentler, T.; Berking, C.; Schadendorf, D.; Schuler, Gerold; Dummer, R.; Heinzerling, Lucie (2018)
EVALuna2:34766

gamma/delta T cells RNA-transfected with a T-cell receptor and a chimeric antigen receptor specific for melanoma - Harrer, D.; Simon, B.; Schuler, Gerold; Uslu, Ugur; Hoyer, S.; Dörrie, Jan; Schaft, Niels (2016)
EVALuna2:19612

Gastrointestinal: Eruptive seborrheic keratoses: sign of Leser-Trélat in gastric adenocarcinoma - Kirchberger, M. C. (Journal of Gastroenterology and Hepatology, 2019)
CRIS-Team Scopus Importer:2019-07-12

Generalisierte pustulöse Psoriasis: Überblick zum Status quo und Ergebnisse einer Diskussionsrunde - Reich, Kristian; Augustin, Matthias; Gerdes, Sascha; Ghoreschi, Kamran; Kokolakis, Georgios; Mößner, Rotraut; Mrowietz, Ulrich; Navarini, Alexander A.; Pinter, Andreas; Schäkel, Knut; Staubach, Petra; Sticherling, Michael; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2022)
CRIS-Team Scopus Importer:2022-06-24

Generalized pustular psoriasis: overview of the status quo and results of a panel discussion - Reich, Kristian; Augustin, Matthias; Gerdes, Sascha; Ghoreschi, Kamran; Kokolakis, Georgios; Mößner, Rotraut; Mrowietz, Ulrich; Navarini, Alexander A.; Pinter, Andreas; Schäkel, Knut; Staubach, Petra; Sticherling, Michael; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2022)
Generalized pustular psoriasis (GPP) is a rare, severe, potentially life-threatening, autoinflammatory, neutrophilic skin disease that may be accompanied by fever and leukocytosis. This paper describes the current state of knowledge on GPP in terms of classification, (differential) diagnosis and prevalence. We present a comparison of the genetics and pathoimmunology of GPP and psoriasis vulgaris with the central mechanisms of autoimmunology and autoinflammation. The currently available therapeutic options, expert recommendations for therapy, and data from early clinical trials investigating targeted therapies will be summarized. We present the results of our discussion with 13 experts for psoriasis vulgaris and GPP and give an integrated overview of indication and therapy based on our personal experience and present an outlook on further research questions. Collectively, this article highlights the high unmet need in GPP, as there exists no satisfactory method of diagnosis or treatment to date and new treatment options will be of great therapeutic benefit to those affected.
CRIS-Team Scopus Importer:2022-06-17

Generation of an oncolytic herpes simplex virus 1 expressing human MelanA - Boscheinen, Jan; Thomann, Sabrina; Knipe, David M.; Deluca, Neal; Schuler-Thurner, Beatrice; Gross, Stefanie; Dörrie, Jan; Schaft, Niels; Bach, Christian; Rohrhofer, Anette; Werner-Klein, Melanie; Schmidt, Barbara; et al. (Frontiers in Immunology, 2019)
Robust anti-tumor immunity requires innate as well as adaptive immune responses. We have shown that plasmacytoid dendritic cells develop killer cell-like activity in melanoma cell cocultures after exposure to the infectious but replication-deficient herpes simplex virus 1 (HSV-1) d106S. To combine this innate effect with an enhanced adaptive immune response, the gene encoding human MelanA/MART-1 was inserted into HSV-1 d106S via homologous recombination to increase direct expression of this tumor antigen. Infection of Vero cells using this recombinant virus confirmed MelanA expression by Western blotting, flow cytometry, and immunofluorescence. HSV-1 d106S-MelanA induced expression of the transgene in fibroblast and melanoma cell lines not naturally expressing MelanA. Infection of a melanoma cell line with CRISPR-Cas9-mediated knockout of MelanA confirmed de novo expression of the transgene in the viral context. Dependent on MelanA expression, infected fibroblast and melanoma cell lines induced degranulation of HLA-matched MelanA-specific CD8+ T cells, followed by killing of infected cells. To study infection of immune cells, we exposed peripheral blood mononuclear cells and in vitro-differentiated macrophages to the parental HSV-1 d106S, resulting in expression of the transgene GFP in CD11c+ cells and macrophages. These data provide evidence that the application of MelanA-encoding HSV-1 d106S could enhance adaptive immune responses and re-direct MelanA-specific CD8+ T cells to tumor lesions, which have escaped adaptive immune responses via downregulation of their tumor antigen. Hence, HSV-1 d106S-MelanA harbors the potential to induce innate immune responses in conjunction with adaptive antitumor responses by CD8+ T cells, which should be evaluated in further studies.
CRIS-Team Scopus Importer:2019-05-14
Keywords: Cytotoxic T cell response; Herpes virus; Malignant melanoma; Oncolytic viruses; Vaccine

Generation of CD8(+) T cells expressing two additional T-cell receptors (TETARs) for personalised melanoma therapy. - Hoefflin, Sandra; Prommersberger, Sabrina; Uslu, Ugur; Schuler, Gerold; Schmidt, Christopher W.; Lennerz, Volker; Dörrie, Jan; Schaft, Niels (Cancer Biology & Therapy, 2015)
Adoptive T-cell therapy of cancer often fails due to the tumor cells' immune escape mechanisms, like antigen loss or down-regulation. To anticipate immune escape by loss of a single antigen, it would be advantageous to equip T cells with multiple specificities. To study the possible interference of 2 T-cell receptors (TCRs) in one cell, and to examine how to counteract competing effects, we generated TETARs, CD8(+) T cells expressing two additional T-cell receptors by simultaneous transient transfection with 2 TCRs using RNA electroporation. The TETARs were equipped with one TCR specific for the common melanoma antigen gp100 and one TCR recognizing a patient-specific, individual mutation of CCT6A (chaperonin containing TCP1, subunit 6A) termed "CCT6A(m) TCR." These CD8(+) T cells proved functional in cytokine secretion and lytic activity upon stimulation with each of their cognate antigens, although some reciprocal inhibition was observed. Murinisation of the CCT6A(m) TCR increased and prolonged its expression and increased the lytic capacity of the dual-specific T cells. Taken together, we generated functional, dual-specific CD8(+) T cells directed against a common melanoma-antigen and an individually mutated antigen for the use in personalised adoptive T-cell therapy of melanoma. The intended therapy would involve repetitive injections of the RNA-transfected cells to overcome the transiency of TCR expression. In case of autoimmunity-related side effects, a cessation of treatment would result in a disappearance of the introduced receptors, which increases the safety of this approach.
EVALuna2:19563

Genetic Analysis of MPO Variants in Four Psoriasis Subtypes in Patients from Germany - Haskamp, Stefan; Horowitz, Joseph; Oji, Vinzenz; Philipp, Sandra; Sticherling, Michael; Schäkel, Knut; Schuhmann, Sarah; Prinz, Jörg C.; Burkhardt, Harald; Behrens, Frank; Böhm, Beate; Köhm, Michaela; et al. (Journal of Investigative Dermatology, 2021)
CRIS-Team Scopus Importer:2021-03-26

German YouTube™ videos as a source of information on cutaneous melanoma: a critical appraisal - Steeb, Theresa; Reinhardt, L.; Görgmayr, C.; Weingarten, H.; Doppler, A.; Brütting, J.; Meier, F.; Berking, Carola (Journal of the European Academy of Dermatology and Venereology, 2020)
CRIS-Team Scopus Importer:2020-06-02

Glaucoma-TrEl: A web-based interactive database to build evidence-based hypotheses on the role of trace elements in glaucoma - Choudhari, Jyoti Kant; Eberhardt, Martin; Chatterjee, Tanushree; Hohberger, Bettina; Vera, Julio (BMC Research Notes, 2022)
Objective: Glaucoma is a chronic neurological disease that is associated with high intraocular pressure (IOP), causes gradual damage to retinal ganglion cells, and often culminates in vision loss. Recent research suggests that glaucoma is a complex multifactorial disease in which multiple interlinked genes and pathways play a role during onset and development. Also, differential availability of trace elements seems to play a role in glaucoma pathophysiology, although their mechanism of action is unknown. The aim of this work is to disseminate a web-based repository on interactions between trace elements and protein-coding genes linked to glaucoma pathophysiology. Results: In this study, we present Glaucoma-TrEl, a web database containing information about interactions between trace elements and protein-coding genes that are linked to glaucoma. In the database, we include interactions between 437 unique genes and eight trace elements. Our analysis found a large number of interactions between trace elements and protein-coding genes mutated or linked to the pathophysiology of glaucoma. We associated genes interacting with multiple trace elements to pathways known to play a role in glaucoma. The web-based platform provides an easy-to-use and interactive tool, which serves as an information hub facilitating future research work on trace elements in glaucoma.
CRIS-Team Scopus Importer:2022-12-02
Keywords: glaucoma; Intraocular pressure; Optic nerve; Oxidative stress; Protein-trace element interactions

GM-CSF Monocyte-Derived Cells and Langerhans Cells As Part of the Dendritic Cell Family - Lutz, Manfred B.; Strobl, Herbert; Schuler, Gerold; Romani, Nikolaus (Frontiers in Immunology, 2017)
Dendritic cells (DCs) and macrophages (Mph) share many characteristics as components of the innate immune system. The criteria to classify the multitude of subsets within the mononuclear phagocyte system are currently phenotype, ontogeny, transcription patterns, epigenetic adaptations, and function. More recently, ontogenetic, transcriptional, and proteomic research approaches uncovered major developmental differences between Flt3L-dependent conventional DCs as compared with Mphs and monocyte-derived DCs (MoDCs), the latter mainly generated in vitro from murine bone marrow-derived DCs (BM-DCs) or human CD14+ peripheral blood monocytes. Conversely, in vitro GM-CSF-dependent monocyte-derived Mphs largely resemble MoDCs whereas tissue-resident Mphs show a common embryonic origin from yolk sac and fetal liver with Langerhans cells (LCs). The novel ontogenetic findings opened discussions on the terminology of DCs versus Mphs. Here, we bring forward arguments to facilitate definitions of BM-DCs, MoDCs, and LCs. We propose a group model of terminology for all DC subsets that attempts to encompass both ontogeny and function.
EVALuna2:34313

GMP-compliant human monocyte-derived dendritic cells for cancer vaccination generated by using the Quantum (R) hollow fiber bioreactor system - Uslu, Ugur; Uslu, U.; Erdmann, M.; Wiesinger, M.; Schuler, Gerold; Schuler-Thurner, Beatrice (ANNALS OF ONCOLOGY, 2019)
CRIS-Team WoS Importer:2020-01-28

Good Manufacturing Practice-Compliant Production and Lot-Release ofEx VivoExpanded Regulatory T Cells As Basis for Treatment of Patients with Autoimmune and Inflammatory Disorders - Wiesinger, Manuel; Stoica, Diane; Roessner, Susanne; Lorenz, Carmen; Fischer, Anika; Atreya, Raja; Neufert, Clemens; Atreya, Imke; Scheffold, Alexander; Schuler-Thurner, Beatrice; Neurath, Markus; Schuler, Gerold; et al. (Frontiers in Immunology, 2017)
In recent years, the exploration of regulatory T cell (Treg)-based cellular therapy has become an attractive strategy to ameliorate inflammation and autoimmunity in various clinical settings. The main obstacle to the clinical application of Treg in human is their low number circulating in peripheral blood. Therefore,ex vivoexpansion is inevitable. Moreover, isolation of Treg bears the risk of concurrent isolation of unwanted effector cells, which may trigger or deteriorate inflammation upon adoptive Treg transfer. Here, we present a protocol for the GMP-compliant production, lot-release and validation ofex vivoexpanded Tregs for treatment of patients with autoimmune and inflammatory disorders. In the presented production protocol, large numbers of Treg, previously enriched from a leukapheresis product by using the CliniMACS®system, areex vivoexpanded in the presence of anti-CD3/anti-CD28 expander beads, exogenous IL-2 and rapamycin during 21 days. The expanded Treg drug product passed predefined lot-release criteria. These criteria include (i) sterility testing, (ii) assessment of Treg phenotype, (iii) assessment of non-Treg cellular impurities, (iv) confirmation of successful anti-CD3/anti-CD28 expander bead removal after expansion, and (v) confirmation of the biological function of the Treg product. Furthermore, the Treg drug product was shown to retain its stability and suppressive function for at least 1 year after freezing and thawing. Also, dilution of the Treg drug product in 0.9% physiological saline did not affect Treg phenotype and Treg function for up to 90 min. These data indicate that these cells are ready to use in a clinical setting in which a cell infusion time of up to 90 min can be expected. The presented production process has recently undergone on site GMP-conform evaluation and received GMP certification from the Bavarian authorities in Germany. This protocol can now be used for Treg-based therapy of various inflammatory and autoimmune disorders.
EVALuna2:33800

Grade 4 Neutropenia Secondary to Immune Checkpoint Inhibition — A Descriptive Observational Retrospective Multicenter Analysis - Zaremba, Anne; Kramer, Rafaela; De Temple, Viola; Bertram, Stefanie; Salzmann, Martin; Gesierich, Anja; Reinhardt, Lydia; Baroudjian, Barouyr; Sachse, Michael M.; Mechtersheimer, Gunhild; Johnson, Douglas B.; Weppler, Alison M.; et al. (Frontiers in Oncology, 2021)
Introduction: Immune checkpoint inhibitors (ICI) are increasingly being used to treat numerous cancer types. Together with improved recognition of toxicities, this has led to more frequent identification of rare immune-related adverse events (irAE), for which specific treatment strategies are needed. Neutropenia is a rare hematological irAE that has a potential for a high mortality rate because of its associated risk of sepsis. Prompt recognition and timely treatment of this life-threatening irAE are therefore critical to the outcome of patients with immune-related neutropenia. Methods: This multicenter international retrospective study was conducted at 17 melanoma centers to evaluate the clinical characteristics, diagnostics, treatment, and outcomes of melanoma patients with grade 4 neutropenia (<500 neutrophils/µl blood) treated with ICI between 2014 and 2020. Some of these patients received metamizole in addition to ICI (ICI+/met+). Bone marrow biopsies (BMB) of these patients were compared to BMB from non-ICI treated patients with metamizole-induced grade 4 neutropenia (ICI-/met+). Results: In total, 10 patients (median age at neutropenia onset: 66 years; seven men) with neutropenia were identified, equating to an incidence of 0.14%. Median onset of neutropenia was 6.4 weeks after starting ICI (range 1.4–49.1 weeks). Six patients showed inflammatory symptoms, including fever (n=3), erysipelas (n=1), pharyngeal abscess (n=1), and mucositis (n=1). Neutropenia was diagnosed in all patients by a differential blood count and additionally performed procedures including BMB (n=5). Nine of 10 patients received granulocyte colony-stimulating factors (G-CSF) to treat their grade 4 neutropenia. Four patients received systemic steroids (including two in combination with G-CSF, and one in combination with G-CSF and additional ciclosporin A). Four patients were treated with one or more antibiotic treatment lines, two with antimycotic treatment, and one with additional antiviral therapy. Five patients received metamizole concomitantly with ICI. One fatal outcome was reported. BMB indicated a numerically lower CD4+ to CD8+ T cells ratio in patients with irNeutropenia than in those with metamizole-induced neutropenia. Conclusion: Grade 4 neutropenia is a rare but potentially life-threatening side effect of ICI treatment. Most cases were sufficiently managed using G-CSF; however, adequate empiric antibiotic, antiviral, and antimycotic treatments should be administered if neutropenic infections are suspected. Immunosuppression using corticosteroids may be considered after other causes of neutropenia have been excluded.
CRIS-Team Scopus Importer:2021-12-10
Keywords: adverse events; hematotoxicity; immune checkpoint inhibition; malignant melanoma; neutropenia

Graph Neural Networks in Multi-Stained Pathological Imaging: Extended Comparative Analysis of Radiomic Features - Rivera Monroy, Luis; Rist, Leonhard; Ostalecki, Christian; Bauer, Andreas; Vera González, Julio; Breininger, Katharina; Maier, Andreas (2025)
Purpose: This study investigates Radiomics features for Graph Neural Networks (GNNs) in MELC pathology sample classification focusing on often misdiagnosed skin diseases. Methods: GNNs processing multiple pathological slides together as cell-level graphs are compared to XGBoost and Random Forest. The analysis assesses the use of MELC vs. Radiomics features, their dimensionality reduction with UMAP or tSNE and the graph connectivity based on spatial and feature closeness. Results: Integrating Radiomics features in a spatially connected graph markedly outperforms standard models when classifying pathologically similar diseases. Additionally, the UMAP dimensionality reduction techniques improves GNN classification performance. Conclusion: Radiomics, processed with GNNs, shows promise for multi-disease classification, enhancing diagnosis accuracy. Considering the potential, future research should extend these methods to a broader range of disease
https://cris.fau.de/converis/publicweb/Publication/321533326
Keywords: Pathology; Dermatology; Artificial Intelligence and Machine Learning; Radiomics; Multi-array Imaging; Graph Neural Network; MELC; Histopathological Analysis

Guidelines for DC preparation and flow cytometric analysis of human lymphohematopoietic tissues - Heger, Lukas; Dudziak, Diana; Amon, Lukas; Hatscher, Lukas; Kaszubowski, Tomasz; Lehmann, Christian (European Journal of Immunology, 2022)
This article is part of the Dendritic Cell Guidelines article series, which provides a collection of state-of-the-art protocols for the preparation, phenotype analysis by flow cytometry, generation, fluorescence microscopy, and functional characterization of mouse and human dendritic cells (DC) from lymphoid organs and various non-lymphoid tissues. Within this article, detailed protocols are presented that allow for the generation of single cell suspensions from human lymphohematopoietic tissues including blood, spleen, thymus, and tonsils with a focus on the subsequent analysis of DC via flow cytometry, as well as flow cytometric cell sorting of primary human DC. Further, prepared single cell suspensions as well as cell sorter-purified DC can be subjected to other applications including cellular enrichment procedures, RNA sequencing, functional assays, and many more. While all protocols were written by experienced scientists who routinely use them in their work, this article was also peer-reviewed by leading experts and approved by all co-authors, making it an essential resource for basic and clinical DC immunologists.
CRIS-Team WoS Importer:2023-01-13

Guidelines for DC preparation and flow cytometry analysis of mouse lymphohematopoietic tissues - Amon, Lukas; Dudziak, Diana; Backer, Ronald A. A.; Clausen, Bjoern E.; Gmeiner, Christina; Heger, Lukas; Jacobi, Lukas; Lehmann, Christian; Probst, Hans-Christian; Seichter, Anna; Tchitashvili, Giorgi; Tochoedo, Nounagnon Romaric; et al. (European Journal of Immunology, 2022)
This article is part of the Dendritic Cell Guidelines article series, which provides a collection of state-of-the-art protocols for the preparation, phenotype analysis by flow cytometry, generation, fluorescence microscopy, and functional characterization of mouse and human DC from lymphoid organs, and various non-lymphoid tissues. Within this chapter, detailed protocols are presented that allow for the generation of single-cell suspensions from mouse lymphohematopoietic tissues including spleen, peripheral lymph nodes, and thymus, with a focus on the subsequent analysis of DC by flow cytometry. However, prepared single-cell suspensions can be subjected to other applications including sorting and cellular enrichment procedures, RNA sequencing, Western blotting, and many more. While all protocols were written by experienced scientists who routinely use them in their work, this article was also peer-reviewed by leading experts and approved by all co-authors, making it an essential resource for basic and clinical DC immunologists.
Created from Fastlane, Scopus look-up
Keywords: dendritic cells; high-parameter flow cytometry; mouse lymphoid tissues; myeloid cells; single-cell suspension preparation

Guidelines for DC preparation and flow cytometry analysis of mouse nonlymphoid tissues - Probst, Hans Christian; Stoitzner, Patrizia; Amon, Lukas; Backer, Ronald A.; Brand, Anna; Chen, Jianzhou; Clausen, Björn E.; Dieckmann, Sophie; Dudziak, Diana; Heger, Lukas; Hodapp, Katrin; Hornsteiner, Florian; et al. (European Journal of Immunology, 2022)
This article is part of the Dendritic Cell Guidelines article series, which provides a collection of state-of-the-art protocols for the preparation, phenotype analysis by flow cytometry, generation, fluorescence microscopy and functional characterization of mouse and human dendritic cells (DC) from lymphoid organs and various nonlymphoid tissues. DC are sentinels of the immune system present in almost every mammalian organ. Since they represent a rare cell population, DC need to be extracted from organs with protocols that are specifically developed for each tissue. This article provides detailed protocols for the preparation of single-cell suspensions from various mouse nonlymphoid tissues, including skin, intestine, lung, kidney, mammary glands, oral mucosa and transplantable tumors. Furthermore, our guidelines include comprehensive protocols for multiplex flow cytometry analysis of DC subsets and feature top tricks for their proper discrimination from other myeloid cells. With this collection, we provide guidelines for in-depth analysis of DC subsets that will advance our understanding of their respective roles in healthy and diseased tissues. While all protocols were written by experienced scientists who routinely use them in their work, this article was also peer-reviewed by leading experts and approved by all coauthors, making it an essential resource for basic and clinical DC immunologists.
Created from Fastlane, Scopus look-up
Keywords: Dendritic cells; Discrimination of dendritic cell subsets; Mouse nonlymphoid tissue; Multiplex flow cytometry analysis; Tissue digestion protocols

Guidelines for mouse and human DC functional assays - Clausen, Bjoern E.; Amon, Lukas; Backer, Ronald A.; Berod, Luciana; Bopp, Tobias; Brand, Anna; Burgdorf, Sven; Chen, Luxia; Da, Meihong; Distler, Ute; Dress, Regine J.; Dudziak, Diana; et al. (European Journal of Immunology, 2022)
This article is part of the Dendritic Cell Guidelines article series, which provides a collection of state-of-the-art protocols for the preparation, phenotype analysis by flow cytometry, generation, fluorescence microscopy, and functional characterization of mouse and human dendritic cells (DC) from lymphoid organs and various non-lymphoid tissues. Recent studies have provided evidence for an increasing number of phenotypically distinct conventional DC (cDC) subsets that on one hand exhibit a certain functional plasticity, but on the other hand are characterized by their tissue- and context-dependent functional specialization. Here, we describe a selection of assays for the functional characterization of mouse and human cDC. The first two protocols illustrate analysis of cDC endocytosis and metabolism, followed by guidelines for transcriptomic and proteomic characterization of cDC populations. Then, a larger group of assays describes the characterization of cDC migration in vitro, ex vivo, and in vivo. The final guidelines measure cDC inflammasome and antigen (cross)-presentation activity. While all protocols were written by experienced scientists who routinely use them in their work, this article was also peer-reviewed by leading experts and approved by all co-authors, making it an essential resource for basic and clinical DC immunologists.<br

Guidelines for mouse and human DC generation - Lutz, Manfred B.; Ali, Shafaqat; Audiger, Cindy; Autenrieth, Stella E.; Berod, Luciana; Bigley, Venetia; Cyran, Laura; Dalod, Marc; Dörrie, Jan; Dudziak, Diana; Florez-Grau, Georgina; Giusiano, Lucila; et al. (European Journal of Immunology, 2022)
This article is part of the Dendritic Cell Guidelines article series, which provides a collection of state-of-the-art protocols for the preparation, phenotype analysis by flow cytometry, generation, fluorescence microscopy, and functional characterization of mouse and human dendritic cells (DC) from lymphoid organs and various non-lymphoid tissues. This article provides protocols with top ticks and pitfalls for preparation and successful generation of mouse and human DC from different cellular sources, such as murine BM and HoxB8 cells, as well as human CD34(+) cells from cord blood, BM, and peripheral blood or peripheral blood monocytes. We describe murine cDC1, cDC2, and pDC generation with Flt3L and the generation of BM-derived DC with GM-CSF. Protocols for human DC generation focus on CD34(+) cell culture on OP9 cell layers for cDC1, cDC2, cDC3, and pDC subset generation and DC generation from peripheral blood monocytes (MoDC). Additional protocols include enrichment of murine DC subsets, CRISPR/Cas9 editing, and clinical grade human DC generation. While all protocols were written by experienced scientists who routinely use them in their work, this article was also peer-reviewed by leading experts and approved by all co-authors, making it an essential resource for basic and clinical DC immunologists.
CRIS-Team WoS Importer:2022-11-11

Guidelines for uveal melanoma: a critical appraisal of systematically identified guidelines using the AGREE II and AGREE-REX instrument - Steeb, Theresa; Hayani, Kinan M.; Förster, Paul; Liegl, Raffael; Toussaint, Frédéric; Schlaak, Max; Berking, Carola; Heppt, Markus (Journal of Cancer Research and Clinical Oncology, 2020)
Purpose: Clinical practice guidelines provide recommendations for the management of diseases. In orphan conditions such as uveal melanoma (UM), guideline developers are challenged to provide practical and useful guidance even in the absence of high-quality evidence. Here, we assessed the methodological quality and identified deficiencies of international guidelines on UM as a base for future guideline development. Methods: A systematic search was carried out in guideline databases, Medline and Embase until 27th May 2019 for guidelines on UM published between 2004 and 2019. Five independent reviewers assessed the methodological quality of the identified guidelines using the instruments “Appraisal of Guidelines for Research and Evaluation II” (AGREE II) and AGREE-REX (Recommendation EXcellence). Descriptive analysis was performed and subgroup differences were explored with the Kruskal–Wallis (H) test. The relationship between the individual domains and items of the instruments were examined using Spearman’s correlation. Results: Five guidelines published from 2014 to 2018 by consortia of the United States of America, Canada and the United Kingdom (UK) were included. The highest scores were obtained by the UK guideline fulfilling 48–86% of criteria in AGREE II and 30–60% for AGREE-REX. All guidelines showed deficiencies in the domains “editorial independence”, “applicability”, and “recommendation”. Subgroup differences were identified only for the domain “editorial independence”. Conclusion: The UK guideline achieved the highest scores with both instruments and may serve as a basis for future guideline development in UM. The domains “editorial independence”, “recommendation”, and “applicability” were identified as methodological weaknesses and require particular attention and improvement in future guidelines.
CRIS-Team Scopus Importer:2020-02-25
Keywords: AGREE; Guideline; Ocular melanoma; Orphan disease; Practice guideline; Uveal melanoma

Guselkumab demonstrates long-term efficacy and maintenance of treatment response postwithdrawal in systemic treatment-naïve patients and nonresponders to fumaric acid esters: results from parts II and III of a randomized active-comparator-controlled phase IIIb trial (POLARIS). - Thaçi, Diamant; Pinter, Andreas; Sebastian, Michael; Termeer, Christian; Sticherling, Michael; Gerdes, Sascha; Schäkel, Knut; Wegner, Sven; Krampe, Stefanie; Bartz, Holger; Rausch, Christian; Taut, Friedemann; et al. (British Journal of Dermatology, 2024)
BACKGROUND: The anti-interleukin-23 antibody guselkumab (GUS) demonstrated favourable week 24 efficacy and safety over fumaric acid esters (FAE) in systemic treatment-naïve patients with moderate-to-severe plaque psoriasis (study part I). OBJECTIVES: To compare, in study part II, the sustainability of treatment responses (weeks 24-32) in GUS- and FAE-treated patients and treatment responses (weeks 32-56) in patients treated with GUS and FAE and in FAE nonresponders switching to GUS; and, in part III, to investigate the maintenance of response through week 100 in patients withdrawn from GUS at week 56. METHODS: At week 0, systemic treatment-naïve patients were randomized 1 : 1 to GUS or FAE as per label. At week 32, patients with a Psoriasis Area and Severity Index (PASI) 75 (≥ 75% improvement in PASI score) response (r) continued assigned treatment (GUSr-GUS; FAEr-FAE), whereas nonresponders (nr) received GUS (FAEnr-GUS; GUSnr-GUS). GUS-treated patients with a week 56 PASI 90 response (≥ 90% improvement in PASI score) were withdrawn (w) and followed until loss of response or week 100. RESULTS: At week 32, 98% (n = 54/55) of GUS- and 41% (n = 14/34) of FAE-treated patients were PASI 75 responders. At week 56, 91%, 50% and 80% of GUSr-GUS, FAEr-FAE and FAEnr-GUS patients, respectively, achieved a PASI 90 response; 72%, 29% and 45%, respectively, achieved a Dermatology Life Quality Index score of 0/1. At week 100, 44 weeks postwithdrawal, 47% (n = 17/36) and 25% (n = 3/12) of GUS-GUSw and FAE-GUSw patients, respectively, maintained a PASI score ≤ 5. Overall, the adverse event and discontinuation rates were lower for GUS than FAE. CONCLUSIONS: In these exploratory analyses, GUS, as a first-line systemic treatment or second-line systemic treatment in FAE nonresponders, was associated with long-term clinical efficacy up to week 100, including a withdrawal period.
EVALuna2:547035

Guselkumab is superior to fumaric acid esters in patients with moderate-to-severe plaque psoriasis who are naive to systemic treatment: results from a randomized, active-comparator-controlled phase IIIb trial (POLARIS) - Thaci, D.; Pinter, A.; Sebastian, M.; Termeer, C.; Sticherling, Michael; Gerdes, S.; Wegner, S.; Krampe, S.; Bartz, H.; Rausch, C.; Mensch, A.; Eyerich, K. (British Journal of Dermatology, 2020)
Background Guselkumab, a fully human interleukin-23 antibody, is approved for systemic treatment of patients with moderate-to-severe plaque psoriasis. Objectives To compare the efficacy and safety of guselkumab with those of fumaric acid esters (FAE) in patients with moderate-to-severe plaque psoriasis who are naive to systemic treatment. Methods Eligible patients were randomized to this multicentre, randomized, open-label, assessor-blinded, active-comparator-controlled phase IIIb study to receive guselkumab 100 mg by subcutaneous injection or oral FAE according to local label guidelines. Results Through week 24, 56 of 60 patients completed guselkumab treatment and 36 of 59 completed FAE treatment. The primary endpoint (proportion of patients with >= 90% improvement from their baseline Psoriasis Area and Severity Index; PASI 90 response) was achieved by significantly more patients receiving guselkumab than FAE at week 24 (82% vs. 14%, P < 0 center dot 001). Analysis of the major secondary endpoints confirmed a statistically significant difference between the treatments with regards to PASI 75 response (90% vs. 27%, P < 0 center dot 001) and Dermatology Life Quality Index score of 0 or 1 (no effect at all on the patient's quality of life; 62% vs. 17%, P < 0 center dot 001). More patients in the guselkumab group achieved completely clear skin (PASI 100 response) than in the FAE group (32% vs. 3%, P < 0 center dot 001). The incidence of adverse events was lower with guselkumab than with FAE (73% vs. 98%). Overall, 28% of patients on FAE discontinued due to an adverse event, compared with none receiving guselkumab. No new safety findings were observed for guselkumab. Conclusions Guselkumab demonstrated superiority over FAE in systemic-treatment-naive patients with moderate-to-severe plaque psoriasis through 24 weeks. What's already known about this topic?
CRIS-Team WoS Importer:2020-01-28

HAND FUNCTION IS IMPAIRED IN PATIENTS WITH RHEUMATOID ARTHRITIS, PSORIATIC ARTHRITIS, AND PSORIASIS COMPARED TO HEALTHY CONTROLS - Liphardt, Anna-Maria; Liehr, Sonja; Manger, Eva; Bieniek, Lisa; Kleyer, Arnd; Simon, David; Tascilar, Koray; Sticherling, Michael; Rech, Jürgen; Schett, Georg; Hueber, Axel (ANNALS OF THE RHEUMATIC DISEASES, 2019)
CRIS-Team WoS Importer:2019-07-12

Harmonisation of Outcome Parameters and Evaluation (HOPE) for actinic keratosis: protocol for the development of a core outcome set - Heppt, Markus V.; Steeb, Theresa; Schmitz, Lutz; Garbe, Claus; French, Lars E.; Leiter, Ulrike; Berking, Carola (Trials, 2019)
BACKGROUND: Actinic keratoses (AK) are common skin lesions that can progress to invasive squamous cell carcinoma of the skin. A variety of lesion- or field-targeted treatment options exist and their efficacy has been demonstrated in numerous randomised controlled trials (RCTs). However, the reported endpoints are highly heterogeneous, making it difficult to assess and compare distinct treatment options and to reach an evidence-based choice of therapy. METHODS: A systematic literature search will be conducted to analyse which endpoints are reported in RCTs. The focus will be on effectiveness, tolerability, cosmesis, and patient satisfaction. The reported endpoints of these studies, as well as their frequency and data collection times, will be documented in a standardised way to generate a comprehensive list of reported endpoints. In order to complete the identified outcomes in the literature search, focus groups on affected patients and structured interviews with board-certified dermatologists will be conducted to identify both patient- and practice-relevant endpoints. After the identification phase, the evaluation of the endpoints follows. In a two-stage Delphi procedure, experts including patient representatives will evaluate the endpoints in a standardised and transparent manner. A final face-to-face consensus meeting will be conducted after the last Delphi round in which a final list of core outcomes will be consented. DISCUSSION: The development of a standardised endpoint set for the treatment of AK will contribute to improving the comparability of therapeutic options. Our catalogue will enhance the synthesis of evidence for the future by reducing heterogeneity in outcomes between RCTs and hence contribute to improving the quality of research, evidence-based and patient-centred treatment. TRIAL REGISTRATION: Core Outcome Measures for Effectiveness ( COMET ) database. Registered in December 2018.
EVALuna2:209212

Harnessing the complete repertoire of conventional dendritic cell functions for cancer immunotherapy - Amon, Lukas; Hatscher, Lukas; Heger, Lukas; Dudziak, Diana; Lehmann, Christian (Pharmaceutics, 2020)
The onset of checkpoint inhibition revolutionized the treatment of cancer. However, studies from the last decade suggested that the sole enhancement of T cell functionality might not suffice to fight malignancies in all individuals. Dendritic cells (DCs) are not only part of the innate immune system, but also generals of adaptive immunity and they orchestrate the de novo induction of tolerogenic and immunogenic T cell responses. Thus, combinatorial approaches addressing DCs and T cells in parallel represent an attractive strategy to achieve higher response rates across patients. However, this requires profound knowledge about the dynamic interplay of DCs, T cells, other immune and tumor cells. Here, we summarize the DC subsets present in mice and men and highlight conserved and divergent characteristics between different subsets and species. Thereby, we supply a resource of the molecular players involved in key functional features of DCs ranging from their sentinel function, the translation of the sensed environment at the DC:T cell interface to the resulting specialized T cell effector modules, as well as the influence of the tumor microenvironment on the DC function. As of today, mostly monocyte derived dendritic cells (moDCs) are used in autologous cell therapies after tumor antigen loading. While showing encouraging results in a fraction of patients, the overall clinical response rate is still not optimal. By disentangling the general aspects of DC biology, we provide rationales for the design of next generation DC vaccines enabling to exploit and manipulate the described pathways for the purpose of cancer immunotherapy in vivo. Finally, we discuss how DC-based vaccines might synergize with checkpoint inhibition in the treatment of malignant diseases.
CRIS-Team Scopus Importer:2020-07-24
Keywords: Antigen targeting; Cancer therapy; Checkpoint inhibition; Dendritic cells; Pattern recognition receptors; T cells; Tumor microenvironment; Vaccination

Harnessing the Participation of Dendritic Cells in Immunity and Tolerance - Boscardin, Silvia Beatriz; Dudziak, Diana; Muenz, Christian; Rosa, Daniela Santoro (Frontiers in Immunology, 2020)
CRIS-Team Scopus Importer:2020-11-13
Keywords: antigen presentation; DC subtypes; dendritic cell; dendritic cell activation; dendritic cell vaccine therapy

HDAC2 Is Involved in the Regulation of BRN3A in Melanocytes and Melanoma - Heppt, Markus; Wessely, Anja; Hornig, Eva; Kammerbauer, Claudia; Graf, Saskia A.; Besch, Robert; French, Lars E.; Matthies, Alexander Oliver; Kuphal, Silke; Kappelmann-Fenzl, Melanie; Boßerhoff, Anja Katrin; Berking, Carola (International Journal of Molecular Sciences, 2022)
The neural crest transcription factor BRN3A is essential for the proliferation and survival of melanoma cells. It is frequently expressed in melanoma but not in normal melanocytes or benign nevi. The mechanisms underlying the aberrant expression of BRN3A are unknown. Here, we investigated the epigenetic regulation of BRN3A in melanocytes and melanoma cell lines treated with DNA methyltransferase (DNMT), histone acetyltransferase (HAT), and histone deacetylase (HDAC) inhibitors. DNMT and HAT inhibition did not significantly alter BRN3A expression levels, whereas panHDAC inhibition by trichostatin A led to increased expression. Treatment with the isoform-specific HDAC inhibitor mocetinostat, but not with PCI-34051, also increased BRN3A expression levels, suggesting that class I HDACs HDAC1, HDAC2, and HDAC3, and class IV HDAC11, were involved in the regulation of BRN3A expression. Transient silencing of HDACs 1, 2, 3, and 11 by siRNAs revealed that, specifically, HDAC2 inhibition was able to increase BRN3A expression. ChIP-Seq analysis uncovered that HDAC2 inhibition specifically increased H3K27ac levels at a distal enhancer region of the BRN3A gene. Altogether, our data suggest that HDAC2 is a key epigenetic regulator of BRN3A in melanocytes and melanoma cells. These results highlight the importance of epigenetic mechanisms in regulating melanoma oncogenes.
CRIS-Team Scopus Importer:2022-02-04
Keywords: BRN3A; ChIP-Seq; DNA methylation; Epigenetic regulation; HAT; HDAC; Melanoma

HDAC2 is involved in the regulation of Brn3a in melanocytes and melanoma - Heppt, Markus; Wessely, Anja; Hornig, E.; Kammerbauer, C.; Graf, S.; Besch, R.; French, L. E.; Kuphal, Silke; Kappelmann-Fenzl, Melanie; Boßerhoff, Anja Katrin; Berking, Carola (EXPERIMENTAL DERMATOLOGY, 2023)
CRIS-Team WoS Importer:2023-06-02

H. E. Becher - his Importance as a Sculptor and Medalist for Moulage Art in Germany - Sticherling, Michael; Emmerling, Johanna (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2021)
CRIS-Team WoS Importer:2021-04-16

Hematological immune related adverse events after treatment with immune checkpoint inhibitors - Kramer, Rafaela; Zaremba, Anne; Moreira, Alvaro; Ugurel, Selma; Johnson, Douglas B.; Hassel, Jessica C.; Salzmann, Martin; Gesierich, Anja; Weppler, Alison; Spain, Lavinia; Loquai, Carmen; Dudda, Milena; et al. (European Journal of Cancer, 2021)
Introduction: With the increasing use of checkpoint inhibitors, rare immune-related adverse events (irAE) are being identified. Haematological irAE (hem-irAE) are difficult to treat and have shown high mortality rates. In order to improve side-effect management for these potentially life-threatening events, we analysed frequency, severity and outcomes. Patients and methods: Patients who developed hem-irAE while being treated with immune checkpoint inhibitors (ICI) therapy were retrospectively identified from 18 international cancer centres. Results: In total, more than 7626 patients treated with ICI were screened, and 50 patients with hem-irAE identified. The calculated incidence amounts to 0.6% and median onset was 6 weeks after the ICI initiation (range 1–128 weeks). Thrombocytopenia and leucopaenia were the most frequent hem-irAE with 34% (17/50) and 34% (17/50), respectively, followed by anaemia 28% (14/50), hemophagocytic lymphohistiocytosis (4% (2/50)), aplastic anaemia (2% (1/50)), acquired haemophilia A (2% (1/50)) and coagulation deficiency (2% (1/50)). Simultaneous thrombocytopenia and neutropenia occurred in two patients, concurrent anaemia and thrombocytopenia in one patient. Other than cessation of ICI (in 60%) and corticosteroids (in 78%), treatment included second-line immunosuppression in 24% of cases. Events resolved in 78% (39/50), while 18% (9/50) had persistent changes, and 2% (1/50) had fatal outcomes (agranulocytosis). Conclusion: Hem-irAE can affect all haematopoietic blood cell lineages and may persist or even be fatal. Management may require immunosuppression beyond corticosteroids. Although these irAE are rare, treating physicians should be aware, monitor blood counts regularly and promptly act upon detection.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Anaemia; Anti-CTLA-4-Antibody; Anti-PD1-Antibody; Autoimmunity; Haematotoxicity; Hemophagocytic lymphohistiocytosis; Leucopaenia; Neutropenia; Side-effects; Thrombocytopenia

Hepatic intra-arterial versus intravenous fotemustine in patients with liver metastases from uveal melanoma (EORTC 18021): a multicentric randomized trial - Leyvraz, S.; Piperno-Neumann, S.; Suciu, S.; Baurain, J. F.; Zdzienicki, M.; Testori, A.; Marshall, E.; Scheulen, M.; Jouary, T.; Negrier, S.; Vermorken, J. B.; Kämpgen, Eckhart; et al. (Annals of Oncology, 2014)
In uveal melanoma (UM) with metastatic disease limited to the liver, the effect of an intrahepatic treatment on survival is unknown. We investigated prospectively the efficacy and toxicity of hepatic intra-arterial (HIA) versus systemic (IV) fotemustine in patients with liver metastases from UM.Patients were randomly assigned to receive either IV or HIA fotemustine at 100 mg/m(2) on days 1, 8, 15 (and 22 in HIA arm only) as induction, and after a 5-week rest period every 3 weeks as maintenance. Primary end point was overall survival (OS). Response rate (RR), progression-free survival (PFS) and safety were secondary end points.Accrual was stopped after randomization of 171 patients based on the results of a futility OS analysis. A total of 155 patients died and 16 were still alive [median follow-up 1.6 years (range 0.25-6 years)]. HIA did not improve OS (median 14.6 months) when compared with the IV arm (median 13.8 months), hazard ratio (HR) 1.09; 95% confidence interval (CI) 0.79-1.50, log-rank P = 0.59. However, there was a significant benefit on PFS for HIA compared with IV with a median of 4.5 versus 3.5 months, respectively (HR 0.62; 95% CI 0.45-0.84, log-rank P = 0.002). The 1-year PFS rate was 24% in the HIA arm versus 8% in the IV arm. An improved RR was seen in the HIA (10.5%) compared with IV treatment (2.4%). In the IV arm, the most frequent grade >=3 toxicity was thrombocytopenia (42.1%) and neutropenia (62.6%), compared with 21.2% and 28.7% in the HIA arm. The main grade >=3 toxicity related to HIA was catheter complications (12%) and liver toxicity (4.5%) apart from two toxic deaths.HIA treatment with fotemustine did not translate into an improved OS compared with IV treatment, despite better RR and PFS. Intrahepatic treatment should still be considered as experimental.2004-002245-12 and NCT00110123.
EVALuna2:19469

Herpes simplex virus type 1 ICP0 induces CD83 degradation in mature dendritic cells independent of its E3 ubiquitin ligase function - Heilingloh, Christiane; Muehl-Zuerbes, Petra; Steinkasserer, Alexander; Kummer, Mirko (Journal of General Virology, 2014)
Mature dendritic cells (mDCs) are the most potent antigen-presenting cells known today, as they are the only antigen-presenting cells able to induce naïve T-cells. Therefore, they play a crucial role during the induction of effective antiviral immune responses. Interestingly, the surface molecule CD83 expressed on mDCs is targeted by several viruses. As CD83 has been shown to exert co-stimulatory functions on mDCs, its downmodulation represents a viral immune escape mechanism. Mechanistically, it has been shown that herpes simplex virus type 1 infection leads to proteasomal degradation of CD83, resulting in a strongly diminished T-cell stimulatory capacity of the infected mDC. Previous data suggest that the viral immediate-early protein ICP0 (infected-cell protein 0) plays an important role in this process. In the present study, we showed that ICP0 is sufficient to induce CD83 degradation in the absence of any other viral factor. However, the mechanism of ICP0-mediated CD83 degradation is not yet understood. Here, we provide evidence that ubiquitination of lysine residues is, despite the published E3 ubiquitin ligase activity of ICP0, not necessary for CD83 degradation. This finding was underlined by the observation that expression of an ICP0 mutant lacking the E3 ubiquitin ligase domain in mDCs still induced CD83 degradation. Finally, inhibition of E1 activating enzyme using the specific inhibitor 4[4-(5-nitro-furan-2-ylmethylene)-3.5-dioxo-pyrazolidin-1-yl]-benzoic acid ethyl ester did not prevent CD83 degradation. Taken together, our data provide strong evidence that ICP0 alone induces CD83 degradation independent of its E3 ubiquitin ligase function and of the ubiquitin machinery.
EVALuna2:26033

Herpes simplex virus type-2 paralyzes the function of monocyte-derived dendritic cells - Grosche, Linda; Mühl-Zürbes, Petra; Ciblis, Barbara; Krawczyk, Adalbert; Kuhnt, Christine; Kamm, Lisa; Steinkasserer, Alexander; Heilingloh, Christiane (Viruses, 2020)
Herpes simplex viruses not only infect a variety of different cell types, including dendritic cells (DCs), but also modulate important cellular functions in benefit of the virus. Given the relevance of directed immune cell migration during the initiation of potent antiviral immune responses, interference with DC migration constitutes a sophisticated strategy to hamper antiviral immunity. Notably, recent reports revealed that HSV-1 significantly inhibits DC migration in vitro. Thus, we aimed to investigate whether HSV-2 also modulates distinct hallmarks of DC biology. Here, we demonstrate that HSV-2 negatively interferes with chemokine-dependent in vitro migration capacity of mature DCs (mDCs). Interestingly, rather than mediating the reduction of the cognate chemokine receptor expression early during infection, HSV-2 rapidly induces β2 integrin (LFA-1)-mediated mDC adhesion and thereby blocks mDC migration. Mechanistically, HSV-2 triggers the proteasomal degradation of the negative regulator of β2 integrin activity, CYTIP, which causes the constitutive activation of LFA-1 and thus mDC adhesion. In conclusion, our data extend and strengthen recent findings reporting the reduction of mDC migration in the context of a herpesviral infection. We thus hypothesize that hampering antigen delivery to secondary lymphoid organs by inhibition of mDC migration is an evolutionary conserved strategy among distinct members of Herpesviridae.
CRIS-Team Scopus Importer:2020-02-04
Keywords: Adhesion; CYTIP; Cytohesin-1; Dendritic cells; HSV-1; HSV-2; LFA-1; Migration

Heterogeneity and function of conventional dendritic cells from early to adult life - Schraml, B.; Papaioannou, N.; Shakiba, R.; Ravi, K.; Kuentzel, V.; Salei, N.; Lehman, C. H.; Fiancette, R.; Messerer, D.; Ohnmacht, C.; Haller, D.; Staub, T.; et al. (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Heterogeneous fate choice of genetically modulated adult neural stem cells in gray and white matter of the central nervous system - Beyer, Felix; Jadasz, Janusz; Samper Agrelo, Iria; Schira-Heinen, Jessica; Groh, Janos; Manousi, Anastasia; Buetermann, Christine; Estrada, Veronica; Reiche, Laura; Cantone, Martina; Vera, Julio; Vigano, Francesca; et al. (Glia, 2019)
Apart from dedicated oligodendroglial progenitor cells, adult neural stem cells (aNSCs) can also give rise to new oligodendrocytes in the adult central nervous system (CNS). This process mainly confers myelinating glial cell replacement in pathological situations and can hence contribute to glial heterogeneity. Our previous studies demonstrated that the p57kip2 gene encodes an intrinsic regulator of glial fate acquisition and we here investigated to what degree its modulation can affect stem cell-dependent oligodendrogenesis in different CNS environments. We therefore transplanted p57kip2 knockdown aNSCs into white and gray matter (WM and GM) regions of the mouse brain, into uninjured spinal cords as well as in the vicinity of spinal cord injuries and evaluated integration and differentiation in vivo. Our experiments revealed that under healthy conditions intrinsic suppression of p57kip2 as well as WM localization promote differentiation toward myelinating oligodendrocytes at the expense of astrocyte generation. Moreover, p57kip2 knockdown conferred a strong benefit on cell survival augmenting net oligodendrocyte generation. In the vicinity of hemisectioned spinal cords, the gene knockdown led to a similar induction of oligodendroglial features; however, newly generated oligodendrocytes appeared to suffer more from the hostile environment. This study contributes to our understanding of mechanisms of adult oligodendrogenesis and glial heterogeneity and further reveals critical factors when considering aNSC mediated cell replacement in injury and disease.
CRIS-Team WoS Importer:2019-10-29

Hierarchical Levels of Biological Systems and their Integration as a Principal Cause for Tumour Occurrence - Nikolov, Svetoslav; Dimitrov, Assen; Vera, Julio (Nonlinear Dynamis, Psychology, and Life Sciences, 2019)
The development of new theories, mathematical methods and models for effective control of complex systems is one of the main problems for modern science. Biological systems are complex and hierarchically organized, with the behaviour of higher levels influencing the dynamics of the lower ones and vice versa. Hierarchical organization can be observed from subcellular to supercellular levels. When biological systems are far from their steady states, then nonlinear dependences take place, and a slight external impact can cause unexpected and unpredictable (chaotic, irregular) behaviour in these systems, resulting in fractal hierarchical structures. By examining tumours as strange (chaotic) attractors, we define in this article the hypothesis that the cause of their occurrence, development and spread (metastasis) is due to disorders in the hierarchical structure and integration of cell signalling pathways in tumour cells. An essential point in this article is the thesis (contrary to the view that the only causality in hierarchical systems is physical causality, i.e. there is no "top-down,' "holistic causality,' "intelligent causality,' etc.) that hierarchical systems are built on the principle of communication. Intelligent systems (in particular biological) that do not interact as mechanical objects, but on the basis of different meanings of biochemical signals obtained after their interpretation, participate in this communication.
CRIS-Team Scopus Importer:2019-07-16

High volume of polysorbate-containing (Tween® 80) solutions induces false-positive results in intradermal test - Wagner, N.; Podda, M. (Journal of the European Academy of Dermatology and Venereology, 2018)
BACKGROUND: Intradermal test is used to detect causative allergens in IgE-mediated hypersensitivity. The surfactant polysorbate 80 can be added to intradermal test solutions to more reliably dissolve the allergen and ensure a constant bioavailability of the injected allergen. Polysorbate 80 has, however, some histamine-releasing properties which could blur the difference to the histamine-induced wheal. Routinely serving as a control. OBJECTIVE: Allergen-free polysorbate 80 containing (0.005%) test solutions were therefore systematically tested at different injection volumes to see whether polysorbate can falsify skin reactions and if yes whether conditions can be identified to avoid this. METHODS: In a partly blinded study, 30 patients were tested intracutaneously at the back: each received at three separate sites 0.05 mL of polysorbate-containing solvent, 0.02 mL polysorbate-containing solvent as well as 0.02 mL polysorbate-free solvent. After 15 min, wheal and erythema were documented and planimetrically quantified. RESULTS: Unexpectedly 23 of 30 (77%) patients showed false-positive test reactions to the volume of 0.05 mL of the polysorbate-containing solvent whereas the polysorbate-containing solvent with 0.02 mL and the polysorbate-free solvent with 0.02 mL injection volume had no reinforcing effect on skin test reaction. CONCLUSIONS: Different volumes of polysorbate-containing solutions, all recommended by manufacturers for intradermal tests, may significantly influence test results. The study shows that a polysorbate 80 used at 0.005% in solvents for intradermal test to provide a better bioavailability of allergens produces false-positive reactivity in a surprising and a hitherto unknown 77% if the 0.05 mL volume is injected. It is, therefore, mandatory to strictly adhere to an intradermal test volume of 0.02 mL as only then falsifying effects of the polysorbate additive are avoided, and comparable test results are ensured.
EVALuna2:34761

HIV-Nef and ADAM17-Containing Plasma Extracellular Vesicles Induce and Correlate with Immune Pathogenesis in Chronic HIV Infection - Lee, Jung-Hyun; Schierer, Stephan; Blume, Katja; Dindorf, Jochen; Wittki, Sebastian; Xiang, Wei; Ostalecki, Christian; Koliha, Nina; Wild, Stefan; Schuler, Gerold; Fackler, Oliver T.; Saksela, Kalle; et al. (EBioMedicine, 2016)
Antiretroviral therapy (ART) efficiently suppresses HIV replication but immune activation and low CD4 T cell counts often persist. The underlying mechanism of this ART-resistant pathogenesis is not clear. We observed that levels of plasma extracellular vesicles (pEV) are strongly elevated in HIV infection and do not decline during ART. Surprisingly, these vesicles contained the viral accessory proteins Nef and Vpu, which are assumed to be not expressed under efficient ART, as well as pro-inflammatory effectors, including activated ADAM17. HIV pEV were characterized by the presence of activated ?v?3 and absence of CD81 and Tsg101. Correlating with immune activation, peripheral monocytes ingested large amounts of pEV, giving rise to an increased population of CD1c(+) CD14(+) cells that secreted inflammatory cytokines. Importantly, the pro-inflammatory content, particularly ADAM17 activity, correlated with low T cell counts. Preliminary evidence suggested that HIV pEV derived from peripheral mononuclear cells and from an unknown myeloid cell population. In summary we propose an important role of pro-inflammatory pEV in chronic HIV infection due to ongoing viral Nef activity.
EVALuna2:4716

HIV Nef- and Notch1-dependent Endocytosis of ADAM17 Induces Vesicular TNF Secretion in Chronic HIV Infection - Ostalecki, Christian; Wittki, Sebastian; Lee, Jung-Hyun; Geist, Miriam M.; Tibroni, Nadine; Harrer, Thomas; Schuler, Gerold; Fackler, Oliver T.; Baur, Andreas (EBioMedicine, 2016)
Tumor necrosis factor (TNF) is a key cytokine in HIV replication and pathogenesis. For reasons that are not entirely clear, the cytokine remains upregulated despite anti-retroviral therapy (ART). Here we demonstrate that HIV Nef induces an alternative TNF secretion mechanism that remains active in chronic infection. Ingestion of Nef-containing plasma extracellular vesicles (pEV) from ART patients by primary immune cells, but also Nef expression, induced intracellular proTNF cleavage and secretion of vesicular TNF endosomes. Key event was the Nef-mediated routing of the TNF-converting enzyme ADAM17 into Rab4+ early endosomes and the Rab27+ secretory pathway. Analysis of lymph-node tissue by multi-epitope-ligand-cartography (MELC) confirmed a vesicular TNF secretion phenotype that co-localized with persistent Nef expression, and implicated Notch1 as an essential co-factor. Surprisingly Notch1 had no transcriptional effect but was required for the endosomal trafficking of ADAM17. We conclude that Nef expression and Nef-containing pEV mobilize TNF from endosomal compartments in acute and chronic infection.
EVALuna2:13372

HIV Nef, paxillin, and Pak1/2 regulate activation and secretion of TACE/ADAM10 proteases - Lee, Jung-Hyun; Wittki, Sebastian; Braeu, Tanja; Dreyer, Florian; Kraetzel, Kirsten; Dindorf, Jochen; Johnston, Ian C. D.; Gross, Stefanie; Kremmer, Elisabeth; Zeidler, Reinhard; Schlötzer-Schrehardt, Ursula; Lichtenheld, Mathias; et al. (Molecular Cell, 2013)
The HIV Nef protein recruits the polycomb protein Eed and mimics an integrin receptor signal for reasons that are not entirely clear. Here we demonstrate that Nef and Eed complex with the integrin effector paxillin to recruit and activate TNF? converting enzyme (TACE alias ADAM 17) and its close relative ADAM10. The activated proteases cleaved proTNF? and were shuttled into extracellular vesicles (EVs). Peripheral blood mononuclear cells that ingested these EVs released TNF?. Analyzing the mechanism, we found that Pak2, an established host cell effector of Nef, phosphorylated paxillin on Ser272/274 to induce TACE-paxillin association and shuttling into EVs via lipid rafts. Conversely, Pak1 phosphorylated paxillin on Ser258, which inhibited TACE association and lipid raft transfer. Interestingly, melanoma cells used an identical mechanism to shuttle predominantly ADAM10 into EVs. We conclude that HIV-1 and cancer cells exploit a paxillin/integrin-controlled mechanism to release TACE/ADAM10-containing vesicles, ensuring better proliferation/growth conditions in their microenvironment.
EVALuna2:12854

How neural crest transcription factors contribute to melanoma heterogeneity, cellular plasticity, and treatment resistance - Wessely, Anja; Steeb, Theresa; Berking, Carola; Heppt, Markus (International Journal of Molecular Sciences, 2021)
Cutaneous melanoma represents one of the deadliest types of skin cancer. The prognosis strongly depends on the disease stage, thus early detection is crucial. New therapies, including BRAF and MEK inhibitors and immunotherapies, have significantly improved the survival of patients in the last decade. However, intrinsic and acquired resistance is still a challenge. In this review, we discuss two major aspects that contribute to the aggressiveness of melanoma, namely, the embryonic origin of melanocytes and melanoma cells and cellular plasticity. First, we summarize the physiological function of epidermal melanocytes and their development from precursor cells that originate from the neural crest (NC). Next, we discuss the concepts of intratumoral heterogeneity, cellular plasticity, and phenotype switching that enable melanoma to adapt to changes in the tumor microenvironment and promote disease progression and drug resistance. Finally, we further dissect the connection of these two aspects by focusing on the transcriptional regulators MSX1, MITF, SOX10, PAX3, and FOXD3. These factors play a key role in NC initiation, NC cell migration, and melanocyte formation, and we discuss how they contribute to cellular plasticity and drug resistance in melanoma.
CRIS-Team Scopus Importer:2021-06-18
Keywords: Cellular plasticity; FOXD3; Melanoma; MITF; MSX1; Neural crest; PAX3; Phenotype switch; SOX10

How to assess the efficacy of interventions for actinic keratosis? A review with a focus on long-term results - Steeb, Theresa; Wessely, Anja; Petzold, Anne; Schmitz, Lutz; Dirschka, Thomas; Berking, Carola; Heppt, Markus (Journal of Clinical Medicine, 2021)
Actinic keratoses (AK) are common lesions of the skin caused by cumulative sun exposure. Since AK may progress to invasive cutaneous squamous cell carcinoma (cSCC), guidelines uniformly recommend early and consequent treatment. A variety of interventions are available; however, most randomized controlled trials, meta-analyses, and guidelines focus on outcomes that are usually evaluated 8–12 weeks after the end of treatment. Importantly, these assessments can capture the short-term, transient outcomes, but do not allow any conclusions about long-term results to be drawn and do not reflect the probability of transition towards cSCC. Until now, few studies have assessed the long-term results of interventions for AK. Indeed, finding the most appropriate end-point and adjunct time point for determining the long-term results of interventions for AK remains a challenge. Here, we provide an overview of the different ways of measuring the efficacy of AK treatments, such as using recurrence rates or sustained clearance rates, and discuss methodological aspects. Furthermore, we highlight the importance of evidence from post-marketing surveillance trials for the detection of efficacy values and safety signals. Additionally, we emphasize that a follow-up period of 12 months might not be sufficient to reflect the long-term results and stress the urgent need for a longer follow-up period and regular risk-stratified surveillance.
CRIS-Team Scopus Importer:2021-10-29
Keywords: Actinic keratosis; Core outcomes; Follow-up; Long-term efficacy; Methodology; Prevention; Squamous cell carcinoma; Surveillance

HSV-1 Modulates IL-6 Receptor Expression on Human Dendritic Cells - Birzer, Alexandra; Krawczyk, Adalbert; Draßner, Christina; Kuhnt, Christine; Mühl-Zürbes, Petra; Heilingloh, Christiane; Steinkasserer, Alexander; Popella, Linda (Frontiers in Immunology, 2020)
Dendritic cells (DCs) are the guardians of the immune system since they are located in the majority of peripheral tissues. In addition, they are crucial for the induction of an effective immune response based on their unique capacity to stimulate naive T cells. During co-evolution, the human pathogen herpes simplex virus type 1 (HSV-1) has evolved several immune evasion mechanisms in order to subvert the host's immune system especially by targeting DC biology and function. Here we demonstrate that HSV-1 infection influences the IL-6 receptor (IL6R) expression both on protein and mRNA levels in/on human monocyte-derived mature DCs (mDCs). Surprisingly, reduced IL6R expression levels were also observed on uninfected bystander mDCs. Mechanistically, we clearly show that HSV-1-derived non-infectious light (L-) particles are sufficient to trigger IL6R regulation on uninfected bystander mDCs. These L-particles lack the viral DNA-loaded capsid and are predominantly produced during infection of mDCs. Our results show that the deletion of the HSV-1 tegument protein vhs partially rescued the reduced IL6R surface expression levels on/in bystander mDCs. Using a neutralizing antibody, which perturbs the transfer of L-particles to bystander mDCs, was sufficient to rescue the modulation of IL6R surface expression on uninfected bystander mDCs. This study provides evidence that L-particles transfer specific viral proteins to uninfected bystander mDCs, thereby negatively interfering with their IL6R expression levels, however, to a lesser extend compared to H-particles. Due to their immune-modulatory capacity, L-particles represent an elaborated approach of HSV-1-mediated immune evasion.
CRIS-Team Scopus Importer:2020-09-18
Keywords: bystander cells; HSV-1; IL-6 receptor; L-particles; mature dendritic cells; vhs

Human adenovirus-specific γ/δ and CD8+ T cells generated by T-cell receptor transfection to treat adenovirus infection after allogeneic stem cell transplantation. - Dörrie, Jan; Krug, Christian; Hofmann, Christian; Mueller, Ina; Wellner, Verena; Knippertz, Ilka; Schierer, Stephan; Thomas, Simone; Zipperer, Elke; Printz, Dieter; Fritsch, Gerhard; Schuler, Gerold; et al. (PLoS ONE, 2014)
Human adenovirus infection is life threatening after allogeneic haematopoietic stem cell transplantation (HSCT). Immunotherapy with donor-derived adenovirus-specific T cells is promising; however, 20% of all donors lack adenovirus-specific T cells. To overcome this, we transfected α/β T cells with mRNA encoding a T-cell receptor (TCR) specific for the HLA-A*0101-restricted peptide LTDLGQNLLY from the adenovirus hexon protein. Furthermore, since allo-reactive endogenous TCR of donor T lymphocytes would induce graft-versus-host disease (GvHD) in a mismatched patient, we transferred the TCR into γ/δ T cells, which are not allo-reactive. TCR-transfected γ/δ T cells secreted low quantities of cytokines after antigen-specific stimulation, which were increased dramatically after co-transfection of CD8α-encoding mRNA. In direct comparison with TCR-transfected α/β T cells, TCR-CD8α-co-transfected γ/δ T cells produced more tumor necrosis factor (TNF), and lysed peptide-loaded target cells as efficiently. Most importantly, TCR-transfected α/β T cells and TCR-CD8α-co-transfected γ/δ T cells efficiently lysed adenovirus-infected target cells. We show here, for the first time, that not only α/β T cells but also γ/δ T cells can be equipped with an adenovirus specificity by TCR-RNA electroporation. Thus, our strategy offers a new means for the immunotherapy of adenovirus infection after allogeneic HSCT.
EVALuna2:19437

Human Cytomegalovirus-Induced Degradation of CYTIP Modulates Dendritic Cell Adhesion and Migration - Grosche, Linda; Drassner, Christina; Mühl-Zürbes, Petra; Kamm, Lisa; Vu Thuy Khanh Le-Trilling,; Trilling, Mirko; Steinkasserer, Alexander; Heilingloh, Christiane (Frontiers in Immunology, 2017)
As potent antigen-presenting cells, dendritic cells (DCs) are essential for the initiation of effective antiviral immune responses. Viruses and especially herpesviruses, which are able to establish lifelong persistence, exploit several immune evasion mechanisms targeting DC biology. Our group has previously shown that the ?-herpesvirus herpes simplex virus type 1 inhibits mature DC (mDC) migration by inducing adhesion via degrading the cellular protein CYTIP (cytohesin-1 interacting protein), an important negative regulator of ?2-integrin activity. In the present study, we extended our analysis to the ?-herpesvirus human cytomegalovirus (HCMV), to investigate whether other herpesviridae also induce such modulations. Indeed, HCMV impairs mDC transwell migration capability following a CCL19-chemokine gradient, despite equivalent expression levels of the cognate chemokine receptor CCR7 at the corresponding time points post-infection. Remarkably, HCMV infection potently induced ?2-integrin activity on mDCs. Furthermore, directly HCMV-infected mDCs, exhibiting viral gene expression, strongly adhere to fibronectin and ICAM-1, in contrast to mDCs lacking infection or viral gene expression. Interestingly, HCMV-positive mDCs display a proteasome-dependent degradation of CYTIP. Contrasting the migration toward CCL19, elevated expression levels of the chemokine receptor CXCR4 in HCMV-infected mDCs were associated with functional CXCL12-chemotaxis under the herein used conditions. In summary, our results show that HCMV shapes mDC adhesion to compromise migration toward CCL19, but retaining CXCL12 responsiveness. Thus, we hypothesize that a preferred migration pattern toward the bone marrow, but not to secondary lymphoid organs, could ultimately cause a failure in the induction of potent antiviral immune responses.
EVALuna2:26038

Human cytomegalovirus interferes with dendritic cell adhesion and migration via the proteasomal degradation of the cytohesin-1 interacting protein - Grosche, Linda; Drassner, C.; Mühl-Zürbes, Petra; Kamm, L.; Le-Trilling, V. T. K.; Trilling, M.; Steinkasserer, Alexander; Heilingloh, Christiane (2018)
EVALuna2:36215

Human Fcγ-receptor IIb modulates pathogen-specific versus self-reactive antibody responses in lyme arthritis - Danzer, Heike; Glaesner, Joachim; Baerenwaldt, Anne; Reitinger, Carmen; Lux, Anja; Heger, Lukas; Dudziak, Diana; Harrer, Thomas; Gessner, Andre; Nimmerjahn, Falk (eLife, 2020)
Pathogen-specific antibody responses need to be tightly regulated to generate protective but limit self-reactive immune responses. While loss of humoral tolerance has been associated with microbial infections, the pathways involved in balancing protective versus autoreactive antibody responses in humans are incompletely understood. Studies in classical mouse model systems have provided evidence that balancing of immune responses through inhibitory receptors is an important quality control checkpoint. Genetic differences between inbred mouse models and the outbred human population and allelic receptor variants not present in mice; however, argue for caution when directly translating these findings to the human system. By studying Borrelia burgdorferi infection in humanized mice reconstituted with human hematopoietic stem cells from donors homozygous for a functional or a non-functional FcγRIIb allele, we show that the human inhibitory FcγRIIb is a critical checkpoint balancing protective and autoreactive immune responses, linking infection with induction of autoimmunity in the human immune system.
CRIS-Team Scopus Importer:2020-09-11
Keywords: arthritis; autoimmunity; borrelia burgdorferi; Fc-receptor; humanized mouse; immunology; inflammation; mouse

Human lymphoid organ dendritic cell identity is predominantly dictated by ontogeny, not tissue microenvironment - Heidkamp, Gordon Frederik; Sander, Jil; Lehmann, Christian; Heger, Lukas; Eissing, Nathalie; Baranska, Anna; Lühr, Jennifer; Hoffmann, Alana; Reimer, Katharina; Lux, Anja; Söder, Stephan; Hartmann, Arndt; et al. (Science immunology, 2016)
In mice, conventional and plasmacytoid dendritic cells (DCs) derive from separate hematopoietic precursors before they migrate to peripheral tissues. Moreover, two classes of conventional DCs (cDC1 and cDC2 DCs) and one class of plasmacytoid DCs (pDCs) have been shown to be transcriptionally and functionally distinct entities. In humans, these three DC subtypes can be identified using the cell surface markers CD1c (cDC2), CD141 (cDC1), and CD303 (pDCs), albeit it remains elusive whether DC functionality is mainly determined by ontogeny or the tissue microenvironment. By phenotypic and transcriptional profiling of these three DC subtypes in different human tissues derived from a large number of human individuals, we demonstrate that DC subpopulations in organs of the lymphohematopoietic system (spleen, thymus, and blood) are strongly defined by ontogeny rather than by signals from the microenvironment. In contrast, DC subsets derived from human lung or skin differed substantially, strongly arguing that DCs react toward modulatory signals from tissue microenvironments. Collectively, the data obtained in this study may serve as a major resource to guide further studies into human DC biology during homeostasis and inflammatio
EVALuna2:6852

Human lymphoid organ dendritic cell identity is predominantly dictated by ontogeny, not tissue microenvironment - Heidkamp, Gordon Frederik; Sander, J.; Lehmann, C. H. K.; Heger, Lukas; Eissing, N.; Baranska, A.; Lühr, Jennifer; Hoffmann, Alana; Reimer, Katharina; Lux, Anja; Söder, Stephan; Hartmann, Arndt; et al. (2017)
EVALuna2:33137

Human T cells expressing two additional receptors (TETARs) specific for HIV-1 recognize both epitopes - Hofmann, Christian; Hoefflin, Sandra; Hueckelhoven, Angela; Bergmann, Silke; Harrer, Ellen; Schuler, Gerold; Dörrie, Jan; Schaft, Niels; Harrer, Thomas (Blood, 2011)
Adoptive TCR transfer against rapidly mutating targets, such as HIV-1 or cancer, must counteract corresponding immune escape. Hence, we generated T cells expressing two additional receptors (TETARs) specific for HIV-1 by TCR mRNA electroporation. An HLA-A2-restricted gag-specific TCR and an HLA-B13-restricted nef-specific TCR were chosen. When both TCRs were transfected simultaneously, strong competitive effects occurred that were overcome by replacing the human constant domains of one TCR with murine counterparts and adapting the amounts of TCR-RNA used for transfection. The resulting TETAR responded to both epitopes with cytokine secretion and cytotoxic function. Cell sorting revealed that one individual cell indeed recognized both epitopes. The T cells diminished their reactivity to each epitope after stimulation but sequentially killed targets that presented the gag epitope and then targets that presented the nef epitope, or vice versa. Taken together, TETARs represent a sophisticated tool to study TCR functionality and might be a useful strategy in immunotherapy. © 2011 by The American Society of Hematology.
CRIS-Team Scopus Importer:2021-10-01

Hybrid modeling of the crosstalk between signaling and transcriptional networks using ordinary differential equations and multi-valued logic - Khan, Faiz M.; Schmitz, Ulf; Nikolov, Svetoslav; Engelmann, David; Puetzer, Brigitte M.; Wolkenhauer, Olaf; Vera González, Julio (BBA - Biochimica et Biophysica Acta, 2014)
A decade of successful results indicates that systems biology is the appropriate approach to investigate the regulation of complex biochemical networks involving transcriptional and post-transcriptional regulations. It becomes mandatory when dealing with highly interconnected biochemical networks, composed of hundreds of compounds, or when networks are enriched in non-linear motifs like feedback and feedforward loops. An emerging dilemma is to conciliate models of massive networks and the adequate description of non-linear dynamics in a suitable modeling framework. Boolean networks are an ideal representation of massive networks that are humble in terms of computational complexity and data demand. However, they are inappropriate when dealing with nested feedback/feedforward loops, structural motifs common in biochemical networks. On the other hand, models of ordinary differential equations (ODEs) cope well with these loops, but they require enormous amounts of quantitative data for a full characterization of the model. Here we propose hybrid models, composed of ODE and logical sub-modules, as a strategy to handle large scale, non-linear biochemical networks that include transcriptional and post-transcriptional regulations. We illustrate the construction of this kind of models using as example a regulatory network centered on E2F1, a transcription factor involved in cancer. The hybrid modeling approach proposed is a good compromise between quantitative/qualitative accuracy and scalability when considering large biochemical networks with a small highly interconnected core, and module of transcriptionally regulated genes that are not part of critical regulatory loops. This article is part of a Special Issue entitled: Computational Proteomics, Systems Biology & Clinical Implications. Guest Editor: Yudong Cai.
EVALuna2:19513

Hydradenitis suppurativa - new exploration on the famous Disease - Oetterich, Kerstin; Heppt, Franz; Sticherling, Michael (2017)
EVALuna2:34354

Hypertonicity-enforced BCL-2 addiction unleashes the cytotoxic potential of death receptors - Sirtl, Simon; Knoll, Gertrud; Dieu Thuy Trinh,; Lang, Isabell; Siegmund, Daniela; Gross, Stefanie; Schuler-Thurner, Beatrice; Neubert, Patrick; Jantsch, Jonathan; Wajant, Harald; Ehrenschwender, Martin (Oncogene, 2018)
Attempts to exploit the cytotoxic activity of death receptors (DR) for treating cancer have thus far been disappointing. DR activation in most malignant cells fails to trigger cell death and may even promote tumor growth by activating cell death-independent DR-associated signaling pathways. Overcoming apoptosis resistance is consequently a prerequisite for successful clinical exploitation of DR stimulation. Here we show that hyperosmotic stress in the tumor microenvironment unleashes the deadly potential of DRs by enforcing BCL-2 addiction of cancer cells. Hypertonicity robustly enhanced cytotoxicity of tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL) and other DR ligands in various cancer entities. Initial events in TRAIL DR signaling remained unaffected, but hypertonic conditions unlocked activation of the mitochondrial death pathway and thus amplified the apoptotic signal. Mechanistically, we demonstrate that hyperosmotic stress imposed a BCL-2-addiction on cancer cells to safeguard the integrity of the outer mitochondrial membrane (OMM), essentially exhausting the protective capacity of BCL-2-like pro-survival proteins. Deprivation of these mitochondrial safeguards licensed DR-generated truncated BH3-interacting domain death agonist (tBID) to activate BCL-2-associated X protein (BAX) and initiated mitochondrial outer membrane permeabilization (MOMP). Our work highlights that hyperosmotic stress in the tumor environment primes mitochondria for death and lowers the threshold for DR-induced apoptosis. Beyond TRAIL-based therapies, our findings could help to strengthen the efficacy of other apoptosis-inducing cancer treatment regimens.
EVALuna2:34786

Hypertonicity primes malignant melanoma cells for apoptosis - Calance, Diana Nicoleta; Steixner, Charlotte; Gross, Stefanie; Schuler-Thurner, Beatrice; Knoll, Gertrud; Ehrenschwender, Martin (Apoptosis, 2018)
The tumor environment critically influences responsiveness of cancer cells to chemotherapies, most of which activate the mitochondria-regulated (intrinsic) apoptotic cascade to kill malignant cells. Especially skin tumors encounter an environment with remarkable biophysical properties. Cutaneous accumulation of Na+ locally establishes osmotic pressure gradients in vivo (hypertonicity or hyperosmotic stress), but whether cutaneous hypertonicity is a factor that modulates the responsiveness of skin cancers to therapeutic apoptosis-induction has thus far not been investigated. Here, we show that hyperosmotic stress lowers the threshold for apoptosis induction in malignant melanoma, the deadliest form of skin cancer. Hypertonic conditions enforce addiction to BCL-2-like proteins to prevent initiation of the mitochondria-regulated (intrinsic) apoptotic pathway. Essentially, hyperosmotic stress primes mitochondria for death. Our work identifies osmotic pressure in the tumor microenvironment as a cell extrinsic factor that modulates responsiveness of malignant melanoma cells to therapy.
EVALuna2:34391

Identification and characterization of the specific murine NK cell subset supporting graft-versus-leukemia- and reducing graft-versus-host-effects - Meinhardt, Kathrin; Kroeger, Irena; Bauer, Ruth; Ganss, Franziska; Ovsiy, Ilja; Rothamer, Johanna; Büttner, Maike; Atreya, Imke; Waldner, Maximilian; Bittrich, Max; Lehmann, Christian; Rieger, Michael A.; et al. (OncoImmunology, 2015)
Clinical studies investigating the impact of natural killer (NK) cells in allogeneic hematopoietic stem cell transplantation settings have yielded promising results. However, NK cells are a functionally and phenotypically heterogeneous population. Therefore, we addressed the functional relevance of specific NK cell subsets distinguished by expression of CD117, CD27 and CD11b surface markers in graft-versus-leukemia (GVL)-reaction and graft-versus-host-disease (GVHD). Our results clearly demonstrate that the subset of c-Kit(-)CD27(-)CD11b(+) NK cells expressed multiple cytotoxic pathway genes and provided optimal graft-versus-leukemia-effects, while significantly reducing T cell proliferation induced by allogeneic dendritic cells. Furthermore, these NK cells migrated to inflamed intestinal tissues where graft-versus-host-colitis was efficiently mitigated. For the first time, we identified the c-Kit(-)CD27(-)CD11b(+) NK cell population as the specific effector NK cell subset capable of significantly diminishing GVHD in fully mismatched bone marrow transplantation settings. In conclusion, the subset of c-Kit(-)CD27(-)CD11b(+) NK cells not only supports GVL, but also plays a unique role in the protection against GVHD by migrating to the peripheral GVHD target organs where they exert efficient immunoregulatory activities. These new insights demonstrate the importance of selecting the optimal NK cell subset for cellular immunotherapy following allogeneic hematopoietic stem cell transplantation.
EVALuna2:1965

Identification of circulating microRNA patterns in patients in psoriasis and psoriatic arthritis - Haschka, Judith; Simon, David; Bayat, Sara; Messner, Zora; Kampylafka, Eleni; Fagni, Filippo; Skalicky, Susanna; Hackl, Matthias; Resch, Heinrich; Zwerina, Jochen; Kleyer, Arnd; Cavallaro, Alexander Josef; et al. (Rheumatology, 2023)
Objective miRNAs are small non-coding RNAs that control gene expression. Specific intra- and extracellular miRNA signatures have been identified in various diseases. Whether certain miRNA signatures are associated with psoriasis (PsO) and PsA is currently unknown. We aimed to search for circulating miRNA signatures associated with PsO and PsA patients. Methods Expression of miRNAs was analysed by reverse transcription quantitative real-time PCR (RT-qPCR) in the serum of PsA, PsO patients and healthy controls. Demographic and disease-specific characteristics and imaging data from hand MRI were recorded. In the discovery phase, 192 miRNA assays were analysed in 48 samples (PsA, PsO, controls: each N = 16). For validation, 17 selected miRNAs were measured in the total population. Results A total of 141 patients and controls were analysed (51 PsA, 40 PsO, 50 controls). In the discovery phase 51 miRNAs in PsO and 64 miRNAs in PsA were down- or upregulated compared with controls, with 33 miRNAs being changed in both (adj. P < 0.05). The 17 top candidates from discovery were assessed in the validation phase, 9 of them discriminated PsA and PsO from controls [area under the curve (AUC) >= 0.70, all P < 0.05]. Four miRNAs (miR-19b-3p, miR-21-5p, miR-92a-3p and let-7b-5p) were significantly differently regulated between PsO and PsA. A combination of these miRNAs increased the AUC to 0.92 in multivariate regression model to discriminate PsO and PsA. Conclusion miRNA signatures in PsA and PsO patients differ from controls. Nine miRNAs were differentially regulated in PsA and PsO patients, five of them previously reported to be involved in bone and cartilage metabolism, indicating an intimate association of psoriatic inflammation and bone/cartilage changes.
CRIS-Team WoS Importer:2023-03-17

IDENTIFICATION OF CIRCULATING MICRORNA SIGNATURES IN PATIENTS WITH PSORIASIS WITH SUBCLINICAL JOINT DISEASE AND PATIENTS WITH PSORIATIC ARTHRITIS - Haschka, J.; Simon, David; Bayat, Sara; Messner, Z.; Kampylafka, E.; Fagni, Filippo; Skalicky, S.; Hackl, M.; Resch, H.; Zwerina, J.; Kleyer, Arnd; Sticherling, Michael; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

Identification of miRNA-mRNA Modules in Colorectal Cancer Using Rough Hypercuboid Based Supervised Clustering - Paul, Sushmita; Lakatos, Petra; Hartmann, Arndt; Schneider-Stock, Regine; Vera, Julio (Scientific Reports, 2017)
Differences in the expression profiles of miRNAs and mRNAs have been reported in colorectal cancer. Nevertheless, information on important miRNA-mRNA regulatory modules in colorectal cancer is still lacking. In this regard, this study presents an application of the RH-SAC algorithm on miRNA and mRNA expression data for identification of potential miRNA-mRNA modules. First, a set of miRNA rules was generated using the RH-SAC algorithm. The mRNA targets of the selected miRNAs were identified using the miRTarBase database. Next, the expression values of target mRNAs were used to generate mRNA rules using the RH-SAC. Then all miRNA-mRNA rules have been integrated for generating networks. The RH-SAC algorithm unlike other existing methods selects a group of co-expressed miRNAs and mRNAs that are also differentially expressed. In total 17 miRNAs and 141 mRNAs were selected. The enrichment analysis of selected mRNAs revealed that our method selected mRNAs that are significantly associated with colorectal cancer. We identified novel miRNA/mRNA interactions in colorectal cancer. Through experiment, we could confirm that one of our discovered miRNAs, hsa-miR-93-5p, was significantly up-regulated in 75.8% CRC in comparison to their corresponding non-tumor samples. It could have the potential to examine colorectal cancer subtype specific unique miRNA/mRNA interactions.
EVALuna2:6844

Identification of Novel STAT6-Regulated Proteins in Mouse B Cells by Comparative Transcriptome and Proteome Analysis - Mokada Gopal, Lavanya; Boeser, Alexander; Lehmann, Christian; Drepper, Friedel; Dudziak, Diana; Warscheid, Bettina; Vöhringer, David (Journal of Immunology, 2017)
The transcription factor STAT6 plays a key role in mediating signaling downstream of the receptors for IL-4 and IL-13. In B cells, STAT6 is required for class switch recombination to IgE and for germinal center formation during type 2 immune responses directed against allergens or helminths. In this study, we compared the transcriptomes and proteomes of primary mouse B cells from wild-type and STAT6-deficient mice cultured for 4 d in the presence or absence of IL-4. Microarray analysis revealed that 214 mRNAs were upregulated and 149 were downregulated >3-fold by IL-4 in a STAT6-dependent manner. Across all samples, 5000 proteins were identified by label-free quantitative liquid chromatography/mass spectrometry. A total of 149 proteins was found to be differentially expressed >3-fold between IL-4-stimulated wild-type and STAT6(-/-) B cells (75 upregulated and 74 downregulated). Comparative analysis of the proteome and transcriptome revealed that expression of these proteins was mainly regulated at the transcriptional level, which argues against a major role for posttranscriptional mechanisms that modulate the STAT6-dependent proteome. Nine proteins were selected for confirmation by flow cytometry or Western blot. We show that CD30, CD79b, SLP-76, DEC205, IL-5R?, STAT5, and Thy1 are induced by IL-4 in a STAT6-dependent manner. In contrast, Syk and Fc receptor-like 1 were downregulated. This dataset provides a framework for further functional analysis of newly identified IL-4-regulated proteins in B cells that may contribute to germinal center formation and IgE switching in type 2 immunity.
EVALuna2:25886

Identification of two novel bullous pemphigoid- associated alleles, HLA-DQA1*05:05 and -DRB1*07:01, in Germans - Schwarm, Christian; Gola, Damian; Holtsche, Maike M.; Dieterich, Anabelle; Bhandari, Anita; Freitag, Miriam; Nürnberg, Peter; Toliat, Mohammad; Lieb, Wolfgang; Wittig, Michael; Franke, André; Worm, Margitta; et al. (Orphanet Journal of Rare Diseases, 2021)
Bullous pemphigoid (BP) is the most common autoimmune skin blistering disease characterized by autoimmunity against the hemidesmosomal proteins BP180, type XVII collagen, and BP230. To elucidate the genetic basis of susceptibility to BP, we performed the first genome-wide association study (GWAS) in Germans. This GWAS was combined with HLA locus targeted sequencing in an additional independent BP cohort. The strongest association with BP in Germans tested in this study was observed in the two HLA loci, HLA-DQA1*05:05 and HLA-DRB1*07:01. Further studies with increased sample sizes and complex studies integrating multiple pathogenic drivers will be conducted.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Autoimmune blistering skin diseases; Bullous pemphigoid; Germans; GWAS; HLA

Identifizierung von Biomarkern und neuen therapeutischen Zielen beim Aderhautmelanom - Wessely, Anja; Koch, Elias; Vera, Julio; Berking, Carola; Heppt, Markus (Journal der Deutschen Dermatologischen Gesellschaft, 2024)
Das Uveamelanom (UM) ist eine seltene Krebserkrankung, obwohl es der häufigste Tumor des Auges bei Erwachsenen ist. Die Patienten werden meist in Hautkrebszentren zur Behandlung der metastasierten Erkrankung vorgestellt. Es gibt jedoch erhebliche genetische, biologische und klinische Unterschiede zum kutanen Melanom. Die bei metastasiertem UM am häufigsten eingesetzten Therapien sind Tebentafusp und die kombinierte Immuncheckpoint-Blockade, die beide niedrige Ansprechraten aufweisen und mit hohen Behandlungskosten und erheblichen immunbedingten Toxizitäten verbunden sein können. Daher ist es von größter Bedeutung, einerseits Biomarker und klinische Profile zu identifizieren, die das Ansprechen auf die Behandlung vorhersagen können und andererseits neue therapeutische Ziele zu finden. Der Einsatz der Immuncheckpoint-Blockade zeigte in einer Reihe retrospektiver Studien günstigere Ergebnisse bei Patienten mit extrahepatischer Metastasierung und normalen Laktatdehydrogenase-Werten im Serum, so dass ihr Einsatz in dieser Subgruppe sinnvoller scheint. Um neue Zielmoleküle für Medikamente zu identifizieren, werden wir die Expression und Relevanz von Transkriptionsfaktoren der Neuralleiste in Bioproben von Patienten mit Next-Generation-Sequenzierung der dritten Generation analysieren. Computeralgorithmen und netzwerkbasierte Analysen werden die Identifizierung von Zielstrukturen für Medikamente erleichtern, die anschließend in Kurzzeit-Zellkulturen von Patienten validiert werden. Dieser Ansatz wird dazu beitragen, neue und personalisierte Behandlungen für das UM zu finde
CRIS-Team Scopus Importer:2024-01-19

Identifying biomarkers and novel therapeutic targets in uveal melanoma - Wessely, Anja; Koch, Elias; Vera, Julio; Berking, Carola; Heppt, Markus (Journal der Deutschen Dermatologischen Gesellschaft, 2023)
Uveal melanoma (UM) is an orphan cancer despite being the most common eye tumor in adults. Patients often present to skin cancer centers for treatment of metastatic disease although there are significant genetic, biological, and clinical differences from cutaneous melanoma. The treatments most commonly used for metastatic UM are tebentafusp and combined immune checkpoint blockade, both of which yield low response rates and may be accompanied by high treatment costs and significant immune-related toxicities. Thus, it is of paramount importance to identify biomarkers and clinical profiles predictive of treatment response and to find novel therapeutic targets. The use of immune checkpoint blockade showed more favorable outcomes in patients with extrahepatic disease and normal levels of serum lactate dehydrogenase in a panel of retrospective studies, making its use more reasonable in this subgroup. To identify novel drug targets, we will analyze the expression and relevance of neural crest transcription factors in patient bio-specimens using next-generation nanopore sequencing. Computer algorithms and network-based analysis will facilitate the identification of druggable targets which will subsequently be validated in patient-derived short-term cell cultures. This approach will help to find novel and personalized treatments for UM.
CRIS-Team Scopus Importer:2023-11-10

"I Feel I'm in Best Hands with You!": A Survey of Patient Satisfaction in a German University Skin Cancer Centre - Steeb, Theresa; Wessely, Anja; Merkl, Heike; Kirchberger, Michael; Bosch-Voskens, Caroline; Erdmann, Michael; Heinzerling, Lucie; Berking, Carola; Heppt, Markus (Acta Dermato-Venereologica, 2021)
An important measure of hospital quality is the satisfaction of patients. The aim of this cross-sectional study, performed in the dermato-oncology unit of the university hospital in Erlangen, Germany, was to assess skin cancer patients' degree of satisfaction with healthcare services. Self-administered questionnaires on patient satisfaction regarding contact with staff, need for information, and recommendation of the skin cancer centre were distributed in the day-care unit and the outpatient department to patients between April and June 2017. Results were reported descriptively and subgroup differences were explored using the Mann-Whitney U test, binary logistic regression, or χ2 test. Overall, 496 of 571 questionnaires were returned (86.9%). The median of all satisfaction items ranged between 1 (very good) and 2 (good). The majority of patients wanted more detailed information about skin cancer (46.7%, 142/304). Long waiting times were often criticized (22.8%; 80/351). Particular attention in addressing specific needs and fears may further increase patient satisfaction.
CRIS-Team Scopus Importer:2021-08-13
Keywords: cross-sectional study; melanoma; quality improvement; quality of care; skin cancer; patient satisfaction

IL-33-induced metabolic reprogramming controls the differentiation of alternatively activated macrophages and the resolution of inflammation - Faas, Maria; Ipseiz, Natacha; Ackermann, Jochen; Culemann, Stephan; Grüneboom, Anika; Schröder, Fenja; Rothe, Tobias; Scholtysek, Carina; Eberhardt, Martin; Böttcher, Martin; Kirchner, Philipp; Stoll, Cornelia; et al. (Immunity, 2021)
Alternatively activated macrophages (AAMs) contribute to the resolution of inflammation and tissue repair. However, molecular pathways that govern their differentiation have remained incompletely understood. Here, we show that uncoupling protein-2-mediated mitochondrial reprogramming and the transcription factor GATA3 specifically controlled the differentiation of pro-resolving AAMs in response to the alarmin IL-33. In macrophages, IL-33 sequentially triggered early expression of pro-inflammatory genes and subsequent differentiation into AAMs. Global analysis of underlying signaling events revealed that IL-33 induced a rapid metabolic rewiring of macrophages that involved uncoupling of the respiratory chain and increased production of the metabolite itaconate, which subsequently triggered a GATA3-mediated AAM polarization. Conditional deletion of GATA3 in mononuclear phagocytes accordingly abrogated IL-33-induced differentiation of AAMs and tissue repair upon muscle injury. Our data thus identify an IL-4-independent and GATA3-dependent pathway in mononuclear phagocytes that results from mitochondrial rewiring and controls macrophage plasticity and the resolution of inflammation.
CRIS-Team Scopus Importer:2021-11-19
Keywords: alternatively activated macrophage; GATA3; interleukin-33; itaconate; mitochondrial rewiring; resolution of inlammation; UCP2; uncoupling

Ileal immune tonus is a prognosis marker of proximal colon cancer in mice and patients - Picard, Marion; Yonekura, Satoru; Slowicka, Karolina; Petta, Ioanna; Rauber, Conrad; Routy, Bertrand; Richard, Corentin; Iebba, Valerio; Tidjani Alou, Maryam; Becharef, Sonia; Ly, Pierre; Pizzato, Eugenie; et al. (Cell Death and Differentiation, 2020)
Ileal epithelial cell apoptosis and the local microbiota modulate the effects of oxaliplatin against proximal colon cancer by modulating tumor immunosurveillance. Here, we identified an ileal immune profile associated with the prognosis of colon cancer and responses to chemotherapy. The whole immune ileal transcriptome was upregulated in poor-prognosis patients with proximal colon cancer, while the colonic immunity of healthy and neoplastic areas was downregulated (except for the Th17 fingerprint) in such patients. Similar observations were made across experimental models of implanted and spontaneous murine colon cancer, showing a relationship between carcinogenesis and ileal inflammation. Conversely, oxaliplatin-based chemotherapy could restore a favorable, attenuated ileal immune fingerprint in responders. These results suggest that chemotherapy inversely shapes the immune profile of the ileum–tumor axis, influencing clinical outcome.
CRIS-Team Scopus Importer:2020-12-11

Immune Checkpoint Blockade for Metastatic Uveal Melanoma: Patterns of Response and Survival According to the Presence of Hepatic and Extrahepatic Metastasis - Koch, Elias; Petzold, Anne; Wessely, Anja; Dippel, Edgar; Gesierich, Anja; Gutzmer, Ralf; Hassel, Jessica C.; Haferkamp, Sebastian; Hohberger, Bettina; Kaehler, Katharina C.; Knorr, Harald; Kreuzberg, Nicole; et al. (Cancers, 2021)
Simple Summary This retrospective multicenter study examines the influence of hepatic and extrahepatic metastases on the response of immune checkpoint blockade (ICB) in patients with metastatic uveal melanoma. A better response to dual ICB was observed in the presence of extrahepatic metastases in two recently published phase II trials. Therefore, we investigated two cohorts with and without extrahepatic metastasis and have assembled a population of 178 patients treated with ICB. The survival of this large cohort of patients with advanced UM was more favorable than that reported in previous benchmark studies. Patients with both hepatic and extrahepatic metastasis showed more favorable survival and higher response to dual ICB than those with hepatic metastasis only. Background: Since there is no standardized and effective treatment for advanced uveal melanoma (UM), the prognosis is dismal once metastases develop. Due to the availability of immune checkpoint blockade (ICB) in the real-world setting, the prognosis of metastatic UM has improved. However, it is unclear how the presence of hepatic and extrahepatic metastasis impacts the response and survival after ICB. Methods: A total of 178 patients with metastatic UM treated with ICB were included in this analysis. Patients were recruited from German skin cancer centers and the German national skin cancer registry (ADOReg). To investigate the impact of hepatic metastasis, two cohorts were compared: patients with liver metastasis only (cohort A, n = 55) versus those with both liver and extra-hepatic metastasis (cohort B, n = 123). Data were analyzed in both cohorts for response to treatment, progression-free survival (PFS), and overall survival (OS). The survival and progression probabilities were calculated with the Kaplan-Meier method. Log-rank tests, chi(2) tests, and t-tests were performed to detect significant differences between both cohorts. Results: The median OS of the overall population was 16 months (95% CI 13.4-23.7) and the median PFS, 2.8 months (95% CI 2.5-3.0). The median OS was longer in cohort B than in cohort A (18.2 vs. 6.1 months; p = 0.071). The best objective response rate to dual ICB was 13.8% and to anti-PD-1 monotherapy 8.9% in the entire population. Patients with liver metastases only had a lower response to dual ICB, yet without significance (cohort A 8.7% vs. cohort B 16.7%; p = 0.45). Adverse events (AE) occurred in 41.6%. Severe AE were observed in 26.3% and evenly distributed between both cohorts. Conclusion: The survival of this large cohort of patients with advanced UM was more favorable than reported in previous benchmark studies. Patients with both hepatic and extrahepatic metastasis showed more favorable survival and higher response to dual ICB than those with hepatic metastasis only.
CRIS-Team WoS Importer:2021-07-23

Immune Checkpoint Blockade for Metastatic Uveal Melanoma: Re-Induction following Resistance or Toxicity - Koch, Elias; Petzold, Anne; Wessely, Anja; Dippel, Edgar; Gesierich, Anja; Gutzmer, Ralf; Hassel, Jessica C.; Haferkamp, Sebastian; Kähler, Katharina C.; Knorr, Harald; Kreuzberg, Nicole; Leiter, Ulrike; et al. (Cancers, 2022)
Re-induction with immune checkpoint blockade (ICB) needs to be considered in many patients with uveal melanoma (UM) due to limited systemic treatment options. Here, we provide hitherto the first analysis of ICB re-induction in UM. A total of 177 patients with metastatic UM treated with ICB were included from German skin cancer centers and the German national skin cancer registry (ADOReg). To investigate the impact of ICB re-induction, two cohorts were compared: patients who received at least one ICB re-induction (cohort A, n = 52) versus those who received only one treatment line of ICB (cohort B, n = 125). In cohort A, a transient benefit of overall survival (OS) was observed at 6 and 12 months after the treatment start of ICB. There was no significant difference in OS between both groups (p = 0.1) with a median OS of 16.2 months (cohort A, 95% CI: 11.1–23.8) versus 9.4 months (cohort B, 95% CI: 6.1–14.9). Patients receiving re-induction of ICB (cohort A) had similar response rates compared to those receiving ICB once. Re-induction of ICB may yield a clinical benefit for a small subgroup of patients even after resistance or development of toxicities.
CRIS-Team Scopus Importer:2022-01-28
Keywords: CTLA-4; Immune checkpoint blockade; PD-1; Re-induction; Toxicity; Treatment resistance; Uveal melanoma

Immune checkpoint blockade in advanced cutaneous squamous cell carcinoma: What do we currently know in 2020? - Wessely, Anja; Steeb, Theresa; Leiter, Ulrike; Garbe, Claus; Berking, Carola; Heppt, Markus (International Journal of Molecular Sciences, 2020)
Cutaneous squamous cell carcinoma (cSCC) is the second most common skin cancer that predominantly arises in chronically sun-damaged skin. Immunosuppression, genetic disorders such as xeroderma pigmentosum (XP), exposure to certain drugs and environmental noxae have been identified as major risk factors. Surgical removal of cSCC is the therapy of choice and mostly curative in early stages. However, a minority of patients develop locally advanced tumors or distant metastases that are still challenging to treat. Immune checkpoint blockade (ICB) targeting CTLA-4, PD-L1 and PD-1 has tremendously changed the field of oncological therapy and especially the treatment of skin cancers as tumors with a high mutational burden. In this review, we focus on the differences between cSCC and cutaneous melanoma (CM) and their implications on therapy, summarize the current evidence on ICB for the treatment of advanced cSCC and discuss the chances and pitfalls of this therapy option for this cancer entity. Furthermore, we focus on special subgroups of interest such as organ transplant recipients, patients with hematologic malignancies, XP and field cancerization.
CRIS-Team Scopus Importer:2020-12-25
Keywords: Cemiplimab; Cutaneous squamous cell carcinoma; Immune checkpoint blockade; Pembrolizumab; Skin cancer

Immune checkpoint inhibitor-induced neurotoxicity is not associated with seroprevalence of neurotropic infections - Schmitt, C.; Hoefsmit, E. P.; Fangmeier, T.; Kramer, N.; Kabakci, C.; Vera González, Julio; Versluis, J. M.; Compter, A.; Harrer, Thomas; Mijočević, H.; Schubert, S.; Hundsberger, T.; et al. (Cancer Immunology, Immunotherapy, 2023)
Background: Immune checkpoint inhibitors (ICI) substantially improve outcome for patients with cancer. However, the majority of patients develops immune-related adverse events (irAEs), which can be persistent and significantly reduce quality of life. Neurological irAEs occur in 1–5% of patients and can induce severe, permanent sequelae or even be fatal. In order to improve the diagnosis and treatment of neurological irAEs and to better understand their pathogenesis, we assessed whether previous neurotropic infections are associated with neurological irAEs. Methods: Neurotropic infections that might predispose to ICI-induced neurological irAEs were analyzed in 61 melanoma patients from 3 countries, the Netherlands, Australia and Germany, including 24 patients with neurotoxicity and 37 control patients. In total, 14 viral, 6 bacterial, and 1 protozoal infections previously reported to trigger neurological pathologies were assessed using routine serology testing. The Dutch and Australian cohorts (NL) included pre-treatment plasma samples of patients treated with neoadjuvant ICI therapy (OpACIN-neo and PRADO trials; NCT02977052). In the Dutch/Australian cohort a total of 11 patients with neurological irAEs were compared to 27 control patients (patients without neurological irAEs). The German cohort (LMU) consisted of serum samples of 13 patients with neurological irAE and 10 control patients without any documented irAE under ICI therapy. Results: The association of neurological irAEs with 21 possible preceding infections was assessed by measuring specific antibodies against investigated agents. The seroprevalence of all the tested viral (cytomegalovirus, Epstein-Barr-Virus, varicella-zoster virus, measles, rubella, influenza A and B, human herpes virus 6 and 7, herpes simplex virus 1 and 2, parvovirus B19, hepatitis A and E and human T-lymphotropic virus type 1 and 2), bacterial (Borrelia burgdorferi sensu lato, Campylobacter jejuni, Mycoplasma pneumoniae, Coxiella burnetti, Helicobacter pylori, Yersinia enterocolitica and Y. pseudotuberculosis) and protozoal (Toxoplasma gondii) infections was similar for patients who developed neurological irAEs as compared to control patients. Thus, the analysis provided no evidence for an association of described agents tested for seroprevalence with ICI induced neurotoxicity. Conclusion: Previous viral, bacterial and protozoal neurotropic infections appear not to be associated with the development of neurological irAEs in melanoma patients who underwent therapy with ICI across 3 countries. Further efforts are needed to unravel the factors underlying neurological irAEs in order to identify risk factors for these toxicities, especially with the increasing use of ICI in earlier stage disease.
CRIS-Team Scopus Importer:2023-09-01
Keywords: Checkpoint-inhibitor; Melanoma; Serology; Side effect

Immune signatures predict development of autoimmune toxicity in patients with cancer treated with immune checkpoint inhibitors - Nuñez, Nicolas Gonzalo; Berner, Fiamma; Friebel, Ekaterina; Unger, Susanne; Wyss, Nina; Gomez, Julia Martinez; Purde, Mette Triin; Niederer, Rebekka; Porsch, Maximilian; Lichtensteiger, Christa; Kramer, Rafaela; Erdmann, Michael; et al. (Med, 2023)
Background: Immune checkpoint inhibitors (ICIs) are among the most promising treatment options for melanoma and non-small cell lung cancer (NSCLC). While ICIs can induce effective anti-tumor responses, they may also drive serious immune-related adverse events (irAEs). Identifying biomarkers to predict which patients will suffer from irAEs would enable more accurate clinical risk-benefit analysis for ICI treatment and may also shed light on common or distinct mechanisms underpinning treatment success and irAEs. Methods: In this prospective multi-center study, we combined a multi-omics approach including unbiased single-cell profiling of over 300 peripheral blood mononuclear cell (PBMC) samples and high-throughput proteomics analysis of over 500 serum samples to characterize the systemic immune compartment of patients with melanoma or NSCLC before and during treatment with ICIs. Findings: When we combined the parameters obtained from the multi-omics profiling of patient blood and serum, we identified potential predictive biomarkers for ICI-induced irAEs. Specifically, an early increase in CXCL9/CXCL10/CXCL11 and interferon-γ (IFN-γ) 1 to 2 weeks after the start of therapy are likely indicators of heightened risk of developing irAEs. In addition, an early expansion of Ki-67+ regulatory T cells (Tregs) and Ki-67+ CD8+ T cells is also likely to be associated with increased risk of irAEs. Conclusions: We suggest that the combination of these cellular and proteomic biomarkers may help to predict which patients are likely to benefit most from ICI therapy and those requiring intensive monitoring for irAEs. Funding: This work was primarily funded by the European Research Council, the Swiss National Science Foundation, the Swiss Cancer League, and the Forschungsförderung of the Kantonsspital St. Gallen.
CRIS-Team Scopus Importer:2023-02-17
Keywords: biomarkers for immunotherapy; cancer immunotherapy; checkpoint blockade; immune-related adverse events; Translation to patients

Immunogenic and tolerogenic effects of the chimeric IL-2-diphtheria toxin cytocidal agent Ontak(®) on CD25(+) cells - Lutz, Manfred B.; Baur, Andreas; Schuler-Thurner, Beatrice; Schuler, Gerold (OncoImmunology, 2014)
Ontak(®), a conjugate between IL-2 and a diphtheria toxin fragment, was recently investigated in cancer clinical trials aiming to kill CD25(+) regulatory T cells (Tregs). We found that the activity of Ontak(®) was more complex on Tregs and conventional T cells (Tconvs) than anticipated, including a novel strong influence on dendritic cells (DCs).
EVALuna2:19435

Immunoglobulin G-dependent inhibition of inflammatory bone remodeling requires pattern recognition receptor Dectin-1 - Seeling, Michaela; Pöhnl, Matthias; Kara, Sibel; Horstmann, Nathalie; Riemer, Carolina Daniela; Wöhner, Miriam; Liang, Chunguang; Brückner, Christin; Eiring, Patrick; Werner, Anja; Biburger, Markus; Altmann, Leon; et al. (Immunity, 2023)
Immunoglobulin G (IgG) antibodies are major drivers of inflammation during infectious and autoimmune diseases. In pooled serum IgG (IVIg), however, antibodies have a potent immunomodulatory and anti-inflammatory activity, but how this is mediated is unclear. We studied IgG-dependent initiation of resolution of inflammation in cytokine- and autoantibody-driven models of rheumatoid arthritis and found IVIg sialylation inhibited joint inflammation, whereas inhibition of osteoclastogenesis was sialic acid independent. Instead, IVIg-dependent inhibition of osteoclastogenesis was abrogated in mice lacking receptors Dectin-1 or FcγRIIb. Atomistic molecular dynamics simulations and super-resolution microscopy revealed that Dectin-1 promoted FcγRIIb membrane conformations that allowed productive IgG binding and enhanced interactions with mouse and human IgG subclasses. IVIg reprogrammed monocytes via FcγRIIb-dependent signaling that required Dectin-1. Our data identify a pathogen-independent function of Dectin-1 as a co-inhibitory checkpoint for IgG-dependent inhibition of mouse and human osteoclastogenesis. These findings may have implications for therapeutic targeting of autoantibody and cytokine-driven inflammation.
CRIS-Team Scopus Importer:2023-05-12
Keywords: bone; Dectin-1; Fc-receptor; glycosylation; IgG; inflammation; osteoclast; rheumatoid arthritis

Immunologic response to the survivin-derived multi-epitope vaccine EMD640744 in patients with advanced solid tumors - Lennerz, Volker; Gross, Stefanie; Gallerani, Elisa; Sessa, Cristiana; Mach, Nicolas; Boehm, Steffen; Hess, Dagmar; Von Boehmer, Lotta; Knuth, Alexander; Ochsenbein, Adrian F.; Gnad-Vogt, Ulrike; Zieschang, Juergen; et al. (Cancer Immunology Immunotherapy, 2014)
Survivin is a member of the inhibitor-of-apoptosis family. Essential for tumor cell survival and overexpressed in most cancers, survivin is a promising target for anti-cancer immunotherapy. Immunogenicity has been demonstrated in multiple cancers. Nonetheless, few clinical trials have demonstrated survivin-vaccine-induced immune responses.This phase I trial was conducted to test whether vaccine EMD640744, a cocktail of five HLA class I-binding survivin peptides in Montanide(®) ISA 51 VG, promotes anti-survivin T-cell responses in patients with solid cancers. The primary objective was to compare immunologic efficacy of EMD640744 at doses of 30, 100, and 300 ?g. Secondary objectives included safety, tolerability, and clinical efficacy.In total, 49 patients who received >=2 EMD640744 injections with available baseline- and >=1 post-vaccination samples [immunologic-diagnostic (ID)-intention-to-treat] were analyzed by ELISpot- and peptide/MHC-multimer staining, revealing vaccine-activated peptide-specific T-cell responses in 31 patients (63 %). This cohort included the per study protocol relevant ID population for the primary objective, i.e., T-cell responses by ELISpot in 17 weeks following first vaccination, as well as subjects who discontinued the study before week 17 but showed responses to the treatment. No dose-dependent effects were observed. In the majority of patients (61 %), anti-survivin responses were detected only after vaccination, providing evidence for de novo induction. Best overall tumor response was stable disease (28 %). EMD640744 was well tolerated; local injection-site reactions constituted the most frequent adverse event.Vaccination with EMD640744 elicited T-cell responses against survivin peptides in the majority of patients, demonstrating the immunologic efficacy of EMD640744.
EVALuna2:19468

Immunotherapy of uveal melanoma: vaccination against cancer : Multicenter adjuvant phase 3 vaccination study using dendritic cells laden with tumor RNA for large newly diagnosed uveal melanoma - Schuler-Thurner, Beatrice; Bartz-Schmidt, K. -U.; Bornfeld, N.; Cursiefen, C.; Fuisting, B.; Grisanti, S.; Heindl, L. M.; Holbach, L.; Keserue, M.; Knorr, H.; Koch, K.; Kruse, Friedrich; et al. (Ophthalmologe, 2015)
Uveal melanomas are the most common malignant tumors of the eye. With modern molecular biological diagnostic methods, such as chromosome 3 typing and gene expression analysis, these tumors can be categorized into highly aggressive (monosomy 3, class II) and less aggressive forms. This molecular biological stratification is primarily important for determining the risk of these tumors as no therapy is currently available that is able to prevent or delay metastases. A randomized study of patients with a poor prognosis (monosomy 3) is currently being carried out in order to determine whether a cancer vaccine prepared from autologous (patient's own) dendritic cells and uveal melanoma RNA can prevent or delay progression and further metastases of this extremely aggressive form of cancer. Inclusion in the uveal melanoma study, which hopes to provide a potential therapeutic option for patients, is only possible if patients are referred to an institution that is able to manufacture and provide this vaccination before the patient is operated on or treated with radiation. Untreated tumor material is necessary for producing the vaccine on an individualized patient basis.
EVALuna2:19521

Impact of Cytokine Inhibitor Therapy on the Prevalence, Seroconversion Rate, and Longevity of the Humoral Immune Response Against SARS-CoV-2 in an Unvaccinated Cohort - Simon, David; Tascilar, Koray; Kleyer, Arnd; Fagni, Filippo; Krönke, Gerhard; Meder, Christine; Dietrich, Peter; Orlemann, Till; Kliem, Thorsten; Moessner, Johanna; Liphardt, Anna-Maria; Schoenau, Verena; et al. (Arthritis and Rheumatology, 2022)
Objective To investigate the impact of biologic disease-modifying antirheumatic drug (bDMARD) treatment on the prevalence, seroconversion rate, and longevity of the humoral immune response against SARS-CoV-2 in patients with immune-mediated inflammatory diseases (IMIDs). Methods Anti-SARS-CoV-2 IgG antibodies were measured in a prospective cohort of health care professional controls and non-health care controls and IMID patients receiving no treatment or receiving treatment with conventional or biologic DMARDs during the first and second COVID-19 waves. Regression models adjusting for age, sex, sampling time, and exposure risk behavior were used to calculate relative risks (RRs) of seropositivity. Seroconversion rates were assessed in participants with polymerase chain reaction (PCR)-positive SARS-CoV-2 infection. Antibody response longevity was evaluated by reassessing participants who tested positive during the first wave. Results In this study, 4,508 participants (2,869 IMID patients and 1,639 controls) were analyzed. The unadjusted RR (0.44 [95% confidence interval (95% CI) 0.31-0.62]) and adjusted RR (0.50 [95% CI 0.34-0.73]) for SARS-CoV-2 IgG antibodies were significantly lower in IMID patients treated with bDMARDs compared to non-health care controls (P < 0.001), primarily driven by treatment with tumor necrosis factor inhibitors, interleukin-17 (IL-17) inhibitors, and IL-23 inhibitors. Adjusted RRs for untreated IMID patients (1.12 [95% CI 0.75-1.67]) and IMID patients receiving conventional synthetic DMARDs (0.70 [95% CI 0.45-1.08]) were not significantly different from non-health care controls. Lack of seroconversion in PCR-positive participants was more common among bDMARD-treated patients (38.7%) than in non-health care controls (16%). Overall, 44% of positive participants lost SARS-CoV-2 antibodies by follow-up, with higher rates in IMID patients treated with bDMARDs (RR 2.86 [95% CI 1.43-5.74]). Conclusion IMID patients treated with bDMARDs have a lower prevalence of SARS-CoV-2 antibodies, seroconvert less frequently after SARS-CoV-2 infection, and may exhibit a reduced longevity of their humoral immune response.
CRIS-Team WoS Importer:2022-04-08

Impact of Nrf2 expression in reconstituting T-cells of allogeneic hematopoietic stem cell transplanted patients - Karl, Franziska; Stoll, Andrej; Gamali, S.; Böttcher-Loschinski, Romy; Böttcher, Martin; Baur, Rebecca; Jacobs, Benedikt; Rösler, Wolf; Mackensen, Andreas; Mougiakakos, Dimitrios; Völkl, Simon (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-10-23

Impact of Plasma Membrane Domains on IgG Fc Receptor Function - Kara, Sibel; Amon, Lukas; Lühr, Jennifer; Nimmerjahn, Falk; Dudziak, Diana; Lux, Anja (Frontiers in Immunology, 2020)
Lipid cell membranes not only represent the physical boundaries of cells. They also actively participate in many cellular processes. This contribution is facilitated by highly complex mixtures of different lipids and incorporation of various membrane proteins. One group of membrane-associated receptors are Fc receptors (FcRs). These cell-surface receptors are crucial for the activity of most immune cells as they bind immunoglobulins such as immunoglobulin G (IgG). Based on distinct mechanisms of IgG binding, two classes of Fc receptors are now recognized: the canonical type I FcγRs and select C-type lectin receptors newly referred to as type II FcRs. Upon IgG immune complex induced cross-linking, these receptors are known to induce a multitude of cellular effector responses in a cell-type dependent manner, including internalization, antigen processing, and presentation as well as production of cytokines. The response is also determined by specific intracellular signaling domains, allowing FcRs to either positively or negatively modulate immune cell activity. Expression of cell-type specific combinations and numbers of receptors therefore ultimately sets a threshold for induction of effector responses. Mechanistically, receptor cross-linking and localization to lipid rafts, i.e., organized membrane microdomains enriched in intracellular signaling proteins, were proposed as major determinants of initial FcR activation. Given that immune cell membranes might also vary in their lipid compositions, it is reasonable to speculate, that the cell membrane and especially lipid rafts serve as an additional regulator of FcR activity. In this article, we aim to summarize the current knowledge on the interplay of lipid rafts and IgG binding FcRs with a focus on the plasma membrane composition and receptor localization in immune cells, the proposed mechanisms underlying this localization and consequences for FcR function with respect to their immunoregulatory capacity.
CRIS-Team Scopus Importer:2020-07-24
Keywords: cell membrane; CLR; FcγR; lipid rafts; membrane; membrane localization; type I FcR; type II FcR

IMPACT OF TOLL-LIKE RECEPTOR 9 IN INFLAMMATORY ARTHRITIS AND OSTEOCLASTOGENESIS - Fischer, Anita; Boehm, Christina; Koenders, Marije; Van Den Berg, Wim; Rothe, Tobias; Krönke, Gerhard; Dudziak, Diana; Steiner, Guenter (2017)
EVALuna2:34374

Impairment of gustatory and olfactory senses in plaque psoriasis - Rueter, P.; Gruenthaler, V.; Zopf, Yurdagül; Sticherling, Michael (2017)
EVALuna2:34082

Impairment of Taste and Smell in Psoriasis- another Cause of Impaired Calorie Intake? - Gruenthaler, V.; Rueter, P.; Zopf, Yurdagül; Sticherling, Michael (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-05-17

Impfungen in aller Munde – Relevanz auch für die Dermatologie? - Sticherling, Michael (Hautarzt, 2021)
CRIS-Team Scopus Importer:2021-02-05

Impfungen in der Dermatologie - Sticherling, Michael (Hautarzt, 2021)
Vaccinations are among the most successful prophylactic measures in medicine. As they are applied to healthy subjects, regulatory steps before licensing of any vaccination are strictly based on clinically controlled studies as well as on registry data in the further course. The probability and relevance of adverse reactions to vaccinations have to be weighed against any harm through the respective natural infection as well as the vaccination-induced protection against infections. Intolerance reactions to vaccinations are far more suspected than proven and altogether rare. Among these, specific dermatoses like psoriasis, atopic dermatitis and lichen planus are found as well as allergic reactions and a number of more nonspecific skin symptoms. Apart from provocation or exacerbation of an underlying dermatological disease, various intolerance reactions may be encountered which are classically allergologic or anaphylactoid. People with chronic dermatoses, especially those on immunosuppressive and immunomodulatory therapy, should have all recommended standard vaccinations. Vaccinations should not be administered during acute skin manifestations and relevant comedication—especially if immunomodulatory or immunosuppressive—has be taken into account in the decision to vaccinate and to define the time point of any vaccination. Inactivated vaccines may be administered even during ongoing immunosuppressive therapy, but may result in decreased immunological reactions and protection to infection. Live vaccines should be avoided.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Adverse reactions; Atopic dermatitis; Intolerance reactions; Lichen planus; Psoriasis

Implementation of dupilumab in routine care of atopic eczema. Results from the German national registry TREATgermany - Abraham, Susanne; Haufe, Eva; Harder, Inken; Heratizadeh, Annice; Kleinheinz, Andreas; Wollenberg, Andreas; Weisshaar, Elke; Augustin, Matthias; Wiemers, Franca; Zink, Alexander; Biedermann, Tilo; Von Kiedrowski, Ralph; et al. (British Journal of Dermatology, 2020)
The German atopic eczema (AE)-registry TREATgermany is a non-interventional multicenter patient cohort study for adult patients with currently moderate-to-severe disease activity or current/previous anti-inflammatory systemic treatment.1,2 Dupilumab has demonstrated to be an effective treatment for patients with moderate-to-severe AE in clinical trials.3-5 Real world evidence is now needed to evaluate its effectiveness and safety in routine care.
EVALuna2:212857

Implications of the COVID-19 Pandemic for the Development and Update of Clinical Practice Guidelines: Viewpoint - Steeb, Theresa; Follmann, Markus; Hagen, Ralf Matthias; Berking, Carola; Heppt, Markus (Journal of Medical Internet Research, 2020)
Following the rapid spread of a new type of coronavirus (SARS-CoV-2), nearly all countries have introduced temporary restrictions affecting daily life, with "social distancing" as a key intervention for slowing the spread of the virus. Despite the pandemic, the development or actualization of medical guidelines, especially in the rapidly changing field of oncology, needs to be continued to provide up-to-date evidence- and consensus-based recommendations for shared decision making and maintaining the treatment quality for patients. In this viewpoint, we describe the potential strengths and limitations of online conferences for medical guideline development. This viewpoint will assist guideline developers in evaluating whether online conferences are an appropriate tool for their guideline conference and audience.
CRIS-Team WoS Importer:2021-01-15

Increased Motility and Suppression of Ex Vivo–Expanded Regulatory T Cells Designed for Adoptive Transfer Therapy in Ulcerative Colitis - Müller, Tanja; Liu, Lijuan; Czerwinski, Tina; Wiesinger, Manuel; Dedden, Mark; Paap, Eva-Maria; Ullrich, Karen; Atreya, Imke; Siegmund, Britta; Atreya, Raja; Fabry, Ben; Berking, Carola; et al. (Cellular and Molecular Gastroenterology and Hepatology, 2023)
CRIS-Team Scopus Importer:2023-06-02

Increasing Participation Rates in Germany's Skin Cancer Screening Program (HELIOS): Protocol for a Mixed Methods Study - Steeb, Theresa; Heppt, Markus; Erdmann, Michael; Wessely, Anja; Klug, Stefanie J.; Berking, Carola (JMIR Research Protocols, 2021)
Background: In 2008, a nationwide skin cancer screening (SCS) program was implemented in Germany. However, participation rates remain low.
CRIS-Team WoS Importer:2022-02-04

Induction of anti-tumor responses via antigen targeting of dendritic cells in vivo - Amon, Lukas; Lehmann, Christian; Baranska, A.; Heidkamp, Gordon Frederik; Heger, Lukas; Lühr, Jennifer; Hofmann, Andrea; Nimmerjahn, Falk; Dudziak, Diana (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08

Infektiöse Reisedermatosen - Rongisch, Robert; Schmidt, Enno; Deresz, Nicolai; Deresz, Katharina; Schöfer, Helmut; Schäkel, Knut; Jakob, Thilo; Maurer, Marcus; Sticherling, Michael; Sunderkötter, Cord; Babilas, Philipp; Spornraft-Ragaller, Petra; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2020)
CRIS-Team Scopus Importer:2020-07-31

Inflammasomes in dendritic cells: Friend or foe? - Hatscher, Lukas; Amon, Lukas; Heger, Lukas; Dudziak, Diana (Immunology Letters, 2021)
Inflammasomes are cytosolic multiprotein complexes that crucially contribute to host defense against pathogens but are also involved in the pathogenesis of autoinflammatory diseases. Inflammasome formation leads to activation of effector caspases (caspase-1, 4, 5, or 11), the proteolytic maturation of IL-1β and IL-18 as well as cleavage of the pore-forming protein Gasdermin D. Dendritic cells are major regulators of immune responses as they bridge innate and adaptive immunity. We here summarize the current knowledge on inflammasome expression and formation in murine bone marrow-, human monocyte-derived as well as murine and human primary dendritic cells. Further, we discuss both, the beneficial and detrimental, involvement of inflammasome activation in dendritic cells in cancer, infections, and autoimmune diseases. As inflammasome activation is typically accompanied by Gasdermin D-mediated pyroptosis, which is an inflammatory form of programmed cell death, inflammasome formation in dendritic cells seems ill-advised. Therefore, we propose that hyperactivation, which is inflammasome activation without the induction of pyroptosis, may be a general model of inflammasome activation in dendritic cells to enhance Th1, Th17 as well as cytotoxic T cell responses.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Dendritic cell; Hyperactivation; Inflammasome; NLRP3; T cell response; Vaccination

Inflammatory markers in autoimmunity induced by checkpoint inhibitors - Husain, Beate; Kirchberger, Michael; Erdmann, Michael; Schüpferling, Sabine; Abolhassani, Amir Reza; Fröhlich, Waltraud; Berking, Carola; Heinzerling, Lucie (Journal of Cancer Research and Clinical Oncology, 2021)
Purpose: Immune checkpoint inhibitors (ICI) are highly effective in several cancer entities, but also invoke a variety of immune-related adverse events (irAE). These are mostly reversible, but can be life-threatening or even fatal. Currently, the pathogenesis is not fully understood, but crucial for effective treatment. Prediction and early detection of irAE could be facilitated and treatment optimized if relevant biomarkers and effector mechanisms were better characterized. Methods: This study included a total of 45 irAE in patients with metastatic melanoma who were treated with ICI. All patients underwent a complete work-up with exclusion of other causes. Longitudinal blood samples were analyzed for a panel of soluble markers and compared to baseline and to patients who did not experience any irAE. Measurements included LDH, interleukin (IL)-6, IL-1β, IL-17, C-reactive protein (CRP) and tumor necrosis factor (TNF)-alpha as well as tumor markers S100 and melanoma inhibitory activity (MIA). Results: During the early onset of irAE increases in serum IL-6 (from mean 24.4 pg/ml at baseline to 51.0 pg/ml; p = 0.003) and CRP (from mean 7.0 mg/l at baseline to 17.7 mg/l; p = 0.001) and a decrease in MIA (from mean 5.4 pg/ml at baseline to 4.8 pg/ml; p = 0.035) were detected. No changes in IL-17 were noted. These effects were observed for irAE of different organ systems. Conclusion: Increases of a combination of IL-6 and CRP serum levels can be used for the early detection of irAE and tailored management. Interestingly, changes in MIA serum levels also correlate with irAE onset.
CRIS-Team Scopus Importer:2021-04-23
Keywords: Cytokines; Immune checkpoint inhibitors; Immune-related adverse events; Melanoma

Influence of adjuvant therapies on organ-specific recurrence of cutaneous melanoma: A multicenter study on 1383 patients of the prospective DeCOG registry ADOReg - Wohlfeil, Sebastian A.; Kranzmann, Leonie; Weiß, Christel; von Wasielewski, Imke; Klespe, Kai C.; Kähler, Katharina C.; Weichenthal, Michael; Schadendorf, Dirk; Zimmer, Lisa; Mohr, Peter; Meier, Friedegund; Pfoehler, Claudia; et al. (International Journal of Cancer, 2024)
This study investigated whether adjuvant treatments in stage III cutaneous melanoma (CM) influenced patterns of recurrence. Patients with primary (n = 1033) or relapsed CM (n = 350) who received adjuvant therapies with Nivolumab (N), Pembrolizumab (P), or Dabrafenib and Trametinib (D + T) were extracted from the prospective multicenter real-world skin cancer registry ADOReg. Endpoints were progression-free survival (PFS), distant metastasis-free survival (DMFS), organ-specific DMFS, and overall survival (OS). For primary cases, D + T indicated an improved PFS (1- and 2-year PFS: 90.9%; 82.7%) as compared to P (81.0%, 73.9%; p =.0208), or N (83.8%, 75.2%; p =.0539). BRAF-mutated(mut) CM demonstrated significantly lower PFS (p =.0022) and decreased DMFS (p =.0580) when treated with immune checkpoint inhibitor (ICI) instead of D + T. Besides, NRAS-mut CM tended to perform worse than wt CM upon ICI (PFS: p =.1349; DMFS: p =.0540). OS was similar between the groups. Relapsed cases showed decreased PFS, DMFS, and OS in comparison to primary (all: p <.001), without significant differences between the subgroups. Organ-specific DMFS was significantly altered for primary cases with bone (p =.0367) or brain metastases (p =.0202). In relapsed CM, the frequency of liver (D + T: 1.5%; P: 12%; N: 9%) and LN metastases (D + T: 1.5%; P: 12%; N: 10.2%) was significantly lower with adjuvant D + T than ICI. NRAS-mut CM showed increased recurrence in primary and relapsed cases. These data show that adjuvant D + T is superior to ICI in primary BRAF-mut CM.
CRIS-Team Scopus Importer:2024-07-19
Keywords: adjuvant treatment; immune checkpoint inhibition; melanoma; targeted therapy; therapy resistance

Influence of TNF-alpha inhibitors and fumaric acid esters on male fertility in psoriasis patients - Heppt, Franz; Colsman, A.; Maronna, A.; Uslu, Ugur; Heppt, M. V.; Kiesewetter, Franklin; Sticherling, Michael (Journal of the European Academy of Dermatology and Venereology, 2017)
OBJECTIVE: Is there any influence of a therapy with TNF-alpha inhibitors or fumaric acid esters and of disease activity status on male fertility and sperm quality in patients with psoriasis? METHODS: In this monocentric, open-label, prospective study, semen samples were collected from patients receiving either TNF-alpha inhibitors or fumaric acid esters for moderate-to-severe plaque psoriasis. Semen was analysed at baseline before onset of the systemic therapy and monitored every 3 months under therapy. Sperm parameters were assessed according to the current WHO definitions. RESULTS: In total, 101 semen specimens from 27 patients were obtained. Mean Psoriasis Area and Severity Index (PASI) score at baseline was 11.05. Only 14.8% of patients showed a normozoospermia without any other abnormal seminal values. 85.2% of patients had at least one sperm/seminal abnormality, including two patients showing an azoospermia. Interestingly, 48.1% showed sperm parameters indicative of genital tract inflammation. Therapy with TNF-alpha inhibitors or fumaric acid esters did not have any negative effects on relevant sperm parameters such as mean total sperm number, sperm concentration, total and progressive motility. No major gonadal dysfunction was observed in any patient. CONCLUSION: At baseline, many patients with psoriasis showed abnormal semen/sperm parameters and remarkably elevated leukocytes and values of seminal polymorphonuclear elastase, indicating a genital tract inflammation. Thus, genital tract inflammation may represent an important comorbidity of psoriasis, little attention paid to so far. Regarding treatment with TNF-alpha inhibitors or fumaric acid esters, no major negative (side-) effects on sperm quality were observed.
EVALuna2:34337

Inhibited Arginase-1 Expression by Fra-1 in Myeloid Cells Enhance Rheumatoid Arthritis Inflammation - Hannemann, Nicole; Schnelzer, A.; Jordan, J.; Eberhardt, Martin; Schleicher, Ulrike; Uebe, Steffen; Ekici, Arif Bülent; Reid, Stephen; Sonnewald, Sophia; Bäuerle, Tobias; Bogdan, Christian; Vera, Julio; et al. (2017)
EVALuna2:33310

Inhibiting the neural crest transcription factor SOX10 leads to cell cycle arrest and apoptosis in uveal melanoma cells - Wessely, A.; Kammerbauer, C.; Lischer, Christopher; Vera González, Julio; Berking, Carola; Heppt, Markus (EXPERIMENTAL DERMATOLOGY, 2021)
CRIS-Team WoS Importer:2021-05-14

INHIBITION OF ARGINASE-1 EXPRESSION BY THE TRANSCRIPTION FACTOR FRA-1 IN MACROPHAGES EXACERBATES RHEUMATOID ARTHRITIS INFLAMMATION - Hannemann, Nicole; Cao, Shan; Schnelzer, A.; Jordan, J.; Eberhardt, Martin; Schleicher, Ulrike; Uebe, Steffen; Ekici, Arif Bülent; Rech, Jürgen; Bäuerle, Tobias; Bogdan, Christian; Vera, Julio; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2019)
CRIS-Team WoS Importer:2019-05-17

Innate extracellular vesicles from melanoma patients suppress beta-catenin in tumor cells by miRNA-34a - Lee, Jung-Hyun; Dindorf, Jochen; Eberhardt, Martin; Lai, Xin; Ostalecki, Christian; Koliha, Nina; Gross, Stefani; Blume, Katja; Bruns, Heiko; Wild, Stefan; Schuler, Gerold; Vera, Julio; et al. (Life Science Alliance, 2019)
Upon tumor development, new extracellular vesicles appear in circulation. Our knowledge of their relative abundance, function, and overall impact on cancer development is still preliminary. Here, we demonstrate that plasma extracellular vesicles (pEVs) of non-tumor origin are persistently increased in untreated and post-excision melanoma patients, exhibiting strong suppressive effects on the proliferation of tumor cells. Plasma vesicle numbers, miRNAs, and protein levels were elevated two-to tenfold and detected many years after tumor resection. The vesicles revealed individual and clinical stage-specific miRNA profiles as well as active ADAM10. However, whereas pEV from patients preventing tumor relapse down-regulated beta-catenin and blocked tumor cell proliferation in an miR-34a-dependent manner, pEV from metastatic patients lost this ability and stimulated beta-catenin-mediated transcription. Cancer-induced pEV may constitute an innate immune mechanismsuppressing tumor cell activity including that of residual cancer cells present after primary surgery.
CRIS-Team WoS Importer:2019-05-17

Insights From the Apremilast After Switching From Fumaric Acid Ester Treatment (APART) Study: An Interim Real-World Safety Analysis - Mrowietz, Ulrich; Ertner, Konstantin; Sticherling, Michael; Grosse, Virginia; Popp, Georg; Schwichtenberg, Uwe; Karl, Lars; Schenck, Florian; Ramaker-Brunke, Jutta; Roemmler-Zehrer, Josefine; Helget, Ursula; Gomez, Natalie Nunez (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2020)
CRIS-Team WoS Importer:2020-02-28

Integration of transcriptomics data into agent-based models of solid tumor metastasis - Retzlaff, Jimmy; Lai, Xin; Berking, Carola; Vera, Julio (Computational and Structural Biotechnology Journal, 2023)
Recent progress in our understanding of cancer mostly relies on the systematic profiling of patient samples with high-throughput techniques like transcriptomics. With this approach, one can find gene signatures and networks underlying cancer aggressiveness and therapy resistance. However, omics data alone cannot generate insights into the spatiotemporal aspects of tumor progression. Here, multi-level computational modeling is a promising approach that would benefit from protocols to integrate the data generated by the high-throughput profiling of patient samples. We present a computational workflow to integrate transcriptomics data from tumor patients into hybrid, multi-scale cancer models. In the method, we conduct transcriptomics analysis to select key differentially regulated pathways in therapy responders and non-responders and link them to agent-based model parameters. We then determine global and local sensitivity through systematic model simulations that assess the relevance of parameter variations in triggering therapy resistance. We illustrate the methodology with a de novo generated agent-based model accounting for the interplay between tumor and immune cells in a melanoma micrometastasis. The application of the workflow identifies three distinct scenarios of therapy resistance.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Immunotherapy; Melanoma; Multi-scale modelling; Systems biology

Intensity and longevity of SARS-CoV-2 vaccination response in patients with immune-mediated inflammatory disease: a prospective cohort study. - Simon, David; Tascilar, Koray; Fagni, Filippo; Kleyer, Arnd; Krönke, Gerhard; Meder, Christine; Dietrich, Peter; Orlemann, Till; Mößner, Johanna; Taubmann, Jule; Mutlu, Melek Yalcin; Knitza, Johannes; et al. (The Lancet Rheumatology, 2022)
Background: Concerns have been raised about the reduced immunogenicity of vaccines against SARS-CoV-2 in patients with immune-mediated inflammatory diseases and the higher risk of breakthrough infections. The objective of our study was to investigate the intensity and longevity of SARS-CoV-2 vaccination responses in patients with immune-mediated inflammatory diseases, and to assess the effects of diagnosis, treatment, and adapted vaccination schedules. Methods: SARS-CoV-2 IgG antibody response after SARS-CoV-2 vaccination was measured over time in a large prospective cohort of healthy controls and participants with immune-mediated inflammatory diseases (attending or admitted to affiliated centres) between Dec 15, 2020, and Dec 1, 2021. Cohort participants with immune-mediated inflammatory diseases and control participants with no diagnosis of immune-mediated inflammatory diseases, were eligible for this analysis. Demographic data and disease-specific data were collected using a questionnaire. Humoral response was compared across treatment and disease groups, and with respect to the receipt of additional vaccinations. SARS-CoV-2 antibody response was measured by ELISA using optical density ratio units and modelled over time with age and sex adjustment using mixed-effects models. Using these models, marginal mean antibody titres and marginal risks of a poor response (optical density ratio <1·1) were calculated for each week starting from week 8 after the first vaccination to week 40. Findings: Among 5076 individuals registered, 2535 participants with immune-mediated inflammatory diseases (mean age 55·0 [15·2] years; 1494 [58·9%] women and 1041 [41·1%] men) and 1198 healthy controls (mean age 40·7 [13·5] years; 554 [46·2%] women and 644 [53·8%] men) were included in this analysis. Mean antibody titres were higher in healthy controls compared with people with immune-mediated inflammatory diseases at all timepoints, with a peak antibody response in healthy controls (mean optical density ratio 12·48; 95% CI 11·50-13·53) of more than twice that in participants with immune-mediated inflammatory diseases (5·50; 5·23-5·77; mean difference 6·98; 5·92-8·04). A poor response to vaccination was observed in participants with immune-mediated inflammatory diseases who were taking B-cell inhibitors (peak mean difference from healthy controls 11·68; 10·07-13·29) and T-cell inhibitors (peakmean difference from healthy controls 10·43; 8·33-12·53). Mean differences in antibody responses between different immune-mediated inflammatory diseases were small. Participants with immune-mediated inflammatory diseases who were given a third vaccine dose had higher mean antibody titres than did healthy controls vaccinated with two vaccine doses at 40 weeks after the initial vaccination (mean difference 1·34; 0·01-2·69). Interpretation: People with immune-mediated inflammatory diseases show a lower and less durable SARS-CoV-2 vaccination response and are at risk of losing humoral immune protection. Adjusted vaccination schedules with earlier booster doses or more frequent re-doses, or both, could better protect people with immune-mediated inflammatory diseases. Funding: Deutsche Forschungsgemeinschaft, Bundesministerium für Bildung und Forschung, European Research Council, Innovative Medicine Initiative, Friedrich-Alexander-Universität Erlangen-Nürnberg, Else Kröner-Memorial Foundation.
EVALuna2:506737

Interest in tanning beds and sunscreen in German-speaking countries - Kirchberger, Michael C.; Kirchberger, Laura F.; Eigentler, Thomas K.; Reinhard, Raphael; Berking, Carola; Schuler, Gerold; Heinzerling, Lucie; Heppt, Markus V. (Journal der Deutschen Dermatologischen Gesellschaft, 2017)
BACKGROUND: The growing incidence of nearly all types of skin cancer can be attributed to increased exposure to natural or artificial ultraviolet (UV) radiation. However, there is a scarcity of statistical data on risk behavior or sunscreen use, which would be important for any prevention efforts. METHODS: Using the search engine Google® , we analyzed search patterns for the terms Solarium (tanning bed), Sonnencreme (sunscreen), and Sonnenschutz (sun protection) in Germany, Austria, and Switzerland between 2004 and 2016, and compared it to search patterns worldwide. For this purpose, "normalized search volumes" (NSVs) were calculated for the various search queries. The corresponding polynomial functions were then compared with each other over the course of time. RESULTS: Since 2001, there has been a marked worldwide decrease in the search queries for tanning bed, whereas those for sunscreen have steadily increased. In German-speaking countries, on the other hand, there have - for years - consistently been more search queries for tanning bed than for sunscreen. There is an annual periodicity of the queries, with the highest NSVs for tanning bed between March and May and those for sunscreen in the summer months around June. In Germany, the city-states of Hamburg and Berlin have particularly high NSVs for tanning bed. CONCLUSIONS: Compared to the rest of the world, German-speaking countries show a strikingly unfavorable search pattern. There is still great need for education and prevention with respect to sunscreen use and avoidance of artificial UV exposure.
EVALuna2:34311

Interleukin 17 Blockade in Psoriasis Patients with Subclinical Joint Inflammation- Prospective Open Study to Influence the Course of the Disease by means of Secukinumab - Kampylafka, E.; Oliveira, I.; Linz, C.; Lerchen, V.; Englbrecht, Matthias; Simon, David; Rech, Jürgen; Kleyer, Arnd; Schett, Georg; Sticherling, Michael; Hueber, Axel (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-05-17

Interleukin-17 Blockade Leads to Shifts from Stage-based Towards Response-based Disease Clusters- Comparative Data from Very Early and Established Psoriatic Arthritis - Kampylafka, Eleni; Tascilar, Koray; Lerchen, Veronika; Linz, Christina; Sokolova, Maria; Zekovic, Ana; Kleyer, Arnd; Simon, David; Rech, Jürgen; Sticherling, Michael; Schett, Georg; Hueber, Axel (ARTHRITIS & RHEUMATOLOGY, 2020)
CRIS-Team WoS Importer:2021-01-15

Interleukin-3 is a predictive marker for severity and outcome during SARS-CoV-2 infections - Bénard, Alan; Jacobsen, Anne; Brunner, Maximilian; Krautz, Christian; Klösch, Bettina; Swierzy, Izabela; Naschberger, Elisabeth; Podolska, Malgorzata; Kouhestani, Dina; David, Paul; Birkholz, Torsten; Castellanos, Ixchel; et al. (Nature Communications, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a worldwide health threat. In a prospective multicentric study, we identify IL-3 as an independent prognostic marker for the outcome during SARS-CoV-2 infections. Specifically, low plasma IL-3 levels is associated with increased severity, viral load, and mortality during SARS-CoV-2 infections. Patients with severe COVID-19 exhibit also reduced circulating plasmacytoid dendritic cells (pDCs) and low plasma IFNα and IFNλ levels when compared to non-severe COVID-19 patients. In a mouse model of pulmonary HSV-1 infection, treatment with recombinant IL-3 reduces viral load and mortality. Mechanistically, IL-3 increases innate antiviral immunity by promoting the recruitment of circulating pDCs into the airways by stimulating CXCL12 secretion from pulmonary CD123+ epithelial cells, both, in mice and in COVID-19 negative patients exhibiting pulmonary diseases. This study identifies IL-3 as a predictive disease marker for SARS-CoV-2 infections and as a potential therapeutic target for pulmunory viral infections.
CRIS-Team Scopus Importer:2021-03-05

Interleukin-3 protects against viral pneumonia in sepsis by enhancing plasmacytoid dendritic cell recruitment into the lungs and T cell priming - Benard, Alan; Hansen, Frederik; Uhle, Florian; Klösch, Bettina; Czubayko, Franziska; Mittelstädt, Anke; Jacobsen, Anne; David, Paul; Podolska, Malgorzata; Anthuber, Anna; Swierzy, Izabela; Schaack, Dominik; et al. (Frontiers in Immunology, 2023)
Rationale: Sepsis, a global health burden, is often complicated by viral infections leading to increased long-term morbidity and mortality. Interleukin-3 (IL-3) has been identified as an important mediator amplifying acute inflammation in sepsis; however, its function in the host response to viral infections during sepsis remains elusive. Objectives: To investigate the role of IL-3 during viral pneumonia in sepsis. Methods: We included septic patients from two different cohorts and used in vitro and in vivo assays. The obtained data were substantiated using a second model (SARS-CoV-2 infections). Measurements and main results: Low plasma IL-3 levels were associated with increased herpes simplex virus (HSV) airway infections in septic patients, resulting in reduced overall survival. Likewise, Il-3-deficient septic mice were more susceptible to pulmonary HSV-1 infection and exhibited higher pulmonary inflammation than control mice. Mechanistically, IL-3 increases innate antiviral immunity by promoting the recruitment of circulating plasmacytoid dendritic cells (pDCs) into the airways and by enhancing pDC-mediated T cell activation upon viral stimulation. Interestingly, the ability of IL-3 to improve adaptive immunity was confirmed in patients with SARS-CoV-2 infections. Conclusion: Our study identifies IL-3 as a predictive disease marker for viral reactivation in sepsis and reveals that IL-3 improves antiviral immunity by enhancing the recruitment and the function of pDCs.
CRIS-Team Scopus Importer:2023-03-24
Keywords: interleukin-3; plasmacytoid dendritic cells; sepsis; T cell priming; viral pneumonia

Inter-Rater Agreement in Assessing Risk of Bias in Melanoma Prediction Studies Using the Prediction Model Risk of Bias Assessment Tool (PROBAST): Results from a Controlled Experiment on the Effect of Specific Rater Training - Kaiser, Isabelle; Pfahlberg, Annette Bettina; Mathes, Sonja; Uter, Wolfgang; Diehl, Katharina; Steeb, Theresa; Heppt, Markus; Gefeller, Olaf (Journal of Clinical Medicine, 2023)
Assessing the risk of bias (ROB) of studies is an important part of the conduct of systematic reviews and meta-analyses in clinical medicine. Among the many existing ROB tools, the Prediction Model Risk of Bias Assessment Tool (PROBAST) is a rather new instrument specifically designed to assess the ROB of prediction studies. In our study we analyzed the inter-rater reliability (IRR) of PROBAST and the effect of specialized training on the IRR. Six raters independently assessed the risk of bias (ROB) of all melanoma risk prediction studies published until 2021 (n = 42) using the PROBAST instrument. The raters evaluated the ROB of the first 20 studies without any guidance other than the published PROBAST literature. The remaining 22 studies were assessed after receiving customized training and guidance. Gwet’s AC1 was used as the primary measure to quantify the pairwise and multi-rater IRR. Depending on the PROBAST domain, results before training showed a slight to moderate IRR (multi-rater AC1 ranging from 0.071 to 0.535). After training, the multi-rater AC1 ranged from 0.294 to 0.780 with a significant improvement for the overall ROB rating and two of the four domains. The largest net gain was achieved in the overall ROB rating (difference in multi-rater AC1: 0.405, 95%-CI 0.149–0.630). In conclusion, without targeted guidance, the IRR of PROBAST is low, questioning its use as an appropriate ROB instrument for prediction studies. Intensive training and guidance manuals with context-specific decision rules are needed to correctly apply and interpret the PROBAST instrument and to ensure consistency of ROB ratings.
CRIS-Team Scopus Importer:2023-03-24
Keywords: inter-rater agreement; inter-rater reliability; melanoma; prediction; PROBAST; risk of bias

Interventions for Actinic Keratosis in Nonscalp and Nonface Localizations: Results from a Systematic Review with Network Meta-Analysis - Steeb, Theresa; Wessely, Anja; Schmitz, Lutz; Heppt, Franz; Kirchberger, Michael; Berking, Carola; Heppt, Markus (Journal of Investigative Dermatology, 2020)
Myriad interventions are available for the treatment of actinic keratosis located on the face or scalp. However, lesions located outside the head and neck have received little attention until now. We aimed to synthesize the current knowledge of interventions for actinic keratosis in nonscalp and nonface localizations. Randomized controlled trials reporting data for these localizations were searched in MEDLINE, Embase, and The Cochrane Library CENTRAL, as well as in pertinent trial registers until 25 March 2020. A total of 13 randomized controlled trials with 1,380 patients were included in a systematic review. Five treatment modalities were evaluated and compared with placebo in a frequentist network meta-analysis, including cryosurgery, ingenol mebutate, photodynamic therapy, colchicine, and 5-fluorouracil. In the network meta-analysis, cryosurgery showed the highest participant complete clearance rates (risk ratio, 7.73; 95% confidence interval = 3.21–18.61; 10 studies; I2 = 20.3%; Grading of Recommendations Assessment, Development, and Evaluation, ++–) and lesion clearance rates (risk ratio, 2.97; 95% confidence interval = 2.45–3.59; 4 studies; I2 = 0%; Grading of Recommendations Assessment, Development, and Evaluation, ++–) compared with placebo. Ingenol mebutate demonstrated the highest participant partial clearance rates compared with placebo (risk ratio, 7.12; 95% confidence interval = 4.36–11.64; 5 studies; I2 = 0%; Grading of Recommendations Assessment, Development, and Evaluation, +++-). The mean reduction of lesions and occurrence of adverse events was poorly reported. The certainty of the evidence varied from very low to high and was limited by imprecision and study limitations.
CRIS-Team Scopus Importer:2020-08-07

Intranodal vaccination with mRNA-optimized dendritic cells in metastatic melanoma patients - Bol, Kalijn F.; Figdor, Carl G.; Aarntzen, Erik H. J. G.; Welzen, Marieke E. B.; Van Rossum, Michelle M.; Blokx, Willeke A. M.; Van De Rakt, Mandy W. M. M.; Scharenborg, Nicole M.; De Boer, Annemiek J.; Pots, Jeanette M.; Nordkamp, Michel A. M. Olde; Van Oorschot, Tom G. M.; et al. (OncoImmunology, 2015)
Autologous dendritic cell (DC) therapy is an experimental cellular immunotherapy that is safe and immunogenic in patients with advanced melanoma. In an attempt to further improve the therapeutic responses, we treated 15 patients with melanoma, with autologous monocyte-derived immature DC electroporated with mRNA encoding CD40 ligand (CD40L), CD70 and a constitutively active TLR4 (caTLR4) together with mRNA encoding a tumor-associated antigen (TAA; respectively gp100 or tyrosinase). In addition, DC were pulsed with keyhole limpet hemocyanin (KLH) that served as a control antigen. Production of this DC vaccine with high cellular viability, high expression of co-stimulatory molecules and MHC class I and II and production of IL-12p70, was feasible in all patients. A vaccination cycle consisting of three vaccinations with up to 15×10(6) DC per vaccination at a biweekly interval, was repeated after 6 and 12 months in the absence of disease progression. mRNA-optimized DC were injected intranodally, because of low CCR7 expression on the DC, and induced de novo immune responses against control antigen. T cell responses against tyrosinase were detected in the skin-test infiltrating lymphocytes (SKIL) of two patients. One mixed tumor response and two durable tumor stabilizations were observed among 8 patients with evaluable disease at baseline. In conclusion, autologous mRNA-optimized DC can be safely administered intranodally to patients with metastatic melanoma but showed limited immunological responses against tyrosinase and gp100.
EVALuna2:19574

Intravascular Large B-Cell Lymphoma: A Review with a Focus on the Prognostic Value of Skin Involvement - Breakell, Thomas; Waibel, Heidi; Schliep, Stefan; Ferstl, Barbara; Erdmann, Michael; Berking, Carola; Heppt, Markus (Current Oncology, 2022)
Intravascular large B-cell lymphoma (IVLBCL) is an aggressive Non-Hodgkin lymphoma (NHL) characterised by the presence of neoplastic lymphoid cells within small-and medium-sized blood vessels. According to the clinical presentation, the current WHO classification distinguishes the ‘classic’ (formerly ‘Western’) from a hemophagocytic syndrome-associated (formerly ‘Asian’) variant. A third ‘cutaneous’ variant has been proposed, characterised by a good prognosis and unique clinical features. While laboratory findings can hint at diagnosis, symptoms are rather nonspecific, and deep skin biopsy supported by further measures such as bone marrow aspiration and positron emission tomography-computed tomography scanning is needed to make a definite diagnosis. Treatment is comprised of anthracycline-based chemotherapy supplemented with rituximab and central nervous system prophylaxis. While there are various prognostic models for NHL, only one is specific to IVLBCL, which does not sufficiently represent some patient groups, especially regarding the lack of differentiation within the patient collective with skin involvement. This underlines the necessity for the establishment of further prognostic models in particular for IVLBCL patients with cutaneous manifestations.
CRIS-Team Scopus Importer:2022-05-13
Keywords: dermato-oncology; intravascular large B-cell lymphoma; IVLBCL; prognostic model; R-CHOP; skin cancer

Introducing SKINFO - the new and unique web-based information platform for German-speaking skin cancer patients - Steeb, Theresa; Hoffmann, Julia; Meier, Friedegund; Weber, Christiane; Bergmann, Maike; Mueller-Schuchardt, Anne; Weiler, Nina; Doppler, Astrid; Berking, Carola; Schadendorf, Dirk (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-12-16

Investigating dynamics of inhibitory and feedback loops in ERK signalling using power-law models - Vera, Julio; et al. (Molecular Biosystems, 2010)

Investigation of a kinetic model reproducing the mechanisms of oligodendrocytes differentiation - Nikolov, S. G.; Nenov, M.; Vera, Julio (Series on Biomechanics, 2021)
Studying of the gene regulatory architecture that controls region-independent dynamics of oligodendrocyte differentiation, Cantone and co-authors derived a kinetic model in 14 ordinary differential equations (ODEs) [Cantone, M. Kuspert, M., Reiprich, S., et al., Glia 67(5), 825-843, 2019]. In this paper, we investigate a reduced version of this model. The reduced model consists four ODEs of mSox9, mSox10, mOlig2 and miR cluster. The cluster is composed of four microRNAs, namely miR17, miR335, miR338, and miR155. The model predicts that the morphogen gradients (signals) and the transcription rate of Olig2 mRNA play a key role in the dynamic behaviour of the model, such as stability, bistability and instability (including self-oscillations (stable limit cycle)).
CRIS-Team Scopus Importer:2021-07-30
Keywords: Analysis; Dynamical behaviour; Kinetic model; Oligodendrocytes

Investigation of the expression of inflammatory markers in oral biofilm samples in patients with systemic scleroderma and the association with clinical periodontal parameters— a preliminary study - Buchbender, Mayte; Lugenbühl, Amelie; Fehlhofer, Jakob Paul; Kirschneck, Christian; Ries, Jutta; Lutz, Rainer; Sticherling, Michael; Kesting, Marco Rainer; Ries, Jutta (Life, 2021)
Background: Systemic scleroderma (SSc) has multiple orofacial effects. The aim of this study was to analyze the expression of inflammatory mediators in biofilm samples. It was hypothesized that different expression levels and clinical associations might be drawn. Methods: A total of 39 biofilm samples from group 1 = SSc and group 2 = healthy control were examined for the expression levels of interleukin (IL)-2,-6, and-10; matrix metalloprotease (MMP)-9; and surface antigens CD90 and CD34 by quantitative real-time PCR and clinical parameters. Relative quantitative (RQ) gene expression was determined using the ∆∆CT method. Results: The mean bleeding on probing values (p = 0.006), clinical attachment loss (CAL) (p = 0.009), gingival recession (p = 0.020), limited mouth opening (p = 0.001) and cervical tooth defects (p = 0.011) were significantly higher in group 1. RQ expressions of IL-2 and CD34 were significantly lower, IL-6, MMP-9, and CD90 were significantly higher. There was a significant positive correlation of IL-6/MMP-9 and negative correlation of mouth opening/CAL and IL-6/CAL. Conclusion: Different expression levels of IL-2, IL-6, MMP-9, CD34 and CD90 were detected in biofilm samples from patients with SSc compared to control. An immunological correlation to the clinical parameters of mouth opening and CAL was shown; thus, we conclude that SSc might have an impact on periodontal tissues.
CRIS-Team Scopus Importer:2021-11-05
Keywords: Biofilm samples; Expression levels of cytokines; Periodontal parameters; Systemic sclero-derma (SSc)

In vitro assessment of checkpoint-induced cytokine levels as new tool in the therapeutic decision-making process after checkpoint-induced cytokine release syndrome in metastatic melanoma - Kramer, Rafaela; Bender-Säbelkampf, Sophia; Berking, Carola; Heppt, Markus; Erdmann, Michael; Bosch-Voskens, Caroline (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2022)
CRIS-Team WoS Importer:2022-09-23

In vivo enzymatic modulation of IgG glycosylation inhibits autoimmune disease in an IgG subclass-dependent manner. - Albert, Heike; Collin, Mattias; Dudziak, Diana; Ravetch, J. V.; Nimmerjahn, Falk (Proceedings of the National Academy of Sciences of the United States of America, 2008)
IgG antibodies are potent inducers of proinflammatory responses. During autoimmune diseases such as arthritis and systemic lupus erythematosus, IgG autoantibodies are responsible for the chronic inflammation and destruction of healthy tissues by cross-linking Fc receptors on innate immune effector cells. The sugar moiety attached to the asparagine-297 residue in the constant domain of the antibody is critical for the overall structure and function of the molecule. Removal of this sugar domain leads to the loss of the proinflammatory activity, suggesting that in vivo modulation of antibody glycosylation might be a strategy to interfere with autoimmune processes. In this work, we investigated whether removal of the majority of the IgG-associated sugar domain by endoglycosidase S (EndoS) from Streptococcus pyogenes is able to interfere with autoimmune inflammation. We demonstrate that EndoS injection efficiently removes the IgG-associated sugar domain in vivo and interferes with autoantibody-mediated proinflammatory processes in a variety of autoimmune models. Importantly, however, we observed a differential impact of EndoS-mediated sugar side chain hydrolysis on IgG activity depending on the individual IgG subclass.

Isolated melanoma cells in sentinel lymph node in stage IIIA melanoma correlate with a favorable prognosis similar to stage IB - Amaral, Teresa; Nanz, Lena; Stadler, Rudolf; Berking, Carola; Ulmer, Anja; Forschner, Andrea; Meiwes, Andreas; Wolfsperger, Frederik; Meraz-Torres, Francisco; Chatziioannou, Eftychia; Martus, Peter; Flatz, Lukas; et al. (European Journal of Cancer, 2024)
Background: The American Joint Committee on Cancer 8th edition (AJCC v8) defines sentinel lymph nodes (SLN) containing any tumor cells as positive SLN. Consequently, even thin melanomas with isolated tumor cells (ic) in SLN are classified as stage IIIA, making them candidates for adjuvant therapy. Objectives and endpoints: We aimed to evaluate survival outcomes of melanoma stage IIIA (ic) and compare them with stage IIIA with lymph node (LN) metastases > 0.1 mm. Primary endpoints were relapse-free survival (RFS) and distant metastases-free survival (DMFS). Secondary endpoint was melanoma specific survival (MSS). Results: The discovery cohort from the Department of Dermatology, University Hospital Tuebingen, included 237 patients; confirmation cohort included 143 patients from the DeCOG trial. The Tuebingen cohort included 95 patients with stage IIIA (ic) and 142 patients with stage IIIA. The DeCOG trial included 39 patients with stage IIIA (ic) and 104 patients with stage IIIA. In the Tuebingen cohort, 10-year RFS rates for stage IIIA (ic) and IIIA were 84% (95% CI 75–94) and 49% (95% CI 39–59), respectively (p < 0.001). 10-year DMFS rates for stage IIIA (ic) and IIIA were 89% (95% CI 81–97) and 56% (95% CI 45–67), respectively; (p < 0.001). In the DeCOG cohort, 10-year RFS for stage IIIA (ic) and stage IIIA were 88% (95% CI 78–99) and 35% (95% CI 7–62), respectively; (p = 0.009). 10-year DMFS for stage IIIA (ic) and IIIA was 88% (95% CI 77–99) and 60% (95% CI 39–80), respectively (p = 0.061). Conclusion: Stage IIIA (ic) melanoma exhibits a prognosis similar to stage IB. Recommendation of adjuvant therapy in Stage IIIA (ic) warrants thorough discussion.
CRIS-Team Scopus Importer:2024-03-01
Keywords: Adjuvant therapy; Early stage; Isolated cells; Melanoma; Sentinel lymph node biopsy

Is tebentafusp superior to combined immune checkpoint blockade and other systemic treatments in metastatic uveal melanoma? A comparative efficacy analysis with population adjustment - Petzold, Anne; Steeb, Theresa; Wessely, Anja; Koch, Elias; Vera, Julio; Berking, Carola; Heppt, Markus (Cancer Treatment Reviews, 2023)
Background: Distinct systemic treatments exist for metastatic uveal melanoma. Tebentafusp and combined immune checkpoint blockade (ICB) with ipilimumab plus anti-PD-1 antibodies are the most commonly used treatment options but their comparative efficacy is unclear. The aim of this study is to compare currently available systemic treatments regarding overall survival (OS) and progression-free survival (PFS) with a focus on the comparison of tebentafusp versus combined ICB. Methods: The protocol for this study was defined a priori and registered online in the PROSPERO international prospective register of systematic reviews (CRD42022308356, date of registration: 7.2.2022). We performed a systematic literature search in Medline, Embase, and Central to identify eligible studies reporting Kaplan-Meier curves or individual-level survival data showing OS and PFS for metastatic uveal melanoma patients treated with systemic treatments. Kaplan-Meier curves were digitized using the “WebPlotDigitizer” program. Individual-level survival data were subsequently remodelled and pooled for distinct treatment groups. To compare the OS of tebentafusp versus combined ICB, we used matching-adjusted indirect comparison (MAIC), two-stage MAIC (2SMAIC), and simulated treatment comparison (STC) together with digitized individual-level survival data as population-adjusted models. Results: Overall, 55 independent studies were included of which 2,682 patients were evaluable for OS and 2,258 for PFS. Tebentafusp showed the highest median OS (mOS) of 22.4 months (95% confidence interval (CI): 19.9–29.6) compared to combined ICB (mOS: 15.7 months (95% CI: 14.4–17.9)), anti-PD-(L)1 antibody (mOS: 10.9 months (95% CI: 9.8–13.4)), chemotherapy (mOS: 9.95 months (95% CI: 8.9–11.2)), targeted therapies (mOS: 8.86 months (95% CI: 7.5–10.8)), and anti-CTLA-4 antibody (mOS: 7.8 months (95% CI: 6.8–9.3). The median PFS (mPFS) was similar among the treatment groups ranging from 2.7 months to 3.4 months. For the comparison of tebentafusp versus combined ICB, the hazard ratio (HR) was 0.641 (95% CI: 0.449–0.915) in the unadjusted model, whereas the population-adjusted models showed a HR of 0.386 (95% CI: 0.236–0.631) using MAIC, 0.378 (95% CI: 0.234–0.612) applying 2SMAIC and 0.284 (95% CI: 0.184–0.440) using STC. Conclusions: Tebentafusp achieved the best results compared to combined ICB and other systemic treatments, although these results have to be interpreted with caution due to the approximative methodical approach and high heterogeneity of included studies.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Immune checkpoint blockade; Individual patient data; Population-adjusted models; Survival; Tebentafusp; Uveal melanoma

Itching and Neurodermatitis: Results from the German Neurodermatitis Register TREATgermany - Haufe, Eva; Heinrich, Luise; Weisshaar, Elke; Abraham, Susanne; Heratizadeh, Annice; Harder, Inken; Kleinheinz, Andreas; Wollenberg, Andreas; Wiemers, Franca; Augustin, Matthias; Zink, Alexander; Von Kiedrowski, Ralph; et al. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2020)
CRIS-Team WoS Importer:2020-02-28

Itching and treatments in atopic dermatitis (AD): results from the German AD registry TREATgermany - Weisshaar, Elke; Bentz, Philipp; Haufe, Eva; Heinrich, Luise; Apfelbacher, Christian; Heratizadeh, Annice; Abraham, Susanne; Harder, Inken; Kleinheinz, Andreas; Wollenberg, Andreas; Schäkel, Knut; Wiemers, Franca; et al. (British Journal of Dermatology, 2023)
CRIS-Team Scopus Importer:2023-05-05

Itching in Atopic Dermatitis: Patient-and Physician-reported Outcomes in the German Atopic Dermatitis Registry TREATgermany - Weisshaar, Elke; Bentz, Philipp; Apfelbacher, Christian; Haufe, Eva; Heinrich, Luise; Heratizadeh, Annice; Abraham, Susanne; Harder, Inken; Kleinheinz, Andreas; Wollenberg, Andreas; Schäkel, Knut; Wiemers, Franca; et al. (Acta Dermato-Venereologica, 2023)
TREATgermany is an investigator-initiated prospective disease registry. It investigates physician-and patient-reported disease severity (Eczema Area and Severity Index (EASI), objective Scoring Atopic Dermatitis (oSCORAD), Investigator Global Assessment, Patient-Oriented Eczema Measure (POEM), Patient Global Assessment (PGA)), patient-reported symptoms (itch, sleep loss, depressive symptoms), therapy courses and dermatological quality of life (DLQI) in moderate-to-severe atopic dermatitis with SCORAD > 20. 1,134 atopic dermatitis patients (mean age 41.0 ± 14.7 years, 42.5% females) were enrolled by 40 German recruiting sites (dermatological clinics and practices) between June 2016 and April 2021. The cur-rent analysis focuses on itch scores obtained with a numerical rating scale (NRS)) documented for the pre-vious 3 days prior to baseline visit. The results show that 97.2% (1,090 of 1,121) patients experienced itch. Itch severity correlated moderately with severity of atopic dermatitis oSCORAD (rho = 0.44 (0.39–0.48)) and EASI score (rho = 0.41 (0.36–0.46)). A strong cor-relation was found with self-reported disease severity as PGA (rho = 0.68 (0.65–0.71)), POEM sum score (rho = 0.66 (0.63–0.69)) and dermatological quality of life impairment DLQI (rho = 0.61 (0.57–0.65)). Itch as a subjective complaint is more closely correlated with patient-reported outcomes than with objective assessments by the physician.
CRIS-Team Scopus Importer:2023-02-10
Keywords: EASI; POEM; pruritus; quality of life; registry

Itch, sleep loss, depressive symptoms, fatigue, and productivity loss in patients with moderate-to-severe atopic dermatitis: Analyses of TREATgermany registry data - Birkner, Thomas; Siegels, Doreen; Heinrich, Luise; Haufe, Eva; Abraham, Susanne; Heratizadeh, Annice; Harder, Inken; Bell, Magnus; Fell, Isabell; Worm, Margitta; Handrick, Christiane; Effendy, Isaak; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2023)
Background: TREATgermany is a multicenter registry including patients with moderate-to-severe atopic dermatitis (AD) from currently 74 study centers (university clinics, hospitals and practices) in Germany. As of August 31, 2021, 1,230 adult patients were enrolled. Methods: In TREATgermany, patients and physicians fill in questionnaires pertaining to symptoms, disease severity, quality of life, depressiveness, and fatigue. In particular, limitations in work performance are assessed using the Work Limitations Questionnaire (WLQ). To assess associations between occupational performance/work limitations and symptoms, correlations and regression models were calculated. Results: The examined sample of 228 employed patients reported an average of 6% at-work productivity loss within the past two weeks prior to enrolment in the registry. The WLQ productivity loss score was moderately associated with itch (r = 0.32) and sleep loss (r = 0.39) and strongly associated with depressive symptoms (r = 0.68) and fatigue (r = 0.60). Conclusions: The analyses of the registry data show that moderate-to-severe atopic dermatitis has a negative impact on the work productivity of the patients. The analyses further point out the relevant associations between work productivity, depressive symptoms, and fatigue highlighting the disease burden caused by the psychological components of AD.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Atopic dermatitis; productivity loss; registry; work limitations

Juckreiz, Schlafstörungen, depressive Symptome, Fatigue und Einschränkungen der Arbeitsproduktivität bei Patienten mit moderater bis schwerer atopischer Dermatitis: Daten aus dem TREATgermany-Register - Birkner, Thomas; Siegels, Doreen; Heinrich, Luise; Haufe, Eva; Abraham, Susanne; Heratizadeh, Annice; Harder, Inken; Bell, Magnus; Fell, Isabell; Worm, Margitta; Handrick, Christiane; Effendy, Isaak; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2023)
CRIS-Team Scopus Importer:2023-11-10
Keywords: Arbeitseinschränkungen; Atopic dermatitis; Atopische Dermatitis; productivity loss; Produktivitätsverlust; Register; registry; work limitations

Just One Position-Independent Lysine Residue Can Direct MelanA into Proteasomal Degradation following N-Terminal Fusion of Ubiquitin - Setz, Christian; Friedrich, Melanie; Hahn, Sabine; Dörrie, Jan; Schaft, Niels; Schuler, Gerold; Schubert, Ulrich (PLoS ONE, 2013)
N-terminal stable in frame fusion of ubiquitin (Ub) has been shown to target the fusion protein for proteasomal degradation. This pathway, called the Ub fusion degradation (UFD), might also elevate MHC class I (MHC-I) antigen presentation of specific antigens. The UFD, mainly studied on cytosolic proteins, has been described to be mediated by polyubiquitination of specific lysine residues within the fused Ub moiety. Using the well characterized melanoma-specific antigen MelanA as a model protein, we analyzed the requirements of the UFD for ubiquitination and proteasomal degradation of a transmembrane protein. Here we show that fusion of the non-cleavable UbG76V variant to the N-terminus of MelanA results in rapid proteasomal degradation via the endoplasmic reticulum-associated degradation (ERAD) pathway and, consequently, leads to an increased MHC-I antigen presentation. While lysine residues within Ub are dispensable for these effects, the presence of one single lysine residue, irrespectively of its location along the fusion protein, is sufficient to induce degradation of MelanA. These results show that the ubiquitination, ER to cytosol relocation and proteasomal degradation of a transmembrane protein can be increased by N-terminal fusion of Ub at the presence of at least one, position independent lysine residue. These findings are in contrast to the conventional wisdom concerning the UFD and indicate a new concept to target a protein into the ubiquitin-proteasome system (UPS) and thus for enhanced MHC-I antigen presentation, and might open up new possibilities in the development of tumor vaccines. © 2013 Setz et al.
CRIS-Team Scopus Importer:2021-10-01

Kinetic modeling-based detection of genetic signatures that provide chemoresistance via the E2F1-p73/DNp73-miR-205 network - Vera González, Julio; et al. (Cancer Research, 2013)
Drug resistance is a major cause of deaths from cancer. E2F1 is a transcription factor involved in cell proliferation, apoptosis and metastasis through an intricate regulatory network, which includes other transcription factors like p73 and cancer-related microRNAs like miR-205. To investigate the emergence of drug resistance, we developed a methodology that integrates experimental data with a network biology and kinetic modeling approach. Using a regulatory map developed to summarize knowledge on E2F1 its interplay with p73/DNp73 and miR-205 in cancer drug responses, we derived a kinetic model that represents the network response to certain genotoxic and cytostatic anti-cancer drugs. By perturbing the model parameters we mimic heterogeneous cell configurations referred to as in silico cell lines. These were used to detect genetic signatures characteristic for single or double drug resistance. We identified a signature composed of high E2F1 and low miR-205 expression that promotes resistance to genotoxic drugs. In this signature, downregulation of miR-205 can be mediated by an imbalance in the p73/DNp73 ratio or by dysregulation of other cancer-related regulators of miR-205 expression like TGFβ-1 or TWIST1. In addition, we found that a genetic signature composed of high E2F1, low miR-205 and high ERBB3 can render tumor cells insensitive to both cytostatic and genotoxic drugs. Our model simulations also suggested that conventional genotoxic drug treatment favors selection of chemoresistant cells in genetically heterogeneous tumors, in a manner requiring dysregulation of incoherent feedforward loops that involve E2F1, p73/DNp73 and miR-205. <
Keywords: Computational modelling; melanoma; network biology; cancer therapy resistance; miRNAs; Transcription factors; systems biology

Kit regulates HSC engraftment across the human-mouse species barrier - Cosgun, Kadriye Nehir; Rahmig, Susann; Mende, Nicole; Reinke, Soeren; Hauber, Ilona; Schaefer, Carola; Petzold, Anke; Weisbach, Henry; Heidkamp, Gordon Frederik; Purbojo, Ariawan; Cesnjevar, Robert; Platz, Alexander; et al. (Cell Stem Cell, 2014)
In-depth analysis of the cellular and molecular mechanisms regulating human HSC function will require a surrogate host that supports robust maintenance of transplanted human HSCs in vivo, but the currently available options are problematic. Previously we showed that mutations in the Kit receptor enhance engraftment of transplanted HSCs in the mouse. To generate an improved model for human HSC transplantation and analysis, we developed immune-deficient mouse strains containing Kit mutations. We found that mutation of the Kit receptor enables robust, uniform, sustained, and serially transplantable engraftment of human HSCs in adult mice without a requirement for irradiation conditioning. Using this model, we also showed that differential KIT expression identifies two functionally distinct subpopulations of human HSCs. Thus, we have found that the capacity of this Kit mutation to open up stem cell niches across species barriers has significant potential and broad applicability in human HSC research.
EVALuna2:19491

Kutanes Plattenepithelkarzinom - Leiter, U.; Gutzmer, R.; Alter, M.; Ulrich, C.; Meiwes, A.; Heppt, Markus; Steeb, Theresa; Berking, Carola; Lonsdorf, A. S.; Sachse, M. M.; Garbe, C.; Hillen, U. (Hautarzt, 2020)
Cutaneous squamous cell carcinoma (cSCC) is one of the most common cancers of the Caucasian population and accounts for 20% of all skin tumours. An S3 guideline of the German Guideline Program in Oncology has been available since 2019. The diagnosis is based on the clinical examination. Excision and histological confirmation is required for all clinically suspicious lesions to allow prognostic assessment and correct treatment. The therapy of first choice is complete excision with histological control of the surgical margin. In cSCC with risk factors such as tumor thickness >6 mm, sentinel lymph node biopsy may be discussed, but there is currently no clear evidence of its prognostic and therapeutic relevance. Adjuvant radiation therapy may be considered in cases of high risk of recurrence and should be tested in cases of inoperable tumors. The indication for electrochemotherapy should also be considered in the treatment of local or locoregional recurrence. The immune checkpoint inhibitor cemiplimab is approved for the treatment of inoperable or metastasized cSCC. In case of contraindications, chemotherapeutic agents, epidermal growth factor receptor (EGFR) inhibitors or palliative radiotherapy can be used. Since the evidence is low in these cases, a systemic therapy should be used preferentially within clinical studies. Follow-up care should be risk-adapted and includes a dermatological control, supplemented by ultrasound examinations in high-risk patients.
CRIS-Team Scopus Importer:2020-07-10
Keywords: Aftercare; Diagnosis; Management; Non melanoma skin cancer; Treatment

Landscape of Bone Marrow Metastasis in Human Neuroblastoma Unraveled by Transcriptomics and Deep Multiplex Imaging - Lazic, Daria; Kromp, Florian; Rifatbegovic, Fikret; Repiscak, Peter; Kirr, Michael; Mivalt, Filip; Halbritter, Florian; Bernkopf, Marie; Bileck, Andrea; Ussowicz, Marek; Ambros, Inge M.; Ambros, Peter F.; et al. (Cancers, 2021)
Simple Summary Bone marrow metastasis frequently occurs in patients with solid cancers and most often leads to poor outcome. Yet, the composition of bone marrow metastases, including tumor and surrounding cells, has so far not been characterized. Herein, we aimed to investigate the diversity of tumor and surrounding cells, i.e., the microenvironment, in bone marrow metastases, using the childhood tumor neuroblastoma as a model. To this end, we screened genome-wide datasets to define a panel of cell-specific markers for multiplex microscopy of metastatic bone marrow samples, and developed DeepFLEX, a computational pipeline for subsequent image analysis. Thereby, we identified 35,000 single cells covering metastasized tumor cells, and various types of developing immune and bone marrow cells. In parallel, we analyzed the transcriptome, i.e., all genes that are expressed as mRNA, of 38 patients with and without bone marrow metastasis. We found vast tumor cell diversity and identified a marker protein, FAIM2, which can help to identify a broader range of tumor cell variants. In addition we showed that tumor cell metastasis in the bone marrow is associated with an immune response resembling inflammation, and the presence of cells that can repress an immune attack against cancer cells. Our study suggests that metastatic tumor cells are shaping the bone marrow microenvironment and builds the basis to further investigate its clinical relevance. While the bone marrow attracts tumor cells in many solid cancers leading to poor outcome in affected patients, comprehensive analyses of bone marrow metastases have not been performed on a single-cell level. We here set out to capture tumor heterogeneity and unravel microenvironmental changes in neuroblastoma, a solid cancer with bone marrow involvement. To this end, we employed a multi-omics data mining approach to define a multiplex imaging panel and developed DeepFLEX, a pipeline for subsequent multiplex image analysis, whereby we constructed a single-cell atlas of over 35,000 disseminated tumor cells (DTCs) and cells of their microenvironment in the metastatic bone marrow niche. Further, we independently profiled the transcriptome of a cohort of 38 patients with and without bone marrow metastasis. Our results revealed vast diversity among DTCs and suggest that FAIM2 can act as a complementary marker to capture DTC heterogeneity. Importantly, we demonstrate that malignant bone marrow infiltration is associated with an inflammatory response and at the same time the presence of immuno-suppressive cell types, most prominently an immature neutrophil/granulocytic myeloid-derived suppressor-like cell type. The presented findings indicate that metastatic tumor cells shape the bone marrow microenvironment, warranting deeper investigations of spatio-temporal dynamics at the single-cell level and their clinical relevance.
CRIS-Team WoS Importer:2021-09-24

Lenalidomide enhances MOR202-dependent macrophage-mediated effector functions via the vitamin D pathway - Busch, Leonhard; Mougiakakos, Dimitrios; Büttner-Herold, Maike; Müller, Miriam J.; Volmer, Dietrich A.; Bach, Christian; Fabri, Mario; Bittenbring, Jörg T.; Neumann, Frank; Boxhammer, Rainer; Nolting, Jens; Bisht, Savita; et al. (Leukemia, 2018)
Macrophages are key mediators of the therapeutic effects exerted by monoclonal antibodies, such as the anti-CD38 antibody MOR202, currently introduced in multiple myeloma (MM) therapy. Therefore, it is important to understand how antibody-mediated effector functions of myeloma-associated macrophages (MAMs) are regulated. Here, we focused on the effects of vitamin D, a known regulator of macrophage effector functions. Consequently, it was the aim of this study to assess whether modulation of the vitamin D pathway alters the tumoricidal activity of MAMs. Here, we demonstrate that MAMs display a defective vitamin D pathway with reduced expression level of CYP27B1 and limited tumoricidal activity which can be restored by the IMiD lenalidomide in vitro. Furthermore, our data indicate that the vitamin D pathway of MAMs from MM patients does recover during an IMiD-containing therapy shown by an improved MOR202-mediated cytotoxic activity of these MAMs against primary MM cells ex vivo. Here, the ex vivo cytotoxic activity could be further enhanced by vitamin D supplementation. These data suggest that vitamin D holds a key role for the effector functions of MAMs and that vitamin D supplementation in IMiD combination trials could further increase the therapeutic efficacy of anti-CD38 antibodies such as MOR202, which remains to be investigated in clinical studies.
EVALuna2:34165

Leukoreduction system chambers are an efficient, valid, and economic source of functional monocyte-derived dendritic cells and lymphocytes - Pfeiffer, Isabell A.; Zinser, Elisabeth; Strasser, Erwin; Stein, Marcello F.; Dörrie, Jan; Schaft, Niels; Steinkasserer, Alexander; Knippertz, Ilka (Immunobiology, 2013)
The demand for human monocyte-derived dendritic cells (moDCs), as well as for primary human B and T lymphocytes for immunological research purposes has been increased in recent years. Classically, these monocytes are isolated from blood, leukapheresis products or buffy coats of healthy donors by plastic adherence of peripheral blood mononuclear cells (PBMCs), followed by stimulation with granulocyte macrophage colony-stimulating factor (GM-CSF) and interleukin (IL)-4, while lymphocytes are usually isolated from the non-adherent fraction (NAF) by magnetic cell sorting. However, donor-blood is a limited resource and not every blood bank offers leukapheresis products or buffy coats for laboratory use. Additionally, a leukapheresis is very expensive and also the generation/isolation of cells is time- and cost-intensive. To overcome some of these obstacles, we evaluated if low-cost leukoreduction system chambers (LRSCs), which arise after routine donor plateletpheresis procedures, and are usually discarded, would be an alternative and appropriate source of PBMCs to generate moDCs and to isolate lymphocytes. By analyzing the number and phenotype of immature and mature dendritic cells (DCs), as well as of B and T lymphocytes derived from LRSCs, we found all cells to be of high quantity and quality. Further investigations on DCs comprising transwell migration assays, allogeneic mixed lymphocyte reactions (MLR), cytokine secretion assays, and cytotoxic T cell induction assays revealed high migratory, as well as stimulatory capacity of these cells. In addition, DCs and T cells were efficiently electroporated with mRNA and showed characteristic cytokine production after co-culture, demonstrating LRSCs as an efficient, valid, and economic source for generation of moDCs and lymphocytes for research purposes. © 2013 Elsevier GmbH.
CRIS-Team Scopus Importer:2021-10-01
Keywords: B cell; Leukoreduction system chamber; Monocyte-derived dendritic cell; Peripheral blood mononuclear cell; T cell

Life-threatening Autoimmune Cardiomyopathy Reproducibly Induced in a Patient by Checkpoint Inhibitor Therapy - Tajmir-Riahi, Azadeh; Bergmann, Tanja; Schmid, Michael; Agaimy, Abbas; Schuler, Gerold; Heinzerling, Lucie (Journal of Immunotherapy, 2018)
Checkpoint inhibitors induce a plethora of immune-related adverse events (irAEs) including autoimmune colitis, hepatitis, endocrinopathies, and rarer side effects like neuritis. Here, a case of autoimmune cardiomyopathy (grade 3 CTCAE) and myocarditis under combination therapy with nivolumab plus ipilimumab in a 72-year-old melanoma patient is reported. Treatment induced a partial response for 14 months. However, after 10 infusions the patient developed dyspnea, edema of the legs, ascites and a weight gain of 10 kg because of a decompensated heart insufficiency with a reduced ejection fraction from formerly 48%-50% to 15%. Ischemia and viral infections were ruled out. Histopathology showed hypertrophic myocarditis with interstitial lymphocytes. Prednisolone improved the patient's condition within 3 days, leading to a 25% and 30% ejection fraction after 2 and 8 weeks, respectively, and clinical symptoms subsided completely. Importantly, reinduction of anti-PD1 therapy resulted in a flare of myocarditis. Awareness for potentially life-threatening irAE of checkpoint inhibitors like autoimmune cardiomyopathy and myocarditis is crucial to rapidly initiate adequate treatment.
EVALuna2:34413

Lipase elevation and type 1 diabetes mellitus related to immune checkpoint inhibitor therapy – A multicentre study of 90 patients from the German Dermatooncology Group - Grimmelmann, Imke; Momma, Michael; Zimmer, Lisa; Hassel, Jessica C.; Heinzerling, Lucie; Pföhler, Claudia; Loquai, Carmen; Ruini, Cristel; Utikal, Jochen; Thoms, Kai Martin; Kähler, Katharina C.; Eigentler, Thomas; et al. (European Journal of Cancer, 2021)
Aim: Immune checkpoint inhibition (ICI) triggers immune-related adverse events (irAEs). The relevance of lipase elevation remains unclear. Patients and methods: Skin cancer patients with newly detected serum lipase elevation (at least twofold upper normal limit) or newly diagnosed type I diabetes mellitus upon ICI therapy were retrospectively collected at 14 German skin cancer centres. Results: We identified 68 patients with lipase elevation occurring after a median time of 19 (range 1–181) weeks on ICI, 15 (22%) thereof had symptoms consistent with pancreatitis. Forty-seven patients (73%) had other irAE, mainly colitis. Discontinuation (n = 24, 35%) or interruption (n = 26, 38%) of ICI resulted in decrease of lipase after reinduction of ICI lipase levels increased again in 12 of 24 patients. In 18 patients (27%), ICI was continued unchanged, and in 12 (67%) of them, lipase levels normalised. Twenty-two patients were identified with newly diagnosed type I diabetes mellitus related to ICI, and 12 (55%) thereof had also lipase elevation mainly shortly before or after the diagnosis of diabetes. Fourteen (64%) patients had other irAE, mainly thyroiditis. Irrespective of lipase elevation, patients frequently showed a rapid onset with ketoacidosis, decreased c-peptide, and strongly increased blood glucose levels. Conclusion: Increased serum lipase during ICI is often not associated with pancreatitis but with other irAE as possible cause. Therefore, it might be sufficient to regularly monitor blood glucose levels and perform further workup only in case of signs or symptoms of pancreatitis and/or exocrine pancreas insufficiency.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Diabetes; Diabetes mellitus; Immune checkpoint inhibitors; Immune-related adverse events; Ipilimumab; Lipase; Nivolumab; Pancreatitis; PD-1 inhibitor; Pembrolizumab

Liver-directed treatment is associated with improved survival and increased response to immune checkpoint blockade in metastatic uveal melanoma: results from a retrospective multicenter trial - Koch, Elias; Petzold, Anne; Wessely, Anja; Dippel, Edgar; Eckstein, Markus; Gesierich, Anja; Gutzmer, Ralf; Hassel, Jessica C.; Knorr, Harald; Kreuzberg, Nicole; Leiter, Ulrike; Loquai, Carmen; et al. (Frontiers of Medicine, 2023)
Metastases of uveal melanoma (UM) spread predominantly to the liver. Due to low response rates to systemic therapies, liver-directed therapies (LDT) are commonly used for tumor control. The impact of LDT on the response to systemic treatment is unknown. A total of 182 patients with metastatic UM treated with immune checkpoint blockade (ICB) were included in this analysis. Patients were recruited from prospective skin cancer centers and the German national skin cancer registry (ADOReg) of the German Dermatologic Cooperative Oncology Group (DeCOG). Two cohorts were compared: patients with LDT (cohort A, n = 78) versus those without LDT (cohort B, n = 104). Data were analyzed for response to treatment, progression-free survival (PFS), and overall survival (OS). The median OS was significantly longer in cohort A than in cohort B (20.1 vs. 13.8 months; P = 0.0016) and a trend towards improved PFS was observed for cohort A (3.0 vs. 2.5 months; P = 0.054). The objective response rate to any ICB (16.7% vs. 3.8%, P = 0.0073) and combined ICB (14.1% vs. 4.5%, P = 0.017) was more favorable in cohort A. Our data suggest that the combination of LDT with ICB may be associated with a survival benefit and higher treatment response to ICB in patients with metastatic UM.
CRIS-Team Scopus Importer:2023-07-21
Keywords: anti-CTLA-4; anti-PD-1; immune checkpoint blockade; liver-directed therapy; SIRT; uveal melanoma

Loading of Primary Human T Lymphocytes with Citrate-Coated Superparamagnetic Iron Oxide Nanoparticles Does Not Impair Their Activation after Polyclonal Stimulation - Mühlberger, Marina; Unterweger, Harald; Band, Julia; Lehmann, Christian; Heger, Lukas; Dudziak, Diana; Alexiou, Christoph; Lee, Geoffrey; Janko, Christina (Cells, 2020)
For the conversion of immunologically cold tumors, characterized by a low T cell infiltration, into hot tumors, it is necessary to enrich T cells in the tumor area. One possibility is the use of magnetic fields to direct T cells into the tumor. For this purpose, primary T cells that were freshly isolated from human whole blood were loaded with citrate-coated superparamagnetic iron oxide nanoparticles (SPIONCitrate). Cell toxicity and particle uptake were investigated by flow cytometry and atomic emission spectroscopy. The optimum loading of the T cells without any major effect on their viability was achieved with a particle concentration of 75 mu g Fe/mL and a loading period of 24 h. The cellular content of SPIONCitrate was sufficient to attract these T cells with a magnet which was monitored by live-cell imaging. The functionality of the T cells was only slightly influenced by SPIONCitrate, as demonstrated by in vitro stimulation assays. The proliferation rate as well as the expression of co-stimulatory and inhibitory surface molecules (programmed cell death 1 (PD-1), lymphocyte activation gene 3 (LAG-3), T cell immunoglobulin and mucin domain containing 3 (Tim-3), C-C motif chemokine receptor 7 (CCR7), CD25, CD45RO, CD69) was investigated and found to be unchanged. Our results presented here demonstrate the feasibility of loading primary human T lymphocytes with superparamagnetic iron oxide nanoparticles without influencing their viability and functionality while achieving sufficient magnetizability for magnetically controlled targeting. Thus, the results provide a strong fundament for the transfer to tumor models and ultimately for new immunotherapeutic approaches for cancer treatment.
CRIS-Team WoS Importer:2020-04-21

Localized Scleroderma of the Head and Face Area: A Retrospective Cross-sectional Study of 96 Patients from 5 German Tertiary Referral Centres - Kreuter, Alexander; Mitrakos, Georg; Hofmann, Silke C.; Lehmann, Percy; Sticherling, Michael; Krieg, Thomas; Lahner, Nina; Tigges, Christian; Hunzelmann, Nicolas; Moinzadeh, Pia (Acta Dermato-Venereologica, 2018)
EVALuna2:34377

Locally renewing resident synovial macrophages provide a protective barrier for the joint - Culemann, Stephan; Grüneboom, Anika; Nicolás-Ávila, José Ángel; Weidner, Daniela; Lämmle, Katrin Franziska; Rothe, Tobias; Quintana, Juan A.; Kirchner, Philipp; Krljanac, Branislav; Eberhardt, Martin; Ferrazzi, Fulvia; Kretzschmar, Elke; et al. (Nature, 2019)
Macrophages are considered to contribute to chronic inflammatory diseases such as rheumatoid arthritis1. However, both the exact origin and the role of macrophages in inflammatory joint disease remain unclear. Here we use fate-mapping approaches in conjunction with three-dimensional light-sheet fluorescence microscopy and single-cell RNA sequencing to perform a comprehensive spatiotemporal analysis of the composition, origin and differentiation of subsets of macrophages within healthy and inflamed joints, and study the roles of these macrophages during arthritis. We find that dynamic membrane-like structures, consisting of a distinct population of CX3CR1+ tissue-resident macrophages, form an internal immunological barrier at the synovial lining and physically seclude the joint. These barrier-forming macrophages display features that are otherwise typical of epithelial cells, and maintain their numbers through a pool of locally proliferating CX3CR1− mononuclear cells that are embedded into the synovial tissue. Unlike recruited monocyte-derived macrophages, which actively contribute to joint inflammation, these epithelial-like CX3CR1+ lining macrophages restrict the inflammatory reaction by providing a tight-junction-mediated shield for intra-articular structures. Our data reveal an unexpected functional diversification among synovial macrophages and have important implications for the general role of macrophages in health and disease.
CRIS-Team Scopus Importer:2019-08-16

Long-term Effectiveness of Interventions for actinic Keratoses: Results of a systematic Review and Network Meta-Analysis - Steeb, Theresa; Wessely, Anja; Petzold, Anne; Brinker, T.; Schmitz, L.; Lei-Ter-Stoppke, U.; Garbe, C.; Schöffski, Oliver; Berking, Carola; Heppt, Markus (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2021)
CRIS-Team WoS Importer:2021-09-24

Long-term efficacy of interventions for actinic keratosis: protocol for a systematic review and network meta-analysis - Steeb, Theresa; Heppt, Markus; Becker, Lars; Kohl, Christoph; French, Lars E.; Berking, Carola (Systematic Reviews, 2019)
BACKGROUND: Actinic keratoses (AK) are common precancerous lesions of the skin due to cumulative sun exposure. A variety of interventions are available for the treatment; however, the majority of randomised controlled trials (RCTs) and meta-analyses focus on short-term efficacy outcomes. This network meta-analysis aims to investigate the long-term (> 12 months) efficacy of interventions for AK. METHODS: To identify relevant studies, we will perform a systematic literature research in MEDLINE, Embase, and CENTRAL and hand-search pertinent trial registers. Two authors will independently screen titles and abstracts for eligibility. We will include RCTs with an inter-individual (parallel arm) design. The study population includes patients with a clinical or histopathologic diagnosis of AK. Eligibility will be restricted to the following interventions: surgical approaches, cryosurgery, ablative laser treatment, topical drug treatment with 5-fluorouracil, imiquimod, ingenol mebutate, diclofenac, or photodynamic therapy. As outcomes, we will consider the following endpoints: (1) the participant complete clearance rate, (2) the participant partial clearance rate, (3) the lesion-specific clearance, (4) the mean lesion reduction per patient, and (5) the number of withdrawals due to adverse events after at least 12 months after the end of treatment. Monotherapy or placebo will serve as a comparison. Estimates of effects from individual studies will be pooled using a random-effects model. Heterogeneity will be evaluated based on I2 and chi-square test. The risk of bias will be estimated with the Cochrane Risk of Bias Tool by two review authors independently. The quality of evidence of the outcomes will be assessed with the GRADE approach. A network meta-analysis will be performed to combine direct and indirect evidence from the included RCTs. DISCUSSION: The potential of interventions to achieve a sustained clearance of AK has not been assessed to date. To investigate the long-term efficacy of interventions is important as the natural disease course is highly variable and relapses occur frequently even after initial lesion clearance. This review will help to set a framework for clinical decision making in patients with AK. SYSTEMATIC REVIEW REGISTRATION: CRD42018095903 (PROSPERO).
EVALuna2:211408

LONG-TERM HUMORAL RESPONSE TO SARS-COV-2 VACCINATION IN PATIENTS WITH IMMUNE-MEDIATED INFLAMMATORY DISEASE - Tascilar, Koray; Simon, David; Kleyer, Arnd; Fagni, Filippo; Krönke, Gerhard; Meder, Christine; Dietrich, Peter; Orlemann, Till; Kliem, Thorsten; Moessner, J.; Liphardt, Anna-Maria; Schönau, Verena; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

Long-Term Management of Advanced Basal Cell Carcinoma: Current Challenges and Future Perspectives - Heppt, Markus; Gebhardt, Christoffer; Hassel, Jessica C.; Alter, Mareike; Gutzmer, Ralf; Leiter, Ulrike; Berking, Carola (Cancers, 2022)
Simple Summary Local therapies are no longer an option for locally advanced basal cell carcinoma. Abnormal activation of the hedgehog signaling pathway leads to uncontrolled tumor growth. Hedgehog pathway inhibitors are an effective treatment option for this kind of tumor. However, treatment-related toxicity under long-term treatment may lead to limitations in quality of life, and thus to therapy interruption or even discontinuation. This review summarizes pertinent treatment adjustments and novel therapeutic strategies for effective treatment of locally advanced basal cell carcinoma. The first-line therapy for locally advanced basal cell carcinoma (laBCC) is Hedgehog pathway inhibitors (HHIs), as they achieve good efficacy and duration of response. However, toxicity in the course of long-term treatment may lead to a decrease in the quality of life, and consequently to interruption or even discontinuation of therapy. As HHI therapy is a balancing act between effectiveness, adverse events, quality of life, and adherence, numerous successful treatment strategies have evolved, such as dose reduction and dose interruptions with on-off treatment schedules or interruptions with re-challenge after progression. As a small percentage of patients show primary or acquired resistance to HHIs, the inhibition of programmed cell death protein 1 (PD-1) has been approved as a second-line therapy, which may also be accompanied by immune-related toxicities and non-response. Thus, optimization of current treatment schedules, novel agents, and combination strategies are urgently needed for laBCC. Here, we narratively model the treatment sequence for patients with laBCC and summarize the current state of approved treatment regimens and therapeutic strategies to optimize the long-term management of laBCC.
CRIS-Team WoS Importer:2022-10-28

Long-term recurrence rates of actinic keratosis: A systematic review and pooled analysis of randomized controlled trials - Steeb, Theresa; Wessely, Anja; Petzold, Anne; Brinker, Titus J.; Schmitz, Lutz; Schöffski, Oliver; Berking, Carola; Heppt, Markus (Journal of the American Academy of Dermatology, 2021)
CRIS-Team Scopus Importer:2021-06-18

L Particles Transmit Viral Proteins from Herpes Simplex Virus 1-Infected Mature Dendritic Cells to Uninfected Bystander Cells, Inducing CD83 Downmodulation - Heilingloh, Christiane; Kummer, Mirko; Muehl-Zuerbes, Petra; Drassner, Christina; Daniel, Christoph; Klewer, Monika; Steinkasserer, Alexander (Journal of Virology, 2015)
Mature dendritic cells (mDCs) are known as the most potent antigen-presenting cells (APCs) since they are also able to prime/induce naive T cells. Thus, mDCs play a pivotal role during the induction of antiviral immune responses. Remarkably, the cell surface molecule CD83, which was shown to have costimulatory properties, is targeted by herpes simplex virus 1 (HSV-1) for viral immune escape. Infection of mDCs with HSV-1 results in downmodulation of CD83, resulting in reduced T cell stimulation. In this study, we report that not only infected mDCs but also uninfected bystander cells in an infected culture show a significant CD83 reduction. We demonstrate that this effect is independent of phagocytosis and transmissible from infected to uninfected mDCs. The presence of specific viral proteins found in these uninfected bystander cells led to the hypothesis that viral proteins are transferred from infected to uninfected cells via L particles. These L particles are generated during lytic replication in parallel with full virions, called H particles. L particles contain viral proteins but lack the viral capsid and DNA. Therefore, these particles are not infectious but are able to transfer several viral proteins. Incubation of mDCs with L particles indeed reduced CD83 expression on uninfected bystander DCs, providing for the first time evidence that functional viral proteins are transmitted via L particles from infected mDCs to uninfected bystander cells, thereby inducing CD83 downmodulation.HSV-1 has evolved a number of strategies to evade the host's immune system. Among others, HSV-1 infection of mDCs results in an inhibited T cell activation caused by degradation of CD83. Interestingly, CD83 is lost not only from HSV-1-infected mDCs but also from uninfected bystander cells. The release of so-called L particles, which contain several viral proteins but lack capsid and DNA, during infection is a common phenomenon observed among several viruses, such as human cytomegalovirus (HCMV), Epstein-Barr virus, and HSV-1. However, the detailed function of these particles is poorly understood. Here, we provide for the first time evidence that functional viral proteins can be transferred to uninfected bystander mDCs via L particles, revealing important biological functions of these particles during lytic replication. Therefore, the transfer of viral proteins by L particles to modulate uninfected bystander cells may represent an additional strategy for viral immune escape.
EVALuna2:19522

Lungs Ailment - other Comorbidity of the Psoriasis? - Moreira, Alvaro; Sticherling, Michael (2017)
EVALuna2:34355

MAGNETIC RESONANCE IMAGING (MRI) OF HANDS OF PSORIASIS PATIENTS: HIGH INCIDENCE OF INFLAMMATION - Simon, David; Faustini, F.; Englbrechtl, M.; Kleyer, Arnd; Kocijan, R.; Haschka, J.; Kraus, S.; Hueber, Axel; Sticherling, Michael; Schell, G.; Rech, Jürgen (2014)
EVALuna2:12862

Malignant Tumors as important Differential Diagnosis of chronic Ulcers - Toussaint, Frédéric; Erdmann, M.; Berking, Carola; Erfurt-Berge, Cornelia (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2020)
CRIS-Team WoS Importer:2020-09-11

Malignant Tumours Presenting as Chronic Leg or Foot Ulcers - Toussaint, Frédéric; Erdmann, Michael; Berking, Carola; Erfurt-Berge, Cornelia (Journal of Clinical Medicine, 2021)
Our purpose was to collect data on the incidence of malignant skin tumours presenting as chronic leg or foot ulcers in a tertiary centre, and to analyse the frequency and type of initial clinical misdiagnoses in these cases. A retrospective chart review of cases with melanoma or other malignant neoplasms of the skin of the lower extremity treated in a tertiary centre during January 2010 until February 2020 was conducted to identify cases that presented as chronic ulcers. Out of 673 cases, 26 (3.9%) were identified with a total of 27 malignant tumours presenting as chronic ulcers of the lower leg or foot. Therefrom, seven were diagnosed as melanoma, eight as squamous cell carcinoma, and twelve as basal cell carcinoma. The mean interval until diagnosis for all tumour types was 44.4 months (median 24 months). A delay in correct treatment occurred in 12 out of 26 cases (46%) as a result of misdiagnosis with subsequent treatment as chronic leg or foot ulcers of a different etiology. Misdiagnoses were venous ulcer, traumatic wound, mixed arterial and venous ulcer, arterial ulcer, and ulcer of an unknown origin. Malignant ulcers presenting as chronic ulcers are rare, but often lead to misdiagnosis.
CRIS-Team WoS Importer:2021-06-25

Management of cutaneous squamous cell carcinoma Vorgehen bei kutanem Plattenepithelkarzinom - Leiter, U.; Gutzmer, R.; Alter, M.; Ulrich, C.; Meiwes, A.; Heppt, Markus; Steeb, Theresa; Berking, Carola; Lonsdorf, A. S.; Sachse, M.; Hillen, U. (Onkologe, 2021)
Cutaneous squamous cell carcinoma (SCC) is one of the most common cancers of the Caucasian population and accounts for 20% of all skin tumors. An S3 guideline of the German Oncology Guidelines Program has been available since 2019. The diagnosis is based on the clinical examination. Excision and histological confirmation is required for all clinically suspicious lesions to allow prognostic assessment and correct treatment. The therapy of first choice is complete excision with histological control of the surgical margin. In cutaneous SCC with risk factors such as tumor thickness > 6 mm, sentinel lymph node biopsy (SLNB) may be discussed, but there is currently no clear evidence regarding its prognostic and therapeutic relevance. Adjuvant radiotherapy may be considered if there is a high risk of recurrence, radiotherapy should be considered in case of inoperable tumors. For inoperable local or locoregional recurrence, electrochemotherapy can also be indicated. In case of inoperable/or metastasized SCC, the immune checkpoint inhibitor cemiplimab is approved and recommended as the therapy of first choice. In case of contraindications, chemotherapeutics, epidermal growth factor receptor (EGFR) inhibitors or palliative radiotherapy can be used. Since evidence is limited, systemic therapy should preferably be performed in clinical studies. Follow-up should be risk-adapted and includes dermatological examinations supplemented by ultrasound examinations in high-risk patients.
CRIS-Team Scopus Importer:2021-04-30
Keywords: Diagnostic techniques and procedures; Margins of excision; Sentinel lymph node biopsy; Skin and connective tissue diseases; Treatment

Managing toxicities of immunotherapies - a side effect register for rare and severe side effects of checkpoint Inhibitor therapy - Heinzerling, Lucie; Schuler, Gerold (2018)
EVALuna2:34408

Mass Spectrometric Characterization of HSV-1 L-Particles From Human Dendritic Cells and BHK21 Cells and Analysis of Their Functional Role - Birzer, Alexandra; Kraner, Max; Heilingloh, Christiane Silke; Mühl-Zürbes, Petra; Hofmann, Jörg; Steinkasserer, Alexander; Popella, Linda (Frontiers in Microbiology, 2020)
Herpes simplex virus type 1 (HSV-1) is a very common human pathogenic virus among the world’s population. The lytic replication cycle of HSV-1 is, amongst others, characterized by a tripartite viral gene expression cascade, the assembly of nucleocapsids involving their subsequent nuclear egress, tegumentation, re-envelopment and the final release of progeny viral particles. During productive infection of a multitude of different cell types, HSV-1 generates not only infectious heavy (H-) particles, but also non-infectious light (L-) particles, lacking the capsid. In monocyte-derived mature dendritic cells (mDCs), HSV-1 causes a non-productive infection with the predominant release of L-particles. Until now, the generation and function of L-particles is not well understood, however, they are described as factors transferring viral components to the cellular microenvironment. To obtain deeper insights into the L-particle composition, we performed a mass-spectrometry-based analysis of L-particles derived from HSV-1-infected mDCs or BHK21 cells and H-particles from the latter one. In total, we detected 63 viral proteins in both H- and L-particle preparations derived from HSV-1-infected BHK21 cells. In L-particles from HSV-1-infected mDCs we identified 41 viral proteins which are differentially distributed compared to L-particles from BHK21 cells. In this study, we present data suggesting that L-particles modify mDCs and suppress their T cell stimulatory capacity. Due to the plethora of specific viral proteins incorporated into and transmitted by L-particles, it is tempting to speculate that L-particles manipulate non-infected bystander cells for the benefit of the virus.
CRIS-Team Scopus Importer:2020-10-23
Keywords: BHK21 cells; dendritic cells; heavy particles; HSV-1; immunomodulatory effect; light particles; mass spectrometry; T cell stimulation

Mast-Cell-Derived TNF Amplifies CD8(+) Dendritic Cell Functionality and CD8(+) T Cell Priming - Dudeck, Jan; Ghouse, Shanawaz Mohammed; Lehmann, Christian; Hoppe, Anja; Schubert, Nadja; Nedospasov, Sergei A.; Dudziak, Diana; Dudeck, Anne (Cell Reports, 2015)
Mast cells are critical promoters of adaptive immunity in the contact hypersensitivity model, but the mechanism of allergen sensitization is poorly understood. Using Mcpt5-CreTNF(FL/FL) mice, we show here that the absence of TNF exclusively in mast cells impaired the expansion of CD8(+) T cells upon sensitization and the T-cell-driven adaptive immune response to elicitation. T cells primed in the absence of mast cell TNF exhibited a diminished efficiency to transfer sensitization to naive recipients. Specifically, mast cell TNF promotes CD8(+) dendritic cell (DC) maturation and migration to draining lymph nodes. The peripherally released mast cell TNF further critically boosts the CD8(+) T-cell-priming efficiency of CD8(+) DCs, thereby linking mast cell effects on T cells to DC modulation. Collectively, our findings identify the distinct potential of mast cell TNF to amplify CD8(+) DC functionality and CD8(+) T-cell-dominated adaptive immunity, which may be of great importance for immunotherapy and vaccination approaches.
EVALuna2:19558

Mathematical modelling in biomedicine: A primer for the curious and the skeptic - Vera, Julio; Lischer, Christopher; Nenov, Momchil; Nikolov, Svetoslav; Lai, Xin; Eberhardt, Martin (International Journal of Molecular Sciences, 2021)
In most disciplines of natural sciences and engineering, mathematical and computational modelling are mainstay methods which are usefulness beyond doubt. These disciplines would not have reached today’s level of sophistication without an intensive use of mathematical and computational models together with quantitative data. This approach has not been followed in much of molecular biology and biomedicine, however, where qualitative descriptions are accepted as a satisfactory replacement for mathematical rigor and the use of computational models is seen by many as a fringe practice rather than as a powerful scientific method. This position disregards mathematical thinking as having contributed key discoveries in biology for more than a century, e.g., in the connection between genes, inheritance, and evolution or in the mechanisms of enzymatic catalysis. Here, we discuss the role of computational modelling in the arsenal of modern scientific methods in biomedicine. We list frequent misconceptions about mathematical modelling found among biomedical experimentalists and suggest some good practices that can help bridge the cognitive gap between modelers and experimental researchers in biomedicine. This manuscript was written with two readers in mind. Firstly, it is intended for mathematical modelers with a background in physics, mathematics, or engineering who want to jump into biomedicine. We provide them with ideas to motivate the use of mathematical modelling when discussing with experimental partners. Secondly, this is a text for biomedical researchers intrigued with utilizing mathematical modelling to investigate the pathophysiology of human diseases to improve their diagnostics and treatment.
CRIS-Team Scopus Importer:2021-01-22
Keywords: Biomathematics; Computational drug discovery; Computational modelling; Data-driven mathematical modelling; Mathematical oncology; Scientific method; Systems biology

Maturation of monocyte-derived DCs leads to increased cellular stiffness, higher membrane fluidity, and changed lipid composition - Lühr, Jennifer; Alex, Nils; Amon, Lukas; Kraeter, Martin; Kubankova, Marketa; Sezgin, Erdinc; Lehmann, Christian; Heger, Lukas; Heidkamp, Gordon Frederik; Smith, Ana-Suncana; Zaburdaev, Vasily; Böckmann, Rainer; et al. (EUROPEAN JOURNAL OF IMMUNOLOGY, 2021)
CRIS-Team WoS Importer:2022-03-11

Maturation of Monocyte-Derived DCs Leads to Increased Cellular Stiffness, Higher Membrane Fluidity, and Changed Lipid Composition - Luhr, Jennifer J.; Alex, Nils; Amon, Lukas; Krater, Martin; Kubankova, Marketa; Sezgin, Erdinc; Lehmann, Christian; Heger, Lukas; Heidkamp, Gordon Frederik; Smith, Ana-Suncana; Zaburdaev, Vasily; Böckmann, Rainer; et al. (Frontiers in Immunology, 2020)
Dendritic cells (DCs) are professional antigen-presenting cells of the immune system. Upon sensing pathogenic material in their environment, DCs start to mature, which includes cellular processes, such as antigen uptake, processing and presentation, as well as upregulation of costimulatory molecules and cytokine secretion. During maturation, DCs detach from peripheral tissues, migrate to the nearest lymph node, and find their way into the correct position in the net of the lymph node microenvironment to meet and interact with the respective T cells. We hypothesize that the maturation of DCs is well prepared and optimized leading to processes that alter various cellular characteristics from mechanics and metabolism to membrane properties. Here, we investigated the mechanical properties of monocyte-derived dendritic cells (moDCs) using real-time deformability cytometry to measure cytoskeletal changes and found that mature moDCs were stiffer compared to immature moDCs. These cellular changes likely play an important role in the processes of cell migration and T cell activation. As lipids constitute the building blocks of the plasma membrane, which, during maturation, need to adapt to the environment for migration and DC-T cell interaction, we performed an unbiased high-throughput lipidomics screening to identify the lipidome of moDCs. These analyses revealed that the overall lipid composition was significantly changed during moDC maturation, even implying an increase of storage lipids and differences of the relative abundance of membrane lipids upon maturation. Further, metadata analyses demonstrated that lipid changes were associated with the serum low-density lipoprotein (LDL) and cholesterol levels in the blood of the donors. Finally, using lipid packing imaging we found that the membrane of mature moDCs revealed a higher fluidity compared to immature moDCs. This comprehensive and quantitative characterization of maturation associated changes in moDCs sets the stage for improving their use in clinical application.
CRIS-Team Scopus Importer:2020-12-25
Keywords: cell mechanics; cellular stiffness; cholesterol; lipidomics; lipids; low-density lipoprotein; maturation; monocyte-derived dendritic cells

MCS-18, a natural product isolated from Helleborus purpurascens, inhibits maturation of dendritic cells in ApoE-deficient mice and prevents early atherosclerosis progression - Dietel, Barbara; Muench, Rabea; Kühn, Constanze; Kerek, Franz; Steinkasserer, Alexander; Achenbach, Stephan; Garlichs, Christoph; Zinser, Elisabeth (Atherosclerosis, 2014)
Inflammation accelerates both plaque progression and instability in the pathogenesis of atherosclerosis. The inhibition of dendritic cell (DC) maturation is a promising approach to suppress excessive inflammatory immune responses and has been shown to be protective in several autoimmune models. The aim of this study was to investigate the immune modulatory effects of the natural substance MCS-18, an inhibitor of DC maturation, regarding the progression of atherosclerosis in ApoE-deficient mice.ApoE-deficient mice were fed for twelve weeks with a Western-type diet (n = 32) or normal chow (control group; n = 16). Animals receiving high-fat diet were treated with MCS-18 (500 ?g/kg body weight, n = 16) or saline (n = 16) twice a week. After 12 weeks, animals were transcardially perfused and sacrificed. The percentage of mature DCs (CD3(-)/CD19(-)/CD14(-)/NK1.1(-)/CD11c(+)/MHCII(+)/CD83(+)/CD86(+)) and T cell subpopulations (CD4(+)/CD25(+)/Foxp3(+), CD3/CD4/CD8) was analyzed in peripheral blood and in the spleen using flow cytometry. Plaque size was determined in the aortic root and the thoracoabdominal aorta using en-face staining. Immunohistochemical stainings served to detect inflammatory cells in the aortic root. Several cytokines and chemokines were determined in serum using multiplex assays.In splenic cells derived from saline-treated atherosclerotic mice an increased DC maturation, reflected by the upregulation of CD83 and CD86 expression, was observed. The enhanced expression of both maturation markers was absent in MCS-18 treated atherosclerotic mice. While the percentage of splenic Foxp3 expressing Treg was increased in animals receiving MCS-18 compared to saline-treated atherosclerotic mice, cytotoxic T cells were reduced in the spleen and in atherosclerotic lesions of the aortic root. Furthermore, proatherogenic cytokines (e.g. IL-6 and IFN-?) and chemokines (e.g. MIP-1?) were decreased in serum of MCS-18-treated animals when compared to saline-treated atherosclerotic mice. Also plaque size in the aortic root and the thoracoabdominal aorta was significantly lower following administration of MCS-18.This study provides for the first time evidence that MCS-18 is able to prevent the onset of atherosclerosis in ApoE-deficient mice. The observed anti-atherogenic effect is associated with the suppression of DC maturation and an inhibited migration and proliferation of cytotoxic T cells.
EVALuna2:11981

Mechanical Regulation of Epithelial Tissue Homeostasis - Kaliman, Sara; Hubert, Maxime; Wollnik, Carina; Nuic, Lovro; Vurnek, Damir; Gehrer, Simone; Lovrić, Jakov; Dudziak, Diana; Rehfeldt, Florian; Smith, Ana-Suncana (Physical Review X, 2021)
Despite recent efforts to understand homeostasis in epithelial tissues, there are many unknowns surrounding this steady state. It is considered to be regulated by mechanoresponse, but unlike for single cells, this idea remains heavily debated for tissues. Here, we show that changes in matrix stiffness induce a nonequilibrium transition from tubular to squamous Madin-Darby Canine Kidney II tissues. Nonetheless, despite different cell morphologies and densities, all homeostatic tissues display equivalent topologies, which, hence, must be actively targeted and regulated. On the contrary, the mechanoresponse induces dramatic changes in the large-scale organization of the colonies. On stiff gels, this yields an unreported cooperative state of motile cells displaying higher densities than in the arrested homeostatic state, which suggests a more complex relation between cell density and motility than previously anticipated. Our results unequivocally relate the mechanosensitive properties of individual cells to the evolving macroscopic structures, an effect that could be important for understanding the emergent pathologies of living tissues.
CRIS-Team WoS Importer:2021-08-20

Meeting Report: 47th Annual Meeting of the “Arbeitsgemeinschaft Dermatologische Forschung” - Stary, Georg; Fabri, Mario; Gebhardt, Christoffer; Eming, Rüdiger; Matthias, Julia; Vorobyev, Artem; Effern, Maike; Strobl, Johanna; Günther, Claudia; Zielinski, Christina; Dudziak, Diana; Géraud, Cyril; et al. (Experimental Dermatology, 2022)
CRIS-Team Scopus Importer:2022-03-18

Meeting Report of the Pathogenesis of Pemphigus and Pemphigoid Meeting in Munich, September 2016 - Schmidt, Enno; Spindler, Volker; Eming, Ruediger; Amagai, Masayuki; Antonicelli, Frank; Baines, John F.; Belheouane, Meriem; Bernard, Philippe; Borradori, Luca; Caproni, Marzia; Di Zenzo, Giovanni; Grando, Sergei; et al. (Journal of Investigative Dermatology, 2017)
Autoimmune blistering diseases are a heterogeneous group of about a dozen complex disorders that are characterized by intraepidermal (pemphigus) and subepidermal blistering (pemphigoid diseases and dermatitis herpetiformis). The Pathogenesis of Pemphigus and Pemphigoid Meeting, organized by the Departments of Dermatology in Lübeck and Marburg and the Institute of Anatomy and Cell Biology, Munich, was held in September 2016 in Munich. The meeting brought together basic scientists and clinicians from all continents dedicating their work to autoimmune blistering diseases. Considerable advances have been made in describing incidences and prevalences of these diseases and linking comorbidities with autoantibody reactivities and clinical variants, for example, dipeptidyl peptidase-IV inhibitor-associated noninflammatory bullous pemphigoid. Although new entities are still being described, diagnosis of most autoimmune blistering diseases can now be achieved using standardized and widely available serological test systems. Various experimental mouse models of pemphigus and pemphigoid disease are increasingly being used to understand mechanisms of central and peripheral tolerance and to evaluate more specific treatment approaches for these disorders, such as molecules that target autoreactive T and B cells and anti-inflammatory mediators, that is, dimethyl fumarate, phosphodiesterase 4, and leukotriene B4 inhibitors in pemphigoid disorders, and chimeric antigen receptor T cells in pemphigus. Very recent experimental data about the immunopathology and the determinants of autoantibody formation and keratinocyte susceptibility in pemphigus were discussed. With regard to cellular mechanisms leading to the loss of cell-cell adhesion, new ideas were shared in the field of signal transduction. Major steps were taken to put the various partly contradictory and controversial findings about the effects of pemphigus autoantibodies and other inflammatory mediators into perspective and broaden our view of the complex pathophysiology of this disease. Finally, two investigator-initiated multicenter trials highlighted doxycycline and dapsone as valuable medications in the treatment of bullous pemphigoid.
EVALuna2:34348

MEK inhibition may increase survival of NRAS-mutated melanoma patients treated with checkpoint blockade: Results of a retrospective multicentre analysis of 364 patients - Kirchberger, Michael Constantin; Ugurel, Selma; Mangana, Johanna; Heppt, Markus Valentin; Eigentler, Thomas Kurt; Berking, Carola; Schadendorf, Dirk; Schuler, Gerold; Dummer, Reinhard; Heinzerling, Lucie (European Journal of Cancer, 2018)
BACKGROUND: Melanoma harbours genetic alterations in genes such as BRAF, NRAS and KIT. Activating NRAS mutations are present in about 20% of melanomas. Even though BRAF mutations can be effectively targeted with specific inhibitors, this approach has proven more challenging in cases of NRAS mutations. Previous reports suggested that immunotherapy might be more successful in NRAS-mutated compared to BRAF-mutated or BRAF/NRAS wildtype melanoma. PATIENTS AND METHODS: In this study, overall survival and response to anti-PD-1 (nivolumab, pembrolizumab) and anti-CTLA-4 (ipilimumab) therapy of 364 patients with metastatic melanoma were assessed comparing 236 NRAS-mutated patients with 128 NRAS wildtype patients. Subtyping of NRAS mutation in 211 cases revealed 12 different genotypes of which Q61 mutations were predominant (95%). RESULTS: Patients with NRAS mutant melanoma showed similar response rates to checkpoint inhibitor therapy compared to NRAS wildtype patients with 15% versus 13% for ipilimumab (P = 0.731), 21% versus 13% for anti-PD-1 monotherapy (P = 0.210) and 40% versus 39% for ipilimumab and anti-PD-1 therapy in combination or sequence (P = 0.859). Nevertheless, median overall survival of patients with NRAS mutant melanoma was significantly lower with 21 months compared to 33 months in NRAS wildtype melanoma patients (P = 0.034). Therapy with oral MEK inhibitors before or after checkpoint inhibitor therapy showed a trend toward a survival benefit in patients with NRAS mutant melanoma. CONCLUSIONS: Immune checkpoint inhibition shows comparable response rates in NRAS-mutated and NRAS wildtype melanoma even though survival is less favourable in case of NRAS mutation. Additional MEK inhibition might improve clinical benefit.
EVALuna2:34376

Melanocytes as an emerging key player in niche regulation of limbal stem cells - Schlötzer-Schrehardt, Ursula; Polisetti, Naresh; Zenkel, Matthias; Naschberger, Elisabeth; Heger, Lukas; Dudziak, Diana; Stürzl, Michael; Kruse, Friedrich (2018)
EVALuna2:34738

Melanocytes as emerging key players in niche regulation of limbal epithelial stem cells - Polisetti, Naresh; Gießl, Andreas; Zenkel, Matthias; Heger, Lukas; Dudziak, Diana; Naschberger, Elisabeth; Stich, Lena; Steinkasserer, Alexander; Kruse, Friedrich; Schlötzer-Schrehardt, Ursula (Ocular Surface, 2021)
Purpose: Limbal melanocytes (LMel) represent essential components of the corneal epithelial stem cell niche and are known to protect limbal epithelial stem/progenitor cells (LEPCs) from UV damage by transfer of melanosomes. Here, we explored additional functional roles for LMel in niche homeostasis, immune regulation and angiostasis. Methods: Human corneoscleral tissues were morphologically analyzed in normal, inflammatory and wound healing conditions. The effects of LMel on LEPCs were analyzed in direct and indirect co-culture models using electron microscopy, immunocytochemistry, qRT-PCR, Western blotting and functional assays; limbal mesenchymal stromal cells and murine embryonic 3T3 fibroblasts served as controls. The immunophenotype of LMel was assessed by flow cytometry before and after interferon-γ stimulation, and their immunomodulatory properties were analyzed by mixed lymphocytes reaction, monocyte adhesion assays and cytometric bead arrays. Their angiostatic effects on human umbilical cord endothelial cells (HUVECs) were evaluated by proliferation, migration, and tube formation assays. Results: LMel and LEPCs formed structural units in the human limbal stem cell niche in situ, which could be functionally replicated, including melanosome transfer, by co-cultivation in vitro. LMel supported LEPCs during clonal expansion and during epithelial wound healing by stimulating proliferation and migration, and suppressed their differentiation through direct contact and paracrine effects. Under inflammatory conditions, LMel were increased in numbers and upregulated expression of ICAM-1 and MHC II molecules (HLA-DR), but lacked expression of HLA-G, -DP, -DQ and costimulatory molecules CD80 and CD86. They were also found to be potent suppressors of alloreactive T- cell proliferation and cytokine secretion, which largely depended on direct cell-cell interaction. Moreover, the LMel secretome exerted angiostatic activity by inhibiting vascular endothelial cell proliferation and capillary network formation. Conclusion: These findings suggest that LMel are not only professional melanin-producing cells, but exert various non-canonical functions in limbal niche homeostasis by regulating LEPC maintenance, immune responses, and angiostasis. Their potent regulatory, immunomodulatory and anti-angiogenic properties may have important implications for future regenerative cell therapies.
CRIS-Team Scopus Importer:2021-09-03
Keywords: Angiostasis; Immune regulation; Inflammation; Limbal niche; Limbal stem cells; Melanocytes; Wound healing

Melanoma 2.0. Skin cancer as a paradigm for emerging diagnostic technologies, computational modelling and artificial intelligence - Vera, Julio; Lai, Xin; Baur, Andreas; Erdmann, Michael; Gupta, Shailendra; Gutta, Cristiano; Heinzerling, Lucie; Heppt, Markus; Kazmierczak, Philipp Maximilian; Kunz, Manfred; Lischer, Christopher; Putzer, Brigitte M.; et al. (Briefings in Bioinformatics, 2022)
We live in an unprecedented time in oncology. We have accumulated samples and cases in cohorts larger and more complex than ever before. New technologies are available for quantifying solid or liquid samples at the molecular level. At the same time, we are now equipped with the computational power necessary to handle this enormous amount of quantitative data. Computational models are widely used helping us to substantiate and interpret data. Under the label of systems and precision medicine, we are putting all these developments together to improve and personalize the therapy of cancer. In this review, we use melanoma as a paradigm to present the successful application of these technologies but also to discuss possible future developments in patient care linked to them. Melanoma is a paradigmatic case for disruptive improvements in therapies, with a considerable number of metastatic melanoma patients benefiting from novel therapies. Nevertheless, a large proportion of patients does not respond to therapy or suffers from adverse events. Melanoma is an ideal case study to deploy advanced technologies not only due to the medical need but also to some intrinsic features of melanoma as a disease and the skin as an organ. From the perspective of data acquisition, the skin is the ideal organ due to its accessibility and suitability for many kinds of advanced imaging techniques. We put special emphasis on the necessity of computational strategies to integrate multiple sources of quantitative data describing the tumour at different scales and levels.
CRIS-Team WoS Importer:2022-11-04

Melanoma in Pregnancy: CLAUDIUS - a retrospective, multicenter Study to evaluate the Risk of transplacental Transmission to the unborn Child - Gaiser, M. R.; Mueller, V.; Erdmann, Michael; Buehler, B.; Dugas-Breit, S.; Schatton, K.; Reinhardt, L.; Mengoni, M.; Mickler, M.; Pfoehler, C.; Weishaupt, C.; Herbst, R.; et al. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2021)
CRIS-Team WoS Importer:2021-09-24

Melanoma Segmentation and Classification Employing Imaging and Graph Encodings - Rivera Monroy, Luis; Eberhardt, Martin; Ostalecki, Christian; Baur, Andreas; Vera, Julio; Maier, Andreas (Proceedings - 2022 IEEE/ACM International Conference on Connected Health: Applications, Systems and Engineering Technologies, CHASE 2022, 2022)
Histopathology imaging is crucial for the diagnosis and the decision on treating associated tissue diseases. For this reason, Computer-assisted approaches have gained popularity and shown promise in tasks such as segmentation and classification. However, collecting a significant amount of data and high-quality annotations remains a challenge. This work describes a pipeline for toponomy profiling on the population of cells that combines melanoma multidimensional fluorescent imaging, a supervised segmentation of the region of interest, and graph unsupervised embedded representation.The Multi-Epitope-Ligand Cartography (MELC) provides a range of data shown to be optimal for solving supervised and unsuper-vised tasks. This imaging technique and the methodology, such as the one presented here, are promising for further improvement in the study of diagnostic techniques and therapies for skin diseases, such as melanoma.
CRIS-Team Scopus Importer:2023-03-07
Keywords: melanoma; microscopy; neural networks; segmentation

Merkel Cell Carcinoma of the Head and Neck Compared to Other Anatomical Sites in a Real-World Setting: Importance of Surgical Therapy for Facial Tumors - Kirchberger, Michael; Heppt, Markus V.; Schuler, Gerold; Berking, Carola; Heinzerling, Lucie (Facial Plastic Surgery, 2019)
Merkel cell carcinoma (MCC) is a rare and aggressive neuroendocrine skin tumor with a high propensity for nodal involvement, local recurrence, and distant metastases. Up to 50% of MCC arises on head and neck (HN), which may impede oncological treatment due to insufficiently wide excisions and a lower rate of sentinel lymph node detection due to more complicated lymph drainage. Several studies have compared the clinical outcome of HN-MCC with those of non-head and neck (NHN) MCC yielding inconsistent results. This single-center, retrospective analysis compared the clinical outcome of 26 HN-MCC patients with 30 NHN-MCC patients. Overall survival (OS) and disease-free survival (DFS) were calculated with the Kaplan-Meier method assuming proportional hazards. The mean resection margins were 1.6 and 2.0 cm for the HN and NHN cohort, respectively. Local relapses were more frequently observed in patients with HN-MCC (19 vs. 10%). Patients with HN-MCC had a median OS of 4.3 years compared with 7.5 years in patients with NHN-MCC (p = 0.277). The median OS by tumor stage was 11, 3, 2, and 3 years in stage I, II, III, and IV disease, respectively (p = 0.009). The median DFS in HN-MCC was 10 years and not reached in the cohort with NHN-MCC patients (p = 0.939). Our data suggest a trend toward poorer outcomes of HN-MCC compared with NHN-MCC. Patients with MCC on the head and neck carry a higher risk for local relapse, requiring resolute surgical treatment also in facial localizations at early stages.
EVALuna2:212830

Microglial expression of CD83 governs cellular activation and restrains neuroinflammation in experimental autoimmune encephalomyelitis - Sinner, Pia; Peckert-Maier, Katrin; Mohammadian, Hashem; Kuhnt, Christine; Draßner, Christina; Panagiotakopoulou, Vasiliki; Rauber, Simon; Linnerbauer, Mathias; Haimon, Zhana; Royzman, Dmytro; Kronenberg-Versteeg, Deborah; Ramming, Andreas; et al. (Nature Communications, 2023)
Microglial activation during neuroinflammation is crucial for coordinating the immune response against neuronal tissue, and the initial response of microglia determines the severity of neuro-inflammatory diseases. The CD83 molecule has been recently shown to modulate the activation status of dendritic cells and macrophages. Although the expression of CD83 is associated with early microglia activation in various disease settings, its functional relevance for microglial biology has been elusive. Here, we describe a thorough assessment of CD83 regulation in microglia and show that CD83 expression in murine microglia is not only associated with cellular activation but also with pro-resolving functions. Using single-cell RNA-sequencing, we reveal that conditional deletion of CD83 results in an over-activated state during neuroinflammation in the experimental autoimmune encephalomyelitis model. Subsequently, CD83-deficient microglia recruit more pathogenic immune cells to the central nervous system, deteriorating resolving mechanisms and exacerbating the disease. Thus, CD83 in murine microglia orchestrates cellular activation and, consequently, also the resolution of neuroinflammation.
CRIS-Team Scopus Importer:2023-08-11

Mild hyperthermia enhances human monocyte-derived dendritic cell functions and offers potential for applications in vaccination strategies - Knippertz, Ilka; Stein, Marcello F.; Dörrie, Jan; Schaft, Niels; Mueller, Ina; Deinzer, Anja; Steinkasserer, Alexander; Nettelbeck, Dirk. M. (International Journal of Hyperthermia, 2011)
Dendritic cell (DC)-based immunotherapy has been shown to be a promising strategy for anti-cancer therapy. Nevertheless, only a low overall clinical response rate has been observed in vaccinated patients with advanced cancer and therefore methods to improve DC immuno-stimulatory functions are currently under intense investigation. In this respect, we exposed human monocyte-derived DCs to a physiological temperature stress of 40°C for up to 24 h followed by analysis for (i) expression of different heat shock proteins, (ii) survival, (iii) cell surface maturation markers, (iv) cytokine secretion, and (v) migratory capacity. Furthermore, we examined the ability of heat-shocked DCs to prime nave CD8 + T cells after loading with MelanA peptide, by transfection with MelanA RNA, or by transduction with MelanA by an adenovirus vector. The results clearly indicate that in comparison to control DCs, which remained at 37°C, heat-treated cells revealed no differences concerning the survival rate or their migratory capacity. However, DCs exposed to thermal stress showed a time-dependent enhanced expression of the immune-chaperone heat shock protein 70A and both an up-regulation of co-stimulatory molecules such as CD80, CD83, and CD86 and of the inflammatory cytokine TNF-α. Moreover, these cells had a markedly improved capacity to prime autologous nave CD8 + T cells in vitro in an antigen-specific manner, independent of the method of antigen-loading. Thus, our strategy of heat treatment of DCs offers a promising means to improve DC functions during immune activation which, as a physical method, facilitates straight-forward applications in clinical DC vaccination protocols. © 2011 Informa UK Ltd All rights reserved: reproduction in whole or part not permitted.
CRIS-Team Scopus Importer:2021-10-01
Keywords: Cytotoxic T lymphocytes; Dendritic cells; Hsp70; Hyperthermia; Immunotherapy

MiR-205-5p and miR-342-3p cooperate in the repression of the E2F1 transcription factor in the context of anticancer chemotherapy resistance - Lai, Xin; Gupta, Shailendra K.; Schmitz, Ulf; Marquardt, Stephan; Knoll, Susanne; Spitschak, Alf; Wolkenhauer, Olaf; Puetzer, Brigitte M.; Vera, Julio (Theranostics, 2018)
High rates of lethal outcome in tumour metastasis are associated with the acquisition of invasiveness and chemoresistance. Several clinical studies indicate that E2F1 overexpression across high-grade tumours culminates in unfavourable prognosis and chemoresistance in patients. Thus, fine-tuning the expression of E2F1 could be a promising approach for treating patients showing chemoresistance. Methods: We integrated bioinformatics, structural and kinetic modelling, and experiments to study cooperative regulation of E2F1 by microRNA (miRNA) pairs in the context of anticancer chemotherapy resistance. Results: We showed that an enhanced E2F1 repression efficiency can be achieved in chemoresistant tumour cells through two cooperating miRNAs. Sequence and structural information were used to identify potential miRNA pairs that can form tertiary structures with E2F1 mRNA. We then employed molecular dynamics simulations to show that among the identified triplexes, miR-205-5p and miR-342-3p can form the most stable triplex with E2F1 mRNA. A mathematical model simulating the E2F1 regulation by the cooperative miRNAs predicted enhanced E2F1 repression, a feature that was verified by in vitro experiments. Finally, we integrated this cooperative miRNA regulation into a more comprehensive network to account for E2F1-related chemoresistance in tumour cells. The network model simulations and experimental data indicate the ability of enhanced expression of both miR-205-5p and miR-342-3p to decrease tumour chemoresistance by cooperatively repressing E2F1. Conclusions: Our results suggest that pairs of cooperating miRNAs could be used as potential RNA therapeutics to reduce E2F1-related chemoresistance.
EVALuna2:34806
Keywords: Molecular dynamics simulation; Kinetic modelling; MicroRNA; Chemotherapy resistance; E2F1

miR-638 promotes melanoma metastasis and protects melanoma cells from apoptosis and autophagy - Bhattacharya, Animesh; Schmitz, Ulf; Raatz, Yvonne; Schoenherr, Madeleine; Kottek, Tina; Schauer, Marianne; Franz, Sandra; Saalbach, Anja; Anderegg, Ulf; Wolkenhauer, Olaf; Schadendorf, Dirk; Simon, Jan C.; et al. (Oncotarget, 2015)
The present study identified miR-638 as one of the most significantly overexpressed miRNAs in metastatic lesions of melanomas compared with primary melanomas. miR-638 enhanced the tumorigenic properties of melanoma cells in vitro and lung colonization in vivo. mRNA expression profiling identified new candidate genes including TP53INP2 as miR-638 targets, the majority of which are involved in p53 signalling. Overexpression of TP53INP2 severely attenuated proliferative and invasive capacity of melanoma cells which was reversed by miR-638. Depletion of miR-638 stimulated expression of p53 and p53 downstream target genes and induced apoptosis and autophagy. miR-638 promoter analysis identified the miR-638 target transcription factor associated protein 2? (TFAP2A/AP-2?) as a direct negative regulator of miR-638, suggestive for a double-negative regulatory feedback loop. Taken together, miR-638 supports melanoma progression and suppresses p53-mediated apoptosis pathways, autophagy and expression of the transcriptional repressor TFAP2A/AP-2?.
EVALuna2:19520

Model-based genotype-phenotype mapping used to investigate gene signatures of immune sensitivity and resistance in melanoma micrometastasis - Santos Rosales, Guido; Nikolov, Svetoslav; Lai, Xin; Eberhardt, Martin; Dreyer, Florian; Paul, Sushmita; Schuler, Gerold; Vera, Julio (Scientific Reports, 2016)
In this paper, we combine kinetic modelling and patient gene expression data analysis to elucidate biological mechanisms by which melanoma becomes resistant to the immune system and to immunotherapy. To this end, we systematically perturbed the parameters in a kinetic model and performed a mathematical analysis of their impact, thereby obtaining signatures associated with the emergence of phenotypes of melanoma immune sensitivity and resistance. Our phenotypic signatures were compared with published clinical data on pretreatment tumor gene expression in patients subjected to immunotherapy against metastatic melanoma. To this end, the differentially expressed genes were annotated with standard gene ontology terms and aggregated into metagenes. Our method sheds light on putative mechanisms by which melanoma may develop immunoresistance. Precisely, our results and the clinical data point to the existence of a signature of intermediate expression levels for genes related to antigen presentation that constitutes an intriguing resistance mechanism, whereby micrometastases are able to minimize the combined anti-tumor activity of complementary responses mediated by cytotoxic T cells and natural killer cells, respectively. Finally, we computationally explored the efficacy of cytokines used as low-dose co-adjuvants for the therapeutic anticancer vaccine to overcome tumor immunoresistance.
EVALuna2:19575

Model-Based Phenotypic Signatures Governing the Dynamics of the Stem and Semi-differentiated Cell Populations in Dysplastic Colonic Crypts - Nikolov, Svetoslav; Santos Rosales, Guido; Wolkenhauer, Olaf; Vera, Julio (Bulletin of Mathematical Biology, 2018)
Mathematical modeling of cell differentiated in colonic crypts can contribute to a better understanding of basic mechanisms underlying colonic tissue organization, but also its deregulation during carcinogenesis and tumor progression. Here, we combined bifurcation analysis to assess the effect that time delay has in the complex interplay of stem cells and semi-differentiated cells at the niche of colonic crypts, and systematic model perturbation and simulation to find model-based phenotypes linked to cancer progression. The models suggest that stem cell and semi-differentiated cell population dynamics in colonic crypts can display chaotic behavior. In addition, we found that clinical profiling of colorectal cancer correlates with the in silico phenotypes proposed by the mathematical model. Further, potential therapeutic targets for chemotherapy resistant phenotypes are proposed, which in any case will require experimental validation.
EVALuna2:34801

Modelling of protein kinase signaling pathways in melanoma and other cancers - Kunz, Manfred; Vera, Julio (Cancers, 2019)
Melanoma is a highly aggressive tumor with a strong dependence on intracellular signaling pathways. Almost half of all melanomas are driven by mutations in the v-Raf murine sarcoma viral oncogene homolog B (BRAF) with BRAFV600E being the most prevalent mutation. Recently developed targeted treatment directed against mutant BRAF and downstream mitogen-activated protein kinase (MAPK) MAP2K1 (also termed MEK1) have improved overall survival of melanoma patients. However, the MAPK signaling pathway is far more complex than a single chain of consecutively activated MAPK enzymes and it contains nested-, inherent feedback mechanisms, crosstalk with other signaling pathways, epigenetic regulatory mechanisms, and interacting small non-coding RNAs. A more complete understanding of this pathway is needed to better understand melanoma development and mechanisms of treatment resistance. Network reconstruction, analysis, and modelling under the systems biology paradigm have been used recently in different malignant tumors including melanoma to analyze and integrate ‘omics’ data, formulate mechanistic hypotheses on tumorigenesis, assess and personalize anticancer therapy, and propose new drug targets. Here we review the current knowledge of network modelling approaches in cancer with a special emphasis on melanoma.
CRIS-Team Scopus Importer:2019-05-03
Keywords: BRAF oncogene; Checkpoint inhibitors; Feedback regulation; Mitogen-activated protein kinase signaling; Systems biology; Targeted cancer therapy

Model soups improve performance of dermoscopic skin cancer classifiers - Maron, Roman C.; Hekler, Achim; Haggenmüller, Sarah; von Kalle, Christof; Utikal, Jochen S.; Müller, Verena; Gaiser, Maria; Meier, Friedegund; Hobelsberger, Sarah; Gellrich, Frank F.; Sergon, Mildred; Hauschild, Axel; et al. (European Journal of Cancer, 2022)
Background: Image-based cancer classifiers suffer from a variety of problems which negatively affect their performance. For example, variation in image brightness or different cameras can already suffice to diminish performance. Ensemble solutions, where multiple model predictions are combined into one, can improve these problems. However, ensembles are computationally intensive and less transparent to practitioners than single model solutions. Constructing model soups, by averaging the weights of multiple models into a single model, could circumvent these limitations while still improving performance. Objective: To investigate the performance of model soups for a dermoscopic melanoma-nevus skin cancer classification task with respect to (1) generalisation to images from other clinics, (2) robustness against small image changes and (3) calibration such that the confidences correspond closely to the actual predictive uncertainties. Methods: We construct model soups by fine-tuning pre-trained models on seven different image resolutions and subsequently averaging their weights. Performance is evaluated on a multi-source dataset including holdout and external components. Results: We find that model soups improve generalisation and calibration on the external component while maintaining performance on the holdout component. For robustness, we observe performance improvements for pertubated test images, while the performance on corrupted test images remains on par. Conclusions: Overall, souping for skin cancer classifiers has a positive effect on generalisation, robustness and calibration. It is easy for practitioners to implement and by combining multiple models into a single model, complexity is reduced. This could be an important factor in achieving clinical applicability, as less complexity generally means more transparency.
CRIS-Team Scopus Importer:2022-09-09
Keywords: Artificial intelligence; Calibration; Deep learning; Dermatology; Ensembles; Generalisation; Melanoma; Model soups; Nevus; Robustness

Modulation of urelumab glycosylation separates immune stimulatory activity from organ toxicity - Reitinger, Carmen; Ipsen Escobedo, Andrea; Hornung, Chiara; Heger, Lukas; Dudziak, Diana; Lux, Anja; Nimmerjahn, Falk (Frontiers in Immunology, 2022)
Checkpoint control and immunomodulatory antibodies have become important tools for modulating tumor or self-reactive immune responses. A major issue preventing to make full use of the potential of these immunomodulatory antibodies are the severe side-effects, ranging from systemic cytokine release syndrome to organ-specific toxicities. The IgG Fc-portion has been demonstrated to contribute to both, the desired as well as the undesired antibody activities of checkpoint control and immunomodulatory antibodies via binding to cellular Fcγ-receptors (FcγR). Thus, choosing IgG subclasses, such as human IgG4, with a low ability to interact with FcγRs has been identified as a potential strategy to limit FcγR or complement pathway dependent side-effects. However, even immunomodulatory antibodies on the human IgG4 background may interact with cellular FcγRs and show dose limiting toxicities. By using a humanized mouse model allowing to study the immunomodulatory activity of human checkpoint control antibodies in vivo, we demonstrate that deglycosylation of the CD137-specific IgG4 antibody urelumab results in an amelioration of liver toxicity, while maintaining T cell stimulatory activity. In addition, our results emphasize that antibody dosing impacts the separation of side-effects of urelumab from its therapeutic activity via IgG deglycosylation. Thus, glycoengineering of human IgG4 antibodies may be a possible approach to limit collateral damage by immunomodulatory antibodies and allow for a greater therapeutic window of opportunity.
CRIS-Team Scopus Importer:2022-10-28
Keywords: CD137; Fc-receptors; glycosylation; therapeutic antibody; urelumab

Monitoring skin metastases during immuno- and targeted therapy using total-body 3D photography - Erdmann, M.; Heinzerling, Lucie; Schuler, Gerold; Berking, Carola; Schliep, S. (Journal of the European Academy of Dermatology and Venereology, 2020)
CRIS-Team Scopus Importer:2020-08-14

Monocyte-Derived signals activate human natural Killer cells in response to Leishmania Parasites - Messlinger, Helena; Sebald, Heidi; Heger, Lukas; Dudziak, Diana; Bogdan, Christian; Schleicher, Ulrike (Frontiers in Immunology, 2018)
Activated natural killer (NK) cells release interferon (IFN)-gamma, which is crucial for the control of intracellular pathogens such as Leishmania. In contrast to experimental murine leishmaniasis, the human NK cell response to Leishmania is still poorly characterized. Here, we investigated the interaction of human blood NK cells with promastigotes of different Leishmania species (Leishmania major, Leishmania mexicana, Leishmania infantum, and Leishmania donovani). When peripheral blood mononuclear cells or purified NK cells and monocytes (all derived from healthy blood donors from Germany without a history of leishmaniasis) were exposed to promastigotes, NK cells showed increased surface expression of the activation marker CD69. The extent of this effect varied depending on the Leishmania species; differences between dermotropic and viscerotropic L. infantum strains were not observed. Upregulation of CD69 required direct contact between monocytes and Leishmania and was partly inhibitable by anti-interleukin (IL)-18. Unexpectedly, IL-18 was undetectable in most of the supernatants (SNs) of monocyte/parasite cocultures. Confocal fluorescence microscopy of non-permeabilized cells revealed that Leishmania-infected monocytes trans-presented IL-18 to NK cells. Native, but not heat-treated SNs of monocyte/Leishmania cocultures also induced CD69 on NK cells, indicating the involvement of a soluble heat-labile factor other than IL-18. A role for the NK cell-activating cytokines IL-1 beta, IL-2, IL-12, IL-15, IL-21, and IFN-alpha/beta was excluded. The increase of CD69 was not paralleled by NK cell IFN-gamma production or enhanced cytotoxicity. However, prior exposure of NK cells to Leishmania parasites synergistically increased their IFN-gamma release in response to IL-12, which was dependent on endogenous IL-18. CD1c(+) dendritic cells were identified as possible source of Leishmania-induced IL-12. Finally, we observed that direct contact between Leishmania and NK cells reduced the expression of CD56 mRNA and protein on NK cells. We conclude that Leishmania activate NK cells via trans-presentation of IL-18 by monocytes and by a monocyte-derived soluble factor. IL-12 is needed to elicit the IFN-gamma-response of NK cells, which is likely to be an important component of the innate control of the parasite.
EVALuna2:33305

Monocytes Elicit a Neutrophil-Independent Th1/Th17 Response Upon Immunization With a Mincle-Dependent Glycolipid Adjuvant - Desel, Christiane; Murray, Peter J.; Lehmann, Christian; Heger, Lukas; Christensen, Dennis; Andersen, Peter; Mack, Matthias; Dudziak, Diana; Lang, Roland (Frontiers in Immunology, 2022)
Successful subunit vaccination with recombinant proteins requires adjuvants. The glycolipid trehalose-dibehenate (TDB), a synthetic analog of the mycobacterial cord factor, potently induces Th1 and Th17 immune responses and is a candidate adjuvant for human immunization. TDB binds to the C-type lectin receptor Mincle and triggers Syk-Card9-dependent APC activation. In addition, interleukin (IL)-1 receptor/MyD88-dependent signaling is required for TDB adjuvanticity. The role of different innate immune cell types in adjuvant-stimulated Th1/Th17 responses is not well characterized. We investigated cell recruitment to the site of injection (SOI) and to the draining lymph nodes (dLNs) after immunization with the TDB containing adjuvant CAF01 in a protein-based vaccine. Recruitment of monocytes and neutrophils to the SOI and the dramatic increase in lymph node cellularity was partially dependent on both Mincle and MyD88. Despite their large numbers at the SOI, neutrophils were dispensable for the induction of Th1/Th17 responses. In contrast, CCR2-dependent monocyte recruitment was essential for the induction of Th1/Th17 cells. Transport of adjuvant to the dLN did not require Mincle, MyD88, or CCR2. Together, adjuvanticity conferred by monocytes can be separated at the cellular level from potential tissue damage by neutrophils.
CRIS-Team WoS Importer:2022-06-03

Monocyte Subsets Responsible for Immunoglobulin G-Dependent Effector Functions In Vivo - Biburger, Markus; Aschermann, Susanne; Schwab, Inessa; Lux, Anja; Albert, Heike; Danzer, Heike; Woigk, Melissa; Dudziak, Diana; Nimmerjahn, Falk (Immunity, 2011)
Immunoglobulin G (IgG) antibodies confer protection against pathogenic microorganisms, serve as therapeutics in tumor therapy, and are involved in destruction of healthy tissues during autoimmune diseases. Understanding the molecular pathways and effector cell types involved in antibody-mediated effector functions is a prerequisite to modulate these activities. In this study we used two independent model systems to identify innate immune effector cells required for IgG activity in vivo. We first defined the precise repertoire of receptors for the IgG Fc fragment (FcγR) on innate immune effector cells in the blood and on tissue-resident macrophage populations. Despite expression of relevant activating FcγRs on various phagocyte populations, our data indicate that the majority of these cell types are dispensable for IgG activity in vivo. In contrast, IgG-dependent effector functions were selectively impaired in animals lacking the CX CR1 Ly6C CD11c monocyte subset, which expressed the full set of FcγRs required for IgG activity. © 2011 Elsevier Inc.

Morphology as indicator of adaptive changes of model tissues in osmotically and chemically changing environments - Höllring, Kevin; Vurnek, Damir; Gehrer, Simone; Dudziak, Diana; Hubert, Maxime; Smith, Ana-Suncana (Biomaterials Advances, 2023)
We investigate the formation and maintenance of the homeostatic state in the case of 2D epithelial tissues following an induction of hyperosmotic conditions, using media enriched with 80 to 320 mOsm of mannitol, NaCl, and urea. We characterise the changes in the tissue immediately after the osmotic shock, and follow it until the new homeostatic state is formed. We characterise changes in cooperative motility and proliferation pressure in the tissue upon treatment with the help of a theoretical model based on the delayed Fisher-Kolmogorov formalism, where the delay in density evolution is induced by the the finite time of the cell division. Finally we explore the adaptation of the homeostatic tissue to highly elevated osmotic conditions by evaluating the morphology and topology of cells after 20 days in incubation. We find that hyperosmotic environments together with changes in the extracellular matrix induce different mechanical states in viable tissues, where only some remain functional. The perspective is a relation between tissue topology and function, which could be explored beyond the scope of this manuscript. Experimental investigation of morphological effect of change of osmotic conditions on long-term tissue morphology and topology Effect of osmotic changes on transient tissue growth behaviour Analysis of recovery process of tissues post-osmotic-shock Toxicity limits of osmolytes in mid- to long-term tissue evolution Tissue adaptation to physiological changes in environment Long-term tissue stabilisation under altered osmotic conditions.
CRIS-Team Scopus Importer:2023-11-03
Keywords: Epithelium topology and morphology; Fisher-Kolmogorov theory; Hyperosmotic conditions; Model tissue development; Tissue adaptation

Multicentric Sentinel Healthcare Research Project of Skin Cancer Centers in Nuremberg, Erlangen, Regensburg and Wuerzburg - Enzelsberger, K.; Debus, D.; Schultz, E.; Haferkamp, S.; Hegemann, M. V.; Stolze, I.; Erdmann, M.; Schellerer, Vera (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-09-13

Multiepitope tissue analysis reveals SPPL3-mediated ADAM10 activation as a key step in the transformation of melanocytes - Ostalecki, Christian; Lee, Jung-Hyun; Dindorf, Jochen; Collenburg, Lena; Schierer, Stephan; Simon, Beate; Schliep, Stefan; Kremmer, Elisabeth; Schuler, Gerold; Baur, Andreas (Science Signaling, 2017)
The evolution of cancer is characterized by the appearance of specific mutations, but these mutations are translated into proteins that must cooperate to induce malignant transformation. Using a systemic approach with the multiepitope ligand cartography (MELC) technology, we analyzed protein expression profiles (PEPs) in nevi and BRAFV600E-positive superficial spreading melanomas (SSMs) from patient tissues to identify key transformation events. The PEPs in nevi and SSMs differed predominantly in the abundance of specific antigens, but the PEPs of nevi- and melanoma-associated keratinocytes gradually changed during the transformation process. A stepwise change in PEP with similar properties occurred in keratinocytes cocultured with melanoma cells. Analysis of the individual steps indicated that activation of the metalloproteinase ADAM10 by signal peptide peptidase-like 3 (SPPL3) triggered by mutant BRAFV600E was a critical transformation event. SPPL3-mediated ADAM10 activation involved the translocation of SPPL3 and ADAM10 into Rab4- or Rab27-positive endosomal compartments. This endosomal translocation, and hence ADAM10 activation, was inhibited by the presence of the tumor suppressor PTEN. Our findings suggest that systematic tissue antigen analysis could complement whole-genome approaches to provide more insight into cancer development.
EVALuna2:34322

Multi-level cancer profiling through joint cell-graph representations - Rivera Monroy, Luis; Rist, Leonhard; Wilm, Frauke; Ostalecki, Christian; Baur, Andreas; Vera González, Julio; Breininger, Katharina; Maier, Andreas (Smart Health, 2024)
Computer-aided analysis of digitized pathology samples has significantly advanced with the rapid progression of machine and Deep Learning (DL) methods. However, most existing approaches primarily focus on features extracted from patches due to the large image sizes. This focus limits the ability of Convolutional Neural Networks (CNNs) to capture global information from the samples, resulting in an incomplete phenotypical and topological representation and thereby restricting the diagnostic capabilities of these methods. The recent emergence of Graph Neural Networks (GNNs) offers new opportunities to overcome these limitations through graph-driven representations of pathological samples. This work introduces a graph-based framework that encompasses diverse cancer types and integrates different imaging modalities. In this framework, histopathology samples are represented as graphs, and a pipeline facilitating cell-wise and disease classification is developed. The results support this motivation: for cell-wise classification, we achieved an average accuracy of , and for disease-wise classification, an average accuracy of 83%, outperforming reference models such as XGBoost and standard CNNs. This approach not only provides flexibility in combining various diseases but also extends to integrating different staining technique
Keywords: Fluorescence microscopy imageGraph deep learningMultiplex imagingDigital pathology

Multi-Level Computational Modeling of Anti-Cancer Dendritic Cell Vaccination Utilized to Select Molecular Targets for Therapy Optimization - Lai, Xin; Keller, Christine; Santos Rosales, Guido; Schaft, Niels; Dörrie, Jan; Vera, Julio (Frontiers in Cell and Developmental Biology, 2022)
Dendritic cells (DCs) can be used for therapeutic vaccination against cancer. The success of this therapy depends on efficient tumor-antigen presentation to cytotoxic T lymphocytes (CTLs) and the induction of durable CTL responses by the DCs. Therefore, simulation of such a biological system by computational modeling is appealing because it can improve our understanding of the molecular mechanisms underlying CTL induction by DCs and help identify new strategies to improve therapeutic DC vaccination for cancer. Here, we developed a multi-level model accounting for the life cycle of DCs during anti-cancer immunotherapy. Specifically, the model is composed of three parts representing different stages of DC immunotherapy – the spreading and bio-distribution of intravenously injected DCs in human organs, the biochemical reactions regulating the DCs’ maturation and activation, and DC-mediated activation of CTLs. We calibrated the model using quantitative experimental data that account for the activation of key molecular circuits within DCs, the bio-distribution of DCs in the body, and the interaction between DCs and T cells. We showed how such a data-driven model can be exploited in combination with sensitivity analysis and model simulations to identify targets for enhancing anti-cancer DC vaccination. Since other previous works show how modeling improves therapy schedules and DC dosage, we here focused on the molecular optimization of the therapy. In line with this, we simulated the effect in DC vaccination of the concerted modulation of combined intracellular regulatory processes and proposed several possibilities that can enhance DC-mediated immunogenicity. Taken together, we present a comprehensive time-resolved multi-level model for studying DC vaccination in melanoma. Although the model is not intended for personalized patient therapy, it could be used as a tool for identifying molecular targets for optimizing DC-based therapy for cancer, which ultimately should be tested in in vitro and in vivo experiments.
CRIS-Team Scopus Importer:2022-03-04
Keywords: bio-distribution; cellular therapy; dendritic cell vaccine; gene networks; immunotherapy; kinetic modeling; melanoma; systems medicine

Multiple Dermal Abscesses by Trichophyton rubrum in an Immunocompromised Patient - Toussaint, Frédéric; Sticherling, Michael (Frontiers in Medicine, 2019)
We report the case of a 52-year-old man who presented with a 10 year history of multiple nodules with purulent drainage on the upper extremities. Several attempts of treatment with oral antibiotics had been unsuccessful. A skin biopsy specimen showed a dermal abscess with branched septate hyphae. A mycological culture of pus and of the biopsy specimen revealed Trichophyton rubrum. Deeper dermatophytosis presenting as dermal abscesses is a rare disease which occurs normally in immunocompromised conditions. Our patient was on immunosuppressive therapy with methylprednisolone and azathioprine because of inflammatory demyelinating polyneuropathy and presented with extensive abscesses. In cases of dermal abscesses it is important to not only consider bacterial but also fungal infections as underlying cause.
CRIS-Team WoS Importer:2019-05-24

Multiple dermal Abscesses by Trichophyton rubrum in an immunosuppressed Patients - Toussaint, Frédéric; Sticherling, Michael (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-05-17

Multiple interferon regulatory factor and NF-κB sites cooperate in mediating cell-type-and maturation-specific activation of the human CD83 promoter in dendritic cells - Stein, Marcello F.; Lang, Stefan; Winkler, Thomas; Deinzer, Anja; Erber, Sebastian; Nettelbeck, Dirk M.; Naschberger, Elisabeth; Jochmann, Ramona; Stürzl, Michael; Slany, Robert; Werner, Thomas; Steinkasserer, Alexander; et al. (Molecular and Cellular Biology, 2013)
CD83 is one of the best-known surface markers for fully mature dendritic cells (mature DCs), and its cell-type-and maturationspecific regulation makes the CD83 promoter an interesting tool for the genetic modulation of DCs. To determine the mechanisms regulating this DC-and maturation-specific CD83 expression, chromatin immunoprecipitation (ChIP)-on-chip microarray, biocomputational, reporter, electrophoretic mobility shift assay (EMSA), and ChIP analyses were performed. These studies led to the identification of a ternary transcriptional activation complex composed of an upstream regulatory element, a minimal promoter, and an enhancer, which have not been reported in this arrangement for any other gene so far. Notably, these DNA regions contain a complex framework of interferon regulatory factor (IRF)-and NF-κB transcription factor-binding sites mediating their arrangement. Mutation of any of the IRF-binding sites resulted in a significant loss of promoter activity, whereas overexpression of NF-κB transcription factors clearly enhanced transcription. We identified IRF-1, IRF-2, IRF-5, p50, p65, and cRel to be involved in regulating maturation-specific CD83 expression in DCs. Therefore, the characterization of this promoter complex not only contributes to the knowledge of DC-specific gene regulation but also suggests the involvement of a transcriptional module with binding sites separated into distinct regions in transcriptional activation as well as cell-type-and maturation-specific transcriptional targeting of DCs. © 2013, American Society for Microbiology.

Multiple thoracic Erosions after Vacation in Tunisia - Meder, Christine; Sticherling, Michael (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2021)
CRIS-Team WoS Importer:2021-04-16

Multiplex Tissue Analysis of the Tumor Microenvironment and Crucial Factors in Melanoma Pathogenesis - Ostalecki, Christian; Lee, Jung-Hyun; Schierer, Stephan; Collenburg, Lena; Schuler, Gerold; Baur, Andreas (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-03-20

Multiplicity of Mathematical Modeling Strategies to Search for Molecular and Cellular Insights into Bacteria Lung Infection - Cantone, Martina; Santos, Guido; Wentker, Pia; Lai, Xin; Vera, Julio (Frontiers in Physiology, 2017)
Even today two bacterial lung infections, namely pneumonia and tuberculosis, are among the 10 most frequent causes of death worldwide. These infections still lack effective treatments in many developing countries and in immunocompromised populations like infants, elderly people and transplanted patients. The interaction between bacteria and the host is a complex system of interlinked intercellular and the intracellular processes, enriched in regulatory structures like positive and negative feedback loops. Severe pathological condition can emerge when the immune system of the host fails to neutralize the infection. This failure can result in systemic spreading of pathogens or overwhelming immune response followed by a systemic inflammatory response. Mathematical modeling is a promising tool to dissect the complexity underlying pathogenesis of bacterial lung infection at the molecular, cellular and tissue levels, and also at the interfaces among levels. In this article, we introduce mathematical and computational modeling frameworks that can be used for investigating molecular and cellular mechanisms underlying bacterial lung infection. Then, we compile and discuss published results on the modeling of regulatory pathways and cell populations relevant for lung infection and inflammation. Finally, we discuss how to make use of this multiplicity of modeling approaches to open new avenues in the search of the molecular and cellular mechanisms underlying bacterial infection in the lung.
EVALuna2:35406

Murine CD83-positive T cells mediate suppressor functions in vitro and in vivo - Kreiser, Simon; Eckhardt, Jenny; Kuhnt, Christine; Stein, Marcello F.; Krzyzak, Lena; Seitz, Christine; Tucher, Christine; Knippertz, Ilka; Becker, Christoph; Günther, Claudia; Steinkasserer, Alexander; Lechmann, Matthias (Immunobiology, 2015)
The CD83 molecule (CD83) is a well-known surface marker present on mature dendritic cells (mDC). In this study, we show that CD83 is also expressed on a subset of T cells which mediate regulatory T cell (Treg)-like suppressor functions in vitro and in vivo. Treg-associated molecules including CD25, cytotoxic T lymphocyte antigen-4 (CTLA-4), glucocorticoid-induced TNFR family-related gene (GITR), Helios and neuropilin-1 (NRP-1) as well as forkhead box protein 3 (FOXP3) were specifically expressed by these CD83(+) T cells. In contrast, CD83(-) T cells showed a naive T cell phenotype with effector T cell properties upon activation. Noteworthy, CD83(-) T cells were not able to upregulate CD83 despite activation. Furthermore, CD83(+) T cells suppressed the proliferation and inflammatory cytokine release of CD83(-) T cells in vitro. Strikingly, stimulated CD83(+) T cells released soluble CD83 (sCD83), which has been reported to possess immunosuppressive properties. In vivo, using the murine transfer colitis model we could show that CD83(+) T cells were able to suppress colitis symptoms while CD83(-) T cells possessed effector functions. In addition, this CD83 expression is also conserved on expanded human Treg. Thus, from these studies we conclude that CD83(+) T cells share important features with regulatory T cells, identifying CD83 as a novel lineage marker to discriminate between different T cell populations.
EVALuna2:1841

Mutations in IL36RN in patients with generalized pustular psoriasis - Koerber, Andreas; Moessner, Rotraut; Renner, Regina; Sticht, Heinrich; Wilsmann-Theis, Dagmar; Schulz, Peter; Sticherling, Michael; Traupe, Heiko; Hüffmeier, Ulrike (Journal of Investigative Dermatology, 2013)
EVALuna2:9180

Mutations in the splicing factor SF3B1 are linked to frequent emergence of HLA-DRlow/neg monocytes in lower-risk myelodysplastic neoplasms - Winter, Susann; Schneider, Marie; Oelschlaegel, Uta; Maggioni, Giulia; Riva, Elena; Raddi, Marco Gabriele; Bencini, Sara; Peruzzi, Benedetta; Choy, Desmond; Antunes Dos Reis, Rita; Güse, Esther; Lischer, Christopher; et al. (Leukemia, 2024)
CRIS-Team Scopus Importer:2024-05-10

Mycobacterial Cord Factor Reprograms the Macrophage Response to IFN-γ towards Enhanced Inflammation yet Impaired Antigen Presentation and Expression of GBP1 - Huber, Alexandra; Killy, Barbara; Grummel, Nadine; Bodendorfer, Barbara; Paul, Sushmita; Wiesmann, Veit; Naschberger, Elisabeth; Zimmer, Jana; Wirtz, Stefan; Schleicher, Ulrike; Vera, Julio; Ekici, Arif Bülent; et al. (Journal of Immunology, 2020)
Mycobacteria survive in macrophages despite triggering pattern recognition receptors and T cell-derived IFN-γ production. Mycobacterial cord factor trehalose-6,6-dimycolate (TDM) binds the C-type lectin receptor MINCLE and induces inflammatory gene expression. However, the impact of TDM on IFN-γ-induced macrophage activation is not known. In this study, we have investigated the cross-regulation of the mouse macrophage transcriptome by IFN-γ and by TDM or its synthetic analogue trehalose-6,6-dibehenate (TDB). As expected, IFN-γ induced genes involved in Ag presentation and antimicrobial defense. Transcriptional programs induced by TDM and TDB were highly similar but clearly distinct from the response to IFN-γ. The glycolipids enhanced expression of a subset of IFN-γ-induced genes associated with inflammation. In contrast, TDM/TDB exerted delayed inhibition of IFN-γ-induced genes, including pattern recognition receptors, MHC class II genes, and IFN-γ-induced GTPases, with antimicrobial function. TDM downregulated MHC class II cell surface expression and impaired T cell activation by peptide-pulsed macrophages. Inhibition of the IFN-γ-induced GTPase GBP1 occurred at the level of transcription by a partially MINCLE-dependent mechanism that may target IRF1 activity. Although activation of STAT1 was unaltered, deletion of Socs1 relieved inhibition of GBP1 expression by TDM. Nonnuclear Socs1 was sufficient for inhibition, suggesting a noncanonical, cytoplasmic mechanism. Taken together, unbiased analysis of transcriptional reprogramming revealed a significant degree of negative regulation of IFN-γ-induced Ag presentation and antimicrobial gene expression by the mycobacterial cord factor that may contribute to mycobacterial persistence.
CRIS-Team Scopus Importer:2020-09-18

Myeloid cells and the microenvironment, microorganisms and metabolism - Bogdan, Christian; Steinkasserer, Alexander (Immunobiology, 2015)
EVALuna2:7673

Myeloperoxidase Modulates Inflammation in Generalized Pustular Psoriasis and Additional Rare Pustular Skin Diseases - Haskamp, Stefan; Bruns, Heiko; Hahn, Madelaine; Hoffmann, Markus; Gregor, Anne; Löhr, Sabine; Hahn, Jonas; Ringer, Mark; Flamann, Cindy; Frey, Benjamin; Lesner, Adam; Thiel, Christian; et al. (American Journal of Human Genetics, 2020)
Generalized pustular psoriasis (GPP) is a severe multi-systemic inflammatory disease characterized by neutrophilic pustulosis and triggered by pro-inflammatory IL-36 cytokines in skin. While 19%–41% of affected individuals harbor bi-allelic mutations in IL36RN, the genetic cause is not known in most cases. To identify and characterize new pathways involved in the pathogenesis of GPP, we performed whole-exome sequencing in 31 individuals with GPP and demonstrated effects of mutations in MPO encoding the neutrophilic enzyme myeloperoxidase (MPO). We discovered eight MPO mutations resulting in MPO -deficiency in neutrophils and monocytes. MPO mutations, primarily those resulting in complete MPO deficiency, cumulatively associated with GPP (p = 1.85E−08; OR = 6.47). The number of mutant MPO alleles significantly differed between 82 affected individuals and >4,900 control subjects (p = 1.04E−09); this effect was stronger when including IL36RN mutations (1.48E−13) and correlated with a younger age of onset (p = 0.0018). The activity of four proteases, previously implicated as activating enzymes of IL-36 precursors, correlated with MPO deficiency. Phorbol-myristate-acetate-induced formation of neutrophil extracellular traps (NETs) was reduced in affected cells (p = 0.015), and phagocytosis assays in MPO-deficient mice and human cells revealed altered neutrophil function and impaired clearance of neutrophils by monocytes (efferocytosis) allowing prolonged neutrophil persistence in inflammatory skin. MPO mutations contribute significantly to GPP's pathogenesis. We implicate MPO as an inflammatory modulator in humans that regulates protease activity and NET formation and modifies efferocytosis. Our findings indicate possible implications for the application of MPO inhibitors in cardiovascular diseases. MPO and affected pathways represent attractive targets for inducing resolution of inflammation in neutrophil-mediated skin diseases.
CRIS-Team Scopus Importer:2020-09-11
Keywords: ACH; acrodermatitis continua suppurativa Hallopeau; activation of IL-36 precursors; acute generalized 4 exanthematous pustulosis; AGEP; efferocytosis; generalized pustular psoriasis; GPP; impaired NETosis; MPO deficiency; myeloperoxidase; oligogenic inheritance

Myositis and neuromuscular side-effects induced by immune checkpoint inhibitors - Moreira, Alvaro; Loquai, Carmen; Pfoefer, Claudia; Kaehler, Katharina C.; Knauss, Samuel; Heppt, Markus V.; Gutzmer, Ralf; Dimitriou, Florentia; Meier, Friedegund; Mitzel-Rink, Heidrun; Schuler, Gerold; Terheyden, Patrick; et al. (European Journal of Cancer, 2019)
AIM: To characterise clinical presentation, laboratory and histopathologic characteristics and assess the treatment and outcome of neuromuscular side-effects of checkpoint therapy. METHODS: The side-effect registry and the institutional database from ten skin cancer centres were queried for reports on myositis and neuromuscular side-effects induced by checkpoint inhibitors. In total, 38 patients treated with ipilimumab, tremelimumab, nivolumab and pembrolizumab for metastatic skin cancer were evaluated and characterised. RESULTS: Myositis was the most frequent neuromuscular adverse event. In 32% of cases, myositis was complicated by concomitant myocarditis. Furthermore, cases of isolated myocarditis, myasthenia gravis, polymyalgia rheumatica, radiculoneuropathy and asymptomatic creatine kinase elevation were reported. The onset of side-effects ranged from the first week of treatment to 115 weeks after the start of therapy. Most of the cases were severe (49% grade III-IV Common Terminology Criteria for Adverse Events), and there were two fatalities (5%) due to myositis and myositis with concomitant myocarditis. Only half of the cases (50%) completely resolved, whereas the rest was either ongoing or had sequelae. Steroids were given in 80% of the resolved cases and in 40% of the unresolved cases. CONCLUSION: Immune-mediated neuromuscular side-effects of checkpoint inhibitors greatly vary in presentation and differ from their idiopathic counterparts. These side-effects can be life threatening and may result in permanent sequelae. Occurrence of these side-effects must be taken into consideration for patient information, especially when considering adjuvant immunotherapy with anti-programmed cell-death protein 1 (PD-1) antibodies and monitoring, which should include regular surveillance of creatine kinase.
EVALuna2:36556

NanoString technology distinguishes anti-TIF-1γ+ from anti-Mi-2+ dermatomyositis patients - Preusse, Corinna; Eede, Pascale; Heinzerling, Lucie; Freitag, Kiara; Koll, Randi; Froehlich, Waltraud; Schneider, Udo; Allenbach, Yves; Benveniste, Olivier; Schaenzer, Anne; Goebel, Hans-Hilmar; Stenzel, Werner; et al. (Brain Pathology, 2021)
Dermatomyositis (DM) is a systemic idiopathic inflammatory disease affecting skeletal muscle and skin, clinically characterized by symmetrical proximal muscle weakness and typical skin lesions. Recently, myositis-specific autoantibodies (MSA) became of utmost importance because they strongly correlate with distinct clinical manifestations and prognosis. Antibodies against transcription intermediary factor 1γ (TIF-1γ) are frequently associated with increased risk of malignancy, a specific cutaneous phenotype and limited response to therapy in adult DM patients. Anti-Mi-2 autoantibodies, in contrast, are typically associated with classic DM rashes, prominent skeletal muscle weakness, better therapeutic response and prognosis, and less frequently with cancer. Nevertheless, the sensitivity of autoantibody testing is only moderate, and alternative reliable methods for DM patient stratification and prediction of cancer risk are needed. To further investigate these clinically distinct DM subgroups, we herein analyzed 30 DM patients (n = 15 Mi-2+ and n = 15 TIF-1 γ+) and n = 8 non-disease controls (NDC). We demonstrate that the NanoString technology can be used as a very sensitive method to clearly differentiate these two clinically distinct DM subgroups. Using the nCounter PanCancer Immune Profiling Panel™, we identified a set of significantly dysregulated genes in anti-TIF-1γ+ patient muscle biopsies including VEGFA, DDX58, IFNB1, CCL5, IL12RB2, and CD84. Investigation of type I IFN-regulated transcripts revealed a striking type I interferon signature in anti-Mi-2+ patient biopsies. Our results help to stratify both subgroups and predict, which DM patients require an intensified diagnostic procedure and might have a poorer outcome. Potentially, this could also have implications for the therapeutic approach.
CRIS-Team Scopus Importer:2021-06-11
Keywords: dermatomyositis; Mi-2; myositis-specific antibody; NanoString; skeletal muscle; TIF-1γ

Nectin-1 determines the susceptibility of malignant melanoma to oncolytic herpes simplex virus in vitro and in vivo - Schwertner, B.; Lindner, G.; Stauner, C. Toledo; Klapproth, E.; Magnus, C.; Rohrhofer, A.; Gross, S.; Schuler-Thurner, Beatrice; Oettl, V.; Feichtgruber, N.; Drexler, K.; Evert, K.; et al. (EXPERIMENTAL DERMATOLOGY, 2022)
CRIS-Team WoS Importer:2022-03-04

Neoadjuvant imatinib in advanced primary or locally recurrent dermatofibrosarcoma protuberans: a multicenter phase II DeCOG trial with long-term follow-up - Ugurel, Selma; Mentzel, Thomas; Utikal, Jochen; Helmbold, Peter; Mohr, Peter; Pföhler, Claudia; Schiller, Meinhard; Hauschild, Axel; Hein, Rüdiger; Kämpgen, Eckhart; Kellner, Ivonne; Leverkus, Martin; et al. (Clinical Cancer Research, 2014)
Dermatofibrosarcoma protuberans (DFSP) is a rare cutaneous tumor. COL1A1-PDGFB gene fusion is frequent in DFSP, rendering tumor cell proliferation and survival dependent on PDGFR? (platelet-derived growth factor receptor ?) signaling. This trial investigated imatinib as neoadjuvant treatment of DFSP, including long-term follow-up.The primary endpoint of this multicenter phase II trial was response; secondary endpoints were safety, tumor relapse, and response biomarkers. Patients with advanced primary or locally recurrent DFSP and measurable disease by RECIST (response evaluation criteria in solid tumors) were eligible and received imatinib 600 mg/d until definitive surgery with histopathologic proof of tumor-free margins.Sixteen patients received imatinib, and 14 patients were evaluable for all endpoints. Median treatment duration was 3.1 months; median tumor shrinkage was 31.5%. Best overall response was 7.1% complete response (CR), 50.0% partial response (PR), 35.7% stable disease, and 7.1% progressive disease (PD). Toxicity was moderate with 25.0% grade 3 and 4 events. During a median follow-up of 6.4 years, one patient developed secondary resistance to imatinib but responded to second-line sunitinib. This patient also presented local recurrence, distant metastasis, and death from DFSP. Exploratory analysis showed that response to imatinib was associated with decreased tumor cellularity and formation of strong hyalinic fibrosis. Weak PDGFRB phosphorylation and pigmented-type DFSP were associated with nonresponse. Additional to PDGFRB, the kinases EGFR and insulin receptor were found activated in a high percentage of DFSPs.The neoadjuvant use of imatinib 600 mg/d in DFSP is efficacious and well tolerated. Long-term follow-up results do not definitely support smaller surgical margins after successful imatinib pretreatment, and presume that secondary resistance to imatinib might promote accelerated disease progression.
EVALuna2:19472

Network- and systems-based re-engineering of dendritic cells with non-coding RNAs for cancer immunotherapy - Lai, Xin; Dreyer, Florian; Cantone, Martina; Eberhardt, Martin; Gerer, Kerstin F.; Jaitly, Tanushree; Uebe, Steffen; Lischer, Christopher; Ekici, Arif Bülent; Wittmann, Jürgen; Jäck, Hans-Martin; Schaft, Niels; et al. (Theranostics, 2021)
Dendritic cells (DCs) are professional antigen-presenting cells that induce and regulate adaptive immunity by presenting antigens to T cells. Due to their coordinative role in adaptive immune responses, DCs have been used as cell-based therapeutic vaccination against cancer. The capacity of DCs to induce a therapeutic immune response can be enhanced by re-wiring of cellular signalling pathways with microRNAs (miRNAs). Methods: Since the activation and maturation of DCs is controlled by an interconnected signalling network, we deploy an approach that combines RNA sequencing data and systems biology methods to delineate miRNA-based strategies that enhance DC-elicited immune responses. Results: Through RNA sequencing of IKKβ-matured DCs that are currently being tested in a clinical trial on therapeutic anti-cancer vaccination, we identified 44 differentially expressed miRNAs. According to a network analysis, most of these miRNAs regulate targets that are linked to immune pathways, such as cytokine and interleukin signalling. We employed a network topology-oriented scoring model to rank the miRNAs, analysed their impact on immunogenic potency of DCs, and identified dozens of promising miRNA candidates, with miR-15a and miR-16 as the top ones. The results of our analysis are presented in a database that constitutes a tool to identify DC-relevant miRNA-gene interactions with therapeutic potential (www.synmirapy.net/dc-optimization). Conclusions: Our approach enables the systematic analysis and identification of functional miRNA-gene interactions that can be experimentally tested for improving DC immunogenic potenc
CRIS-Team WoS Importer:2020-12-11
Keywords: dendritic cell; therapeutic vaccination in cancer; systems biology; network biology; microRNAs: bioinformatics

Neural Networks for Distinguishing Rheumatoid Arthritis from Psoriatic Arthritis by Using Magnetic Resonance Imaging - Folle, Lukas; Bayat, Sara; Kleyer, Arnd; Fagni, Filippo; Kapsner, Lorenz; Schlereth, Maja; Meinderink, Timo; Breininger, Katharina; Tascilar, Koray; Krönke, Gerhard; Uder, Michael; Sticherling, Michael; et al. (Arthritis Rheumatol., 2022)

Neurological, respiratory, musculoskeletal, cardiac and ocular side-effects of anti-PD-1 therapy - Zimmer, Lisa; Goldinger, Simone M.; Hofmann, Lars; Loquai, Carmen; Ugurel, Selma; Thomas, Ioannis; Schmidgen, Maria I.; Gutzmer, Ralf; Utikal, Jochen S.; Goeppner, Daniela; Hassel, Jessica C.; Meier, Friedegund; et al. (European Journal of Cancer, 2016)
Anti-programmed cell death 1 (PD-1) antibodies represent an effective treatment option for metastatic melanoma and other cancer entities. They act via blockade of the PD-1 receptor, an inhibitor of the T-cell effector mechanisms that limit immune responses against tumours. As reported for ipilimumab, the anti-PD-1 antibodies pembrolizumab and nivolumab can induce immune-related adverse events (irAEs). These side-effects can involve skin, gastrointestinal tract, liver, the endocrine system and other organ systems. Since life-threatening and fatal irAEs have been reported, adequate diagnosis and management are essential.In total, 496 patients with metastatic melanoma from 15 skin cancer centres were treated with pembrolizumab or nivolumab. Two hundred forty two side-effects in 138 patients have been analysed. In 77 of the 138 patients side-effects affected the nervous system, respiratory tract, musculoskeletal system, heart, blood and eyes. Not yet reported side-effects such as meningo-(radiculitis), polyradiculitis, cardiac arrhythmia, asystolia, and paresis have been observed. Rare and difficult to manage side-effects such as myasthenia gravis are described in detail.Anti-PD-1 antibodies can induce a plethora of irAEs. The knowledge of them will allow prompt diagnosis and improve the management resulting in decreased morbidity.
EVALuna2:19571

Neuromuscular Side Effects of Immune Checkpoint Inhibitors - Moreira, Alvaro; Loquai, C.; Knauss, S.; Gutzmer, R.; Dimitriou, F.; Meier, F.; Heppt, M.; Mitzel-Rink, H.; Schuler, Gerold; Terheyden, P.; Thoms, K. M.; Zimmer, L.; et al. (2018)
EVALuna2:34768

NF-κB activation triggers NK-cell stimulation by monocyte-derived dendritic cells. - Bosch, Naomi C.; Voll, Reinhard E.; Voskens, Caroline J.; Gross, Stefanie; Seliger, Barbara; Schuler, Gerold; Schaft, Niels; Dörrie, Jan (Therapeutic Advances in Medical Oncology, 2019)
Background: In therapeutic cancer vaccination, monocyte-derived dendritic cells (moDCs) efficiently activate specific T-cell responses; however, optimizing the activation of innate immune cells could support and improve the antitumor effects. A major disadvantage of moDCs matured with the standard cytokine cocktail (consisting of IL-1 beta, IL-6, TNF alpha, and PGE(2)) is their inability to secrete IL-12p70. IL-12 prominently activates natural killer (NK) cells, which are crucial in innate antitumor immunity, as they act as helper cells for the induction of a cytotoxic T lymphocyte (CTL) response and are also able to directly kill the tumor. Methods: Previously we have shown that triggering the NF-kappa B pathway in moDCs by transfection of mRNA encoding constitutively active IKK beta (caIKK beta) led to IL-12p70 secretion and improved the dendritic cells' capability to activate and expand CTLs with a memory-like phenotype. In this study, we examined whether such dendritic cells could activate autologous NK cells. Results: moDCs matured with the standard cytokine cocktail followed by transfection with the caIKK beta-RNA were able to activate autologous NK cells, detected by the upregulation of CD54, CD69, and CD25 on the NK cells, their ability to secrete IFN gamma, and their high lytic activity. Moreover, the ability of NK-cell activation was not diminished by simultaneous T-cell activation. Conclusion: The capacity of caIKK beta-DCs to activate both the adaptive and innate immune response indicates an enhanced potential for clinical efficacy.
CRIS-Team WoS Importer:2019-12-27

Non-magnetic chromatographic separation of colloidally metastable superparamagnetic iron oxide nanoparticles and suspension cells - Mühlberger, Marina; Janko, Christina; Unterweger, Harald; Band, Julia; Schreiber, Eveline; Lehmann, Christian; Dudziak, Diana; Lee, Geoffrey; Alexiou, Christoph; Tietze, Rainer (Journal of Chromatography B-Analytical Technologies in the Biomedical and Life Sciences, 2019)
For magnetic control of cells for biomedical applications such as targeting of immune cells to tumors, cells must be magnetizable. For that, cells are incubated with superparamagnetic iron oxide nanoparticles (SPIONs)to take them up and thus become magnetizable. When using adherent cells, non-ingested SPIONs can be easily removed by rinsing of the particles regardless of their colloidal stability in cell culture medium. However, if suspension cells such as T cells are to be loaded with SPIONs, established methods to separate excess nanoparticles from cells are based on physicochemical parameters such as density, size or magnetizability. Thus, colloidal stability of the particles is of great importance, since only colloidally stable SPIONs can be completely separated from the cells due to their physicochemical differences. Aggregates of colloidally meta- or unstable particles cannot, however, be separated from cells due to their overlapping sizes and densities. Thus, development of an alternative method for the separation of nanoparticle aggregates from suspension cells is urgently needed. Here, we present an affinity chromatographic separation method based on immunohistochemical properties of the respective cells. A desthiobiotinylated antibody against a cellular surface antigen (here CD90.2 receptor on EL4 T cells)is immobilized on a streptavidin agarose column optimized for cell purification. Subsequently the column is loaded with the particle/cell suspension so that the cells bind to the column. After removing the particles by washing, the cells can be gently eluted with biotin solution under physiological conditions. This allows >95% of the excess iron concentration to be removed while maintaining cell viability.
CRIS-Team Scopus Importer:2019-07-09
Keywords: Affinity chromatography; Antibody; Biotin; Cell viability; Desthiobiotin; Streptavidin

Nonviral RNA transfection to transiently modify T cells with chimeric antigen receptors for adoptive therapy - Riet, Tobias; Holzinger, Astrid; Dörrie, Jan; Schaft, Niels; Schuler, Gerold; Abken, Hinrich (Synthetic Messenger RNA and Cell Metabolism Modulation, 2013)
Redirecting T cells with a chimeric antigen receptor (CAR) of prede fined specificity showed remarkable ef ficacy in the adoptive therapy trials of malignant diseases. The CAR consists of a single chain fragment of variable region (scFv) antibody targeting domain covalently linked to the CD3 z signalling domain of the T cell receptor complex to mediate T cell activation upon antigen engagement. By using an antibodyderived targeting domain a CAR can potentially redirect T cells towards any target expressed on the cell surface as long as a binding domain is available. Antibody-mediated targeting moreover circumvents MHC restriction of the targeted antigen, thereby broadening the potential of applicability of adoptive T cell therapy. While T cells were so far genetically modi fied by viral transduction, transient modification with a CAR by RNA transfection gained increasing interest during the last years. This chapter focuses on methods to modify human T cells from peripheral blood with a CAR by electroporation of in vitro transcribed RNA and to test modi fied T cells for function for use in adoptive immunotherapy. © Springer Science+Business Media New York 2013.
CRIS-Team Scopus Importer:2021-10-01
Keywords: Adoptive cell therapy; Chimeric antigen receptor; Electroporation; In vitro transcription; RNA; T cell

Noonan Syndrome with multiple Lentigines (Leopard Syndrome) - Case Description of a 45-year-old Patient - Sponagl, F.; Sticherling, Michael; Seybold, H.; Erdmann, M.; Wagner, N. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-05-17

Obesity is linked to disease severity in moderate to severe atopic dermatitis—Data from the prospective observational TREATgermany registry - Traidl, Stephan; Hollstein, Moritz M.; Kroeger, Nadine; Fischer, Sascha; Heratizadeh, Annice; Heinrich, Luise; Kind, Barbara; Siegels, Doreen; Abraham, Susanne; Schäfer, Thomas; Augustin, Matthias; Harder, Inken; et al. (Journal of the European Academy of Dermatology and Venereology, 2024)
Background: There are conflicting data on a potential association between obesity and atopic dermatitis (AD). The purpose of this study was to investigate the relationship between obesity and AD disease severity. Methods: Patients from the TREATgermany registry cohort were divided into three groups according to their body mass index (BMI). Due to low numbers, underweight patients (BMI <18.5 kg/m2) were excluded from the analysis. Physician- and patient-reported disease severity scores as well as additional phenotypic characteristics were evaluated for association with BMI. Generalized linear mixed models and multinomial logit models, respectively, were applied to investigate the association of BMI, age, sex and current systemic AD treatment with disease severity. Results: This study encompassed 1416 patients, of which 234 (16.5%) were obese (BMI ≥30 kg/m2). Obesity was associated with lower educational background and smoking. Otherwise, obese and non-obese AD patients had similar baseline characteristics. Increased BMI was associated with higher oSCORAD (adjusted β: 1.24, 95% CI: 1.05–1.46, p = 0.013) and Patient-oriented eczema measure (POEM) (adjusted β: 1.09, 95% CI: 1.01–1.17, p = 0.038). However, the absolute difference in the overall oSCORAD was small between obese and non-obese AD patients (Δ oSCORAD = 2.5). Allergic comorbidity was comparable between all three groups, with the exception of asthma which was more pronounced in obese patients (p < 0.001). Discussion: In this large and well-characterized AD patient cohort, obesity is significantly associated with physician- and patient-assessed measures of AD disease severity. However, the corresponding effect sizes were low and of questionable clinical relevance. The overall prevalence of obesity among the German AD patients was lower than in studies on other AD cohorts from different countries, which confirms previous research on the German population and suggests regional differences in the interdependence of AD and obesity prevalence.
CRIS-Team Scopus Importer:2024-05-03

Objective and subjective hand function reflect grade of tenosynovitis in patients with psoriasis and psoriatic arthritis - Coppers, Birte; Bayat, Sara; Elie-Tino, Godonou; Valor-Mendez, Larissa; Simon, David; Corte, Giulia; Tascilar, Koray; Hueber, Axel; Bohr, Daniela; Schönau, Verena; Sticherling, Michael; Schett, Georg; et al. (poster, Deutsche Gesellschaft für Rheumatologie Kongress, 2023)

Occlusive cutaneous vasculopathies as cause of chronic ulcers - Ronicke, Moritz; Berking, Carola; Erfurt-Berge, Cornelia (Journal der Deutschen Dermatologischen Gesellschaft, 2024)
The term occluding vasculopathies covers a large number of different conditions. These often manifest as skin ulcers. Occluding vasculopathies should be considered in the differential diagnosis of leg ulcers. The term “occlusive vasculopathies” encompasses pathophysiologically related entities that share structural or thrombotic obliteration of small cutaneous vessels. In this article, we will focus on livedoid vasculopathy with and without antiphospholipid syndrome and calciphylaxis with differentiation from hypertonic leg ulcer as the most relevant differential diagnoses of leg ulcer. The term also includes vascular occlusion, for example due to oxalate or cholesterol embolism, and septic vasculopathy. This often leads to acral ulceration and is therefore not a differential diagnosis with classic leg ulcers. It will not be discussed in this article. Occlusive vasculopathy may be suspected in the presence of the typical livedo racemosa or (non-inflammatory) retiform purpura as a sign of reduced cutaneous perfusion in the wound area. Inflammatory dermatoses, especially vasculitides, must be differentiated. This is achieved by histopathological evaluation of a tissue sample of sufficient size and depth taken at the appropriate time. In addition, specific laboratory parameters, particularly coagulation parameters, can support the diagnosis.
CRIS-Team Scopus Importer:2024-03-15
Keywords: calciphylaxis; chronic wounds; livedoid vasculopathy; Martorell's ulcer; vasculopathy

Occupational palmoplantar psoriasis: a clinical case series with consideration of the S1 guidelines on expert medical assessments of occupational psoriasis - Angelovska, Irena; Mahler, Vera (Journal der Deutschen Dermatologischen Gesellschaft, 2014)
Constitutional diseases represent a challenge in the expert assessment of occupational diseases. It is necessary to distinguish professional causes from the spontaneous course of the disease. Recently, a guideline for the assessment of work-related psoriasis has been consented in Germany. We present a case series in which it was applied.129 expert assessments from the Department of dermatology University hospital Erlangen and court cases in established juridical databases were researched for cases with psoriasis and the applicability of the guideline.The guideline was applicable in the n = 6 (3.6 %) identified medical expert opinions. They were fully recognized by the workers compensation boards. The search for law sentences on work-related psoriasis in German court cases yielded a total of four sentences, in one of which the psoriasis was recognized as an occupational disease (BK 5101).In comparison with hand eczema psoriasis of the hands is rare. As has been demonstrated in our case series psoriasis as a constitutional disease may be recognized as an occupational disease (BK 5101) according to the legal system in Germany, if the influence of occupational exposure can be made sufficiently probable and other legal conditions of an occupational disease are met.
EVALuna2:19456

Ocular diseases in metastatic cutaneous melanoma: review of 108 consecutive patients in two German tertiary centers - Grajewski, Rafael S.; Schuler-Thurner, Beatrice; Mauch, Cornelia; Kreuzberg, Nicole; Koch, Konrad R.; Bergua, Antonio; Cursiefen, Claus; Heindl, Ludwig M. (Graefes Archive For Clinical and Experimental Ophthalmology, 2014)
To analyze the incidence and spectrum of ocular disease in patients with metastatic cutaneous melanoma.One hundred and eight consecutive patients with metastatic cutaneous melanoma were screened for ocular diseases using standardized eye examination, including measurement of visual acuity and intraocular pressure, slit-lamp examination, funduscopy in mydriasis, and spectral-domain optical coherence tomography (SDOCT) of the retina. Selected cases with atypical findings underwent electrophysiological studies. One patient was examined for hypercortisolism by a dexamethasone suppression test.Ocular diseases were found in 65 out of 108 patients (60 %) with metastatic cutaneous melanoma, significantly more often in older patients (p = 0.004). Cataract was present in 27 patients (25 %), pseudophakia in 22 patients (20 %), macular disease in 29 patients (28 %), diabetic retinopathy in ten patients (9 %), hypertensive retinal disease in 14 patients (13 %), retinal venous and arterial occlusive disease in three patients (3 %), optic neuropathy in four patients (4 %), and uveitis in one patient (1 %). Eight patients (8 %) had choroidal or iridal nevi, one patient (1 %) choroidal hemangioma, and one patient (1 %) choroidal metastasis. No patient had periocular neoplastic lesions. Paraneoplastic retinopathy manifesting as acute exudative polymorphous vitelliform maculopathy (AEPVM)-like disease was diagnosed in two patients (2 %) with multifocal central serous chorioretinopathy and development of vitelliform or fibrin-like subretinal deposits in one patient.Patients with metastatic cutaneous melanoma reveal ocular diseases with a spectrum similar to the normal population of this age range. Very rarely, uveal metastasis as well as paraneoplastic retinopathy can occur.
EVALuna2:19483

Okkludierende kutane Vaskulopathien als Ursachen chronischer Unterschenkelulzerationen - Ronicke, Moritz; Berking, Carola; Erfurt-Berge, Cornelia (Journal der Deutschen Dermatologischen Gesellschaft, 2024)
CRIS-Team Scopus Importer:2024-04-12
Keywords: Calciphylaxie; chronische Wunden; Livedovaskulopathie; Ulcus cruris hypertonicum Martorell; Vaskulopathie

Old Age, nodular Melanoma, Tumor Thickness and Ulceration are Risk Factors for regional and systemic Metastases in Melanoma Patients after negative Sentinel Node Biopsy - Erdmann, M.; Dominik, S.; Göhl, Jonas; Grützmann, Robert; Schuler, Gerold; Schellerer, Vera (2017)
EVALuna2:15294

Oncological System Therapy to the bitter End? - Berking, Carola (Journal der Deutschen Dermatologischen Gesellschaft, 2021)
CRIS-Team WoS Importer:2021-10-08

One allergen is not enough - RNAi-based down regulation of multiple allergens in tomato plants - Paulus, Kathrin; Mahler,; Sonnewald, Uwe (Allergy, 2015)

One set to collect them all? The development of a core domain set for medium-to-giant congenital melanocytic naevi - Heppt, Markus; Steeb, Theresa; Berking, Carola (British Journal of Dermatology, 2021)
CRIS-Team Scopus Importer:2021-04-02

One Website to Gather them All: Usability Testing of the New German SKin Cancer INFOrmation (SKINFO) Website-A Mixed-methods Approach - Steeb, Theresa; Bruetting, Julia; Reinhardt, Lydia; Hoffmann, Julia; Weiler, Nina; Heppt, Markus; Erdmann, Michael; Doppler, Astrid; Weber, Christiane; Schadendorf, Dirk; Meier, Friedegund; Berking, Carola (Journal of Cancer Education, 2022)
Skin cancer patients increasingly search the internet to acquire disease-related information. However, information on the internet may be misleading. Recently, SKINFO has been launched, a website exclusively created for German-speaking skin cancer patients providing information as well as additional resources of verified quality. Here, we describe the results of the first usability test of SKINFO using a mixed-methods approach. Ten adult patients with skin cancer were recruited for usability testing in the skin cancer units of the University Hospitals of Erlangen and Dresden, Germany. Testing consisted of three different scenarios where patients were asked to find specific information on the SKINFO website guided by the think-aloud method. Descriptive analysis and content analyses were performed. All patients would recommend SKINFO and appreciated its content, design, and structure. Think-aloud analysis identified the topics layout, navigation, and content and structure which would benefit from refinement. Major criticism included the navigation through the website, and the desire for more specific information addressing patients' relatives and the latest, up-to-date information. Overall, usability testing showed that the unique web-based information platform has the potential to support patients coping with skin cancer and thus strengthen informed decision-making.
CRIS-Team WoS Importer:2023-01-27

Onkologische Systemtherapie bis zum bitteren Ende? - Berking, Carola (Journal der Deutschen Dermatologischen Gesellschaft, 2022)
CRIS-Team Scopus Importer:2023-03-23

Online consensus conferences for the development and update of clinical practice guidelines: A survey among participants of the German S3 guideline on actinic keratosis and cutaneous squamous cell carcinoma - Steeb, Theresa; Follmann, Markus; Langer, Thomas; Nothacker, Monika; Wessely, Anja; Garbe, Claus; Leiter, Ulrike; Berking, Carola; Heppt, Markus (Journal der Deutschen Dermatologischen Gesellschaft, 2021)
CRIS-Team Scopus Importer:2021-03-05

Online-Konsensuskonferenzen für die Entwicklung und Aktualisierung von Leitlinien für die klinische Praxis: Eine Umfrage unter den Teilnehmenden der deutschen S3-Leitlinie zur aktinischen Keratose und kutanem Plattenepithelkarzinom - Steeb, Theresa; Follmann, Markus; Langer, Thomas; Nothacker, Monika; Wessely, Anja; Garbe, Claus; Leiter, Ulrike; Berking, Carola; Heppt, Markus (Journal der Deutschen Dermatologischen Gesellschaft, 2021)
CRIS-Team Scopus Importer:2021-04-30

Opportunities to inform German residents about the possibility of skin cancer screening and to inform stakeholders to take appropriate actions: A qualitative approach - Steeb, Theresa; Wessely, Anja; Heppt, Markus; Erdmann, Michael; Klug, Stefanie J.; Berking, Carola (Cancer Medicine, 2023)
Background: The national skin cancer screening (SCS) was introduced in Germany in 2008. However, public awareness and participation rates remain low. There are no campaigns or target group–specific invitation strategies for SCS yet. Thus, our aim was to derive potential suggestions on how to best inform German residents about the possibility of SCS. Methods: Semi–structured, individual interviews with male and female German residents aged =35 years were conducted in Erlangen (Germany) to explore opportunities on raising awareness of SCS. Interviews were audiotaped, transcribed verbatim, and analyzed using qualitative content analysis. Results: Overall, 39 persons were interviewed. About 79.5% (31/39) had already undergone at least one SCS. Numerous opportunities to raise awareness of the possibility of SCS were suggested which were categorized into three main topics: the role of public promotion, health–related caregivers, and health insurance. Similar themes were identified for inviting entitled persons to undergo SCS after 2 years. Furthermore, age–dependent communication approaches were proposed, that is, younger persons should be approached electronically, while the older generation should be targeted with traditional media like mail. Conclusions: The results of this project will inform stakeholders to take appropriate actions. The findings may contribute to increase participation rates in SCS and thus lead to earlier detection of skin cancer.
CRIS-Team WoS Importer:2023-05-12

Outcome of melanoma patients with elevated LDH treated with first-line targeted therapy or PD-1-based immune checkpoint inhibition - Knispel, Sarah; Gassenmaier, Maximilian; Menzies, Alexander M.; Loquai, Carmen; Johnson, Douglas B.; Franklin, Cindy; Gutzmer, Ralf; Hassel, Jessica C.; Weishaupt, Carsten; Eigentler, Thomas; Schilling, Bastian; Schummer, Patrick; et al. (European Journal of Cancer, 2021)
Background: Elevated lactate dehydrogenase (LDH) is a known predictive and prognostic factor for a poor outcome in patients with metastatic melanoma. It is unclear whether first-line targeted therapy (TT) or immune checkpoint inhibition (ICI) is more beneficial in melanoma patients with elevated LDH because prospective studies in this area are lacking. Methods: This multicentre retrospective cohort study was conducted at 25 melanoma centres worldwide to analyse progression-free survival (PFS) and overall survival (OS) among melanoma patients with elevated LDH. The role of confounders was addressed by using inverse probability of treatment weighting. Results: Among 173 BRAFV600-mutant patients, PFS at 12 months in the TT group was 22% compared with 52% in the combined anti-PD-1 and anti-CTLA-4 group (HR 0.6, 95% CI 0.4–1.0, p = 0.07) and 18% in the anti-PD-1 monotherapy group (HR 1.8, 95% CI 1.2–2.8, p = 0.003). Twelve months' OS was 48% in the TT group compared with 83% in the combined anti-PD-1 and anti-CTLA-4 group (HR 0.5, 95% CI 0.3–1.0, p = 0.03) and 50% in the anti-PD-1 monotherapy group (HR 1.2, 95% CI 0.8–2.0, p = 0.37). The ORR in the TT group was 63%, compared with 55% and 20% in the combined anti-PD-1 and anti-CTLA-4 and anti-PD-1 monotherapy group, respectively. Among 314 patients receiving ICI first-line, PFS at 12 months was 33% in the anti-PD-1 group versus 38% in the combined anti-PD-1 and anti-CTLA-4 group (HR 0.8, 95% CI 0.6–1.0; p = 0.07). OS at 12 months was 54% in the anti-PD-1 group versus 66% in the combined ICI group (HR 0.7, 95% CI 0.5–1.0; p = 0.03). The ORR was 30% in the anti-PD-1 monotherapy group and 43% in the combined anti-PD-1 and anti-CTLA-4 group. Results from multivariate analysis confirmed the absence of qualitative confounding. Conclusions: Among BRAF-mutant patients with elevated LDH, combined anti-PD-1 and anti-CTLA-4 blockade seems to be associated with prolonged OS compared with first-line TT. Among patients receiving ICI as a first-line treatment, OS appears to be longer for the combination of anti-PD-1 and anti-CTLA-4 than for anti-PD-1 alone.
CRIS-Team Scopus Importer:2021-03-26
Keywords: CTLA-4; Immune checkpoint inhibition; LDH; Melanoma; PD-1; Progression; Response; Survival; Targeted therapy

Palmoplantar Pustular Psoriasis Is Associated with Missense Variants in CARD14, but Not with Loss-of-Function Mutations in IL36RN in European Patients - Moessner, Rotraut; Frambach, Yvonne; Wilsmann-Theis, Dagmar; Loehr, Sabine; Jacobi, Arnd; Weyergraf, Ansgar; Mueller, Michael; Philipp, Sandra; Renner, Regina; Traupe, Heiko; Burkhardt, Harald; Kingo, Kuelli; et al. (Journal of Investigative Dermatology, 2015)
EVALuna2:9269

PaM - Development and Validation of a palliative medical Integration Model for Melanoma - Bender-Säbelkampf, Sophia; Heckel, Maria; Ostgathe, Christoph; Berking, Carola; Heppt, Markus (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2021)
CRIS-Team WoS Importer:2021-09-24

PASI <= 2 corresponds to PASI 90, irrespective of baseline severity: A post-hoc analysis of the PRIME-study - Reich, K.; Sieder, C.; Bachhuber, T.; Melzer, N.; Sticherling, Michael (2017)
EVALuna2:34343

Pathogenetic Implications of BRAF Mutation Distribution in Stage IV Melanoma Patients - Baiter, Mirjam; Schuler, Gerold; Hartmann, Arndt; Schneider-Stock, Regine; Heinzerling, Lucie (Dermatology, 2015)
BRAF mutation frequencies in melanoma subtypes have clinical implications and offer pathogenetic clues.To characterize BRAF mutation status in melanoma of unknown primary (MUP) patients, in histological melanoma subtypes and by localization of primary tumors.In 179 patients with stage IV metastatic melanoma, BRAF mutation status, histological subtype and localization of primary (except for 29 MUP patients) were analyzed.BRAF mutations were found in 44.3%, of which 80.5% were BRAF V600E and 19.5% showed non-V600E BRAF mutations. BRAF mutation frequency depended on histological subtype (57.4% superficial spreading melanoma, 54.7% nodular melanoma, 11.1% mucosal melanoma, 28.6% acral lentiginous melanoma) and concerning non-V600E BRAF mutations on localization of primary. In MUP the BRAF mutation pattern resembled superficial spreading and nodular melanomas.BRAF mutation frequencies depend on histological subtype and localization of primary melanoma. Non-V600E BRAF mutations mostly occur in patients with primaries on 'head and neck' as well as 'trunk' but not on 'extremities'.
EVALuna2:6729

Patient Characteristics and Treatment Patterns in European Pediatric Patients with Psoriasis: A Real-World, Cross-Sectional Study - Sticherling, Michael; Mcpherson, Tess; Laguna, Raul De Lucas; Costanzo, Antonio; Reed, Catherine; Artime, Esther; Robert, Camille; Lucas, James; Schuster, Christopher; Mahe, Emmanuel (Dermatology and Therapy, 2022)
Introduction This study evaluated patient characteristics and treatment patterns according to weight in pediatric patients with psoriasis in a real-world setting. Methods Primary care and specialist physicians treating pediatric patients with psoriasis aged 6-17 years in five European countries were surveyed in the 2019-2020 Adelphi Real World Pediatric Psoriasis Disease Specific Programme. At least two patients with current or previous biologic use were included per physician. Patient characteristics and treatment patterns were analyzed overall and for patients weighing 25-50 kg or more than 50 kg. Results Data from 772 patients weighing 25-50 kg and 1147 weighing more than 50 kg were analyzed. Median age at diagnosis was significantly less in lighter than heavier patients (10.0 vs. 14.0 years; p < 0.001), as was median disease duration (2.2 vs. 3.0 years; p < 0.001). Topical treatments were prescribed in 59.0% of patients overall (70.3% of lighter and 51.4% of heavier patients; p < 0.001), and were used to treat mild rather than moderate-to-severe psoriasis. Conventional systemic use was low (10.8% of patients overall) and predominantly for moderate-to-severe psoriasis. In this biologic-enriched sample, most biologics (78.2%) were prescribed in older (> 13 years) patients. Biologic use increased with line of therapy (6.6% of first-line, 18.0% of second-line, 33.7% of third-line, 44.7% of fourth-line treatments). Conclusion Biologics are predominantly prescribed in older (> 13 years) and heavier (> 50 kg) patients, with little first- or second-line use. The low use of biologics in European pediatric patients with psoriasis may represent an unmet treatment need, as topical or conventional systemic agents remain the main treatment option for moderate or severe psoriasis in these patients through the treatment pathway.
CRIS-Team WoS Importer:2022-07-22

Patient Perception of Mobile Phone Apps for the Care and Prevention of Sexually Transmitted Diseases: Cross-Sectional Study - Jakob, Lena; Steeb, Theresa; Fiocco, Zeno; Pumnea, Teodora; Jakob, Sophia Nomi; Wessely, Anja; Rothenberger, Christoph Clemens; Brinker, Titus Josef; French, Lars Einar; Berking, Carola; Heppt, Markus (JMIR mHealth and uHealth, 2020)
BACKGROUND: In the emerging era of digitalization and electronic health, various health-related apps have been launched, including apps for sexually transmitted diseases. Until now, little has been known about how patients perceive the value of such apps. OBJECTIVE: To investigate patient's attitudes and awareness toward sexually transmitted disease-related apps in an outpatient sexually transmitted disease clinic setting. METHODS: A cross-sectional study was conducted at a dermatovenereological outpatient unit between April and July 2019. Patients completed a self-administered questionnaire on their perceptions of the popularity and usefulness of sexually transmitted disease-related apps. Descriptive analysis was performed with expression of categorical variables as frequencies and percentages. For continuous variables, the median, range, and interquartile range were indicated. Contingency tables and chi-square tests were used to investigate associations between sociodemographic data and items of the questionnaire. RESULTS: A total of 226 patients were surveyed (heterosexual: 137/193, 71.0%; homosexual: 44/193, 22.8%; bisexual: 12/193, 6.2%); 11.9% (27/225) had previously used health-related apps. Nearly half of the patients (97/214, 45.3%) specifically considered sexually transmitted disease-related apps useful, 47.8% (100/209) voted that they could supplement or support the consultation of a physician. Interestingly, only 35.1% (74/211) preferred a printed patient brochure on sexually transmitted diseases over downloading and using an app, but 64.0% (134/209) would download a sexually transmitted disease-related app recommended by their physician. General information regarding sexually transmitted diseases (93/167, 55.7%), evaluation of skin diseases based on photos or videos (78/167, 53.3%), information on the prevention of sexually transmitted diseases (76/167, 45.5%), mediation of nearby contact points or test sites (74/167, 44.3%), anonymous medical advice (69/167, 41.3%), and calculation of the risk of having a sexually transmitted disease (63/167, 37.3%) were rated as the most important features. Men were more likely than women to find sexually transmitted disease-related apps useful in general (P=.04; χ2=6.28) and to pay for such apps (P=.01; χ2=9.19). Patients aged <40 years would rather download an app recommended by their physician (P=.03; χ2=7.23), whereas patients aged >40 years preferred reading a patient brochure on sexually transmitted diseases (P=.02; χ2=8.14). CONCLUSIONS: This study demonstrated high general interest in the use of sexually transmitted disease-related apps in this sample of dermatovenereological outpatients. In particular, young age and male sex were significantly associated with a positive perception, underlining the high potential of apps in the prevention and early recognition of sexually transmitted diseases in this group. Future studies are warranted to validate these findings in other populations.
CRIS-Team Scopus Importer:2020-11-27
Keywords: health apps; mobile phone apps; sexually transmitted diseases; sexually transmitted infection

Patient perception of the benefit of a BRAF inhibitor in metastatic melanoma: quality-of-life analyses of the BREAK-3 study comparing dabrafenib with dacarbazine - Grob, J. -J.; Amonkar, M. M.; Martin-Algarra, S.; Demidov, L. V.; Goodman, V.; Grotzinger, K.; Haney, P.; Kämpgen, Eckhart; Karaszewska, B.; Mauch, C.; Miller, W. H.; Millward, Michael; et al. (Annals of Oncology, 2014)
In a randomized phase III study (BREAK-3), dabrafenib showed prolonged progression-free survival (PFS) (median 5.1 versus 2.7 months; hazard ratio = 0.30; 95% confidence interval 0.18-0.53; P < 0.0001) compared with dacarbazine (DTIC) in patients with BRAF V600E metastatic melanoma. Assessing how these results are transformed into a real health benefit for patients is crucial.The EORTC QLQ-C30 questionnaire assessed quality of life (QoL) at baseline and follow-up visits.For DTIC, all functional dimensions except role dimension worsened from baseline at follow-up. For dabrafenib, all functionality dimensions remained stable relative to baseline or improved at week 6; mean change in seven symptom dimensions improved from baseline, with appetite loss, insomnia, nausea and vomiting, and pain showing the greatest improvement. In the DTIC arm, symptom dimensions were unchanged or worsened from baseline for all symptoms except pain (week 6), with the greatest exacerbations observed for fatigue and nausea and vomiting. Mixed-model-repeated measures analyses showed significant (P < 0.05) and/or clinically meaningful improvements from baseline in favor of dabrafenib for emotional and social functioning, nausea and vomiting, appetite loss, diarrhea, fatigue, dyspnea, and insomnia at weeks 6 and/or 12. After crossing over to dabrafenib upon progression (n = 35), improvements in all QoL dimensions were evident after receiving dabrafenib for 6 (n = 31) to 12 (n = 25) weeks.This first reported QoL analysis for a BRAF inhibitor in metastatic melanoma demonstrates that the high tumor response rates and PFS superiority of dabrafenib over DTIC is not only a theoretical advantage, but also transforms in a rapid functional and symptomatic benefit for the patient.NCT01227889.
EVALuna2:19471

Patient-reported Outcomes and Burden of Disease in Paediatric Patients with Psoriasis: Real-world Data from EU5 and US - Seyger, Marieke M.B.; Paller, Amy; Sticherling, Michael; Bachhuber, Teresa; Thomas, Nicolas; Hetherington, James; Lucas, James; Richardson, Craig; Augustin, Matthias (Acta Dermato-Venereologica, 2023)
CRIS-Team Scopus Importer:2023-04-28

Patient-reported outcomes and burden of disease in paediatric patients with psoriasis: real-world data from the EU5 and USA - Seyger, M.; Paller, A.; Sticherling, Michael; Bachhuber, T.; Fang, J.; Hetherington, J.; Lucas, J.; Meakin, S.; Richardson, C.; Augustin, M. (BRITISH JOURNAL OF DERMATOLOGY, 2022)
CRIS-Team WoS Importer:2022-01-14

Patients' and Physicians' Preferences for Systemic Psoriasis Treatments: A Nationwide Comparative Discrete Choice Experiment (PsoCompare) - Schaarschmidt, Marthe-Lisa; Herr, Raphael M.; Gutknecht, Mandy; Wroblewska, Katharina; Gerdes, Sascha; Sticherling, Michael; Augustin, Matthias; Peitsch, Wiebke K. (Acta Dermato-Venereologica, 2018)
Systemic antipsoriatic treatment options are increasing rapidly. The aim of this nationwide discrete choice experiment was to compare patients' (n = 222) and physicians' (n = 78) preferences for outcome and process attributes of systemic antipsoriatics using Relative Importance Scores (RIS). Both groups considered Psoriasis Area and Severity Index 90 (PASI 90) to be most important (RIS 21.4 and 20.8, respectively). Moreover, patients were highly concerned about mild and severe adverse events (RIS = 18.2 and 14.2), physicians about severe adverse events (RIS = 14.9) and cost (RIS = 13.8). Compared to physicians, patients worried more about mild adverse events and treatment location, but less about cost and frequency of laboratory tests. Physicians' preferences were influenced by work experience and percentage of biological prescriptions, patients' preferences by age, disease duration and severity. Older and less severely affected patients recruited via a patient organization focused more on safety, but less on efficacy and time until response than did patients from study centres. In conclusion, these differences in trade-offs should be integrated into a shared decision-making.
EVALuna2:34404

Patients Receiving Cytokine Inhibitors Have Low Prevalence of SARS-CoV-2 Infection - Simon, David; Tascilar, Koray; Krönke, Gerhard; Kleyer, Arnd; Zaiss, Mario; Heppt, Franz; Meder, Christine; Atreya, Raja; Klenske, Entcho; Dietrich, Peter; Abdullah, Abdullah; Kliem, Thorsten; et al. (ARTHRITIS & RHEUMATOLOGY, 2020)
CRIS-Team WoS Importer:2021-01-15

PATIENTS WITH IMMUNE MEDIATED INFLAMMATORY DISEASES ARE OVERREPRESENTED IN LOW-FREQUENCY VIRAL SYMPTOM CLUSTERS - Tascilar, Koray; Simon, David; Krönke, Gerhard; Kleyer, Arnd; Ramming, Andreas; Atreya, Raja; Tenbusch, Matthias; Überla, Klaus; Berking, Carola; Sticherling, Michael; Neurath, Markus; Schett, Georg (ANNALS OF THE RHEUMATIC DISEASES, 2021)
CRIS-Team WoS Importer:2021-09-24

Patients with immune-mediated inflammatory diseases receiving cytokine inhibitors have low prevalence of SARS-CoV-2 seroconversion - Simon, David; Tascilar, Koray; Krönke, Gerhard; Kleyer, Arnd; Zaiss, Mario; Heppt, Franz; Meder, Christine; Atreya, Raja; Klenske, Entcho; Dietrich, Peter; Abdullah, Abdullah; Kliem, Thorsten; et al. (Nature Communications, 2020)
Immune-mediated inflammatory diseases (IMIDs) of the joints, gut and skin are treated with inhibitors of inflammatory cytokines. These cytokines are involved in the pathogenesis of coronavirus disease 2019 (COVID-19). Investigating anti-SARS-CoV-2 antibody responses in IMIDs we observe a reduced incidence of SARS-CoV-2 seroconversion in IMID patients treated with cytokine inhibitors compared to patients receiving no such inhibitors and two healthy control populations, despite similar social exposure. Hence, cytokine inhibitors seem to at least partially protect from SARS-CoV-2 infection.
CRIS-Team Scopus Importer:2020-08-07

Patterns of care and follow-up care of patients with uveal melanoma in German-speaking countries: a multinational survey of the German Dermatologic Cooperative Oncology Group (DeCOG) - Steeb, Theresa; Wessely, Anja; Alter, Mareike; Bayerl, Christiane; Bender, Armin; Bruning, Guido; Dabrowski, Evelyn; Debus, Dirk; Devereux, Nina; Dippel, Edgar; Drexler, Konstantin; Dücker, Pia; et al. (Journal of Cancer Research and Clinical Oncology, 2020)
Purpose: Uveal melanoma (UM) is an orphan cancer of high unmet medical need. Current patterns of care and surveillance remain unclear as they are situated in an interdisciplinary setting. Methods: A questionnaire addressing the patterns of care and surveillance in the management of patients with uveal melanoma was distributed to 70 skin cancer centers in Austria, Germany and Switzerland. Frequency distributions of responses for each item of the questionnaire were calculated. Results: 44 of 70 (62.9%) skin cancer centers completed the questionnaire. Thirty-nine hospitals were located in Germany (88.6%), three in Switzerland (6.8%) and two in Austria (4.5%). The majority (68.2%) represented university hospitals. Most patients with metastatic disease were treated in certified skin cancer centers (70.7%, 29/41). Besides, the majority of patients with UM were referred to the respective skin cancer center by ophthalmologists (87.2%, 34/39). Treatment and organization of follow-up of patients varied across the different centers. 35.1% (14/37) of the centers stated to not perform any screening measures. Conclusion: Treatment patterns of patients with uveal melanoma in Germany, Austria and Switzerland remain extremely heterogeneous. A guideline for the treatment and surveillance is urgently needed.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Background; Cross-sectional study; Follow-up; Ocular melanoma; Patterns of care; Surveillance; Treatment patterns; Uveal melanoma

Perception of the coronavirus pandemic by patients with atopic dermatitis - Results from the TREATgermany registry - Helmert, Claudia; Siegels, Doreen; Haufe, Eva; Abraham, Susanne; Heratizadeh, Annice; Kleinheinz, Andreas; Harder, Inken; Schaekel, Knut; Effendy, Isaak; Wollenberg, Andreas; Sticherling, Michael; Stahl, Maren; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2021)
Background TREATgermany, a registry for patients with moderate to severe atopic dermatitis (AD), established an additional questionnaire in spring 2020 to investigate the effects of the coronavirus pandemic on the daily life of patients with AD. Material and Methods A questionnaire was used to analyze general information regarding a patient's experience of the coronavirus pandemic and, using the Inventory of Life-Changing Events, the resulting personal burden. To analyze possible associations between disease severity (EASI score, oSCORAD, IGA, PGA, POEM), quality of life (DLQI) and personal burden, t-tests, analyses of variance and correlations were evaluated, controlled for sex and age. Results 58 % (n = 233) of the included 400 registry patients reported high burden scores caused by the coronavirus pandemic, regardless of an actual infection. Men showed significantly higher burden scores than women, and younger than older respondents (both P = 0.03). There were no differences in burden scores related to the physician's assessment of disease severity. However, patients with higher quality of life impairments and higher disease severity perceived the burden of the coronavirus pandemic as less severe (DLQI P = 0.019, PGA P = 0.044). Conclusions Our data show that registry patients considered the coronavirus pandemic as a life-changing event and perceived the burden differently. This should be taken into account in the treatment of patients with moderate to severe AD as well as in further studies.
CRIS-Team WoS Importer:2022-01-07

Personalized cancer immunotherapy using Systems Medicine approaches - Gupta, Shailendra K.; Jaitly, Tanushree; Schmitz, Ulf; Schuler, Gerold; Wolkenhauer, Olaf; Vera, Julio (Briefings in Bioinformatics, 2016)
The immune system is by definition multi-scale because it involves biochemical networks that regulate cell fates across cell boundaries, but also because immune cells communicate with each other by direct contact or through the secretion of local or systemic signals. Furthermore, tumor and immune cells communicate, and this interaction is affected by the tumor microenvironment. Altogether, the tumor-immunity interaction is a complex multi-scale biological system whose analysis requires a systemic view to succeed in developing efficient immunotherapies for cancer and immune-related diseases. In this review we discuss the necessity and the structure of a systems medicine approach for the design of anticancer immunotherapies. We support the idea that the approach must be a combination of algorithms and methods from bioinformatics and patient-data-driven mathematical models conceived to investigate the role of clinical interventions in the tumor-immunity interaction. For each step of the integrative approach proposed, we review the advancement with respect to the computational tools and methods available, but also successful case studies. We particularized our idea for the case of identifying novel tumor-associated antigens and therapeutic targets by integration of patient's immune and tumor profiling in case of aggressive melanoma.
EVALuna2:19569

Phase Ib/II Trial of Ribociclib in Combination with Binimetinib in Patients with NRAS-mutant Melanoma. - Schuler, Martin; Zimmer, Lisa; Kim, Kevin B.; Sosman, Jeffrey A.; Ascierto, Paolo A.; Postow, Michael A.; De Vos, Filip Y.F.L.; van Herpen, Carla M.L.; Carlino, Matteo S.; Johnson, Douglas B.; Berking, Carola; Reddy, Micaela B.; et al. (Clinical Cancer Research, 2022)
PURPOSE: Enhanced MAPK pathway signaling and cell-cycle checkpoint dysregulation are frequent in NRAS-mutant melanoma and, as such, the regimen of the MEK inhibitor binimetinib and the selective CDK4/6 inhibitor ribociclib is a rational combination. PATIENTS AND METHODS: This is a phase Ib/II, open-label study of ribociclib + binimetinib in patients with NRAS-mutant melanoma (NCT01781572). Primary objectives were to estimate the MTD/recommended phase II dose (RP2D) of the combination (phase Ib) and to characterize combination antitumor activity at the RP2D (phase II). Tumor genomic characterization and pharmacokinetics/pharmacodynamics were also evaluated. RESULTS: Ten patients (16.4%) experienced dose-limiting toxicities in cycle 1 of phase Ib. Overall response rate in the phase II cohort (n = 41) for the selected RP2D (binimetinib 45 mg twice daily + ribociclib 200 mg once daily, 21 days on/7 days off) was 19.5% [8/41; 95% confidence interval (CI), 8.8-34.9]. The response rate was 32.5% (13/40; 95% CI, 20.1-48.0) in patients with NRAS mutation with concurrent alterations of CDKN2A, CDK4, or CCND1. Median progression-free survival was 3.7 months (95% CI, 3.5-5.6) and median overall survival was 11.3 months (95% CI, 9.3-14.2) for all patients. Common treatment-related toxicities included creatine phosphokinase elevation, rash, edema, anemia, nausea, diarrhea, and fatigue. Pharmacokinetics and safety were consistent with single-agent data, supporting a lack of drug-drug interaction. CONCLUSIONS: Ribociclib + binimetinib can be safely administered and is clinically active in patients with NRAS-mutant melanoma. Co-mutations of cell-cycle genes may define a population with greater likelihood of treatment benefit. See related commentary by Moschos, p. 2977.
EVALuna2:499725

Phase II DeCOG-study of ipilimumab in pretreated and treatment-naïve patients with metastatic uveal melanoma - Zimmer, Lisa; Vaubel, Julia; Mohr, Peter; Hauschild, Axel; Utikal, Jochen; Simon, Jan; Garbe, Claus; Herbst, Rudolf; Enk, Alexander; Kämpgen, Eckhart; Livingstone, Elisabeth; Bluhm, Leonie; et al. (PLoS ONE, 2015)
Up to 50% of patients with uveal melanoma (UM) develop metastatic disease with limited treatment options. The immunomodulating agent ipilimumab has shown an overall survival (OS) benefit in patients with cutaneous metastatic melanoma in two phase III trials. As patients with UM were excluded in these studies, the Dermatologic Cooperative Oncology Group (DeCOG) conducted a phase II to assess the efficacy and safety of ipilimumab in patients with metastatic UM.We undertook a multicenter phase II study in patients with different subtypes of metastatic melanoma. Here we present data on patients with metastatic UM (pretreated and treatment-naïve) who received up to four cycles of ipilimumab administered at a dose of 3 mg/kg in 3 week intervals. Tumor assessments were conducted at baseline, weeks 12, 24, 36 and 48 according to RECIST 1.1 criteria. Adverse events (AEs), including immune-related AEs were graded according to National Cancer Institute Common Toxicity Criteria (CTC) v.4.0. Primary endpoint was the OS rate at 12 months.Forty five pretreated (85%) and eight treatment-naïve (15%) patients received at least one dose of ipilimumab. 1-year and 2-year OS rates were 22% and 7%, respectively. Median OS was 6.8 months (95% CI 3.7-8.1), median progression-free survival 2.8 months (95% CI 2.5-2.9). The disease control rate at weeks 12 and 24 was 47% and 21%, respectively. Sixteen patients had stable disease (47%), none experienced partial or complete response. Treatment-related AEs were observed in 35 patients (66%), including 19 grade 3-4 events (36%). One drug-related death due to pancytopenia was observed.Ipilimumab has very limited clinical activity in patients with metastatic UM. Toxicity was manageable when treated as per protocol-specific guidelines.ClinicalTrials.gov NCT01355120.
EVALuna2:19596

Phosphatase PTPN22 Regulates Dendritic Cell Homeostasis and cDC2 Dependent T Cell Responses - Purvis, Harriet A.; Clarke, Fiona; Montgomery, Anna B.; Colas, Chloe; Bibby, Jack A.; Cornish, Georgina H.; Dai, Xuezhi; Dudziak, Diana; Rawlings, David J.; Zamoyska, Rose; Guermonprez, Pierre; Cope, Andrew P. (Frontiers in Immunology, 2020)
Dendritic cells (DCs) are specialized antigen presenting cells that instruct T cell responses through sensing environmental and inflammatory danger signals. Maintaining the homeostasis of the multiple functionally distinct conventional dendritic cells (cDC) subsets that exist in vivo is crucial for regulating immune responses, with changes in numbers sufficient to break immune tolerance. Using Ptpn22-/- mice we demonstrate that the phosphatase PTPN22 is a highly selective, negative regulator of cDC2 homeostasis, preventing excessive population expansion from as early as 3 weeks of age. Mechanistically, PTPN22 mediates cDC2 homeostasis in a cell intrinsic manner by restricting cDC2 proliferation. A single nucleotide polymorphism, PTPN22R620W, is one of the strongest genetic risk factors for multiple autoantibody associated human autoimmune diseases. We demonstrate that cDC2 are also expanded in mice carrying the orthologous PTPN22619W mutation. As a consequence, cDC2 dependent CD4+ T cell proliferation and T follicular helper cell responses are increased. Collectively, our data demonstrate that PTPN22 controls cDC2 homeostasis, which in turn ensures appropriate cDC2-dependent T cell responses under antigenic challenge. Our findings provide a link between perturbations in DC development and susceptibility to a broad spectrum of PTPN22R620W associated human autoimmune diseases.
CRIS-Team Scopus Importer:2020-03-31
Keywords: autoimmunity; cDC2; dendritic cell; homeostasis; polymorphism; proliferation; PTPN22; T follicular helper cell

Photodynamic therapy 'to go' - a strengths, weaknesses, opportunities and threats analysis - Heppt, M. V.; Steeb, T.; Berking, Carola (Journal of the European Academy of Dermatology and Venereology, 2019)
EVALuna2:211758

Physician-reported Clinical Unmet Needs, Burden and Treatment Patterns of Paediatric Psoriasis Patients: A US and EU Real-world Evidence Study - Seyger, Marieke M.B.; Augustin, Matthias; Sticherling, Michael; Bachhuber, Teresa; Fang, Juanzhi; Hetherington, James; Lucas, James; Meakin, Sophie; Richardson, Craig; Paller, Amy S. (Acta Dermato-Venereologica, 2022)
This study is a retrospective analysis using data col-lected from the Adelphi Paediatric Psoriasis Disease-Specific Programme cross-sectional survey. Despite being treated for their psoriasis, a substantial proportion of paediatric patients presented with moderate (18.3%) or severe (1.3%) disease at sampling; 42.9% and 92.0% had a body surface area (BSA) of >10%, and 38.8% and 100.0% had a Psoriasis Area Severity Index (PASI) score >10, respectively. Overall, 69.9% of patients had only ever been treated with a topical therapy for their psoriasis. For patients with moderate or severe disease at sampling, 16.3% and 14.4% were currently receiving conventional systemics or biologic therapy, respectively. There is a clinical unmet need in this paediatric population; a considerable percen-tage of patients still experienced moderate or severe disease and persistent psoriasis symptoms, with nu-merous body areas affected. A significant proportion of patients were undertreated, which may explain the high burden of disease observed.
CRIS-Team Scopus Importer:2022-04-15
Keywords: clinical characteristics; paediatric psoriasis; point-in-time sur-vey; psoriasis; real-world; unmet needs

Pivotal advance: Heme oxygenase 1 expression by human CD4+ T cells is not sufficient for their development of immunoregulatory capacity - Biburger, Markus; Theiner, Gabi; Schädle, Mirjam; Schuler, Gerold; Tiegs, Gisa (Journal of Leukocyte Biology, 2010)
HO-1 is the only inducible one of three isoenzymes that catalyzes the oxidative degradation of heme. HO-1 is inducible by various cellular stress factors and exerts cytoprotective and immunomodulatory effects. Recent publications demonstrated that HO-1 is constitutively expressed by CD4 CD25 T and induced in CD4 CD25 T cells upon FoxP3 transfection. Here, we investigated whether HO-1 was essential and sufficient for human T to exert immunosuppression in vitro. PGJ induced pronounced expression of HO-1 in CD4CD25 T cells without accompanying FoxP3 induction. Treatment of CD4CD25 T cells with PGJ decreased their proliferation, whereas the HO-1 inhibitor SnPP enhanced the proliferation of HO-1-expressing T, suggesting that HO-1 may modulate the proliferative capacity of T lymphocytes. HO-1 modulation by SnPP treatment of T or PGJ treatment of CD4CD25 T cells neither suppressed nor induced immune-modulatory function in these cells, respectively, as measured by responder-cell proliferation and/or IL-2 production. In summary, these data suggest that HO-1 expression by T might contribute to their typical reluctance to proliferate but does not account independently for their suppressive functions. © Society for Leukocyte Biology.
Keywords: CD4+CD25 + Tregs; Immune modulation; Proliferation; Regulatory T cells; Tolerance

Plasma-derived extracellular vesicles discriminate type-1 allergy subjects from non-allergic controls - Wagner, Nicola; Eberhardt, Martin; Vera, Julio; Cuomo, Federica; Blume, Katja; Galster, Silvia; Achenbach, Susanne; Laffert, Bernd; Kahlert, Helga; Schuler, Gerold; Berking, Carola; Baur, Andreas (World Allergy Organization Journal, 2021)
Background: Allergies are on the rise globally, with an enormous impact on affected individuals’ quality of life as well as health care resources. They cause a wide range of symptoms, from slightly inconvenient to potentially fatal immune reactions. While allergies have been described and classified phenomenologically, there is an unmet need for easily accessible biomarkers to stratify the severity of clinical symptoms. Furthermore, biomarkers marking the success of specific immunotherapy are urgently needed. Objectives: Plasma extracellular vesicles (pEV) play a role in coordinating the immune response and may be useful future biomarkers. A pilot study on differences in pEV content was carried out between patients with type I allergy, suffering from rhinoconjunctivitis with or without asthma, and voluntary non-allergic donors. Methods: We examined pEV from 38 individuals (22 patients with allergies and 16 controls) for 38 chemokines, cytokines, and soluble factors using high-throughput data mining approaches. Results: Patients with allergies had a distinct biomarker pattern, with 7 upregulated (TNF-alpha, IL-4, IL-5, IL-6, IL-17F, CCL2, and CCL17) and 3 downregulated immune mediators (IL-11, IL-27, and CCL20) in pEV compared to controls. This reduced set of 10 factors was able to discriminate controls and allergic patients better than the total array. Conclusions: The content of pEV showed potential as a target for biomarker research in allergies. Plasma EV, which are readily measurable via blood test, may come to play an important role in allergy diagnosis. In this proof-of-principle study, it could be shown that pEV's discriminate patients with allergies from controls. Further studies investigating whether the content of pEVs may predict the severity of allergic symptoms or even the induction of tolerance to allergens are needed.
CRIS-Team Scopus Importer:2021-10-08
Keywords: Allergy; Biomarkers; Extracellular vesicles-exosomes; Immune mediators; bioinformatics

Polysaccharides from European Black Elderberry Extract Enhance Dendritic Cell Mediated T Cell Immune Responses - Stich, Lena; Plattner, Stephan; McDougall, Gordon; Austin, Ceri; Steinkasserer, Alexander (International Journal of Molecular Sciences, 2022)
European black elderberry (Sambucus nigra L.) is a popular way to treat common colds or influenza infections. Mechanistically, this might be due to a direct antiviral effect or a stimulatory effect on the immune system of the host. Here, we evaluated the modulatory effects of black elderberry derived water extract (EC15) and its polysaccharide enriched fractions (CPS, BOUND, and UNBOUND) in comparison to a conventional alcoholic extract (EE25), regarding the phenotypical and functional properties of dendritic cells (DCs), which are essential cells to induce potent T cell responses. Interestingly, the water extract and its polysaccharide fractions potently induced DC maturation, while the ethanol extract did not. Moreover, the capacity to stimulate T cells by these matured DCs, as assessed using MLR assays, was statistically higher when induced by the water extracted fractions, compared to immature DCs. On the other hand, the ethanol extract EE25 did not induce T cell stimulation. Finally, the cytokine expression profiles of these DC—T cell cocultures were assessed and correlated well with increased T cell stimulation. Also, the expression of inflammatory cytokines, such as IL‐6, TNF‐α, and IFN‐γ was highly increased in the presence of the elderberry water extract EC15, and the polysaccharide enriched CPS, BOUND, and UNBOUND fractions, but not by EE25. Thus, from these data, we conclude that the polysaccharides present in water‐derived elderberry fractions induce potent immune‐modulatory effects, which represents the basis for a strong immune‐mediated response to viruses including influenza.
CRIS-Team Scopus Importer:2022-04-15
Keywords: dendritic cells; European black elderberry; polysaccharides; T cell stimulation

Pooled safety analysis from two phase III studies of secukinumab in paediatric patients with moderate-to-severe plaque psoriasis up to week 52 - Sticherling, Michael; Nikkels, A. F.; Hamza, A. M.; Kwong, P.; Ortmann, C. -E.; Papanastasiou, P.; Forrer, P.; Keefe, D. (BRITISH JOURNAL OF DERMATOLOGY, 2022)
CRIS-Team WoS Importer:2022-01-14

Poor Adherence to Self-Applied Topical Drug Treatment Is a Common Source of Low Lesion Clearance in Patients with Actinic Keratosis—A Cross-Sectional Study - Koch, Elias; Steeb, Theresa; Bender-Säbelkampf, Sophia; Busch, Dorothee; Feustel, Janina; Kaufmann, Matthias; Maronna, Andreas; Meder, Christine; Ronicke, Moritz; Toussaint, Frédéric; Wellein, Hedwig; Berking, Carola; et al. (Journal of Clinical Medicine, 2023)
Background: Many treatments for actinic keratosis (AK) have been proven efficient in clinical trials. However, patients with AK may still experience unsatisfactory therapeutic outcomes in clinical practice. Objectives: To investigate patient adherence to self-applied topical interventions for AK and to explore factors associated with adherence in a real-world setting. Methods: A cross-sectional study was conducted. Patients presenting with AK were asked to complete a self-administered questionnaire about their last topical AK treatment. Results: A total of 113 patients participated with a median age of 78.5 years (range 58–94). Fifty-four patients (47.8%) received topical diclofenac, ten (8.8%) imiquimod, nine (8%) 5-fluorouracil, nine (8%) 5-fluorouracil plus salicylic acid, and eight (7.1%) photodynamic therapy. The non-adherence rate was 46.9% (n = 53), and only 30.9% (n = 35) used the topical treatments according to the summary of product characteristics (SmPC). These subgroups were compared. Patients of the non-compliant group were significantly less informed about the application time of the specific topical intervention (p = 0.002) and adjusted the timeframe (p < 0.001) and application frequency of the therapy (p = 0.02) independently of their physician. Conversely, patients reporting a sufficient pre-treatment consultation (p = 0.019) generally complied with the SmPC compliance application. Conclusions: A thorough pre-treatment consultation can help to increase treatment adherence and ensure lesion clearance.
CRIS-Team Scopus Importer:2023-06-30
Keywords: actinic keratosis; adherence; compliance; consultation; topical treatment

Practical guidelines for the management of adverse events of the T cell engager bispecific tebentafusp - Hassel, Jessica C.; Berking, Carola; Forschner, Andrea; Gebhardt, Christoffer; Heinzerling, Lucie; Meier, Friedegund; Ochsenreither, Sebastian; Siveke, Jens; Hauschild, Axel; Schadendorf, Dirk (European Journal of Cancer, 2023)
Tebentafusp is a new T cell receptor bispecific fusion protein and the first approved treatment option for human leucocyte antigen-A*02:01 (HLA-A*02:01) metastatic uveal melanoma, with a proven benefit in overall survival versus the investigator's choice. As a first-in-class therapeutic option, this Immune mobilising monoclonal T cell receptor Against Cancer (ImmTAC) is associated with a new adverse event (AE) profile. Based on clinical experience, a national expert group discussed recommendations for tebentafusp treatment, focusing on AE management. Further topics included prerequisites for initiating tebentafusp treatment, appropriate treatment setting, and patient selection criteria. To provide guidance for treating physicians, the resulting recommendations are summarised including a model standard operating procedure for AE management. Patients in good clinical condition and with a low tumour burden are good candidates for tebentafusp treatment, particularly if treated as early as possible after the diagnosis of metastatic disease. The safety profile of tebentafusp is manageable and includes two major pathologies: cytokine release syndrome (CRS) and skin-related events. Postdose monitoring should thus focus on pyrexia and hypotension as the first symptoms of cytokine release. To minimise the risk of hypotension associated with CRS, patients should receive intravenous fluids before starting treatment. The monitoring of liver values is crucial, as patients may experience an increase in transaminases, which can even manifest as tumour lysis syndrome.
CRIS-Team Scopus Importer:2023-09-01
Keywords: Adverse event management; Bispecific; Cytokine release syndrome; Expert opinion; Immune mobilising monoclonal T cell receptor against cancer (ImmTAC); Skin toxicity; Tebentafusp; Treatment recommendation; Uveal melanoma

Preclinical evaluation of a combination of checkpoint blockade and dendritic cell vaccination against Merkel cell carcinoma - Sauerer, Tatjana; Gerer, K.; Hoyer, Stefanie; Erdmann, M.; Berking, Carola; Voll, R.; Schuler-Thurner, Beatrice; Schuler, Gerold; Schaft, Niels; Dörrie, Jan (EXPERIMENTAL DERMATOLOGY, 2021)
CRIS-Team WoS Importer:2021-05-14

Preclinical evaluation of NF-κB-triggered dendritic cells expressing the viral oncogenic driver of Merkel cell carcinoma for therapeutic vaccination - Gerer, Kerstin F.; Erdmann, Michael; Hadrup, Sine R.; Lyngaa, Rikke; Martin, Lena-Marie; Voll, Reinhard E.; Schuler-Thurner, Beatrice; Schuler, Gerold; Schaft, Niels; Hoyer, Stefanie; Dörrie, Jan (Therapeutic Advances in Medical Oncology, 2017)
BACKGROUND: Merkel cell carcinoma (MCC) is a rare but very aggressive skin tumor that develops after integration of a truncated form of the large T-antigen (truncLT) of the Merkel cell polyomavirus (MCV) into the host's genome. Therapeutic vaccination with dendritic cells (DCs) loaded with tumor antigens is an active form of immunotherapy, which intends to direct the immune system towards tumors which express the respective vaccination antigens. METHODS: Cytokine-matured monocyte-derived DCs of healthy donors and MCC patients were electroporated with mRNA encoding the truncLT. To permit major histocompatibility complex (MHC) class II next to class I presentation, we used an RNA construct in which the antigen was fused to a DCLamp sequence in addition to the unmodified antigen. To further improve their immunogenicity, the DCs were additionally activated by co-transfection with the constitutively active nuclear factor (NF)-κB activator caIKK. These DCs were used to stimulate autologous CD8+ T-cells or a mixture of CD4+ and CD8+ T-cells. Then the percentage of T-cells, specific for the truncLT, was quantified by interferon (IFN)γ ELISpot assays. RESULTS: Both the truncLT and its DCLamp-fusion were detected within the DCs by flow cytometry, albeit the latter required blocking of the proteasome. The transfection with caIKK upregulated maturation markers and induced cytokine production. After 2-3 rounds of stimulation, the T-cells from 11 out of 13 healthy donors recognized the antigen. DCs without caIKK appeared in comparison less potent in inducing such responses. When using cells derived from MCC patients, we could induce responses for 3 out of 5 patients; however, here the caIKK-transfected DCs did not display their superiority. CONCLUSION: These results show that optimized DCs are able to induce MCV-antigen-specific T-cell responses. Therapeutic vaccination with such transfected DCs could direct the immune system against MCC.
EVALuna2:34320

Predicting the response of uveal melanoma to immunotherapy with MRI assessments - Moreira, Alvaro; Saake, Marc; Schuler, Gerold; Heinzerling, Lucie (CANCER IMMUNOLOGY RESEARCH, 2019)
CRIS-Team WoS Importer:2021-10-18

Predicting the response to anti-PD1 therapy in metastatic melanoma - Heinzerling, Lucie; Kirchberger, Michael Constantin; Walter, Lisa; Schuler, Gerold (TRANSLATIONAL CANCER RESEARCH, 2016)

Prediction of melanoma evolution in melanocytic nevi via artificial intelligence: A call for prospective data (vol 119, pg 30, 2019) - Sondermann, Wiebke; Utikal, Jochen Sven; Enk, Alexander H.; Schadendorf, Dirk; Klode, Joachim; Hauschild, Axel; Weichenthal, Michael; French, Lars E.; Berking, Carola; Schilling, Bastian; Haferkamp, Sebastian; Froehling, Stefan; et al. (European Journal of Cancer, 2019)
EVALuna2:212166

Predictive value of PD-L1 based on mRNA level in the treatment of stage IV melanoma with ipilimumab - Brueggemann, C.; Kirchberger, M. C.; Goldinger, S. M.; Weide, B.; Konrad, A.; Erdmann, M.; Schadendorf, D.; Croner, R. S.; Krahenbuhl, L.; Kaehler, K. C.; Hafner, C.; Leisgang, W.; et al. (Journal of Cancer Research and Clinical Oncology, 2017)
PD-L1 is established as a predictive marker for therapy of non-small cell lung cancer with pembrolizumab. Furthermore, PD-L1 positive melanoma has shown more favorable outcomes when treated with anti-PD1 antibodies and dacarbazine compared to PD-L1 negative melanoma. However, the role of PD-L1 expression with regard to response to checkpoint inhibition with anti-CTLA-4 is not clear, yet. In addition, the lack of standardization in the immunohistochemical assessment of PD-L1 makes the comparison of results difficult. In this study, we investigated the PD-L1 gene expression with a new fully automated technique via RT-PCR and correlated the findings with the response to the anti-CTLA-4 antibody ipilimumab.Within a retrospective multi-center trial, PD-L1 gene expression was evaluated in 78 melanoma patients in a total of 111 pre-treatment tumor samples from 6 skin cancer centers and analyzed with regard to response to ipilimumab. For meaningful statistical analysis, the cohort was enriched for responders with 30 responders and 48 non-responders. Gene expression was assessed by quantitative RT-PCR after extracting mRNA from formalin-fixed paraffin embedded tumor tissue and correlated with results from immunohistochemical (IHC) stainings.The evaluation of PD-L1 expression based on mRNA level is feasible. Correlation between PD-L1 expression as assessed by IHC and RT-PCR showed varying levels of concordance depending on the antibody employed. RT-PCR should be further investigated to measure PD-L1 expression, since it is a semi-quantitative method with observer-independent evaluation. With this approach, there was no statistical significant difference in the PD-L1 expression between responders and non-responders to the therapy with ipilimumab. The evaluation of PD-L1 expression based on mRNA level is feasible. Correlation between PD-L1 expression as assessed by IHC and RT-PCR showed varying levels of concordance depending on the antibody employed. RT-PCR should be further investigated to measure PD-L1 expression, since it is a semi-quantitative method with observer-independent evaluation. With this approach, there was no statistical significant difference in the PD-L1 expression between responders and non-responders to the therapy with ipilimumab.
EVALuna2:15289

Predictors of long-term survival of stage IV melanoma patients: a multicenter DeCOG study on 539 patients from the prospective skin cancer registry ADOREG - Placke, J. M.; Mohr, P.; Bluhm, L.; Kahler, K.; Weichenthal, M.; Meier, F.; Garzarolli, M.; Gutzmer, R.; Grimmelmann, I.; Utikal, J. S.; Pfohler, C.; Herbst, R.; et al. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2022)
CRIS-Team WoS Importer:2022-09-23

Pre-incubation of corneal donor tissue with sCD83 improves graft survival via the induction of alternatively activated macrophages and tolerogenic dendritic cells - Peckert-Maier, Katrin; Schoenberg, Alfrun; Wild, Andreas; Royzman, Dmytro; Braun, Gabriele; Stich, Lena; Hadrian, Karina; Tripal, Philipp; Cursiefen, Claus; Steinkasserer, Alexander; Zinser, Elisabeth; Bock, Felix (American Journal of Transplantation, 2021)
Immune responses reflect a complex interplay of cellular and extracellular components which define the microenvironment of a tissue. Therefore, factors that locally influence the microenvironment and re-establish tolerance might be beneficial to mitigate immune-mediated reactions, including the rejection of a transplant. In this study, we demonstrate that pre-incubation of donor tissue with the immune modulator soluble CD83 (sCD83) significantly improves graft survival using a high-risk corneal transplantation model. The induction of tolerogenic mechanisms in graft recipients was achieved by a significant upregulation of Tgfb, Foxp3, II27, and II10 in the transplant and an increase of regulatory dendritic cells (DCs), macrophages (M phi) and T cells (Tregs) in eye-draining lymph nodes. The presence of sCD83 during in vitro DC and M phi generation directed these cells toward a tolerogenic phenotype leading to reduced proliferation-stimulating activity in MLRs. Mechanistically, sCD83 induced a tolerogenic M phi and DC phenotype, which favors Treg induction and significantly increased transplant survival after adoptive cell transfer. Conclusively, pre-incubation of corneal grafts with sCD83 significantly prolongs graft survival by modulating recipient M phi and DCs toward tolerance and thereby establishing a tolerogenic microenvironment. This functional strategy of donor graft pre-treatment paves the way for new therapeutic options in the field of transplantation.
CRIS-Team WoS Importer:2021-10-01

Pre-incubation of corneal donor tissue with soluble CD83 improves graft survival via the induction of pro-resolving macrophages - Peckert-Maier, Katrin; Schoenberg, Alfrun; Wild, Andreas; Royzman, Dmytro; Braun, Gabriele; Hadrian, Karina; Tripal, Philipp; Cursiefen, Claus; Steinkasserer, Alexander; Zinser, Elisabeth; Bock, Felix (WOUND REPAIR AND REGENERATION, 2022)
CRIS-Team WoS Importer:2022-09-16

Primary Biliary Cirrhosis and Granulomatous Hepatitis after Immune Checkpoint Blockade in Patients with Metastatic Melanoma: Report of 2 Cases and Literature Discussion - Ruini, Cristel; Haas, Carolin; Mastnik, Sebastian; Knott, Maximilian; French, Lars E.; Schlaak, Max; Berking, Carola (Journal of immunotherapy (Hagerstown, Md. : 1997), 2021)
Immune-related adverse events (irAEs) of immune checkpoint inhibitors can potentially affect every organ system, are sometimes challenging, and require a multidisciplinary approach. Most common irAEs are very well characterized, but some other such rare autoimmune liver diseases are probably underdiagnosed and less explored. We present here the case of a 69-year-old man with metastatic melanoma developing a severe primary biliary cirrhosis under pembrolizumab, and of a 52-year-old woman with metastatic melanoma with granulomatous hepatitis in the context of an immune-related multiorgan inflammatory reaction due to ipilimumab and nivolumab. Both cases were in part steroid refractory and required a complex diagnostic assessment and long-term therapeutic management. The liver biopsy was crucial for ensuring a correct diagnosis. Clinicians should be aware of rare liver diseases in the context of increased liver enzymes under immune checkpoint inhibitors, especially if not responding to corticosteroids. The primary diagnostic workup should localize the liver damage (biliary or parenchymal) and distinguish irAEs from other pathologic conditions such as metastasis, second benign and malignant tumors, viral hepatitis, and cholelithiasis. If in doubt, a liver biopsy should be performed. Early diagnosis and accurate assessment of hepatic adverse events is necessary for prompt and effective treatment, with reduction of inappropriate discontinuation of immunotherapy, morbidity, and mortality.
CRIS-Team Scopus Importer:2021-03-19
Keywords: granulomatous hepatitis; immune checkpoint blockade; metastatic melanoma; primary biliary cirrhosis

Primary cutaneous manifestation of systemically aggressive diffuse large B-cell lymphoma - Bender-Säbelkampf, Sophia; Spriewald, Bernd; Berking, Carola; Erdmann, Michael; Wagner, Nicola (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2022)
CRIS-Team WoS Importer:2022-09-23

PRI: Re-Analysis of a Public Mass Cytometry Dataset Reveals Patterns of Effective Tumor Treatments - Hoang, Yen; Gryzik, Stefanie; Hoppe, Ines; Rybak, Alexander; Schaedlich, Martin; Kadner, Isabelle; Walther, Dirk; Vera, Julio; Radbruch, Andreas; Groth, Detlef; Baumgart, Sabine; Baumgrass, Ria (Frontiers in Immunology, 2022)
Recently, mass cytometry has enabled quantification of up to 50 parameters for millions of cells per sample. It remains a challenge to analyze such high-dimensional data to exploit the richness of the inherent information, even though many valuable new analysis tools have already been developed. We propose a novel algorithm "pattern recognition of immune cells (PRI)" to tackle these high-dimensional protein combinations in the data. PRI is a tool for the analysis and visualization of cytometry data based on a three or more-parametric binning approach, feature engineering of bin properties of multivariate cell data, and a pseudo-multiparametric visualization. Using a publicly available mass cytometry dataset, we proved that reproducible feature engineering and intuitive understanding of the generated bin plots are helpful hallmarks for re-analysis with PRI. In the CD4(+)T cell population analyzed, PRI revealed two bin-plot patterns (CD90/CD44/CD86 and CD90/CD44/CD27) and 20 bin plot features for threshold-independent classification of mice concerning ineffective and effective tumor treatment. In addition, PRI mapped cell subsets regarding co-expression of the proliferation marker Ki67 with two major transcription factors and further delineated a specific Th1 cell subset. All these results demonstrate the added insights that can be obtained using the non-cluster-based tool PRI for re-analyses of high-dimensional cytometric data.
CRIS-Team WoS Importer:2022-06-03

Proactive Management with twice-a-week Use of topical Cal/BD Spray Foam Management extends the Effectiveness of the Treatment in Comparison to Reactive Management in Patients with Plaque Psoriasis - Stein-Gold, L.; Alonso-Llamazares, J.; Laws, P.; Perrussel, M.; Yamauchi, P.; Thoning, H.; Toxvaerd, C.; Sticherling, Michael (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2021)
CRIS-Team WoS Importer:2021-04-16

Prognosis of Patients With Primary Melanoma Stage I and II According to American Joint Committee on Cancer Version 8 Validated in Two Independent Cohorts: Implications for Adjuvant Treatment. - Garbe, Claus; Keim, Ulrike; Amaral, Teresa; Berking, Carola; Eigentler, Thomas K.; Flatz, Lukas; Gesierich, Anja; Leiter, Ulrike; Stadler, Rudolf; Sunderkötter, Cord; Tüting, Thomas; Utikal, Jochen; et al. (Journal of Clinical Oncology, 2022)
PURPOSE: The first randomized trial of adjuvant treatment with checkpoint inhibitor in stage II melanoma reported a significant reduction in risk of tumor recurrence. This study evaluates two independent data sets to further document survival probabilities for patients with primary stage I and II melanoma. PATIENTS AND METHODS: The Central Malignant Melanoma Registry (CMMR) in Germany evaluated 17,544 patients with a primary diagnosis of stage I and II melanoma from 2000 to 2015. The exploratory cohort consisted of 6,725 patients from the Center for Dermato-Oncology at the University of Tübingen, and the confirmatory cohort consisted of 10,819 patients from 11 other German centers. Survival outcomes were compared with published American Joint Committee on Cancer version 8 (AJCCv8) stage I and II survival data. RESULTS: For the two CMMR cohorts in stage IA compared with the AJCCv8 cohort, melanoma-specific survival rates at 10 years were 95.1%-95.6% versus 98%; 89.7%-90.9% versus 94% in stage IB; 80.7%-83.1% versus 88% in stage IIA; 72.0%-79.9% versus 82% in stage IIB; and 57.6%-64.7% versus 75% in stage IIC, respectively. Recurrence rates were approximately twice as high as melanoma-specific mortality rates in stages IA-IIA. CONCLUSION: The melanoma-specific survival rates in the two CMMR cohorts across stages I and II are less favorable than published in AJCCv8. This has important implications for the consideration of adjuvant treatment in this population.
EVALuna2:505688

Propagation of SARS-CoV-2 in a Closed Cell Culture Device: Potential GMP Compatible Production Platform for Live-Attenuated Vaccine Candidates under BSL-3 Conditions? - Klessing, Stephan; Peter, Antonia Sophia; Fraedrich, Kirsten; Wagner, Jannik; Kummer, Mirko; Deutschmann, Janina; Steininger, Philipp; Steibl, Hans Dieter; Überla, Klaus (Viruses, 2023)
Live-attenuated SARS-CoV-2 vaccines present themselves as a promising approach for the induction of broad mucosal immunity. However, for initial safety assessment in clinical trials, virus production requires conditions meeting Good Manufacturing Practice (GMP) standards while maintaining biosafety level 3 (BSL-3) requirements. Since facilities providing the necessary complex ventilation systems to meet both requirements are rare, we here describe a possibility to reproducibly propagate SARS-CoV-2 in the automated, closed cell culture device CliniMACS Prodigy® in a common BSL-3 laboratory. In this proof-of-concept study, we observed an approximately 300-fold amplification of SARS-CoV-2 under serum-free conditions with high lot-to-lot consistency in the infectious titers obtained. With the possibility to increase production capacity to up to 3000 doses per run, this study outlines a potential fast-track approach for the production of live-attenuated vaccine candidates based on highly pathogenic viruses under GMP-like conditions that may contribute to pandemic preparedness.
CRIS-Team Scopus Importer:2023-03-10
Keywords: CliniMACS Prodigy®; GMP; human challenge study; live-attenuated vaccines; SARS-CoV-2; virus propagation

Prospective study in bullous pemphigoid: association of high serum anti-BP180 IgG levels with increased mortality and reduced Karnofsky score - Holtsche, M. M.; Goletz, S.; Van Beek, N.; Zillikens, Detlef; Benoit, S.; Harman, K.; Walton, S.; English, J.; Sticherling, Michael; Chapman, A.; Levell, N. J.; Groves, R.; et al. (British Journal of Dermatology, 2018)
BACKGROUND: Bullous pemphigoid (BP) is a subepidermal blistering disease characterized by autoantibodies against the two hemidesmosomal proteins, BP180 (type XVII collagen) and BP230. The multicentre prospective BLISTER (Bullous Pemphigoid Steroids and Tetracyclines) trial randomized 253 patients with BP to compare the benefits and harms between initial treatment with doxycycline or prednisolone. OBJECTIVES: To analyse distinct autoantibody profiles for the prediction of the disease course in a well-characterized cohort of BP sera. METHODS: One hundred and forty-three patients of the BLISTER trial consented to participate in this serological study. Sera taken at baseline were analysed by (i) indirect immunofluorescence, (ii) anti-BP180 NC16A (16th noncollagenous domain) and anti-BP230 enzyme-linked immunosorbent assay and (iii) immunoblotting with various substrates. Results were then linked with clinical parameters including age, Karnofsky score, number of blisters, related adverse events and mortality. RESULTS: Disease activity correlated with immunoglobulin (Ig)G anti-BP180 levels but not with levels of anti-BP230 IgG and anti-BP180 IgE. High levels of both anti-BP180 IgG and anti-BP230 IgG were associated with a low Karnofsky score. The presence of anti-BP230 IgG was more frequent in older patients. Those with higher total IgE serum levels suffered from fewer adverse events. Higher IgG anti-BP180 levels were associated with an increased 1-year mortality rate. CONCLUSIONS: Analysis of the autoantibody profile is not only of diagnostic relevance but may also be helpful in predicting the course of the disease.
EVALuna2:34763

Proteasomes generate spliced epitopes by two different mechanisms and as efficiently as non-spliced epitopes - Ebstein, F.; Textoris-Taube, K.; Keller, C.; Golnik, R.; Vigneron, N.; Van Den Eynde, B. J.; Schuler-Thurner, Beatrice; Schadendorf, D.; Lorenz, F. K. M.; Uckert, W.; Urban, S.; Lehmann, A.; et al. (Scientific Reports, 2016)
Proteasome-catalyzed peptide splicing represents an additional catalytic activity of proteasomes contributing to the pool of MHC-class I-presented epitopes. We here biochemically and functionally characterized a new melanoma gp100 derived spliced epitope. We demonstrate that the gp100(mel)47-52/40-42 antigenic peptide is generated in vitro and in cellulo by a not yet described proteasomal condensation reaction. gp100(mel)47-52/40-42 generation is enhanced in the presence of the ?5i/LMP7 proteasome-subunit and elicits a peptide-specific CD8(+) T cell response. Importantly, we demonstrate that different gp100(mel)-derived spliced epitopes are generated and presented to CD8(+) T cells with efficacies comparable to non-spliced canonical tumor epitopes and that gp100(mel)-derived spliced epitopes trigger activation of CD8(+) T cells found in peripheral blood of half of the melanoma patients tested. Our data suggest that both transpeptidation and condensation reactions contribute to the frequent generation of spliced epitopes also in vivo and that their immune relevance may be comparable to non-spliced epitopes.
EVALuna2:19591

Pruritus in Psoriasis - Correlation to the Severity of the clinical appearance of the Skin? - Achterberg, Fritz Leonard; Kremer, Andreas; Sticherling, Michael (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-05-17

Psoriasis and autoimmunity - Sticherling, Michael (Autoimmunity Reviews, 2016)
Psoriasis is one of the most common chronic inflammatory human skin diseases. Though clinically well characterized, the exact etiological and pathogenic mechanisms are still not known in detail. Current knowledge indicates distinct overlap to other inflammatory as well as autoimmune disorders. However, the one or more relevant autoantigens could not be characterized so-far. On the other side, several autoimmune diseases were shown to be associated with psoriasis. In addition, serological autoimmune phenomena, namely diverse circulating specific autoantibodies could be demonstrated in the past. A matter of current debate is if psoriasis is a primary autoimmune disease or secondarily evolving into autoimmunity as seen in other chronic inflammatory diseases. Related to this aspect is the concept of autoinflammation versus autoimmunity where psoriasis shares mechanisms of both entities. Though T-cells remain among the most important cellular players in the pathogenesis of psoriasis and current therapeutic strategies successfully target these cells or their products irrespective of these concepts, autoimmunity if relevant will add to the treatment armamentarium by using protective and prophylactic antigen-specific modalities.
EVALuna2:19626

Psoriasis as a Manifestation of an Immune Reconstitution in Two Patients with Hepatitis C Treated with Ledipasvir/Sofosbuvir - Heppt, Franz; Sticherling, Michael (Acta Dermato-Venereologica, 2017)
EVALuna2:34349

Psoriasis capitis and seborrhoic eczema of scalp diseases - Sticherling, Michael (Hautarzt, 2017)
The scalp may be affected by various diseases with equally varying manifestations. Erythema and scaling is often accompanied by agonizing itch. Scalp psoriasis and seborrheic eczema represent the most frequent diseases, which can be differentiated into classical cases; however, overlap and similarities are seen. Sharply demarcated erythematosquamous plaques across the natural hairline in psoriasis are opposed to blurred dark-red erythema and yellowish, greasy scales in seborrheic eczema. Whereas with the latter diffuse alopecia may frequently be found, hair loss is rarely seen in psoriasis and may also be related to therapeutic agents. Treatment is based on acuity as well as extent of disease and individual life quality aspects of the patients. It is mainly based on topical corticosteroids, combined with vitamin D derivatives in psoriasis and antimycotic agents in seborrheic eczema. In severe cases and widespread psoriatic disease, systemic treatment may be necessary, including the classic agents methotrexate, fumarates and ciclosporin as well as biologicals. Systemic treatment of seborrheic eczema is rarely necessary and resides on corticosteroids, antimycotic agents and vitamin A derivatives. In addition, intensive counseling of patients on the necessity of consequent and long-term treatment as well as use of mild skin care products is mandatory.
EVALuna2:34347

Psoriasis in children: a single center analysis - Heppt, Franz; Raap, J.; Sticherling, Michael (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-05-17

Psoriasis in children: a single-centre analysis - Heppt, Franz; Raap, J.; Sticherling, Michael (2017)
EVALuna2:34339

Psoriasis in routine clinical care: Complete skin clearance rates with guselkumab increase through week 52-Results from the real-life PERSIST study - Hoffmann, Matthias; Sticherling, Michael; Korge, Bernhard; Mortazawi, Dariusch; Personke, Yvonne; Gomez, Mario; Wegner, Sven; Gerdes, Sascha (JOURNAL OF THE AMERICAN ACADEMY OF DERMATOLOGY, 2021)
CRIS-Team WoS Importer:2021-08-27

Psoriasis - Occurrence and Reality: Disease of the Psoriasis Group - Leupolz, S.; Sticherling, Michael (2017)
EVALuna2:34353

Psoriasis vulgaris as Manifestation of Immune Reconstitution in Patients with Hepatitis C under Treatment with Ledipasvir/Sofosbuvir - Heppt, Franz; Sticherling, Michael (2017)
EVALuna2:34350

Psoriatic arthritis epidemiology, comorbid disease profiles and risk factors: Results from a claims database analysis - Rech, Jürgen; Sticherling, Michael; Stoessel, Daniel; Biermann, Mona H.C.; Häberle, Benjamin M.; Reinhardt, Maximilian (Rheumatology Advances in Practice, 2020)
Objective. Psoriasis is a systemic inflammatory disease often accompanied by comorbidities, including metabolic syndrome, cardiovascular diseases and depression. Up to 41% of psoriasis patients develop psoriatic arthritis (PsA), making it one of the most relevant manifestations. A large health claims data set was analysed to determine the rate of PsA development in psoriasis patients. Furthermore, comorbid disease profiles of psoriasis patients with or without PsA were compared, and potential risk factors for the development of PsA were identified. Methods. This was a non-interventional, retrospective analysis of anonymized insurance health claims data using a subset of the Institute of Applied Health Research Berlin (InGef) database. The primary outcome was the prevalence and incidence of diagnosed PsA among psoriasis patients in Germany. Risk factors for the development of PsA in psoriasis patients were determined by conditional logistic regression analysis. Results. The cumulative percentage of patients with existing psoriasis developing concomitant PsA over 4 years was 3.44%, with a mean time to diagnosis of PsA of 1.5 years. Psoriasis patients diagnosed with acute rheumatism (odds ratio: 2.93, 95% CI=1.76, 4.86; P<0.001) or pain in unspecific joints (odds ratio: 1.74, 95% CI=1.01, 2.99; P=0.047) showed an increased risk for development of PsA later on. Interestingly, fewer than half of the patients with concomitant PsA consulted a rheumatologist. Conclusions. Unspecific arthritic symptoms are likely to precede PsA diagnoses and can develop soon after onset of psoriasis, with accumulating risk over time. There is a high unmet need for early rheumatological assessment of psoriasis patients.
CRIS-Team Scopus Importer:2020-12-04
Keywords: Comorbid disease; Epidemiology; Incidence; Insurance health claims data; PsA; Psoriasis; Risk factors

Psoriatic Arthritis - Epidemiology, Incidence Rate in Psoriasis Patients, Comorbidity Profiles and Risk Factor Analysis - Rech, Jürgen; Sticherling, Michael; Biermann, Mona; Haeberle, Benjamin; Reinhardt, Maximilian (ARTHRITIS & RHEUMATOLOGY, 2019)
CRIS-Team WoS Importer:2020-02-07

PU.1 controls fibroblast polarization and tissue fibrosis - Wohlfahrt, Thomas; Rauber, Simon; Uebe, Steffen; Luber, Markus; Soare, Alina; Ekici, Arif Bülent; Weber, Stefanie; Matei, Alexandru-Emil; Chen, Chih-Wei; Maier, Christiane; Karouzakis, Emmanuel; Kiener, Hans P.; et al. (Nature, 2019)
Fibroblasts are polymorphic cells with pleiotropic roles in organ morphogenesis, tissue homeostasis and immune responses. In fibrotic diseases, fibroblasts synthesize abundant amounts of extracellular matrix, which induces scarring and organ failure. By contrast, a hallmark feature of fibroblasts in arthritis is degradation of the extracellular matrix because of the release of metalloproteinases and degrading enzymes, and subsequent tissue destruction. The mechanisms that drive these functionally opposing pro-fibrotic and pro-inflammatory phenotypes of fibroblasts remain unknown. Here we identify the transcription factor PU.1 as an essential regulator of the pro-fibrotic gene expression program. The interplay between transcriptional and post-transcriptional mechanisms that normally control the expression of PU.1 expression is perturbed in various fibrotic diseases, resulting in the upregulation of PU.1, induction of fibrosis-associated gene sets and a phenotypic switch in extracellular matrix-producing pro-fibrotic fibroblasts. By contrast, pharmacological and genetic inactivation of PU.1 disrupts the fibrotic network and enables reprogramming of fibrotic fibroblasts into resting fibroblasts, leading to regression of fibrosis in several organs.
EVALuna2:35476

Quantitative and Qualitative Changes of Bone in Psoriasis and Psoriatic Arthritis Patients - Kocijan, Roland; Englbrecht, Matthias; Haschka, Judith; Simon, David; Kleyer, Arnd; Finzel, Stephanie; Kraus, Sebastian; Resch, Heinrich; Muschitz, Christian; Engelke, Klaus; Sticherling, Michael; Rech, Jürgen; et al. (Journal of Bone and Mineral Research, 2015)
Psoriatic arthritis (PsA) is a chronic inflammatory disease characterized by periarticular bone loss and new bone formation. Current data regarding systemic bone loss and bone mineral density (BMD) in PsA are conflicting. The aim of this study was to evaluate bone microstructure and volumetric BMD (vBMD) in patients with PsA and psoriasis. We performed HR-pQCT scans at the ultradistal and periarticular radius in 50 PsA patients, 30 psoriasis patients, and 70 healthy, age- and sex-related controls assessing trabecular bone volume (BV/TV), trabecular number (Tb.N), inhomogeneity of the trabecular network, cortical thickness (Ct.Th), and cortical porosity (Ct.Po), as well as vBMD. Trabecular BMD (Tb.BMD, p = 0.021, 12.0%), BV/TV (p = 0.020, -11.9%), and Tb.N (p = 0.035, 7.1%) were significantly decreased at the ultradistal radius and the periarticular radius in PsA patients compared to controls. In contrast, bone architecture of the ultradistal radius and periarticular radius was similar in patients with psoriasis and healthy controls. Duration of skin disease was associated with low BV/TV and Tb.N in patients with PsA. These data suggest that trabecular BMD and bone microstructure are decreased in PsA patients. The observation that duration of skin disease determines bone loss in PsA supports the concept of subclinical musculoskeletal disease in psoriasis patients. © 2015 American Society for Bone and Mineral Research.
EVALuna2:10104

Quercetin induces an immunoregulatory phenotype in maturing human dendritic cells - Michalski, Julia; Deinzer, Anja; Stich, Lena; Zinser, Elisabeth; Steinkasserer, Alexander; Knippertz, Ilka (Immunobiology, 2020)
The aryl hydrocarbon receptor (AhR) is an environmental sensor and ligand-activated transcription factor that is critically involved in the regulation of inflammatory responses and the induction of tolerance by modulating immune cells. As dendritic cells (DCs) express high AhR levels, they are efficient to induce immunomodulatory effects after being exposed to AhR-activating compounds derived from the environment or diet. To gain new insights into the molecular targets following AhR-activation in human monocyte-derived (mo)DCs, we investigated whether the natural AhR ligand quercetin or the synthetic ligand 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) modulates the function of human moDCs regarding their capability to prime naïve T cells or to migrate. As only quercetin, but not TCDD, impaired T cell activation and migration of LPS-matured DCs (LPS-DCs), we analyzed the mode of action of quercetin on moDCs in more detail. Here, we found a specific down-regulation of the immunomodulatory molecule CD83 through the direct binding of the activated AhR to the CD83 promoter. Furthermore, treatment of LPS-DCs with quercetin resulted in a reduced production of the pro-inflammatory cytokine IL-12p70 and in an increased expression of the immunoregulatory molecules disabled adaptor protein (Dab) 2, immunoglobulin-like transcript (ILT)-3, ILT4, ILT5 as well as ectonucleotidases CD39 and CD73, thereby inducing a tolerogenic phenotype in quercetin-treated maturing DCs. Overall, these data demonstrate that quercetin represents a potent immunomodulatory agent to alter human DC phenotype and function, shifting the immune balance from inflammation to resolution.
CRIS-Team Scopus Importer:2020-03-10
Keywords: Aryl hydrocarbon receptor; Dendritic cells; Quercetin; Regulatory T cells; TCDD; Tolerance

Radiosensitization by BRAF inhibitor therapy-mechanism and frequency of toxicity in melanoma patients - Hecht, Markus; Zimmer, L.; Loquai, C.; Weishaupt, C.; Gutzmer, R.; Schuster, B.; Gleisner, S.; Schulze, B.; Goldinger, S. M.; Berking, C.; Forschner, A.; Clemens, P.; et al. (Annals of Oncology, 2015)
Recent evidence suggests that ionizing radiation may be associated with unexpected side-effects in melanoma patients treated with concomitant BRAF inhibitors. A large multicenter analysis was carried out to generate reliable safety data and elucidate the mechanism.A total of 161 melanoma patients from 11 European skin cancer centers were evaluated for acute and late toxicity, of whom 70 consecutive patients received 86 series of radiotherapy with concomitant BRAF inhibitor therapy. To further characterize and quantify a possible radiosensitization by BRAF inhibitors, blood samples of 35 melanoma patients were used for individual radiosensitivity testing by fluorescence in situ hybridization of chromosomal breaks after ex vivo irradiation.With radiotherapy and concomitant BRAF inhibitor therapy the rate of acute radiodermatitis >=2° was 36% and follicular cystic proliferation was seen in 13% of all radiotherapies. Non-skin toxicities included hearing disorders (4%) and dysphagia (2%). Following whole-brain radiotherapy, rates of radiodermatitis >=2° were 44% and 8% (P < 0.001) for patients with and without BRAF inhibitor therapy, respectively. Concomitant treatment with vemurafenib induced acute radiodermatitis >=2° more frequently than treatment with dabrafenib (40% versus 26%, P = 0.07). In line with these findings, analysis of chromosomal breaks ex vivo indicated significantly increased radiosensitivity for patients under vemurafenib (P = 0.004) and for patients switched from vemurafenib to dabrafenib (P = 0.002), but not for patients on dabrafenib only. No toxicities were reported after stereotactic treatment.Radiotherapy with concomitant BRAF inhibitor therapy is feasible with an acceptable increase in toxicity. Vemurafenib is a more potent radiosensitizer than dabrafenib.
EVALuna2:18285

Rapid development of bilateral necroses of the upper extremity - Kirchberger, Michael C.; Erfurt-Berge, Cornelia (Journal der Deutschen Dermatologischen Gesellschaft, 2017)
EVALuna2:35400

Rapid Response of a multilocular metastatic Merkel Cell Carcinoma with an unclear Primarius to Avelumab - Bender-Säbelkampf, Sophia; Berking, Carola; Erdmann, M. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2021)
CRIS-Team WoS Importer:2021-09-24

Rapid Response of locally distinct CD30 positive primary cutaneous anaplastic large T-Cell Lymphoma under Brentuximab Vedotin - Bender-Säbelkampf, Sophia; Berking, Carola; Erdmann, Michael (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2021)
CRIS-Team WoS Importer:2021-09-24

Rasches Ansprechen eines lokal ausgeprägten CD30-positiven primär kutanen anaplastisch-großzelligen T-Zell-Lymphoms unter Brentuximab-Vedotin - Bender-Säbelkampf, Sophia; Berking, Carola; Erdmann, Michael (Abstractband anlässlich des 31. Deutschen Hautkrebskongresses (ADO-Jahrestagung) 8.–11. September 2021, 2021)
CD30-Positivität gilt nicht nur als Indikator aktivierter Lymphozyten, sondern wird auch in der Lymphom-Entstehung diskutiert. Wir stellen den Fall einer 73-jährigen Landwirtin mit einer 2005 systemisch behandelten chronisch lymphatischen B-Zell-Leukämie (B-CLL) im Binet-Stadium B sowie mit einem neu aufgetretenen, rasch wachsenden, fazialen, CD30-positiven, primär kutanen anaplastisch-großzelligen T-Zell-Lymphom vor. An denselben Stellen waren vormals multiple Basalzell- und Plattenepithelkarzinome sowie ein primär kutanes B-Zell-Lymphom vom Keimzentrumstyp exzidiert worden. Histologisch zeigten sich nun plasmazytoide Zellen sowie teils großzellig blastär imponierende, CD30-positive Zellen. Bei immunhistologisch diagnostiziertem Lymphom der Haut ist die Abgrenzung eines primär kutanen gegenüber einem sekundär kutanen Lymphom im Rahmen der klinisch-pathologischen Korrelation inklusive bildgebender Verfahren zu treffen. Hierbei sind die fehlende Expression von ALK1, CD15 und EMA sowie die Histomorphologie mit häufig landkartenartiger Nekrose inmitten eines eosinophilenreichen Zellinfiltrats wichtige Indikatoren für ein primär kutanes CD30-positives primär kutanes anaplastisch-großzelliges T-Zell-Lymphom. In der Ausbreitungsdiagnostik mittels CT Hals-Thorax-Abdomen bestätigte sich die bereits im Rahmen der B-CLL bekannte Lymphadenopathie. Differentialblutbild sowie Blutausstrich verblieben bis auf die Leukämie-bedingte Lymphozytose unauffällig. Daher wurde von einer Knochenmarkspunktion und Lymphknotenbiopsie zum Ausschluss einer Richter-Transformation und dadurch ermöglichten kutanen T-Zell-Erkrankung abgesehen. Aufgrund der Befundausprägung sowie der bereits stattgehabten Chemotherapie im Rahmen der B-CLL entschieden wir uns für die Einleitung einer intravenösen, gewichtsadaptierten CD30-gerichteten-Antikörpertherapie mittels Brentuximab-Vedotin. Bereits nach dem 1. Zyklus kam es zu einer signifikanten Tumormassenreduktion sowie nach 6 Zyklen zu einer vollständigen Abheilung. Parallel zum klinischen Ansprechen fand sich ein hämatoonkologisch nicht behandlungsbedürftiger Anstieg der Leukozyten im Rahmen der B-CLL von 65.000 auf 115.000. Bemerkenswerterweise zeigte sich zudem ein präinterventionell histologisch gesichertes Basalzellkarzinom links retroaurikulär unter der onkologischen Systemtherapie gegen das kutane T-Zell-Lymphom klinisch regredient.<br

Rasches Ansprechen eines multilokulär metastasierten Merkelzellkarzinoms bei unklarem Primarius auf Avelumab - Bender-Säbelkampf, Sophia; Berking, Carola; Erdmann, Michael (Abstractband anlässlich des 31. Deutschen Hautkrebskongresses (ADO-Jahrestagung) 8.–11. September 2021, 2021)
Die seit 2017 zugelassene PD-L1-Antikörper-Therapie mit Avelumab zeigt beim metastasierten Merkelzellkarzinom eine objektive Ansprechrate von 62,1 % mit 13,8 % Vollremissionen und ein 5-Jahres-Überleben von 51 % bei lokaler, 35 % bei lymphonodaler und 14 % bei viszeraler Metastasierung. Wir stellen einen 84-jährigen Patienten mit innerhalb von 3 Monaten am Capillitium rasch wachsenden, multiplen, in Größe und Aussehen gleichartig imponierenden Hautmetastasen eines Merkelzellkarzinoms bei unklarem Primarius vor. In der Schnittbildgebung zeigten sich zusätzlich hepatische und ossäre Metastasen. Trotz initialer Bedenken seitens des betagten Patienten aufgrund bestehender Komorbiditäten wie chronischer Niereninsuffizienz Stadium III-IV, insulinpflichtigem Diabetes, koronarer Herzkrankheit sowie metabolischem Syndrom entschied er sich bei erhaltener Selbstständigkeit und einem ECOG-Status von 1 für die Systemtherapie mit Avelumab, die er gewichtsadaptiert alle 2 Wochen erhielt. Sowohl die Lokal- als auch Fernmetastasierung ergab im klinischen sowie radiologischen Verlauf ein rasches Ansprechen mit einer Vollremission nach 8 Gaben. Bei stark juckenden, erythematösen Papeln wurde ein bullöses Pemphigoid serologisch und (immun-)histologisch ausgeschlossen. Es zeigten sich irritierte ekzematoide Veränderungen, welches wir bei undulierenden renalen Retentionswerten im Rahmen der chronischen Niereninsuffizienz Stadium III-IV einordneten. Bei entsprechender topischer glukokortikoid-haltiger Therapie wurde die Systemtherapie bislang ohne autoimmunvermittelte Nebenwirkungen gut vertragen. Interessanterweise bildete sich zusätzlich die vorbekannte aktinische Feldkanzerisierung im Laufe der Immuntherapie weitestgehend zurück. Dies könnte theoretisch über beschriebene MHC-Klasse I-bindende Neoantigene bei aktinischen Keratosen und damit einhergehender T-Zell-Rezeptor-Erkennung erklärt werden. Schlussfolgerung: Auch im fortgeschrittenen Alter mit entsprechenden Komorbiditäten stellt die Immuncheckpoint-Blockade mit anti-PD-L1-Antikörpern eine Option mit hoher Erfolgsaussicht und guter Verträglichkeit beim fortgeschrittenen Merkelzellkarzinom auch bei unklarem Primarius dar.<br

Real-world analysis of dabrafenib plus trametinib in patients with BRAFV600-mutated melanoma brain metastases - Berking, Carola; Schadendorf, D.; Weichenthal, M.; Eigentler, T.; Mohr, P.; Schober, K.; Kiecker, F.; Loquai, C.; Debus, D.; Gutzmer, R.; Leiter-Stoeppke, U. (ANNALS OF ONCOLOGY, 2020)
CRIS-Team WoS Importer:2020-10-30

Real-world clinical outcomes of pembrolizumab for advanced melanoma in the German ADOREG skin cancer registry - Mohr, P.; Scherrer, E.; Alar, V.; Assaf, C.; Beissert, S.; Berking, Carola; Eigentler, T.; Grimmelmann, I.; Gutzmer, R.; Haferkamp, S.; Hassel, J. C.; Hauschild, A.; et al. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2022)
CRIS-Team WoS Importer:2022-09-23

Real-world data on the effectiveness, safety and drug survival of dupilumab: an analysis from the TREATgermany registry - Stoelzl, Dora; Sander, Nicole; Heratizadeh, Annice; Haufe, Eva; Harder, Inken; Abraham, Susanne; Heinrich, Luise; Kleinheinz, Andreas; Wollenberg, Andreas; Weisshaar, Elke; Schaekel, Knut; Ertner, Konstantin; et al. (British Journal of Dermatology, 2022)
CRIS-Team Scopus Importer:2022-11-11

Real-world effectiveness of guselkumab in patients with psoriasis: Health-related quality of life and efficacy data from the noninterventional, prospective, German multicenter PERSIST trial - Gerdes, Sascha; Bräu, Beate; Hoffmann, Matthias; Korge, Bernhard; Mortazawi, Dariusch; Wiemers, Franca; Wegner, Sven; Personke, Yvonne; Gomez, Mario; Sticherling, Michael (Journal of Dermatology, 2021)
Psoriasis is a common, chronic inflammatory skin disorder negatively impacting health-related quality of life (HRQoL). Guselkumab, targeting interleukin-23 (IL-23), is an approved biologic therapy for psoriasis. PERSIST is an ongoing prospective, noninterventional, long-term, German multicenter study evaluating the effect of guselkumab on HRQoL, and its efficacy and safety in patients with moderate-to-severe psoriasis in a real-world setting. The primary endpoint is the proportion of patients with a Dermatology Life Quality Index (DLQI) score ≤ 1 at week 28. Of 303 patients enrolled and treated with guselkumab, mean age and disease duration were 49.7 and 21.0 years, respectively, and 51.2% (n = 155) of patients had received ≥1 prior biologic therapy. Mean baseline DLQI score was 13.7, and mean symptom and sign scores in the Psoriasis Symptoms and Signs Diary (PSSD) were 51.9 and 60.8, respectively. Baseline Psoriasis Area Severity Index (PASI) and body surface area (%) scores were 16.4 and 27.5. Following 28 weeks of guselkumab treatment, the mean DLQI score decreased to 2.8, and 56.8% of patients (n = 150) achieved DLQI ≤ 1. Mean PSSD symptom and sign scores also improved, decreasing to 12.5 and 15.9, respectively. At week 28, PASI 90 response was 55.3%; significant improvement was observed in patients with psoriasis in difficult-to-treat areas. Overall, analyses demonstrated that guselkumab was effective in the real-world setting, as measured by HRQoL and skin improvements, even in patients with a high burden of disease and those who have received multiple biologic therapies. No new safety signals were observed.
CRIS-Team Scopus Importer:2021-09-17
Keywords: anogenital; guselkumab; palmoplantar; psoriasis; quality of life; RWE; scalp

Real-world evidence from the non-interventional, prospective, German multicentre PERSIST study of patients with psoriasis after 1 year of treatment with guselkumab - Gerdes, S.; Asadullah, K.; Hoffmann, M.; Korge, B.; Mortazawi, D.; Wegner, S.; Personke, Y.; Gomez, M.; Sticherling, Michael (Journal of the European Academy of Dermatology and Venereology, 2022)
Background: PERSIST was a prospective, non-interventional, long-term, German multicentre study of patients with moderate-to-severe psoriasis receiving guselkumab, an approved monoclonal antibody that binds to the p19 subunit of interleukin (IL)-23, in a real-world setting. Objectives: Evaluation of the efficacy and safety of guselkumab, and its effect on health-related quality of life (HRQoL), in patients with moderate-to-severe psoriasis who have received 52 weeks of treatment. Methods: Patients (≥18 years old) were prescribed guselkumab as per routine clinical practice. End points assessed include Psoriasis Area and Severity Index (PASI), Physician's Global Assessment (PGA), target Nail Psoriasis Severity Index (NAPSI), and the Dermatology Life Quality Index (DLQI). Results: Overall, 303 patients were enrolled and treated with guselkumab. Mean disease duration was 21.0 years, and 77.2% and 51.2% of patients had received ≥1 prior conventional systemic or ≥1 prior biologic therapy, respectively. Mean PASI score decreased from 16.4 at baseline to 3.0 by Week (W) 28, and further decreased to 2.4 by W52, while the proportion of patients achieving an absolute PASI score of ≤1 increased from 1.3% at baseline, to 50.8% at W28 and to 58.4% by W52. PASI90 and PASI100 responses also showed marked improvements between W28 and W52, regardless of biologic treatment history. Clearance of psoriatic skin was observed in difficult-to-treat areas, with the percentage of patients achieving a PGA score ≤1 increasing between W28 and W52. Guselkumab improved HRQoL; mean DLQI score decreased from 13.7 at baseline to 2.8 by W28, and further decreased to 2.4 by W52. At W52, 64.6% of patients achieved a DLQI score ≤1. The cumulative probability of drug survival was 92.4% at W52. Conclusions: Guselkumab is efficacious and well tolerated regardless of previous biologic therapies, comorbidities or psoriasis manifestation in difficult-to-treat areas. No new safety signals were observed.
CRIS-Team Scopus Importer:2022-06-03

Real world experience in low-dose ipilimumab in combination with PD-1 blockade in advanced melanoma patients - Kirchberger, Michael Constantin; Moreira, Alvaro; Erdmann, Michael; Schuler, Gerold; Heinzerling, Lucie (Oncotarget, 2018)
Dual immune-checkpoint blockade with the anti-PD-1 antibody nivolumab (1 mg/kg) and standard-dose ipilimumab (3 mg/kg) is the mainstay of immunotherapy in advanced melanoma and it is approved since 2016. However, severe side effects (grade 3/4) occur in up to 60% of the patients. Recently, clinical trials have shown similar anti-tumor activity with a more favorable toxicity profile in patients treated with low-dose ipilimumab (1 mg/kg) and standard-dose pembrolizumab (2 mg/kg). In this study we report on the real-world experience of this dosing regime in advanced melanoma patients not eligible for clinical trials. A total of 33 patients with metastatic melanoma (24 with cutaneous and 9 with uveal melanoma) were assessed, retrospectively. Brain metastases were present in 33% of the patients and lactate dehydrogenase was elevated in 70%. Overall response rates were 38% and 0% in cutaneous melanoma and uveal melanoma respectively. Median overall survival was not reached in cutaneous melanoma and was 18 months in uveal melanoma. In 18% of the patients at least one treatment-related severe adverse event was observed. Our observation that the combination of standard dose pembrolizumab and low-dose ipilimumab has a favorable toxicity profile yet anti-tumor activity comparable to the approved standard-dose combination regime in advanced patients not suitable for enrollment in clinical trials is encouraging.
EVALuna2:34415

Real-World Therapy with Pembrolizumab: Outcomes and Surrogate Endpoints for Predicting Survival in Advanced Melanoma Patients in Germany - Mohr, Peter; Scherrer, Emilie; Assaf, Chalid; Bender, Marc; Berking, Carola; Chandwani, Sheenu; Eigentler, Thomas; Grimmelmann, Imke; Gutzmer, Ralf; Haferkamp, Sebastian; Hassel, Jessica C.; Hauschild, Axel; et al. (Cancers, 2022)
Knowledge on the real-world characteristics and outcomes of pembrolizumab-treated advanced melanoma patients in Germany and on the value of different real-world endpoints as surrogates for overall survival (OS) is limited. A sample of 664 pembrolizumab-treated patients with advanced melanoma from the German registry ADOReg was used. We examined OS, real-world progression-free survival (rwPFS), real-world time to next treatment (rwTtNT), and real-world time on treatment (rwToT). Spearman’s rank and iterative multiple imputation (IMI)-based correlation coefficients were computed between the OS and the rwPFS, rwTtNT, and rwToT and reported for the first line of therapy and the overall sample. The median OS was 30.5 (95%CI 25.0–35.4) months, the rwPFS was 3.9 months (95%CI 3.5–4.9), the rwTtNT was 10.7 months (95%CI 9.0–12.9), and the rwToT was 6.2 months (95%CI 5.1–6.8). The rwTtNT showed the highest correlation with the OS based on the IMI (rIMI = 0.83), Spearman rank correlations (rs = 0.74), followed by the rwToT (rIMI = 0.74 and rs = 0.65) and rwPFS (rIMI = 0.69 and rs = 0.56). The estimates for the outcomes and correlations were similar for the overall sample and those in first-line therapy. The median OS was higher compared to recent real-world studies, supporting the effectiveness of pembrolizumab in regular clinical practice. The rwTtNT may be a valuable OS surrogate, considering the highest correlation was observed with the OS among the investigated real-world endpoints.
CRIS-Team Scopus Importer:2022-04-15
Keywords: advanced melanoma; overall survival (OS); pembrolizumab; real-world evidence; surrogate endpoint; time to next treatment (rwTtNT)

Regulation of autoantibody activity by the IL-23-TH17 axis determines the onset of autoimmune disease. - Pfeifle, René; Rothe, Tobias; Ipseiz, Natacha; Scherer, Hans U.; Culemann, Stephan; Harre, Ulrike; Ackermann, Jochen; Seefried, Martina; Kleyer, Arnd; Uderhardt, Stefan; Haugg, Benjamin; Huebert, Axel J.; et al. (Nature Immunology, 2017)
The checkpoints and mechanisms that contribute to autoantibody-driven disease are as yet incompletely understood. Here we identified the axis of interleukin 23 (IL-23) and the TH17 subset of helper T cells as a decisive factor that controlled the intrinsic inflammatory activity of autoantibodies and triggered the clinical onset of autoimmune arthritis. By instructing B cells in an IL-22- and IL-21-dependent manner, TH17 cells regulated the expression of β-galactoside α2,6-sialyltransferase 1 in newly differentiating antibody-producing cells and determined the glycosylation profile and activity of immunoglobulin G (IgG) produced by the plasma cells that subsequently emerged. Asymptomatic humans with rheumatoid arthritis (RA)-specific autoantibodies showed identical changes in the activity and glycosylation of autoreactive IgG antibodies before shifting to the inflammatory phase of RA; thus, our results identify an IL-23-TH17 cell-dependent pathway that controls autoantibody activity and unmasks a preexisting breach in immunotoleranc

Reply: Intra-patient heterogeneity of BRAF mutation status: fact or fiction? - Heinzerling, Lucie; Schuler, Gerold; Hartmann, Arndt; Schneider-Stock, Regine (British Journal of Cancer, 2014)
EVALuna2:6657

Reporting Quality of Studies Developing and Validating Melanoma Prediction Models: An Assessment Based on the TRIPOD Statement - Kaiser, Isabelle; Diehl, Katharina; Heppt, Markus; Mathes, Sonja; Pfahlberg, Annette Bettina; Steeb, Theresa; Uter, Wolfgang; Gefeller, Olaf (Healthcare, 2022)
Transparent and accurate reporting is essential to evaluate the validity and applicability of risk prediction models. Our aim was to evaluate the reporting quality of studies developing and validating risk prediction models for melanoma according to the TRIPOD (Transparent Reporting of a multivariate prediction model for Individual Prognosis Or Diagnosis) checklist. We included studies that were identified by a recent systematic review and updated the literature search to ensure that our TRIPOD rating included all relevant studies. Six reviewers assessed compliance with all 37 TRIPOD components for each study using the published “TRIPOD Adherence Assessment Form”. We further examined a potential temporal effect of the reporting quality. Altogether 42 studies were assessed including 35 studies reporting the development of a prediction model and seven studies reporting both development and validation. The median adherence to TRIPOD was 57% (range 29% to 78%). Study components that were least likely to be fully reported were related to model specification, title and abstract. Although the reporting quality has slightly increased over the past 35 years, there is still much room for improvement. Adherence to reporting guidelines such as TRIPOD in the publication of study results must be adopted as a matter of course to achieve a sufficient level of reporting quality necessary to foster the use of the prediction models in applications.
CRIS-Team Scopus Importer:2022-02-04
Keywords: Melanoma; Prediction models; reporting quality; TRIPOD

Resolution of synovitis and arrest of catabolic and anabolic bone changes in patients with psoriatic arthritis by IL-17A blockade with secukinumab: results from the prospective PSARTROS study - Kampylafka, Eleni; D'Oliveira, Isabelle; Linz, Christina; Lerchen, Veronika; Stemmler, Fabian; Simon, David; Englbrecht, Matthias; Sticherling, Michael; Rech, Juergen; Kleyer, Arnd; Schett, Georg; Hueber, Axel (Arthritis Research & Therapy, 2018)
BACKGROUND: Although the effects of interleukin-17A (IL-17A) inhibition on the signs and symptoms of psoriatic arthritis (PsA) are well defined, little is known about its impact of local inflammatory and structural changes in the joints. The PSARTROS study was designed to elucidate the effects of IL-17A inhibition on inflammation and bone changes in joints affected by PsA. METHODS: This was a prospective open-label study in 20 patients with active PsA receiving 24 weeks of treatment with the IL-17A inhibitor secukinumab. Magnetic resonance imaging (MRI), power Doppler ultrasound (PDUS), and high-resolution peripheral quantitative computer tomography (HR-pQCT) of the hands were performed at baseline and after 24 weeks to assess synovitis, periarticular inflammation, bone erosion, enthesiophyte formation, and bone structure. Demographic and clinical measures of joint disease (DAPSA and DAS28-ESR), skin disease (PASI and BSA), and composite measures (minimal disease activity, or MDA) were also recorded. RESULTS: Treatment with secukinumab led to significant improvement of signs and symptoms of PsA; 46% reached MDA and 52% DAPSA low disease activity. MRI synovitis (P = 0.034) and signal in PDUS (P = 0.030) significantly decreased after 24 weeks of treatment. Bone erosions in MRI and HR-pQCT and enthesiophytes in the HR-pQCT did not show any progression, and structural integrity and functional bone strength remained stable. CONCLUSIONS: IL-17 inhibition by secukinumab over 24 weeks led to a significant decrease of synovial inflammation and no progression of catabolic and anabolic bone changes in the joints of patients with PsA. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT02483234 , June 26, 2015; retrospectively registered.
EVALuna2:34447

Response to First-Line Treatment with Immune-Checkpoint Inhibitors in Patients with Advanced Cutaneous Squamous Cell Carcinoma: A Multicenter, Retrospective Analysis from the German ADOReg Registry - Haist, Maximilian; Stege, Henner; Lang, Berenice Mareen; Tsochataridou, Aikaterini; Salzmann, Martin; Mohr, Peter; Schadendorf, Dirk; Ugurel, Selma; Placke, Jan Malte; Weichenthal, Michael; Gutzmer, Ralf; Leiter, Ulrike; et al. (Cancers, 2022)
Cutaneous squamous cell carcinoma (cSCC) is a common malignancy of the skin and has an overall favorable outcome, except for patients with an advanced stage of the disease. The efficacy of checkpoint inhibitors (CPI) for advanced cSCC has been demonstrated in recent clinical studies, but data from real-world cohorts and trial-ineligible cSCC patients are limited. We retrospectively investigated patients with advanced cSCC who have been treated with CPI in a first-line setting at eight German skin cancer centers registered within the multicenter registry ADOReg. Clinical outcome parameters including response, progression-free (PFS) and overall survival (OS), time-to-next-treatment (TTNT), and toxicity were analyzed and have been stratified by the individual immune status. Among 39 evaluable patients, the tumor response rate (rwTRR) was 48.6%, the median PFS was 29.0 months, and the median OS was not reached. In addition, 9 patients showed an impaired immune status due to immunosuppressive medication or hematological diseases. Our data demonstrated that CPI also evoked tumor responses among immunocompromised patients (rwTRR: 48.1 vs. 50.0%), although these responses less often resulted in durable remissions. In line with this, the median PFS (11 vs. 40 months, p = 0.059), TTNT (12 months vs. NR, p = 0.016), and OS (29 months vs. NR, p < 0.001) were significantly shorter for this patient cohort. CPI therapy was well tolerated in both subcohorts with 15% discontinuing therapy due to toxicity. Our real-world data show that first-line CPI therapy produced strong and durable responses among patients with advanced cSCC. Immunocompromised patients were less likely to achieve long-term benefit from anti-PD1 treatment, despite similar tumor response rates.
CRIS-Team Scopus Importer:2022-12-02
Keywords: advanced cutaneous squamous cell carcinoma; cemiplimab; checkpoint inhibitor therapy; immunosuppression; real-world data; response durability

Retrospective analysis of autoimmune bullous diseases in Middle Franconia - Sollfrank, Lukas; Schönfelder, Valerie; Sticherling, Michael (Frontiers in Immunology, 2023)
Introduction: Autoimmune bullous diseases (AIBDs) are a group of rare cutaneous disorders affecting cornified skin and mucous membranes. They are characterized by tense or flaccid blistering and erosions due to autoantibodies against desmosomal and hemidesmosomal structural proteins of the skin. This group of disorders can be divided into those of pemphigoid and those of pemphigus diseases. If left untreated, these autoimmune diseases can cause serious or even life-threatening complications such as loss of fluid, superinfections or impaired food intake. Due to modern standardized serological assays, the diagnosis of AIBDs can usually be confirmed in combination with their clinical appearance. Whereas for a long time corticosteroids were the major players in the treatment of these diseases, with the approval of rituximab and other immunosuppressive agents, the therapy has increasingly improved. Methods: In this study, we aimed to investigate epidemiologic and clinical features as well as diagnostics and therapy of bullous autoimmune diseases in Middle Franconia, a governorate within the German federal state of Bavaria. Patients diagnosed or treated because of a AIBDs between 01.04.2013 and 31.03.2019 at the dermatological department of the university hospital Erlangen were included in this retrospective study (n = 242). Patients were either diagnosed for the first time (n=176) or the diagnosis has been confirmed (n=66) at the department. The respective incidence was calculated among the 176 subjects who had been diagnosed at the center in this period. Data was taken from patient records and analyzed with Microsoft® Excel. The evaluation included the diagnoses of pemphigus vulgaris (PV), pemphigus foliaceus (PF), bullous pemphigoid (BP), mucous membrane pemphigoid (MMP), linear IgA dermatosis (LAD), epidermolysis bullosa acquisita (EBA), and dermatitis herpetiformis (DH). Results: This study shows that the incidence of each AIBDs in Middle Franconia is low and comparable (PV, PF, LAD, EBA) or lower (BP, MMP, DH) than in other studies and regions. BP is the most common newly diagnosed AIBD in Middle Franconia. Discussion: Due to the chronic and sometimes severe course of AIBDs, repeated in-house treatments are often necessary. To date, mainly topically and systemically applied corticosteroids in combination with immunomodulators are used as first-line therapy.
CRIS-Team Scopus Importer:2023-11-03
Keywords: autoimmune bullous dermatoses; bullous dermatoses; bullous pemphigod; epidemiology; pemphigoid diseases; pemphigus diseases

Retrospective interactive rigid fusion of 18F-FDG-PET and CT: Additional diagnostic information in melanoma patients - Römer, Wolfgang; Nömayr, Anton; Greess, Holger; Fiedler, Ekkehard; Platsch, Günter; Schuler-Thurner, Beatrice; Pfahlberg, Annette; Hothorn, Torsten; Schuler, Gerold; Hornegger, Joachim; Bautz, Werner; Kuwert, Torsten (Nuklearmedizin-Nuclear Medicine, 2006)
Aim: This study investigates whether interactive rigid fusion of routine PET and CT data improves localization, detection and characterization of lesions compared to separate reading. For this purpose, routine PET and CT scans of patients with metastases from malignant melanoma were used. Patients, methods: In 34 patients with histologically confirmed malignant melanoma, FDG-PET and spiral CT were performed using clinical standard protocols. For all of these patients, gold standard was available. Clinical and radiological follow-up identified 82 lesions as definitely pathological. Two board-certified nuclear medicine physicians and two board-certified radiologists analyzed PET and CT images independently from each other. For each patient up to 32 anatomical regions (24 lymph node regions, 8 extranodular regions) were systematically classified. Discordant areas were interactively analyzed in manually and rigidly registered images using a commercially available fusion tool. No side-by-side reading was performed. Results: Image fusion disclosed that the evaluation of the PET images alone led to a mislocalization in 26 of 91 focally FDG enhancing lesions. The overall sensitivities of PET, CT, and image fusion were 85, 88, and 94%, respectively; the overall specificities of PET, CT and image fusion were 98, 95 and 100%, respectively. Image fusion exhibited statistically significant higher specificity values as compared with CT. Ten definitely malignant sites were false-negative in CT, but could be detected by PET. On the other hand, twelve metastases were false-negative in PET, but could be detected by CT. These included two lesions, which had a clear correlate on the PET image when the fused images were evaluated. On the whole, registration of the PET and CT images yielded additional diagnostic information in 44% of the definitely malignant lesions. Conclusion: Retrospective image fusion of independently obtained PET and CT data is particularly valuable in exactly lodizing foci of abnormal FDG uptake and improves the detection of metastases of malignant melanoma. © 2006 Schattauer GmbH.

Risk Factors for Regional and Systemic Metastases in Patients with Sentinel Lymph Node-negative Melanoma - Erdmann, Michael; Sigler, Dominic; Uslu, Ugur; Göhl, Jonas; Grützmann, Robert; Schuler, Gerold; Schellerer, Vera (Anticancer Research, 2018)
BACKGROUND: Sentinel lymph node status is a strong prognostic factor in melanoma. However, up to 21% of sentinel lymph node-negative patients develop locoregional and distant metastases during follow-up. AIM: To analyze risk factors for locoregional and distant metastasis in patients with sentinel lymph node-negative melanoma. PATIENTS AND METHODS: A total of 545 patients underwent sentinel lymph node biopsy (SNB) between 2005 and 2013 at our hospital. Data for 449 patients with a negative SNB were analyzed regarding risk factors and development of metastases. Follow-up was performed until 2016. RESULTS: A total of 72 SNB-negative patients developed metastases, including 25 (34.7%) distant and 47 (63.3%) locoregional metastases. Locoregional metastases occurred earlier compared to distant metastases (with a mean of 24.2 and 23.5 months for regional lymph node and cutaneous metastases, respectively, vs. 31.4 months for distant metastases). Patients with metastases despite negative SNB had a greater tumor thickness (p=0.001), a higher rate of nodular melanoma (p=0.001), ulceration (p<0.001), and were older (p=0.05) compared to SNB-negative patients without subsequent metastases. Out of SNB-negative patients, 16% developed metastases. CONCLUSION: Close clinical follow-up including sonography of the draining lymph node region is mandatory for melanoma patients regardless of SNB status.
EVALuna2:203619

Risk Factors for Relapse after Intentional Discontinuation of Immune Checkpoint Inhibitors in Melanoma Patients - Persa, Oana D.; Schatton, Kerstin; Rübben, Albert; Berking, Carola; Erdmann, Michael; Schlaak, Max; Mauch, Cornelia; Steeb, Theresa (Journal of Immunotherapy, 2021)
Immune checkpoint inhibitors (ICIs) have tremendously changed the therapeutic landscape of melanoma since they are associated with a durable response, allowing for intentional discontinuation of therapy after complete or partial remission. However, a subset of patients develops a relapse after cessation of ICI treatment and may not respond to reinduction of ICIs. The aim of the present study was to identify risk factors for relapse after intentional discontinuation of ICI therapy. Patients with intentional discontinuation of ICI therapy for metastatic or unresectable melanoma from 5 German university hospitals were analyzed retrospectively. Clinicopathologic and follow-up data of 87 patients were collected and analyzed by univariate and multivariate Cox proportional-hazards models. The following parameters were associated with relapse after cessation of ICI treatment in the univariate Cox regression analysis: concurrent radiotherapy and ICI, best overall response, and presence of brain metastases. Duration of treatment, type of primary tumor, body mass index, programmed-death ligand 1 expression, and lactate dehydrogenase levels did not significantly influence the risk for relapse. In the multivariate analysis, partial remission [hazard ratio 4.217 (95% confidence interval: 1.424-12.49), P=0.009] and stable disease [3.327 (1.204-9.19), P=0.02] were associated with a significant decrease in progression-free survival compared with complete remission. Concurrent radiotherapy and ICI [3.619 (1.288-10.168), P=0.015] are additional independent risk factors for decreased progression-free survival upon ICI discontinuation, whereas the presence of brain metastasis did not reach statistical significance on multivariate analysis.
CRIS-Team Scopus Importer:2021-06-25
Keywords: checkpoint inhibitor therapy; melanoma; nivolumab; pembrolizumab; radiotherapy

RNA sequencing of collecting duct renal cell carcinoma suggests an interaction between miRNA and target genes and a predominance of deregulated solute carrier genes - Wach, Sven; Taubert, Helge; Weigelt, Katrin; Hase, Nora; Köhn, Marcel; Misiak, Danny; Hüttelmaier, Stefan; Stöhr, Christine G.; Kahlmeyer, Andreas; Haller, Florian; Vera, Julio; Hartmann, Arndt; et al. (Cancers, 2020)
Collecting duct carcinoma (CDC) is a rare renal cell carcinoma subtype with a very poor prognosis. There have been only a few studies on gene expression analysis in CDCs. We compared the gene expression profiles of two CDC cases with those of eight normal tissues of renal cell carcinoma patients. At a threshold of |log2fold-change| ≥ 1, 3349 genes were upregulated and 1947 genes were downregulated in CDCs compared to the normal samples. Pathway analysis of the deregulated genes revealed that cancer pathways and cell cycle pathways were most prominent in CDCs. The most upregulated gene was keratin 17, and the most downregulated gene was cubilin. Among the most downregulated genes were four solute carrier genes (SLC3A1, SLC9A3, SLC26A7, and SLC47A1). The strongest negative correlations between miRNAs and mRNAs were found between the downregulated miR-374b-5p and its upregulated target genes HIST1H3B, HK2, and SLC7A11 and between upregulated miR-26b-5p and its downregulated target genes PPARGC1A, ALDH6A1, and MARC2. An upregulation of HK2 and a downregulation of PPARGC1A, ALDH6A1, and MARC2 were observed at the protein level. Survival analysis of the cancer genome atlas (TCGA) dataset showed for the first time that low gene expression of MARC2, cubilin, and SLC47A1 and high gene expression of KRT17 are associated with poor overall survival in clear cell renal cell carcinoma patients. Altogether, we identified dysregulated protein-coding genes, potential miRNA-target interactions, and prognostic markers that could be associated with CDC.
CRIS-Team Scopus Importer:2020-01-10
Keywords: Collecting duct carcinoma; RNA sequencing; Solute carrier proteins

RNA-transfection of gamma/delta T cells with a chimeric antigen receptor or an alpha/ss T-cell receptor: a safer alternative to genetically engineered alpha/ss T cells for the immunotherapy of melanoma - Harrer, D.; Simon, B.; Fujii, S. I.; Kanako, S.; Uslu, Ugur; Schuler, Gerold; Gerer, K. F.; Hoyer, S.; Dörrie, Jan; Schaft, Niels (2017)
EVALuna2:34308

RNA-transfection of γ/δ T cells with a chimeric antigen receptor or an α/β T-cell receptor: a safer alternative to genetically engineered α/β T cells for the immunotherapy of melanoma - Harrer, Dennis C.; Simon, Bianca; Fujii, Shin-Ichiro; Shimizu, Kanako; Uslu, Ugur; Schuler, Gerold; Gerer, Kerstin F.; Hoyer, Stefanie; Dörrie, Jan; Schaft, Niels (BMC Cancer, 2017)
BACKGROUND: Adoptive T-cell therapy relying on conventional T cells transduced with T-cell receptors (TCRs) or chimeric antigen receptors (CARs) has caused substantial tumor regression in several clinical trials. However, genetically engineered T cells have been associated with serious side-effects due to off-target toxicities and massive cytokine release. To obviate these concerns, we established a protocol adaptable to GMP to expand and transiently transfect γ/δ T cells with mRNA. METHODS: PBMC from healthy donors were stimulated using zoledronic-acid or OKT3 to expand γ/δ T cells and bulk T cells, respectively. Additionally, CD8+ T cells and γ/δ T cells were MACS-isolated from PBMC and expanded with OKT3. Next, these four populations were electroporated with RNA encoding a gp100/HLA-A2-specific TCR or a CAR specific for MCSP. Thereafter, receptor expression, antigen-specific cytokine secretion, specific cytotoxicity, and killing of the endogenous γ/δ T cell-target Daudi were analyzed. RESULTS: Using zoledronic-acid in average 6 million of γ/δ T cells with a purity of 85% were generated from one million PBMC. MACS-isolation and OKT3-mediated expansion of γ/δ T cells yielded approximately ten times less cells. OKT3-expanded and CD8+ MACS-isolated conventional T cells behaved correspondingly similar. All employed T cells were efficiently transfected with the TCR or the CAR. Upon respective stimulation, γ/δ T cells produced IFNγ and TNF, but little IL-2 and the zoledronic-acid expanded T cells exceeded MACS-γ/δ T cells in antigen-specific cytokine secretion. While the cytokine production of γ/δ T cells was in general lower than that of conventional T cells, specific cytotoxicity against melanoma cell lines was similar. In contrast to OKT3-expanded and MACS-CD8+ T cells, mock-electroporated γ/δ T cells also lysed tumor cells reflecting the γ/δ T cell-intrinsic anti-tumor activity. After transfection, γ/δ T cells were still able to kill MHC-deficient Daudi cells. CONCLUSION: We present a protocol adaptable to GMP for the expansion of γ/δ T cells and their subsequent RNA-transfection with tumor-specific TCRs or CARs. Given the transient receptor expression, the reduced cytokine release, and the equivalent cytotoxicity, these γ/δ T cells may represent a safer complementation to genetically engineered conventional T cells in the immunotherapy of melanoma (Exper Dermatol 26: 157, 2017, J Investig Dermatol 136: A173, 2016).
EVALuna2:34316

Role of Nuclear Factor (Erythroid-Derived 2)-Like 2 Signaling for Effects of Fumaric Acid Esters on Dendritic Cells - Hammer, Anna; Waschbisch, Anne; Knippertz, Ilka; Zinser, Elisabeth; Berg, Johannes; Joerg, Stefanie; Kuhbandner, Kristina; David, Christina; Pi, Jingbo; Bayas, Antonios; Lee, De-Hyung; Haghikia, Aiden; et al. (Frontiers in Immunology, 2017)
To date, the intracellular signaling pathways involved in dendritic cell (DC) function are poorly understood. The antioxidative transcription factor nuclear factor (erythroid-derived 2)-like 2 (Nrf2) has been shown to affect maturation, function, and subsequent DC-mediated T cell responses of murine and human DCs. In experimental autoimmune encephalomyelitis (EAE), as prototype animal model for a T helper cell-mediated autoimmune disease, antigen presentation, cytokine production, and costimulation by DCs play a major role. We explore the role of Nrf2 in DC function, and DC-mediated T cell responses during T cell-mediated autoimmunity of the central nervous system using genetic ablation and pharmacological activation in mice and men to corroborate our data in a translational setting. In murine and human DCs, monomethyl fumarate induced Nrf2 signaling inhibits DC maturation and DC-mediated T cell proliferation by reducing inflammatory cytokine production and expression of costimulatory molecules. In contrast, Nrf2-deficient DCs generate more activated T helper cells (Th1/Th17) but fewer regulatory T cells and foster T cell proliferation. Transfer of DCs with Nrf2 activation during active EAE reduces disease severity and T cell infiltration. Our data demonstrate that Nrf2 signaling modulates autoimmunity in murine and human systems via inhibiting DC maturation and function thus shedding further light on the mechanism of action of antioxidative stress pathways in antigen-presenting cells.
EVALuna2:22557

Rough hypercuboid based supervised clustering of miRNAs - Paul, Sushmita; Vera González, Julio (Molecular Biosystems, 2015)
The microRNAs are small, endogenous non-coding RNAs found in plants, animals, and some viruses, which function in RNA silencing and post-transcriptional regulation of gene expression. It is suggested by various genome-wide studies that a substantial fraction of miRNA genes is likely to form clusters. The coherent expression of the miRNA clusters can then be used to classify samples according to the clinical outcome. In this regard, a new clustering algorithm, termed as rough hypercuboid based supervised attribute clustering (RH-SAC), is proposed to find such groups of miRNAs. The proposed algorithm is based on the theory of rough set, which directly incorporates the information of sample categories into the miRNA clustering process, generating a supervised clustering algorithm for miRNAs. The effectiveness of the new approach is demonstrated on several publicly available miRNA expression data sets using support vector machine. The so-called B.632+ bootstrap error estimate is used to minimize the variability and biasedness of the derived results. The association of the miRNA clusters to various biological pathways is also shown by doing pathway enrichment analysis.
EVALuna2:19519

S100A8 BUT NOT S100A9 LEVEL IS RELATED TO THE EXTENT OF EROSIVE BONE DAMAGE IN PSORIATIC ARTHRITIS PATIENTS - Simon, David; Nas, K.; Faustini, F.; Kleyer, Arnd; Haschka, J.; Englbrecht, Matthias; Hueber, Axel; Kocijan, R.; Sticherling, Michael; Schett, Georg; Rech, Jürgen (2016)
EVALuna2:13430

S1-guideline atypical fibroxanthoma (AFX) and pleomorphic dermal sarcoma (PDS) - Helbig, Doris; Ziemer, Mirjana; Dippel, Edgar; Erdmann, Michael; Hillen, Uwe; Leiter, Ulrike; Mentzel, Thomas; Osterhoff, Georg; Ugurel, Selma; Utikal, Jochen; von Bubnoff, Dagmar; Weishaupt, Carsten; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2022)
Atypical fibroxanthoma (AFX) and pleomorphic dermal sarcoma (PDS) are rare cutaneous neoplasms representing histomorphological, genetic as well as epigenetic variants of a disease spectrum. Both tumors typically manifest as nonspecific, often ulcerated, skin- to flesh-colored nodules in chronically sun-damaged skin of elderly male patients. AFX is a rather well demarcated, often rapidly growing tumor. PDS tumors are poorly circumscribed and are characterized by aggressive infiltrative growth. Fast as well as slow growth behavior has been reported for both tumors. Histologically, both are composed of spindle-shaped and epithelioid tumor cells with pleomorphic nuclei as well as atypical multinucleated giant cells. Atypical mitoses are common. In contrast to AFX, PDS involves relevant parts of the subcutis and shows areas of tumor necrosis and/or perineural infiltration. Due to the poorly differentiated nature of AFX/PDS (Grade 3), histopathologically similar cutaneous sarcomas, undifferentiated carcinomas, melanomas and other diseases have to be excluded by immunohistochemical analysis. The treatment of choice is micrographically controlled surgery. In cases of AFX, a cure can be assumed after complete excision. Local recurrence rates are low as long as PDS tumors are surgically removed with a safety margin of 2 cm. Metastasis is rare and mostly associated with very thick or incompletely excised tumors; it mainly affects the skin and lymph nodes. Distant metastasis is even more rare. No approved and effective systemic therapy has been established.
CRIS-Team Scopus Importer:2022-02-25

S1-guideline cutaneous and subcutaneous leiomyosarcoma - Helbig, Doris; Dippel, Edgar; Erdmann, Michael; Frisman, Alexander; Kage, Paula; Leiter, Ulrike; Mentzel, Thomas; Seidel, Clemens; Weishaupt, Carsten; Ziemer, Mirjana; Ugurel, Selma (Journal der Deutschen Dermatologischen Gesellschaft, 2023)
Superficial leiomyosarcomas (LMS) are rare skin cancers (2–3% of cutaneous sarcomas) that originate from dermally located hair follicle muscles, dartos or areolar muscles (cutaneous/dermal LMS), or from vascular muscle cells of the subcutaneous adipose tissue (subcutaneous LMS). These superficial LMS are distinct from LMS of the deep soft tissues. Leiomyosarcomas are typically localized at the lower extremities, trunk or capillitium, and present as painful, erythematous to brownish nodules. Diagnosis is made by histopathology. The treatment of choice for primary LMS is complete (R0) microscopically controlled excision, with safety margins of 1 cm in dermal LMS, and 2 cm in subcutaneous LMS, if possible. Non-resectable or metastatic LMS require individual treatment decisions. After R0 resection with 1 cm safety margins, the local recurrence rate of dermal LMS is very low, and metastasis is very rare. Subcutaneous LMS, very large, or incompletely excised LMS recur and metastasize more frequently. For this reason, clinical follow-up examinations are recommended every six months for cutaneous LMS, and every three months for subcutaneous LMS within the first two years (in subcutaneous LMS including locoregional lymph node sonography). Imaging such as CT/MRI is indicated only in primary tumors with special features, recurrences, or already metastasized tumors.
CRIS-Team Scopus Importer:2023-04-21

S1-Leitlinie dermales und subkutanes Leiomyosarkom - Helbig, Doris; Dippel, Edgar; Erdmann, Michael; Frisman, Alexander; Kage, Paula; Leiter, Ulrike; Mentzel, Thomas; Seidel, Clemens; Weishaupt, Carsten; Ziemer, Mirjana; Ugurel, Selma (Journal der Deutschen Dermatologischen Gesellschaft, 2023)
CRIS-Team Scopus Importer:2023-05-26

S2k guideline: Diagnosis and management of cutaneous lupus erythematosus - Part 1: Classification, diagnosis, prevention, activity scores - Worm, Margitta; Zidane, Miriam; Eisert, Lisa; Fischer-Betz, Rebecca; Foeldvari, Ivan; Guenther, Claudia; Iking-Konert, Christof; Kreuter, Alexander; Mueller-Ladner, Ulf; Nast, Alexander; Ochsendorf, Falk; Schneider, Matthias; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2021)
CRIS-Team WoS Importer:2021-08-27

S2k guideline: Diagnosis and management of cutaneous lupus erythematosus – Part 2: Therapy, risk factors and other special topics - Worm, Margitta; Zidane, Miriam; Eisert, Lisa; Fischer-Betz, Rebecca; Foeldvari, Ivan; Gunther, Claudia; Iking-Konert, Christof; Kreuter, Alexander; Muller-Ladner, Ulf; Nast, Alexander; Ochsendorf, Falk; Schneider, Matthias; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2021)
CRIS-Team Scopus Importer:2021-08-13

S2k Guideline for the diagnosis and treatment of mucous membrane pemphigoid - Hofmann, Silke C.; Gunther, Claudia; Bockle, Barbara C.; Didona, Dario; Ehrchen, Jan; Gaskins, Matthew; Geerling, Gerd; Glaser, Regine; Hadaschik, Eva; Hampl, Monika; Habkamp, Pia; Jackowski, Jochen; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2022)
Mucous membrane pemphigoid (MMP) is a pemphigoid disease with predominant mucous membrane involvement. It mainly affects the mucous membranes of the mouth, eyes, nose and pharynx, but also the larynx, trachea, esophagus, genital and perianal regions. The manifestation of the disease covers a wide spectrum from gingival erythema and single oral lesions to severe tracheal strictures that obstruct breathing and conjunctival scarring with marked visual impairment and, not infrequently, blindness. In addition to a clinical picture of predominant mucosal involvement, diagnosis is based on direct immunofluorescence of a peri-lesional biopsy and serology. The main target antigen is BP180 (collagen XVII), and reactivity with laminin 332 is associated with malignancy in approximately 25 % of MMP patients. The treatment of MMP is challenging. On the one hand, due to the involvement of different mucous membranes, good interdisciplinary cooperation is required; on the other hand, due to the rarity of the disease, no randomized controlled clinical trials are available. The aim of this guideline is to present the clinical picture, including severity and scoring systems, and to give guidance for diagnosing and treating this complex disease. In MMP, interdisciplinary cooperation plays an essential role as well as the prompt diagnosis and initiation of adequate therapy in order to avoid irreversible damage to the mucous membranes with serious complications.
CRIS-Team WoS Importer:2022-11-25

S2k guideline for the diagnosis of pemphigus vulgaris/foliaceus and bullous pemphigoid - Schmidt, Enno; Goebeler, Matthias; Hertl, Michael; Sardy, Miklos; Sitaru, Cassian; Eming, Ruediger; Hofmann, Silke C.; Hunzelmann, Nicolas; Kern, Johannes S.; Kramer, Harald; Orzechowski, Hans-Dieter; Pfeiffer, Christiane; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2015)
EVALuna2:19565

S2k guidelines for the treatment of pemphigus vulgaris/foliaceus and bullous pemphigoid: 2019 update - Schmidt, Enno; Sticherling, Michael; Sárdy, Miklós; Eming, Rüdiger; Goebeler, Matthias; Hertl, Michael; Hofmann, Silke C.; Hunzelmann, Nicolas; Kern, Johannes S.; Kramer, Harald; Nast, Alexander; Orzechowski, Hans Dieter; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2020)
CRIS-Team Scopus Importer:2020-05-26

S2k guidelines for the treatment of pemphigus vulgaris/foliaceus and bullous pemphigoid - Eming, Ruediger; Sticherling, Michael; Hofmann, Silke C.; Hunzelmann, Nicolas; Kern, Johannes S.; Kramer, Harald; Pfeiffer, Christiane; Schuster, Volker; Zillikens, Detlef; Goebeler, Matthias; Hertl, Michael; Nast, Alexander; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2015)
EVALuna2:19564

S2k guidelines for the treatment of psoriasis in children and adolescents – Short version part 1 - Eisert, Lisa; Augustin, Matthias; Bach, Sabine; Dittmann, Martin; Eiler, Renate; Fölster-Holst, Regina; Gerdes, Sascha; Hamm, Henning; Höger, Peter; Horneff, Gerd; von Kiedrowski, Ralph; Philipp, Sandra; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2019)
The present guidelines are aimed at residents and board-certified physicians in the fields of dermatology, pediatrics, pediatric dermatology and pediatric rheumatology as well as policymakers and insurance funds. They were developed by dermatologists and pediatric dermatologists in collaboration with pediatric rheumatologists using a formal consensus process (S2k). The guidelines highlight topics such as disease severity, quality of life, treatment goals as well as problems associated with off-label drug therapy in children. Trigger factors and diagnostic aspects are discussed. The primary focus is on the various topical, systemic and UV-based treatment options available and includes recommendations for use and treatment algorithms. Other aspects addressed herein include vaccinations in children and adolescents with psoriasis as well as various disease subtypes such as guttate psoriasis, diaper psoriasis, pustular psoriasis and psoriatic arthritis. Finally, we also provide recommendations for imaging studies and the diagnostic workup to rule out tuberculosis prior to initiating systemic treatment. Note: This article constitutes part 1 of the Sk2 guidelines for the treatment of psoriasis in children and adolescents. Part 2 will be published in the next issue. It contains chapters on UV therapy, systemic treatment, tonsillectomy and antibiotics, vaccinations, guttate psoriasis, psoriatic arthritis, complementary medicine, as well as imaging studies and diagnostic workup to rule out tuberculosis prior to systemic treatment.
CRIS-Team Scopus Importer:2019-08-30

S2k guidelines for the treatment of psoriasis in children and adolescents - Short version part 2. - Eisert, Lisa; Augustin, Matthias; Bach, Sabine; Dittmann, Martin; Eiler, Renate; Foelster-Holst, Regina; Gerdes, Sascha; Hamm, Henning; Hoeger, Peter; Horneff, Gerd; Von Kiedrowski, Ralph; Philipp, Sandra; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2019)
The present guidelines are aimed at residents and board-certified physicians in the fields of dermatology, pediatrics, pediatric dermatology and pediatric rheumatology as well as policymakers and insurance funds. They were developed by dermatologists and pediatric dermatologists in collaboration with pediatric rheumatologists using a formal consensus process (S2k). The guidelines highlight topics such as disease severity, quality of life, treatment goals as well as problems associated with off-label drug therapy in children. Trigger factors and diagnostic aspects are discussed. The primary focus is on the various topical, systemic and UV-based treatment options available and includes recommendations for use and treatment algorithms. Other aspects addressed herein include vaccinations in children and adolescents with psoriasis as well as various disease subtypes such as guttate psoriasis, diaper psoriasis, pustular psoriasis and psoriatic arthritis. Finally, we also provide recommendations for imaging studies and the diagnostic workup to rule out tuberculosis prior to initiating systemic treatment. Note: This article constitutes part 2 of the Sk2 guidelines for the treatment of psoriasis in children and adolescents. Part 1 was published in last month's issue. It contained introductory remarks and addressed aspects of diagnosis and topical treatment.
EVALuna2:212834

S2k-Leitlinie zur Diagnostik und Therapie des kutanen Lupus erythematodes – Teil 1: Klassifikation, Diagnostik, Prävention und Aktivitätsscores - Worm, Margitta; Zidane, Miriam; Eisert, Lisa; Fischer-Betz, Rebecca; Foeldvari, Ivan; Günther, Claudia; Iking-Konert, Christof; Kreuter, Alexander; Müller-Ladner, Ulf; Nast, Alexander; Ochsendorf, Falk; Schneider, Matthias; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2021)
CRIS-Team Scopus Importer:2021-09-17

S2k-Leitlinie zur Therapie der Psoriasis bei Kindern und Jugendlichen – Kurzfassung Teil 1 - Eisert, Lisa; Augustin, Matthias; Bach, Sabine; Dittmann, Martin; Eiler, Renate; Fölster-Holst, Regina; Gerdes, Sascha; Hamm, Henning; Höger, Peter; Horneff, Gerd; von Kiedrowski, Ralph; Philipp, Sandra; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2019)
CRIS-Team Scopus Importer:2019-08-30

S2k-Leitlinie zur Therapie der Psoriasis bei Kindern und Jugendlichen - Kurzfassung Teil 2. - Eisert, Lisa; Augustin, Matthias; Bach, Sabine; Dittmann, Martin; Eiler, Renate; Fölster-Holst, Regina; Gerdes, Sascha; Hamm, Henning; Höger, Peter; Horneff, Gerd; von Kiedrowski, Ralph; Philipp, Sandra; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2019)
Diese Leitlinie richtet sich an Assistenz- und Fachärzte der Dermatologie, Pädiatrie, Kinderdermatologie und Kinderrheumatologie sowie an Kostenträger und politische Entscheidungsgremien. Die Leitlinie wurde im formellen Konsensusverfahren (S2k) von Dermatologen und Kinderdermatologen unter Einbindung von Kinderrheumatologen erstellt. Die Leitlinie stellt einen Überblick über Schweregrad, Lebensqualität und Therapieziele mit Erläuterung der Off-Label-Problematik im Kindesalter dar. Es werden Diagnosestellung und Triggerfaktoren erläutert. Der Schwerpunkt der Leitlinie liegt auf der Darstellung der verschiedenen topischen Therapien, UV-Therapien und systemischen Therapieoptionen mit Abbildung der Empfehlungen zur Anwendung der Therapien sowie Therapiealgorithmen. Darüber hinaus wird im Kontext auf Impfungen bei Psoriasis im Kindesalter sowie auf verschiedene Sonderformen wie Psoriasis guttata, Windelpsoriasis, Psoriasis pustulosa und Psoriasisarthritis eingegangen. Auch werden Empfehlungen zu Tuberkulosediagnostik und Röntgenuntersuchung vor Systemtherapie gegebe
EVALuna2:212833

S2k-Leitlinie zur Therapie des Pemphigus vulgaris/foliaceus und des bullösen Pemphigoids: 2019 Update - Schmidt, Enno; Sticherling, Michael; Sárdy, Miklós; Eming, Rüdiger; Goebeler, Matthias; Hertl, Michael; Hofmann, Silke C.; Hunzelmann, Nicolas; Kern, Johannes S.; Kramer, Harald; Nast, Alexander; Orzechowski, Hans Dieter; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2020)
CRIS-Team Scopus Importer:2020-05-22

S3 guideline "actinic keratosis and cutaneous squamous cell carcinoma"- update 2023, part 1: treatment of actinic keratosis, actinic cheilitis, cutaneous squamous cell carcinoma in situ (Bowen's disease), occupational disease and structures of care - Heppt, Markus; Leiter, Ulrike; Steeb, Theresa; Alter, Mareike; Amaral, Teresa; Bauer, Andrea; Bechara, Falk G.; Becker, Jürgen C.; Breitbart, Eckhard W.; Breuninger, Helmut; Diepgen, Thomas; Dirschka, Thomas; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2023)
Actinic keratosis (AK) are common lesions in light-skinned individuals that can potentially progress to cutaneous squamous cell carcinoma (cSCC). Both conditions may be associated with significant morbidity and constitute a major disease burden, especially among the elderly. To establish an evidence-based framework for clinical decision making, the guideline “actinic keratosis and cutaneous squamous cell carcinoma” was updated and expanded by the topics cutaneous squamous cell carcinoma in situ (Bowen's disease) and actinic cheilitis. The guideline is aimed at dermatologists, general practitioners, ear nose and throat specialists, surgeons, oncologists, radiologists and radiation oncologists in hospitals and office-based settings, as well as other medical specialties, policy makers and insurance funds involved in the diagnosis and treatment of patients with AK and cSCC. A separate guideline exists for patients and their relatives. In this part, we will address aspects relating to AK, actinic cheilitis, Bowen's disease, occupational disease and care structure
EVALuna2:541007

S3 guideline „actinic keratosis and cutaneous squamous cell carcinoma“ – update 2023, part 2: epidemiology and etiology, diagnostics, surgical and systemic treatment of cutaneous squamous cell carcinoma (cSCC), surveillance and prevention - Leiter, Ulrike; Heppt, Markus; Steeb, Theresa; Alter, Mareike; Amaral, Teresa; Bauer, Andrea; Bechara, Falk G.; Becker, Jürgen C.; Breitbart, Eckhard W.; Breuninger, Helmut; Diepgen, Thomas; Dirschka, Thomas; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2023)
Actinic keratosis (AK) are common lesions in light-skinned individuals that can potentially progress to cutaneous squamous cell carcinoma (cSCC). Both conditions may be associated with significant morbidity and constitute a major disease burden, especially among the elderly. To establish an evidence-based framework for clinical decision making, the guideline “actinic keratosis and cutaneous squamous cell carcinoma” was updated and expanded by the topics cutaneous squamous cell carcinoma in situ (Bowen's disease) and actinic cheilitis. The guideline is aimed at dermatologists, general practitioners, ear nose and throat specialists, surgeons, oncologists, radiologists and radiation oncologists in hospitals and office-based settings, as well as other medical specialties, policy makers and insurance funds involved in the diagnosis and treatment of patients with AK and cSCC. A separate guideline exists for patients and their relatives. In this part, we will address aspects relating to epidemiology and etiology, diagnostics, surgical and systemic treatment of cutaneous squamous cell carcinoma (cSCC), surveillance and prevention.
CRIS-Team Scopus Importer:2023-11-17

S3 guideline for actinic keratosis and cutaneous squamous cell carcinoma (cSCC) - short version, part 2: epidemiology, surgical and systemic treatment of cSCC, follow-up, prevention and occupational disease - Leiter, Ulrike; Heppt, Markus; Steeb, Theresa; Amaral, Teresa; Bauer, Andrea; Becker, Juergen C.; Breitbart, Eckhardt; Breuninger, Helmut; Diepgen, Thomas; Dirschka, Thomas; Eigentler, Thomas; Flaig, Michael; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2020)
Actinic keratoses (AKs) are common lesions in light-skinned individuals that can potentially progress to cutaneous squamous cell carcinoma (cSCC). Both conditions may be associated with significant morbidity and constitute a major disease burden, especially among the elderly. To establish an evidence-based framework for clinical decision making, the guidelines for actinic keratosis and cutaneous squamous cell carcinoma were developed using the highest level of methodology (S3) according to regulations issued by the Association of Scientific Medical Societies in Germany (AWMF). The guidelines are aimed at dermatologists, general practitioners, ENT specialists, surgeons, oncologists, radiologists and radiation oncologists in hospitals and office-based settings as well as other medical specialties involved in the diagnosis and treatment of patients with AKs and cSCC. The guidelines are also aimed at affected patients, their relatives, policy makers and insurance funds. In the second part, we will address aspects relating to epidemiology, etiology, surgical and systemic treatment of cSCC, follow-up and disease prevention, and discuss AKs and cSCC in the context of occupational disease regulations.
CRIS-Team WoS Importer:2020-04-17

S3 guideline for actinic keratosis and cutaneous squamous cell carcinoma – short version, part 1: diagnosis, interventions for actinic keratoses, care structures and quality-of-care indicators - Heppt, Markus V.; Leiter, Ulrike; Steeb, Theresa; Amaral, Teresa; Bauer, Andrea; Becker, Jürgen C.; Breitbart, Eckhard; Breuninger, Helmut; Diepgen, Thomas; Dirschka, Thomas; Eigentler, Thomas; Flaig, Michael; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2020)
Actinic keratoses (AK) are common lesions in light-skinned individuals that can potentially progress to cutaneous squamous cell carcinoma (cSCC). Both conditions may be associated with significant morbidity and constitute a major disease burden, especially among the elderly. To establish an evidence-based framework for clinical decision making, the guideline “actinic keratosis and cutaneous squamous cell carcinoma” was developed using the highest level of methodology (S3) according to regulations issued by the Association of Scientific Medical Societies in Germany (AWMF). The guideline is aimed at dermatologists, general practitioners, ENT specialists, surgeons, oncologists, radiologists and radiation oncologists in hospitals and office-based settings as well as other medical specialties involved in the diagnosis and treatment of patients with AK and cSCC. The guideline is also aimed at affected patients, their relatives, policy makers and insurance funds. In the first part, we will address aspects relating to diagnosis, interventions for AK, care structures and quality-of-care indicators.
CRIS-Team Scopus Importer:2020-03-17

S3-Leitlinie „Aktinische Keratose und Plattenepithelkarzinom der Haut“ – Kurzfassung, Teil 1: Diagnostik, Interventionen bei aktinischen Keratosen, Versorgungsstrukturen und Qualitätsindikatoren - Heppt, Markus V.; Leiter, Ulrike; Steeb, Theresa; Amaral, Teresa; Bauer, Andrea; Becker, Jürgen C.; Breitbart, Eckhard; Breuninger, Helmut; Diepgen, Thomas; Dirschka, Thomas; Eigentler, Thomas; Flaig, Michael; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2020)
Aktinische Keratosen (AK) sind häufige Hautveränderungen bei hellhäutigen Menschen mit dem Potenzial, in ein kutanes Plattenepithelkarzinom (PEK) überzugehen. Beide Erkrankungen können mit erheblicher Morbidität verbunden sein und stellen eine große Krankheitslast insbesondere in der älteren Bevölkerung dar. Um eine evidenzbasierte, klinische Entscheidungsfindung zu unterstützen, wurde die Leitlinie “Aktinische Keratose und Plattenepithelkarzinom der Haut” auf der Methodikebene S3 nach dem Regelwerk der AWMF entwickelt. Die Leitlinie richtet sich dabei an Dermatologen, Allgemeinmediziner, HNO-Ärzte, Chirurgen, Onkologen, Radiologen und Strahlentherapeuten in Klinik und Praxis sowie an andere medizinische Fachgebiete, die sich mit der Diagnose und Behandlung von Patienten mit AK und PEK befassen. Die Leitlinie richtet sich auch an betroffene Patienten, deren Angehörige, politische Entscheidungsträger und Versicherungsgesellschaften. In diesem Teil behandeln wir die Themen Diagnostik, Interventionen bei AK, Versorgungsstrukturen und Qualitätsindikatoren.
CRIS-Team Scopus Importer:2020-03-17

S3-Leitlinie "Aktinische Keratose und Plattenepithelkarzinom der Haut" - Kurzfassung, Teil 2: Epidemiologie, chirurgische und systemische Therapie des Plattenepithelkarzinoms, Nachsorge, Pravention und Berufskrankheit - Leiter, Ulrike; Heppt, Markus V.; Steeb, Theresa; Amaral, Teresa; Bauer, Andrea; Becker, Juergen C.; Breitbart, Eckhardt; Breuninger, Helmut; Diepgen, Thomas; Dirschka, Thomas; Eigentler, Thomas; Flaig, Michael; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2020)
Zusammenfassung Aktinische Keratosen (AK) sind haufige Hautveranderungen bei hellhautigen Menschen mit dem Potenzial, in ein kutanes Plattenepithelkarzinom (PEK) uberzugehen. Beide Erkrankungen konnen mit erheblicher Morbiditat verbunden sein und stellen eine gro ss e Krankheitslast insbesondere in der alteren Bevolkerung dar. Um eine evidenzbasierte, klinische Entscheidungsfindung zu unterstutzen, wurde die Leitlinie Aktinische Keratose und kutanes Plattenepithelkarzinom" auf der Methodikebene S3 nach dem Regelwerk der AWMF entwickelt. Die Leitlinie richtet sich dabei an Dermatologen, Allgemeinmediziner, HNO-Arzte, Chirurgen, Onkologen, Radiologen und Strahlentherapeuten in Klinik und Praxis sowie an andere medizinische Fachgebiete, die sich mit der Diagnose und Behandlung von Patienten mit AK und PEK befassen. Die Leitlinie richtet sich auch an betroffene Patienten, deren Angehorige, politische Entscheidungstrager und Versicherungsgesellschaften. In diesem Teil behandeln wir die Themen Epidemiologie, Atiologie, chirurgische und systemische Behandlung des PEK, Nachsorge des PEK, Pravention und Berufskrankheit durch AK und PEK.
CRIS-Team WoS Importer:2020-05-15

S3-Leitlinie “Aktinische Keratose und Plattenepithelkarzinom der Haut“ – Update 2023, Teil 1: Therapie der aktinischen Keratose, Morbus Bowen, Cheilitis actinica, berufsbedingte Erkrankung und Versorgungsstrukturen - Heppt, Markus; Leiter, Ulrike; Steeb, Theresa; Alter, Mareike; Amaral, Teresa; Bauer, Andrea; Bechara, Falk G.; Becker, Jürgen C.; Breitbart, Eckhard W.; Breuninger, Helmut; Diepgen, Thomas; Dirschka, Thomas; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2023)
CRIS-Team Scopus Importer:2023-10-27

Safety and tolerability of a single infusion of autologous ex vivo expanded regulatory T cells in adults with ulcerative colitis (ER-TREG 01): protocol of a phase 1, open-label, fast-track dose-escalation clinical trial - Voskens, Caroline; Stoica, Diane; Roessner, Susanne; Vitali, Francesco; Zundler, Sebastian; Rosenberg, Marita; Wiesinger, Manuel; Wunder, Jutta; Siegmund, Britta; Schuler-Thurner, Beatrice; Schuler, Gerold; Berking, Carola; et al. (BMJ Open, 2021)
Introduction Accumulating evidence suggests that the adoptive transfer of ex vivo expanded regulatory T cells (Treg) may overcome colitogenic immune responses in patients with inflammatory bowel diseases. The objective of the ER-TREG 01 trial is to assess safety and tolerability of a single infusion of autologous ex vivo expanded Treg in adults with ulcerative colitis.
CRIS-Team WoS Importer:2021-12-24

Safety of topical interventions for the treatment of actinic keratosis - Koch, Elias; Wessely, Anja; Steeb, Theresa; Berking, Carola; Heppt, Markus (Expert Opinion on Drug Safety, 2021)
Introduction: Actinic keratosis (AK) are proliferations of atypical keratinocytes that may eventually progress to cutaneous squamous cell carcinoma. Therefore, AK requires consequent and early treatment. Areas covered: A variety of effective approaches is currently available for the clearance of AK. These interventions may be applied either in a lesion-directed or field-directed mode as AK can occur as single or multiple lesions. Field-directed approaches typically comprise topical drug-mediated interventions which aim at eliminating all visible lesions and also at clearing subclinical changes of the actinically damaged field. However, most treatment options are associated with local adverse events such as erythema, scaling, pain, and rarely with systemic symptoms. This expert review provides a comprehensive and up-to-date overview of the safety considerations of the commonly prescribed topical treatment agents cyclooxygenase inhibitors, 5-fluorouracil, imiquimod, ingenol mebutate, and photodynamic therapy. All these therapies have been proven efficient, yet they differ considerably regarding their safety profile. Expert opinion: In the future, safety concerns will relate to long-term and irreversible adverse drug events instead of application site reactions. In particular, the rate of treatment-associated non-melanoma skin cancers will increasingly come into focus and warrant investigation in postmarketing surveillance trials with a long-term follow-up.
CRIS-Team Scopus Importer:2021-08-06
Keywords: 5-fluorouracil; actinic keratosis; diclofenac; imiquimod; ingenol mebutate; photodynamic therapy

Sarcoidosis Under Dendritic Cell Vaccination Immunotherapy in Long-term Responding Patients with Metastatic Melanoma - Uslu, Ugur; Erdmann, Michael; Schliep, Stefan; Dörrie, Jan; Schaft, Niels; Schuler, Gerold; Schuler-Thurner, Beatrice (Anticancer Research, 2017)
Sarcoidosis, a chronic inflammatory disorder, results from increased immune responses. Its development can be triggered in patients under immunotherapy, as activation of the immune system in these patients is desired. Since 1997, 249 patients with metastasized cutaneous melanoma (stage III and IV, AJCC 2009) have been treated with dendritic cell (DC)-based vaccines at our hospital. Three out of these patients were diagnosed with sarcoidosis after or during long-term DC vaccination therapy (1.20%). Metastatic disease was initially suspected based on the radiographic manifestation of lung masses or bilateral hilar lymphadenopathy. Histological assessment, however, revealed the appropriate diagnosis. Interestingly, all three patients are long-term responders and have remained free of metastatic or progressive disease for over a period of at least 4 years. In summary, sarcoidosis can occur in patients with cancer who have benefited from DC-based therapeutic vaccination and thus, its development, even with substantial delay, may be associated with successful anticancer immunotherapy.
EVALuna2:34321

SARS-CoV-2 Transmission from Presymptomatic Meeting Attendee, Germany - Hijnen, Dirkjan; Marzano, Angelo Valerio; Eyerich, Kilian; Geurtsvankessel, Corine; Giménez-Arnau, Ana Maria; Joly, Pascal; Vestergaard, Christian; Sticherling, Michael; Schmidt, Enno (Emerging Infectious Diseases, 2020)
During a meeting in Munich, Germany, a presymptomatic attendee with severe acute respiratory syndrome coronavirus 2 infected at least 11 of 13 other participants. Although 5 participants had no or mild symptoms, 6 had typical coronavirus disease, without dyspnea. Our findings suggest hand shaking and face-to-face contact as possible modes of transmission.
CRIS-Team WoS Importer:2020-08-07

SARS-CoV-2 vaccination responses in untreated, conventionally treated and anticytokine-treated patients with immune-mediated inflammatory diseases - Simon, David; Tascilar, Koray; Fagni, Filippo; Krönke, Gerhard; Kleyer, Arnd; Meder, Christine; Meder, Christine; Atreya, Raja; Leppkes, Moritz; Kremer, Andreas E.; Pachowsky, Milena; Schuch, Florian; et al. (Annals of the Rheumatic Diseases, 2021)
Objectives: To better understand the factors that influence the humoral immune response to vaccination against SARS-CoV-2 in patients with immune-mediated inflammatory diseases (IMIDs). Methods: Patients and controls from a large COVID-19 study, with (1) no previous history of COVID-19, (2) negative baseline anti-SARS-CoV-2 IgG test and (3) SARS-CoV-2 vaccination at least 10 days before serum collection were measured for anti-SARS-CoV-2 IgG. Demographic, disease-specific and vaccination-specific data were recorded. Results: Vaccination responses from 84 patients with IMID and 182 controls were analysed. While all controls developed anti-SARS-CoV-2 IgG, five patients with IMID failed to develop a response (p=0.003). Moreover, 99.5% of controls but only 90.5% of patients with IMID developed neutralising antibody activity (p=0.0008). Overall responses were delayed and reduced in patients (mean (SD): 6.47 (3.14)) compared with controls (9.36 (1.85); p<0.001). Estimated marginal means (95% CI) adjusted for age, sex and time from first vaccination to sampling were 8.48 (8.12-8.85) for controls and 6.90 (6.45-7.35) for IMIDs. Significantly reduced vaccination responses pertained to untreated, conventionally and anticytokine treated patients with IMID. Conclusions: Immune responses against the SARS-CoV-2 are delayed and reduced in patients with IMID. This effect is based on the disease itself rather than concomitant treatment.
CRIS-Team Scopus Importer:2021-05-21
Keywords: biological therapy; COVID-19; epidemiology; vaccination

SCLE manifestation after mRNA COVID-19 vaccination - Rechtien, Laura; Erfurt-Berge, Cornelia; Sticherling, Michael (Journal of the European Academy of Dermatology and Venereology, 2022)
CRIS-Team WoS Importer:2022-01-14

Secondary syphilis infection under treatment with ustekinumab - Uslu, Ugur; Heppt, Franz; Sticherling, Michael (Clinical and Experimental Dermatology, 2017)
EVALuna2:34342

Secukinumab 2-weekly vs. 4-weekly dosing in patients with plaque-type psoriasis: results from the randomized GAIN study - Reich, K.; Koerber, A.; Mrowietz, U.; Sticherling, Michael; Sieder, C.; Frueh, J.; Bachhuber, T. (British Journal of Dermatology, 2020)
Background: Secukinumab is a fully human monoclonal antibody that selectively neutralizes interleukin-17A and shows long-lasting efficacy and safety in plaque psoriasis. More evidence is required to optimize secukinumab dosing according to clinical response. Objectives: GAIN compared the efficacy and safety of secukinumab 300 mg every 2 weeks (q2w) with 300 mg every 4 weeks (q4w) in patients achieving ≥ 75% improvement in Psoriasis Area and Severity Index (PASI 75) but not PASI 90 after 16 weeks. Methods: In total, 772 patients with moderate-to-severe plaque psoriasis received secukinumab 300 mg subcutaneously at baseline and weeks 1, 2, 3 and 4, then q4w until week 16. At week 16, patients with PASI ≥ 75 to PASI < 90 were randomized 1: 1 to continue q4w dosing (n = 162) or switch to q2w (n = 163) to week 32. The primary endpoint was superiority of q2w to q4w dosing for PASI 90 response at week 32. Results: PASI 90 response at week 32 was numerically greater with secukinumab 300 mg q2w than with secukinumab 300 mg q4w in suboptimal responders, but this did not reach statistical significance (64·4% vs. 57·4%; odds ratio 0·64, 95% confidence interval 0·39–1·07; P = 0·087). Although the primary endpoint was not met, absolute PASI was significantly lower at week 32 in q2w vs. q4w patients (2·11 vs. 2·84, P = 0·024). Significantly more patients with q2w vs. q4w dosing showed minimal disease activity (Investigator’s Global Assessment score 0 or 1: 73·0% vs. 64·1%, P < 0·05) and improved quality of life (Dermatology Life Quality Index score 0 or 1: 58·9% vs. 50·6%, P < 0·05) at week 32. No new or unexpected safety signals arose. Conclusions: Most patients achieved PASI 90 response with secukinumab q4w. There was potential benefit of q2w dosing in some suboptimal responders. Continued q4w treatment can improve response even after 16 weeks.
CRIS-Team Scopus Importer:2020-12-04

Secukinumab in Pediatric Patients with Plaque Psoriasis: Pooled Safety Analysis from Two Phase 3 Randomized Clinical Trials - Sticherling, Michael; Nikkels, Arjen F.; Hamza, Ashraf M.; Kwong, Pearl; Szepietowski, Jacek C.; El Sayed, Mahira; Ghislain, Pierre Dominique; Khotko, Alkes A.; Patekar, Manmath; Ortmann, Christine Elke; Forrer, Pascal; Papanastasiou, Philemon; et al. (American Journal of Clinical Dermatology, 2023)
Background: Plaque psoriasis affects 1% of the pediatric population, negatively impacting quality of life. The efficacy and safety of secukinumab in pediatric patients with moderate to severe or severe chronic plaque psoriasis have been established in two pivotal phase 3 trials (open-label, NCT03668613; double-blind, NCT02471144). Objectives: The aims were to report the pooled safety of secukinumab up to 52 weeks from two studies in subgroups of pediatric patients stratified by age and bodyweight, and to present, alongside the pediatric data, the pooled safety data from four pivotal adult secukinumab trials. Methods: The safety of secukinumab was evaluated in subgroups of pediatric patients defined by age (6 to < 12 and 12 to < 18 years) and bodyweight (< 25 kg, 25 to < 50 kg, and ≥ 50 kg) in the pooled population. Patients received secukinumab low dose (LD; 75/75/150 mg), secukinumab high dose (HD; 75/150/300 mg), placebo, or etanercept (0.8 mg/kg). For safety analyses, data were pooled from the pediatric studies NCT03668613 and NCT02471144, and presented alongside the pooled data from four adult pivotal studies (NCT01365455, NCT01636687, NCT01358578, NCT01555125). Results: A total of 198 pediatric patients (overall exposure: 184.6 patient-years [PY]) and 1989 adult patients (1749.5 PY) receiving secukinumab up to week 52 were included in this analysis. At week 52, the incidence of adverse events (AEs) was lower in the lower age and bodyweight subgroups. The AEs reported within these subgroups were consistent with the overall AEs reported in this analysis. Overall, exposure-adjusted incidence rates for treatment-emergent AEs were lower in the secukinumab-treated pediatric pool (198.8/100 PY) compared with the etanercept (266.3/100 PY) and adult pools (256.1/100 PY). Up to 52 weeks, the incidence rates of the AEs in the secukinumab-treated patients in the 6 to < 12 years subgroup and 12 to < 18 years subgroup were 167.7/100 PY and 214.7/100 PY, respectively. Similarly, incidence rates of the AEs in the secukinumab-treated patients in the < 25 kg, 25 kg to < 50 kg, and ≥ 50 kg subgroups were 177.3/100 PY, 192.5/100 PY, and 206.8/100 PY, respectively. Nasopharyngitis was the most frequently reported AE in secukinumab-treated pediatric patients across age (< 12 years: 11.8/100 PY; ≥ 12 years: 42.4/100 PY) and bodyweight (< 25 kg: 22.8/100 PY; 25 kg to < 50 kg: 19.0/100 PY; ≥ 50 kg: 43.0/100 PY). Of the 198 secukinumab-treated pediatric patients, one reported nail Candida, one reported skin Candida, and two reported vulvovaginal Candida. Transient and mostly mild events of neutropenia were observed with secukinumab, none leading to study treatment discontinuation. No incidence of treatment-emergent anti-drug antibodies was reported in pediatric patients treated with secukinumab. Conclusions: Secukinumab was well tolerated in pediatric patients with moderate to severe and severe plaque psoriasis across age and bodyweight subgroups. The overall safety profile of secukinumab in pediatric patients was consistent with that of adult patients. ClinicalTrials.gov Identifier: NCT03668613 (Novartis Study Code CAIN457A2311, referred to as A2311), actual study start date: August 29, 2018; actual primary completion date: September 19, 2019; estimated study completion date: September 14, 2023. NCT02471144 (Novartis Study Code CAIN457A2310, referred to as A2310), study start date: September 29, 2015; primary completion date: December 13, 2018; estimated study completion date: March 31, 2023.
CRIS-Team Scopus Importer:2023-07-07

Secukinumab is superior to Fumaric Acid Esters in the Treatment of Patients with moderate to severe Plaque Psoriasis without previous Systemic Therapy for Improvement of Skin Symptoms: PASI and IGA mod. 2011-Results of the PRIME Study - Reich, K.; Mrowietz, U.; Augustin, M.; Thaci, D.; Kneidl, J.; Hentschke, C.; Simang, M.; Sieder, C.; Melzer, N.; Sticherling, Michael (2017)
EVALuna2:34358

Secukinumab is superior to Fumaric Acid Esters in the Treatment of Patients with moderate to severe Plaque Psoriasis without prior System Therapy with regard to compatibility-related Therapeutic Adherence: Safety Results of the PRIME Study - Mrowietz, U.; Augustin, M.; Thaci, D.; Reich, K.; Kneidl, J.; Hentschke, C.; Simang, M.; Sieder, C.; Melzer, N.; Sticherling, Michael (2017)
EVALuna2:34361

Secukinumab is superior to Fumaric Acid Esters in the Treatment of Patients with moderate to severe Plaque Psoriasis without prior System Therapy with respect to the Improvement of quality of life: DLQI and SF-36 Results of the PRIME Study - Augustin, M.; Thaci, D.; Reich, K.; Mrowietz, U.; Kneidl, J.; Hentschke, C.; Simang, M.; Sieder, C.; Melzer, N.; Sticherling, Michael (2017)
EVALuna2:34359

Secukinumab is superior to Fumaric Acid Esters in the Treatment of Patients with moderate to severe Plaque Psoriasis with without previous Systemic Therapy for Improvement of Nail Symptoms: NAPSI Results PRIME Study - Thaci, D.; Reich, K.; Mrowietz, U.; Augustin, M.; Kneidl, J.; Hentschke, C.; Simang, M.; Sieder, C.; Melzer, N.; Sticherling, Michael (2017)
EVALuna2:34360

Secukinumab is superior to fumaric acid esters in treating patients with moderate-to-severe plaque psoriasis who are naive to systemic treatments: results from the randomized controlled PRIME trial - Sticherling, Michael; Mrowietz, U.; Augustin, M.; Thaci, D.; Melzer, N.; Hentschke, C.; Kneidl, J.; Sieder, C.; Reich, K. (British Journal of Dermatology, 2017)
BACKGROUND: Secukinumab is a fully human antibody that neutralizes interleukin-17A. It has significant efficacy and a favourable safety profile in moderate-to-severe plaque psoriasis and psoriatic arthritis. OBJECTIVES: To compare secukinumab with fumaric acid esters (FAEs) in a randomized controlled trial. METHODS: In this 24-week, randomized, open-label, multicentre study with blinded assessment, patients with moderate-to-severe plaque psoriasis, naive to systemic treatments, were randomized to receive secukinumab 300 mg subcutaneously or oral FAEs. The primary end point was ≥ 75% improvement from baseline Psoriasis Area and Severity Index score (PASI 75 response) at week 24, and missing patients were considered responders if they were responders at the time of dropout. RESULTS: In total 202 patients were randomized and 200 were treated with at least one dose. Outcomes at week 24 were available for 147 and imputed for 53 patients. Discontinuations were mostly due to adverse events, which occurred more frequently in the FAE group (1·9% vs. 33·0%). At week 24, significantly more patients receiving secukinumab compared with FAEs achieved PASI 75 response (89·5% vs. 33·7%, P < 0·001), PASI 90 response (81·0% vs. 28·4%, P < 0·001) and Dermatology Life Quality Index 0 or 1 response (71·4% vs. 25·3%, P < 0·001). CONCLUSIONS: Secukinumab demonstrated superior efficacy to FAEs in patients with psoriasis over a 24-week period.
EVALuna2:34340

Secukinumab leads to shifts from stage-based towards response-based disease clusters-comparative data from very early and established psoriatic arthritis - Kampylafka, Eleni; Tascilar, Koray; Lerchen, Veronika; Linz, Christina; Sokolova, Maria; Zekovic, Ana; Kleyer, Arnd; Simon, David; Rech, Jürgen; Sticherling, Michael; Schett, Georg; Hueber, Axel (Arthritis Research & Therapy, 2020)
Background: Limited information exists about the very early forms of psoriatic arthritis. In particular, differences and responsiveness of patient-reported outcomes (PROs) in very early as compared to established PsA have not been investigated to date. Methods: Cross-sectional and prospective longitudinal evaluation of PROs related to pain (VAS), physical function (HAQ-DI, SF-36 physical), mental function (SF-36 mental), impact of psoriatic skin (DLQI), joint (PsAID), and global disease (VAS) in two small prospective observational studies on secukinumab 300 mg over 6 months in very early disease patients (IVEPSA study, N = 20) and established PsA (PSARTROS study, N = 20). Cluster analysis was performed at baseline and 24-weeks of follow-up. Results: While responses in pain and physical activity-related PROs to secukinumab were more pronounced in established PsA than a very early disease, effects on PROs related to general health perception, as well as those related to emotional and mental well-being, were modified in a similar way in very early disease and established PsA. Cluster analysis based on global disease activity and PROs showed that baseline clusters reflected very early disease and established PsA, while after secukinumab treatment these clusters were abolished and new clusters based on differential responses to physically and mentally oriented PROs formed. Conclusions: Inhibition of IL-17A by secukinumab leads to comprehensive improvement of general health perception and mental well-being in very early and established PsA, while overall responses in pain and physical activity are more pronounced in established disease. Most importantly, treatment restructures the original patients' clusters based on disease stage and leads to the formation of new clusters that reflect their response in physical and mental-orientated PROs. Trial registration: NCT02483234, registered 26 June 2015, retrospectively registered.
CRIS-Team Scopus Importer:2020-10-02
Keywords: Cluster analysis; IL-17A; Psoriatic arthritis; Quality of life; Secukinumab

Secukinumab Treatment of moderate to severe Plaque Psoriasis in the clinical Routine Care: Baseline Data from the PROSPECT Study on Psoriasis Pre-treatment - Von Kiedrowski, R.; Korber, A.; Kraehn-Senftleben, G.; Sticherling, Michael; Lange, L.; Bachhuber, T.; Kasparek, T. R.; Augustin, M.; Thaci, D.; Amon, U. (2017)
EVALuna2:34357

Select Clr-g Expression on Activated Dendritic Cells Facilitates Cognate Interaction with a Minor Subset of Splenic NK Cells Expressing the Inhibitory Nkrp1g Receptor - Friede, Miriam E.; Leibelt, Stefan; Dudziak, Diana; Steinle, Alexander (Journal of Immunology, 2018)
Natural killer gene complex-encoded immunomodulatory C-type lectin-like receptors include members of the NKRP1 and C-type lectin-like 2 (CLEC2) gene families, which constitute genetically linked receptor-ligand pairs and are thought to allow for NK cell-mediated immunosurveillance of stressed or infected tissues. The mouse C-type lectin-like receptor Nkrp1g was previously shown to form several receptor-ligand pairs with the CLEC2 proteins Clr-d, Clr-f, and Clr-g, respectively. However, the physiological expression of Nkrp1g and its CLEC2 ligands as well as their functional relevance remained poorly understood. Recently, we demonstrated a gut-restricted expression of Clr-f on intestinal epithelial cells that is spatially matched by Nkrp1g on subsets of intraepithelial lymphocytes. In this study, we investigated expression and ligand interaction of Nkrp1g in the splenic compartment, and found an exclusive expression on a small subset of NK cells that upregulates Nkrp1g after cytokine exposure. Whereas transcripts of Clr-d and Clr-f are virtually absent from the spleen, Clr-g transcripts were abundantly detected throughout different leukocyte populations and hematopoietic cell lines. However, a newly generated anti-Clr-g mAb detected only residual Clr-g surface expression on splenic monocytes, whereas many hematopoietic cell lines brightly display Clr-g. Clr-g surface expression was strongly upregulated on splenic CD8α+ conventional dendritic cells (DCs) and plasmacytoid DCs upon TLR-mediated activation and detectable by Nkrp1g, which dampens NK cell effector functions upon Clr-g engagement. Hence, different to the intestinal tract, in the spleen, Nkrp1g is selectively expressed by a subset of NK cells, thereby potentially allowing for an inhibitory engagement with Clr-g-expressing activated DCs during immune responses.
EVALuna2:34802

Select hyperactivating NLRP3 ligands enhance the TH1-and TH17-inducing potential of human type 2 conventional dendritic cells - Hatscher, Lukas; Lehmann, Christian; Purbojo, Ariawan; Onderka, Constantin; Liang, Chunguang; Hartmann, Arndt; Cesnjevar, Robert; Bruns, Heiko; Gross, Olaf; Nimmerjahn, Falk; Burmazovic, Ivana Ivanovic; Kunz, Meik; et al. (Science Signaling, 2021)
The detection of microorganisms and danger signals by pattern recognition receptors on dendritic cells (DCs) and the consequent formation of inflammasomes are pivotal for initiating protective immune responses. Although the activation of inflammasomes leading to secretion of the cytokine IL-1 is typically accompanied by pyroptosis (an inflammatory form of lytic programmed cell death), some cells can survive and exist in a state of hyperactivation. Here, we found that the conventional type 2 DC (cDC2) subset is the major human DC subset that is transcriptionally and functionally poised for inflammasome formation and response without pyroptosis. When cDC2 were stimulated with ligands that relatively weakly activated the inflammasome, the cells did not enter pyroptosis but instead secreted IL-12 family cytokines and IL-1. These cytokines induced prominent T helper type 1 (TH1) and TH17 responses that were superior to those seen in response to Toll-like receptor (TLR) stimulation alone or to stronger, classical inflammasome ligands. These findings not only define the human cDC2 subpopulation as a prime target for the treatment of inflammasome-dependent inflammatory diseases but may also inform new approaches for adjuvant and vaccine development.
CRIS-Team Scopus Importer:2021-05-14
Keywords: Dendritic cells; cDC2; CD1c; inflammasome; hyperactivation; L18-MDP; T cell differentiation

Select hyperactivating NLRP3 ligands enhance the TH1-and TH17-inducing potential of human type 2 conventional dendritic cells - Heger, Lukas; Hatscher, Lukas; Lehmann, Christian; Purbojo, Ariawan; Onderka, Constantin; Liang, C.; Hartmann, Arndt; Cesnjevar, Robert; Bruns, Heiko; Gross, O.; Nimmerjahn, Falk; Ivanovic-Burmazovic, I.; et al. (EXPERIMENTAL DERMATOLOGY, 2022)
CRIS-Team WoS Importer:2022-03-04

Semi-Automatic Cell Correspondence Analysis Using Iterative Point Cloud Registration - Chen, Shuqing; Gehrer, Simone; Kaliman, Sara; Ravikumar, Nishant; Becit, Abdurrahman; Aliee, Maryam; Dudziak, Diana; Merkel, Rudolf; Smith, Ana-Suncana; Maier, Andreas (Bildverarbeitung für die Medizin 2019. Informatik aktuell., 2019)

Senescence markers: Predictive for response to checkpoint inhibitors - Moreira, Alvaro; Gross, Stefanie; Kirchberger, Michael Constantin; Erdmann, Michael; Schuler, Gerold; Heinzerling, Lucie (International Journal of Cancer, 2019)
Recent studies suggest that the age-related remodeling of the immune system, known as immunosenescence, could impact the efficacy of immune checkpoint inhibitors in leukemia or nonsmall cell lung cancer. We investigated whether senescence markers can predict response to checkpoint inhibitor therapy in melanoma patients. The peripheral blood of patients with newly diagnosed, untreated metastatic melanoma was analyzed by flow cytometry to correlate the frequency of senescence markers with clinical response as measured by RECIST after 12 weeks of treatment with immune checkpoint inhibitors. The loss of surface markers CD27 and CD28 or the expression of Tim-3 and CD57 on T cells was associated with resistance to checkpoint inhibitor blockade, presenting these phenotypes as possible predictive biomarkers for checkpoint inhibitor therapy. Immunosenescence seems to impact on the response to checkpoint inhibitor therapy in melanoma patients. Thus, lymphocyte phenotyping for senescence markers, with the introduction of immunosenescence panels, could be predictive for checkpoint inhibitor response.
CRIS-Team Scopus Importer:2019-05-21
Keywords: biomarker; immune checkpoint inhibitors; immunosenescence; melanoma

Serial or Parallel Metastasis of Cutaneous Melanoma? A Study of the German Central Malignant Melanoma Registry - Gassenmaier, Maximilian; Eigentler, Thomas Kurt; Keim, Ulrike; Goebeler, Matthias; Fiedler, Eckhard; Schuler, Gerold; Leiter, Ulrike; Weide, Benjamin; Grischke, Eva-Maria; Martus, Peter; Garbe, Claus (Journal of Investigative Dermatology, 2017)
For more than a century the Halstedian hypothesis of contiguous metastasis from the primary tumor through the lymphatics to distant sites shaped lymph node surgery for melanoma. We challenge this dogma of serial metastatic dissemination. A single-center series of 2,299 patients with cutaneous metastatic melanoma was investigated to analyze overall survival and distant metastasis-free survival of stage IV patients with or without primary lymphatic metastasis. Results were then compared with those of 2,134 patients from three independent centers of the German Central Malignant Melanoma Registry. A multivariate binary logistic regression model was used to identify risk factors for the initial metastatic pathway. Distant metastasis-free survival (hazard ratio = 1.02; 95% confidence interval = 0.91-1.14; P = 0.76) and overall survival (HR = 1.09; 95% CI = 0.96-1.23; P = 0.177) did not differ between stage IV patients with primary hematogenous or primary lymphatic metastasis. Melanoma localization was the only significant risk factor for the initial metastatic pathway. These findings indicate that regional and distant metastases originate from the primary tumor itself in a rather parallel than serial fashion and could explain the lack of survival benefit associated with immediate complete lymph node dissection in sentinel lymph node-positive melanoma patients.
EVALuna2:34312

SERIO - Side Effect Registry Immuno-Oncology Side Effect Registry for rare, severe and complex Side Effects of Immunotherapy - Kramer, Rafaela; Mentzer, D.; Erdmann, M.; Knauss, S.; Broeckelmann, P. J.; Hassel, J. C.; Ugurel, S.; Pavel, Marianne Ellen; Nickel, Franziska; Landendinger, M.; Fuchs, Friederike; Meidenbauer, Norbert; et al. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2020)
CRIS-Team WoS Importer:2020-09-11

Serio - Side Effect Registry in Immuno-Oncology - Koutzamanidis, Rafaela; Mentzer, Dirk; Knauss, Samuel; Broeckelmann, Paul J.; Hassel, Jessica Cecile; Ugurel-Becker, Selma; Pavel, Marianne Ellen; Nickel, Florian; Landendinger, Melanie; Fuchs, Florian; Meidenbauer, Norbert; Jefremow, Andre; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-03-20

Serositis in Association with System Therapy with Checkpoint Inhibitors - More frequent than thought? - An Evaluation of the SERIO Adverse Event Registry - Zierold, S.; Kramer, R.; Erdmann, Michael; Akcetin, S. L.; Maier, A. M.; Koenig, A.; Theurich, S.; French, L. E.; Heinzerling, Lucie (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2021)
CRIS-Team WoS Importer:2021-09-24

Serum autoantibody reactivity in bullous pemphigoid is associated with neuropsychiatric disorders and the use of antidiabetics and antipsychotics: a large, prospective cohort study - Dikmen, H. O.; Yilmaz, K.; Benoit, S.; Bernard, P.; Drenovska, Kossara; Gerdes, S.; Glaeser, R.; Guenther, C.; Homey, B.; Horvath, O. N.; Huilaja, L.; Joly, P.; et al. (Journal of the European Academy of Dermatology and Venereology, 2022)
Background: Bullous pemphigoid (BP), the by far most frequent autoimmune blistering skin disease (AIBD), is immunopathologically characterized by autoantibodies against the two hemidesmosomal proteins BP180 (collagen type XVII) and BP230 (BPAG1 or dystonin). Several comorbidities and potentially disease-inducing medication have been described in BP, yet a systematic analysis of these clinically relevant findings and autoantibody reactivities has not been performed. Objective: To determine associations of autoantibody reactivities with comorbidities and concomitant medication. Methods: In this prospective multicenter study, 499 patients diagnosed with BP in 16 European referral centers were included. The relation between anti-BP180 NC16A and anti-BP230 IgG ELISA values at the time of diagnosis as well as comorbidities and concomitant medication collected by a standardized form were analysed. Results: An association between higher serum anti-BP180 reactivity and neuropsychiatric but not atopic and metabolic disorders was observed as well as with the use of insulin or antipsychotics but not with dipeptidyl peptidase-4 (DPP4) inhibitors, inhibitors of platelet aggregation and L-thyroxine. The use of DPP4 inhibitors was associated with less anti-BP180 and anti-BP230 reactivity compared with BP patients without these drugs. This finding was even more pronounced when compared with diabetic BP patients without DPP4 inhibitors. Associations between anti-BP180 and anti-BP230 reactivities were also found in patients using insulin and antipsychotics, respectively, compared with patients without this medication, but not for the use of inhibitors of platelet aggregation, and L-thyroxine. Conclusion: Taken together, these data imply a relation between autoantibody reactivities at the time of diagnosis and both neuropsychiatric comorbidities as well as distinct concomitant medication suggesting a link between the pathological immune mechanisms and clinical conditions that precede the clinically overt AIBD.
CRIS-Team Scopus Importer:2022-07-22

Serum interleukin-8 reflects tumor burden and treatment response across malignancies of multiple tissue origins - Sanmamed, Miguel F.; Carranza-Rua, Omar; Alfaro, Carlos; Onate, Carmen; Martin-Algarra, Salvador; Perez, Guiomar; Landazuri, Sara F.; Gonzalez, Alvaro; Gross, Stefanie; Rodriguez, Inmaculada; Munoz-Calleja, Cecilia; Rodriguez-Ruiz, Maria; et al. (Clinical Cancer Research, 2014)
Interleukin-8 (IL8) is a chemokine produced by malignant cells of multiple cancer types. It exerts various functions in shaping protumoral vascularization and inflammation/immunity. We evaluated sequential levels of serum IL8 in preclinical tumor models and in patients to assess its ability to estimate tumor burden.IL8 levels were monitored by sandwich ELISAs in cultured tumor cells supernatants, tumor-xenografted mice serum, and in samples from 126 patients with cancer. We correlated IL8 serum levels with baseline tumor burden and with treatment-induced changes in tumor burden, as well as with prognosis.IL8 concentrations correlated with the number of IL8-producing tumor cells in culture. In xenografted neoplasms, IL8 serum levels rapidly dropped after surgical excision, indicating an accurate correlation with tumor burden. In patients with melanoma (n = 16), renal cell carcinoma (RCC; n = 23), non-small cell lung cancer (NSCLC; n = 21), or hepatocellular carcinoma (HCC; n = 30), serum IL8 concentrations correlated with tumor burden and stage, survival (melanoma, n = 16; RCC, n = 23; HCC, n = 33), and objective responses to therapy, including those to BRAF inhibitors (melanoma, n = 16) and immunomodulatory monoclonal antibodies (melanoma, n = 8). IL8 concentrations in urine (n = 18) were mainly elevated in tumors with direct contact with the urinary tract.IL8 levels correlate with tumor burden in preclinical models and in patients with cancer. IL8 is a potentially useful biomarker to monitor changes in tumor burden following anticancer therapy, and has prognostic significance.
EVALuna2:19512

Serum levels of miR-320 family members are associated with clinical parameters and diagnosis in prostate cancer patients - Lieb, Verena; Weigelt, Katrin; Scheinost, Lena; Fischer, Kersten; Greither, Thomas; Marcou, Marios; Theil, Gerit; Klocker, Helmut; Holzhausen, Hans Juergen; Lai, Xin; Vera, Julio; Ekici, Arif Bülent; et al. (Oncotarget, 2018)
We studied the association of the serum levels of the microRNA family members miR-320a/-b/-c with clinico-pathological data to assess their applicability as diagnostic biomarker in prostate cancer (PCa) patients. The levels of miR-320a/-b/-c in 3 groups were evaluated by qRT-PCR (145 patients with PCa, 31 patients with benign prostatic hyperplasia (BPH) and 19 healthy controls). The levels of the three family members of miR-320 were directly correlated within each group (P < 0.001), but they differed significantly among the three groups (P < 0.001). The serum levels of the miR-320 family members were significantly increased in older patients compared to younger patients (≤ 66 years vs. > 66 years, P ≤ 0.001). In addition, the levels of all three miR-320 family members were significantly different in patients with low tumor stage compared with those with high tumor stage (miR-320a: P = 0.034; miR-320b: P = 0.006; miR-320c: P = 0.007) and in patients with low serum PSA compared with those with high serum PSA (≤ 4 ng vs. > 4 ng; miR-320a: P = 0.003; miR-320b: P = 0.003; miR-320c: P = 0.006). The levels of these miRNAs were inversely correlated with serum PSA levels. Detection in the serum samples of PCa patients with or without PSA relapse revealed higher levels of miR-320a/-b/-c in the group without PSA relapse before/after radical prostatectomy than in that with PCa relapse. In summary, the differences among the PCa/BPH/healthy control groups with respect to miR-320a/-b/-c levels in conjunction with higher levels in patients without a PSA relapse than in those with a relapse suggest the diagnostic potential of these miRNA-320 family members in PCa patients.
EVALuna2:35121

Short Peptide Vaccine Induces CD4+ T Helper Cells in Patients with Different Solid Cancers - Gross, Stefanie; Lennerz, Volker; Gallerani, Elisa; Mach, Nicolas; Boehm, Steffen; Hess, Dagmar; Von Boehmer, Lotta; Knuth, Alexander; Ochsenbein, Adrian; Gnad-Vogt, Ulrike; Forssmann, Ulf; Woelfel, Thomas; et al. (Cancer Immunology Research, 2016)
Previous cancer vaccination trials often aimed to activate CD8(+) cytotoxic T-cell (CTL) responses with short (8-10mer) peptides and targeted CD4(+) helper T cells (TH) with HLA class II-binding longer peptides (12-16 mer) that were derived from tumor antigens. Accordingly, a study of immunomonitoring focused on the detection of CTL responses to the short, and TH responses to the long, peptides. The possible induction of concurrent TH responses to short peptides was widely neglected. In a recent phase I vaccination trial, 53 patients with different solid cancers were vaccinated with EMD640744, a cocktail of five survivin-derived short (9- or 10-mer) peptides in Montanide ISA 51VG. We monitored 49 patients and found strong CD8(+) T-cell responses in 63% of the patients. In addition, we unexpectedly found CD4(+) TH cell responses against at least two of the five short peptides in 61% (23/38) of the patients analyzed. The two peptides were recognized by HLA-DP4- and HLA-DR-restricted TH1 cells. Some short peptide-reactive (sp)CD4 T cells showed high functional avidity. Here, we show that a short peptide vaccine is able to activate a specific CD4(+) T-cell repertoire in many patients, facilitating a strong combined CD4(+)/CD8(+) T-cell response.
EVALuna2:19595

Siglec-15 on osteoclasts is crucial for bone erosion in serum-Transfer arthritis - Korn, Marina; Schmitt, Heike; Angermüller, Sieglinde; Chambers, David; Seeling, Michaela; Lux, Uwe; Brey, Stefanie; Royzman, Dmytro; Bruckner, Christin; Popp, Vanessa; Percivalle, Elena; Bäuerle, Tobias; et al. (Journal of Immunology, 2020)
Siglec-15 is a conserved sialic acid binding Ig-like lectin, which is expressed on osteoclasts. Deficiency of Siglec-15 leads to an impaired osteoclast development, resulting in a mild osteopetrotic phenotype. The role of Siglec-15 in arthritis is still largely unclear. To address this, we generated Siglec-15 knockout mice and analyzed them in a mouse arthritis model.We could show that Siglec-15 is directly involved in pathologic bone erosion in the K/BxN serum-Transfer arthritis model. Histological analyses of joint destruction provided evidence for a significant reduction in bone erosion area and osteoclast numbers in Siglec-152/2 mice, whereas the inflammation area and cartilage destruction was comparable to wild-Type mice. Thus, Siglec-15 on osteoclasts has a crucial function for bone erosion during arthritis. In addition, we generated a new monoclonal anti Siglec-15 Ab to clarify its expression pattern on immune cells. Whereas this Ab demonstrated an almost exclusive Siglec-15 expression on murine osteoclasts and hardly any other expression on various other immune cell types, human Siglec-15 was more broadly expressed on human myeloid cells, including human osteoclasts. Taken together, our findings show a role of Siglec-15 as a regulator of pathologic bone resorption in arthritis and highlight its potential as a target for future therapies, as Siglec-15 blocking Abs are available.
CRIS-Team Scopus Importer:2020-11-20

Siglec-H-Deficient Mice Show Enhanced Type I IFN Responses, but Do Not Develop Autoimmunity After Influenza or LCMV Infections - Szumilas, Nadine; Corneth, Odilia B.J.; Lehmann, Christian; Schmitt, Heike; Cunz, Svenia; Cullen, Jolie G.; Chu, Talyn; Marosán, Anita; Mócsai, Attila; Benes, Vladimir; Zehn, Dietmar; Dudziak, Diana; et al. (Frontiers in Immunology, 2021)
Siglec-H is a DAP12-associated receptor on plasmacytoid dendritic cells (pDCs) and microglia. Siglec-H inhibits TLR9-induced IFN-α production by pDCs. Previously, it was found that Siglec-H-deficient mice develop a lupus-like severe autoimmune disease after persistent murine cytomegalovirus (mCMV) infection. This was due to enhanced type I interferon responses, including IFN-α. Here we examined, whether other virus infections can also induce autoimmunity in Siglec-H-deficient mice. To this end we infected Siglec-H-deficient mice with influenza virus or with Lymphocytic Choriomeningitis virus (LCMV) clone 13. With both types of viruses we did not observe induction of autoimmune disease in Siglec-H-deficient mice. This can be explained by the fact that both types of viruses are ssRNA viruses that engage TLR7, rather than TLR9. Also, Influenza causes an acute infection that is rapidly cleared and the chronicity of LCMV clone 13 may not be sufficient and may rather suppress pDC functions. Siglec-H inhibited exclusively TLR-9 driven type I interferon responses, but did not affect type II or type III interferon production by pDCs. Siglec-H-deficient pDCs showed impaired Hck expression, which is a Src-family kinase expressed in myeloid cells, and downmodulation of the chemokine receptor CCR9, that has important functions for pDCs. Accordingly, Siglec-H-deficient pDCs showed impaired migration towards the CCR9 ligand CCL25. Furthermore, autoimmune-related genes such as Klk1 and DNase1l3 are downregulated in Siglec-H-deficient pDCs as well. From these findings we conclude that Siglec-H controls TLR-9-dependent, but not TLR-7 dependent inflammatory responses after virus infections and regulates chemokine responsiveness of pDCs.
CRIS-Team Scopus Importer:2021-09-17
Keywords: Interferon-alpha; plasmacytoid dendritic cells; Siglec; SLE; TLR9

Similar Impact of Psoriatic Arthritis and Rheumatoid Arthritis on Objective and Subjective Parameters of Hand Function - Liphardt, Anna-Maria; Manger, Eva; Liehr, Sonja; Bieniek, Lisa Maria; Kleyer, Arnd; Simon, David; Tascilar, Koray; Sticherling, Michael; Rech, Jürgen; Schett, Georg; Hueber, Axel (ACR Open Rheumatology, 2020)
ObjectiveThe objective of this study was to compare the impact of psoriatic disease (psoriatic arthritis [PsA] and psoriasis) and rheumatoid arthritis (RA) on objective and subjective parameters of hand function.
CRIS-Team WoS Importer:2021-07-16

Similar Impact of Psoriatic Arthritis and Rheumatoid Arthritis on Objective and Subjective Parameters of Hand Function - Liphardt, Anna-Maria; Manger, Eva; Liehr, Sonja; Bieniek, Lisa; Kleyer, Arnd; Simon, David; Tascilar, Koray; Sticherling, Michael; Rech, Jürgen; Schett, Georg; Hueber, Axel (ARTHRITIS & RHEUMATOLOGY, 2020)
CRIS-Team WoS Importer:2021-01-15

Simultaneous presentation of two skin lesions suspected of being malignant Gleichzeitiges Auftreten zweier malignomverdächtiger Hautveränderungen - Kaufmann, Matthias; Erdmann, Michael; Schliep, Stefan; Voskens, Caroline; Berking, Carola; Bauerschmitz, Jürgen (Die Dermatologie, 2024)
CRIS-Team Scopus Importer:2024-06-14

Simultaneous quantification of bone erosions and enthesiophytes in the joints of patients with psoriasis or psoriatic arthritis - effects of age and disease duration - Simon, David; Kleyer, Arnd; Faustini, Francesca; Englbrecht, Matthias; Haschka, Judith; Berlin, Andreas; Kraus, Sebastian; Hueber, Axel; Kocijan, Roland; Sticherling, Michael; Rech, Jürgen; Schett, Georg (Arthritis Research & Therapy, 2018)
BACKGROUND: Comprehensive simultaneous quantification of bone erosion and enthesiophytes in the joints of patients with psoriatic arthritis (PsA) has not been performed. Herein, we aimed to compare the extent of bone erosion and enthesiophytes in patients with PsA, psoriasis (PSO) and healthy controls, assess the influence of age and disease duration on the development of erosions and enthesiophytes and define their impact on physical function. METHODS: Patients with PsA or with PSO and controls were analysed by high-resolution peripheral quantitative computed tomography (HR-pQCT). The extent of bone erosions and enthesiophytes was assessed and plotted according to different categories of age, duration of PSO and duration of PsA, respectively. In addition, demographic and disease-specific data, including physical function (health assessment questionnaire) were collected. RESULTS: A total of 203 patients were analysed; 101 had PsA, 55 had PSO and 47 were healthy individuals. Patients with PsA had significantly more and larger erosions (p = 0.002/p = 0.003) and enthesiophytes (p < 0.001) compared to patients with PSO and healthy controls. Patients with PSO and healthy controls did not differ in erosions, while enthesiophytes were more frequent in patients with PSO than in healthy controls. Bone erosions, but not enthesiophytes, showed strong age-dependency in all three groups. In contrast, enthesiophytes were mostly influenced by the duration of PSO and PsA and, in contrast to bone erosions, were associated with poorer physical function. CONCLUSIONS: Bone erosions are age-dependent, enhanced in PsA and increase with disease duration. Enthesiophytes are less age-dependent, are enhanced in both PSO and PsA and strongly influenced by disease duration. Enthesiophytes impact physical function in PsA suggesting the need for early therapeutic interventions to prevent damage.
EVALuna2:34666

Single-cell Transcriptome Analysis and clonal Kinetics in a Patient after CD19.CAR-T Cell Therapy - Lischer, Christopher; Eisenhauer, Nina; Aigner, Michael; Jacobs, Benedikt; Schletter, M.; Gebhard, C.; Rehli, M.; Bruns, Heiko; Müller, Fabian; Mackensen, Andreas; Vera González, Julio; Völkl, Simon (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-11-18

Single-Molecule RNA Sequencing Reveals IFN gamma-Induced Differential Expression of Immune Escape Genes in Merkel Cell Polyomavirus-Positive MCC Cell Lines - Sauerer, Tatjana; Lischer, Christopher; Weich, Adrian; Berking, Carola; Vera, Julio; Dörrie, Jan (Frontiers in Microbiology, 2021)
Merkel cell carcinoma (MCC) is a rare and highly aggressive cancer, which is mainly caused by genomic integration of the Merkel cell polyomavirus and subsequent expression of a truncated form of its large T antigen. The resulting primary tumor is known to be immunogenic and under constant pressure to escape immune surveillance. Because interferon gamma (IFN gamma), a key player of immune response, is secreted by many immune effector cells and has been shown to exert both anti-tumoral and pro-tumoral effects, we studied the transcriptomic response of MCC cells to IFN gamma. In particular, immune modulatory effects that may help the tumor evade immune surveillance were of high interest to our investigation. The effect of IFN gamma treatment on the transcriptomic program of three MCC cell lines (WaGa, MKL-1, and MKL-2) was analyzed using single-molecule sequencing via the Oxford Nanopore platform. A significant differential expression of several genes was detected across all three cell lines. Subsequent pathway analysis and manual annotation showed a clear upregulation of genes involved in the immune escape of tumor due to IFN gamma treatment. The analysis of selected genes on protein level underlined our sequencing results. These findings contribute to a better understanding of immune escape of MCC and may help in clinical treatment of MCC patients. Furthermore, we demonstrate that single-molecule sequencing can be used to assess characteristics of large eukaryotic transcriptomes and thus contribute to a broader access to sequencing data in the community due to its low cost of entry.
CRIS-Team WoS Importer:2022-01-28

siRNA Electroporation to Modulate Autophagy in Herpes Simplex Virus Type 1-Infected Monocyte-Derived Dendritic Cells - Düthorn, Alexandra; Turan, Aykut; Drassner, Christina; Muehl-Zurbes, Petra; Heilingloh, Christiane; Steinkasserer, Alexander; Grosche, Linda (Journal of Visualized Experiments, 2019)
Herpes simplex virus type-1 (HSV-1) induces autophagy in both, immature dendritic cells (iDCs) as well as mature dendritic cells (mDCs), whereas autophagic flux is only observed in iDCs. To gain mechanistic insights, we developed efficient strategies to interfere with HSV-1-induced autophagic turnover. An inhibitor-based strategy, to modulate HSV-1-induced autophagy, constitutes the first choice, since it is an easy and fast method. To circumvent potential unspecific off-target effects of such compounds, we developed an alternative siRNA-based strategy, to modulate autophagic turnover in iDCs upon HSV-1 infection. Indeed, electroporation of iDCs with FIP200-specific siRNA prior to HSV-1 infection is a very specific and successful method to ablate FIP200 protein expression and thereby to inhibit autophagic flux. Both presented methods result in the efficient inhibition of HSV-1-induced autophagic turnover in iDCs, whereby the siRNA-based technique is more target specific. An additional siRNA-based approach was developed to selectively silence the protein expression of KIF1 B and KIF2A, facilitating autophagic turnover upon HSV-1 infection in mDCs. In conclusion, the technique of siRNA electroporation represents a promising strategy, to selectively ablate the expression of distinct proteins and to analyze their influence upon an HSV-1 infection.
CRIS-Team WoS Importer:2019-11-15

Sister-Mary-Joseph-Knoten der Brust – Beschreibung einer neuen Entität? - Popp, Judith; Heppt, Markus; Berking, Carola; Heppt, Franz (Journal der Deutschen Dermatologischen Gesellschaft, 2021)
CRIS-Team Scopus Importer:2021-04-23

Six-Color Confocal Immunofluorescence Microscopy with 4-Laser Lines - Heger, Lukas; Lühr, Jennifer J.; Amon, Lukas; Smith, Ana-Suncana; Eissing, Nathalie; Dudziak, Diana (Methods in Molecular Biology, 2021)
Confocal immunofluorescence microscopy is an advanced imaging technique routinely applied in the laboratory and clinics. Histological analyses are performed from tissue material. In general, a single fluorochrome per laser is employed, limiting simultaneous analysis to four antigens in one staining with a conventional 4-laser line microscope. Here, we describe a protocol for combining fluorochromes with the same excitation but different emission properties that allows for the analysis of six different antigens in confocal immunofluorescence microscopy with a conventional 4-laser line microscope. The proposed multiplexed method permits the identification and characterization of complex cell populations in rare tissue material.
CRIS-Team Scopus Importer:2021-10-01
Keywords: DC; Dendritic cells; Fluorochrome; Histology; Multicolor imaging; Tissue

Skin and Soft Tissue Infections Caused by Mycobacterium chelonae: More Common Than Expected? - Uslu, Ugur; Boehm, Olga; Heppt, Franz; Sticherling, Michael (Acta Dermato-Venereologica, 2019)
Mycobacterium chelonae is a rapidly growing non-tuberculous mycobacterium, which causes infections of the human skin and soft tissue. Despite an increasing incidence of such infections, patients are often misdiagnosed. We report here 5 patients with cutaneous and/or soft tissue infection due to M. chelonae who were diagnosed and treated at our centre. Two of the 5 patients were on immunosuppressive treatment. While clinical presentations differed in each patient, all had a long history of skin lesions. In addition to careful history-taking, tissue biopsies were obtained for mycobacterial culture and histopathological examination. Culture-directed antibiotic therapy was initiated, which resulted in a slow, but continuous, healing of the lesions. In summary, M. chelonae infections are still relatively rare, but should be considered in both immunocompromised and immunocompetent patients with prolonged skin lesions resistant to standard antibiotic treatment. For diagnosis, tissue analysis for mycobacterial culture and histopathological examination, and once diagnosed, adequate antibiotic treatment, is needed.
CRIS-Team WoS Importer:2019-09-10

Skin lesions may be misleading for final diagnosis – a case of delayed diagnosis and therapy - Meder, Christine; Sticherling, Michael (Journal der Deutschen Dermatologischen Gesellschaft, 2023)
CRIS-Team Scopus Importer:2023-06-09
Keywords: bacterial infections; T cell; virus

Sklerosierende Hauterkrankungen - Sticherling, Michael (Internist, 2019)
Sclerosing skin manifestations are more a symptom than a diagnosis and must therefore be meticulously clarified. Systemic scleroderma as a multiorgan disease must be distinguished from localized scleroderma or morphea because in addition to a different clinical picture they have a different prognosis and necessitate other therapeutic procedures. Rare sclerosing skin diseases with implications for internal medicine are eosinophilic fasciitis, Buschke’s scleredema adultorum, scleromyxedema and nephrogenic systemic fibrosis.
CRIS-Team Scopus Importer:2019-08-02
Keywords: Mixed connective tissue disease; Morphea; Scleredema adultorum; Scleromyxedema; Systemic scleroderma

Soluble CD83 ameliorates experimental colitis in mice - Eckhardt, Jenny; Kreiser, Simon; Döbbeler, Marina; Nicolette, C.; Debenedette, M. A.; Tcherepanova, I. Y.; Ostalecki, Christian; Pommer, A. J.; Becker, Christoph; Günther, Claudia; Zinser, E.; Mak, T. W.; et al. (Mucosal Immunology, 2014)
The physiological balance between pro- and anti-inflammatory processes is dysregulated in inflammatory bowel diseases (IBD) as in Crohn's disease and ulcerative colitis. Conventional therapy uses anti-inflammatory and immunosuppressive corticosteroids to treat acute-phase symptoms. However, low remission rate and strong side effects of these therapies are not satisfying. Thus, there is a high medical need for new therapeutic strategies. Soluble CD83, the extracellular domain of the transmembrane CD83 molecule, has been reported to have interesting therapeutic and immunosuppressive properties by suppressing dendritic cell (DC)-mediated T-cell activation and inducing tolerogenic DCs. However, the expression and function of CD83 in IBD is still unknown. Here, we show that CD83 expression is upregulated by different leukocyte populations in a chemical-induced murine colitis model. Furthermore, in this study the potential of sCD83 to modulate colitis using an experimental murine colitis model was investigated. Strikingly, sCD83 ameliorated the clinical disease symptoms, drastically reduced mortality, and strongly decreased inflammatory cytokine expression in mesenteric lymph nodes and colon. The infiltration of macrophages and granulocytes into colonic tissues was vigorously inhibited. Mechanistically, we could show that sCD83-induced expression of indolamine 2,3-dioxygenase is essential for its protective effects.
EVALuna2:1840

Soluble CD83 improves and accelerates wound healing by the induction of pro-resolving macrophages - Royzman, Dmytro; Peckert-Maier, Katrin; Stich, Lena; König, Christina; Wild, Andreas; Tauchi, Miyuki; Ostalecki, Christian; Kiesewetter, Franklin; Seyferth, Stefan; Lee, Geoffrey; Eming, Sabine A.; Fuchs, Maximilian; et al. (Frontiers in Immunology, 2022)
To facilitate the recovery process of chronic and hard-to-heal wounds novel pro-resolving treatment options are urgently needed. We investigated the pro-regenerative properties of soluble CD83 (sCD83) on cutaneous wound healing, where sCD83 accelerated wound healing not only after systemic but also after topical application, which is of high therapeutic interest. Cytokine profile analyses revealed an initial upregulation of inflammatory mediators such as TNFα and IL-1β, followed by a switch towards pro-resolving factors, including YM-1 and IL-10, both expressed by tissue repair macrophages. These cells are known to mediate resolution of inflammation and stimulate wound healing processes by secretion of growth factors such as epidermal growth factor (EGF) and vascular endothelial growth factor (VEGF), which promote vascularization as well as fibroblast and keratinocyte differentiation. In conclusion, we have found strong wound healing capacities of sCD83 beyond the previously described role in transplantation and autoimmunity. This makes sCD83 a promising candidate for the treatment of chronic- and hard-to-heal wounds.
CRIS-Team Scopus Importer:2022-10-28
Keywords: CD83; macrophages; stem cells; therapy; tissue regeneration; wound healing

Soluble CD83 inhibits skin inflammation to chemical sensitizers - Mihatsch, P.; Boyd, P.; Krzyzak, Lena; Lechmann, Matthias; Nicolas, J.; Mahler, Vera; Steinkasserer, Alexander; Vocanson, Marc (2016)
EVALuna2:26037

Soluble CD83 Inhibits T Cell Activation by Binding to the TLR4/MD-2 Complex on CD14(+) Monocytes - Horvatinovich, Joe M.; Grogan, Elizabeth W.; Norris, Marcus; Steinkasserer, Alexander; Lemos, Henrique; Mellor, Andrew L.; Tcherepanova, Irina Y.; Nicolette, Charles A.; Debenedette, Mark A. (Journal of Immunology, 2017)
The transmembrane protein CD83, expressed on APCs, B cells, and T cells, can be expressed as a soluble form generated by alternative splice variants and/or by shedding. Soluble CD83 (sCD83) was shown to be involved in negatively regulating the immune response. sCD83 inhibits T cell proliferation in vitro, supports allograft survival in vivo, prevents corneal transplant rejection, and attenuates the progression and severity of autoimmune diseases and experimental colitis. Although sCD83 binds to human PBMCs, the specific molecules that bind sCD83 have not been identified. In this article, we identify myeloid differentiation factor-2 (MD-2), the coreceptor within the TLR4/MD-2 receptor complex, as the high-affinity sCD83 binding partner. TLR4/MD-2 mediates proinflammatory signal delivery following recognition of bacterial LPSs. However, altering TLR4 signaling can attenuate the proinflammatory cascade, leading to LPS tolerance. Our data show that binding of sCD83 to MD-2 alters this signaling cascade by rapidly degrading IL-1R-associated kinase-1, leading to induction of the anti-inflammatory mediators IDO, IL-10, and PGE2 in a COX-2-dependent manner. sCD83 inhibited T cell proliferation, blocked IL-2 secretion, and rendered T cells unresponsive to further downstream differentiation signals mediated by IL-2. Therefore, we propose the tolerogenic mechanism of action of sCD83 to be dependent on initial interaction with APCs, altering early cytokine signal pathways and leading to T cell unresponsiveness.
EVALuna2:26040

Soluble CD83 modulates human-monocyte-derived macrophages toward alternative phenotype, function, and metabolism. - Peckert-Maier, Katrin; Wild, Andreas; Sprißler, Laura; Fuchs, Maximilian; Beck, Philipp; Auger, Jean-Philippe; Sinner, Pia; Strack, Astrid; Mühl-Zürbes, Petra; Ramadan, Ntilek; Kunz, Meik; Krönke, Gerhard; et al. (Frontiers in Immunology, 2023)
Alterations in macrophage (Mφ) polarization, function, and metabolic signature can foster development of chronic diseases, such as autoimmunity or fibrotic tissue remodeling. Thus, identification of novel therapeutic agents that modulate human Mφ biology is crucial for treatment of such conditions. Herein, we demonstrate that the soluble CD83 (sCD83) protein induces pro-resolving features in human monocyte-derived Mφ biology. We show that sCD83 strikingly increases the expression of inhibitory molecules including ILT-2 (immunoglobulin-like transcript 2), ILT-4, ILT-5, and CD163, whereas activation markers, such as MHC-II and MSR-1, were significantly downregulated. This goes along with a decreased capacity to stimulate alloreactive T cells in mixed lymphocyte reaction (MLR) assays. Bulk RNA sequencing and pathway analyses revealed that sCD83 downregulates pathways associated with pro-inflammatory, classically activated Mφ (CAM) differentiation including HIF-1A, IL-6, and cytokine storm, whereas pathways related to alternative Mφ activation and liver X receptor were significantly induced. By using the LXR pathway antagonist GSK2033, we show that transcription of specific genes (e.g., PPARG, ABCA1, ABCG1, CD36) induced by sCD83 is dependent on LXR activation. In summary, we herein reveal for the first time mechanistic insights into the modulation of human Mφ biology by sCD83, which is a further crucial preclinical study for the establishment of sCD83 as a new therapeutical agent to treat inflammatory conditions.
EVALuna2:549687

Soluble CD83 promotes cutaneous wound healing in an IDO-and beta-catenindependent manner - Royzman, Dmytro; Peckert-Maier, K.; Stich, L.; Wild, Andreas; Ostalecki, C.; Kiesewetter, Franklin; Seyferth, Stefan; Lee, Geoffrey; Eming, S. A.; Berking, Carola; Zinser, Elisabeth; Steinkasserer, Alexander (EXPERIMENTAL DERMATOLOGY, 2022)
CRIS-Team WoS Importer:2022-03-04

Soluble CD83 Triggers Resolution of Arthritis and Sustained Inflammation Control in IDO Dependent Manner - Royzman, Dmytro; Andrev, Darja; Stich, Lena; Rauh, Manfred; Bäuerle, Tobias; Ellmann, Stephan; Boon, Louis; Kindermann, Markus; Peckert, Katrin; Bozec, Aline; Schett, Georg; Steinkasserer, Alexander; et al. (Frontiers in Immunology, 2019)
Interference with autoimmune-mediated cytokine production is a key yet poorly developed approach to treat autoimmune and inflammatory diseases such as rheumatoid arthritis. Herein, we show that soluble CD83 (sCD83) enhances the resolution of autoimmune antigen-induced arthritis (AIA) by strongly reducing the expression levels of cytokines such as IL-17A, IFN gamma, IL-6, and TNF alpha within the joints. Noteworthy, also the expression of RANKL, osteoclast differentiation, and joint destruction was significantly inhibited by sCD83. In addition, osteoclasts which were cultured in the presence of synovial T cells, derived from sCD83 treated AIA mice, showed a strongly reduced number of multinuclear large osteoclasts compared to mock controls. Enhanced resolution of arthritis by sCD83 was mechanistically based on IDO, since inhibition of IDO by 1-methyltryptophan completely abrogated sCD83 effects on AIA. Blocking experiments, using anti-TGF-beta antibodies further revealed that also TGF-beta is mechanistically involved in the sCD83 induced reduction of bone destruction and cartilage damage as well as enhanced resolution of inflammation. Resolution of arthritis was associated with increased numbers of regulatory T cells, which are induced in a sCD83-IDO-TGF-beta dependent manner. Taken together, sCD83 represents an interesting approach for downregulating cytokine production, inducing regulatory T cells and inducing resolution of autoimmune arthritis.
CRIS-Team WoS Importer:2019-04-12

Sonnenschutz, Stahl, Strahl, Salbe und Systemtherapie - Berking, Carola; Szeimies, R. M. (Hautarzt, 2020)
CRIS-Team Scopus Importer:2020-08-07

SOX10-based drug repurposing identifies novel therapeutic targets in uveal melanoma - Wessely, A.; Kammerbauer, C.; Lischer, Christopher; Weich, A.; Vera, Julio; Berking, Carola; Heppt, Markus (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2022)
CRIS-Team WoS Importer:2022-09-23

Spatial, structural and density determinants of DC:T cell interaction under immunostimulatory conditions - Vurnek, D.; Amon, Lukas; Buttazzo, L.; Lehmann, C.; Zaburdaev, Vasily; Dudziak, Diana (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Specific dermatoses of pregnancy - Ambros-Rudolph, C. M.; Sticherling, Michael (Hautarzt, 2017)
The specific dermatoses of pregnancy represent a heterogeneous group of inflammatory skin diseases related to pregnancy and/or the postpartum period. A clinically relevant classification has been well established over the past 10 years and includes pemphigoid gestationis, polymorphic eruption of pregnancy, intrahepatic cholestasis of pregnancy, and atopic eruption of pregnancy. The hallmark of all four entities is severe pruritus that is accompanied by characteristic skin changes. While some of these dermatoses are distressing only to the mother because of pruritus, others may be associated with significant fetal risks. Early diagnosis and prompt treatment are therefore essential. In this review, we discuss in detail pemphigoid gestationis, polymorphic and atopic eruptions of pregnancy whereas intrahepatic cholestasis of pregnancy is discussed in a separate article (Kremer A, Ständer S, DOI 10.1007/s00105-016-3923-y ). Furthermore, we present a helpful algorithm for diagnosis and management of pruritus in pregnancy.
EVALuna2:34362

Specific phenotype and function of CD56-expressing innate immune cell subsets in human thymus - Gerstner, Stephanie; Köhler, Wolfgang; Heidkamp, Gordon Frederik; Purbojo, Ariawan; Uchida, Shizuka; Ekici, Arif Bülent; Heger, Lukas; Luetke-Eversloh, Merlin; Schubert, Ralf; Bader, Peter; Klingebiel, Thomas; Koehl, Ulrike; et al. (Journal of Leukocyte Biology, 2016)
Whereas innate immune cells, such as NK and innate lymphoid cells (ILCs), have been characterized in different human tissues, knowledge on the thymic CD56-expressing cell subsets is limited. In this study, the rare subpopulations of thymic CD56(+)CD3(-) cells from samples of >100 patients have been successfully analyzed. The results revealed fundamental differences between thymic and peripheral blood (PB) CD56(+)CD3(-) cells. Thymic tissues lacked immunoregulatory CD56(high)CD16(dim) NK cells but showed two Eomes(+)CD56(dim) subsets on which common NK cell markers were significantly altered. CD56(dim)CD16(high) cells expressed high amounts of NKG2A, NKG2D, and CD27 with low CD57. Conversely, CD56(dim)CD16(dim) cells displayed high CD127 but low expression of KIR, NKG2D, and natural cytotoxicity receptors (NCRs). Thymic CD56(+)CD3(-) cells were able to gain cytotoxicity but were especially immunoregulatory cells, producing a broad range of cytokines. Finally, one population of thymic CD56(+) cells resembled conventional NK cells, whereas the other represented a novel, noncanonical NK subset.
EVALuna2:9311

Spontaneous regression rates of actinic keratosis: a systematic review and pooled analysis of randomized controlled trials. - Steeb, Theresa; Petzold, Anne; Hornung, Annkathrin; Wessely, Anja; Berking, Carola; Heppt, Markus (Scientific Reports, 2022)
Actinic keratosis (AK) are precancerous lesions of the skin which may progress to invasive squamous cell carcinoma. However, single lesions may also persist or even regress and heal spontaneously. Until now, evidence on the natural course of AK including spontaneous regression is limited. We aimed to synthesize regression rates of AK. We performed a systematic literature research in Medline, Embase, and CENTRAL for eligible trials until 3rd March 2020. Spontaneous regression rates were pooled using a random-effects model to calculate pooled proportions of participant-specific and lesion-specific complete clearance rates reported for the placebo arms of randomized controlled trials. Subgroup analyses were performed to dissect differences according to the type of placebo, immunocompetence of the participants, and localization of the lesions. Data from 38 records was included. The pooled participant-specific clearance rate was 8% (95% CI 6-10%, I2 = 71%) while the lesion-specific clearance rate was 23% (95% CI 16-31%, I2 = 97%). The highest participant- and lesion-specific clearance rates were achieved 12 weeks after the end of treatment (12% and 33%, respectively). Subgroup analysis revealed participant- as well as lesion-specific clearance rates of 0% for organ transplant recipients (OTR). We conclude that only a few participants achieve complete regression of their AK without any active treatment. Besides, the results underline that lesion clearance without active treatment is unlikely in OTR. Thus, early and consequent treatment of AK is recommended. Special attention should be paid when treating AK of OTR.
EVALuna2:502113

Stability and activity of MCSP-specific chimeric antigen receptors (CARs) depend on the scFv antigen-binding domain and the protein backbone - Krug, Christian; Birkholz, Katrin; Paulus, Alexander; Schwenkert, Michael; Schmidt, Patrick; Hoffmann, Nicole; Hombach, Andreas; Fey, Georg; Abken, Hinrich; Schuler, Gerold; Schuler-Thurner, Beatrice; Dörrie, Jan; et al. (Cancer Immunology Immunotherapy, 2015)
Chimeric antigen receptor (CAR)-modified T cells emerged as effective tools in the immunotherapy of cancer but can produce severe on-target off-tissue toxicities. This risk can conceivably be overcome, at least partially, by transient transfection. The design of CARs, however, has so far not been optimized for use in non-permanent T cell modification. Here we compared the performance of T cells modified with three different first- and second-generation CARs, each specific for MCSP (HMW-MAA) which is commonly expressed by melanoma cells. Upon RNA transfer, the expression of all receptors was limited in time. The second-generation CARs, which combined CD28-CD3ζ signaling, were expressed at higher levels and more prolonged than first-generation CARs with CD3ζ only. The CD28 domain increased the cytokine production, but had only an indirect effect on the lytic capacity, by prolonging the CAR expression. Especially for the second-generation CARs, the scFv clearly impacted the level and duration of CAR expression and the T cell performance. Thus, we identified a CAR high in both expression and anti-tumor cell reactivity. T cells transfected with this CAR increased the mean survival time of mice after challenge with melanoma cells. To facilitate clinical application, this CAR was used to redirect T cells from late-stage melanoma patients by RNA transfection. These T cells mediated effective antigen-specific tumor cell lysis and release of pro-inflammatory cytokines, even after cryoconservation of the transfected T cells. Taken together, the analysis identified a CAR with superior anti-melanoma performance after RNA transfer which is a promising candidate for clinical exploration.
EVALuna2:19545

Standardized Computer-Assisted Analysis of PRAME Immunoreactivity in Dysplastic Nevi and Superficial Spreading Melanomas - Koch, Elias; Erdmann, Michael; Berking, Carola; Kiesewetter, Franklin; Kramer, Rafaela; Schliep, Stefan; Heppt, Markus (International Journal of Molecular Sciences, 2023)
PRAME (PReferentially expressed Antigen in MElanoma) is a cancer testis antigen that is frequently expressed in melanoma compared to benign melanocytic proliferations and nevi. However, the interpretation of the intensity and distribution of PRAME immunostaining is not standardized a lot, which makes interpretation difficult. PRAME-stained histological slides of superficial spreading melanomas (SSM) and dysplastic nevi (DN) were digitized and analyzed using the digital pathology and image platform QuPath. t-tests and ROC AUCs were performed with SPSS. A p-value of <0.05 was used for statistical significance, and a ROC AUC score of >0.8 was considered a good result. A cut-off score was defined in an evaluation cohort and subsequently analyzed in an independent validation cohort. In total, 81 PRAME-stained specimens were included. The evaluation cohort included 32 (50%) SSM and 32 (50%) DN, and the mean of PRAME-positive cells/mm2 for the entire lesion was 455.3 (SD 428.2) in SSM and 60.5 (SD 130.1; p < 0.001) in DN. The ROC AUC of PRAME-positive cells of the entire lesion was 0.866, and in the epidermis it was 0.901. The defined cut-off score to distinguish between DN and SSM was 97.67 cells/mm2. In the validation cohort, 16 out of 17 cases (94.1%) were correctly classified by the cut-off score. The computer-aided assessment of PRAME immunostaining is a useful tool in dermatopathology to distinguish between DN and SSM. Lesions with a moderate expression and indifferent morphologic features will remain a challenge for dermatopathologists.
CRIS-Team Scopus Importer:2023-04-21
Keywords: computer-assisted analysis; dysplastic nevus; immunohistochemistry; melanoma; PRAME

Status report on the atopic dermatitis registry TREATgermany Statusbericht zum Neurodermitisregister TREATgermany - Siegels, D.; Haufe, E.; Heinrich, L.; Werfel, T.; Weidinger, S.; Schmitt, Jochen; Abraham, S.; Asefi, M.; Asmussen, Andrea; Augustin, M.; Bell, Magnus; Bieber, T.; et al. (Allergologie, 2021)
CRIS-Team Scopus Importer:2021-10-22
Keywords: Atopic dermatitis; Atopic eczema; Clinical registry; Clinical symptom severity; Systemic treatment

Step-by-step Improvement of mRNA-electroporated dendritic Cells in a Phase I / II Clinical Study in cutaneous Melanoma Patients: better Survival correlates with a higher Immunoscore and increased Expression of PEBP1 in the Blood - Dörrie, Jan; Schaft, Niels; Gross, S.; Ostalecki, Christian; Eberhardt, Martin; Vera-Gonzales, J.; Uslu, Ugur; Moreira, Alvaro; Koch, Elias; Kummer, Mirko; Erdmann, M.; Schliep, S.; et al. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2020)
CRIS-Team WoS Importer:2020-09-11

Still Alive and Kicking: In-Vitro-Generated GM-CSF Dendritic Cells! - Lutz, Manfred B.; Inaba, Kayo; Schuler, Gerold; Romani, Nikolaus (Immunity, 2016)
EVALuna2:19572

Stringent monitoring can decrease mortality of immune checkpoint inhibitor induced cardiotoxicity - Wang, Ying; Ertl, Carolin; Schmitt, Christina; Hammann, Linda; Kramer, Rafaela; Grabmaier, Ulrich; Schöberl, Florian; Anz, David; Piseddu, Ignazio; Pesch, Giulia; Vera, Julio; Froehlich, Waltraud; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background: Immune checkpoint inhibitor (ICI)-induced myocarditis is a rare immune-related adverse event (irAE) with a fatality rate of 40%–46%. However, irMyocarditis can be asymptomatic. Thus, improved monitoring, detection and therapy are needed. This study aims to generate knowledge on pathogenesis and assess outcomes in cancer centers with intensified patient management. Methods: Patients with cardiac irAEs from the SERIO registry (www.serio-registry.org) were analyzed for demographics, ICI-related information (type of ICI, therapy line, combination with other drugs, onset of irAE, and tumor response), examination results, irAE treatment and outcome, as well as oncological endpoints. Cardiac biopsies of irMyocarditis cases (n = 12) were analyzed by Nanostring and compared to healthy heart muscle (n = 5) and longitudinal blood sampling was performed for immunophenotyping of irMyocarditis-patients (n = 4 baseline and n = 8 during irAE) in comparison to patients without toxicity under ICI-therapy (n = 4 baseline and n = 7 during ICI-therapy) using flow cytometry. Results: A total of 51 patients with 53 cardiac irAEs induced by 4 different ICIs (anti-PD1, anti-PD-L1, anti-CTLA4) were included from 12 centers in 3 countries. Altogether, 83.0% of cardiac irAEs were graded as severe or life-threatening, and 11.3% were fatal (6/53). Thus, in centers with established consequent troponin monitoring, work-up upon the rise in troponin and consequent treatment of irMyocarditis with corticosteroids and –if required–second-line therapy mortality rate is much lower than previously reported. The median time to irMyocarditis was 36 days (range 4–1,074 days) after ICI initiation, whereas other cardiotoxicities, e.g. asystolia or myocardiopathy, occurred much later. The cytokine-mediated signaling pathway was differentially regulated in myocardial biopsies as compared to healthy heart based on enrichment Gene Ontology analysis. Additionally, longitudinal peripheral blood mononuclear cell (PBMC) samples from irMyocarditis-patients indicated ICI-driven enhanced CD4+ Treg cells and reduced CD4+ T cells. Immunophenotypes, particularly effector memory T cells of irMyocarditis-patients differed from those of ICI-treated patients without side effects. LAG3 expression on T cells and PD-L1 expression on dendritic cells could serve as predictive indicators for the development of irMyocarditis. Conclusion: Interestingly, our cohort shows a very low mortality rate of irMyocarditis-patients. Our data indicate so far unknown local and systemic immunological patterns in cardiotoxicity.
CRIS-Team Scopus Importer:2024-06-28
Keywords: cardiovascular toxicity; checkpoint inhibitor; immunotherapy; melanoma; myocarditis

STRUCTURAL ENTHESEAL LESIONS IN PSORIASIS PATIENTS ARE ASSOCIATED WITH AN INCREASED RISK OF PROGRESSION TO PSORIATIC ARTHRITIS - A PROSPECTIVE COHORT STUDY - Simon, David; Tascilar, K.; Kleyer, Arnd; Bayat, Sara; Kampylafka, E.; Hueber, Axel; Rech, Jürgen; Schuster, Louis; Engel, K.; Sticherling, Michael; Schett, Georg (ANNALS OF THE RHEUMATIC DISEASES, 2020)
CRIS-Team WoS Importer:2020-08-21

Subclinical joint inflammation in patients with psoriasis without concomitant psoriatic arthritis: a cross-sectional and longitudinal analysis - Faustini, Francesca; Simon, Dominic; Oliveira, Isabelle; Kleyer, Arnd; Haschka, Judith; Englbrecht, Matthias; Cavalcante, Alan Rodrigues; Kraus, Sebastian; Tabosa, Taiane Ponte; Figueiredo, Camille; Hueber, Axel; Kocijan, Roland; et al. (Annals of the Rheumatic Diseases, 2016)
To search for subclinical inflammatory joint disease in patients with psoriasis without psoriatic arthritis (PsA), and to determine whether such changes are associated with the later development of PsA.Eighty-five subjects without arthritis (55 with psoriasis and 30 healthy controls) received high field MRI of the hand. MRI scans were scored for synovitis, osteitis, tenosynovitis and periarticular inflammation according to the PsAMRIS method. Patients with psoriasis additionally received complete clinical investigation, high-resolution peripheral quantitative CT for detecting erosions and enthesiophytes and were followed up for at least 1 year for the development of PsA.47% of patients with psoriasis showed at least one inflammatory lesion on MRI. Synovitis was the most prevalent inflammatory lesion (38%), while osteitis (11%), tenosynovitis (4%) and periarticular inflammation (4%) were less frequent. The mean (±SD) PsAMRIS synovitis score was 3.0±2.5 units. Enthesiophytes and bone erosions were not different between patients with psoriasis with or without inflammatory MRI changes. The risk for developing PsA was as high as 60% if patients had subclinical synovitis and symptoms related to arthralgia, but only 13% if patients had normal MRIs and did not report arthralgia.Prevalence of subclinical inflammatory lesions is high in patients with cutaneous psoriasis. Arthralgia in conjunction with MRI synovitis constitutes a high-risk constellation for the development of PsA.
EVALuna2:13265

SUBJECTIVE ASSESSMENT OF PHYSICAL FUNCTION DOES NOT SUFFICIENTLY EXPLAIN VARIANCE OF MEASURED HAND FUNCTION AND GRIP STRENGTH IN ARTHRITIS PATIENTS AND NON-ARTHRITIS CONTROLS - Liphardt, Anna-Maria; Tascilar, Koray; Coppers, Birte; Manger, Eva; Liehr, Sonja; Bieniek, Lisa Maria; Bayat, Sara; Simon, David; Sticherling, Michael; Rech, Jürgen; Hueber, A.; Schett, Georg; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

Subsets of CD1c+ DCs: Dendritic Cell Versus Monocyte Lineage - Heger, Lukas; Hofer, Thomas P.; Bigley, Venetia; de Vries, I. Jolanda M.; Dalod, Marc; Dudziak, Diana; Ziegler-Heitbrock, Loems (Frontiers in Immunology, 2020)
Currently three bona fide dendritic cell (DC) types are distinguished in human blood. Herein we focus on type 2 DCs (DC2s) and compare the three defining markers CD1c, CD172, and CD301. When using CD1c to define DC2s, a CD14+ and a CD14− subset can be detected. The CD14+ subset shares features with monocytes, and this includes substantially higher expression levels for CD64, CD115, CD163, and S100A8/9. We review the current knowledge of these CD1c+CD14+ cells as compared to the CD1c+CD14− cells with respect to phenotype, function, transcriptomics, and ontogeny. Here, we discuss informative mutations, which suggest that two populations have different developmental requirements. In addition, we cover subsets of CD11c+CD8− DC2s in the mouse, where CLEC12A+ESAMlow cells, as compared to the CLEC12A−ESAMhigh subset, also express higher levels of monocyte-associated markers CD14, CD3, and CD115. Finally, we summarize, for both man and mouse, the data on lower antigen presentation and higher cytokine production in the monocyte-marker expressing DC2 subset, which demonstrate that the DC2 subsets are also functionally distinct.
CRIS-Team Scopus Importer:2020-10-30
Keywords: CD14; CD172; CD1c; CD301; DC subsets; DC2; dendritic cells

Successful Treatment of a primary cutaneous aggressive epidermotropic CD8+T-cell Lymphoma with Nivolumab - Toussaint, Frédéric; Erdmann, M.; Grosch, Ella; Schuler, Gerold; Schliep, S.; Heinzerling, Lucie (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-09-13

Successful treatment of refractory palmoplantar psoriasis in a psoriatic arthritis patient with the JAK inhibitor tofacitinib - Valor-Mendez, Larissa; Sticherling, Michael; Kleyer, Arnd; Schett, Georg (Clinical and Experimental Rheumatology, 2021)
CRIS-Team WoS Importer:2021-03-26

Successful treatment of ulcerative necrobiosis lipoidica with JAK inhibitor - Erfurt-Berge, Cornelia; Sticherling, Michael (Journal of the European Academy of Dermatology and Venereology, 2020)
Necrobiosis lipoidica (NL) is a rare granulomatous disease that predominantly affects middle aged women and is often associated with diabetes mellitus and other metabolic disorders 1 . About 30 % of the patients develop ulcerations within NL lesions on the lower leg, which complicate the course of disease and are often recalcitrant to standard wound care procedures 2 . Systemic therapies for NL are reported only for single cases or in small case series with varying outcome 3 . Randomized controlled trials are missing due to the character of NL as an orphan disease.
EVALuna2:212858

Sudden Otovestibular Dysfunction in 3 Metastatic Melanoma Patients Treated With Immune Checkpoint Inhibitors - Stuermer, Suzan H.; Lechner, Axel; Berking, Carola (Journal of Immunotherapy, 2021)
Immune-related adverse events have been described in 86%-96% of high-risk melanoma patients treated with immune checkpoint inhibitors (ICI), while in 17%-59% of cases these are classified as severe or even life-threatening. The most common immune-related adverse events include diarrhea, fatigue, hypothyroidism, and hepatitis. Bilateral uveitis and unspecific vertigo have been described in 1% of cases, respectively, in the pivotal studies of ICIs, but the affection of the vestibule-cochlear system has not been reported before. In this case series, we present 3-stage IV melanoma patients with sudden onset of otovestibular dysfunction (hearing loss and vestibulopathy), partly combined with uveitis because of ICIs. We describe detailed diagnostic work-up and therapeutic interventions and discuss possible pathogenic mechanisms of this rare and disabling event.
CRIS-Team WoS Importer:2021-06-11

Sun protection in outdoor workers – Development and validation of standardized questionnaires for behavior and knowledge - Rönsch, Henriette; Rocholl, Marc; Ludewig, Michaela; Staudt, Andreas; Langner, Mathias; Steeb, Theresa; Wilke, Annika; John, Swen Malte; Berking, Carola; Beissert, Stefan; Bauer, Andrea (Journal der Deutschen Dermatologischen Gesellschaft, 2024)
Background and objectives: Outdoor workers are at increased risk of developing non-melanoma skin cancer. We aimed to address the lack of validated German-language measurement instruments for outdoor workers’ sun safety behavior and knowledge by compiling and validating two questionnaires. Participants and methods: By expert consensus, items for the assessment of protective behavior (OccuSun) were compiled based on existing instruments. For knowledge, a translation of the Skin Cancer and Sun Knowledge (SCSK) scale was selected. After a pre-test, a validation study including 68 outdoor workers (62% female) was conducted in 2020. Results: The retest reliability was r = 0.93 (95% confidence interval: 0.86–0.96) for the protection score and rs = 0.78 (0.67–0.86) for the knowledge score. Protective behaviors were correlated with respective diary data (0.38 ≤ rs ≤ 0.74, p < 0.001) and skin pigmentation changes (–0.23 ≥ rs ≥ –0.42, 0.007 ≤ p ≤ 0.165) but not with self-reported sunburn frequency (0.21 ≥ rs ≥ –0.04). Conclusions: Among German outdoor workers, two questionnaires for the assessment of sun protection behavior (OccuSun) and knowledge (SCSK) demonstrated good reliability. The OccuSun had generally good validity. Both instruments are fit for subsequent validation to determine their sensitivity to change.
CRIS-Team Scopus Importer:2024-04-12

Suppression of proatherogenic leukocyte interactions by MCS-18 - Impact on advanced atherosclerosis in ApoE-deficient mice - Kühn, Constanze; Tauchi, Miyuki; Stumpf, Christian; Daniel, Christoph; Bäuerle, Tobias; Schwarz, Marc; Kerek, Franz; Steinkasserer, Alexander; Zinser, Elisabeth; Achenbach, Stephan; Dietel, Barbara (Atherosclerosis, 2016)
Atherosclerosis is associated with chronic inflammatory responses of the arterial blood vessels. The previously observed protective effect of the MCS-18 substance against the initiation of atherosclerosis in a murine model was explained by its pronounced anti-inflammatory activity. Here, we investigated its impact on murine plaque progression in advanced atherosclerosis and on proatherogenic processes.ApoE-deficient mice were fed a high-fat diet for 12 weeks to induce atherosclerosis, followed by normal chow and intraperitoneal injections of either MCS-18 (500 ?g, n = 10) or saline (n = 10) twice a week for another 12 weeks. Plaque size was reduced in MCS-18 treated mice compared to controls (p = 0.001), which was associated with a reduced size of the lipid core (p = 0.01). There was a decrease in apoptotic cells (p = 0.02), endothelial ICAM-1 expression (p < 0.001), and macrophage density (p = 0.01) in the MCS-18 group. In addition, human and murine dendritic cells (DCs) and human umbilical vein endothelial cells (HUVECs) were treated with MCS-18 (50-200 ?g/ml) to analyze cell migration and adhesion under flow conditions. MCS-18 reduced human (p = 0.01) and murine (p = 0.006) DC migration. Furthermore, adhesion of MCS-18-treated DCs to a HUVEC monolayer was decreased (p < 0.001). Compared to controls, CD209 (p < 0.001) and CCR7 (p = 0.003) expression was decreased in MCS-18-treated DCs, while in HUVECs lower levels of ICAM-1 (p < 0.001) and of phosphorylated NF-?B-p65 (p = 0.002) were observed. Blocking of ICAM-1 reduced DC adhesion (p < 0.001).MCS-18 exhibits interesting therapeutic effects when applied in advanced murine atherosclerosis. Its antiatherogenic impact might be associated with a suppressed adhesion to the endothelium due to down-regulation of endothelial ICAM-1 expression.
EVALuna2:12031

Surveillance of patients with conjunctival melanoma in German-speaking countries: A multinational survey of the German dermatologic cooperative oncology group - Wessely, Anja; Steeb, Theresa; Berking, Carola; Schlaak, Max; Heppt, Markus; Alter, Mareike; Bayerl, Christiane; Bender, Armin; Bruning, Guido; Dabrowski, Evelyn; Debus, Dirk; Devereux, Nina; et al. (European Journal of Cancer, 2021)
CRIS-Team Scopus Importer:2020-12-11

Survival of metastatic melanoma patients after dendritic cell vaccination correlates with expression of leukocyte phosphatidylethanolamine-binding protein 1/Raf kinase inhibitory protein - Buschow, Sonja I.; Ramazzotti, Matteo; Reinieren-Beeren, Inge M. J.; Heinzerling, Lucie; Westdorp, Harm; Stefanini, Irene; Beltrame, Luca; Hato, Stanleyson V.; Ellebaek, Eva; Gross, Stefanie; Van Anh Nguyen,; Weinlich, Georg; et al. (Oncotarget, 2017)
Immunotherapy for metastatic melanoma offers great promise but, to date, only a subset of patients have responded. There is an urgent need to identify ways of allocating patients to the most beneficial therapy, to increase survival and decrease therapy-associated morbidity and costs. Blood-based biomarkers are of particular interest because of their straightforward implementation in routine clinical care. We sought to identify markers for dendritic cell (DC) vaccine-based immunotherapy against metastatic melanoma through gene expression analysis of peripheral blood mononuclear cells. A large-scale microarray analysis of 74 samples from two treatment centers, taken directly after the first round of DC vaccination, was performed. We found that phosphatidylethanolamine binding protein 1 (PEBP1)/Raf Kinase inhibitory protein (RKIP) expression can be used to identify a significant proportion of patients who performed poorly after DC vaccination. This result was validated by q-PCR analysis on blood samples from a second cohort of 95 patients treated with DC vaccination in four different centers. We conclude that low PEBP1 expression correlates with poor overall survival after DC vaccination. Intriguingly, this was only the case for expression of PEBP1 after, but not prior to, DC vaccination. Moreover, the change in PEBP1 expression upon vaccination correlated well with survival. Further analyses revealed that PEBP1 expression positively correlated with genes involved in T cell responses but inversely correlated with genes associated with myeloid cells and aberrant inflammation including STAT3, NOTCH1, and MAPK1. Concordantly, PEBP1 inversely correlated with the myeloid/lymphoid-ratio and was suppressed in patients suffering from chronic inflammatory disease.
EVALuna2:34315

Survivin-specific T-cell reactivity correlates with tumor response and patient survival: A phase-II peptide vaccination trial in metastatic melanoma - Becker, Juergen C.; Andersen, Mads H.; Hofmeister-Mueller, Valeska; Wobser, Marion; Frey, Lidia; Sandig, Christiane; Walter, Steffen; Singh-Jasuja, Harpreet; Kämpgen, Eckhart; Opitz, Andreas; Zapatka, Marc; Broecker, Eva-B.; et al. (Cancer Immunology, Immunotherapy, 2012)
Keywords: Melanoma; Peptide vaccination; Survivin; T-cell reactivity; Therapy

Sweet SIGNs: IgG glycosylation leads the way in IVIG-mediated resolution of inflammation - Brückner, Christin; Lehmann, Christian; Dudziak, Diana; Nimmerjahn, Falk (International Immunology, 2017)
A hallmark of many chronic inflammatory and autoimmune diseases is that there is an impaired resolution of inflammation and return to the steady state. The infusion of high doses of pooled serum IgG preparations from thousands of donors [intravenous immunoglobulin (IVIG) therapy] has been shown to induce resolution of inflammation in a variety of chronic inflammatory and autoimmune diseases, suggesting that IgG molecules can instruct the immune system to stop inflammatory processes and initiate the return to the steady state. The aim of this review is to discuss how insights into the mechanism of IVIG activity may help to understand the molecular and cellular pathways underlying resolution of inflammation. We will put a special emphasis on pathways dependent on the IgG FC domain and IgG sialylation, as several recent studies have provided new insights into how this glycosylation-dependent pathway modulates innate and adaptive immune responses through different sets of C-type or I-type lectins.
EVALuna2:34371

Systemic sclerosis - the dermatological perspective - Sticherling, Michael (Journal der Deutschen Dermatologischen Gesellschaft, 2019)
Systemic scleroderma/systemic sclerosis (SSc) is an inflammatory connective tissue disease clinically characterized by two major subtypes: limited and diffuse SSc. While both conditions present with Raynaud's phenomenon (paroxysmal digital ischemia), diffuse SSc is associated with rapid disease progression and early - prognostically relevant - involvement of internal organs. Treatment is challenging. In addition to general lifestyle modifications, measures include treatments aimed at improving circulation as well as immunosuppressive and immunomodulatory drugs. However, these agents are effective only in terms of slowing disease progression.
CRIS-Team WoS Importer:2019-08-13

Systemic therapy with calcitonin has positive clinical effects on systemic sclerosis in patients with cutaneous manifestations - Uslu, Ugur; Streiff, Laura; Sticherling, Michael (European Journal of Dermatology, 2018)
BACKGROUND: Calcitonin gene-related peptide (CGRP) is a vasodilatory neuropeptide that plays an important role in the blood vessels of heart and peripheral circulation, a lack of which may cause vasculopathies. OBJECTIVE: In this study, the clinical course of disease, as well as the efficacy, side effects, and patient satisfaction of systemic calcitonin therapy in patients with systemic sclerosis (SSc), was evaluated. METHODS: Forty-nine patients received repetitive intravenous calcitonin infusions as first-line treatment. The average number of cycles was 12.2 ± 10.3 over a period of 30 months (each cycle: 100 U/day over 10 days). Clinical examinations, laboratory tests, and organ imaging were performed before the start of, and at regular intervals during therapy in order to evaluate organ manifestations and the clinical course of the disease. In addition, patients' own experiences of the therapy, side effects, and therapy success were evaluated with standardized questionnaires. RESULTS: Over the course of the treatment, seven patients experienced improvements in their condition with a considerable reduction in digital ulceration and improved movement (14.3%). Pulmonary function in seven patients improved during the therapy (14.3%). With regards to side effects, nausea (41.7%), headaches (33.3%), fluctuations in blood pressure (29.2%), and flushing (29.2%) were observed. Overall, 45.8% of patients evaluated the therapy as good and 58.3% would undergo further courses of therapy with calcitonin. CONCLUSIONS: Systemic calcitonin treatment seems to have positive clinical effects on SSc and contributes to relieving symptoms, especially in patients with cutaneous manifestations. No severe side effects were reported during this study.
EVALuna2:34793

Systemische Sklerodermie - die dermatologische Sicht - Sticherling, Michael (Journal der Deutschen Dermatologischen Gesellschaft, 2019)
EVALuna2:212837

Systems biology-based investigation of cooperating microRNAs as monotherapy or adjuvant therapy in cancer - Lai, Xin; Eberhardt, Martin; Schmitz, Ulf; Vera, Julio (Nucleic Acids Research, 2019)
MicroRNAs (miRNAs) are short, noncoding RNAs that regulate gene expression by suppressing mRNA translation and reducing mRNA stability. A miRNA can potentially bind many mRNAs, thereby affecting the expression of oncogenes and tumor suppressor genes as well as the activity of whole pathways. The promise of miRNA therapeutics in cancer is to harness this evolutionarily conserved mechanism for the coordinated regulation of gene expression, and thus restoring a normal cell phenotype. However, the promiscuous binding of miRNAs can provoke unwanted off-target effects, which are usually caused by high-dose single-miRNA treatments. Thus, it is desirable to develop miRNA therapeutics with increased specificity and efficacy. To achieve that, we propose the concept of miRNA cooperativity in order to exert synergistic repression on target genes, thus lowering the required total amount of miRNAs. We first review miRNA therapies in clinical application. Next, we summarize the knowledge on the molecular mechanism and biological function of miRNA cooperativity and discuss its application in cancer therapies. We then propose and discuss a systems biology approach to investigate miRNA cooperativity for the clinical setting. Altogether, we point out the potential of miRNA cooperativity to reduce off-target effects and to complement conventional, targeted, or immune-based therapies for cancer.
CRIS-Team Scopus Importer:2019-09-17

Targeting of DEC-205 on human dendritic cells results in efficient MHC class II-restricted antigen presentation - Birkholz, Katrin; Schwenkert, Michael; Kellner, Christian; Gross, Stefanie; Fey, Georg; Schuler-Thurner, Beatrice; Schuler, Gerold; Schaft, Niels; Dörrie, Jan (Blood, 2010)
The use of dendritic cells (DCs) in therapeutic cancer vaccination requires their loading with tumor-specific antigen(s). DEC-205, a phagocytosis receptor mediating antigen uptake, is associated with CD8+ T-cell responses in mice. Here we fused an anti-DEC-205scFv to an HLA-DP4-restricted epitope from the tumor antigen MAGE-A3, and examined the suitability and efficacy of DEC-205 to deliver a helper epitope to human monocytederived DCs (moDCs). The construct specifically bound DEC-205 on human moDCs without negative impact on DC phenotype and function. We measured antigen presentation with specific autologous CD4+ T cells, generated by TCR-RNA transfection. DEC-205 targeting resulted in significant major histocompatibility complex class II-restricted antigen presentation, and was superior to loading DCs by electroporation of mRNA encoding endosome-targeted MAGE-A3-DCLAMP or by direct peptide pulsing. Anti-DEC-205scFv-MAGE-A3 was presented 100 times more efficiently than the control constructs. DC maturation before or during incubation with anti-DEC-205scFv-MAGE-A3 reduced the interleukin-10/interleukin- 2 ratio. Moreover, we successfully applied the DEC-205 targeting strategy to moDCs from malignant melanoma patients. Again, DEC-205-targeted mature DCs (mDCs) presented the antigen more efficiently than peptide-pulsed DCs and maintained their stimulatory capacity after cryoconservation. Thus, DEC-205 targeting represents a feasible and effective method to deliver helper epitopes to DCs in anticancer vaccine strategies, which may also be suitable for DC targeting in vivo. © 2010 by The American Society of Hematology.
CRIS-Team Scopus Importer:2021-10-01

Tebentafusp als neuartige Immuntherapie zeigt einen Überlebensvorteil beim metastasierten Uveamelanom und wird bereits in Deutschland eingesetzt. - Hassel, Jessica C.; Berking, Carola (Journal der Deutschen Dermatologischen Gesellschaft, 2022)
EVALuna2:502114

Tebentafusp in Patients with Metastatic Uveal Melanoma: A Real-Life Retrospective Multicenter Study. - Tomsitz, Dirk; Ruf, Theresa; Heppt, Markus; Staeger, Ramon; Ramelyte, Egle; Dummer, Reinhard; Garzarolli, Marlene; Meier, Friedegund; Meier, Eileen; Richly, Heike; Gromke, Tanja; Siveke, Jens T.; et al. (Cancers, 2023)
BACKGROUND: Tebentafusp has recently been approved for the treatment of metastatic uveal melanoma (mUM) after proving to have survival benefits in a first-line setting. PATIENTS AND METHODS: This retrospective, multicenter study analyzed the outcomes and safety of tebentafusp therapy in 78 patients with mUM. RESULTS: Patients treated with tebentafusp had a median PFS of 3 months (95% CI 2.7 to 3.3) and a median OS of 22 months (95% CI 10.6 to 33.4). In contrast to a published Phase 3 study, our cohort had a higher rate of patients with elevated LDH (65.4% vs. 35.7%) and included patients with prior systemic and local ablative therapies. In patients treated with tebentafusp following ICI, there was a trend for a longer median OS (28 months, 95% CI 26.9 to 29.1) compared to the inverse treatment sequence (24 months, 95% CI 13.0 to 35.0, p = 0.257). The most common treatment-related adverse events were cytokine release syndrome in 71.2% and skin toxicity in 53.8% of patients. Tumor lysis syndrome occurred in one patient. CONCLUSIONS: Data from this real-life cohort showed a median PFS/OS similar to published Phase 3 trial data. Treatment with ICI followed by tebentafusp may result in longer PFS/OS compared to the inverse treatment sequence.
EVALuna2:538270

TEMPORAL MIGRATION OF IMMUNE CELLS FROM PSORIATIC SKIN TO JOINTS INITIATING SYNOVIAL INFLAMMATION IN PSORIATIC ARTHRITIS - Raimondo, Maria Gabriella; Rauber, Simon; Xu, Cong; Mohammadian, Hashem; Vogg, Mario; Anchang, Charles Gwellem; Rigau, Aleix; Luber, M.; Labinsky, Hannah; Soare, A.; Distler, Jörg; Fearon, U.; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

Th17 Cell-Mediated Colitis Is Positively Regulated by Interferon Regulatory Factor 4 in a T Cell-Extrinsic Manner - Buchele, Vera; Konein, Patrick; Vogler, Tina; Kunert, Timo; Enderle, Karin; Khan, Hanif; Büttner-Herold, Maike; Lehmann, Christian; Amon, Lukas; Wirtz, Stefan; Dudziak, Diana; Neurath, Markus; et al. (Frontiers in Immunology, 2021)
Inflammatory bowel diseases (IBDs) are characterized by chronic, inflammatory gastrointestinal lesions and often require life-long treatment with immunosuppressants and repetitive surgical interventions. Despite progress in respect to the characterization of molecular mechanisms e.g. exerted by TNF-alpha, currently clinically approved therapeutics fail to provide long-term disease control for most patients. The transcription factor interferon regulatory factor 4 (IRF4) has been shown to play important developmental as well as functional roles within multiple immune cells. In the context of colitis, a T cell-intrinsic role of IRF4 in driving immune-mediated gut pathology is established. Here, we conversely addressed the impact of IRF4 inactivation in non-T cells on T cell driven colitis in vivo. Employing the CD4+CD25− naïve T cell transfer model, we found that T cells fail to elicit colitis in IRF4-deficient compared to IRF4-proficient Rag1−/− mice. Reduced colitis activity in the absence of IRF4 was accompanied by hampered T cell expansion both within the mesenteric lymph node (MLN) and colonic lamina propria (cLP). Furthermore, the influx of various myeloids, presumably inflammation-promoting cells was abrogated overall leading to a less disrupted intestinal barrier. Mechanistically, gene profiling experiments revealed a Th17 response dominated molecular expression signature in colon tissues of IRF4-proficient, colitic Rag1−/− but not in colitis-protected Rag1−/−Irf4−/− mice. Colitis mitigation in Rag1−/−Irf4−/− T cell recipients resulted in reduced frequencies and absolute numbers of IL-17a-producing T cell subsets in MLN and cLP possibly due to a regulation of conventional dendritic cell subset 2 (cDC2) known to impact Th17 differentiation. Together, extending the T cell-intrinsic role for IRF4 in the context of Th17 cell driven colitis, the provided data demonstrate a Th17-inducing and thereby colitis-promoting role of IRF4 through a T cell-extrinsic mechanism highlighting IRF4 as a putative molecular master switch among transcriptional regulators driving immune-mediated intestinal inflammation through both T cell-intrinsic and T cell-extrinsic mechanisms. Future studies need to further dissect IRF4 controlled pathways within distinct IRF4-expressing myeloid cell types, especially cDC2s, to elucidate the precise mechanisms accounting for hampered Th17 formation and, according to our data, the predominant mechanism of colitis protection in Rag1−/−Irf4−/− T cell receiving mice.
CRIS-Team Scopus Importer:2021-02-26
Keywords: inflammatory bowel disease (IBD); interferon regulatory factor 4 (IRF4); intestinal inflammation; myeloid cells; Th17

The acidic protein rich in leucines Anp32b is an immunomodulator of inflammation in mice - Chemnitz, Jan; Pieper, Dorothea; Stich, Lena; Schumacher, Udo; Balabanov, Stefan; Spohn, Michael; Grundhoff, Adam; Steinkasserer, Alexander; Hauber, Joachim; Zinser, Elisabeth (Scientific Reports, 2019)
ANP32B belongs to a family of evolutionary conserved acidic nuclear phosphoproteins (ANP32A-H). Family members have been described as multifunctional regulatory proteins and proto-oncogenic factors affecting embryonic development, cell proliferation, apoptosis, and gene expression at various levels. Involvement of ANP32B in multiple processes of cellular life is reflected by the previous finding that systemic gene knockout (KO) of Anp32b leads to embryonic lethality in mice. Here, we demonstrate that a conditional KO of Anp32b is well tolerated in adult animals. However, after immune activation splenocytes isolated from Anp32b KO mice showed a strong commitment towards Th17 immune responses. Therefore, we further analyzed the respective animals in vivo using an experimental autoimmune encephalomyelitis (EAE) model. Interestingly, an exacerbated clinical score was observed in the Anp32b KO mice. This was accompanied by the finding that animal-derived T lymphocytes were in a more activated state, and RNA sequencing analyses revealed hyperactivation of several T lymphocyte-associated immune modulatory pathways, attended by significant upregulation of Tfh cell numbers that altogether might explain the observed strong autoreactive processes. Therefore, Anp32b appears to fulfill a role in regulating adequate adaptive immune responses and, hence, may be involved in dysregulation of pathways leading to autoimmune disorders and/or immune deficiencies.
CRIS-Team WoS Importer:2019-04-02

The AP-1 Transcription Factor c-Jun Promotes Arthritis by Regulating Cyclooxygenase-2 and Arginase-1 Expression in Macrophages - Hannemann, Nicole; Jordan, Jutta; Paul, Sushmita; Reid, Stephen; Baenkler, Hanns-Wolf; Sonnewald, Sophia; Bäuerle, Tobias; Vera, Julio; Schett, Georg; Bozec, Aline (Journal of Immunology, 2017)
Activation of proinflammatory macrophages is associated with the inflammatory state of rheumatoid arthritis. Their polarization and activation are controlled by transcription factors such as NF-?B and the AP-1 transcription factor member c-Fos. Surprisingly, little is known about the role of the AP-1 transcription factor c-Jun in macrophage activation. In this study, we show that mRNA and protein levels of c-Jun are increased in macrophages following pro- or anti-inflammatory stimulations. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway enrichment cluster analyses of microarray data using wild-type and c-Jun-deleted macrophages highlight the central function of c-Jun in macrophages, in particular for immune responses, IL production, and hypoxia pathways. Mice deficient for c-Jun in macrophages show an amelioration of inflammation and bone destruction in the serum-induced arthritis model. In vivo and in vitro gene profiling, together with chromatin immunoprecipitation analysis of macrophages, revealed direct activation of the proinflammatory factor cyclooxygenase-2 and indirect inhibition of the anti-inflammatory factor arginase-1 by c-Jun. Thus, c-Jun regulates the activation state of macrophages and promotes arthritis via differentially regulating cyclooxygenase-2 and arginase-1 levels.
EVALuna2:13412

The Art of Making Moulages - a hidden Art? - Sticherling, Michael; Groenhardt, K.; Saake, Marc (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-05-17

The CD83 Molecule – An Important Immune Checkpoint - Grosche, Linda; Knippertz, Ilka; König, Christina; Royzman, Dmytro; Wild, Andreas; Zinser, Elisabeth; Sticht, Heinrich; Muller, Yves; Steinkasserer, Alexander; Lechmann, Matthias (Frontiers in Immunology, 2020)
The CD83 molecule has been identified to be expressed on numerous activated immune cells, including B and T lymphocytes, monocytes, dendritic cells, microglia, and neutrophils. Both isoforms of CD83, the membrane-bound as well as its soluble form are topic of intensive research investigations. Several studies revealed that CD83 is not a typical co-stimulatory molecule, but rather plays a critical role in controlling and resolving immune responses. Moreover, CD83 is an essential factor during the differentiation of T and B lymphocytes, and the development and maintenance of tolerance. The identification of its interaction partners as well as signaling pathways have been an enigma for the last decades. Here, we report the latest data on the expression, structure, and the signaling partners of CD83. In addition, we review the regulatory functions of CD83, including its striking modulatory potential to maintain the balance between tolerance versus inflammation during homeostasis or pathologies. These immunomodulatory properties of CD83 emphasize its exceptional therapeutic potential, which has been documented in specific preclinical disease models.
CRIS-Team Scopus Importer:2020-05-08
Keywords: autoimmunity; CD83; immune tolerance; Treg cells; viral escape mechanism

The CD83 molecule expressed by dendritic cells is a checkpoint to regulate resolution of inflammation as well as homeostasis within periphery and CNS - Wild, Andreas; Krzyzak, Lena; Mattner, Jochen; Winkler, Thomas; Nitschke, Lars; Steinkasserer, Alexander (2018)
EVALuna2:36214

The COVID-19 pandemic: implications for patients undergoing immunomodulating or immunosuppressive treatments in dermatology - Reinholz, Markus; French, Lars E.; Berking, Carola; Heppt, Markus (European Journal of Dermatology, 2020)
CRIS-Team WoS Importer:2021-02-26

The Current State of Systemic Therapy of Metastatic Uveal Melanoma - Koch, Elias; Heppt, Markus; Berking, Carola (American Journal of Clinical Dermatology, 2024)
Uveal melanoma (UM) is genetically a distinct tumor compared to cutaneous melanoma (CM), and due to its low mutational burden, it is far less perceptible to the immune system. Thus, treatments that have revolutionized the treatment of CM remain widely inefficient in metastatic UM or only demonstrate effectiveness in a small subpopulation of patients. To this end, the therapeutic benefit of immune checkpoint blockade is very limited and may come at the expense of severe immune-related adverse events that could potentially affect all organ systems. Notably, tebentafusp, an entirely novel class of anti-cancer drugs, has received official authorization for the treatment of metastatic UM. It is the first agent that demonstrated a survival advantage in a randomized controlled trial of metastatic UM patients. Despite the survival benefit and approval, the restriction of tebentafusp to HLA-A*02:01-positive patients and the low objective response rate indicate the persistent need for additional therapies. Thus, liver-directed therapies are commonly used for tumor control of hepatic metastases and represent a central pillar of the daily management of liver-dominant disease. Further, promising data from targeted therapies independent of MEK-inhibitors, such as the combination of darovasertib and crizotinib, raise hope for additional options in metastatic UM in the future. This narrative review provides a timely and comprehensive overview of the current treatment landscape for metastatic UM.
CRIS-Team Scopus Importer:2024-06-28

The delivery of antigens to dendritic cells is a potent futureoption for anti-tumor therapies - Lehmann, Christian; Heger, Lukas; Neubert, K.; Harzer, Christina; Amon, Lukas; Yamazaki, S.; Heidkamp, Gordon Frederik; Eissing, N.; Krug, A.; Leusen, J.; Ravetch, J.; Nimmerjahn, Falk; et al. (2017)
EVALuna2:34372

The distribution of C-type lectin receptors in the Dendritic cell membrane - Lühr, Jennifer; Eissing, N.; Heidkamp, Gordon Frederik; Lehmann, C. H. K.; Heger, Lukas; Dudziak, Diana (2017)
EVALuna2:34370

The Effect of Hyperthermia and Radiotherapy Sequence on Cancer Cell Death and the Immune Phenotype of Breast Cancer Cells - Sengedorj, Azzaya; Hader, Michael; Heger, Lukas; Frey, Benjamin; Dudziak, Diana; Fietkau, Rainer; Ott, Oliver; Scheidegger, Stephan; Barba, Sergio Mingo; Gaipl, Udo; Rückert, Michael (Cancers, 2022)
Hyperthermia (HT) is an accepted treatment for recurrent breast cancer which locally heats the tumor to 39–44◦C, and it is a very potent sensitizer for radiotherapy (RT) and chemotherapy. However, currently little is known about how HT with a distinct temperature, and particularly, how the sequence of HT and RT changes the immune phenotype of breast cancer cells. Therefore, human MDA-MB-231 and MCF-7 breast cancer cells were treated with HT of different temperatures (39, 41 and 44◦C), alone and in combination with RT (2 × 5 Gy) in different sequences, with either RT or HT first, followed by the other. Tumor cell death forms and the expression of immune checkpoint molecules (ICMs) were analyzed by multicolor flow cytometry. Human monocyte-derived dendritic cells (moDCs) were differentiated and co-cultured with the treated cancer cells. In both cell lines, RT was the main stressor for cell death induction, with apoptosis being the prominent cell death form in MCF-7 cells and both apoptosis and necrosis in MDA-MB-231 cells. Here, the sequence of the combined treatments, either RT or HT, did not have a significant impact on the final outcome. The expression of all of the three examined immune suppressive ICMs, namely PD-L1, PD-L2 and HVEM, was significantly increased on MCF-7 cells 120 h after the treatment of RT with HT of any temperature. Of special interest for MDA-MB-231 cells is that only combinations of RT with HT of both 41 and 44◦C induced a significantly increased expression of PD-L2 at all examined time points (24, 48, 72, and 120 h). Generally, high dynamics of ICM expression can be observed after combined RT and HT treatments. There was no significant difference between the different sequences of treatments (either HT + RT or RT + HT) in case of the upregulation of ICMs. Furthermore, the co-culture of moDCs with tumor cells of any treatment had no impact on the expression of activation markers. We conclude that the sequence of HT and RT does not strongly affect the immune phenotype of breast cancer cells. However, when HT is combined with RT, it results in an increased expression of distinct immune suppressive ICMs that should be considered by including immune checkpoint inhibitors in multimodal tumor treatments with RT and HT. Further, combined RT and HT affects the immune system in the effector phase rather than in the priming phase.
CRIS-Team Scopus Importer:2022-04-29
Keywords: breast cancer; dendritic cell activation; hyperthermia; hyperthermia treatment sequence; immune checkpoint molecules; immune phenotype; radiotherapy

The effects of dexmedetomidine and tramadol on post-operative pain and agitation, and extubation quality in paediatric patients undergoing adenotonsillectomy surgery: A randomized trial - Koceroglu, Ikbal; Devrim, Sibel; Bingol Tanriverdi, Tugba; Gura Celik, Melek (Journal of Clinical Pharmacy and Therapeutics, 2019)
What is known and objective Adenotonsillectomies are common surgical procedures performed under general anaesthesia in childhood. Post-operative pain and agitation are complications associated with this procedure. We compared the effects of dexmedetomidine and tramadol on post-operative pain, agitation, haemodynamic parameters, and extubation quality in patients undergoing an adenotonsillectomy using sevoflurane as an anaesthetic agent. Methods Sixty paediatric patients who had undergone an adenotonsillectomy were included in this study. The patients were randomized into two groups that received either dexmedetomidine (n = 30) or tramadol (n = 30). Haemodynamic variables, extubation time, post-operative pain, agitation and adverse events were recorded for all patients. Post-operative pain was assessed with the pain point system scale (PPSS), and agitation was assessed using the Riker Sedation-Agitation Scale (SAS). Results Patients in the dexmedetomidine group had significantly lower heart rates than the tramadol group. In addition, patients in the dexmedetomidine group had significantly lower post-operative PPSS and Riker SAS scores than patients in the tramadol group. Not breathing, cough-bucking and desaturation after extubation occurred less frequently in patients who received dexmedetomidine than in patients who received tramadol. However, the time to extubation was significantly longer for patients who received dexmedetomidine. What is new and conclusion Our study demonstrated that dexmedetomidine was more effective than tramadol for mitigating post-operative pain and agitation in paediatric patients following an adenotonsillectomy with sevoflurane. Although dexmedetomidine was associated with a longer time to extubation, it was also associated with fewer complications following extubation compared with tramadol.
CRIS-Team WoS Importer:2019-12-13

The future of affordable cancer immunotherapy - Schaft, Niels; Dörrie, Jan; Schuler, Gerold; Schuler-Thurner, Beatrice; Sallam, Husam; Klein, Shiri; Eisenberg, Galit; Frankenburg, Shoshana; Lotem, Michal; Khatib, Areej (Frontiers in Immunology, 2023)
The treatment of cancer was revolutionized within the last two decades by utilizing the mechanism of the immune system against malignant tissue in so-called cancer immunotherapy. Two main developments boosted cancer immunotherapy: 1) the use of checkpoint inhibitors, which are characterized by a relatively high response rate mainly in solid tumors; however, at the cost of serious side effects, and 2) the use of chimeric antigen receptor (CAR)-T cells, which were shown to be very efficient in the treatment of hematologic malignancies, but failed to show high clinical effectiveness in solid tumors until now. In addition, active immunization against individual tumors is emerging, and the first products have reached clinical approval. These new treatment options are very cost-intensive and are not financially compensated by health insurance in many countries. Hence, strategies must be developed to make cancer immunotherapy affordable and to improve the cost-benefit ratio. In this review, we discuss the following strategies: 1) to leverage the antigenicity of “cold tumors” with affordable reagents, 2) to use microbiome-based products as markers or therapeutics, 3) to apply measures that make adoptive cell therapy (ACT) cheaper, e.g., the use of off-the-shelf products, 4) to use immunotherapies that offer cheaper platforms, such as RNA- or peptide-based vaccines and vaccines that use shared or common antigens instead of highly personal antigens, 5) to use a small set of predictive biomarkers instead of the “sequence everything” approach, and 6) to explore affordable immunohistochemistry markers that may direct individual therapies.
CRIS-Team Scopus Importer:2023-09-29
Keywords: adoptive cell therapy; affordable; biomarkers; immunohistochemistry; immunotherapy; microbiome; RNA-based vaccines

The Generation of CAR-Transfected Natural Killer T Cells for the Immunotherapy of Melanoma - Simon, Bianca; Wiesinger, Manuel; Maerz, Johannes; Wistuba-Hamprecht, Kilian; Weide, Benjamin; Schuler-Thurner, Beatrice; Schuler, Gerold; Dörrie, Jan; Uslu, Ugur (International Journal of Molecular Sciences, 2018)
Natural killer T (NKT) cells represent a cell subpopulation that combines characteristics of natural killer (NK) cells and T cells. Through their endogenous T-cell receptors (TCRs), they reveal a pronounced intrinsic anti-tumor activity. Thus, a NKT cell transfected with a chimeric antigen receptor (CAR), which recognizes a tumor-specific surface antigen, could attack tumor cells antigen-specifically via the CAR and additionally through its endogenous TCR. NKT cells were isolated from peripheral blood mononuclear cells (PBMCs), expanded, and electroporated with mRNA encoding a chondroitin sulfate proteoglycan 4 (CSPG4)-specific CAR. The CAR expression on NKT cells and their in vitro functionality were analyzed. A transfection efficiency of more than 80% was achieved. Upon stimulation with melanoma cells, CAR-NKT cells produced cytokines antigen-specifically. Compared with conventional CAR-T cells, cytokine secretion of CAR-NKT cells was generally lower. Specific cytotoxicity, however, was similar with CAR-NKT cells showing a trend towards improved cytotoxicity. Additionally, CAR-NKT cells could kill target cells through their endogenous TCRs. In summary, it is feasible to generate CAR-NKT cells by using mRNA electroporation. Their CAR-mediated cytotoxicity is at least equal to that of conventional CAR-T cells, while their intrinsic cytotoxic activity is maintained. Thus, CAR-NKT cells may represent a valuable alternative to conventional CAR-T cells for cancer immunotherapy.
EVALuna2:34785

The Generation of CAR-transfected NKT Cells for the Immunotherapy of Melanoma - Simon, B.; Wiesinger, M.; Marz, J.; Wistuba-Hamprecht, K.; Weide, B.; Schuler-Thurner, Beatrice; Schuler, Gerold; Dörrie, Jan; Uslu, Ugur (2018)
EVALuna2:34767

The genetic basis for most patients with pustular skin disease remains elusive - Mössner, R.; Wilsmann-Theis, D.; Oji, V.; Gkogkolou, P.; Löhr, S.; Schulz, P.; Körber, A.; Prinz, J. C.; Renner, R.; Schäkel, K.; Vogelsang, L.; Peters, K. P.; et al. (British Journal of Dermatology, 2017)
Rare variants in the genes IL36RN, CARD14 and AP1S3 have been identified to cause/ contribute to pustular skin diseases, primarily generalized pustular psoriasis (GPP).To better understand the disease-relevance of these genes, we screened our cohorts of patients with pustular skin diseases (primarily GPP and palmoplantar pustular psoriasis [PPP]) for coding changes in these three genes. Carriers of single heterozygous IL36RN mutations were screened for a second mutation in IL36RN.Coding exons of IL36RN, CARD14 and AP1S3 were sequenced in 67 patients - 61 with GPP, 2 with acute generalized exanthematous pustulosis and 4 with acrodermatitis continua suppurativa Hallopeau. We screened IL36RN and AP1S3 for intragenic copy-number-variants, 258 PPP patients for coding changes in AP1S3. 11 heterozygous IL36RN mutations carriers were analyzed for a 2(nd) non-coding IL36RN mutation. Genotype-phenotype-correlations in carriers/ non-carriers of IL36RN mutations were assessed within the GPP cohort.The majority of patients (GPP:64%) did not carry rare variants in any of the three genes. Bi-allelic and mono-allelic IL36RN mutations were identified in 15 and 5 GPP patients, respectively. Non-coding rare IL36RN variants were not identified in heterozygous carriers. The only significant genotype-phenotype-correlation observed for IL36RN mutation carriers was early age of disease onset. Additional rare CARD14 or AP1S3 variants were identified in 15% of IL36RN mutations carriers.The identification of IL36RN mutation carriers harboring additional rare variants in CARD14 or AP1S3, indicates a more complex mode of inheritance of pustular psoriasis. Our results suggest additional disease-causing genetic factors in heterozygous IL36RN mutation carriers outside IL36RN. This article is protected by copyright. All rights reserved.
EVALuna2:9330

THE GERMAN AD REGISTRY TREATGERMANY: RESULTS FROM AN INTERIM DATA ANALYSIS ON BASELINE CHARACTERISTICS, COMORBIDITIES AND TREATMENT HISTORY - Heratizadeh, Annice; Haufe, Eva; Stoelzl, Dora; Abraham, Susanne; Heinrich, Luise; Kleinheinz, Andreas; Wollenberg, Andreas; Weisshaar, Elke; Augustin, Matthias; Wiemers, Franca; Zink, Alexander; Von Kiedrowski, Ralph; et al. (ACTA DERMATO-VENEREOLOGICA, 2021)
CRIS-Team WoS Importer:2021-05-07

The IKZF1–IRF4/IRF5 axis controls polarization of myeloma-associated macrophages - Mougiakakos, Dimitrios; Bach, Christian; Böttcher, Martin; Beier, Fabian; Röhner, Linda; Stoll, Andrej; Rehli, Michael; Gebhard, Claudia; Lischer, Christopher; Eberhardt, Martin; Vera, Julio; Büttner-Herold, Maike; et al. (Cancer Immunology Research, 2021)
The bone marrow niche has a pivotal role in progression, survival, and drug resistance of multiple myeloma cells. Therefore, it is important to develop means for targeting the multiple myeloma bone marrow microenvironment. Myeloma-associated macrophages (MAM) in the bone marrow niche are M2 like. They provide nurturing signals to multiple myeloma cells and promote immune escape. Reprogramming M2-like macrophages toward a tumoricidal M1 phenotype represents an intriguing therapeutic strategy. This is especially interesting in view of the successful use of mAbs against multiple myeloma cells, as these therapies hold the potential to trigger macrophage-mediated phagocytosis and cytotoxicity. In this study, we observed that MAMs derived from patients treated with the immunomodulatory drug (IMiD) lenalidomide skewed phenotypically and functionally toward an M1 phenotype. Lenalidomide is known to exert its beneficial effects by modulating the CRBN-CRL4 E3 ligase to ubiquitinate and degrade the transcription factor IKAROS family zinc finger 1 (IKZF1). In M2-like MAMs, we observed enhanced IKZF1 levels that vanished through treatment with lenalidomide, yielding MAMs with a bioenergetic profile, T-cell stimulatory properties, and loss of tumor-promoting capabilities that resemble M1 cells. We also provide evidence that IMiDs interfere epigenetically, via degradation of IKZF1, with IFN regulatory factors 4 and 5, which in turn alters the balance of M1/M2 polarization. We validated our observations in vivo using the CrbnI391V mouse model that recapitulates the IMiD-triggered IKZF1 degradation. These data show a role for IKZF1 in macrophage polarization and can provide explanations for the clinical benefits observed when combining IMiDs with therapeutic antibodies. See related Spotlight on p. 254
CRIS-Team Scopus Importer:2021-03-19

The Influence of MHC Class II on B Cell Defects Induced by Invariant Chain/CD74 N-Terminal Fragments - Schneppenheim, Janna; Loock, Ann-Christine; Huettl, Susann; Schweizer, Michaela; Luellmann-Rauch, Renate; Oberg, Hans-Heinrich; Arnold, Philipp; Lehmann, Christian; Dudziak, Diana; Kabelitz, Dieter; Lucius, Ralph; Lennon-Dumenil, Ana-Maria; et al. (Journal of Immunology, 2017)
The invariant chain (CD74) mediates assembly and targeting of MHC class II (MHCII) complexes. In endosomes, CD74 undergoes sequential degradation by different proteases, including cathepsin S (CatS) and the intramembrane protease signal peptide peptidase-like 2a (SPPL2a). In their absence, CD74 N-terminal fragments (NTFs) accumulate. In SPPL2a-/- B cells, such an NTF impairs endosomal trafficking and BCR signal transduction. In mice, this leads to a loss of splenic B cells beyond the transitional stage 1. To gain insight into CD74 determinants and the role of MHCII, we compared B cells from CatS-/- , SPPL2a-/- , and SPPL2a-MHCII double-deficient mice. We assessed differentiation of B cells in bone marrow and spleen and analyzed their endosomal morphology, BCR expression, and signal transduction. We demonstrate that MHCII is dispensable for the B cell phenotype of SPPL2a-/- mice, further supporting a CD74-intrinsic effect. Despite significant vacuolization of endosomal compartments similar to SPPL2a-/- B cells, CatS-/- traditional stage 1 B cells show unimpaired degradation of endocytic cargo, have intact BCR signaling, and do not exhibit any relevant defects in maturation. This could indicate that CD74 NTF-induced structural changes of endosomes are not directly involved in these processes. We further found that the block of CD74 degradation in CatS-/- B cells is incomplete, so that NTF levels are significantly lower than in SPPL2a-/- B cells. This suggests a dose dependency and threshold for the CD74 NTF-associated impairment of B cell signaling and maturation. In addition, different functional properties of the longer, MHCII-bound CD74 NTF could contribute to the milder phenotype of CatS-/- B cells.
EVALuna2:34373

The involvement of Toll-like receptor 9 in the pathogenesis of erosive autoimmune arthritis - Fischer, Anita; Abdollahi-Roodsaz, Shahla; Boehm, Christina; Niederreiter, Birgit; Meyer, Brigitte; Yau, Anthony C. Y.; Lonnblom, Erik; Joosten, Leo A. B.; Koenders, Marije; Lehmann, Christian; Dudziak, Diana; Krönke, Gerhard; et al. (Journal of Cellular and Molecular Medicine, 2018)
Endogenous nucleic acids and their receptors may be involved in the initiation of systemic autoimmune diseases including rheumatoid arthritis (RA). As the role of the DNA sensing Toll-like receptor (TLR) 9 in RA is unclear, we aimed to investigate its involvement in the pathogenesis of autoimmune arthritis using three different experimental models of RA. The data obtained revealed involvement of TLR9 in the T cell-dependent phase of inflammatory arthritis. In rats with pristane-induced arthritis (PIA), TLR9 inhibition before disease onset reduced arthritis significantly and almost completely abolished bone erosion. Accordingly, serum levels of IL-6, α-1-acid-glycoprotein and rheumatoid factor were reduced. Moreover, in TLR9-/- mice, streptococcal cell wall (SCW)-induced arthritis was reduced in the T cell-dependent phase, whereas T cell-independent serum-transfer arthritis was not affected. Remarkably, while TLR7 expression did not change during in vitro osteoclastogenesis, TLR9 expression was higher in precursor cells than in mature osteoclasts and partial inhibition of osteoclastogenesis was achieved only by the TLR9 antagonist. These results demonstrate a pivotal role for TLR9 in the T cell-dependent phases of inflammatory arthritis and additionally suggest some role during osteoclastogenesis. Hence, endogenous DNA seems to be crucially involved in the pathophysiology of inflammatory autoimmune arthritis.
EVALuna2:34780

The Major Immediate-Early Protein IE2 of Human Cytomegalovirus Is Sufficient to Induce Proteasomal Degradation of CD83 on Mature Dendritic Cells - Heilingloh, Christiane; Grosche, Linda; Kummer, Mirko; Mühl-Zürbes, Petra; Kamm, Lisa; Scherer, Myriam; Latzko, Melanie; Stamminger, Thomas; Steinkasserer, Alexander (Frontiers in Microbiology, 2017)
Human cytomegalovirus (HCMV) is the prototypic beta-herpesvirus and widespread throughout the human population. While infection is asymptomatic in healthy individuals, it can lead to high morbidity and mortality in immunocompromised persons. Importantly, HCMV evolved multiple strategies to interfere with immune cell function in order to establish latency in infected individuals. As mature DCs (mDCs) are antigen-presenting cells able to activate naïve T cells they play a crucial role during induction of effective antiviral immune responses. Interestingly, earlier studies demonstrated that the functionally important mDC surface molecule CD83 is down-regulated upon HCMV infection resulting in a reduced T cell stimulatory capacity of the infected cells. However, the viral effector protein and the precise mechanism of HCMV-mediated CD83 reduction remain to be discovered. Using flow cytometric analyses, we observed significant down-modulation of CD83 surface expression becoming significant already 12 h after HCMV infection. Moreover, Western bot analyses revealed that, in sharp contrast to previous studies, loss of CD83 is not restricted to the membrane-bound molecule, but also occurs intracellularly. Furthermore, inhibition of the proteasome almost completely restored CD83 surface expression during HCMV infection. Results of infection kinetics and cycloheximide-actinomycin D-chase experiments, strongly suggested that an HCMV immediate early gene product is responsible for the induction of CD83 down-modulation. Consequently, we were able to identify the major immediate early protein IE2 as the viral effector protein that induces proteasomal CD83 degradation.
EVALuna2:26039

The need for regular training in skin cancer screening: a cross-sectional study among general practitioners in Germany - Steeb, Theresa; Reinhardt, Lydia; Strasser, C.; Wessely, Anja; Schelling, J.; Petzold, Anne; Heppt, Markus; Meier, Friedegund; Berking, Carola (Journal of the European Academy of Dermatology and Venereology, 2022)
CRIS-Team Scopus Importer:2022-07-15

The Neural Crest Transcription Factor SOX10 is essential for the Survival of Uveal Melanoma Cells - Wessely, A.; Kammerbauer, C.; Berking, Carola; Heppt, Markus (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2020)
CRIS-Team WoS Importer:2020-09-11

The novel role of lymphatic vessels in the pathogenesis of ocular diseases - Clahsen, Thomas; Hadrian, Karina; Notara, Maria; Schlereth, Simona L.; Howaldt, Antonia; Prokosch, Verena; Volatier, Thomas; Hos, Deniz; Schroedl, Falk; Kaser-Eichberger, Alexandra; Heindl, Ludwig M.; Steven, Philipp; et al. (Progress in Retinal and Eye Research, 2023)
Historically, the eye has been considered as an organ free of lymphatic vessels. In recent years, however, it became evident, that lymphatic vessels or lymphatic-like vessels contribute to several ocular pathologies at various peri- and intraocular locations. The aim of this review is to outline the pathogenetic role of ocular lymphatics, the respective molecular mechanisms and to discuss current and future therapeutic options based thereon. We will give an overview on the vascular anatomy of the healthy ocular surface and the molecular mechanisms contributing to corneal (lymph)angiogenic privilege. In addition, we present (i) current insights into the cellular and molecular mechanisms occurring during pathological neovascularization of the cornea triggered e.g. by inflammation or trauma, (ii) the role of lymphatic vessels in different ocular surface pathologies such as dry eye disease, corneal graft rejection, ocular graft versus host disease, allergy, and pterygium, (iii) the involvement of lymphatic vessels in ocular tumors and metastasis, and (iv) the novel role of the lymphatic-like structure of Schlemm's canal in glaucoma. Identification of the underlying molecular mechanisms and of novel modulators of lymphangiogenesis will contribute to the development of new therapeutic targets for the treatment of ocular diseases associated with pathological lymphangiogenesis in the future. The preclinical data presented here outline novel therapeutic concepts for promoting transplant survival, inhibiting metastasis of ocular tumors, reducing inflammation of the ocular surface, and treating glaucoma. Initial data from clinical trials suggest first success of novel treatment strategies to promote transplant survival based on pretransplant corneal lymphangioregression.
CRIS-Team Scopus Importer:2023-06-30
Keywords: Corneal (lymph)angiogenic privilege; Corneal immune reaction; Glaucoma; Limbal stem cells; Lymphangiogenesis; Transplantation

The ontogenetic path of human dendritic cells - Amon, Lukas; Lehmann, Christian; Heger, Lukas; Heidkamp, Gordon Frederik; Dudziak, Diana (Molecular Immunology, 2020)
Dendritic cells (DCs) orchestrate adaptive immune responses. In healthy individuals, DCs are drivers and fine-tuners of T cell responses directed against invading pathogens or cancer cells. In parallel, DCs control autoreactive T cells, thereby maintaining T cell tolerance. Under various disease conditions, a disruption of this delicate balance can lead to chronic infections, tumor evasion, or autoimmunity. While great efforts have been made to unravel the origin and development of this powerful cell type in mice, only little is known about the ontogeny of human DCs. Here, we summarize the current understanding of the developmental path of DCs from hematopoietic stem cells to fully functional DCs in their local tissue environment and provide a template for the identification of DCs across various tissues.
CRIS-Team Scopus Importer:2020-03-06
Keywords: Conventional; DC; Human; Ontogeny; Progeny; Transcription factor

The p.Arg435His Variation of IgG3 With High Affinity to FcRn Is Associated With Susceptibility for Pemphigus Vulgaris-Analysis of Four Different Ethnic Cohorts - Recke, Andreas; Konitzer, Sarah; Lemcke, Susanne; Freitag, Miriam; Sommer, Nele Maxi; Abdelhady, Mohammad; Amoli, Mahsa M.; Benoit, Sandrine; El-Chennawy, Farha; Eldarouti, Mohammad; Eming, Ruediger; Glaeser, Regine; et al. (Frontiers in Immunology, 2018)
IgG3 is the IgG subclass with the strongest effector functions among all four IgG subclasses and the highest degree of allelic variability among all constant immunoglobulin genes. Due to its genetic position, IgG3 is often the first isotype an antibody switches to before IgG1 or IgG4. Compared with the other IgG subclasses, it has a reduced half-life which is probably connected to a decreased affinity to the neonatal Fc receptor (FcRn). However, a few allelic variants harbor an amino acid replacement of His435 to Arg that reverts the half-life of the resulting IgG3 to the same level as the other IgG subclasses. Because of its functional impact, we hypothesized that the p.Arg435His variation could be associated with susceptibility to autoantibody-mediated diseases like pemphigus vulgaris (PV) and bullous pemphigoid (BP). Using a set of samples from German, Turkish, Egyptian, and Iranian patients and controls, we were able to demonstrate a genetic association of the p.Arg435His variation with PV risk, but not with BP risk. Our results suggest a hitherto unknown role for the function of IgG3 in the pathogenesis of PV.
EVALuna2:34784

The Quality of Guidelines for the Treatment of Cutaneous Melanoma: A methodological Assessment - Steeb, Theresa; Wessely, A.; Drexler, K.; Salzmann, M.; Toussaint, Frédéric; Heinzerling, Lucie; Reinholz, M.; Berking, Carola; Heppt, Markus (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2020)
CRIS-Team WoS Importer:2020-09-11

The quality of national skin cancer screening from the perspective of general practitioners: A questionnaire-based comparison between Saxony and Bavaria (SaBaScreen) - Strasser, C.; Reinhardt, L.; Steeb, Theresa; Wessely, Anja; Schelling, Jörg; Petzold, Anne; Heppt, Markus; Meier, F.; Berking, Carola (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2022)
CRIS-Team WoS Importer:2022-09-23

The quality of practice guidelines for melanoma: A methodologic appraisal with the agree ii and agree-rex instruments - Steeb, Theresa; Wessely, Anja; Drexler, Konstantin; Salzmann, Martin; Toussaint, Frédéric; Heinzerling, Lucie; Reinholz, Markus; Berking, Carola; Heppt, Markus (Cancers, 2020)
Multiple guidelines on cutaneous melanoma (CM) are available from several consortia and countries. To provide up-to-date guidance in the rapidly changing field of melanoma treatment, guideline developers have to provide regular updates without compromises of quality. We performed a systematic search in guideline databases, Medline and Embase to identify guidelines on CM. The methodological quality of the identified guidelines was independently assessed by five reviewers using the instruments “Appraisal of Guidelines for Research and Evaluation” (AGREE II) and “Recommendation EXcellence” (AGREE-REX). We performed descriptive analysis, explored subgroup differences using the Kruskal–Wallis (H) test and examined the relationship between distinct domains and items of the instruments with Spearman’s correlation. Six guidelines by consortia from Australia, France, Germany, Scotland, Spain and the United States of America were included. The German guideline fulfilled 71%–98% of criteria in AGREE II and 78%–96% for AGREE-REX, obtaining the highest scores. Deficiencies in the domains of “applicability” and “values and preferences” were observed in all guidelines. The German and Spanish guidelines significantly differed from each other in most of the domains. The domains “applicability” and “values and preferences” were identified as methodological weaknesses requiring careful revision and improvement in the future.
CRIS-Team Scopus Importer:2020-06-26
Keywords: AGREE; Cutaneous melanoma; Level of evidence; Melanoma treatment; Practice guideline

Therapeutic cancer vaccination with ex vivo rna-transfected dendritic cells—an update - Dörrie, Jan; Schaft, Niels; Schuler, Gerold; Schuler-Thurner, Beatrice (Pharmaceutics, 2020)
Over the last two decades, dendritic cell (DC) vaccination has been studied extensively as active immunotherapy in cancer treatment and has been proven safe in all clinical trials both with respect to short and long-term side effects. For antigen-loading of dendritic cells (DCs) one method is to introduce mRNA coding for the desired antigens. To target the whole antigenic repertoire of a tumor, even the total tumor mRNA of a macrodissected biopsy sample can be used. To date, reports have been published on a total of 781 patients suffering from different tumor entities and HIV-infection, who have been treated with DCs loaded with mRNA. The majority of those were melanoma patients, followed by HIV-infected patients, but leukemias, brain tumors, prostate cancer, renal cell carcinomas, pancreatic cancers and several others have also been treated. Next to antigen-loading, mRNA-electroporation allows a purposeful manipulation of the DCs’ phenotype and function to enhance their immunogenicity. In this review, we intend to give a comprehensive summary of what has been published regarding clinical testing of ex vivo generated mRNA-transfected DCs, with respect to safety and risk/benefit evaluations, choice of tumor antigens and RNA-source, and the design of better DCs for vaccination by transfection of mRNA-encoded functional proteins.
CRIS-Team Scopus Importer:2020-02-04
Keywords: Clinical trial; Dendritic cells; Electroporation; Immunotherapy; RNA; Therapeutic vaccination

Therapy Management of the first Recurrence after adjuvant Therapy in Stage III: multicenter real-world Data - Lodde, G.; Forschner, A.; Hassel, J. C.; Wulfken, L. M.; Meier, F.; Mohr, P.; Kaehler, K.; Schilling, B.; Loquai, C.; Berking, Carola; Huening, S.; Eckardt, J.; et al. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2022)
CRIS-Team WoS Importer:2022-09-23

The RNA world in the 21st century-a systems approach to finding non-coding keys to clinical questions - Schmitz, Ulf; Naderi-Meshkin, Hojjat; Gupta, Shailendra K.; Wolkenhauer, Olaf; Vera, Julio (Briefings in Bioinformatics, 2016)
There was evidence that RNAs are a functionally rich class of molecules not only since the arrival of the next-generation sequencing technology. Non-coding RNAs (ncRNA) could be the key to accelerated diagnosis and enhanced prediction of disease and therapy outcomes as well as the design of advanced therapeutic strategies to overcome yet unsatisfactory approaches.In this review, we discuss the state of the art in RNA systems biology with focus on the application in the systems biomedicine field. We propose guidelines for analysing the role of microRNAs and long non-coding RNAs in human pathologies. We introduce RNA expression profiling and network approaches for the identification of stable and effective RNomics-based biomarkers, providing insights into the role of ncRNAs in disease regulation. Towards this, we discuss ways to model the dynamics of gene regulatory networks and signalling pathways that involve ncRNAs. We also describe data resources and computational methods for finding putative mechanisms of action of ncRNAs. Finally, we discuss avenues for the computer-aided design of novel RNA-based therapeutics.
EVALuna2:19592

The Road to Effective Cancer Immunotherapy—A Computational Perspective on Tumor Epitopes in Anti-Cancer Immunotherapy - Lischer, Christopher; Vera González, Julio (Systems Medicine, 2021)
A current option for anti-cancer immunotherapy is to make use of epitopes which can guide cytotoxic T cells to destroy the tumor. It is however difficult to find immunogenic epitopes which engage the T cells sufficiently to fight cancer effectively. Additionally, cancer heterogeneity makes the development of such epitopes even more difficult since there is little general overlap between two cancers. Hence an epitope-based approach requires the use of many modern aspects of biological science like bioinformatics, next-generation sequencing and biostatistics. In this article, we provide a broad introduction to the topic from a computational perspective and offer insights into current paradigms of data-driven epitope selection, explain some fundamental workflows and outline avenues for future research in vitro and in silico.<br
Keywords: Antigen presentation; Bioinformatics; Cancer; Decision support systems; Epitopes; Immunoinformatics; Immunology; Immunotherapy; Introduction; Systems biology; Workflows

The role of age, neutrophil infiltration and antibiotics timing in the severity of streptococcus pneumoniae pneumonia. Insights from a multi-level mathematical model approach - Santos, Guido; Vera, Julio (International Journal of Molecular Sciences, 2020)
Bacterial pneumonia is one of the most prevalent infectious diseases and has high mortality in sensitive patients (children, elderly and immunocompromised). Although an infection, the disease alters the alveolar epithelium homeostasis and hinders normal breathing, often with fatal consequences. A special case is hospitalized aged patients, which present a high risk of infection and death because of the community acquired version of the Streptococcus pneumoniae pneumonia. There is evidence that early antibiotics treatment decreases the inflammatory response during pneumonia. Here, we investigate mechanistically this strategy using a multi-level mathematical model, which describes the 24 first hours after infection of a single alveolus from the key signaling networks behind activation of the epithelium to the dynamics of the local immune response. With the model, we simulated pneumonia in aged and young patients subjected to different antibiotics timing. The results show that providing antibiotics to elderly patients 8 h in advance compared to young patients restores in aged individuals the effective response seen in young ones. This result suggests the use of early, probably prophylactic, antibiotics treatment in aged hospitalized people with high risk of pneumonia.
CRIS-Team Scopus Importer:2020-11-20
Keywords: Inflammation; Macrophages; Mathematical model; Monocytes; Multi-level; Neutrophils; Pneumonia; Streptococcus pneumoniae

The role of cooperativity in a p53-miR34 dynamical mathematical model - Nikolov, Svetoslav; Wolkenhauer, Olaf; Vera, Julio; Nenov, Momchil (Journal of Theoretical Biology, 2020)
The objective of this study is to evaluate the role of cooperativity, captured by the Hill coefficient, in a minimal mathematical model describing the interactions between p53 and miR-34a. The model equations are analyzed for negative, none and normal cooperativity using a specific version of bifurcation theory and they are solved numerically. Special attention is paid to the sign of so-called first Lyapunov value. Interpretations of the results are given, both according to dynamic theory and in biological terms. In terms of cell signaling, we propose the hypothesis that when the outgoing signal of a system spends a physiologically significant amount of time outside of its equilibrium state, then the value of that signal can be sampled at any point along the trajectory towards that equilibrium and indeed, at multiple points. Coupled with non-linear behavior, such as that caused by cooperativity, this feature can account for a complex and varied response, which p53 is known for. From dynamical point of view, we found that when cooperativity is negative, the system has only one stable equilibrium point. In the absence of cooperativity, there is a single unstable equilibrium point with a critical boundary of stability. In the case with normal cooperativity, the system can have one, two, or three steady states with both, bi-stability and bi-instability occurring.
CRIS-Team Scopus Importer:2020-04-14
Keywords: Cooperativity; Numerical analysis; p53-miR34 dynamics; Qualitative analysis

The role of immune checkpoint blockade in uveal melanoma - Wessely, Anja; Steeb, Theresa; Erdmann, Michael; Heinzerling, Lucie; Vera, Julio; Schlaak, Max; Berking, Carola; Heppt, Markus (International Journal of Molecular Sciences, 2020)
Uveal melanoma (UM) represents the most common intraocular malignancy in adults and accounts for about 5% of all melanomas. Primary disease can be effectively controlled by several local therapy options, but UM has a high potential for metastatic spread, especially to the liver. Despite its clinical and genetic heterogeneity, therapy of metastatic UM has largely been adopted from cutaneous melanoma (CM) with discouraging results until now. The introduction of antibodies targeting CTLA-4 and PD-1 for immune checkpoint blockade (ICB) has revolutionized the field of cancer therapy and has achieved pioneering results in metastatic CM. Thus, expectations were high that patients with metastatic UM would also benefit from these new therapy options. This review provides a comprehensive and up-to-date overview on the role of ICB in UM. We give a summary of UM biology, its clinical features, and how it differs from CM. The results of several studies that have been investigating ICB in metastatic UM are presented. We discuss possible reasons for the lack of efficacy of ICB in UM compared to CM, highlight the pitfalls of ICB in this cancer entity, and explain why other immune-modulating therapies could still be an option for future UM therapies.
CRIS-Team Scopus Importer:2020-02-14
Keywords: CTLA-4; Cytotoxic T lymphocyte-associated antigen; Immune checkpoint blockade; Ipilimumab; Nivolumab; Ocular melanoma; PD-1; Pembrolizumab; Programmed death 1; Uveal melanoma

The Role of MicroRNAs in Cancer Biology and Therapy from a Systems Biology Perspective - Lai, Xin; Schmitz, Ulf; Vera, Julio (Springer, 2022)
Since the discovery of microRNAs (miRNAs) in Caenorhabditis elegans, our understanding of their cellular function has progressed continuously. Today, we have a good understanding of miRNA-mediated gene regulation, miRNA-mediated cross talk between genes including competing endogenous RNAs, and miRNA-mediated signaling transduction both in normal human physiology and in diseases. Besides, these noncoding RNAs have shown their value for clinical applications, especially in an oncological context. They can be used as reliable biomarkers for cancer diagnosis and prognosis and attract increasing attention as potential therapeutic targets. Many achievements made in the miRNA field are based on joint efforts from computational and molecular biologists. Systems biology approaches, which integrate computational and experimental methods, have played a fundamental role in uncovering the cellular functions of miRNAs. In this chapter, we review and discuss the role of miRNAs in oncology from a system biology perspective. We first describe biological facts about miRNA genetics and function. Next, we discuss the role of miRNAs in cancer progression and review the application of miRNAs in cancer diagnostics and therapy. Finally, we elaborate on the role that miRNAs play in cancer gene regulatory networks. Taken together, we emphasize the importance of systems biology approaches in our continued efforts to study miRNA cancer regulation.
CRIS-Team Scopus Importer:2022-12-02
Keywords: Bioinformatics; Circulating miRNA; Mathematical modelling; Metastamir; mRNA destabilization; Network biology; Oncomir; Posttranscriptional gene regulation; Translation repression; Tumor suppressor miRNA

The simultaneous siRNA-mediated downregulation of inhibitory receptors to improve CAR-T cell immunotherapy of melanoma - Simon, B.; Harrer, D.; Weide, B.; Schuler, Gerold; Schuler-Thurner, Beatrice; Dörrie, Jan; Schaft, Niels; Uslu, Ugur (2017)
EVALuna2:34317

The simultaneous siRNA-mediated downregulation of PD-1 and CTLA-4 to improve CAR-T cell immunotherapy of melanoma - Simon, B.; Harrer, D.; Schuler-Thurner, Beatrice; Dörrie, Jan; Schaft, Niels; Schuler, Gerold; Uslu, Ugur (2018)
EVALuna2:34395

The siRNA-mediated downregulation of PD-1 alone or simultaneously with CTLA-4 shows enhanced in vitro CAR-T-cell functionality for further clinical development towards the potential use in immunotherapy of melanoma - Simon, Bianca; Harrer, Dennis C.; Schuler-Thurner, Beatrice; Schaft, Niels; Schuler, Gerold; Dörrie, Jan; Uslu, Ugur (Experimental Dermatology, 2018)
Chimeric antigen receptor (CAR)-T cells have been used successfully for cancer immunotherapy. While substantial tumor regression was observed in leukaemia and lymphoma, CAR therapy of solid tumors needs further improvement. A major obstacle to the efficiency of engineered T cells is posed by triggering of inhibitory receptors, for example programmed cell death protein 1 (PD-1) and cytotoxic T lymphocyte-associated protein 4 (CTLA-4), leading to an impaired antitumor activity. To boost CAR-T-cell function, we co-electroporated T cells with both, mRNA encoding a CAR specific for chondroitin sulphate proteoglycan 4 (CSPG4) and small-interfering RNAs (siRNAs) to downregulate PD-1 (siPD-1) and CTLA-4 (siCTLA-4). Flow cytometry revealed that activation-induced upregulation of both PD-1 and CTLA-4 was suppressed when compared to CAR-T cells electroporated with negative control siRNA. The siRNA transfection showed no influence on CAR expression of engineered T cells. Functionality assays were performed using PD-L1- and CD80-transfected melanoma cells endogenously expressing CSPG4. CAR-T cells transfected with siPD-1 alone showed improvement in cytokine secretion. Additionally, CAR-T cells transfected with either siPD-1 alone or together with siCTLA-4 exhibited a significantly increased cytotoxicity. No or only little effects were observed when CAR-T cells were co-transfected with siCTLA-4 only. Taken together, it is feasible to optimize CAR-T cells by co-transfection of CAR-encoding mRNA and siRNAs to downregulate inhibitory receptors. Our in vitro data indicate an improvement of the functionality of these CAR-T cells, suggesting that this strategy could represent a novel method to enhance CAR-T-cell immunotherapy of cancer.
EVALuna2:34375

The soluble CD83 molecule accelerates wound closure and improves wound healing quality - Royzman, Dmytro; Peckert-Maier, Katrin; Stich, Lena; Wild, Andreas; Ostalecki, Christian; Seyferth, Stefan; Eming, Sabine A.; Fuchs, Maximilian; Kunz, Meik; Sturmer, Ewa K.; Peters, Eva M. J.; Berking, Carola; et al. (WOUND REPAIR AND REGENERATION, 2022)
CRIS-Team WoS Importer:2022-09-16

The soluble CD83 protein prevents bone destruction by inhibiting the formation of osteoclasts and inducing resolution of inflammation in arthritis - Royzman, Dmytro; Andreev, Darja; Stich, Lena; Peckert, Katrin; Wild, Andreas; Zinser, Elisabeth; Mühl-Zürbes, Petra; Jones, Evan; Adam, Susanne; Frey, Silke; Fuchs, Maximilian; Kunz, Meik; et al. (Frontiers in Immunology, 2022)
Here we show that soluble CD83 induces the resolution of inflammation in an antigen-induced arthritis (AIA) model. Joint swelling and the arthritis-related expression levels of IL-1 beta, IL-6, RANKL, MMP9, and OC-Stamp were strongly reduced, while Foxp3 was induced. In addition, we observed a significant inhibition of TRAP(+) osteoclast formation, correlating with the reduced arthritic disease score. In contrast, cell-specific deletion of CD83 in human and murine precursor cells resulted in an enhanced formation of mature osteoclasts. RNA sequencing analyses, comparing sCD83- with mock treated cells, revealed a strong downregulation of osteoclastogenic factors, such as Oc-Stamp, Mmp9 and Nfatc1, Ctsk, and Trap. Concomitantly, transcripts typical for pro-resolving macrophages, e.g., Mrc1/2, Marco, Klf4, and Mertk, were upregulated. Interestingly, members of the metallothionein (MT) family, which have been associated with a reduced arthritic disease severity, were also highly induced by sCD83 in samples derived from RA patients. Finally, we elucidated the sCD83-induced signaling cascade downstream to its binding to the Toll-like receptor 4/(TLR4/MD2) receptor complex using CRISPR/Cas9-induced knockdowns of TLR4/MyD88/TRIF and MTs, revealing that sCD83 acts via the TRIF-signaling cascade. In conclusion, sCD83 represents a promising therapeutic approach to induce the resolution of inflammation and to prevent bone erosion in autoimmune arthritis.
CRIS-Team WoS Importer:2022-09-09

The tanning habits and interest in sunscreen of Google users: what happened in 12 years? - Kirchberger, Michael C.; Heppt, Markus V.; Eigentler, Thomas K.; Kirchberger, Markus A.; Schuler, Gerold; Heinzerling, Lucie (Photodermatology Photoimmunology & Photomedicine, 2017)
BACKGROUND: The incidence of melanoma has been rising worldwide. One possible reason for this is natural and artificial UV exposure. Only little data on actual consumer statistics from tanning studios and the usage of sunscreen are available. Therefore, it is difficult to describe trends for both and identify the impact of preventive measures. METHODS: To gain knowledge about the popularity of 'tanning bed' and 'sunscreen', normalized search volumes for both search queries were obtained from Google Trends for 11 countries between January 2004 and June 2016. RESULTS: With few exceptions, worldwide interest in 'tanning bed' has been declining, whereas interest in 'sunscreen' has been increasing. The assessed countries from the Southern Hemisphere showed minor interest in tanning compared to the Northern Hemisphere. Both search queries were observed to fluctuate in a seasonal pattern. Skin cancer prevention measures influence the interest in tanning beds and sunscreen. CONCLUSION: Google Trends data can act as a first surrogate marker to evaluate the influence of skin cancer campaigns on the popularity of tanning beds and sunscreen. Fine-tuning of skin cancer campaigns according to seasonal and geographic trends and behaviors may help to maximize their success.
EVALuna2:34324

The transfection of natural killer T cells with a tumor-antigen specific chimeric antigen receptor (CAR) for melanoma immunotherapy - Simon, B.; Wiesinger, M.; Maerz, J.; Wistuba-Hamprecht, K.; Weide, B.; Schuler-Thurner, Beatrice; Schuler, Gerold; Dörrie, Jan; Uslu, Ugur (EXPERIMENTAL DERMATOLOGY, 2019)
CRIS-Team WoS Importer:2019-03-26

The value of convolutional neural networks in the diagnosis of melanoma simulators - Heppt, Markus; Berking, Carola (Journal of the European Academy of Dermatology and Venereology, 2020)
CRIS-Team Scopus Importer:2020-06-26

The value of total body photography for the early detection of melanoma: A systematic review - Hornung, Annkathrin; Steeb, Theresa; Wessely, Anja; Brinker, Titus J.; Breakell, Thomas; Erdmann, Michael; Berking, Carola; Heppt, Markus (International Journal of Environmental Research and Public Health, 2021)
Early detection of melanoma is critical to reduce the mortality and morbidity rates of this tumor. Total body photography (TBP) may aid in the early detection of melanoma. To summarize the current evidence on TBP for the early detection of melanoma, we performed a systematic literature search in Medline, Embase, and the Cochrane Central Register of Controlled Trials (CENTRAL) for eligible records up to 6th August 2020. Outcomes of interest included melanoma incidence, incisional and excisional biopsy rates, as well as the Breslow’s index of detected tumors. Results from individual studies were described qualitatively. The risks of bias and applicability of the included studies was assessed using the QUADAS-2 checklist. In total, 14 studies published between 1997 and 2020 with an overall sample size of n = 12082 (range 100–4692) were included in the qualitative analysis. Individuals undergoing TBP showed a trend towards a lower Breslow’s thickness and a higher proportion of in situ melanomas compared to those without TBP. The number needed to excise one melanoma varied from 3:1 to 14.3:1 and was better for lesions that arose de novo than for tracked ones. The included studies were judged to be of unclear methodological concern with specific deficiencies in the domains “flow and timing” and “reference standard”. The use of TBP can improve the early detection of melanoma in high-risk populations. Future studies are warranted to reduce the heterogeneity of phenotypic risk factor definition and the technical implementation of TBP. Artificial intelligence-assisted analysis of images derived from 3-D TBP systems and digital dermoscopy may further improve the early detection of melanoma.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Artificial intelligence; Early detection; Melanoma; Photography; Prevention; Skin cancer; Total body photographic cutaneous surveillance

Third-Kind Encounters in Biomedicine: Immunology Meets Mathematics and Informatics to Become Quantitative and Predictive - Eberhardt, Martin; Lai, Xin; Tomar, Namrata; Gupta, Shailendra; Schmeck, Bernd; Steinkasserer, Alexander; Schuler, Gerold; Vera, Julio (Methods in Molecular Biology, 2016)
The understanding of the immune response is right now at the center of biomedical research. There are growing expectations that immune-based interventions will in the midterm provide new, personalized, and targeted therapeutic options for many severe and highly prevalent diseases, from aggressive cancers to infectious and autoimmune diseases. To this end, immunology should surpass its current descriptive and phenomenological nature, and become quantitative, and thereby predictive.Immunology is an ideal field for deploying the tools, methodologies, and philosophy of systems biology, an approach that combines quantitative experimental data, computational biology, and mathematical modeling. This is because, from an organism-wide perspective, the immunity is a biological system of systems, a paradigmatic instance of a multi-scale system. At the molecular scale, the critical phenotypic responses of immune cells are governed by large biochemical networks, enriched in nested regulatory motifs such as feedback and feedforward loops. This network complexity confers them the ability of highly nonlinear behavior, including remarkable examples of homeostasis, ultra-sensitivity, hysteresis, and bistability. Moving from the cellular level, different immune cell populations communicate with each other by direct physical contact or receiving and secreting signaling molecules such as cytokines. Moreover, the interaction of the immune system with its potential targets (e.g., pathogens or tumor cells) is far from simple, as it involves a number of attack and counterattack mechanisms that ultimately constitute a tightly regulated multi-feedback loop system. From a more practical perspective, this leads to the consequence that today's immunologists are facing an ever-increasing challenge of integrating massive quantities from multi-platforms.In this chapter, we support the idea that the analysis of the immune system demands the use of systems-level approaches to ensure the success in the search for more effective and personalized immune-based therapies.
EVALuna2:19605

THP-1-derived macrophages render lung epithelial cells hypo-responsive to Legionella pneumophila - a systems biology study - Schulz, Christine; Lai, Xin; Bertrams, Wilhelm; Jung, Anna Lena; Sittka-Stark, Alexandra; Herkt, Christina Elena; Janga, Harshavadhan; Zscheppang, Katja; Stielow, Christina; Schulte, Leon; Hippenstiel, Stefan; Vera, Julio; et al. (Scientific Reports, 2017)
Immune response in the lung has to protect the huge alveolar surface against pathogens while securing the delicate lung structure. Macrophages and alveolar epithelial cells constitute the first line of defense and together orchestrate the initial steps of host defense. In this study, we analysed the influence of macrophages on type II alveolar epithelial cells during Legionella pneumophila-infection by a systems biology approach combining experimental work and mathematical modelling. We found that L. pneumophila-infected THP-1-derived macrophages provoke a pro-inflammatory activation of neighboring lung epithelial cells, but in addition render them hypo-responsive to direct infection with the same pathogen. We generated a kinetic mathematical model of macrophage activation and identified a paracrine mechanism of macrophage-secreted IL-1β inducing a prolonged IRAK-1 degradation in lung epithelial cells. This intercellular crosstalk may help to avoid an overwhelming inflammatory response by preventing excessive local secretion of pro-inflammatory cytokines and thereby negatively regulating the recruitment of immune cells to the site of infection. This suggests an important but ambivalent immunomodulatory role of macrophages in lung infection.
EVALuna2:35404

Three generations of suffering: cryopyrin-associated periodic syndrome with NLRP3 mutation in a family - Wagner, Nicola; Manger, Bernhard; Kittler, Julia; Rech, Jürgen; Sticherling, Michael; Berking, Carola; Kirchberger, Michael Constantin (Journal der Deutschen Dermatologischen Gesellschaft, 2021)
CRIS-Team Scopus Importer:2021-12-24

Threshold Optimization for Tumor Markers S100b and MIA in Uveal Melanoma - A Single Center Analysis - Glaser, Naemi; Petzold, Anne; Wessely, Anja; Kaufmann, Matthias; Koch, Elias; Knorr, Harald; Voskens, Caroline; Heppt, Markus; Berking, Carola; Erdmann, Michael (Anticancer Research, 2023)
Background/Aim: Uveal melanoma (UM) is the most common malignant tumor of the eye in adults. Metastases develop in 50% of the patients, predominantly in the liver. In UM, the cut-off concentrations of the bloodbased tumor markers S100b and MIA are inconclusive. Patients and Methods: In this retrospective monocenter study, we statistically evaluated 1,878 S100b and 1,768 MIA measurements in 244 patients with UM from 2011-2020. Threshold optimization was performed using receiver operating characteristic (ROC) curves. Results: A total of 171 patients with non-metastatic UM (nmUM) and 73 patients with metastatic UM (mUM) showed no differences in sex, age at diagnosis or the affected eye. In mUM, 80% of the patients developed metastases to the liver at a median of 46 months after initial diagnosis. The sensitivity and specificity of S100b was 16.10% and 94.52%, and that of MIA was 31.86% and 81.42%, respectively. ROC curves revealed poor values for the area under the curve of 0.57 for S100b and 0.55 for MIA. The optimal cut-off concentration to detect metastases was 0.14 μg/l for S100b and 17.4 ng/ml for MIA. With at least one tumor marker elevated, optimized sensitivity was 20.40% and specificity 96.76%. Conclusion: Current thresholds for S100b and MIA in UM are not able to detect early metastatic disease and require additional diagnostics to clarify false positive results. Threshold optimization considering both S100b and MIA results in a better diagnostic validity with an acceptable specificity and a poor sensitivity. Highly sensitive blood-based and imaging methods to detect metastases early in UM are urgently needed.
CRIS-Team Scopus Importer:2023-11-03
Keywords: MIA; S100b; threshold optimization; tumor marker; Uveal melanoma

Thymic CD4 T cell selection requires attenuation of March8-mediated MHCII turnover in cortical epithelial cells through CD83 - Von Rohrscheidt, Julia; Petrozziello, Elisabetta; Nedjic, Jelena; Federle, Christine; Krzyzak, Lena; Ploegh, Hidde L.; Ishido, Satoshi; Steinkasserer, Alexander; Klein, Ludger (Journal of Experimental Medicine, 2016)
Deficiency of CD83 in thymic epithelial cells (TECs) dramatically impairs thymic CD4 T cell selection. CD83 can exert cell-intrinsic and -extrinsic functions through discrete protein domains, but it remains unclear how CD83's capacity to operate through these alternative functional modules relates to its crucial role in TECs. In this study, using viral reconstitution of gene function in TECs, we found that CD83's transmembrane domain is necessary and sufficient for thymic CD4 T cell selection. Moreover, a ubiquitination-resistant MHCII variant restored CD4 T cell selection in Cd83(-/-) mice. Although during dendritic cell maturation CD83 is known to stabilize MHCII through opposing the ubiquitin ligase March1, regulation of March1 did not account for CD83's TEC-intrinsic role. Instead, we provide evidence that MHCII in cortical TECs (cTECs) is targeted by March8, an E3 ligase of as yet unknown physiological substrate specificity. Ablating March8 in Cd83(-/-) mice restored CD4 T cell development. Our results identify CD83-mediated MHCII stabilization through antagonism of March8 as a novel functional adaptation of cTECs for T cell selection. Furthermore, these findings suggest an intriguing division of labor between March1 and March8 in controlling inducible versus constitutive MHCII expression in hematopoietic antigen-presenting cells versus TECs.
EVALuna2:26036

Thymic stromal lymphopoietin deficiency attenuates experimental autoimmune encephalomyelitis - Eckhardt, J.; Döbbeler, Marina; Koenig, C.; Kuczera, K.; Kuhnt, C.; Ostalecki, C.; Zinser, E.; Mak, T. W.; Steinkasserer, Alexander; Lechmann, Matthias (Clinical and Experimental Immunology, 2015)
In the present study we examined the role of thymic stromal lymphopoietin (TSLP) in experimental autoimmune encephalomyelitis (EAE). Here, we report that TSLP knock-out (KO) mice display a delayed onset of disease and an attenuated form of EAE. This delayed onset was accompanied by a reduced number of encephalitogenic T helper type 1 (Th1) cells in the central nervous system (CNS) of TSLP KO mice. In addition, CD4(+) and CD8(+) T cells from CNS of TSLP KO mice show a reduced activation status in comparison to wild-type mice. It is noteworthy that we could also show that lymph node cells from TSLP KO mice expanded less efficiently and that interleukin (IL)-6-, interferon (IFN)-? and tumour necrosis factor (TNF)-? levels were reduced. Furthermore, CD3(+) T cells isolated in the preclinical phase from myelin oligodendrocyte glycoprotein peptide 35-55 (MOG(35-55))-immunized TSLP KO mice showed a reduced response after secondary exposure to MOG(35-55), indicating that differentiation of naive T cells into MOG(35-55)-specific effector and memory T cells was impaired in KO mice. The addition of recombinant TSLP enhanced T cell proliferation during MOG(35-55) restimulation, showing that T cells also respond directly to TSLP. In summary, these data demonstrate that expression of, and immune activation by, TSLP contributes significantly to the immunopathology of EAE.
EVALuna2:19524

TILGen: A Program to Investigate Immune Targets in Breast Cancer Patients - First Results on the Influence of Tumor-Infiltrating Lymphocytes - Würfel, Franziska; Erber, Ramona; Hübner, Hanna; Hein, Alexander; Lux, Michael P.; Jud, Sebastian; Kremer, Anita; Kranich, Hannah; Mackensen, Andreas; Häberle, Lothar; Hack, Carolin; Rauh, Claudia; et al. (Breast Care, 2018)
Background: Despite advancements in the treatment of primary and metastatic breast cancer, many patients lack a durable response to these treatments. Patients with triplenegative breast cancer (TNBC) and human epidermal growth factor receptor 2(HER2)-positive breast cancer who do not have a pathological complete response (pCR) after neoadjuvant chemotherapy (NACT) have a very poor prognosis. Tumor-infiltrating lymphocytes (TILs) have been identified as a predictive marker for pCR after NACT in TNBC and HER2-positive breast cancer. These patient populations could also be suitable for novel treatment strategies including neoepitope-based therapies. This work analyses the effect of TILs on the pCR in neoadjuvantly treated patients in the TILGen study and presents the procedures aimed at establishing neoepitope-based therapies in this study. Methods: Neoadjuvantly treated HER2positive and TNBC patients were eligible for the presented analysis concerning the association between TILs and pCR. A total of 146 patients could be identified within the TILGen study. TILs were evaluated as percentage of stromal tumor tissue in core biopsies at primary diagnosis. The phenotype 'lymphocyte-predominant breast cancer' (LPBC) was associated with pCR by logistic regression adjusted for estrogen receptor status, progesterone receptor status, HER2 status, age at diagnosis, and grading. Results: LPBC was seen in 24 (16.4%) patients. In this patient group, 66.7% achieved a pCR, while the pCR rate was 32.8% in patients with a low TIL count. The adjusted odds ratio was 6.60 (95% confidence interval 2.02-21.56; p < 0.01). Conclusion: TILs are a strong predictor of pCR in TNBC and HER2-positive breast cancer patients. Implications for the use of this information including the effect on prognosis might help to identify patients most likely to benefit from a neoepitope-based therapy approach. (C) 2018 S. Karger GmbH, Freiburg
EVALuna2:34061
Keywords: Tumor-infiltrating lymphocytes; Response; Neoadjuvant chemotherapy; TILGen study

Tilting the Balance: Therapeutic Prospects of CD83 as a Checkpoint Molecule Controlling Resolution of Inflammation - Peckert-Maier, Katrin; Royzman, Dmytro; Langguth, Pia; Marosán, Anita; Strack, Astrid; Sadeghi Shermeh, Atefeh; Steinkasserer, Alexander; Zinser, Elisabeth; Wild, Andreas (International Journal of Molecular Sciences, 2022)
Chronic inflammatory diseases and transplant rejection represent major challenges for modern health care. Thus, identification of immune checkpoints that contribute to resolution of inflammation is key to developing novel therapeutic agents for those conditions. In recent years, the CD83 (cluster of differentiation 83) protein has emerged as an interesting potential candidate for such a “pro-resolution” therapy. This molecule occurs in a membrane-bound and a soluble isoform (mCD83 and sCD83, respectively), both of which are involved in resolution of inflammation. Originally described as a maturation marker on dendritic cells (DCs), mCD83 is also expressed by activated B and T cells as well as regulatory T cells (Tregs) and controls turnover of MHC II molecules in the thymus, and thereby positive selection of CD4+ T cells. Additionally, it serves to confine overshooting (auto-)immune responses. Consequently, animals with a conditional deletion of CD83 in DCs or regulatory T cells suffer from impaired resolution of inflammation. Pro-resolving effects of sCD83 became evident in pre-clinical autoimmune and transplantation models, where application of sCD83 reduced disease symptoms and enhanced allograft survival, respectively. Here, we summarize recent advances regarding CD83-mediated resolution of inflammatory responses, its binding partners as well as induced signaling pathways, and emphasize its therapeutic potential for future clinical trials.
CRIS-Team Scopus Importer:2022-01-14
Keywords: Adoptive transfer; CD83; IDO/TGF-β-axis; Pro-resolving macrophages; Resolution of inflammation; Transplantation

Tirbanibulin 1% Ointment Significantly Reduces the Actinic Keratosis Area and Severity Index in Patients with Actinic Keratosis: Results from a Real-World Study - Kirchberger, Michael; Gfesser, Michael; Erdmann, Michael; Schliep, Stefan; Berking, Carola; Heppt, Markus (Journal of Clinical Medicine, 2023)
Background: Actinic keratosis (AK) is a cutaneous lesion resulting from the proliferation of atypical epidermal keratinocytes caused by long-term exposure to ultraviolet radiation. AK may progress to cutaneous squamous cell carcinoma (cSCC) and therefore is often treated with topical agents such as 5-fluorouracil, diclofenac, imiquimod, and photodynamic therapy. Tirbanibulin has been approved based on two phase III trials in the USA. However, real-world evidence for tirbanibulin is absent. Methods: This was a single-centre study of adult patients with clinically typical, visible AK on the face or scalp treated with tirbanibulin 1% ointment. Treatment was administered as per label once daily for 5 consecutive days on the same lesions or field. Treatment outcomes were assessed 4 weeks after treatment, with additional optional assessments conducted at later time points. Efficacy was measured using the actinic keratosis area and severity index (AKASI) and digital dermoscopy. Results: A total of 33 patients were treated of whom 30 were analysed. The median AKASI score was 5.6 (1.4–11) pre-treatment and 1.2 (0–7.4) post-treatment (p < 0.0001). Complete clearance as defined by AKASI scores less than 1 was achieved in 47% (n = 14) and 57% (n = 13) at the first and second follow-up, respectively. All local reactions resolved spontaneously and without sequelae. The most common local reactions were erythema (80%, n = 26) and flaking or scaling (43%, n = 13). Conclusions: Tirbanibulin 1% ointment significantly and rapidly reduced the AKASI score in a real-world setting. The complete clearance rates were in line with those observed in the two pivotal trials.
CRIS-Team Scopus Importer:2023-08-11
Keywords: actinic keratosis; AKASI score; Klisyri

TNF-Mediated Restriction of Arginase 1 Expression in Myeloid Cells Triggers Type 2 NO Synthase Activity at the Site of Infection - Schleicher, Ulrike; Paduch, Katrin; Debus, Andrea; Obermeyer, Stephanie; Koenig, Till; Kling, Jessica C.; Ribechini, Eliana; Dudziak, Diana; Mougiakakos, Dimitrios; Murray, Peter J.; Ostuni, Renato; Koerner, Heinrich; et al. (Cell Reports, 2016)
Neutralization or deletion of tumor necrosis factor (TNF) causes loss of control of intracellular pathogens in mice and humans, but the underlying mechanisms are incompletely understood. Here, we found that TNF antagonized alternative activation of macrophages and dendritic cells by IL-4. TNF inhibited IL-4-induced arginase 1 (Arg1) expression by decreasing histone acetylation, without affecting STAT6 phosphorylation and nuclear translocation. In Leishmania major-infected C57BL/6 wild-type mice, type 2 nitric oxide (NO) synthase (NOS2) was detected in inflammatory dendritic cells or macrophages, some of which co-expressed Arg1. In TNF-deficient mice, Arg1 was hyperexpressed, causing an impaired production of NO in situ. A similar phenotype was seen in L. major-infected BALB/c mice. Arg1 deletion in hematopoietic cells protected these mice from an otherwise lethal disease, although their disease-mediating T cell response (Th2, Treg) was maintained. Thus, deletion or TNF-mediated restriction of Arg1 unleashes the production of NO by NOS2, which is critical for pathogen control.
EVALuna2:7700

Topical application of soluble CD83 induces IDO-mediated immune modulation, increases Foxp3+ T cells, and prolongs allogeneic corneal graft survival - Bock, Felix; Roessner, Susanne; Onderka, Jasmine; Lechmann, Matthias; Pallotta, Maria Teresa; Fallarino, Francesca; Boon, Louis; Nicolette, Charles; Debenedette, Mark A.; Tcherepanova, Irina Y.; Grohmann, Ursula; Steinkasserer, Alexander; et al. (Journal of Immunology, 2013)
Modulation of immune responses is one of the main research aims in transplant immunology. In this study, we investigate the local immunomodulatory properties of soluble CD83 (sCD83) at the graft-host interface using the high-risk corneal transplantation model. In this model, which mimics the inflammatory status and the preexisting vascularization of high-risk patients undergoing corneal transplantation, allogeneic donor corneas are transplanted onto sCD83-treated recipient animals. This model allows the direct and precise application of the immune modulator at the transplantation side. Interestingly, sCD83 was able to prolong graft survival after systemic application as well as after topical application, which is therapeutically more relevant. The therapeutic effect was accompanied by an increase in the frequency of regulatory T cells and was mediated by the immune-regulatory enzyme IDO and TGF-?. In vitro, sCD83 induced long-term IDO expression in both conventional and plasmacytoid dendritic cells via autocrine or paracrine production of TGF-?, a cytokine previously shown to be an essential mediator of IDO-dependent, long-term tolerance. These findings open new treatment avenues for local immune modulation after organ and tissue transplantation.
EVALuna2:21223

Topical therapy of psoriasis vulgaris - a treatment pathway - Koerber, Andreas; Wilsmann-Theis, Dagmar; Augustin, Matthias; Von Kiedrowski, Ralph; Mrowietz, Ulrich; Rosenbach, Thomas; Meller, Stephan; Pinter, Andreas; Sticherling, Michael; Gerdes, Sascha (Journal der Deutschen Dermatologischen Gesellschaft, 2019)
In daily practice topical treatment of psoriasis and its subtypes is of high importance. It is standard for the treatment of mild psoriasis and is used to support treatment of moderate-to-severe psoriasis. When optimizing psoriasis treatment not only the choice of suitable compounds, but also the formulation aspect matters. Developments in the latter field were not considered in the 2017 published update of the current S3-guideline on psoriasis. The presented pathway was prepared during a PsoNet speaker conference and confirmed by the national psoriasis care conference. It aims to illustrate current treatment options.
CRIS-Team WoS Importer:2019-05-09

Transcriptional Analysis identifies long non-coding RNAs as potential biomarkers in pneumonia and COPD exacerbation - Bertrams, W.; Griss, K.; Han, M.; Seidel, K.; Klemmer, A.; Sittka-Stark, A.; Hippenstiel, S.; Suttorp, N.; Finkernagel, F.; Wilhelm, J.; Greulich, T.; Vogelmeier, C.; et al. (PNEUMOLOGIE, 2020)
CRIS-Team WoS Importer:2020-11-27

Transcriptional analysis identifies potential biomarkers and molecular regulators in pneumonia and COPD exacerbation - Bertrams, W.; Griss, K.; Han, M.; Eberhardt, M.; Seidel, K.; Klemmer, A.; Sittka-Stark, A.; Hippenstiel, S.; Suttorp, N.; Finkernagel, F.; Wilhelm, J.; Greulich, T.; et al. (PNEUMOLOGIE, 2020)
CRIS-Team WoS Importer:2020-11-27

Transcriptional analysis identifies potential biomarkers and molecular regulators in pneumonia and COPD exacerbation - Bertrams, Wilhelm; Griss, Kathrin; Han, Maria; Seidel, Kerstin; Klemmer, Andreas; Sittka-Stark, Alexandra; Hippenstiel, Stefan; Suttorp, Norbert; Finkernagel, Florian; Wilhelm, Jochen; Greulich, Timm; Vogelmeier, Claus F.; et al. (Scientific Reports, 2020)
Lower respiratory infections, such as community-acquired pneumonia (CAP), and chronic obstructive pulmonary disease (COPD) rank among the most frequent causes of death worldwide. Improved diagnostics and profound pathophysiological insights are urgent clinical needs. In our cohort, we analysed transcriptional networks of peripheral blood mononuclear cells (PBMCs) to identify central regulators and potential biomarkers. We investigated the mRNA- and miRNA-transcriptome of PBMCs of healthy subjects and patients suffering from CAP or AECOPD by microarray and Taqman Low Density Array. Genes that correlated with PBMC composition were eliminated, and remaining differentially expressed genes were grouped into modules. One selected module (120 genes) was particularly suitable to discriminate AECOPD and CAP and most notably contained a subset of five biologically relevant mRNAs that differentiated between CAP and AECOPD with an AUC of 86.1%. Likewise, we identified several microRNAs, e.g. miR-545-3p and miR-519c-3p, which separated AECOPD and CAP. We furthermore retrieved an integrated network of differentially regulated mRNAs and microRNAs and identified HNF4A, MCC and MUC1 as central network regulators or most important discriminatory markers. In summary, transcriptional analysis retrieved potential biomarkers and central molecular features of CAP and AECOPD.
CRIS-Team Scopus Importer:2020-02-07

Transcriptional control of dendritic cell development and functions - Amon, Lukas; Lehmann, Christian; Baranska, Anna; Schoen, Janina; Heger, Lukas; Dudziak, Diana (Immunobiology of Dendritic Cells Part B, 2019)
Dendritic cells (DCs) are major regulators of adaptive immunity, as they are not only capable to induce efficient immune responses, but are also crucial to maintain peripheral tolerance and thereby inhibit autoimmune reactions. DCs bridge the innate and the adaptive immune system by presenting peptides of self and foreign antigens as peptide MHC complexes to T cells. These properties render DCs as interesting target cells for immunomodulatory therapies in cancer, but also autoimmune diseases. Several subsets of DCs with special properties and functions have been described. Recent achievements in understanding transcriptional programs on single cell level, together with the generation of new murine models targeting specific DC subsets, advanced our current understanding of DC development and function. Thus, DCs arise from precursor cells in the bone marrow with distinct progenitor cell populations splitting the monocyte populations and macrophage populations from the DC lineage, which upon lineage commitment can be separated into conventional cDC1, cDC2, and plasmacytoid DCs (pDCs). The DC populations harbor intrinsic programs enabling them to react for specific pathogens in dependency on the DC subset, and thereby orchestrate T cell immune responses. Similarities, but also varieties, between human and murine DC subpopulations are challenging, and will require further investigation of human specimens under consideration of the influence of the tissue micromilieu and DC subset localization in the future.
CRIS-Team Scopus Importer:2019-11-29
Keywords: Antigen presentation; BatF3; CDP; Cross-presentation; DC; Dendritic cell; IRF; Lineage commitment; Ontogeny; Progenitor; Transcription factor; Zbtb46

Transcriptional Profiling of Ligand Expression in Cell Specific Populations of the Adult Mouse Forebrain That Regulates Neurogenesis - Azim, Kasum; Akkermann, Rainer; Cantone, Martina; Vera, Julio; Jadasz, Janusz J.; Kuery, Patrick (Frontiers in Neuroscience, 2018)
In the adult central nervous system (CNS), the subventricular zone (SVZ) of the forebrain is the largest and most active source of neural stem cells (NSCs) that generates mainly neurons and few glial cells lifelong. A large body of evidence has shed light on the distinct families of signaling ligands (i.e., morphogens, growth factors, secreted molecules that alter signaling pathways) in regulating NSC biology. However, most of the research has focused on the mRNA expression of individual or few signaling ligands and their pathway components in specific cell types of the CNS in the context of neurogenesis. A single unifying study that underlines the expression of such molecules comprehensively in different cell types in spatial contexts has not yet been reported. By using whole genome transcriptome datasets of individual purified cell specific populations of the adult CNS, the SVZ niche, NSCs, glial cells, choroid plexus, and performing a bioinformatic meta-analysis of signaling ligands, their expression in the forebrain was uncovered. Therein, we report that a large plethora of ligands are abundantly expressed in the SVZ niche, largely from the vasculature than from other sources that may regulate neurogenesis. Intriguingly, this sort of analysis revealed a number of ligands with unknown functions in neurogenesis contexts that warrants further investigations. This study therefore serves as a framework for investigators in the field for understanding the expression patterns of signaling ligands and pathways regulating neurogenesis.
EVALuna2:34797

Transcriptional Targeting of Mature Dendritic Cells with Adenoviral Vectors via a Modular Promoter System for Antigen Expression and Functional Manipulation - Knippertz, Ilka; Deinzer, Anja; Dörrie, Jan; Schaft, Niels; Nettelbeck, Dirk M.; Steinkasserer, Alexander (International Journal of Microbiology and Immunology Research, 2016)
To specifically target dendritic cells (DCs) to simultaneously express different therapeutic transgenes for inducing immune responses against tumors, we used a combined promoter system of adenoviral vectors. We selected a 216 bp short Hsp70B'. core promoter induced by a mutated, constitutively active heat shock factor (mHSF) 1 to drive strong gene expression of therapeutic transgenes Melan A, BclxL, and IL-12p70 in HeLa cells, as well as in mature DCs ( mDCs). As this involves overexpressing mHSF1, we first evaluated the resulting effects on DCs regarding upregulation of heat shock proteins and maturation markers, toxicity, cytokine profile, and capacity to induce antigen-specific CD8+ T cells. Second, we generated the two-vector-based "modular promoter" system, where one vector contains the mHSF1 under the control of the human CD83 promoter, which is specifically active only in DCs and after maturation. mHSF1, in turn, activates the Hsp70B.. core promotor-driven expression of transgenes MelanA and IL-12p70 in the DC-like cell line XS52 and in human mature and hence immunogenic DCs, but not in tolerogenic immature DCs. These in vitro experiments provide the basis for an in vivo targeting of mature DCs for the expression of multiple transgenes. Therefore, this modular promoter system represents a promising tool for future DC-based immunotherapies in vivo.
EVALuna2:19603

Transcription factor Fra-1 targets arginase-1 to enhance macrophage-mediated inflammation in arthritis - Hannemann, Nicole; Cao, Shan; Eriksson, Daniel; Schnelzer, Anne; Jordan, Jutta; Eberhardt, Martin; Schleicher, Ulrike; Rech, Jürgen; Uebe, Steffen; Ekici, Arif Bülent; Canete, Juan D.; Chen, Xiaoxiang; et al. (Journal of Clinical Investigation, 2019)
The polarization of macrophages is regulated by transcription factors, such as NF-κB and activator protein 1 (AP-1). In this manuscript, we delineated the role of the transcription factor Fos-related antigen 1 (Fra-1) during macrophage activation and development of arthritis. Network level interaction analysis of microarray data derived from Fra-1- or Fra-2-deficient macrophages revealed a central role of Fra-1, but not of Fra-2, in orchestrating the expression of genes related to wound response, Toll-like receptor activation, and interleukin signaling. ChIP sequencing and standard ChIP analyses of macrophages identified arginase 1 (Arg1) as a target of Fra-1. Luciferase reporter assays revealed that Fra-1 downregulated Arg1 expression by direct binding to the promoter region. Using macrophage-specific Fra-1- or Fra-2-deficient mice, we observed enhanced expression and activity of Arg1 and a reduction of arthritis in the absence of Fra-1, but not of Fra-2. This phenotype was reversed by treatment with the arginase inhibitor Nω-hydroxy-nor-arginine, while -arginine supplementation increased arginase activity and alleviated arthritis, supporting the notion that reduced arthritis in macrophage-specific Fra-1-deficient mice resulted from enhanced Arg1 expression and activity. Moreover, patients with active rheumatoid arthritis (RA) showed increased Fra-1 expression in the peripheral blood and elevated Fra-1 protein in synovial macrophages compared with RA patients in remission. In addition, the Fra-1/ARG1 ratio in synovial macrophages was related to RA disease activity. In conclusion, these data suggest that Fra-1 orchestrates the inflammatory state of macrophages by inhibition of Arg1 expression and thereby impedes the resolution of inflammation.
CRIS-Team Scopus Importer:2019-07-16

Transcription factor Sox10 induces the microRNAs miR-335, miR-338 and miR-155 to ensure correct timing of oligodendrocyte development - Küspert, Melanie; Reiprich, Simone; Cantone, Martina; Weider, Matthias; Baroti, Tina; Wittstatt, Jan; Vera, Julio; Wegner, Michael (GLIA, 2019)
CRIS-Team WoS Importer:2020-01-10

Transcription factor Sox10 regulates oligodendroglial Sox9 levels via microRNAs. - Reiprich, Simone; Cantone, Martina; Weider, Matthias; Baroti, Tina; Wittstatt, Jan; Schmitt, Christian; Küspert, Melanie; Vera, Julio; Wegner, Michael (Glia, 2017)
During development of myelin-forming oligodendrocytes in the central nervous system the two closely related transcription factors Sox9 and Sox10 play essential roles that are partly shared and partly unique. Whereas Sox9 primarily functions during oligodendroglial specification, Sox10 is uniquely required to induce terminal differentiation and myelination. During this process, Sox10 protein levels rise substantially. As this coincides with a reciprocal decrease in Sox9, we postulated that Sox10 influences Sox9 amounts in differentiating oligodendrocytes. Here we show that Sox9 levels are indeed inversely coupled to Sox10 levels such that Sox10 deletion in oligodendroglial cells evokes a reciprocal increase in Sox9. We furthermore provide evidence that this coupling involves upregulation of microRNAs miR335 and miR338 as direct transcriptional targets of Sox10. The two microRNAs in turn recognize the 3′-UTR of Sox9 mRNA and may thereby reduce Sox9 protein levels posttranscriptionally in oligodendroglial cells. Such a mechanism may enable oligodendroglial cells to adapt the ratio of both related Sox proteins in a manner required for successful lineage progression and differentiation. Mathematical modeling furthermore shows that the identified regulatory circuit has the potential to convert a transient stimulus into an irreversible switch of cellular properties and may thus contribute to terminal differentiation of oligodendrocytes.
EVALuna2:33479
Keywords: glia; HMG; miR338; oligodendrocyte; Sox

Transcriptomes of MPO-deficient patients with generalized pustular psoriasis reveals expansion of CD4+cytotoxic T cells and an involvement of complement system and interferon pathways - Hüffmeier, Ulrike; Frey, Benjamin; Becker, Ina; Atreya, Imke; Berking, Carola; Moessner, R.; Wilsmann-Theis, D.; Uebe, Steffen; Kirchner, P.; Haskamp, Stefan (JOURNAL OF INVESTIGATIVE DERMATOLOGY, 2021)
CRIS-Team WoS Importer:2021-11-05

Transcriptomes of MPO-Deficient Patients with Generalized Pustular Psoriasis Reveals Expansion of CD4+ Cytotoxic T Cells and an Involvement of the Complement System - Haskamp, Stefan; Frey, Benjamin; Becker, Ina; Schulz-Kuhnt, Anja; Atreya, Imke; Berking, Carola; Pauli, David; Ekici, Arif Bülent; Berges, Johannes; Mößner, Rotraut; Wilsmann-Theis, Dagmar; Sticherling, Michael; et al. (Journal of Investigative Dermatology, 2022)
Generalized pustular psoriasis is a severe psoriatic subtype characterized by epidermal neutrophil infiltration. Although variants in IL36RN and MPO have been shown to affect immune cells, a systematic analysis of neutrophils and PBMC subsets and their differential gene expression dependent on MPO genotypes was not performed yet. We assessed the transcriptomes of MPO-deficient patients using single-cell RNA sequencing of PBMCs and RNA sequencing of neutrophils in a stable disease state. Cell-type annotation by multimodal reference mapping of single-cell RNA-sequencing data was verified by flow cytometry of surface and intracellular markers; the proportions of CD4+ cytotoxic T lymphocytes and other CD4+ effector cells were increased in generalized pustular psoriasis, whereas the frequencies of naïve CD4+ T cells were significantly lower. The expression of FGFBP2 marking CD4+ cytotoxic T lymphocytes and CD8+ effector memory T cells was elevated in patients with generalized pustular psoriasis with disease-contributing variants compared with that in noncarriers (P = 0.0015). In neutrophils, differentially expressed genes were significantly enriched in genes of the classical complement activation pathway. Future studies assessing affected cell types and pathways will show their contribution to generalized pustular psoriasis's pathogenesis and indicate whether findings can be transferred to the acute epidermal situation and whether depletion or inactivation of CD4+ cytotoxic T lymphocytes may be a reasonable therapeutic approach.
CRIS-Team Scopus Importer:2022-07-08

Transfer of mRNA encoding recombinant immunoreceptors reprograms CD4+ and CD8+ T cells for use in the adoptive immunotherapy of cancer - Birkholz, K.; Hombach, A.; Krug, C.; Reuter, S.; Kershaw, Michael; Kämpgen, Eckhart; Schuler, Gerold; Abken, H.; Schaft, Niels; Dörrie, Jan (Gene Therapy, 2009)
Human T lymphocytes can be redirected with a new defined specificity by expression of a chimeric T-cell receptor (immunoreceptor) for the use in adoptive immunotherapy of cancer. Whereas standard procedures use retroviral gene transduction to constitutively express immunoreceptors in T cells, we here explored for the first time mRNA electroporation to achieve transient immunoreceptor expression, and thereby minimizing the risk of persistence of potential autoaggression. CD4+ and CD8+ T cells were efficiently transfected with immunoreceptors specific for ErbB2 and CEA. The immunoreceptor expression was transient with half-maximal expression at day 2 and no detectable immunoreceptor expression at day 9 after electroporation. Immunoreceptor-transfected T cells were specifically activated upon coincubation with ErbB2+ and CEA+ tumor cells, respectively, resulting in secretion of interferon-γ (IFNγ), interleukin-2 (IL-2), and tumor necrosis factor-α (TNFα). Furthermore, immunoreceptor-transfected CD8+ T cells specifically lysed ErbB2+ and CEA+ tumor cells, respectively. The RNA-transfected T cells retained their cytotoxic function after 2 days of activation and exhibited cytolytic activities like retrovirally transduced T cells. RNA electroporation of T cells thereby provides a versatile tool for transient immunoreceptor expression, which may be of advantage in avoiding the persistence of unintended autoaggression.
CRIS-Team Scopus Importer:2021-10-01

Transient response to nivolumab and relapse after infliximab in a patient with primary cutaneous CD8-positive aggressive epidermotropic cytotoxic T-cell lymphoma - Toussaint, Frédéric; Erdmann, M.; Grosch, Ella; Schliep, S.; Schuler, Gerold; Dummer, R.; Heinzerling, Lucie (British Journal of Dermatology, 2020)
CRIS-Team WoS Importer:2020-10-02

Trauma as a Trigger Factor for the First clinical Manifestation of cutaneous Leishmaniasis - Hiernickel, J.; Bogdan, Christian; Erfurt-Berge, Cornelia (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-05-17

Travel-associated infectious skin diseases - Rongisch, Robert; Schmidt, Enno; Deresz, Nicolai; Deresz, Katharina; Schoefer, Helmut; Schaekel, Knut; Jakob, Thilo; Maurer, Marcus; Sticherling, Michael; Sunderkoetter, Cord; Babilas, Philipp; Spornraft-Ragaller, Petra; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2020)
CRIS-Team Scopus Importer:2020-05-12

Treatment Decision when there is an Indication for adjuvant Therapy for Melanoma - multicenter Real World Data - Lodde, G.; Forschner, A.; Wulfken, L. M.; Meier, F.; Mohr, P.; Kaehler, K. C.; Schilling, B.; Loquai, C.; Berking, Carola; Gebhardt, C.; Huening, S.; Schatton, K.; et al. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2020)
CRIS-Team WoS Importer:2020-09-11

Treatment management for BRAF-mutant melanoma patients with tumor recurrence on adjuvant therapy: a multicenter study from the prospective skin cancer registry ADOREG - Haist, Maximilian; Stege, Henner; Rogall, Friederike; Tan, Yuqi; von Wasielewski, Imke; Klespe, Kai Christian; Meier, Friedegund; Mohr, Peter; Kähler, Katharina C.; Weichenthal, Michael; Hauschild, Axel; Schadendorf, Dirk; et al. (Journal for ImmunoTherapy of Cancer, 2023)
BACKGROUND: Adjuvant therapy with immune-checkpoint inhibitors (CPI) or BRAF/MEK-directed targeted therapy (TT) improves recurrence-free survival (RFS) for patients with advanced, BRAFV600-mutant (BRAFmut) resected melanoma. However, 40% of these patients will develop distant metastases (DM) within 5 years, which require systemic therapy. Little data exist to guide the choice of upfront adjuvant therapy or treatment management upon DM. This study evaluated the efficacy of subsequent treatments following tumor recurrence upon upfront adjuvant therapy. METHODS: For this multicenter cohort study, we identified 515 BRAFmut patients with resected stage III melanoma who were treated with PD-1 inhibitors (anti-PD1) or TT in the adjuvant setting. Disease characteristics, treatment regimens, details on tumor recurrence, subsequent treatment management, and survival outcomes were collected within the prospective, real-world skin cancer registry ADOReg. Primary endpoints included progression-free survival (PFS) following DM and best tumor response to first-line (1L) treatments. RESULTS: Among 515 eligible patients, 273 patients received adjuvant anti-PD1 and 242 adjuvant TT. At a median follow-up of 21 months, 54.6% of anti-PD1 patients and 36.4% of TT patients recurred, while 39.6% (anti-PD1) and 29.3% (TT) developed DM. Risk of recurrence was significantly reduced in patients treated with TT compared with anti-PD1 (adjusted HR 0.52; 95% CI 0.40 to 0.68, p<0.001). Likewise, median RFS was significantly longer in TT-treated patients (31 vs 17 months, p<0.001). Patients who received TT as second adjuvant treatment upon locoregional recurrence had a longer RFS2 as compared with adjuvant CPI (41 vs 6 months, p=0.009). Patients who recurred at distant sites following adjuvant TT showed favorable response rates (42.9%) after switching to 1L ipilimumab+nivolumab (ipi+nivo). Patients with DM during adjuvant anti-PD1 achieved response rates of 58.7% after switching to 1L TT and 35.3% for 1L ipi+nivo. Overall, median PFS was significantly longer in patients who switched treatments for stage IV disease (median PFS 9 vs 5 months, p=0.004). CONCLUSIONS: BRAFmut melanoma patients who developed DM upon upfront adjuvant therapy achieve favorable tumor control and prolonged PFS after switching treatment modalities in the first-line setting of stage IV disease. Patients with locoregional recurrence benefit from complete resection of recurrence followed by a second adjuvant treatment with TT.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Adjuvant Drug Therapy; Immune Checkpoint Inhibitors; Melanoma; Molecular Targeted Therapy; Recurrence

Treatment Motivations and Expectations in Patients with Actinic Keratosis: A German-Wide Multicenter, Cross-Sectional Trial - Steeb, Theresa; Wessely, Anja; Von Bubnoff, Dagmar; Dirschka, Thomas; Drexler, Konstantin; Falkenberg, Conrad; Hassel, Jessica C.; Hayani, Kinan; Huening, Svea; Kaehler, Katharina C.; Karrer, Sigrid; Krammer, Christian; et al. (Journal of Clinical Medicine, 2020)
Patient-centered motives and expectations of the treatment of actinic keratoses (AK) have received little attention until now. Hence, we aimed to profile and cluster treatment motivations and expectations among patients with AK in a nationwide multicenter, cross-sectional study including patients from 14 German skin cancer centers. Patients were asked to complete a self-administered questionnaire. Treatment motives and expectations towards AK management were measured on a visual analogue scale from 1-10. Specific patient profiles were investigated with subgroup and correlation analysis. Overall, 403 patients were included. The highest motivation values were obtained for the items "avoid transition to invasive squamous cell carcinoma" (mean +/- standard deviation; 8.98 +/- 1.46), "AK are considered precancerous lesions" (8.72 +/- 1.34) and "treating physician recommends treatment" (8.10 +/- 2.37; p < 0.0001). The highest expectation values were observed for the items "effective lesion clearance" (8.36 +/- 1.99), "safety" (8.20 +/- 2.03) and "treatment-related costs are covered by health insurance" (8.00 +/- 2.41; p < 0.0001). Patients aged >= 77 years and those with >= 7 lesions were identified at high risk of not undergoing any treatment due to intrinsic and extrinsic motivation deficits. Heat mapping of correlation analysis revealed four clusters with distinct motivation and expectation profiles. This study provides a patient-based heuristic tool for a personalized treatment decision in patients with AK.
CRIS-Team WoS Importer:2020-06-26

Treatment of generalised vitiligo with tacrolimus 0.1% ointment vs. UVB intense pulsed light phototherapy: a pilot study - Hartmann, Arndt; Löhberg, Lisa; Keikavoussi, Petra; Eichner, Saskia; Schuler, Gerold (Acta Dermato-Venereologica, 2014)
EVALuna2:19436

Treatment of moderate-to-severe atopic dermatitis with baricitinib: Results from an interim analysis of the TREATgermany registry - Traidl, Stephan; Heinrich, Luise; Siegels, Doreen; Heratizadeh, Annice; Kind, Barbara; Haufe, Eva; Abraham, Susanne; Schäfer, Thomas; Augustin, Matthias; Harder, Inken; Pinter, Andreas; Schäkel, Knut; et al. (Journal of the European Academy of Dermatology and Venereology, 2024)
CRIS-Team Scopus Importer:2024-04-12

Treatment of vitiligo using targeted UVB-Intense Pulsed Light (IPL)- phototherapy: evaluation of variables affecting therapeutic success - Hartmann, Arndt; Schmidt-Habel, Anne; Löhberg, Lisa; Zajitschek, Jörg; Englbrecht, Matthias; Eichner, Saskia; Schuler, Gerold (European Journal of Dermatology, 2014)
Targeted UVB intense pulsed light (IPL)-phototherapy has gained interest for repigmentation of vitiligo as it allows selective treatment, sparing the surrounding skin. However, optimal treatment frequency and duration are not known.We compared the efficacy and safety of two treatment protocols, weekly and every two weeks, for a maximum of 12 months. Variables affecting treatment response were evaluated.22 patients (16 female, 6 male; aged 15 - 67 years) with generalised vitiligo were evaluated retrospectively. UVB-IPL had been administered weekly (13 patients, group A), or every second week (9 patients, group B). In cases of no response, treatment stopped after 6 months. Regimentation was evaluated qualitatively and quantitatively.After 6 months, 12/13 patients (A), 3/9 patients (B) showed repigmentation. Due to lack of success, treatment was stopped after 6 months in 1 group A patient and 6/9 group B patients. After 12 months, lesions on the face and trunk in group A showed a mean of 70 ± 27% and 60 ± 29% repigmentation, respectively. Moderate to good repigmentation was seen in 78% of group A patients on the ulnar region on the forearms and the shins. Side effects were minimal. Treatment success depended on treatment frequency, number of treatments and the anatomical site of lesions.UVB-IPL phototherapy seems to be effective and well-tolerated in non-segmental vitiligo. A treatment frequency of weekly intervals rather than every two weeks appears preferable. Our observations will help in designing a sufficiently powered prospective clinical trial to test this hypothesis.
EVALuna2:13137

Triggering of NF-κB in cytokine-matured human DCs generates superior DCs for T-cell priming in cancer immunotherapy. - Pfeiffer, Isabell; Hoyer, Stefanie; Gerer, Kerstin; Voll, Reinhard E.; Knippertz, Ilka; Gueckel, Eva; Schuler, Gerold; Schaft, Niels; Dörrie, Jan (European Journal of Immunology, 2014)
Understanding the signaling that governs the immunogenicity of human dendritic cells (DCs) is a prerequisite for improving DC-based therapeutic vaccination strategies, in which the ability of DCs to induce robust and lasting Ag-specific CTL responses is of critical importance. Cytokine-matured DCs are regularly used, but to induce memory-type CTLs, they require additional activation stimuli, such as CD4+ T-cell help or TLR activation. One common denominator of these stimuli is the activation of NF-?B. Here, we show that human monocyte-derived, cytokine cocktail-matured DCs transfected with constitutively active mutants of I?B kinases (caIKKs) by mRNA electroporation, further upregulated maturation markers, and secreted enhanced amounts of cytokines, including IL-12p70, which was produced for more than 48 h after transfection. Most importantly, cytotoxic T cells induced by caIKK-transfected DCs combined high CD27 expression, indicating a more memory-like phenotype, and a markedly enhanced secondary expandability with a high lytic capacity. In contrast, CTLs primed and expanded with unmodified cytokine cocktail-matured DCs did not maintain their proliferative capacity upon repetitive stimulations. We hypothesize that "designer" DCs expressing constitutively active I?B kinases will prove highly immunogenic also in vivo and possibly emerge as a new strategy to improve the clinical efficacy of therapeutic vaccinations against cancer and other chronic diseases.
EVALuna2:19501

Tumor location determines tissue-specific recruitment of tumor-associated macrophages and antibody-dependent immunotherapy response - Lehmann, Birgit; Biburger, Markus; Brückner, Christin; Ipsen Escobedo, Andrea; Gordan, Sina; Lehmann, Christian; Vöhringer, David; Winkler, Thomas; Schaft, Niels; Dudziak, Diana; Sirbu, Horia; Nimmerjahn, Falk; et al. (Science immunology, 2017)
Despite recent advances in activating immune cells to target tumors, the presence of some immune cells, such as tumor-associated macrophages (TAMs) or tumor-associated neutrophils (TANs), may promote rather than inhibit tumor growth. However, it remains unclear how antibody-dependent tumor immunotherapies, such as cytotoxic or checkpoint control antibodies, affect different TAM or TAN populations, which abundantly express activating Fcγ receptors. In this study, we show that the tissue environment determines which cellular effector pathways are responsible for antibody-dependent tumor immunotherapy. Although TAMs derived from Ly6Chigh monocytes recruited by the CCL2-CCR2 axis were critical for tumor immunotherapy of skin tumors, the destruction of lung tumors was CCL2-independent and required the presence of colony-stimulating factor 2–dependent tissue-resident macrophages. Our findings suggest that TAMs may have a dual role not only in promoting tumor growth in certain tissue environments on the one hand but also in contributing to tumor cell destruction during antibody-mediated immunotherapy on the other hand.
EVALuna2:15237
Keywords: Cancer; Macrophages; Tumor associated macrophages; Antibodies; Tumor therapy; Immunotherapy

Tumors as chaotic attractors - Nikolov, Svetoslav; Wolkenhauer, Olaf; Vera González, Julio (Molecular Biosystems, 2014)
Malignant tumor growth, progression and evolution share several of the features associated with strange attractors, a special type of dynamical behavior of non-linear systems. In this framework, the genetic instability of tumor cells represents a local-scale driving force for instability that lets the tumor evolve with time, while selective pressures discarding inefficient cell clones play the role of a dissipative process, providing the tumor with global stability and robustness with respect to perturbations. This setup induces global stability combined with local instability, and is in our opinion the real source of tumor robustness and plasticity, and ultimately the origin of the remarkable resistance of many tumors to anti-cancer therapies. A scientific program taking into consideration the vision of tumors as strange attractors requires the development of experimental and computational tools to link the micro- and mesoscopic perspectives of tumor biology. We here develop the idea of a tumor as a dynamical system, sharing characteristics with strange attractors and investigate several features of such systems, including: (a) local instability combined with global stability, a property inherent to the tremendous non-linearity of the biochemical regulatory circuits governing the individual fate and the interactions between tumor cells; (b) self-similarity at different levels; (c) and strong sensitivity to initial conditions in the composition and features of the tumor and its microenvironment.
EVALuna2:19516

Tumor-suppressing Plasma extracellular Vesicles (pEV) from Melanoma Patients are secreted by Liver Cells and PBMC - Baur, A.; Lee, J. H.; Eberhardt, Martin; Blume, K.; Schuler, Gerold; Vera González, Julio (2018)
EVALuna2:34773

Twelve-year survival and immune correlates in dendritic cell-vaccinated melanoma patients - Gross, Stefanie; Erdmann, Michael; Haendle, Ina; Voland, Steve; Berger, Thomas; Schultz, Erwin; Strasser, Erwin; Dankerl, Peter; Janka, Rolf Matthias; Schliep, Stefan; Heinzerling, Lucie; Sotlar, Karl; et al. (JCI Insight, 2017)
BACKGROUND: Reports on long-term (≥10 years) effects of cancer vaccines are missing. Therefore, in 2002, we initiated a phase I/II trial in cutaneous melanoma patients to further explore the immunogenicity of our DC vaccine and to establish its long-term toxicity and clinical benefit after a planned 10-year followup. METHODS: Monocyte-derived DCs matured by TNFα, IL-1β, IL-6, and PGE2 and then loaded with 4 HLA class I and 6 class II-restricted tumor peptides were injected intradermally in high doses over 2 years. We performed serial immunomonitoring in all 53 evaluable patients. RESULTS: Vaccine-specific immune responses including high-affinity, IFNγ-producing CD4+ and lytic polyfunctional CD8+ T cells were de novo induced or boosted in most patients. Exposure of mature DCs to trimeric soluble CD40 ligand, unexpectedly, did not further enhance such immune responses, while keyhole limpet hemocyanin (KLH) pulsing to provide unspecific CD4+ help promoted CD8+ T cell responses - notably, their longevity. An unexpected 19% of nonresectable metastatic melanoma patients are still alive after 11 years, a survival rate similar to that observed in ipilimumab-treated patients and achieved without any major (>grade 2) toxicity. Survival correlated significantly with the development of intense vaccine injection site reactions, and with blood eosinophilia after the first series of vaccinations, suggesting that prolonged survival was a consequence of DC vaccination. CONCLUSIONS: Long-term survival in advanced melanoma patients undergoing DC vaccination is similar to ipilimumab-treated patients and occurs upon induction of tumor-specific T cells, blood eosinophilia, and strong vaccine injection site reactions occurring after the initial vaccinations. TRIAL REGISTRATION: ClinicalTrials.gov NCT00053391. FUNDING: European Community, Sixth Framework Programme (Cancerimmunotherapy LSHC-CT-2006-518234; DC-THERA LSHB-CT-2004-512074), and German Research Foundation (CRC 643, C1, Z2).
EVALuna2:14632

TYPE 3 INNATE LYMPHOID CELLS ARE KEY DRIVERS OF PSORIATIC ARTHRITIS - Raimondo, M. G.; Rauber, S.; Luber, M.; Rigau, A. Rius; Weber, Stefanie; Anchang, Charles Gwellem; Agarwal, Rahul; Soare, A.; Sticherling, Michael; Rech, Jürgen; Kleyer, Arnd; Distler, Jörg; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2020)
CRIS-Team WoS Importer:2020-08-21

Ulcerative colitis: yet another paradoxical effect of tumour necrosis factor blockers? - Sticherling, Michael (British Journal of Dermatology, 2018)
EVALuna2:34402

Unbiased high-dimensional flow cytometry identified NK and DC immune cell signature in Luminal A-type and triple negative breast cancer - Heger, Lukas; Heidkamp, Gordon Frederik; Amon, Lukas; Nimmerjahn, Falk; Bäuerle, Tobias; Maier, Andreas; Erber, Ramona; Hartmann, Arndt; Hack, Carolin; Rübner, Matthias; Hübner, Hanna; Fasching, Peter; et al. (OncoImmunology, 2024)
Breast cancer is the most common malignancy in women worldwide and a highly heterogeneous disease. Four different subtypes are described that differ in the expression of hormone receptors as well as the growth factor receptor HER2. Treatment modalities and survival rate depend on the subtype of breast cancer. However, it is still not clear which patients benefit from immunotherapeutic approaches such as checkpoint blockade. Thus, we aimed to decipher the immune cell signature of the different breast cancer subtypes based on high-dimensional flow cytometry followed by unbiased approaches. Here, we show that the frequency of NK cells is reduced in Luminal A and B as well as triple negative breast cancer and that the phenotype of residual NK cells is changed toward regulatory CD11b−CD16− NK cells. Further, we found higher frequencies of PD-1+ CD4+ and CD8+ T cells in triple negative breast cancer. Moreover, while Luminal A-type breast cancer was enriched for CD14+ cDC2 (named type 3 DC (DC3)), CD14− cDC2 (named DC2) were more frequent in triple negative breast cancer. In contrast, HER2-enriched breast cancer did not show major alterations in the composition of the immune cell compartment in the tumor microenvironment. These findings suggest that patients with Luminal A- and B-type as well as triple negative breast cancer might benefit from immunotherapeutic approaches targeting NK cells.
CRIS-Team Scopus Importer:2024-01-12
Keywords: Breast cancer; immune cell signature; NK cells; PD-1; tumor microenvironment

Uncommon Presentation of Scleromyxoedema with a Distribution Pattern Mimicking a Photodermatosis - Kirchberger, Michael Constantin; Sticherling, Michael; Erdmann, Michael (Acta Dermato-Venereologica, 2017)
EVALuna2:34345

Understanding microRNA-mediated gene regulatory networks through mathematical modelling - Lai, Xin; Wolkenhauer, Olaf; Vera González, Julio (Nucleic Acids Research, 2016)
The discovery of microRNAs (miRNAs) has added a new player to the regulation of gene expression. With the increasing number of molecular species involved in gene regulatory networks, it is hard to obtain an intuitive understanding of network dynamics. Mathematical modelling can help dissecting the role of miRNAs in gene regulatory networks, and we shall here review the most recent developments that utilise different mathematical modelling approaches to provide quantitative insights into the function of miRNAs in the regulation of gene expression. Key miRNA regulation features that have been elucidated via modelling include: (i) the role of miRNA-mediated feedback and feedforward loops in fine-tuning of gene expression; (ii) the miRNA-target interaction properties determining the effectiveness of miRNA-mediated gene repression; and (iii) the competition for shared miRNAs leading to the cross-regulation of genes. However, there is still lack of mechanistic understanding of many other properties of miRNA regulation like unconventional miRNA-target interactions, miRNA regulation at different sub-cellular locations and functional miRNA variant, which will need future modelling efforts to deal with. This review provides an overview of recent developments and challenges in this field.
Keywords: miRNAs; network biology; systems biology; computational modelling

Understanding microRNA-mediated immunogenicity of dendritic cells using an integrative approach - Lai, Xin; Dreyer, Florian; Jaitly, T.; Cantone, Martina; Gerer, K. F.; Schuler, Gerold; Dörrie, Jan; Schaft, Niels; Vera, Julio (2018)
EVALuna2:34381

Unraveling a tumor type-specific regulatory core underlying E2F1-mediated epithelial-mesenchymal transition to predict receptor protein signatures - Khan, Faiz M.; Marquardt, Stephan; Gupta, Shailendra K.; Knoll, Susanne; Schmitz, Ulf; Spitschak, Alf; Engelmann, David; Vera, Julio; Wolkenhauer, Olaf; Puetzer, Brigitte M. (Nature Communications, 2017)
Cancer is a disease of subverted regulatory pathways. In this paper, we reconstruct the regulatory network around E2F, a family of transcription factors whose deregulation has been associated to cancer progression, chemoresistance, invasiveness, and metastasis. We integrate gene expression profiles of cancer cell lines from two E2F1-driven highly aggressive bladder and breast tumors, and use network analysis methods to identify the tumor type-specific core of the network. By combining logic-based network modeling, in vitro experimentation, and gene expression profiles from patient cohorts displaying tumor aggressiveness, we identify and experimentally validate distinctive, tumor type-specific signatures of receptor proteins associated to epithelial-mesenchymal transition in bladder and breast cancer. Our integrative network-based methodology, exemplified in the case of E2F1-induced aggressive tumors, has the potential to support the design of cohort- as well as tumor type-specific treatments and ultimately, to fight metastasis and therapy resistance.Deregulation of E2F family transcription factors is associated with cancer progression and metastasis. Here, the authors construct a map of the regulatory network around the E2F family, and using gene expression profiles, identify tumour type-specific regulatory cores and receptor expression signatures associated with epithelial-mesenchymal transition in bladder and breast cancer.
EVALuna2:35407

Updated results of 100 patients on clinical features and therapeutic options in necrobiosis lipoidica in a retrospective multicentre study - Dissemond, Joachim; Schwede, Katharina; Seitz, Anna-Theresa; Al Ghazal, Philipp; Wollina, Uwe; Renner, Regina; Erfurt-Berge, Cornelia (European Journal of Dermatology, 2015)
Necrobiosis lipoidica (NL) is a rare granulomatous disorder of unknown aetiology which can manifest in ulcerative skin lesions and is widely recognised in association with diabetes. We evaluated in total 100 patients to improve knowledge about the epidemiology and clinical course of NL. Additionally we focused on treatment options according to evidence level and expert opinion.To examine the clinical features of patients with necrobiosis lipoidica and to give recommendations for topical and systemic treatment.This multicentre retrospective study covers data from 100 patients with the diagnosis of NL of the lower leg, treated during the period between 01/2006 and 06/2014. Data from 5 German dermatological centres with 23 men and 77 women with a median age of 52 years were evaluated. We also asked 15 dermatological experts for their opinions about ulceration, associated diseases and their preferences for treatment modalities of NL.Patients' ages ranged from 15 to 95 years (median age 52 years, mean age 49.8 years). NL was significantly more common in women (77%). Ulceration of the NL was observed in 33% of cases, in particular in male patients and in patients with concomitant diabetes mellitus. Thyroidal disorders were found in 15% of all cases.Our data confirm that female sex, middle age and endocrine disorders like diabetes mellitus or thyroid dysfunction are characteristics of patients suffering from NL. Existing therapeutic options were very variable and - according to the opinion of our experts - only a few highly effective.
EVALuna2:19576

Update on the management of Bowen disease with a focus on patients' needs. - Berking, Carola (British Journal of Dermatology, 2023)
EVALuna2:517117

Usage and effectiveness of systemic treatments in adults with severe atopic eczema: First results of the German Atopic Eczema Registry TREATgermany - Schmitt, Jochen; Abraham, Susanne; Trautmann, Freya; Stephan, Victoria; Foelster-Holst, Regina; Homey, Bernhard; Bieber, Thomas; Novak, Natalija; Sticherling, Michael; Augustin, Matthias; Kleinheinz, Andreas; Elsner, Peter; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2017)
BACKGROUND: The goal of clinical registries is to document the use and effectiveness of therapeutic interventions under real-life conditions. They are an indispensable prerequisite of evidence-based health care. METHODS: Initiated in 2011, the German Atopic Dermatitis Registry TREATgermany is the first registry of patients with severe atopic dermatitis worldwide. Adults with severe atopic dermatitis (current/prior systemic antiinflammatory treatment and/or objective SCORAD ≥ 40) are prospectively followed over the course of 24 months. Employed treatment modalities are documented, and validated measuring tools are used to assess clinical disease severity (EASI, objective SCORAD), quality of life (DLQI), symptoms (POEM), global disease severity, as well as patient satisfaction. Herein, we describe the characteristics, therapeutic selection, and effectiveness of systemic antiinflammatory treatments of patients enrolled in the registry until October 2014. RESULTS: Overall, 78 individuals (mean age 39 years, 61 % men) were enrolled at five recruitment centers. Patients frequently made use of inpatient and outpatient services. Not only was cyclosporine the most frequently administered systemic treatment, but also the most effective (EASI 50 response rate 51 %; EASI 75 response rate 34 % at 12 weeks). Azathioprine, methotrexate, oral prednisolone, mycophenolate, alitretinoin, and leflunomide were also used in some patients. CONCLUSIONS: The present analysis of the German Atopic Dermatitis Registry provides important data with respect to current medical care of adults with severe atopic dermatitis in Germany. It shows the high disease burden, the benefits of current treatment options, and the need for additional effective and safe long-term treatment options.
EVALuna2:34363

Using multiple real-world dermoscopic photographs of one lesion improves melanoma classification via deep learning - Hekler, Achim; Maron, Roman C.; Haggenmüller, Sarah; Schmitt, Max; Wies, Christoph; Utikal, Jochen S.; Meier, Friedegund; Hobelsberger, Sarah; Gellrich, Frank F.; Sergon, Mildred; Hauschild, Axel; French, Lars E.; et al. (Journal of the American Academy of Dermatology, 2024)
CRIS-Team Scopus Importer:2024-02-16
Keywords: artificial intelligence; deep learning; dermatology; dermoscopy; diagnosis; diagnostic accuracy; melanoma; robustness; uncertainty estimation

Using the Prediction Model Risk of Bias Assessment Tool (PROBAST) to Evaluate Melanoma Prediction Studies - Kaiser, Isabelle; Mathes, Sonja; Pfahlberg, Annette Bettina; Uter, Wolfgang; Berking, Carola; Heppt, Markus; Steeb, Theresa; Diehl, Katharina; Gefeller, Olaf (Cancers, 2022)
Rising incidences of cutaneous melanoma have fueled the development of statistical models that predict individual melanoma risk. Our aim was to assess the validity of published prediction models for incident cutaneous melanoma using a standardized procedure based on PROBAST (Prediction model Risk Of Bias ASsessment Tool). We included studies that were identified by a recent systematic review and updated the literature search to ensure that our PROBAST rating included all relevant studies. Six reviewers assessed the risk of bias (ROB) for each study using the published “PROBAST Assessment Form” that consists of four domains and an overall ROB rating. We further examined a temporal effect regarding changes in overall and domain-specific ROB rating distributions. Altogether, 42 studies were assessed, of which the vast majority (n = 34; 81%) was rated as having high ROB. Only one study was judged as having low ROB. The main reasons for high ROB ratings were the use of hospital controls in case-control studies and the omission of any validation of prediction models. However, our temporal analysis results showed a significant reduction in the number of studies with high ROB for the domain “analysis”. Nevertheless, the evidence base of high-quality studies that can be used to draw conclusions on the prediction of incident cutaneous melanoma is currently much weaker than the high number of studies on this topic would suggest.
CRIS-Team Scopus Importer:2022-07-22
Keywords: melanoma; prediction models; PROBAST; risk of bias; risk prediction

Vaccination with dendritic Cells for metastasized Uveal Melanoma: immunological and clinical Responses - Moreira, Alvaro; Gross, S.; Uslu, Ugur; Dörrie, Jan; Kummer, Mirko; Schliep, S.; Sponagl, F.; Lischer, Christopher; Erdmann, M.; Heinzerling, Lucie; Schuler, Gerold; Schuler-Thurner, Beatrice (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-09-13

Vasoactive Therapy in Systemic Sclerosis: Real-life Therapeutic Practice in More Than 3000 Patients - Moinzadeh, Pia; Riemekasten, Gabriela; Siegert, Elise; Fierlbeck, Gerhard; Henes, Joerg; Blank, Norbert; Melchers, Inga; Mueller-Ladner, Ulf; Frerix, Marc; Kreuter, Alexander; Tigges, Christian; Lahner, Nina; et al. (Journal of Rheumatology, 2016)
Vasculopathy is a key factor in the pathophysiology of systemic sclerosis (SSc) and the main cause for Raynaud phenomenon (RP), digital ulcers (DU), and/or pulmonary arterial hypertension (PAH). It is so far unknown how patients with SSc are treated with vasoactive agents in daily practice. To determine to which extent patients with SSc were treated with different vasoactive agents, we used data from the German Network for Systemic Scleroderma registry.The data of 3248 patients with SSc were analyzed.Patients were treated with vasoactive drugs in 61.1% of cases (1984/3248). Of these, 47.6% received calcium channel inhibitors, followed by 34.2% treated with angiotensin-converting enzyme (ACE) inhibitors, 21.1% treated with intravenous (IV) prostanoids, 10.1% with pentoxifylline, 8.8% with angiotensin 1 receptor antagonists (AT1RA), 8.7% with endothelin 1 receptor antagonists (ET1RA), 4.1% with phosphodiesterase type 5 (PDE5) inhibitors, and 5.3% with others. Patients with RP received vasoactive therapy in 63.3% of cases, with DU in 70.1%, and with PAH in 78.2% of cases. Logistic regression analysis revealed that patients with PAH were significantly more often treated with PDE5 inhibitors and ET1RA, and those with DU with ET1RA and IV prostanoids. In addition, 41.8% of patients were treated with ACE inhibitors and/or AT1RA. Patients registered after 2009 received significantly more often ET1RA, AT1RA, and IV prostanoids compared with patients registered prior to 2005.These data clearly indicate that many patients with SSc do not yet receive sufficient vasoactive therapy. Further, in recent years, a marked change of treatment regimens can be observed.
EVALuna2:13183

VEXAS syndrome mimicking lupus-like disease - Valor-Mendez, Larissa; Sticherling, Michael; Zeschick, Martin; Atreya, Raja; Schmidt, Daniela; Waldfahrer, Frank; Saake, Marc; Hüffmeier, Ulrike; Schett, Georg; Rech, Jürgen (Rheumatology, 2023)
CRIS-Team WoS Importer:2023-03-17

Wahrnehmung der Corona-Pandemie durch Neurodermitispatienten – Ergebnisse aus dem Neurodermitisregister TREATgermany - Helmert, Claudia; Siegels, Doreen; Haufe, Eva; Abraham, Susanne; Heratizadeh, Annice; Kleinheinz, Andreas; Harder, Inken; Schäkel, Knut; Effendy, Isaak; Wollenberg, Andreas; Sticherling, Michael; Stahl, Maren; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2022)
CRIS-Team Scopus Importer:2022-02-04

What Goes Around, Comes Around - HSV-1 Replication in Monocyte-Derived Dendritic Cells - Grosche, Linda; Kummer, Mirko; Steinkasserer, Alexander (Frontiers in Microbiology, 2017)
HSV-1 is a very successful human pathogen, known for its high sero-prevalence and the ability to infect a wide range of different cell types, including dendritic cells (DCs). As very potent antigen-presenting cells DCs play an important role in the induction of antiviral immune responses and therefore represent a strategic target for viral-mediated immune escape mechanisms. It is known that HSV-1 completes its gene expression profile in immature as well as in mature DCs, while lytic infection is only found in immature DCs (iDCs). Notably, HSV-1 infected mature DCs (mDCs) fail to release infectious progeny virions into the supernatant. Apart from HSV-1 dissemination via extracellular routes cell-to-cell spread counteracts a yet unknown mechanism by which the virus is trapped in mDCs and not released into the supernatant. The dissemination in a cell-cell contact-dependent manner enables HSV-1 to infect bystander cells without the exposure toward the extracellular environment. This supports the virus to successfully infect the host and establish latency. In this review the mechanism of HSV-1 replication in iDCs and mDCs and its immunological as well as virological implications, will be discussed.
EVALuna2:36216

What is the current State of Knowledge of Skin Cancer Patients about fertility-preserving Measures? an exploratory Cross Sectional Survey - Hornung-Eichler, Annkathrin; Steeb, Theresa; Erdmann, M.; Berking, Carola; Heppt, Markus (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2021)
CRIS-Team WoS Importer:2021-09-24

Where do we stand with immune checkpoint blockade for advanced cutaneous squamous cell carcinoma? A systematic review and critical appraisal of existing evidence - Steeb, Theresa; Wessely, A.; Heppt, Franz; Harlaß, M.; Berking, Carola; Heppt, Markus (British Journal of Dermatology, 2020)
Immune checkpoint blockade (ICB) has tremendously changed the field of oncological therapy. Recently, the PD-1-blocking antibody cemiplimab was approved by the FDA and the EMA for the treatment of advanced cutaneous squamous cell carcinoma (cSCC).1 However, clinical practice guidelines currently do not cover specific recommendations regarding the management of advanced cSCC with ICB. Hence, we have performed a systematic review on the current use of ICB for advanced cSCC.
EVALuna2:212852

Which patients should receive adjuvant treatment - an analysis of stage IIA-IIIA patients of the CMMR - Leiter-Stoppke, U.; Keim, U.; Amaral, T.; Forschner, A.; Berking, Carola; Gesierich, A.; Gutzmer, R.; Sunderkotter, C.; Utikal, J. S.; Zimmer, L.; Flatz, L.; Garbe, C. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2022)
CRIS-Team WoS Importer:2022-09-23

Whither systems medicine? - Apweiler, Rolf; Beissbarth, Tim; Berthold, Michael R.; Bluethgen, Nils; Burmeister, Yvonne; Dammann, Olaf; Deutsch, Andreas; Feuerhake, Friedrich; Franke, Andre; Hasenauer, Jan; Hoffmann, Steve; Hoefer, Thomas; et al. (Experimental and Molecular Medicine, 2018)
New technologies to generate, store and retrieve medical and research data are inducing a rapid change in clinical and translational research and health care. Systems medicine is the interdisciplinary approach wherein physicians and clinical investigators team up with experts from biology, biostatistics, informatics, mathematics and computational modeling to develop methods to use new and stored data to the benefit of the patient. We here provide a critical assessment of the opportunities and challenges arising out of systems approaches in medicine and from this provide a definition of what systems medicine entails. Based on our analysis of current developments in medicine and healthcare and associated research needs, we emphasize the role of systems medicine as a multilevel and multidisciplinary methodological framework for informed data acquisition and interdisciplinary data analysis to extract previously inaccessible knowledge for the benefit of patients.
EVALuna2:34798

XCR1 expression distinguishes human conventional dendritic cell type 1 with full effector functions from their immediate precursors - Heger, Lukas; Hatscher, Lukas; Liang, Chunguang; Lehmann, Christian; Amon, Lukas; Lühr, Jennifer J.; Kaszubowski, Tomasz; Nzirorera, Rayk; Schaft, Niels; Dörrie, Jan; Irrgang, Pascal; Tenbusch, Matthias; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2023)
Dendritic cells (DCs) are major regulators of innate and adaptive immune responses. DCs can be classified into plasmacytoid DCs and conventional DCs (cDCs) type 1 and 2. Murine and human cDC1 share the mRNA expression of XCR1. Murine studies indicated a specific role of the XCR1-XCL1 axis in the induction of immune responses. Here, we describe that human cDC1 can be distinguished into XCR1- and XCR1+ cDC1 in lymphoid as well as nonlymphoid tissues. Steady-state XCR1+ cDC1 display a preactivated phenotype compared to XCR1- cDC1. Upon stimulation, XCR1+ cDC1, but not XCR1- cDC1, secreted high levels of inflammatory cytokines as well as chemokines. This was associated with enhanced activation of NK cells mediated by XCR1+ cDC1. Moreover, XCR1+ cDC1 excelled in inhibiting replication of Influenza A virus. Further, under DC differentiation conditions, XCR1- cDC1 developed into XCR1+ cDC1. After acquisition of XCR1 expression, XCR1- cDC1 secreted comparable level of inflammatory cytokines. Thus, XCR1 is a marker of terminally differentiated cDC1 that licenses the antiviral effector functions of human cDC1, while XCR1- cDC1 seem to represent a late immediate precursor of cDC1.
CRIS-Team Scopus Importer:2023-08-25
Keywords: antiviral immunity; cDC1; DC differentiation; IL-12; XCR1

YouTube (R)-Videos about Skin Cancer as an Information Source for Patients: Assessment of quality, Comprehensibility and Reliability - Reinhardt, L.; Steeb, Theresa; Harlass, M.; Brutting, J.; Berking, Carola; Meier, F. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2021)
CRIS-Team WoS Importer:2021-09-24

β2-microglobulin triggers NLRP3 inflammasome activation in tumor-associated macrophages to promote multiple myeloma progression - Hofbauer, Daniel; Mougiakakos, Dimitrios; Broggini, Luca; Zaiss, Mario; Büttner-Herold, Maike; Bach, Christian; Spriewald, Bernd; Neumann, Frank; Bisht, Savita; Nolting, Jens; Zeiser, Robert; Hamarsheh, Shaima'a; et al. (Immunity, 2021)
As substantial constituents of the multiple myeloma (MM) microenvironment, pro-inflammatory macrophages have emerged as key promoters of disease progression, bone destruction, and immune impairment. We identify beta-2-microglobulin (β2m) as a driver in initiating inflammation in myeloma-associated macrophages (MAMs). Lysosomal accumulation of phagocytosed β2m promotes β2m amyloid aggregation in MAMs, resulting in lysosomal rupture and ultimately production of active interleukin-1β (IL-1β) and IL-18. This process depends on activation of the NLRP3 inflammasome after β2m accumulation, as macrophages from NLRP3-deficient mice lack efficient β2m-induced IL-1β production. Moreover, depletion or silencing of β2m in MM cells abrogates inflammasome activation in a murine MM model. Finally, we demonstrate that disruption of NLRP3 or IL-18 diminishes tumor growth and osteolytic bone destruction normally promoted by β2m-induced inflammasome signaling. Our results provide mechanistic evidence for β2m's role as an NLRP3 inflammasome activator during MM pathogenesis. Moreover, inhibition of NLRP3 represents a potential therapeutic approach in MM.
CRIS-Team Scopus Importer:2021-08-13
Keywords: inflammation; macrophages; multiple myeloma; NLRP3; phagocytosis; tumor-associated macrophages

Clinical characteristics and outcomes of coronavirus 2019 disease (COVID-19) in cancer patients treated with immune checkpoint inhibitors (ICI). - Rogiers, Aljosja; Tondini, Carlo; Grimes, Joe M.; Trager, Megan H.; Nahm, Sharon; Zubiri, Leyre; Papneja, Neha; Elkrief, Arielle; Borgers, Jessica; Rose, April; Mangana, Johanna; Erdmann, Michael; et al. (CLINICAL CANCER RESEARCH, 2020)
CRIS-Team WoS Importer:2020-10-16

Dyspnoea under Immunotherapy for Patients with Melanoma: Pneumonia, Pulmonary Embolism, Pneumonitis or Myocarditis? - Koeceroglu, I.; Bosch-Voskens, C.; Erdmann, M. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-05-17

Psychiatric disorders are common comorbidities in patients with chronic spontaneous or inducible urticaria in Germany - Weller, K.; Maurer, M.; Bauer, A.; Wedi, B.; Wagner, N.; Schliemann, S.; Baeumer, D.; Boehm, K.; Staubach, P. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-05-17